Diamond Burr for the Treatment of an Indolent Corneal Ulcer in a Foal - Pigatto, JAT; de Albuquerque, L; Bacchin, ABD; da Silva, GMR; Petersen, MB; Reiter, GG (ACTA SCIENTIAE VETERINARIAE, 2017)
Background: Indolent corneal ulcers have been described as superficial ulcers with an associated rim of loose peripheral epithelium Treatment for indolent ulcers include debridement, grid keratotomy, multiple punctate keratotomy, third eyelid flaps, application of cyanoacrylate tissue adhesives, superficial keratectomy, and a debridement with a diamond burr. Case: A 2-month-old female American Quarter Horse was referred to the Ophthalmology Veterinary Section of the Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, Brazil, presenting epiphora and blepharospasm. A local veterinarian doctor had prescribed broad spectrum topical antibiotic and anti-inflammatory drops, although there was no positive response to the treatment for the past two weeks. Ophthalmic examination reveals and moderate discomfort in the left eye, epiphora, and mild corneal edema in the area of the defect. Slit lamp biomicroscopy revealed a superficial corneal ulcer with about 6 mm. Corneal epithelium did not adhere to underlying corneal stroma. The remainder of the ophthalmic examination of the left eye was unremarkable. The diagnosis of a corneal ulcer was made based on these clinical signs and fluorescein staining of the cornea where the stain dissects under the unattached epithelial lip. A handheld battery-operated motorized diamond burr, with a 3.5 mm medium grit tip, was utilized to remove the epithelium. The medical treatment included tobramycin eye drops, and flurbiprofen sodium ophthalmic solution, being applied six times daily, after the procedure, during two weeks, and atropine sulphate 1% was applied once a day, during three days. The foal was hospitalized until healing the corneal ulcer. For two weeks, the foal was assessed daily, and, after that, follow-up visits were scheduled weekly for four months. Healing was defined as the point at which the cornea no longer retained fluorescein. Discussion: Ulcers localized to the corneal epithelium, do not heal within the expected time frame, and have been characterized by epithelial border poorly adherent corneal and being commonly referred as indolent corneal ulcers. In this case, corneal ulcers are chronic and have not responded to an appropriate therapy for 14 days. The corneal ulcer was diagnosed based on history, clinical signs and fluorescein staining of the cornea. Usually, medical treatments provide disappointing results. Surgical treatment aims to remove the loosened epithelium in order to facilitate the growth of new epithelial cells, with stronger adhesion complexes. The utilization of a diamond burr, for the treatment of an indolent corneal ulcer, has been previously reported in humans, and dogs. In the present case, the debridement with a diamond burr was chosen on account of excellent results obtained in previous studies in humans and dogs, when treating indolent corneal ulcers. In the current case, the corneal ulcer healed in ten days, while in a study comparing the outcome in 23 horses treated by debridement, grid keratotomy, or superficial keratectomy, the mean times until complete healing were 15, 16 and 23 days, respectively. In the present case, debridement with diamond burr was effective in the treatment of a recurrent corneal ulcer in a foal.

DISEASE AND RISKS ASSOCIATED WITH CONTACT-LENSES - DART, JKG (BRITISH JOURNAL OF OPHTHALMOLOGY, 1993)

Comparison of topical fixed-combination fortified vancomycin-amikacin (VA solution) to conventional separate therapy in the treatment of bacterial corneal ulcer - Chiang, CC; Lin, JM; Chen, WL; Chiu, YT; Tsai, YY (EYE, 2009)
Purpose In an in vitro study, fixed-combination fortified vancomycin and amikacin ophthalmic solutions (VA solution) had the same potency and stable physical properties as the separate components. In this retrospective clinical study, we evaluated the efficacy of the topical VA solution in the treatment of bacterial corneal ulcer and comparison with separate topical fortified vancomycin and amikacin. Methods Separate topical fortified eye drops was used prior to January 2004 and switched to the VA solution afterwards in the treatment of bacterial corneal ulcer. The medical records of 223 patients diagnosed with bacterial corneal ulcers between January 2002 and December 2005 were reviewed retrospectively. There were 122 patients in the VA group and 101 in the separate group. Cure was defined as complete healing of the ulcer accompanied by a nonprogressive stromal infiltrate on two consecutive visits. Results No significant difference was found between the VA and separate therapy group. The mean treatment duration was 15.4 days in the VA group and 16.1 days in the separate therapy group. The average hospital stay was 5.4 days (VA) and 7.2 days (separate antibiotics). Stromal infiltration regressed significantly without further expansion in both groups. All corneal ulcers completely re-epithelialized without complications related to drugs. Conclusion VA solution provided similar efficacy to the conventional separate therapy in the treatment of bacterial corneal ulcers; however, it is more convenient and tolerable, promotes patient's compliance, avoids the washout effect, and reduces nurse utilization. Hence, VA solution is a good alternative to separate therapy.

Novel drug delivery methods for the treatment of keratitis: moving away from surgical intervention - Garg, P; Venuganti, VVK; Roy, A; Roy, G (EXPERT OPINION ON DRUG DELIVERY, 2019)
Introduction: Corneal ulceration is one of the leading causes of blindness especially in low- and midincome countries (LMICs). Surgical treatment of microbial keratitis is associated with multiple challenges that include non-availability of donor corneal tissues, lack of trained corneal surgeons, and poor compliance to follow up care. As a result, the surgery fails in 70-90% cases. Therefore, improving outcome of medical treatment and thereby avoiding the need for the surgery is an unmet need in the care of corneal ulcer cases. Areas covered: In this review article, the authors have tried to compile information on the novel drugdelivery systems that have potential to enhance success of medical management. We have discussed the following systems: cyclodextrins, gel formulations, colloidal system, nanoformulations, drug-eluting contact lens, microneedle patch, and ocular inserts. Expert opinion: The goals of corneal ulcer treatment are as follows: rapid eradication of causative microorganisms, control of damage from induced inflammation and microbial toxins, and facilitation of repair. The ocular surface anatomy poses several challenges for drug delivery using standard topical therapy. The novel drug-delivery systems mentioned above aim to enhanced tear solubility; superior stability; improved bio-availability; reduced toxicity; besides facilitating targeted drug delivery and convenience of administration.

Blueberry Eye: Acquired Total Anterior Staphyloma After a Fungal Corneal Ulcer - Grieser, EJ; Tuli, SS; Chabi, A; Schultz, S; Downer, D (CORNEA, 2009)
Purposes: The purposes of this study were to report the presentation and management of an acquired total anterior staphyloma that resulted from a fungal corneal ulcer and to discuss its pathogenesis. Methods: Observational case report. Clinical observation and surgical intervention of a patient who developed a total anterior staphyloma after a partially treated fungal corneal ulcer. Results: The patient presented with a large traumatic fungal ulcer but was poorly compliant with follow-up and medications. He Subsequently presented with a large total anterior staphyloma that resulted from perforation of the ulcer with plugging of the defect with iris and formation of a pseudocornea over the iris. The anterior staphyloma measured 15 X 16 mm and progressed to a stage where the patient was unable to close his eyelids and required a sclerokeratoplasm Currently, vision is poor from amblyopia and a Cloudy graft; however, the eye is intact and comfortable. Conclusions: Anterior staphylomas usually result from untreated Fungal ulcers in developing nations. Poor compliance with medications and follow-up was the cause of our patient's anterior staphyloma. Sclerokeratoplasty can restore the globe Structurally but has poor visual prognosis.

Acquired anterior staphyloma after corneal ulcer associated with the use of crack - de Vasconcelos, SBD; Guerra, FM; Morato, GM; das Neves, NT; Tzelikis, PF (ARQUIVOS BRASILEIROS DE OFTALMOLOGIA, 2016)
We describe an unusual case of acquired anterior staphyloma in a patient addicted to crack cocaine. At the beginning of his crack cocaine abuse, he noticed redness and irritation of his eyes. Over the next 4 months, the patient also noticed the onset of decreasing visual acuity in his right eye (OD). Initially, his visual acuity was light perception in OD, and slit-lamp examination revealed a corneal infiltrate with a peripheral perforation and an iris prolapse. The patient was hospitalized to ensure compliance with the prescribed treatment and was advised to undergo therapeutic keratoplasty; however, the patient left the hospital against medical advice and was lost to follow-up for the next 6 months. He returned with complaints of photophobia and the inability to close his right eyelids. At this time, his cornea had developed an anterior staphyloma and required a sclerokeratoplasty. Following surgery, the patient was again lost to follow-up.

Adherence to Topical Glaucoma Medications in Ethiopian Patients - Tamrat, L; Gessesse, GW; Gelaw, Y (MIDDLE EAST AFRICAN JOURNAL OF OPHTHALMOLOGY, 2015)
Purpose: Successful outcomes of medical treatment for glaucoma require proper and daily use of medication to prevent disease progression. The aim of this study was to determine the adherence to anti-glaucoma medications and factors associated with non-adherence among patients with ocular hypertension (OHT) or glaucoma at Jimma University Specialized Hospital, Ethiopia. Materials and Methods: A hospital based cross sectional study was conducted on 200 consecutive patients from July to November 2010 at Jimma University Hospital in Southwest Ethiopia. Patients with OHT or glaucoma who were taking topical anti-glaucoma medications for more than six months were included. The study subjects were interviewed and their medical records were reviewed. Non-adherence to glaucoma therapy (NAGT) was defined as self-reported on missed medications or missed appointments, or a physician noting poor adherence. A P < 0.05 was statistically significant. Result: Overall, 135 (67.5%) patients were non adherent to glaucoma therapy. Non adherence was associated with older age (P = 0.04), advanced stage of glaucoma (P = 0.01), longer frequency of follow up (P = 0.00) and financial problem (P = 0.000). Sex (P = 0.53), level of education (P = 0.09), and marital status (P = 0.77) were not statistically significantly associated with non-adherence to anti-glaucoma drug treatment. Conclusion: A relatively high proportion of patients were not adhering to the medications regimen for glaucoma. Older age, advanced glaucoma, lengthier frequency of follow-up and financial hardship were associated with non-adherence. Eye care providers should be aware of the problem of non-adherence to topical medications.

Loss to follow-up amongst glaucoma patients in selected hospitals of the Limpopo Province, South Africa - Tshivhase, SE; Khoza, LB; Tshitangano, TG (AFRICAN VISION AND EYE HEALTH JOURNAL, 2021)
Background: Glaucoma is associated with visual field loss for which elevated intraocular pressure is the primary risk factor. Proper medication adherence requires daily intake of prescribed medication for a lifetime. Non-adherence patients are at greater risk of poor outcome than adherent patients. Aim: To identify behavioural determinants contributing to loss to follow-up amongst glaucoma patients. Setting: The study was conducted in selected hospitals of South Africa. Methods: A hospital-based cross-sectional study was conducted on glaucoma patients with age ranging from 18 years and above. Quantitative methods were used to collect data from purposefully selected glaucoma patients. Structured questionnaires were distributed to collect data from patients attending glaucoma clinics. The patients should have missed an appointment review at least once during the 12-month period. Results: Amongst the 429 glaucoma patients interviewed, the majority (79%, n = 341) of the patients missed their follow-up more than once during the 12-month period. The most cited contributory barriers to poor follow-up were accessibility (26%) followed by lack of escort and financial cost at 22% and 21%, respectively. About 115 of the 429 study respondents were found to be non-adherent. The main reasons given were shortage of medication and forgetfulness at 36% and 29%, respectively. Conclusion: Accessibility and lack of escort were significant barriers to loss to follow-up. Identifying the predictors of poor follow-up can help in improving follow-up care. Therefore, patient education and support may improve adherence to glaucoma therapy.

Factors contributing to nonadherence to follow-up appointments in a resident glaucoma clinic versus primary eye care clinic - Fudemberg, SJ; Lee, B; Waisbourd, M; Murphy, RA; Dai, Y; Leiby, BE; Hark, LA (PATIENT PREFERENCE AND ADHERENCE, 2016)
Purpose: To determine the rate of adherence to follow-up appointment recommendations in a resident glaucoma clinic with no mechanism for reminders, compared to a resident cataract and primary eye care (CPEC) clinic in which telephone reminders were used, and to identify factors that contribute to adherence in each patient group. Methods: This retrospective cohort study included subjects in the CPEC clinic who received telephone reminders and those in the glaucoma clinic who did not. Each sample was selected to have a similar proportion of follow-up recommendations for 1, 3, and 6 months. Subjects were considered adherent if they returned within a specified timeframe. Results: A total of 144 subjects from the glaucoma clinic and 151 subjects from the CPEC clinic were included. There was no significant difference between follow-up adherence rates of patients who received telephone reminders and those who did not (odds ratio [OR] = 1.35, 95% confidence interval [CI] 0.79-2.32, P=0.28). Patients who were on more than two ocular medications were more likely to return for follow-up (OR=3.11, 95% CI 1.53-6.35, P=0.0018). Subjects between the ages 50 and 80 years were more likely to be adherent compared to their younger and older peers (P=0.02). Conclusion: The follow-up adherence of patients in a CPEC clinic who received telephone reminders was similar to patients in a glaucoma clinic who did not receive any intervention to increase their adherence. Younger (<50 years old) and elderly (>80 years old) subjects, as well as patients using less than two glaucoma medications, were less likely to adhere to their follow-up appointments.

Impact of COVID-19 on follow-up and medication adherence in patients with glaucoma in a tertiary eye care centre in south India - Subathra, G; Rajendrababu, SR; Senthilkumar, VA; Mani, I; Udayakumar, B (INDIAN JOURNAL OF OPHTHALMOLOGY, 2021)
Purpose: COVID-19 pandemic has affected the healthcare system worldwide hindering the continuum of treatment of chronic disease patients. The objective of the study is to analyze the barriers encountered by the glaucoma patients for the follow-up visit and medication adherence during the pandemic. Methods: This cross-sectional study included glaucoma patients who did not attend the scheduled appointment from April 1, 2020 to July 31, 2020 in a tertiary eye care center (88.21%). Eligible patients of age >18 years and advised antiglaucoma medication in Madurai Zone were interviewed with validated questionnaire through telephonic call. Results: 363 patients answered the questionnaire through telephonic interview. 57.3% of the patients were found to be non-adherent to medication. The main barriers for glaucoma follow-up visit during the pandemic were lockdown restriction, transport problem, and financial difficulties. The top barriers for medication adherence were non availability of medication (54.81%), financial difficulties (30.29%), did not feel much improvement with eye drops (20.19%). On multiple regression analysis, longer distance to hospital, low socioeconomic status, more than one antiglaucoma medication use, lack of awareness of glaucoma, non-complaint before COVID-19 and stress due to the pandemic were found to be significant factors for medication non adherence. Conclusion: COVID-19 pandemic has emphasized the need for reformation in health care system for accessibility of medical care to patients in rural areas. Decentralization of health system to primary care level and utilization of teleophthalmology should be considered by health care planners in future.

Understanding Barriers to Glaucoma Treatment Adherence among Participants in South India - Killeen, OJ; Pillai, MR; Udayakumar, B; Shroff, S; Vimalanathan, M; Cho, J; Newman-Casey, PA (OPHTHALMIC EPIDEMIOLOGY, 2020)
Purpose: Data on glaucoma treatment barriers in South India is limited; improved knowledge of barriers could advance disease self-management. We aimed to understand glaucoma treatment barriers in South India. Methods: Glaucoma patients >= 18 taking >= 1 medication at the Aravind Eye Hospital were screened with a validated medication adherence tool. Patients who self-reported poor adherence and/or were >3 months late for follow-up completed semi-structured interviews on treatment barriers. Interviews were audio-recorded, transcribed, translated and back-translated to ensure accuracy. Researchers used grounded theory to code the transcripts and identify themes using NVivo 11.0. Demographic and clinical characteristics were abstracted from the medical record. Results: 70/167 (42%) had poor self-reported adherence to drops. The 45 interviewed were 62 +/- 12 years and took 1.6 +/- 0.7 drops. Forty-two (93%) were non-adherent to medication and 21 (47%) were late for follow-up. Top barriers to medication adherence were difficulty obtaining drops (20, 44%), being busy (18, 40%), and the expense (17, 38%). Top barriers to appointment follow-up were distance to the hospital (21, 47%), expense (20, 44%), and no escort (15, 33%). Other important barriers included mistrust in the health system, poor knowledge of glaucoma and family needs. Conclusions: Previously, 6% of glaucoma patients in South India self-reported poor medication adherence; the 42% identified in this study is in line with glaucoma medication adherence rates globally. Complex factors caused high rates of non-adherence. Societal-level interventions that address systemic barriers and counselling that supports patients' and families' motivation for behaviour change should be implemented.

Follow-up Adherence and Barriers to Care for Pediatric Glaucomas at a Tertiary Care Center - Mikolajczyk, B; Greenberg, ER; Fuher, H; Berres, M; May, LL; Areaux, RG (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2021)
PURPOSE: To determine the percent adherence to follow-up for patients with pediatric glaucomas seen at a tertiary care center and to elucidate risk factors. DESIGN: Retrospective cohort study. METHODS: Patients with pediatric glaucomas seen at the University of Minnesota over 8.5 years were classified as adherent, nonadherent, or lost to tertiary follow-up if they followed up within 0-30 days, between 31 and 180 days, or later than 180 days of the recommended appointment time or never, respectively. RESULTS: Of 176 patients analyzed, 95 (54%) were adherent (51% male; mean [standard deviation (SD)] age: 56.1 [59.8] months), 5 (3%) were nonadherent (20% male; mean [SD] age: 25.0 [35.8] months), and 76 (43%) were lost to tertiary follow-up (55% male; mean [SD] age: 58.9 [53.1] months). Multiple logistic regression analysis of variables that were significant in isolation revealed that only race (white: odds ratio, 3.58; 95% confidence interval, 1.42-9.05; P = .007) and distance from the eye clinic (per 50 miles: odds ratio, 0.79; 95% confidence interval, 0.67-0.92; P = .003) significantly impacted adherence. CONCLUSIONS: This is the first study of adherence to follow-up recommendations for patients with pediatric glaucomas. Percent adherence to follow-up appointments was alarmingly low, and decreased adherence was observed with non-white race and increased distance to the eye clinic. Physicians should consider these risk factors when risk-stratifying patients with pediatric glaucomas for nonadherence to follow-up. Additional studies to improve adherence through interventions that reduce biases and barriers to follow-up are needed. ((C) 2020 Elsevier Inc. All rights reserved.)

Comprehensive Analysis to Uncover Determinants of Patient Appointment Compliance in Ophthalmology at the Kresge Eye Institute, USA - Khambati, A; Dowell, L; Tajran, J; Juzych, D; Syeda, S; Wilson, MR; Juzych, MS; Kumar, A (PATIENT PREFERENCE AND ADHERENCE, 2021)
Introduction: Appointment compliance (AC) has a significant impact on patient care; however, determinants of AC in Ophthalmology and its subspecialties remains elusive. Methods: We performed a five-year retrospective analysis across Kresge Eye Institute (KEI) and its affiliated Michigan locations. A total of 597,364 appointments across >13 subspecialties were included. AC was the primary outcome of interest. Compliant (CO) and non-compliant (NC) groups were compared to the following variables: patient characteristics (gender, race, age, insurance), appointment rank (relative to patient history), scheduling location, month, and ophthalmic specialty, in regard to arrival and no-show. Results: Among all appointments, 59.77% were associated with a female patient and 79.16% of the total number of appointments depicted patient compliance. AC differed concerning specialty, with retina representing the highest compliance across all appointments. Among 200+ insurance providers, Medicare was most frequently used and represented the highest share of CO appointments. African Americans were the primary ethnicity served by KEI and had the highest number of NC appointments. Conclusion: Our study demonstrates the impact of patient demographics, appointment characteristics, and ophthalmic subspecialty on AC. A better understanding of these determinants could allow for an increased CO for Ophthalmology practices.

Patient-Related and System-Related Barriers to Glaucoma Follow-up in a County Hospital Population - Lee, BW; Murakami, Y; Duncan, MT; Kao, AA; Huang, JY; Lin, S; Singh, K (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2013)
PURPOSE. To identify the barriers to glaucoma follow-up and to assess how ethnicity influences the effect of such barriers among patients in a county hospital population. METHODS. This cross-sectional study included 152 patients, 76 with poor clinic follow-up and 76 with good clinic follow-up, who were recruited at the San Francisco General Hospital glaucoma clinic as part of a case-control study. All subjects were required to be established patients with glaucoma initially seen and diagnosed in the clinic at least 1 year before enrollment. An oral questionnaire pertaining to the barriers to follow-up for glaucoma, as well as patient ethnicity, was administered to all participating subjects. The main outcome measure was the prevalence of significant barriers to follow-up, both overall and stratified by ethnicity. RESULTS. The most prevalent barriers to follow-up included long clinic waiting times (75%), appointment scheduling difficulties (38%), the effect of other medical or physical comorbidities (29%), and difficulties related to medical interpretation (23%). While several barriers were cited as being important across different ethnicities, Latinos and Asian-Pacific Islanders were particularly affected by difficulties related to medical interpretation (P = 0.0001) and long waiting times in the clinic (P = 0.048). CONCLUSIONS. Understanding patient-reported barriers to glaucoma follow-up and their variation based on ethnicity may give providers insight as to why patients do not adhere to follow-up recommendations. Strategies to improve follow-up may include reduced clinic wait times, simplified appointment scheduling, and provision of appropriate education and counseling regardless of the patient's native language and ethnicity.

The Relationship of Travel Distance to Postoperative Follow-up Care on Glaucoma Surgery Outcomes - Funk, IT; Strelow, BA; Klifto, MR; Knight, OJ; Van Buren, E; Lin, FC; Fleischman, D (JOURNAL OF GLAUCOMA, 2020)
Precis: This study addresses the paucity of literature examining glaucoma patients' distance from clinic on postoperative follow-up outcomes. Greater distance from clinic was associated with higher likelihood of loss to follow-up and missed appointments. Purpose: To investigate the relationship of patient travel distance and interstate access to glaucoma surgery postoperative follow-up visit attendance. Methods and Participants: Retrospective longitudinal chart review of all noninstitutionalized adult glaucoma patients with initial trabeculectomies or drainage device implantations between April 4, 2014 and December 31, 2018. Patients were stratified into groups on the basis of straight-line distance from residence to University of North Carolina at Chapel Hill's Kittner Eye Center and distance from residence to interstate access. Corrective procedures, visual acuity, appointment cancellations, no-shows, and insurance data were recorded. Means were compared using 2-tailed Student t-test, Pearson chi(2), analysis of variance, and multivariate logistical regression determined odds ratios for loss to follow-up. Results: In total, 199 patients met all inclusion criteria. Six-month postoperatively, patients >50 miles from clinic had greater odds of loss to follow-up compared with patients <25 miles (odds ratios, 3.47; 95% confidence interval, 1.24-4.12; P<0.05). Patients >50 miles from clinic had significantly more missed appointments than patients 25 to 50 miles away, and patients <25 miles away (P=0.008). Patients >20 miles from interstate access had greater loss to follow-up than those <10 miles (t((150))=2.05; P<0.05). Mean distance from clinic was 12.59 miles farther for patients lost to follow-up (t((197))=3.29; P<0.01). Patients with Medicaid coverage had more missed appointments than those with Medicare plans (t((144))=-2.193; P<0.05). Conclusions: Increased distance from clinic and interstate access are associated with increased missed appointments and loss to follow-up. Glaucoma specialists should consider these factors when choosing surgical interventions requiring frequent postoperative evaluations.

Barriers to Follow-Up and Strategies to Improve Adherence to Appointments for Care of Chronic Eye Diseases - Thompson, AC; Thompson, MO; Young, DL; Lin, RC; Sanislo, SR; Moshfeghi, DM; Singh, K (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2015)
PURPOSE. To understand factors associated with poor attendance of follow-up appointments for care of glaucoma (GL), AMD, and diabetic retinopathy (DR) in a tertiary referral center, and to identify strategies to improve adherence. METHODS. Cross-sectional study of 240 adults attending follow-up appointments for GL, AMD, or DR. Cases (N = 102) were patients with poor follow-up who missed and failed to reschedule an appointment within 1 month of the recommended follow-up date during the preceding year. Controls (N = 138) were patients who completed the assigned follow-up. Data regarding the factors impacting adherence to appointments were collected via an orally administered questionnaire. Multivariate logistic regression was performed to determine factors associated with poor follow-up. RESULTS. In a multivariate logistic regression model, independent factors significantly associated with poor follow-up included incorrectly answering more than 50% of questions about eye disease (adjusted odds ratio [OR] = 3.24, P = 0.001), legal blindness (adjusted OR 2.64, P = 0.013), the presence of glaucomatous versus retinal disease (adjusted OR 2.06, P = 0.013), and difficulty for the study subject and/or escort taking time away from work for the appointments (adjusted OR 1.80, P = 0.049). Subjects identified the following strategies to improve follow-up: contact with others having the same eye condition (41.3%), greater education regarding eye disease (40.8%), and improved transportation services to the clinic (44.6%). CONCLUSIONS. Low disease knowledge scores, legal blindness, and difficulty getting time away from work for appointments adversely impacted follow-up independent of eye disease diagnosis. Improvements in patient education, transportation services, and clinic efficiency may increase adherence to recommended appointment intervals.

Effectiveness and Cost of a Personalized Reminder Intervention to Improve Adherence to Glaucoma Care - Pizzi, LT; Tran, J; Shafa, A; Waisbourd, M; Hark, L; Murchison, AP; Dai, Y; Mayro, EL; Haller, JA (APPLIED HEALTH ECONOMICS AND HEALTH POLICY, 2016)
Background Glaucoma is the leading cause of irreversible blindness in the USA. Glaucomatous vision loss is preventable with proper eye care, including appointment adherence. Therefore, interventions that improve appointment adherence can reduce the number of patients with more severe glaucoma. Objectives The primary study aim was to determine the efficacy and cost-effectiveness of a multifaceted personal reminder intervention, which included a customized letter and personal telephone outreach, in improving appointment adherence of patients with glaucoma. A secondary study aim was to identify patient characteristics that were associated with non-adherence. Methods This prospective, randomized, controlled study included a cost-effectiveness analysis completed using a decision analytic model. The subjects included 256 patients with glaucoma. Study measures included appointment adherence and incremental cost effectiveness ratios. Results Patients in the intervention group were more likely to adhere to appointments (82.31 vs. 69.05 %; RR 1.23; 95 % CI 1.04-1.37, p< 0.012) than patients in the usual care group. Patients in the intervention group were 23 % more likely to adhere to appointments (RR 1.23; 95 % CI 1.08-1.41, p< 0.0021) than patients in the usual care group, when adjusting for age, secondary insurance, primary open angle glaucoma diagnosis, number of previous visits at Wills Eye Hospital, and follow-up recommendation using Poisson regression. Per-patient cost of the program was US$11.32, and cost per follow-up attended within the adherence window was US$73.56. Conclusions A low cost reminder intervention consisting of a personalized letter and telephone outreach significantly improved appointment adherence of patients with glaucoma.

An Exploratory Study of Factors Influencing Glaucoma Treatment Adherence - Stryker, JE; Beck, AD; Primo, SA; Echt, KV; Bundy, L; Pretorius, GC; Glanz, K (JOURNAL OF GLAUCOMA, 2010)
Purpose: To understand the factors that influence glaucoma treatment adherence with medication taking, prescription refills, and appointment keeping to develop an intervention for a specific population. Patients and Methods: In-depth interviews were conducted with 80 individuals diagnosed with open-angle glaucoma, glaucoma suspect, or ocular hypertension. Additional eligibility requirements were that all participants were: between the ages of 18 to 80; white or African American; spoke and understood English, and were taking daily doses of topical glaucoma treatments for at least the past year. Cross-tabulations and chi(2) tests were conducted to compare adherent and nonadherent individuals, classified as such based on self-report and medical chart/pharmacy data. Results: Compared with adherent participants, nonadherent participants were less likely to: believe their eye doctors spent sufficient time, with them: ask their eye doctor if they had any questions: know of benefits to taking their glaucoma medication regularly; and have someone help them take their glaucoma medications or drive them to eye appointments. Conversely, compared with adherent individuals. nonadherent participants were more likely to have difficulty remembering to take their medications and to believe their glaucoma Would affect their eye sight in the future. Conclusions: Nonadherent glaucoma patients struggle with a variety of issues related to consistent use of glaucoma medicine and routine eye care. Interventions are needed to address these modifiable factors related to glaucoma treatment adherence.

A randomized, controlled trial to test the effectiveness of a glaucoma patient navigator to improve appointment adherence - Hark, LA; Johnson, DM; Berardi, G; Patel, NS; Zeng, LC; Dai, Y; Mayro, EL; Waisbourd, M; Katz, LJ; Glaucoma Res Grp (PATIENT PREFERENCE AND ADHERENCE, 2016)
Purpose: Patients with glaucoma who do not keep their follow-up eye care appointments are at risk for developing more severe ocular disease. The primary aim of the current study was to evaluate whether the use of a patient navigator altered adherence to follow-up eye care appointments in community-versus office-based settings. Patients and methods: Patients diagnosed with a glaucoma-related condition following a comprehensive eye examination at 43 community sites in Philadelphia, PA, USA, were enrolled in this prospective, randomized, controlled trial. Patients were randomized into three groups for a 1-year period: Group 1 (G1) received follow-up eye care in a community-based setting with assistance from a patient navigator; Group 2 (G2) received follow-up eye care in an office-based setting with assistance from a patient navigator; and Group 3 (G3) received follow-up eye care in an office-based setting without a patient navigator (usual care). Adherence rates were compared among these three groups using a chi-squared test at a significance level of 0.05. Results: A total of 155 patients with glaucoma-related diagnoses were enrolled. The mean age (+/- standard deviation) was 71.2 (+/- 10.0) years. Patients were predominantly female (65.8%, n= 102/155) and African-American (71.6%, n= 111/155). The mean (+/- standard deviation) number of follow-up visits during the 1-year study period was 1.3 (+/- 1.3) for G1, 1.6 (+/- 1.3) for G2, and 1.3 (+/- 1.1) for G3 (P= 0.48). Appointment adherence, defined as attendance of >= 1 follow-up visit, was 69.8% (n= 37/53) for G1, 82.5% (n= 47/57) for G2, and 73.3% (n= 33/45) for G3, (P= 0.28). Sub-analysis of adherence rates for patients who attended >= 2 follow-up visits were 91.3% (n= 21/23) for G1, 74.3% (n= 26/35) for G2, and 66.7% (n= 18/27) for G3, (P= 0.11). Conclusion: Help from a patient navigator did not increase the likelihood of keeping >= 1 follow-up appointment in an office-based setting. Adherence rates for follow-up appointments reached close to 70% or above in a self-selected patient population.

The Association Between Compliance With Recommended Follow-up and Glaucomatous Disease Severity in a County Hospital Population - Ung, C; Murakami, Y; Zhang, E; Alfaro, T; Zhang, M; Seider, MI; Singh, K; Lin, SC (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2013)
PURPOSE: To assess the association between insufficient follow-up and clinical parameters such as disease severity and medication use among glaucoma patients at a metropolitan county hospital. DESIGN: Cross-sectional study. METHODS: Two-hundred and six patients with established glaucoma were recruited from San Francisco General Hospital. Subjects were classified based on compliance with recommended follow-up examination intervals over the year preceding commencement of the study, as determined by patient medical records. Glaucoma severity was determined based on the American Academy of Ophthalmology Preferred Practice Patterns guidelines. Multivariate logistic regression analysis was used to assess the relationship between adherence with follow-up visits and disease severity. RESULTS: After adjustment for the impact of potential confounding variables, subjects with severe glaucomatous disease were found to have been less adherent to their recommended follow-up than those patients with mild or moderate glaucomatous disease (adjusted OR 1.89, 95% CI 1.21-2.94; P = .01). Subjects who were on glaucoma medications were found to be less adherent to follow-up recommendations (adjusted OR 3.29, 95% CI 1.41-7.65, P = .01). CONCLUSION: Subjects with poor follow-up adherence were significantly more likely to have severe glaucomatous disease, suggesting that poor follow-up may contribute to disease worsening or, alternatively, those with more severe disease are less inclined to follow up at appropriate intervals. Published by Elsevier Inc.

Understanding the reasons for loss to follow-up in patients with glaucoma at a tertiary referral teaching hospital in Korea - Kim, YK; Jeoung, JW; Park, KH (BRITISH JOURNAL OF OPHTHALMOLOGY, 2017)
Background/aims To assess the reasons and factors for discontinuation of follow-up among patients with glaucoma at a tertiary referral teaching hospital in Seoul, Korea. Methods We identified all adult patients with glaucoma (>= 18 years), who had visited the glaucoma clinic of Seoul National University Hospital between April 2012 and March 2014 and had missed an appointment by at least 12 months. These patients were traced via cellular phone, and their true status and reasons for discontinuation of follow-up were documented. Results A total of 6848 patients with glaucoma (3512 men and 3336 women) were considered. Among them, 247 (3.61%) had missed a scheduled appointment by 12 months or more. Among 230 (93.1%) who were successfully traced, 4 (1.7%) had died and 96 (41.7%) had self-transferred to another glaucoma clinic. Of the 130 patients left, 123 (94.6%) had treatment and follow-up interruptions, and 7 (5.4%) had been treated with alternative medicine. The two main reasons cited for treatment and follow-up interruptions were lack of understanding regarding the necessity of follow-up (46.3%) and unawareness of appointment schedule (30.9%). In stepwise linear regression analysis, older age (p=0.001. beta=0.13), male gender (p=0.013, beta=0.08) and lower baseline intraocular pressure (p=0.005, beta=0.11) were independently associated with follow-up loss involving treatment interruptions. Conclusions This study's results emphasise the need for ongoing educational support and improved appointment notification, especially for the elderly, men and patients with low baseline intraocular pressure.

Factors Associated with Non-compliance for Diabetic Retinopathy Follow-up in an Urban Safety-Net Hospital - Chen, AJ; Hwang, V; Law, PY; Stewart, JM; Chao, DL (OPHTHALMIC EPIDEMIOLOGY, 2018)
Purpose: Diabetic retinopathy (DR) is the leading cause of preventable blindness in working-aged adults, and compliance in ophthalmic follow-up appointments is critical to prevent vision loss. However, barriers to follow-up care have not been well studied, especially in socio-economically disadvantaged groups. We investigated the risk factors for non-compliance to DR follow-up appointments in a safety-net county hospital. Methods: Two hundred and nine patients who were treated for DR at the Zuckerberg San Francisco General Hospital retina clinic between 1 July 2015 and 30 January 2016 were enrolled in the study. Multivariate logistic regression analysis of demographic and medical information was used to determine independent risk factors for non-compliance to DR follow-up appointments. Results: The mean patient age was 58 years. Sixty-three percent (132/209) of patients were male; the mean haemoglobin A1c level was 8.5 (SD 0.14). Forty-six percent (97/209) of patients attended <80% of their DR follow-up appoinments. Independent risk factors for non-compliance after multivariate logistic regression analysis were diabetic foot involvement [OR: 2.40, 95% CI: (1.04-5.55)] and foot/kidney involvement [OR: 3.79 (1.35-10.5)], history of major depressive disorder (MDD) [OR: 2.11 (1.05-4.26), and having Medi-Cal [OR: 5.01 (2.00-12.5)] or SF Health insurance [OR: 6.79 (2.14-21.5)]. Conclusions and Relevance: In conclusion, this is the first study to identify diabetic end organ damage and MDD as independent risk factors for non-compliance in DR follow-up appointments. It is important that health care providers identify these patient subsets and increase efforts to more deliberately encourage follow-up in these high-risk patient groups for DR.

Tenons Patch Graft in the Management of Large Corneal Perforations - Korah, S; Selvin, SST; Pradhan, ZS; Jacob, P; Kuriakose, T (CORNEA, 2016)
Purpose:To describe a technique to manage corneal perforations between 3 and 6 mm in size using autologous Tenons tissue with cyanoacrylate glue and a bandage contact lens.Methods:A thin layer of Tenons capsule harvested from the patient's own eye is used to seal the perforation and act as a scaffold. The Tenons patch graft is spread over the perforation and held in place by the application of cyanoacrylate glue. A bandage contact lens is then placed on the eye.Results:A 6-year retrospective review of 28 patients who underwent this procedure was performed. One patient was lost to follow-up. Of the 27 patients who were followed up, 20 healed completely, with an adherent leucoma and preservation of the anterior chamber. The condition of one patient (with a perforated Pseudomonas corneal ulcer) progressively worsened despite maximum medical therapy and had to undergo evisceration.Conclusions:This procedure makes use of easily available autologous Tenons tissue in patients with corneal perforations too large to be managed with cyanoacrylate glue alone, to preserve eyeball morphology. A corneal transplant can then be done when the cornea has healed.

Failure of Glaucoma Follow-up Compliance - Ung, C; Spaeth, GL; Lin, SC; Singh, K (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2015)

Compliance to topical anti-glaucoma medications among patients at a tertiary hospital in North India - Rajurkar, K; Dubey, S; Gupta, PP; John, D; Chauhan, L (JOURNAL OF CURRENT OPHTHALMOLOGY, 2018)
Purpose: The present study aims to estimate the prevalence of non-compliance and improper drop administration technique among glaucoma patients and describe common obstacles to medication compliance. Methods: A hospital-based cross-sectional study, using standardized questionnaire and direct observation by study personnel was conducted among glaucoma patients aged 18 years and above at a tertiary care charitable eye hospital in North India. 151 consecutive glaucoma patients on medical therapy following up at the glaucoma clinics for at least 6 months were recruited. Non-compliance was defined as missing at-least one drop of medication per week and (or) the inability to accurately describe the medication regimen. Study personnel also assessed drop administration technique during application of eye drops by patients treating ophthalmologist-provided information, including measures of disease stability. Factors such as socioeconomic status, presence of caregiver, and number of medications with their effect on compliance were studied using chi-square statistics. Results: Among 151 patients interviewed, around 49% of patients reported problems in using glaucoma medications, with 16% of them reporting total non-compliance. 35% of patients demonstrated improper drop administration technique. Forgetfulness was cited as the main reason for being non-compliant and had a significant association with non-compliance (P = 0.00). Paying patients were more compliant as compared to subsidized patients (P = 0.05). Disease was more stable in compliant patients compared to non-compliant patients (P = 0.05). No other factor had significant association with compliance (P > 0.05). Conclusions: Over 50% of the patients surveyed were non-compliant, and 35% demonstrated improper administration technique. Glaucoma patients should be educated on the importance of compliance and aids that minimize forgetfulness, and delivery systems facilitating the delivery of medications to the eye could be considered to enhance patient adherence. Copyright (C) 2017, Iranian Society of Ophthalmology. Production and hosting by Elsevier B.V.

Racial and Ethnic Disparities in Adherence to Glaucoma Follow-up Visits in a County Hospital Population - Murakami, Y; Lee, BW; Duncan, M; Kao, A; Huang, JY; Singh, K; Lin, SC (ARCHIVES OF OPHTHALMOLOGY, 2011)
Objectives: To identify predictors of inconsistent attendance at glaucoma follow-up visits in a county hospital population. Methods: Prospective recruitment from August 1, 2008, through January 31, 2009, of 152 individuals with glaucoma, with 1-to-1 matching of patients (those with inconsistent follow-up) and controls (those with consistent follow-up). Data were collected via oral questionnaire. Survey results were correlated with attendance at follow- up examinations, using the t test, chi(2) test, and multivariate stepwise logistic regression analysis to calculate the odds ratios (ORs) and 95% confidence intervals. Results: After adjusting for covariates in the logistic regression analysis, factors independently associated with inconsistent follow-up included black race (adjusted OR, 7.16; 95% confidence interval, 1.64-31.24), Latino eth-nicity (adjusted OR, 4.77; 1.12-20.29), unfamiliarity with necessary treatment duration (adjusted OR, 3.54; 1.26-9.94), lack of knowledge of the permanency of glaucomainduced vision loss (adjusted OR, 3.09; 1.18-8.04), and perception that it is not important to attend all follow- up visits (adjusted OR, 3.54; 1.26-9.94). Conclusions: Demographic factors, including race and ethnicity, may directly or indirectly affect adherence to recommended glaucoma follow-up visits. Lack of information regarding irreversible vision loss from glaucoma, need for lifelong treatment, and lack of visual symptoms may be significant barriers to follow-up in this population. Targeted glaucoma education by physicians may improve follow-up, thereby decreasing the morbidity associated with glaucomatous disease.

Providing Prescheduled Appointments as a Strategy for Improving Follow-Up Compliance After Community-Based Glaucoma Screening: Results from an Urban Underserved Population - van Zyl, T; Su, Z; Zhou, E; Wong, RK; Mohsenin, A; Rogers, S; Tsai, JC; Forster, SH (JOURNAL OF COMMUNITY HEALTH, 2015)
To determine if receiving a prescheduled appointment is associated with an increased likelihood of complying with follow-up eye care among individuals identified as at risk for glaucoma during community-based glaucoma screening in an urban underserved population. This study sampled 362 individuals aged a parts per thousand yen30 years without known glaucoma from low-income, predominantly black/Hispanic neighborhoods in New Haven, Connecticut presenting to one of twelve community-based glaucoma screening events from May 2010 to October 2012. A quasi-experimental design systematically assigned 63 individuals identified as at risk for glaucoma into either intervention or control group with a 1:2 ratio. Individuals in the control group (n = 41) received counseling on glaucoma and a recommendation for obtaining a follow-up appointment at the eye department of a local community health center, which offers affordable health services with income-adjusted fee discounts to uninsured, low-income patients. Those in the intervention group (n = 22) received the same counseling and a prescheduled appointment at the community health center. The overall rate of follow-up compliance within 3 months of screening was 30 % (41 % in the intervention group; 24 % in the control group). Multivariate logistic regression analysis adjusting for sex, age, ethnicity, health insurance status, car access, living situation, and smoking status found that follow-up compliance was significantly associated with intervention (adjusted odds ratio 4.8; 95 % confidence interval 1.1-20.9). Providing prescheduled appointments can improve follow-up compliance after community-based glaucoma screening. This finding may be potentially applicable to community-based health screening for other preventable diseases.

A Randomized Trial to Improve Adherence to Follow-up Eye Examinations Among With Glaucoma - Leiby, BE; Hegarty, SE; Zhan, TT; Myers, JS; Katz, LJ; Haller, JA; Waisbourd, M; Burns, C; Divers, M; Molineaux, J; Henderer, J; Brodowski, C; et al. (PREVENTING CHRONIC DISEASE, 2021)
Introduction Appointment nonadherence is common among people with glauc-oma, making it difficult for eye care providers to monitor glauc-oma progression. Our objective was to determine whether the use of patient navigators, in conjunction with social worker support, could increase adherence to recommended follow-up eye appoint-ments. Methods A randomized, controlled trial evaluated the effectiveness of an in-tervention that used patient navigators and social workers to im-prove patient adherence to follow-up eye care compared with usu-al care. Participants with glaucoma and other eye diseases (N = 344) were identified at primary care clinics in community settings through telemedicine screening of imaging and then randomized to enhanced intervention (EI) or usual care (UC). Data on parti-cipants & rsquo; visits with local ophthalmologists were collected for up to 3 years from randomization. Groups were compared for timely at-tendance at the first visit with the local ophthalmologist and adher-ence to recommended follow-up visits. Results Timely attendance at the first visit was higher for EI than UC (74.4% vs 39.0%; average relative risk [aRR] = 1.85; 95% CI, 1.51 & ndash;2.28; P < .001). Rates of adherence to recommended annual follow-up during year 1 were 18.6% in the EI group and 8.1% in the usual care group (aRR = 2.08; 95% CI, 1.14 & ndash;3.76; P = .02). The aRR across years 2 and 3 was 3.92 (95% CI, 1.24 & ndash;12.43; P = .02). Conclusion An intervention using patient navigators and social workers doubled the rate of adherence to annual recommended follow-up eye care compared with usual care in community settings, and was effective at increasing connections with local ophthalmologists. Interventions to further improve long-term adherence are needed.

Adherence to Follow-up Recommendations Among Individuals in the Philadelphia Glaucoma Detection and Treatment Project - Hark, LA; Leiby, BE; Waisbourd, M; Myers, JS; Fudemberg, SJ; Mantravadi, AV; Dai, Y; Gilligan, JP; Resende, AF; Katz, LJ (JOURNAL OF GLAUCOMA, 2017)
Purpose:To evaluate rates of adherence to free follow-up eye exam appointments among participants in the Philadelphia Glaucoma Detection and Treatment Project.Patients and Methods:Ophthalmologists and testing equipment were brought directly to participants at risk for glaucoma at 43 community sites in Philadelphia. Those diagnosed with glaucoma-related pathology were recommended to return for follow-up to be reexamined on site. Rates of adherence and clinical and demographic risk factors for adherence were evaluated.Results:Five hundred thirty-one participants were diagnosed with glaucoma-related conditions and recommended to attend community-based follow-up exams. Follow-up adherence rate was 61.2% (n=325/531). Significant factors associated with greater eye exam appointment adherence, based on our univariable analysis, included final diagnosis of glaucoma (risk ratio [RR]=1.33; 95% confidence interval [CI], 1.13-1.57), male sex (RR=1.19; 95% CI, 1.04-1.36), white race (RR=1.26; 95% CI, 1.08-1.48), age (RR=1.17; 95% CI, 1.00-1.37) recommendation for glaucoma medication (RR=1.52; 95% CI, 1.35-1.71), recommendation for laser peripheral iridotomy (RR=1.18; 95% CI, 1.02-1.35), diagnosis of age-related macular degeneration (RR=1.42; 95% CI, 1.13-1.77) and an increased intraocular pressure (>22 mm Hg in the worse eye) (RR=1.23; 95% CI, 1.06-1.42). On the basis of our multivariable model, diagnosis, sex, and recommended glaucoma medications were significantly associated with follow-up adherence.Conclusions:This study demonstrates that individuals living in underserved urban communities would take advantage of free eye exams in community sites and return for follow-up eye exams in these same settings. Future studies could investigate interventions to improve eye exam appointment adherence in community-based settings to detect glaucoma-eye conditions.

RISK-FACTORS FOR NONCOMPLIANCE WITH GLAUCOMA FOLLOW-UP VISITS - KOSOKO, O; QUIGLEY, HA; VITALE, S; ENGER, C; TIELSCH, J; KERRIGAN, LA (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 1995)

The Maccabi Glaucoma Study: Treatment Patterns and Persistence With Glaucoma Therapy in a Large Israeli Health Maintenance Organization - Goldshtein, I; Shalev, V; Zigman, N; Chodick, G; Levkovitch-Verbin, H (JOURNAL OF GLAUCOMA, 2016)
Purpose: To describe treatment patterns, adherence, and persistence with initial therapy among glaucoma patients in the community. Materials and Methods: A population-based historical prospective cohort study, using the electronic medical databases of Maccabi Healthcare Services, a 2 million member health maintenance organization in Israel. Newly diagnosed glaucoma patients between 2003 and 2010, who purchased at least 1 antiglaucoma medication, were followed up to December 31, 2012. Outcome measures included medication adherence analyzed by proportion of days covered by drugs during follow-up time, and persistence with initial therapy measured by time until switch or discontinuation of first-line therapy. Results: A total of 5934 incident definite glaucoma patients were identified, 13% of whom were nonadherent with therapy (covered <20% of the follow-up time), and only 25% exhibited high adherence (covered at least 80% of the follow-up period). Adherence was positively associated with female sex, age, socioeconomic status, frequent follow-up visits, and higher baseline intraocular pressure. Lower median adherence (P < 0.01) was observed among patients of normal tension glaucoma (52%) and angle closure (59%) as compared with open angle (65%) and exfoliation glaucoma (68%). Patients treated by glaucoma specialists had similar adherence to those treated by general ophthalmologists (proportion of days covered = 65% vs. 63%, P = 0.42). Persistence with initial line of therapy varied by type of medication, with prostaglandin initiators exhibiting the highest persistence (13% reduced likelihood of switch or discontinuation as compared with beta-blockers, P < 0.01) and alpha-agonists the lowest persistence (39% increased likelihood of switch or discontinuation as compared with beta-blockers, P < 0.01). Conclusions: This large-scale analysis of real-world use of glaucoma medications reveals that adherence to glaucoma therapy is associated with medication type, patient's sex, age, socioeconomic status, type of glaucoma, follow-up visits, and baseline intraocular pressure.

Risk factors for noncompliance with glaucoma follow-up visits in a residents' eye clinic - Kosoko, O; Quigley, HA; Vitale, S; Enger, C; Kerrigan, L; Tielsch, JM (OPHTHALMOLOGY, 1998)
Objective: This study aimed to identify factors associated with compliance with glaucoma follow-up visits. Design: Computer records of a university residents' eye clinic were reviewed to identify a random sample of all persons who had an examination with International Classification of Disease (ICD) 9 coding (ICD9) for glaucoma suspect or glaucoma during a 2-year period (1991-1993) to undergo telephone interview. Participants: Those who were seen at least every 6 months regardless of earlier return instructions were defined as compliant with follow-up (controls, n 362). Those who had any lapse between visits of longer than 6 months were defined as noncompliant (cases, n = 362). Results: Interviews were completed for 196 cases and 242 controls. Noncompliant persons were significantly more likely to be suspects for glaucoma rather than to have definite glaucoma and to be dissatisfied with waiting time in the clinic (29.1% vs. 17.8%, P < 0.005) and to state that they did not take their glaucoma medications as prescribed (25.4% vs. 13.4%, P < 0.004). They also were less likely to have been prescribed eyedrop medication. A high percentage of both patients and controls knew that glaucoma can lead to blindness (85.2% and 88.4%, respectively). The most common reasons patients gave for not keeping follow-up visits were the perception that their eye problem was "not serious enough," the cost of examinations, and that the doctor did not tell them to come back. Conclusion: Compliance with follow-up visits for glaucoma is associated with markers for early disease. Attempts to improve compliance might focus on improved communication of the seriousness of the disease and improvements in clinic waiting time.

Awareness of ocular diagnosis, transportation means, and barriers to ophthalmology follow-up in the Philadelphia Telemedicine Glaucoma Detection and Follow-up Study - Hark, LA; Radakrishnan, A; Madhava, M; Anderson-Quinones, C; Fudemberg, S; Robinson, D; Myers, JS; Zhan, TT; Adeghate, J; Hegarty, S; Leite, S; Leiby, BE; et al. (SOCIAL WORK IN HEALTH CARE, 2019)
Purpose: The purpose of this study was to assess factors affecting follow-up eye care in participants enrolled in the Philadelphia Telemedicine Glaucoma Detection and Follow-up Study, such as awareness of ocular diagnosis, availability of transportation methods, and reasons for missing eye care appointments. Methods: The sample included 172 participants who were randomized to the intervention group and contacted by the social worker. Results: A total of 155 participants completed the assessment form, which was used as an instrument to assess factors affecting adherence to follow-up eye care. The main reasons for missing eye exam appointments were feeling ill (38.1%, n = 59) and forgetting the appointment (34.2%, n = 53). In addition, 45 (29.2%) participants were unaware of or did not comprehend the severity of their ocular diagnosis. Common methods of transportation included public transportation (31.6%, n = 49), driving (29.7%, n = 46), and being driven (27.7%, n = 43) to their appointment. Conclusion: These results suggest that individuals in need of eye care may benefit from additional assistance of a social worker regarding ongoing eye exam appointment reminders and in-depth explanation of their ocular diagnosis.

Glaucoma Care of Prison Inmates at an Academic Hospital - Kanu, LN; Jang, I; Oh, DJ; Tiwana, MS; Mehta, AA; Dikopf, MS; Vajaranant, TS; Aref, AA; Edward, DP (JAMA OPHTHALMOLOGY, 2020)
Question What is the glaucoma profile of prison inmates referred to an academic center, and how is the treatment of those patients managed? Findings In this cohort study of 82 prison inmates, suspected and primary open-angle glaucoma were the most common diagnoses, with advanced disease present in 53.2% of patients with confirmed glaucoma. Most patients self-reported medication nonadherence, and follow-up visits often were delayed, with approximately one-quarter of visits during the recommended time frame and one-third delayed by more than 1 month. Meaning These findings suggest that glaucoma management of prison inmates requires careful consideration of barriers to care, and close communication with the referring facility may be advised. Importance Glaucoma care for prison inmates is underrepresented in the literature even though managing the treatment of such patients may provide unique challenges. Objectives To evaluate the glaucoma profile of prison inmates treated at an academic ophthalmology center and to report on the medical and surgical management and follow-up metrics. Design, Setting, and Participants This retrospective cohort study assessed data from 82 incarcerated patients treated at the glaucoma clinic, an academic referral center at the University of Illinois at Chicago, between January 2013 and December 2017. Main Outcomes and Measures Diagnosis, glaucoma severity, medical and surgical interventions, and patient-reported medication adherence were recorded for each visit. Recommended and actual follow-up times were recorded and compared. Data analyses were conducted from January 2013 to December 2018. Results In total, 82 patients (161 eyes) had 375 visits during the study period. All patients were male and ranged from 20 to 75 years of age (mean [SD] age, 50.8 [11.9] years). Most participants were black patients (65 [79.3%]). The most common diagnoses were primary open-angle glaucoma (POAG; 53 eyes [32.9%]) and POAG suspect (52 eyes [32.3%]). Glaucoma severity ranged from mild (25 of 77 eyes [32.5%]) to advanced (41 of 77 eyes [53.2%]). Overall, 59 patients (73.2%) were treated medically with up to 4 topical agents (40.0%). Of those treated, 70.0% of patients (95% CI, 57.7%-81.2%) reported medication nonadherence during at least 1 visit. Medication nonadherence was more common among those taking 4 different topical medications (21 of 24 [87.5%]) compared with others taking fewer medications (20 of 35 [57.1%]), for a difference of 30.4% (95% CI, 7.0%-53.6%; P = .02), and among those with advanced disease (22 of 26 [84.6%]) compared with glaucoma suspect (6 of 13 [46.2%]), for a difference of 38.4% (95% CI, 9.3%-67.5%; P = .02). Nineteen office procedures, including laser peripheral iridotomy and laser trabeculoplasty, were performed on 14 eyes. Seventeen incisional glaucoma procedures were performed on 15 eyes, including glaucoma drainage device implant (11 procedures [64.7%]) and trabeculectomy (3 procedures [17.6%]). Only 26.6% of return office visits (95% CI, 21.3%-32.3%) occurred within the recommended follow-up time frame. Furthermore, 93 patients (34.8%; 95% CI, 28.2%-40.0%) were seen more than 1 month after the recommended follow-up. Conclusions and Relevance Despite incarceration in prison, where medication administration and appointment attendance are theoretically controlled, the results of this study suggested that substantial medication and follow-up nonadherence exists among inmates. This cohort study conducted in an academic ophthalmology referral center assesses the glaucoma disease profile and medical and surgical glaucoma management and follow-up metrics of prison inmates.

A Comprehensive Perspective on Patient Adherence to Topical Glaucoma Therapy - Tsai, JC (OPHTHALMOLOGY, 2009)
Topic: Risk factors for poor adherence or nonadherence to topical glaucoma medication regimens. Clinical Relevance: Poor adherence to glaucoma medication regimens maybe associated with subsequent visual loss and irreversible optic nerve damage. Methods: A literature search was performed using the words "glaucoma AND adherence AND risk" and "glaucoma AND compliance AND risk," limited to those studies in English and focused on care in the United States. Publications from well-regarded journals in this field were reviewed, and a focused summary of the literature is presented. Results: There are a myriad of adherence barriers inherent to the glaucoma patient population. Although most of these obstacles are common in the elderly (e.g., reduced cognition, musculoskeletal problems, and transportation difficulties), older age has not been shown to be a consistent risk factor for poor adherence to glaucoma medication regimens. Other expected barriers, such as medication cost, limited health insurance, disease severity, and role of complicated dosing regimens, have varied effects based on the patient population studied and the definition of adherence. Poor medication adherence also is associated with decreased adherence to follow-up medical visit schedules. A systematic taxonomy of adherence barriers has been formulated. In addition, subanalyses from the Glaucoma Adherence and Persistency Study identified 8 variables that affect adherence to glaucoma medication regimens as well as several characteristics that support the importance of and associations between doctor-patient communications. Conclusions: Recent studies have provided valuable insights into the many factors that increase the risk(s) for poor adherence in patients prescribed glaucoma medications. Four major types of barriers to effective patient adherence (medication regimen, patient factors, provider factors, and situational or environmental factors) have been identified. Addressing these specific barriers will require a tailored, patient-centered approach. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references. Ophthalmology 2009; 1 16:S30-S36 (C) 2009 by the American Academy of Ophthalmology.

Impact of a Health Communication Intervention to Improve Glaucoma Treatment Adherence - Glanz, K; Beck, AD; Bundy, L; Primo, S; Lynn, MJ; Cleveland, J; Wold, JA; Echt, KV (ARCHIVES OF OPHTHALMOLOGY, 2012)
Objective: To determine the efficacy of an automated, interactive, telephone-based health communication intervention for improving glaucoma treatment adherence among patients in 2 hospital-based eye clinics. Method: A total of 312 patients with glaucoma (18-80 years of age) were enrolled in a randomized controlled trial at 2 eye clinics located in hospitals in the southeastern United States. These patients were considered nonadherent because they did not take their medication, refill their medication, and/or keep their appointments. The treatment group received an automated, interactive, tailored, telephone-based health communication intervention and tailored print materials. The control group received usual care. Main Outcome Measures: Adherence with medication taking, prescription refills, and appointment keeping measured by interviews, medical charts, appointment records, and pharmacy data. Results: A statistically significant increase was found for all adherence measures in both the intervention and control groups. Interactive telephone calls and tailored print materials did not significantly improve adherence measures compared with controls. Conclusions: During the study period, patient adherence to glaucoma treatment and appointment keeping improved in both study arms. Participation in the study and interviews may have contributed. Strategies that address individuals' barriers and facilitators may increase the impact of telephone calls, especially for appointment keeping and prescription refills. Application to Clinical Practice: Glaucoma patient care should include reminders about consistent use of medication and the importance of keeping appointments. More frequent, and personalized, telephone contact may be helpful to patients who are known to be nonadherent.

Philadelphia Telemedicine Glaucoma Detection and Follow-up Study: Adherence to Community Eye Exam Appointments - Hark, LA; Katz, LJ; Myers, JS; Haller, JA (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2018)

Adherence to Medical Treatment and Its Determinants Among Adult Saudi Glaucoma Patients in Riyadh City - Shadid, A; Alrashed, W; Bin Shihah, A; Alhomoud, A; Alghamdi, M; Alturki, A; Shadid, A; Osman, E; Alfaris, A; Khandekar, R (CUREUS, 2020)
Background Glaucoma in adults is a leading eye disease that causes blindness. Its management is life long and both surgical and medical treatment options are available to manage this ailment. Patients and their caregiver's cooperation in instilling timely eye drops is crucial for the effective reduction of intraocular pressure (IOP) and by halting/delaying the progression of visual disabilities due to glaucoma. Periodic assessment and strict adherence to medical treatment has been found to be less than desired. It is influenced by the severity of the disease, the duration of the ailment, the number of eye drops being used, the literacy level, and the cost of medication. We present the adherence rate of topical medications and its determinants among adult Saudi glaucoma patients getting treated in 2017 in a tertiary eye center in Saudi Arabia. Methodology This cross-sectional survey was carried out from January to March 2017 at a tertiary eye hospital in Riyadh, Saudi Arabia. To undertake a cross-sectional study, we assumed that among 1300 patients visiting the eye department of a tertiary eye hospital, the level of non-adherence to glaucoma medication would be in 27% of glaucoma patients. To achieve a 95% confidence interval and an acceptable error margin of 5% for a survey, we needed to interview at least 253 participants. Results We interviewed 263 randomly selected glaucoma patients among 1236 patients visiting the eye department of the tertiary eye hospital in Riyadh, Saudi Arabia. Two-thirds of participants were school graduates, Saudi nationals, and had undergone surgery for glaucoma in the past; perhaps only YAG laser peripheral iridotomy (PI). Less than half of the participants (43%) had less than a one-year duration of glaucoma. The client-perceived subjective adherence rate to glaucoma medication was noted in 191/263 = 72.6% (95% Confidence Interval 67.2 -78.0). Of the 263 glaucoma patients, 229 judiciously abided with their follow-up appointments with ophthalmologists. Thus, the compliance to follow-up for glaucoma treatment was 87.1% (95% CI 83.0 - 91.1). Conclusion Our study with a large sample is perhaps the first one to assess compliance with medical treatment among adult Saudi glaucoma patients. The adherence rate for topical glaucoma medication measured using the subjective method was 72% among adult glaucoma patients. Adherence with the follow-up appointment with the glaucoma specialist was as high as 87%. Adherence with medical treatment found in the present study versus the literature review suggested that despite different sets of barriers, the adherence rate in Saudi adult glaucoma patients noted in our study was high. Knowledge, beliefs, and attitude are known to affect the adherence rate. In our study, education level and relatives having glaucoma were not associated with the adherence rate. This indirectly suggests that knowledge about the use of medication in the treatment of glaucoma that is gained by patients had a limited influence on adherence in our glaucoma patients. Modes of dispersing knowledge to elderly glaucoma patients and their impact on the adherence rates of medications for glaucoma management need to be further studied.

Protocol for a randomised controlled trial to estimate the effects and costs of a patient centred educational intervention in glaucoma management - Cate, H; Bhattacharya, D; Clark, A; Fordham, R; Notley, C; Broadway, DC (BMC OPHTHALMOLOGY, 2012)
Background: Poor glaucoma education is thought to be a causative factor of non-adherence to glaucoma therapy. However, the multi-factorial nature of non-adherent behaviour may explain the failure of purely educational interventions to achieve significant improvement in adherence. Behaviour Change Counselling (BCC) allows both the imparting of information and assessment of patient ambivalence to medication use and may elicit behaviour change in order to achieve better adherence. The chronic and complex nature of glaucoma means that patient non-adherence to glaucoma therapy does not easily correlate with measureable objective clinical endpoints. However, electronic medication monitoring offers an objective method of measuring adherence without reliance on clinical endpoints. Methods/design: The study is a randomised controlled trial (RCT) with glaucoma (open angle) or ocular hypertension patients attending a glaucoma clinic and prescribed travoprost. The study will determine whether additional glaucoma education using BCC is beneficial and cost effective in improving adherence with glaucoma therapy. An 8-month follow-up period, using an electronic adherence monitoring device (Travalert (R) dosing aid, TDA), will indicate if the intervention is likely to be sustained in the longer term. Additionally, a cost-effectiveness framework will be used to estimate the cost benefit of improving adherence. The development of a novel intervention to deliver glaucoma education using BCC required practitioner training and fidelity testing. Five practitioners were successfully trained to become Glaucoma Support Assistants able to deliver the BCC intervention. The research group had prior clinical and investigative experience in this setting, and used multiple strategies to design a method to address the study objectives. Discussion: This RCT, using BCC to improve adherence to ocular hypotensive therapy, to our knowledge is the first within this disease area. Using a variety of adherence measures allows examination of the known inaccuracies of patient self-report with respect to glaucoma medication. The novel BCC component has undergone fidelity testing using BECCI and the BCC template will ensure conformity to a standardised intervention.

Philadelphia glaucoma detection and treatment project: ocular outcomes and adherence to follow-up at a single health centre - Adeghate, JO; Hark, LA; Brown, H; Henderer, JD; Waisbourd, M; Molineaux, J; Malik, K; Maity, A; Chuang, D; Donches, K; Heres, C; Eburuoh, R; et al. (CANADIAN JOURNAL OF OPHTHALMOLOGY-JOURNAL CANADIEN D OPHTALMOLOGIE, 2019)
Objectives: To determine ocular outcomes and factors associated with adherence to ophthalmic follow-up in a medically underserved population at a single health centre in Philadelphia. Design: Retrospective chart review. Participants: Patients from a community glaucoma screening program. Methods: Chart review was conducted for participants who received a complete eye examination at the Philadelphia District Health Center 5 between January 1, 2012 and May 31, 2014 within the Philadelphia Glaucoma Detection and Treatment Project. Multivariate logistic regression was used to determine factors related to ophthalmic follow-up adherence. Results: A total of 249 participants completed an eye examination (mean age = 57.7 +/- 6.9 years). Most were African American (n = 220; 88.4%); female (n = 129; 51.8%). Forty-seven participants (18.9%) received glaucoma-related diagnoses, 20 (8.0%) were prescribed ocular medication, and 26 (10.4%) underwent laser therapy. Ninety (36.1%) attended their recommended follow-up eye examination at the health centre. Glaucoma-related diagnosis (p < 0.001), recommendation of a 4- to 6-week follow-up period (p < 0.001), prescribed eye drops (p < 0.001), or received laser therapy (p = 0.047) were factors most predictive of ophthalmic follow-up adherence. Conclusions: The collaborative effort of eye care providers and health centres offers an important opportunity to detect, treat, and manage glaucoma and other ocular pathology in medically underserved communities. Having a glaucoma-related diagnosis, initiating treatment, and scheduling regular follow-up visits are the most important factors influencing adherence to follow-up eye appointments.

Resource Planning in Glaucoma: A Tool to Evaluate Glaucoma Service Capacity - Batra, R; Sharma, HE; Elaraoud, I; Mohamed, S (SEMINARS IN OPHTHALMOLOGY, 2018)
Background: The National Patient Safety Agency (2009) publication advising timely follow-up of patients with established glaucoma followed several reported instances of visual loss due to postponed appointments and patients lost to follow-up. The Royal College of Ophthalmologists Quality Standards Development Group stated that all hospital appointments should occur within 15% of the intended follow-up period. Aim: To determine whether: 1. Glaucoma follow-up appointments at a teaching hospital occur within the requested time 2. Appointments are requested at appropriate intervals based on the NICE Guidelines 3. The capacity of the glaucoma service is adequate Methods: A two-part audit was undertaken of 98 and 99 consecutive patients respectively attending specialist glaucoma clinics. In the first part, the reasons for delayed appointments were recorded. In the second part the requested follow-up was compared with NICE guidelines where applicable. Based on the findings, changes were implemented and a re-audit of 100 patients was carried out. Results: The initial audit found that although clinical decisions regarding follow-up intervals were 100% compliant with NICE guidelines where applicable, 24% of appointments were delayed beyond 15% of the requested period, due to administrative errors and inadequate capacity, leading to significant clinical deterioration in two patients. Following the introduction of an electronic appointment tracker and increased clinical capacity created by extra clinics and clinicians, the re-audit found a marked decrease in the percentage of appointments being delayed (9%). Conclusions: This audit is a useful tool to evaluate glaucoma service provision, assist in resource planning for the service and bring about change in a non-confrontational way. It can be widely applied and adapted for use in other medical specialities.

Adherence to Follow-Up Appointments in a Resident Glaucoma Clinic vs. Primary Eye Care Clinic: A Retrospective Analysis - Lee, B; Fudemberg, S; Murphy, R; Hark, LA; Waisbourd, M; Dai, Y; Leiby, B (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2015)

Systematic Review of Educational Interventions to Improve Glaucoma Medication Adherence - Newman-Casey, PA; Weizer, JS; Heisler, M; Lee, PP; Stein, JD (SEMINARS IN OPHTHALMOLOGY, 2013)
Adherence to prescribed glaucoma medications is often poor, and proper adherence can be challenging for patients. We systematically reviewed the literature and identified eight studies using educational interventions to improve glaucoma medication adherence. Overall, five of the eight studies found that educational interventions lead to a significant improvement in medication adherence, and two additional studies found a trend towards improvement. Using information from this systematic review and Health Behavior Theory, we constructed a conceptual framework to illustrate how counseling and education can improve glaucoma medication adherence. More rigorous studies grounded in Health Behavior Theory with adequately powered samples and longer follow-up are needed.

Adherence of Finnish people with glaucoma to treatment plans and connected factors - Lunnela, J; Kaariainen, M; Kyngas, H (INTERNATIONAL JOURNAL OF CIRCUMPOLAR HEALTH, 2011)
Objectives. The aim of the study was to describe the adherence of Finnish people with glaucoma to prescribed treatment plans, the factors connected to adherence and to produce knowledge for developing effective interventions to improve adherence to treatment plans. Study design. This was a cross-sectional study. Methods. The data (n=249) were collected at one point in time from Finnish adults diagnosed with glaucoma with a questionnaire covering adherence to treatment. These patients used glaucoma medication and had follow-up appointments with ophthalmologists. Results. Sixty-seven percent (n=166) of the patients with glaucoma were very adherent to the prescribed treatment plan in terms of self-care, treatment and follow-up visits. Almost all were very adherent to medical care (97%, n=242). More than half of those who had received information from physicians and nurses were very adherent to treatment (66%, n=163). Two factors, support from physicians and nurses (p<0.001) and being informed of the consequences of treatments (p=0.003), had a statistically significant connection to treatment adherence. Conclusions. This study indicates that people with glaucoma in Finland adhere well to care and exceptionally well to medical care. Support and patient education from health care personnel is crucial to maintain patient adherence to treatment. These results indicate that nurses play a very important role in patient education and support. In practice, it is crucial to maintain this level of patient engagement by developing more tailored and time-saving education and support methods. The results of this study could be helpful for developing new patient education and support approaches for people with glaucoma. (Int J Circumpolar Health 2011; 70(1):79-89)

Shared care of patients with ocular hypertension in the Community and Hospital Allied Network Glaucoma Evaluation Scheme (CHANGES) - Mandalos, A; Bourne, R; French, K; Newsom, W; Chang, L (EYE, 2012)
Aims The Community and Hospital Allied Network Glaucoma Evaluation Scheme (CHANGES) used accredited community-based optometrists with a special interest (OSIs) in glaucoma to monitor ocular hypertensive (OHT) patients under virtual supervision of the Hospital Glaucoma Service (HGS). The purpose of this paper was to report the outcomes of the first completed community-based visit. Methods Eligible patients underwent a glaucoma consultant-led clinical examination before transfer to CHANGES. Individualised intraocular pressure (IOP) and follow-up time interval targets were set for each patient. OSIs used applanation tonometry, slit-lamp biomicroscopy, automated visual field testing and digital optic disc photography. The hospital-based glaucoma team evaluated the data virtually. Patients were referred back to the HGS according to specific criteria. Results One hundred and sixty eight OHT patients were invited to attend their first OSI appointment. Of these, 144 attended their appointment (attendance rate 85.7%). Outcomes of 130 patients with complete data sets are reported. Sixteen patients (12.3%) were referred back to the HGS due to IOP above target, new visual field defects and/or optic nerve changes. The glaucoma consultant retained eight patients (6.1%) within the HGS on the basis of definite or probable glaucomatous conversion. Conclusions CHANGES freed up capacity within a busy HGS. However, improvements need to be made regarding non-attendance rates in the community. The relatively high one-year definite or probable conversion rate emphasises the importance of the comprehensive review of OHT patients and of hospital-led virtual supervision to maintain patient safety. Eye (2012) 26, 564-567; doi:10.1038/eye.2011.350; published online 6 January 2012

Proposing new indicators for glaucoma healthcare service - Liang, YB; Zhang, Y; Musch, DC; Congdon, N (EYE AND VISION, 2017)
Glaucoma is the first leading cause of irreversible blindness worldwide with increasing importance in public health. Indicators of glaucoma care quality as well as efficiency would benefit public health assessments, but are lacking. We propose three such indicators. First, the glaucoma coverage rate (GCR), which is the number of people known to have glaucoma divided by the total number of people with glaucoma as estimated from population-based studies multiplied by 100%. Second, the glaucoma detection rate (GDR), which is number of newly diagnosed glaucoma patients in one year divided by the population in a defined area in millions. Third, the glaucoma follow-up adherence rate (GFAR), calculated as the number of patients with glaucoma who visit eye care provider(s) at least once a year over the total number of patients with glaucoma in given eye care provider(s) in a specific period. Regularly tracking and reporting these three indicators may help to improve the healthcare system performance at national or regional levels.

Demographics and Behaviour of Patients with Contact Lens-Related Infectious Keratitis in Singapore - Lam, JSH; Tan, G; Tan, DTH; Mehta, JS (ANNALS ACADEMY OF MEDICINE SINGAPORE, 2013)
Introduction: This study aims to identify the demographics and hygiene behaviours associated with contact lens (CL)-related microbial keratitis in Singapore. Materials and Methods: The hygiene and social behaviours of lens wearers presenting with infectious keratitis in Singapore were examined using an externally validated questionnaire. Fifty-eight consecutive lens wearers who presented with infectious keratitis at Singapore National Eye Centre were surveyed using a self-administered questionnaire. Patients' demographics, CL-related behaviour, attitude to aftercare visits and microbial study results were collected and analysed. Results: More than half (55%) of the patients surveyed were female, and the average age of the participants was 25.7 +/- 6.4 years. Ninety-six percent of participants used soft CL, with the majority wearing monthly disposable lenses (74.1%). Myopia was the commonest reason for use of CL. CL overwear (81%), sleeping (50.9%) and swimming (33%) with their CL were the major non-compliant behaviours discovered. When encountered with eye discomfort as a result of lens-related infective keratitis, 83% of patients sought the advice of general medical practitioners prior to presentation at the hospital. Many (59%) patients have encountered media coverage but only 24% had any behavioural change as a result. Many patients relied on the recommendations of eyecare practitioners when purchasing disinfecting solutions (26%) and other hygiene practices. Pseudomonas Aeruginosa was the most common organism grown in 22.4% of patients while 47% of patients were culture-negative. Conclusion: Inadequate lens cleaning, poor aftercare, sleeping and swimming with CL were the major non-compliant behaviours among participants, and these are significant factors when assessing risks in acquiring CL-related infectious keratitis. General eyecare practitioners are the first-line of contact in patients presenting with keratitis symptoms and play an important role in emphasising the need for regular aftercare and good hygiene practices to CL wearers.

Prevalence and Causes of Patient Dropout After Glaucoma Surgery - Gupta, V; Chandra, A; Yogi, R; Sihota, R; Singh, D (OPHTHALMIC EPIDEMIOLOGY, 2013)
Purpose: To determine the prevalence of patient dropout after glaucoma surgery and reasons for the same based on patient attitudes and beliefs. Design: A hospital-based retrospective case-control study. Methods: Clinical and demographic data of patients who failed to attend follow-up within 12 months of their last scheduled appointment after glaucoma surgery were analyzed. These patients were issued recall letters and those who returned were interviewed to establish the reasons for their dropout. A structured interview was conducted to assess the educational and socioeconomic status of the patients, their knowledge and belief regarding glaucoma, their attitude towards surgery and the specific reason for their inability to follow up post-operatively. Control subjects who were regularly followed-up post-operatively were also interviewed. Results: Of 312 patients operated on from 2004-2006, only 92 (30%) patients maintained a 5-year follow-up. Of patients who dropped out, 43 patients responded to the recall letters and were interviewed along with 45 control patients. The demographic profile of those who dropped out was statistically similar to the controls; however, the controls had a significantly better awareness of glaucoma and higher monthly income (p < 0.001 and p = 0.01, respectively). Among those who dropped out, 38 (88%) believed surgery was the cure to the disease in comparison to 12 (46%) controls (p < 0.001). Conclusions: Dropout after glaucoma surgery is high among patients from lower socioeconomic strata. Misconceptions regarding surgery as a cure to glaucoma and situational factors are the most common reasons for patient dropout in this population.

Shared Care in Monitoring Stable Glaucoma Patients: A Randomized Controlled Trial - Holtzer-Goor, KM; van Vliet, EJ; van Sprundel, E; Plochg, T; Koopmanschap, MA; Klazinga, NS; Lemij, HG (JOURNAL OF GLAUCOMA, 2016)
Purpose: Comparing the quality of care provided by a hospital-based shared care glaucoma follow-up unit with care as usual. Patients and Methods: This randomized controlled trial included stable glaucoma patients and patients at risk for developing glaucoma. Patients in the Usual Care group (n = 410) were seen by glaucoma specialists. In the glaucoma follow-up unit group (n = 405), patients visited the glaucoma follow-up unit twice followed by a visit to a glaucoma specialist. The main outcome measures were: compliance to the working protocol by glaucoma follow-up unit employees; difference in intraocular pressure between baseline and at >= 18 months; and patient satisfaction. Results: Glaucoma follow-up unit employees closely adhered to the working protocol for the measurement of intraocular pressure, visual acuity and GDx (>= 97.5% of all visits). Humphrey Field Analyzer examinations were not performed as frequently as prescribed by the working protocol, but more often than in the Usual Care group. In a small minority of patients that required back-referral, the protocol was disregarded, notably when criteria were only slightly exceeded. There was no statistically significant difference in changes in intraocular pressure between the 2 treatment groups (P = 0.854). Patients were slightly more satisfied with the glaucoma follow-up unit employees than with the glaucoma specialists (scores: 8.56 vs. 8.40; P = 0.006). Conclusions: In general, the hospital-based shared care glaucoma follow-up closely observed its working protocol and patients preferred it slightly over the usual care provided by medical doctors. The glaucoma follow-up unit operated satisfactorily and might serve as a model for shared care strategies elsewhere.

Clinical characteristics and outcomes of patients admitted with presumed microbial keratitis to a tertiary medical center in Israel - Lavinsky, F; Avni-Zauberman, N; Barequet, IS (ARQUIVOS BRASILEIROS DE OFTALMOLOGIA, 2013)
Purposes: Microbial keratitis is commonly diagnosed worldwide, and continues to cause significant ocular morbidity, requiring prompt and appropriate treatment. The objective of this study is to describe the clinical characteristics and outcomes of patients with presumed microbial keratitis admitted to The Goldschleger Eye Institute, Sheba Medical Center, Tel Aviv University, Tel Hashomer, Israel. Methods: A cross-sectional study was conducted, in which the medical records of patients with presumed microbial keratitis admitted during a period of 3 years were reviewed. Results: Keratitis was diagnosed in 276 patients (51% males and 48.9% females). The mean age was 39.29 +/- 22.30 years. The hospital length of stay ranged from 1 to 65 days (mean 5.69 +/- 5.508). Fortified antibiotics were still used at discharge in 72% of the cases. Overall visual acuity improved significantly from the time of admission to the 1st-week follow up visit showing a p<0.001 on the Wilcoxon signed ranks test. Contact lens wearing was present in 36.1% of the patients, although there was no significant relation with severity of the presentation and visual outcome (p>0.05). The degree of hypopyon and cells in the anterior chamber was significantly related to the hospital length of stay (r Spearman=0.31; p<0.001 and r Spearman=0.21; p<.001, respectively) as well as to a worse visual outcome (r Spearman=0.32; p<0.01 and r Spearman=0.18; p=0.01, respectively). Of all patients, 2.3% required an urgent therapeutic penetrating keratoplasty, and 1% underwent evisceration. There was no enucleation. Conclusion: Treating keratitis aggressively and assuring patient compliance is imperative for a good final visual outcome. Inpatient treatment may have a positive impact on this outcome.

Barriers to Receiving Follow-Up Eye Care and Detection of Non-Glaucomatous Ocular Pathology in the Philadelphia Glaucoma Detection and Treatment Project - Zheng, CX; Hu, WD; Tran, J; Siam, L; Berardi, GG; Sembhi, H; Hark, LA; Katz, LJ; Waisbourd, M (JOURNAL OF COMMUNITY HEALTH, 2016)
This cross-sectional study aimed to evaluate adherence rates and identify barriers to receiving follow-up eye care in participants diagnosed with significant non-glaucomatous eye pathology in the Philadelphia Glaucoma Detection and Treatment Project. This community-based project aimed to improve detection, management, treatment, and follow-up eye care of individuals at high risk for glaucoma in community-based settings. Participants throughout Philadelphia, Pennsylvania, USA were enrolled. After a comprehensive eye examination, follow-up recommendations were given to each participant. A telephone survey was administered to individuals diagnosed with non-glaucomatous ocular pathology 3 months after initial eye examination to assess rates of follow-up and to evaluate potential barriers to follow-up. Of the 1649 participants enrolled in this project, 249 (15 %) were diagnosed with significant non-glaucomatous ocular pathology requiring follow-up care. There were 143 (57 %) who responded to the telephone survey. Respondents had a median age of 72 years, and were predominately female (69 %) and African-American (64 %). Of the respondents, 36 (25 %) attended a follow-up appointment. Participants who did not remember the results of their examinations, did not remember their recommendations, and had not seen an eye doctor within the past year were less likely to make a follow-up appointment (P = 0.04, 0.001 and 0.005, respectively). The Philadelphia Glaucoma Detection and Treatment Program was able to detect a significant amount of non-glaucomatous ocular pathology requiring follow-up care. Actual follow-up rates were sub-optimal. Further research is needed to determine interventions to overcome barriers and increase adherence with follow-up recommendations.

A Randomized, Controlled Trial to Test the Effectiveness of Patient Navigation in a Community versus Office-Based Setting to Improve Follow-up Appointment Adherence in Patients with Glaucoma - Zeng, L; Waisbourd, M; Dai, Y; Johnson, DM; Patel, N; Molineaux, J; Divers, M; Burns, C; Spaeth, GL; Katz, LL (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2016)

The Effect of Eye Drop Technique Education in Patients With Glaucoma - Carpenter, DM; Sayner, R; Blalock, SJ; Muir, KW; Hartnett, ME; Lawrence, SD; Giangiacomo, AL; Goldsmith, JA; Tudor, GE; Robin, AL; Sleath, BL (HEALTH COMMUNICATION, 2016)
Education about how to administer eye drops may improve a patient's ability to instill his or her eye drops correctly. Our objectives were to (a) document the methods providers use to educate glaucoma patients about eye drop technique; (b) determine whether eye drop technique education varies by provider and patient characteristics; and (c) evaluate whether education predicts improved patient technique. We conducted an 8-month longitudinal study of 279 glaucoma patients and 15 providers in which we recorded on videotape the content of glaucoma office visits at two time points (baseline and 4- to 6-week follow-up) and videotaped patient eye drop technique at three time points (baseline, 4- to 6-week follow-up, and 8-month follow-up). Mann-Whitney rank sum tests were used to determine whether education was associated with improved patient eye drop technique over time. Ninety-four patients (34%) received technique education at either visit; 31% received verbal education and 10% received a technique demonstration. Only 24 patients (47%) who were new to eye drops received technique education at the baseline visit. Patients who were new to drops at baseline (p = .008) and patients who asked a question about drops (p < .001) were more likely to receive technique education. Education was not associated with improved technique. Eye drop technique education occurs infrequently during glaucoma office visits. Future studies should compare the effectiveness of different educational methods, such as patient demonstration versus provider verbal instruction, to determine which method is best at improving patient eye drop technique.

Analysis of Factors Affecting Patients' Compliance to Topical Antiglaucoma Medications in Egypt as a Developing Country Model - Abu Hussein, NB; Eissa, I; Abdel-Kader, AA (JOURNAL OF OPHTHALMOLOGY, 2015)
Purpose. To study factors affecting patients' compliance to antiglaucoma medications in Egypt where there are unique factors as a developing country. Patients and Methods. A cross-sectional descriptive study on 440 Egyptian patients with open angle glaucoma (OAG) recruited for over two years. The patients were thoroughly interviewed about their age, education level, duration of glaucoma, difficulty in instilling the drops, medication regimens, a family history of glaucoma, knowledge of the disease, and the presence of medical insurance. Results. 236 (53.6%) were noncompliant compared to 204 (46.4%) who were compliant. Females had a tendency for higher compliance (P = 0.061). Patient age above 50 years and low level of education and negative family history of glaucoma were factors significantly associated with poor compliance (P < 0.0001). Polytherapy and lack of medical insurance could be contributing factors. Conclusion. Egyptian patients have a high rate of noncompliance compared to the average in literature. Great effort is needed in educating patients about the importance of medications and the risk and the prognosis of this disease. Economic factors must also be taken into consideration in developing countries with large number of poor patients. We recommend simplifying drug regimens, incorporating electronic dose monitors, and creating reminders for follow-up visits of glaucoma patients.

Effectiveness of a Short Message Reminder in Increasing Compliance with Pediatric Cataract Treatment A Randomized Trial - Lin, HT; Chen, WR; Luo, LX; Congdon, N; Zhang, XY; Zhong, XJ; Liu, ZC; Chen, W; Wu, CR; Zheng, DY; Deng, DM; Ye, SB; et al. (OPHTHALMOLOGY, 2012)
Objective: Regular follow-up is essential to successful management of childhood cataract. We sought to assess whether a mobile phone short message service (SMS) for parents of children with cataract could improve follow-up adherence and the proportion of procedures performed in timely fashion. Design: Randomized, controlled trial. This trial is registered with ClinicalTrials.gov, NCT01417819. Participants: We included 258 parent-child pairs involved in the Childhood Cataract Program of the Chinese Ministry of Health. Methods: Participants were randomized (1: 1) to a mobile phone SMS intervention or standard follow-up appointments. All participants were scheduled to attend >4 follow-up appointments according to the protocol. Parents in the intervention group received SMS automated reminders before scheduled appointments. The control group parents did not receive SMSs or any alternative reminder of scheduled appointments. Regular ocular examinations and analyses were performed by investigators masked to group allocation; however, study participants and the manager in charge of randomization and sending SMSs were not masked. Main Outcome Measures: Number of follow-up appointments attended, additional surgeries, laser treatments, changes in eyeglasses prescription, and occurrence of secondary ocular hypertension. Results: Among parent-child participants, 135 were randomly assigned to the SMS intervention and 123 to standard appointments. Attendance rates for the SMS group (first visit, 97.8%; second, 91.9%; third, 92.6%; fourth, 83%) were significantly higher than those for the control group (first visit, 87.8%; second, 69.9%; third, 56.9%; fourth, 33.3%). The increase in attendance rate for total number of follow-up visits with SMS reminders was 47.2% (relative risk [RR] for attendance, 1.47; 95% confidence interval [CI], 1.16-1.78; P = 0.003). The number needed to remind (NNR) to gain 1 additional visit by 1 child was 3 (95% CI, 1.8-4.2). A total of 247 clinical interventions were carried out in the SMS group and 134 in the control group (RR, 1.68; 95% CI, 1.37-1.99; P = 0.007). The NNR to result in 1 additional clinical intervention was 5 (95% CI, 3.5-6.5). Conclusions: The SMS reminders significantly improved follow-up adherence in pediatric cataract treatment. Using readily available mobile phone resources may be an effective and economic strategy to improve management of childhood cataract in China. Financial Disclosure(s): The authors have no proprietary or commercial interest in any of the materials discussed in this article. Ophthalmology 2012;119:2463-2470 (C) 2012 by the American Academy of Ophthalmology.

Wound or suture insufficiency complicating penetrating keratoplasty - Nolle, B; Halene, MA; Grutters, G; Duncker, GIW (OPHTHALMOLOGE, 2000)
Background:With regard to penetrating keratoplasty methods to culture corneal donor tissues, microsurgical techniques, HLA typing and understanding of basic mechanisms in inflammation and especially graft rejection,and postoperative treatment schedules have been improved in recent years. This now enables successful penetrating keratoplasty in many more patients than previously performed. However, in rare cases relevant problems in wound closure may appear. Patients and methods:A standardized treatment protocol was applied to 1,253 penetrating keratoplasties performed in a single center. Patients were continously followed up. Simple leakage after corneal grafting was not further analyzed if conservative treatment or additional sutures achieved sufficient wound closure. In 21 cases, however, the causes of large wound dehiscence after corneal grafting were analyzed. Results: During the first week early problems in suturing penetrating keratoplasty in five patients were associated with the instability of the recipients' cornea I stroma (stromal thinning in keratoconus or corneal herpes, suture problems in keratomalacia,active herpes keratitis, corneal burns, or rheumatic diseases). Long-term complications in 16 patients were associated with alcoholism, herpes keratitis, rheumatic disorders or traumatic suture defects. Overall, nine patients lost functionally or even anatomically one eye because of wound dehiscence after corneal grafting. Conclusions: When penetrating keratoplasty is indicated,special attention should be given to (1) the compliance of the patient, (2) sufficient treatment of herpes keratitis or other infections, (3) adequate immunosuppression in autoimmune corneal inflammation,(4) double running continuous sutures as primary suture with sometimes additonal single sutures to stabilize the graft, and (5) surgery in time.

A review of 145234 ophthalmic patient episodes lost to follow-up - Davis, A; Baldwin, A; Hingorani, M; Dwyer, A; Flanagan, D (EYE, 2017)
Purpose Lost to follow-up and delays in follow-up care are a major problem in chronic diseases, particularly when irreversible progression precedes symptoms. The NPSA Glaucoma Safety Alert in 2009 highlighted the risk and requirements for consistent robust review systems in ophthalmology. In response, Moorfields Eye Hospital reviewed the records of all patients in all subspecialties without review appointments booked. The purpose of this study was to determine whether ophthalmic patients lost to follow-up had come to harm and develop investigation techniques to optimise safety, which do not put excessive demands on clinical staff time. Methods The health records of all patients lost to follow-up (LTFU) between July 2007 and November 2012 were reviewed for evidence of clinical harm using a risk-based strategy involving an initial administrative review, then a clinician led electronic patient record review, followed by a review of paper records by clinicians. The final stage was a clinical outpatient review where required determined by clinical risk. Results Patients identified as lost to follow-up were 145 234; 79 562 episodes were closed following administrative review; 50 519 were discharged following clinician examination of paper records; 12 316 patients required clinical review; and 16 serious incidents were identified, of which 14 patients had glaucoma, 1 a medical retinal condition with secondary glaucoma, and 1 an oculoplastic condition. A number of actions implemented hospital wide are described which minimise future risk. Conclusion Risk from delays or lost to follow-up care continue and require better capacity and more accurate data nationally.

Analysis of Patient-Reported Barriers to Diabetic Retinopathy Follow-Up - Lu, AJ; Chen, AJ; Hwang, V; Law, PY; Stewart, JM; Chao, DL (OPHTHALMIC SURGERY LASERS & IMAGING RETINA, 2019)
BACKGROUND AND OBJECTIVES: Close follow-up of diabetic retinopathy (DR) has been linked to improved visual outcomes. This study elucidates patient-identified barriers to DR follow-up in a diverse urban clinic population. PATIENTS AND METHODS: Patients 18 years of age or older with DR or macular edema were interviewed using a 21-question survey on attitudes and barriers toward care. Univariate and multivariate logistic analysis identified barriers associated with noncompliance to follow-up. RESULTS: Two hundred nine patients participated with mean age of 58.2 years and hemoglobin A1c of 8.5%. The most common barriers cited were long waiting times (46.4%), other medical conditions (35.9%), forgetting (28.2%), and inability to leave work (9.1%). In a multivariate analysis, forgetting (odds ratio [OR]: 4.35) and other medical conditions (OR: 1.91) were barriers independently associated with non-compliance. Having proliferative DR was associated with other medical conditions in univariate (OR: 4.60) and multivariate analysis (OR: 4.35). CONCLUSION: Patients with DR who report other medical conditions or forgetting have a higher risk of non-compliance to follow-up.

Acceptability, adherence and economic analyses of a new clinical pathway for the identification of non-responders to glaucoma eye drops: a prospective observational study - Waterman, H; Read, S; Morgan, JE; Gillespie, D; Nollett, C; Allen, D; Weiss, M; Anderson, P (BRITISH JOURNAL OF OPHTHALMOLOGY, 2020)
Background/aims Assess whether a new clinical pathway for glaucoma was acceptable to patients and healthcare professionals and whether it provided useful clinical information on non-responsiveness and non-adherence to the treatment of elevated intraocular pressure with latanoprost eye drops. Methods A single arm non-randomised prospective observational study incorporating new glaucoma/ocular hypertension patients. To assess issues of acceptability, qualitative observation and interviews were conducted with patients and healthcare professionals. To determine clinical responsiveness, intraocular pressures were measured before and 4 hours after a clinician-instilled eye drop over two distinct appointments. Adherence data were collected using a Medicine Event Monitoring System. Economic analyses compared the costs between novel and standard care pathways. Results Of 72 patients approached, 53 entered the study (74.3%) and 50 completed all procedures (94.3%). Intraocular pressure was reduced more than 15% in 83 out of 92 study eyes by final visit (90.2%). The non-response rate was 5.1% once the effect of low adherence was minimised. For the 1376 drop instillation days under observation, eye drops were instilled as prescribed on 1004 days (73.0%), over-instilled on 137 days (9.9%) and not instilled on 235 days (17.1%). The Cardiff Model of Glaucoma Care involved negligible cost, although acceptance for healthcare professionals showed variation. Conclusions The Cardiff Model of Glaucoma Care offers novel clinical and adherence insights at marginal costs while acceptable to patients. Healthcare professionals felt that 4 hour and 4 week follow-up appointments could cause administrative problems. A streamlined version of the pathway has therefore been developed to facilitate clinical adoption.

Assessment of the impact of medPlan (R), a medication reminder mobile application, in glaucoma patients in Benin City, Nigeria - Osahon, PT; Mote, LA; Ntaji, VI (TROPICAL JOURNAL OF PHARMACEUTICAL RESEARCH, 2020)
Purpose: To assess the impact of medPlan (R), a medication reminder mobile application in glaucoma patients in Benin City, Nigeria. Methods: In a randomized control trial with 2 months follow-up period, 200 patients receiving drug therapy for glaucoma were randomized into either into a control or study group. The study group comprised participants who made use of a medication reminder mobile application, medPlan (R), while the control group consisted of those patients who did not use the application. Adherence to medication was measured for all the patients in both groups. Data was collected using a carefully designed questionnaire and statistically analyzed. Results: This study recorded 100 % response rate from the participants. In the study group, 56 % were very adherent while 18 % were moderately adherent, and 26 % were non-adherent respondents as against 45 % very adherent, 13 % moderately adherent and 42 % non-adherent respondents from the control group. In addition, 78 % of those in the study group agreed that there was improvement in their medication adherence since they started using the medication reminder application. This showed a significant positive impact of the medication reminder application (p = 0.0110) on adherence to medication. Conclusion: Medication adherence was improved in glaucoma patients who used medPlan (R), a smartphone medication reminder application. This study lays a foundation for further research on medication reminder mobile applications.

Predictors of and barriers associated with poor follow-up in patients with glaucoma in South India - Lee, BW; Sathyam, P; John, RK; Singh, K; Robin, AL (ARCHIVES OF OPHTHALMOLOGY, 2008)
Objectives: To determine predictors of and reasons for poor longitudinal glaucoma follow-up in South India. Methods: This 1-to-1, matched, case-control study enrolled 300 patients with established glaucoma. We defined cases (poor follow-up) and controls (good follow-up) based on number of and maximum interval between glaucoma follow-up Visits attended in the preceding year. We collected data by oral questionnaire and used step-wise multivariate logistic regression to calculate odds ratios (ORs) for poor follow-up. Results: Adjusting for age and sex, independent predictors of poor follow-up included lack of formal education (adjusted OR, 4.13; 95% confidence interval [CI], 1.44-11.90), no use of prescribed glaucoma medications (adjusted OR, 2.17; 95% CI, 1.06-4.43), and belief that follow-up is less important if one uses glaucoma medications and has no noticeable visual changes (adjusted OR, 10-59; 95% CI, 3.74-29.97). Age, sex, and disease severity were not significant predictors. The most prevalent barriers to follow-up were belief that there was no problem with one's eyes (44.4%) and lack of escort (19.7%). Conclusions: Knowing predictors of poor follow-up can help identify patients who need individualized strategies to improve follow-up. Because believing one's eyes are problem-free and lacking escorts are significant barriers to follow-up, novel strategies in patient education (eg, intensive counseling, audiovisual aides, and patient support groups) and escort provision may improve longitudinal glaucoma follow-tip and disease management.

Delayed follow-up in patients with diabetic retinopathy in South India: Social factors and impact on disease progression - Vengadesan, N; Ahmad, M; Sindal, MD; Sengupta, S (INDIAN JOURNAL OF OPHTHALMOLOGY, 2017)
Purpose: To identify social factors associated with delayed follow-up in South Indian patients with diabetic retinopathy (DR) and to study DR progression during the delayed follow-up period. Materials and Methods: In this cross-sectional study, 500 consecutive patients with DR returning after greater than twice the advised follow-up period were identified from a tertiary referral center in South India. A previously validated 19-item questionnaire was administered to study patients to assess causes for the follow-up delay. Patient demographics, DR status, and treatment plan were recorded at the study visit and the visit immediately before the delay. The eye with the most severe disease was included in the analysis. Results: Complete data were available for 491 (98.2%) patients. Among these, 248 (50.5%) cited "my eyes were okay at the time," 201 (41.0%) cited "no attender to accompany me," and 190 (38.6%) cited "financial cost" as causes of the follow-up delay. Those with vision-threatening DR (VTDR, n = 233) predominantly reported " financial cost" (47% vs. 32%, P = 0.001), whereas those with non-VTDR more frequently reported " my eyes were okay at the time" (58% vs. 42%, P = 0.001). Evidence of disease progression from non-VTDR to VTDR was seen in 67 (26%) patients. Almost 1/3rd (29%) of patients who were previously advised regular examination required additional intervention. Conclusion: Many patient-level factors affect poor compliance with follow-up in DR, and these factors vary by disease severity. Targeting these barriers to care through patient education and clinic procedures may promote timely follow-up and better outcomes in these patients.

The effect of appointment rescheduling on monitoring interval and patient attendance in the glaucoma outpatient clinic - Tatham, A; Murdoch, I (EYE, 2012)
Aim To assess the effect of appointment rescheduling on monitoring intervals and patient attendance in the glaucoma clinic. Methods A retrospective review of 100 consecutive patients was conducted. Patients were categorised into groups based on risk of progressive visual loss. The monitoring interval requested by the clinician was compared with the interval recommended by national guidelines. One hundred consecutive patients who had had their appointment rescheduled were also examined to assess the effect of appointment rescheduling on the actual monitoring interval. Patient non-attendance rates and attendances at the emergency department were also examined. Results After excluding patients with secondary glaucoma, glaucoma suspects, and those with short-term factors affecting monitoring interval, 54 patients with chronic open-angle glaucoma (COAG) were included. Forty-eight (89%) of patients had a monitoring interval requested in accordance with national guidelines (2 had longer intervals by 1-2 months and 4 had shorter time intervals). The monitoring interval was not influenced by disease severity (Kruskal-Wallis test, P = 0.16), but was significantly shorter if the intraocular pressure was above target (P < 0.0001) or the patient showed structural or functional progression (P < 0.0001). Hospital-initiated appointment rescheduling led to significant lengthening of monitoring interval. The mean difference between intended and actual monitoring interval was 5.6 months. Eight percent (8/100) of patients with rescheduled appointments did not attend compared with 15% (39/265) without rescheduled appointments. Conclusion Clinical staff are selecting appropriate monitoring intervals for patients with COAG; however, hospital-initiated rescheduling of appointments is a major challenge to appropriate follow-up. Eye (2012) 26, 729-733; doi: 10.1038/eye.2012.22; published online 2 March 2012

Follow-up and adherence to glaucoma care by newly diagnosed glaucoma patients in enugu, nigeria - Kizor-Akaraiwe, NN (OPHTHALMIC EPIDEMIOLOGY, 2019)
Purpose: To determine uptake, adherence and influencing factors to follow-up care by newly diagnosed glaucoma patients from free eye screening exercise. Methods: The study was a cross-sectional survey of newly diagnosed glaucoma patients during free eye screenings carried out in March and October, 2016 in Enugu, Nigeria. Data on participants were analyzed after a minimum of 6 months from the screening for uptake and adherence to follow-up care. Qualifying patients had questionnaires administered to them by phone interview. Information requested regards awareness, knowledge on diagnosis as well as reasons for non-uptake and non-adherence. Results: 182 newly diagnosed glaucoma patients were included of which 121 (66.5%) were males, with median age of 50years.About 164 (90.1%) had at least a primary education. There were more self- employed persons 59 (32.4%) compared to other occupations. Uptake of follow up care was 17.6% (32/182). Adherence rate was 25% (8/32). Major reasons for non-uptake were lack of funds 54.9% (n = 50/91), distance 11% (n = 10/91) and receiving care from other facilities 11.0% (n = 10/91). Others include discourteous staff behavior and lack of information on diagnosis. Similarly, major reasons for non-adherence were lack of funds 44.4% (n = 8/18) and distance 22.2% (n = 4/18). Knowledge and prior awareness of glaucoma were found to be significantly associated with uptake of follow up care (p = 0.020). Conclusion: Uptake and adherence to follow-up was found to be low in this study population mainly attributed to cost, distance and poor knowledge of glaucoma natural history. Reviewing cost/out of pocket expenditure, providing care closer to patients, adequate education of staff and patients may significantly improve uptake of care after initial diagnosis.

Survey of medical treatment in primary open-angle glaucoma - Tchabi, S; Abouki, C; Sounouvou, I; Yehouessi, L; Doutetien, C; Bassabi, SK (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2011)
Purpose.-To survey patient understanding of primary open-angle glaucoma (POAG) and difficulties associated with medical treatment of POAG patients, to determine patient compliance rates with medical therapy, to study factors influencing compliance rates, and to formulate suggestions to improve patient compliance. Patients and methods.-Our descriptive prospective study was carried out at the ophthalmology clinic of the Hubert K. Maga national university medical center and in the "La Lumiere" ophthalmology clinic in Cotonou, from January 5 through April 25, 2009. The study included all glaucoma patients under medical treatment for at least 1 year with no surgical POAG intervention, seen in consultation during the study period, i.e. 120 patients. The following parameters were studied: whether the patient took or forgot to take his or her medication within the week preceding the survey, the patient's statement of whether or not voluntary interruption of anti-glaucoma treatment occurred for more than 1 day, and the regularity of follow-up appointments with the doctor over the preceding 2 years. Results.-The median age of the patients was 56.5 +/- 11.9 years. A percentage of 90.8 of patients understood the chronic nature of POAG. A percentage of 91.7 knew that, in the absence of treatment, POAG can result in irreversible blindness. A percentage of 90 knew that medical treatment is intended to be lifelong. A percentage of 84.2 knew that the dosing schedule must be adhered to. The rate of total compliance was 53.3%. Only regularity of follow-up visits and adherence to dosing schedules were found as significant factors (P < 0.05). Conclusion.-Compliance is a dynamic variable which ophthalmologists need to evaluate throughout the follow-up of POAG patients, in order to reduce the prevalence of glaucoma blindness in Benin. (C) 2011 Elsevier Masson SAS. All rights reserved.

Effect of smartphone application assisted medical service on follow-up adherence improvement in pediatric cataract patients - Chang, PJ; Lin, L; Zhang, HF; Zhao, YY; Xie, JL; Yu, YH; Zhao, YE (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2018)
To evaluate the potential of the smartphone application assisted medical service to increase patient compliance in attendance of follow-up after pediatric cataract treatment. This prospective study enrolled a total of 163 pediatric cataract patients with uneventful surgery. According to their follow-up intervention method, patients were divided into the smartphone application assisted medical service group (WeChat group, 75 patients) or control group (88 patients). Attendance at five follow-up appointments after surgery was recorded. The percentage of patients that attend each follow-up appointment and the compliance of refractive correction were assessed. Although no significant difference was observed in the first appointment comparing the two groups (98.7% vs. 94.3%, p = 0.293), the attendance rates at the other appointments of the WeChat group were significantly higher than the control group (second: 98.7% vs. 89.8%, third: 97.3% vs. 83%, fourth: 93.3% vs. 78.4%, fifth: 80% vs. 56.8%, total: 93.6% vs. 80.5%, respectively). Compared with the control group, the odd ratios for adherence improvement were 4.4 for males (95% confidence index [CI] 2.54-7.65), 4.75 for patients more than 2 years old (95% CI 2.41-9.36), 4.19 for intraocular lens implantation (2.29-7.66), 6.93 for unilateral cataract (2.9-16.52), 4.87 for undeveloped cities (2.74-8.65), and 3.49 for cities far away (2.04-5.96), with all the p < 0.0001. This study demonstrates that the use of smartphone application assisted medical service can significantly improve follow-up attendance after pediatric cataract treatment.

Clinical outcomes of patterned laser trabeculoplasty as adjuvant therapy in open angle glaucoma and ocular hypertension - Espinoza, G; Castellanos, L; Rodriguez-Una, I; Camacho, PA; Parra, JC (INTERNATIONAL JOURNAL OF OPHTHALMOLOGY, 2018)
AIM: To assess the efficacy and safety of patterned laser trabeculoplasty (PLT) as an adjunctive treatment in open angle glaucoma (OAG) or ocular hypertension (OHT) patients who were under antiglaucoma medical treatment. METHODS: This study was a retrospective review of primary or secondary OAG patients and OHT patients with medically uncontrolled (>= 18 mm Hg) intraocular pressure (IOP) who underwent 360 degrees PLT from June 2016 to August 2016. Follow-up visits at week 1, and 1, 3 and 6mo were performed. IOP, best corrected visual acuity (BCVA), complications and eye drop glaucoma medication were recorded at each follow-up visit. Success was defined as IOP reduction >= 20% from baseline. RESULTS: Forty-one eyes of 25 patients were included in this study. Pre-treatment mean IOP was 20.2 +/- 1.6 mm Hg. After PLT, IOP was 19.3 +/- 5.2, 16.1 +/- 2.7, 17.1 +/- 3.7 and 16.3 +/- 3.5 mm Hg, at 1wk, 1, 3 and 6mo, respectively. IOP reduction from baseline was statistically significant from the first month, remaining stable at 6mo (P<0.001). PLT success at 6mo of follow-up was 48.78%. The number of glaucoma medication per eye (P=0.10) and the mean BCVA both remained constant (P=0.37). Complications included transient IOP spikes in 4 eyes (9.8%) and peripheral anterior synechiae in 7 eyes (17.1%). CONCLUSION: PLT is an effective and safe method for the management of patients with OHT or OAG as an adjunctive therapy. Additional larger studies should be designed to verify the long-term stability of IOP reduction with this laser technology.

Sutureless amniotic membrane fixation using fibrin glue for ocular surface reconstruction in a rabbit model - Szurman, P; Warga, M; Grisanti, S; Roters, S; Rohrbach, JM; Aisenbrey, S; Kaczmarek, RT; Bartz-Schmidt, KU (CORNEA, 2006)
Purpose: Amniotic membrane transplantation has become an important treatment option for corneal surface reconstruction. However, suture fixation of the transplant has various disadvantages like corneal irritation, scarring, graft loss due to membrane shrinkage, and the need for subsequent Suture removal. Replacement of sutures by bioadhesives might be an advantageous alternative. This controlled study was designed to evaluate a new sutureless technique for amniotic membrane fixation onto the corneal Surface by using fibrin glue. Methods: Standardized disks of cryopreserved amniotic membranes were transplanted onto the deepithelialized cornea of 12 rabbits using either conventional Suture fixation or a new fibrin glue technique. The rabbits were followed-up with slit-lamp examination and fluorescein staining until epithelialization was completed. Consecutively, the rabbits were killed and the eyes processed for histology and immunohistochemistry for cytokeratin-3. Results: All membranes of both groups stayed in place throughout the follow-up time and showed a progressive graft epithelialization that was completed after 12 days. Whereas suture-fixated membranes showed progressive tissue shrinkage, fibrin-glued sheets remained unaltered. In the bioadhesive group, histology revealed a smooth fibrin layer in the graft-host interface and a continuous, stratified layer of cytokeratin-3 expressing corneal epithelial cells on the membrane surface. In contrast, suture-fixated membranes showed contracted and prominent membrane edges with epithelial ingrowth into the submembrane interface. Conclusion: Our results demonstrate the general feasibility of reproducible and reliable sutureless amniotic membrane fixation onto the corneal surface in rabbits. Stable adherence is maintained until epithelialization is completed. The sutureless technique gives sufficient manipulation time for the sheet before the final cross-linking process is completed. Furthermore, several advantageous characteristics could be demonstrated as increased biocompatibility, better epithelialization pattern and the lack of membrane shrinkage.

Advanced glaucoma at presentation is associated with poor follow-up among glaucoma patients attending a tertiary eye facility in Southern Nigeria - Momoh, RO; Bunce, C; Oko-oboh, GA; Gilbert, CE (OPHTHALMIC EPIDEMIOLOGY, 2018)
Purpose: Globally, particularly in Africa, poor compliance with medication is a major problem in glaucoma management but little is known about follow-up rates among African glaucoma patients. The aim of this study was to determine rates of follow-up among glaucoma patients attending a tertiary hospital in southern Nigeria and investigate predictors of poor follow-up.Methods: Data were extracted from medical records of new glaucoma patients who attended the hospital between June 2011 and May 2013. Socio-demographic and clinical parameters (visual acuity; stage of glaucoma) recorded at diagnosis were extracted using a pre-tested form. Follow-up was defined as good if they had attended within 9months of the study date, inadequate when the last follow-up was more than 9months and failed if they did not attend any follow-up or the most recent visit was more than 14months from the study date. Univariate and multivariable analyses were undertaken to explore predictors of poor follow-up (inadequate plus failed).Results: Three hundred forty-eight patients were recruited, 54% were male and the mean age was 52.7 (range 16-88) years. Follow-up was as follows: good 28.4%, inadequate 46.6%, failed 25%. Overall, 71.6% had poor follow-up. Independent predictors of poor follow-up were poorer visual acuity (OR 3.85, 95% confidence interval (CI) 1.25-11.80 for visual impairment; OR 4.11, 95% CI 1.32-12.81 for blind) and end-stage glaucoma (OR 3.55 (1.31-9.62), p=0.01).Conclusion: Enhanced counselling of patients with moderate to advanced glaucoma and visual impairment is required to improve follow-up and hence glaucoma management.

Risk factors for noncompliance with follow-up among normal-tension glaucoma suspects - Ngan, R; Lam, DL; Mudumbai, RC; Chen, PP (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2007)
PURPOSE: To evaluate noncompliance with follow-up in normal-tension glaucoma (NTG) suspects. DESIGN: Retrospective cohort study. METHODS: We reviewed 203 patient charts at a university eye clinic, identified as NTG suspects from a database of optic disk photographs. Noncompliance was defined as less than one year of follow-up and/or fewer than two completed visual field (VF) tests. RESULTS: Twenty-two patients (11%) were excluded be cause at least two VF tests were not ordered. The 181 patients analyzed included 45 (25%) non-Whites and 16 (9%) non-English speakers. Eighty-three patients (46%) were noncompliant. These patients were significantly younger (50.5 +/- 15.0 years vs 55.1 +/- 12.8 years; P =.028), were more likely to speak English (P =.023), and were more likely to have no or unknown health insurance (P < .001). CONCLUSIONS: Almost half of NTG suspects lacked appropriate follow-up. Lack of health insurance may be a significant barrier to compliance with follow-up in this population.

Communication Predicts Medication Self-Efficacy in Glaucoma Patients - Carpenter, DM; Blalock, SJ; Sayner, R; Muir, KW; Robin, AL; Hartnett, ME; Giangiacomo, AL; Tudor, GE; Sleath, BL (OPTOMETRY AND VISION SCIENCE, 2016)
Purpose Medication self-efficacy, or patients' confidence that they can perform medication-related behaviors, is associated with better glaucoma medication adherence. Little is known about how to enhance glaucoma patients' medication self-efficacy. Our purpose is to examine whether patient-provider communication increases glaucoma patients' medication self-efficacy. Methods During an 8-month cohort study of 279 glaucoma patients and 15 providers, two office visits were videotape-recorded, transcribed, and coded for six patient-provider communication behaviors. A validated scale was used at baseline and 8-month follow-up to assess patients' confidence in overcoming adherence barriers (adherence barriers self-efficacy) and carrying out tasks to use eye drops correctly (eye drop task self-efficacy). We ran two generalized estimating equations to examine whether more frequent patient-provider communication during office visits predicted increased patient adherence barriers self-efficacy and eye drop task self-efficacy at 8-month follow-up. Results For each additional topic providers educated about, patients reported an average increase of 0.35 in self-efficacy in overcoming adherence barriers (p < 0.001). Patients also reported an average increase of 1.01 points in eye drop task self-efficacy when providers asked about patients' views of glaucoma and its treatment versus not (p < 0.001). Patients who asked more medication questions (p < 0.001) and African-American patients (p < 0.05) reported lower adherence barriers self-efficacy by 0.30 and 2.15 points, respectively. Women had a 0.63 lower eye drop task self-efficacy than men (p < 0.05). Conclusions When providers educate glaucoma patients and assess patient views about glaucoma and its treatment, patients report higher medication self-efficacy. Providers should be aware that patients who ask more medication questions may have less confidence in their ability to overcome barriers to adherence.

Patterns of Glaucoma Medication Adherence over Four Years of Follow-Up - Newman-Casey, PA; Blachley, T; Lee, PP; Heisler, M; Farris, KB; Stein, JD (OPHTHALMOLOGY, 2015)
Purpose: To assess longer-term patterns of glaucoma medication adherence and identify whether patterns established during the first year of medication use persist during 3 subsequent years of follow-up. Design: Retrospective, longitudinal cohort analysis. Participants: Beneficiaries aged >= 40 years who were enrolled in a United States (US)-managed care plan for >= 7 years between 2001 and 2012 and newly diagnosed and treated for open-angle glaucoma. Methods: For each enrollee, we quantified medication adherence using the medication possession ratio. Group-based trajectory modeling (GBTM) was applied to identify patterns of adherence for 1 and 4 years of follow-up. The percent of beneficiaries who remained in the same trajectory group in the 1- and 4-year models was tabulated to evaluate group stability. Factors impacting adherence at 1 and 4 years were identified using regression analyses. Main Outcome Measures: Patterns of glaucoma medication adherence. Results: Of the 1234 eligible beneficiaries, GBTM identified 5 distinct glaucoma medication adherence patterns in both the 1-year and 4-year follow-up periods. These groups were as follows: (1) never adherent after their index prescription fill (7.5% and 15.6% of persons in the 1- and 4-year models, respectively); (2) persistently very poor adherence (14.9% and 23.4% of persons in the 1- and 4-year models, respectively); (3) declining adherence (9.5% and 9.1% of persons in the 1- and 4-year models, respectively); (4) persistently moderate adherence (48.1% and 37.0% of persons in the 1- and 4-year models, respectively); and (5) persistently good adherence (20.0% and 15.0% of persons in the 1- and 4-year models, respectively). More than 90% of beneficiaries in the 4 groups with the worst and best adherence patterns (groups 1, 2, 3, 5) maintained their patterns from their first year throughout their 4 years of follow-up. Those with persistently moderate adherence (group 4), the largest group, were most likely to change groups from 1 to 4 years of follow-up. Persons with the best adherence over 4 years were more likely to be white, to be older, to earn >$60 000/year, and to have more eye care visits (P < 0.05 for all comparisons). Those with a higher initial copayment cost had lower adherence rates (beta = -0.06/dollar, P = 0.03). Conclusions: For most patients who were newly prescribed glaucoma medications, adherence patterns observed in the first year of treatment reflect adherence patterns over the subsequent 3 years. Investing resources in both identifying and helping patients with suboptimal adherence patterns over the first year may have a large impact on longer-term adherence. (C) 2015 by the American Academy of Ophthalmology.

Philadelphia Telemedicine Glaucoma Detection and Follow-up Study: Methods and Screening Results - Hark, LA; Katz, LJ; Myers, JS; Waisbourd, M; Johnson, D; Pizzi, LT; Leiby, BE; Fudemberg, SJ; Mantravadi, AV; Henderer, JD; Zhan, TT; Molineaux, J; et al. (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2017)
PURPOSE: To describe methodology and screening results from the Philadelphia Telemedicine Glaucoma Detection and Follow-up Study. DESIGN: Screening program results for a prospective randomized clinical trial. METHODS: Individuals were recruited who were African-American, Hispanic/Latino, or Asian over age 40 years; white individuals over age 65 years; and any ethnicity over age 40 years with a family history of glaucoma or diabetes. Primary care offices and Federally Qualified Health Centers were used for telemedicine (Visit 1). Two posterior fundus photographs and 1 anterior segment photograph were captured per eye in each participant, using a nonmydriatic, autofocus, hand-held fundus camera (Volk Optical, Mentor, Ohio, USA). Medical and ocular history, family history of glaucoma, visual acuity, and intraocular pressure measurements using the ICare rebound tonometer (ICare, Helsinki, Finland) were obtained. Images were read remotely by a trained retina reader and a glaucoma specialist. RESULTS: From April 1, 2015, to February 6, 2017, 906 individuals consented and attended Visit 1. Of these, 553 participants were female (61.0%) and 550 were African-American (60.7%), with a mean age of 58.7 years. A total of 532 (58.7%) participants had diabetes, and 616 (68%) had a history of hypertension. During Visit 1, 356 (39.3%) participants were graded with a normal image. Using image data from the worse eye, 333 (36.8%) were abnormal and 155 (17.1%) were unreadable. A total of 258 (28.5%) had a suspicious nerve, 62 (6.8%) had ocular hypertension, 102 (11.3%) had diabetic retinopathy, and 68 (7.5%) had other retinal abnormalities. CONCLUSION: An integrated telemedicine screening intervention in primary care offices and Federally Qualified Health Centers detected high rate of suspicious optic nerves, ocular hypertension, and retinal pathology. (C) 2017 Elsevier Inc. All rights reserved.

Microbial flora of tears of orthokeratology patients, and microbial contamination of contact lenses and contact lens accessories - Boost, MV; Cho, P (OPTOMETRY AND VISION SCIENCE, 2005)
(ortho-k) patients, and the levels of contamination of their lenses and lens accessories, and to correlate compliance with levels of contamination. Method Normal ocular flora of 41 subjects was determined twice before commencing ortho-k lens wear by culture of the lower conjunctiva. Further specimens were collected on six follow-up visits after beginning lens wear, as were samples from their lenses, cases, and suction holders. A questionnaire on lens care was administered after the fifth visit. Results. Three subjects provided conjunctival samples yielding Staphylococcus aureus on one occasion before lens wear, one being positive for this organism after beginning lens wear. Of 38 subjects yielding no growth or only normal eye flora before use, 28 remained free of ocular pathogens after beginning lens wear. Only four subjects had positive cultures on more than one occasion after lens wear. There was no significant difference in isolation levels of pathogens with lens wear (p = 0.423). Lens culture of 54% of subjects yielded no growth or normal flora only; lenses of 16 subjects yielded potential pathogens, including three subjects contaminated on more than one occasion. Lens isolates did not match the organisms transiently colonizing the eye. Lens case, the most frequently contaminated item, was associated with lens contamination (p < 0.001), the same organism being isolated from both items in 11 subjects. Lens suction holder was less frequently contaminated. Neither lens case nor suction holder contamination was associated with isolates from the eye. Reported good compliance correlated with lack of contamination in all but one subject. The most frequent breaches in the lens care protocol were failure to clean, disinfect, and replace the lens case. Conclusion. Ocular flora was not altered by ortho-k lens wear over an extended period, and patients remained free of infection. Contaminants identified were generally of a transient nature. Most patients had significant contamination of at least one item, most frequently the lens case. Lens case isolates were significantly associated with those from the lens. The majority of patients reporting good compliance had low or no contamination of their lenses and accessories.

A novel EyePhone (c) App for improving adherence to glaucoma therapy - Leshno, A; Gaton, D; Singer, R; Eliasi, E; Vorobichik-Berar, O; Madgar, S; Stern, O; Jaber, W; Kapelushnik, N; Skaat, A (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2021)
Purpose Despite advances in glaucoma treatment options, patient adherence and compliance remain very low. The EyePhone (c) App is a free non-commercial reminder application designed specifically for the needs of glaucoma patients. In this study, we evaluated its usefulness in improving adherence to medical treatment among glaucoma patients. Methods This is a prospective multicenter interventional study. Glaucoma patients were recruited from a tertiary center and a large community glaucoma service center. After a short explanation, the EyePhone (c) App was installed on their smartphone device, and the notifications for the current medical treatment were entered. After enrollment and at 1-month follow-up, subjects completed the Morisky Medication Adherence Scale (MMAS-8) and the Quality of Life and Glaucoma 17-item (GlauQOL-17) questionnaires for evaluation of adherence and QOL, respectively. Results In the study, 133 patients (71 men and 62 women) aged 62 +/- 15.5 years and using 2.0 +/- 0.9 IOP-lowering drugs participated. The proportion of highly adherent subjects improved from 29.3% (39/133) at baseline to 42.1% (56/133) at follow-up (P < 0.001), and the proportion of poorly adherent subjects decreased from 29.3 (39/133) to 20.3% (27/133) at follow-up (P = 0.012). QOL also improved, as evidenced by a significant increase in the GlauQOL-17 score (P < 0.05). In a subgroup of patients for whom IOP measurements were available, IOP reduced by 0.92 mmHg (P = 0.069). Conclusions Significant improvements in glaucoma adherence and QOL were achieved among poorly adherent glaucoma patients after 1 month of using the EyePhone (c) App.

Compliance and barriers for follow-up care in community eye screening: the SToP Glaucoma Study - Zhao, D; Guallar, E; Swenor, BK; Gajwani, P; Mude, L; Friedman, DS (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2016)

Resident Compliance with the American Academy of Ophthalmology Preferred Practice Pattern Guidelines for Primary Open-Angle Glaucoma - Ong, SS; Sanka, K; Mettu, PS; Brosnan, TM; Stinnett, SS; Lee, PP; Challa, P (OPHTHALMOLOGY, 2013)
Purpose: To examine resident adherence to preferred practice pattern (PPP) guidelines set up by the American Academy of Ophthalmology for follow-up care of primary open-angle glaucoma (POAG) patients. Design: Retrospective chart review. Participants: One hundred three charts were selected for analysis from all patients with an International Classification of Diseases, Ninth Revision, code of open-angle glaucoma or its related entities who underwent a follow-up evaluation between July 2, 2003, and December 15, 2004, at the resident ophthalmology clinic in the Durham Veteran Affairs Medical Center. Methods: Follow-up visits of POAG patients were evaluated for documentation of 19 elements in accordance to PPP guidelines. Main Outcome Measures: Compliance rates for the 19 elements of PPP guidelines first were averaged in all charts, and then were averaged per resident and were compared among 8 residents between their first and second years of residency. Results: The overall mean compliance rate for all 19 elements was 82.6% for all charts (n = 103), 78.8% for first-year residents, and 81.7% for second-year residents. The increase from first to second year of residency was not significant (P>0.05). Documentation rates were high (>90%) for 14 elements, including all components of the physical examination and follow-up as well as most components of the examination history and management plan. Residents documented adjusting target intraocular pressure downward, local or systemic problems with medications, and impact of visual function on daily living approximately 50% to 80% of the time. Documentation rates for components of patient education were the lowest, between 5% and 16% in all charts. Conclusions: Residents' compliance with PPP guidelines for a POAG follow-up visit was very high for most elements, but documentation rates for components of patient education were poor. Adherence rates to PPP guidelines can be used as a tool to evaluate and improve resident performance during training. However, further studies are needed to establish the advantages of using PPP guidelines for resident education and to determine if such assessments can lead to improved patient care. (C) 2013 by the American Academy of Ophthalmology.

Overcoming Barriers to Eye Care: Patient Response to a Medical Social Worker in a Glaucoma Service - Fudemberg, SJ; Amarasekera, DC; Silverstein, MH; Linder, KM; Heffner, P; Hark, LA; Waisbourd, M (JOURNAL OF COMMUNITY HEALTH, 2016)
This paper investigates the patient response to a medical social worker in a glaucoma clinic. The literature suggests that medical social workers are effective in a variety of health care settings, yet the efficacy of a medical social worker in an adult ophthalmic setting has not been studied. We present the results of a retrospective chart review of 50 patients with glaucoma referred to a medical social worker between January 5, 2015 and June 31, 2015 in an outpatient clinic of an urban eye hospital. Clinical and demographic data, as well as the data from a quality of care questionnaire, were collected for each patient. Patients rated their interaction with the medical social worker as highly positive (mean = 4.75, 5-point Likert scale), and nearly 90 % of patients expressed interest in future contact with the social worker. Additionally, most patients reported that the social worker resolved the issues they were facing (61.1 %), supported them in seeing their ophthalmologist (70.6 %), and helped them to manage their glaucoma (69.7 %). Reported barriers to glaucoma care were emotional distress; cost of office visits and medications; lack of medical insurance; transportation; poor medication adherence; impairment of daily activities; follow-up adherence; and language. As vision loss from glaucoma is irreversible, it is important to detect and treat patients at early stages of the disease. Therefore, it is imperative for patients to regularly visit their eye care providers and adhere to treatment and follow-up recommendations. This study suggests that a medical social worker could play a pivotal role in helping patients with glaucoma overcome barriers to treatment and facilitate disease management.

Determinants of Self-Reported Barriers to Glaucoma Medicine Administration and Adherence: A Multisite Study - Sleath, BL; Blalock, SJ; Muir, KW; Carpenter, DM; Lawrence, SD; Giangiacomo, AL; Goldsmith, JA; Hartnett, ME; Slota, C; Robin, AL (ANNALS OF PHARMACOTHERAPY, 2014)
Background: Many factors influence glaucoma medication adherence. A better understanding of the relationships between health literacy, depressive symptoms, and patient-reported problems in using glaucoma medications may reveal opportunities for intervention that could improve patients' clinical outcomes. Objective: To examine the relationship between patient characteristics (demographics, health literacy, and depressive symptoms) and patient-reported problems in using glaucoma medications and to assess factors related to patients' self-reported adherence to glaucoma medications. Methods: Patients diagnosed with primary open-angle glaucoma (n = 228) currently taking intraocular pressure lowering medications were recruited at 6 ophthalmology clinics. Patients were interviewed to identify problems using glaucoma medications, and self-reported medication adherence was determined using a Visual Analog Scale. Questionnaires were administered to assess health literacy, depressive symptoms, outcome expectations, and medication self-efficacy. Results: Younger patients (P = 0.03), patients with depressive symptoms (P = 0.02), and patients who reported more medication problems (P = 0.005) were significantly less adherent to their glaucoma medications. Patients with higher glaucoma medication self-efficacy adherence scores (P = 0.003) and higher outcome expectations (P = 0.03) were significantly more adherent. Conclusions: Providers should consider using tools to screen glaucoma patients for depressive symptoms and for problems in using medications to identify patients who are at higher risk of nonadherence to treatment and who might benefit from follow-up with primary care providers.

Relationship between electronically measured medication adherence and vision-related quality of life in a cohort of patients with open-angle glaucoma - Thompson, AC; Woolson, S; Olsen, MK; Danus, S; Bosworth, HB; Muir, KW (BMJ OPEN OPHTHALMOLOGY, 2018)
Objective To investigate whether electronically measured medication adherence is associated with vision-related quality of life (VRQoL) in patients with open-angle glaucoma. Methods and analysis This is a 3-year prospective cohort study of 79 subjects with open-angle glaucoma at a Veterans Affairs medical centre. Participants returned a medication event monitoring system (MEMS) for their glaucoma eye-drops and had at least two visits with glaucoma during the study period. Those taking less than 80% of prescribed glaucoma medication doses were considered to be non-adherent. Subjects were interviewed using the National Eye Institute's Visual Function Results Thirty per cent (n=24/79) of participants took less than 80% of prescribed doses of their glaucoma medications at baseline. Patients who did not adhere to their medications at baseline had lower mean composite VFQ-25 scores at baseline (70.66 +/- 20.50 vs 75.91 +/- 19.12, standardised mean difference=0.27) and after 3 years (71.68 +/- 21.93 vs 76.25 +/- 21.67, standardised mean difference=0.21). Visual acuity (P=0.03), but not visual field severity (P=0.13) or medication adherence (P=0.30), was significantly associated with composite VFQ-25 score in an adjusted model. Conclusions Subjects who were non-adherent to their glaucoma medications at baseline as assessed by a MEMS device reported lower VRQoL than adherent subjects at baseline and after 3 years. However, visual acuity was significantly associated with VRQoL. Future studies should assess whether improved adherence to eye-drops impacts VRQoL in patients with glaucoma.

Compliance to topical anti-glaucoma medication among glaucoma patients at Menelik II Tertiary Hospital, Addis Ababa, Ethiopia - Tadesse, F; Mulugeta, A (ETHIOPIAN JOURNAL OF HEALTH DEVELOPMENT, 2015)
Background: Glaucoma is one of the major public health problems. Lowering intraocular pressure has been shown to inhibit the progression of glaucomatous optic nerve damage which depends on compliance with the treatment. Objectives: To determine the extent of noncompliance to treatment among glaucoma patients at Menelik II Hospital. Methods: A hospital based cross sectional study was conducted on patients who were on topical anti glaucoma treatment and follow-up at glaucoma clinic, Menelik Hospital during May 1 to July 30, 2014. Four hundred one eligible patients were interviewed with a pretested structured questionnaire by the principal investigator. Medical charts of each patient were reviewed for specific information like type of previous procedures and visual acuity. Results: Among the 401 patients interviewed, 230 patients (57.4%) were found to be noncompliant. Younger ages, higher educational level, previous history of procedures for glaucoma were associated with better compliance. Factors associated with noncompliance included poor vision, more than one drug therapy, fair or poor understanding of the disease, use of other systemic medications, unavailability of drugs in the market, dependency on others for instilling the drops. Sex, side effects of the drugs, number of years with glaucoma and family history were not found to be predictors of noncompliance. The main reasons given by the participants were forgetfulness, followed by running out of medications before visiting the clinic. Conclusions: The study has indicated the presence of substantial noncompliance of glaucoma patients at a tertiary center. More attention to the issue of noncompliance, including health education and use of memory aids, could result in important benefits in the preservation of sight.

Effectiveness of Glaucoma Counseling on Rates of Follow-up and Glaucoma Knowledge in a South Indian Population - Do, AT; Pillai, MR; Balakrishnan, V; Chang, RT; Robin, AL; Singh, K; Lee, BW (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2016)
PURPOSE: To evaluate the impact of traditional counseling, and patient-centered counseling, either alone or with recorded audio counseling reinforcement, on glaucoma knowledge and clinical follow-up. DESIGN: Prospective randomized controlled trial. METHODS: Newly diagnosed adult glaucoma patients were randomized to 1 of 3 categories of glaucoma counseling: traditional counseling, patient-centered counseling, or patient-centered counseling with audio counseling reinforcement. Demographic and clinical information from each subject was ascertained, and all subjects completed the Glaucoma Knowledge Assessment before and after counseling sessions at the time of diagnosis and at 1-month follow-up. Patients were instructed to return to clinic for routine follow-up at 1, 3, 6, 9, and 12 months after enrollment. A multivariate logistic regression model was used to determine factors associated with appropriate clinical follow-up. RESULTS: Overall, only 13.5% of subjects had appropriate clinical follow-up at 1 year, defined as attending at least 3 follow-up visits during that interval, and there was no significant difference between counseling groups. The mean glaucoma knowledge assessment score (GKAS) improved by 77.6% with the initial counseling intervention (P<.0001), decreased by 17.4% within a 1-month period following initial counseling, and improved by 22.8% (P<.001) after the second counseling intervention. Monthly household income over 2500 rupees, GKAS greater than 5 after initial counseling, and undergoing any ocular surgical procedure were all independent predictors of appropriate follow-up. CONCLUSION: While all 3 counseling methods resulted in transient improvement of patient knowledge regarding glaucomatous disease, follow-up rates were poor for all groups. Poor retention of glaucoma knowledge may impact the likelihood of patient follow-up, and reinforcement with repeated counseling may be beneficial with regard to both disease knowledge and follow-up. (C) 2016 by Elsevier Inc. All rights reserved.

Better tolerance of preservative-free latanoprost compared to preserved glaucoma eye drops: the 12-month real-life FREE study - Economou, MA; Laukeland, HK; Grabska-Liberek, I; Rouland, JF (CLINICAL OPHTHALMOLOGY, 2018)
Background: Lack of efficacy due to bad compliance caused by intolerance issues is the main reason for a change to a better tolerated ocular treatment, such as using preservative-free (PF) eye drops. Aim: To assess the efficacy and local tolerance after 12 months and patient satisfaction regarding local treatment tolerance and handling at inclusion and after 6 months of PF latanoprost compared to preserved glaucoma eye drops. Methods: This was an international, prospective, and observational real-life study. Up to three visits, one at inclusion and two follow-up visits (one after 6 and one after 12 months) were planned. Efficacy, local tolerance, and patient satisfaction were the main evaluation criteria. Results: Data from 721 patients were available for the statistical analysis. Overall, 64.8% (467/721) of patients switched treatment before inclusion: 62.2% in the preserved and 68.9% in the PF latanoprost group. IOP values were similar between PF latanoprost and preserved eye drops and remained stable at all visits. Ocular signs and symptoms improved after switching to PF latanoprost; the prevalence of conjunctival hyperemia was significantly lower (P=0.0015) at both follow-up visits. At follow-up visit 1, 49.5% of the patients who switched to PF latanoprost decreased or stopped the use of artificial tears. Satisfaction regarding tolerance in patients using PF latanoprost improved significantly after the switch from preserved eye drops to PF latanoprost (88.9% and 42.5%, respectively, P<0.0001). Conclusion: This first real-fife study showed that PF latanoprost was as efficacious but better tolerated than preserved eye drops over a sustained period of 12 months, while providing a significantly higher patient satisfaction and potentially allowing improvement in the patient's daily life.

Community screening for eye disease by laypersons: The Hoffberger program - Quigley, HA; Park, CK; Tracey, PA; Pollack, IP (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2002)
Purpose: To describe the results of a community, based eye screening program in Baltimore. Design: Cross-sectional study. Methods: This was a retrospective study of the results of screening both eyes of 5352 persons who presented at multiple community sites. The screening examination had eight risk factor questions, visual acuity measurement, and a screening field test and was carried out by technicians and lay volunteers. Screened persons (screenees) received a definitive eye examination at no out,of,pocket cost, transportation was offered, and inexpensive eyeglasses were provided if needed. The main outcome measures were the rate of appointment keeping and the eye diseases identified. Telephone interviews were used to assess reasons for missing appointments and satisfaction with visits. Results: Screenees had a median age of 45 years, were 71% black, 59% female, and had estimated median annual family income of $24,000. Among 1331 screenees who scheduled a definitive examination appointment, 552 (41%) completed the visit. Data on definitive diagnosis was available in 480 out of 552 persons (87%). Reasons given for failing to come for definitive examination were: no appointment given (26%), forgot (20%), lack of transportation (9%), and lack of insurance coverage (6%). Of those who accepted a second visit date after defaulting, only 25% (41/167) appeared. Of 17 persons identified with glaucoma at screening, 4 had previously been diagnosed, but had ceased active care. Conclusion: After community screening for eye disease, efforts to provide definitive ophthalmic examination were only modestly effective. Failure of screenees to come for examination and loss to follow up were identified as serious problems. (Am J Ophtlialmol 2002; 133: 386-392. (C) 2002 by Elsevier Science Inc. All rights reserved.).

Applying the resources and supports in self-management framework to examine ophthalmologist-patient communication and glaucoma medication adherence - Sleath, B; Carpenter, DM; Blalock, SJ; Sayner, R; Muir, KW; Slota, C; Giangiacomo, AL; Hartnett, ME; Tudor, G; Robin, AL (HEALTH EDUCATION RESEARCH, 2015)
Little is known about how ophthalmologist-patient communication over time is associated with glaucoma patient long-term adherence. The purpose of our study was to examine the association between provider use of components of the resources and supports in self-management model when communicating with patients and adherence to glaucoma medications measured electronically over an 8-month period. In this longitudinal prospective cohort study, the main variables studied were ophthalmologist communication-individualized assessment, collaborative goal setting and skills enhancement. Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited from six ophthalmology clinics. Patients' baseline and next follow-up visits were videotape-recorded. Patients were interviewed after their visits. Patients used medication event monitoring systems (MEMS) for 8 months after enrollment into the study, and adherence was measured electronically using MEMS for 240 days after their visits. Two hundred and seventy-nine patients participated. Patient race and regimen complexity were negatively associated with glaucoma medication adherence over an 8-month period. Provider communication behaviors, including providing education and positive reinforcement, can improve patient adherence to glaucoma medications over an 8-month period.

A novel approach for successful closure of sinonasal fistulae - Nelson, L; Burke-Smith, A; Kirkpatrick, N (JOURNAL OF PLASTIC RECONSTRUCTIVE AND AESTHETIC SURGERY, 2014)
Medial canthus sinonasal fistula is associated with troublesome aesthetic and functional issues. Corneal irritation and drying results from escape of both air and secretions from the nasal cavity across the ocular surface as well as misting of spectacles if worn. Reconstruction of such fistulae is associated with a high rate of recurrence and thus presents a difficult surgical challenge. Methods: This paper describes the senior author's surgical approach to manage medial canthus sinonasal fistulae utilizing an interpolated forehead flap combined with extended galeafrontalis and pericranial flap for stepped closure. The technique of flap elevation and inset is discussed, with emphasis on key manoeuvres to prevent sinus recurrence. A retrospective review of consecutive cases is presented. Results: Four patients were treated using this technique over 12 months. In all cases, fistulae developed following adjuvant radiotherapy for tumour resection. Flap elevation was performed in combination with a bicoronal approach in 2 patients and via direct forehead approach in 2 patients. No post-operative complications or recurrence of fistula have occurred over 12 months follow-up. Conclusion: The success of this technique is attributed to inclusion of a galeafrontalis and pericranial extension to the forehead flap. In addition, the fistula site must be prepared to accommodate the flap by dissection of a wide subcutaneous pocket. This stepped method of closure provides an effective barrier to air and nasal secretions and also achieves an excellent aesthetic outcome. (C) 2014 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.

Level of Compliance in Orthokeratology - Jiang, J; Bian, ZW; Wang, FF; Lian, LL; Lu, F (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2018)
Objectives: To investigate the level of compliance with orthokeratology (ortho-k) guidelines and the main behaviors of poor compliance to guide clinical care. Methods: A questionnaire was sent to ortho-k patients in the Eye Hospital of Wenzhou Medical University (EHWMU) in Mainland China who were prescribed ortho-k lenses after January 2013 and have worn ortho-k lenses for more than 1 year to determine the compliance rate for eight wear and care behaviors. Follow-up visit compliance was then investigated among these patients using a retrospective survey. Results: A total of 1,500 questionnaires were distributed, and 405 patients responded. The mean age of the patients was 13.1 +/- 3.9 years (range 9-22 years); 60.5% of the patients were female, and 98.3% were younger than 18 years. The full compliance rate was 14.1%, the compliance rate for wear and care behaviors was 18.5%, and the compliance rate for follow-up visits was 63.3%. The three highest noncompliance categories for wear and care behaviors were exposure to nonsterile solution, not removing lens depositions according to the eye care practitioners' (ECPs) recommendations and inadequate hand washing. No correlation was observed between the compliance for wear and care behaviors and age, sex, and wearing experience. The follow-up visit compliance rate significantly decreased from the third month to the ninth month. The common reasons for discontinuing follow-up were lack of time, no symptoms, and inconvenience. Conclusions: The level of compliance with ortho-k lens wear in Mainland China is not high, necessitating ECPs to stress to patients the details of wear and care behaviors, especially avoiding exposing lenses to nonsterile solution. Improving monitoring of follow-up visits, particularly within the first 9 months of wearing ortho-k lenses, is needed.

In Vivo Assessment of Antimicrobial Efficacy of Silver-Impregnated Contact Lens Storage Cases - Dantam, J; Zhu, H; Willcox, M; Ozkan, J; Naduvilath, T; Thomas, V; Stapleton, F (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2012)
PURPOSE. To evaluate microbial contamination in silver-impregnated contact lens (CL) storage cases while establishing the effect of "wet" and "dry" case maintenance and to determine its association with clinical signs, symptoms, and compliance. METHODS. Two noncontemporaneous prospective studies were conducted. Regular storage cases in study 1 (n = 40) and silver-impregnated cases in study 2 (n = 41) were used in conjunction with CL solution and CLs (balafilcon A). Cases were replaced monthly and collected at 1, 3, and 4 (for silver-impregnated cases only) months. Regular cases and the fourth-month silver-impregnated cases were maintained dry, and the other cases were maintained wet between uses. At collection, storage cases were sampled and cultured for microbial identification and enumeration. Ocular clinical findings, subjective responses to CL wear, and compliance were recorded at each visit. RESULTS. The percentages of microbial contamination for silver-impregnated and regular cases were 71% and 82% respectively. There were significantly (P < 0.005) fewer organisms in silver-impregnated cases (1.7 log CFU per well) than in regular cases (4.1 log CFU per well). In particular, silver-impregnated cases showed lower levels of Gram-negative bacteria (P = 0.04), Gram-positive bacilli (P = 0.03), and fungi (P = 0.006). Maintaining the silver-impregnated cases wet resulted in a lower percentage of contamination (71%; P < 0.01) than maintaining them dry (94%). There was no association between any clinical signs, symptoms, or compliance and microbial contamination of storage cases. CONCLUSIONS. More than 70% of the storage cases used in daily wear CL care for a month was contaminated irrespective of the types of cases. However, silver-impregnated cases were colonized by reduced levels of Gram-negative bacteria. (www.anzctr.org.au number, ACTRN12609000165280.) (Invest Ophthalmol Vis Sci. 2012;53:1641-1648) DOI: 10.1167/iovs.11-8197

Prevalence and Correlates of Self-reported Nonadherence With Eye Drop Treatment: The Belgian Compliance Study in Ophthalmology (BCSO) - Vandenbroeck, S; De Geest, S; Dobbels, F; Fieuws, S; Stalmans, I; Zeyen, T (JOURNAL OF GLAUCOMA, 2011)
Purpose: This study aimed to investigate (1) the prevalence of nonadherence with eye drop treatment; (2) selected correlates of nonadherence at the patient and health-care organization level; and (3) the diagnostic value of the ophthalmologists' ratings, using patients' self-reports as standard. Methods: This cross-sectional multicenter survey used questionnaires for ophthalmologists and their patients to assess self-reported nonadherence and its correlates. One item, using a 4-point scale [never (ie, adherent) to daily], asked the patients whether they had forgotten to administer eye drops during the past 2 weeks. Ophthalmologists rated their patients as adherent or nonadherent. Nonadherence was also determined by combined methods, whereby either could indicate nonadherence. Given the nested structure of the data, multilevel modeling was used to investigate self-reported nonadherence-correlates. Diagnostic values of ophthalmologists' report were calculated. Results: Of 663 patients (48% female, 44% >69 years), nonadherence was indicated in 39.2% (n=260) through self-reporting, 2.1% (n=14) through ophthalmologists' ratings, and 40% (n= 266) through combined measures. The multivariable, multilevel model showed following significant nonadherence-correlates: Male sex (P=0.01), younger age (P=0.027), and higher-dose frequency (P=0.001). No significant correlation with treating ophthalmologist (P=0.21) could be seen. Yet, the patients visiting their ophthalmologists at least every 3 months were less nonadherent than patients with fewer consultations (P=0.01). The ophthalmologists' report showed a sensitivity and specificity of 3% and 98.5%, respectively. Conclusions: The prevalence of self-reported nonadherence was congruent with literature. The patients visiting their ophthalmologists at least every 3 months have a lower risk of nonadherence. Ophthalmologist report is an insensitive method for detecting nonadherence.

Characteristics of patients who dropout from a glaucoma clinic - Ashaye, AO; Adeoye, AO (JOURNAL OF GLAUCOMA, 2008)
Purpose: To find the dropout rate and identify the clinical characteristics of patients who drop out in the first year of follow-up from a glaucoma clinic. Design: Descriptive hospital-based study at a tertiary hospital eye department. Methods: Clinical characteristics of consecutive patients newly diagnosed with glaucoma who dropped out (n = 452) were compared with patients who did not drop out (n = 295) within 12 months. Results: The rate of dropout from follow-up was 60.5% within 1 year; 43. 1 % of the study group dropped out after their first follow-up visit. The dropout rate was high in all age groups, but higher in the age groups 21 to 30 years, 41 to 50 years, and over 70 years. Males had a higher dropout rate than females (78.6% vs. 34.5%). Dropout rate was higher among those with mild/ moderate glaucoma than those with severe disease (88.2% vs. 37.2%); those who lived further away from the hospital than those who lived nearer to the hospital (72.5% vs. 40.8%), those who were referred from screening clinics for nonblinding eye disease compared with those referred because of a blinding eye disease (72.2% vs. 58.9%). More patients (63.8%) unsure of their family eye disease history dropped out, compared with 34.3% of those with positive family history of glaucoma and other potentially blinding diseases. More patients who had no systemic disease dropped out, than those with systemic disease (54.6% vs. 39.6%); whereas patients on 2 medications or more had a higher dropout rate than those on less than 2 medications (68.1 % vs. 52.1%). Of the study factors, those that were statistically significantly associated with dropping out of follow-up from the glaucoma clinic were age, sex, place of domicile, diagnosis at referral, severity of disease, family history, and polydrug use. Conclusions: The dropout rate from this glaucoma clinic in the first year was high (60.5%). Patients who were more likely to dropout were younger patients, male, those who travelled far distances to the clinic, those with mild to moderate glaucoma, those with no family history of blinding eye diseases, and patients taking 2 or more eyedrops. Patients who seem to perceive their problems as not serious dropped out of follow-up. These findings have great implications in planning future studies and intervention to improve the follow-up of glaucoma patients in the study area.

The Association between Medication Adherence and Visual Field Progression in the Collaborative Initial Glaucoma Treatment Study - Newman-Casey, PA; Niziol, LM; Gillespie, BW; Janz, NK; Lichter, PR; Musch, DC (OPHTHALMOLOGY, 2020)
Purpose: To evaluate the relationship between medication adherence and visual field progression in participants randomized to the medication arm of the Collaborative Initial Glaucoma Treatment Study (CIGTS). Design: The CIGTS was a randomized, multicenter clinical trial comparing initial treatment with topical medications to trabeculectomy for 607 participants with newly diagnosed glaucoma. Participants: Three hundred seven participants randomized to the medication arm of the CIGTS. Methods: Participants were followed up at 6-month intervals for up to 10 years. Self-reported medication adherence and visual fields were measured. Medication adherence was assessed by telephone from responses to the question, "Did you happen to miss any dose of your medication yesterday?" The impact of medication adherence on mean deviation (MD) over time was assessed with a linear mixed regression model adjusting for the effects of baseline MD and age, cataract extraction, interactions, and time (through year 8, excluding time after crossover to surgery). Medication adherence was modeled as a cumulative sum of the number of prior visits where a missed dose of medication was reported. Main Outcome Measure: Mean deviation over time. Results: Three hundred seven subjects (306 with adherence data) were randomized to treatment with topical medications and followed up for an average of 7.3 years (standard deviation, 2.3 years). One hundred forty-two subjects (46%) reported never missing a dose of medication over all available follow-up, 112 patients (37%) reported missing medication at up to one third of visits, 31 patients (10%) reported missing medication at one third to two thirds of visits, and 21 patients (7%) reported missing medication at more than two thirds of visits. Worse medication adherence was associated with loss of MD over time (P = 0.005). For subjects who reported never missing a dose of medication, the average predicted MD loss over 8 years was 0.62 dB, consistent with age-related loss (95% confidence interval [CI], 0.17-1.06; P = 0.007); subjects who reported missing medication doses at one third of visits had a loss of 1.42 dB (95% CI, 0.86-1.98; P < 0.0001); and subjects who reported missing medication doses at two thirds of visits showed a loss of 2.23 dB (95% CI, 1.19-3.26; P < 0.0001). Conclusions: This longitudinal assessment demonstrated a statistically and clinically significant association between medication nonadherence and glaucomatous vision loss. (C) 2019 by the American Academy of Ophthalmology

Patient and Clinician Satisfaction With Shared Medical Appointments for Glaucoma - Tam, EK; De Arrigunaga, S; Shah, MD; Kefella, H; Soriano, S; Rowe, S (SEMINARS IN OPHTHALMOLOGY)
Shared Medical Appointments (SMAs) are patient-centered care tools designed to administer patient counseling and education, typically delivered individually, in a group setting. SMAs are effective in facilitating peer-learning, resulting in improvement in knowledge and health behavior. This study aimed to implement what we know of as the first ophthalmology SMA done in the United States. We evaluated the implementation feasibility, patient and provider experience, changes in patient knowledge, and provider stress. Five glaucoma patients who expressed issues with adherence during their clinic visit at Boston Medical Center (BMC) who were interested in the SMA were recruited. Patients and staff had a positive experience with the SMA. There was a marked increase in patient glaucoma knowledge and a decrease in average staff member stress level score during the SMA. From all standpoints, including billing and management, we conclude that SMA implementation is feasible in ophthalmology departments in academic settings.

Glaucoma Patient Expression of Medication Problems and Nonadherence - Slota, C; Sayner, R; Vitko, M; Carpenter, DM; Blalock, SJ; Robin, AL; Muir, KW; Hartnett, ME; Sleath, B (OPTOMETRY AND VISION SCIENCE, 2015)
Purpose. The purpose of this study was to examine if patient demographic factors influenced self-reporting of medication side effects, difficulty with drop instillation, and nonadherence to glaucoma therapy. Methods. English-speaking adult glaucoma patients (n = 279) from six ophthalmology clinics were enrolled. Patients' medical visits were videotaped and patients were interviewed immediately afterward by research assistants. The videotapes were transcribed verbatim and coded to identify patients who expressed problems with medication side effects, eye drop administration, and nonadherence during the glaucoma office visits. Generalized estimating equations were performed to identify whether patient characteristics were associated with expression of problems with glaucoma medication and medication nonadherence during the office visit. Results. Patients with lower health literacy were significantly less likely to express problems with side effects (odds ratio [OR], 0.47; 95% confidence interval [CI], 0.25 to 0.88) and eye drop administration (OR, 0.26; 95% CI, 0.11 to 0.63) during the visit. Patients who reported eye drop administration and side effect problems during the interview were significantly more likely to express these problems to their ophthalmologist (OR, 3.13; 95% CI, 1.82 to 5.37 and OR, 1.86; 95% CI, 1.12 to 3.08, respectively). Patients who expressed a problem with eye drop administration and with side effects were significantly more likely to express medication nonadherence to their ophthalmologist (OR, 2.89; 95% CI, 1.44 to 5.80 and OR, 2.03; 95% CI, 1.16 to 3.54, respectively). Patients who reported greater than 80% medication adherence during the interview were significantly less likely to express nonadherence to their ophthalmologist (OR, 0.22; 95% CI, 0.12 to 0.40). Conclusions. Eye care providers should be aware that glaucoma patients with lower health literacy are less likely to express problems with side effects and eye drop administration. Providers should work with patients to assess medication-related problems to mitigate potential barriers to medication adherence because patients who expressed medication problems were also more likely to express nonadherence.

Glaucoma Medication Adherence in Veterans and Influence of Coexisting Chronic Disease - Asefzadeh, B; Rett, D; Pogoda, TK; Selvin, G; Cavallerano, A (JOURNAL OF GLAUCOMA, 2014)
Background: The aim of this study was to characterize veterans' adherence to glaucoma medications and follow-up eye care, and to examine the influence of coexisting chronic conditions such as posttraumatic stress disorder (PTSD)/anxiety. Patients and Methods: A retrospective review of computerized medical records was performed for 161 veterans taking topical glaucoma medications. Medication possession ratio (MPR) was calculated using pharmacy data. Mean follow-up ratio (FUR) was calculated using the number of days between visits. Results: Among the health conditions examined, the most prevalent was hearing loss (0.34), followed by arthritis (0.29), PTSD, or other anxiety disorder (0.27), and dementia or other memory disorder (0.09). The average rates of MPR and FUR were 0.69 +/- 0.20 and 0.84 +/- 0.19, respectively. Group comparisons found that patients with hearing loss had higher MPR compared with patients without hearing loss, and patients who were white had higher FUR than African American patients. When demographic and health characteristics were examined simultaneously in multiple linear regressions, hearing loss emerged as a significant predictor of MPR, and being older was significantly related to FUR. Younger age was also associated with MPR and being white (vs. African American) or having a PTSD/other anxiety disorder was related to FUR, although these findings did not reach statistical significance. Conclusions: FUR was better than MPR in a veteran population being treated for glaucoma. Hearing loss was significantly related to higher MPR, whereas being older was significantly associated with higher FUR. These characteristics should be taken into consideration in future programs to improve adherence to glaucoma care.

Advantages of fixed combinations - Lachkar, Y (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2008)
Fixed combinations are indicated in the treatment of glaucoma and ocular hypertension when monotherapy does not sufficiently reduce IOP. Fixed combinations show better efficacy than the instillation of each separate component and are at least equivalent to the administration of both components in a separate association. They simplify treatment, increase compliance and quality of life, and decrease exposure to preservatives. Although they are less aggressive for patients when a new drug needs to be added, the use of fixed combinations should not decrease the follow-up.

Accuracy of Patient-reported Adherence to Glaucoma Medications on a Visual Analog Scale Compared With Electronic Monitors - Sayner, R; Carpenter, DM; Blalock, SJ; Robin, AL; Muir, KW; Hartnett, ME; Giangiacomo, AL; Tudor, G; Sleath, B (CLINICAL THERAPEUTICS, 2015)
Purpose: Glaucoma medications can improve clinical outcomes when patients adhere to their medication regimen. Providers often ask patients with glaucoma to self-report their adherence, but the accuracy of self-reporting has received little scientific attention. The purpose of this article was to compare a self-reported medication adherence measure with adherence data collected from Medication Event Monitoring Systems (MEMS) electronic monitors. An additional goal was to identify which patient characteristics were associated with overreporting adherence on the self-reported measure. Methods: English-speaking adult patients with glaucoma were recruited from 6 ophthalmology practices for this observational cohort study. Patients were interviewed after their initial visit and were given MEMS contains, which recorded adherence over a 60-day period. MEMS percent adherence measured the percentage of the prescribed number of doses taken. MEMS-measured timing adherence assessed the percent doses taken on time. Patients self-reported adherence to their glaucoma medications on a visual analog scale (VAS) 60 days after the baseline visit. Bivariate analyses and logistic regressions were used to analyze the data. Self-reported medication adherence on the VAS was plotted against MEMS adherence to illustrate the discrepancy between self-reported and electronically monitored adherence. Findings: The analyses included 240 patients who returned their MEMS containers and self-reported medication adherence at the 60-day follow-up visit. Compared with MEMS-measured percent adherence, 31% of patients (n = 75) overestimated their adherence on the VAS. Compared with MEMS-measured timing adherence, 74% (n = 177) of patients overestimated their adherence. For the MEMS-measured percent adherence, logistic regression revealed that patients who were newly prescribed glaucoma medications were significantly more likely to overreport adherence on the VAS (odds ratio, 3.07 [95% CI, 1.22-7.75]). For the MEMS-measured timing adherence, being male (chi(2) test, 6.78; P = 0.009) and being prescribed glaucoma medications dosed multiple times daily (chi(2) test, 4.02; P = 0.045) were significantly associated with patients overreporting adherence. However, only male sex remained a significant predictor of overreporting adherence in the logistic regression (odds ratio, 4.05 [95% CI, 1.73-9.47]). (C) 2015 Elsevier HS Journals, Inc. All rights reserved.

Factors associated with failure to follow up after glaucoma screening - A study in an African American population - Gwira, JA; Vistamehr, S; Shelsta, H; Bashford, K; Forster, S; Palmisano, P; Shafranov, G; Shields, MB (OPHTHALMOLOGY, 2006)
Purpose: To evaluate variables associated with failure to access free eye care after participating in glaucoma screening. Design: Review of responses to a survey completed by participants during glaucoma screening. Participants: Two hundred seventy-three surveys completed by participants of African descent during screening. Methods: African Americans 40 years or older participated in community glaucoma screening clinics, which included a survey with demographic and social variables. Each participant was given a preliminary diagnosis and encouraged to attend a free eye clinic for a complete examination. Survey results were correlated with attendance at the follow-up examination, using Student's t test, chi-square test, and logistic regression analysis. Main Outcome Measure: Noncompliance with follow-up after glaucoma screening. Results: When adjusting for risk factors in logistic regression analysis, noncompliance was associated with living alone (P = 0.008), smoking (P = 0.0005), and lacking a car (P < 0.01). Odds of noncompliance for participants living alone were 2.2 times higher than those for participants not living alone. Odds of noncompliance for participants who smoked were 3.0 times greater than those for participants who did not smoke. Odds of noncompliance for participants who did not have access to a car for their last eye examination were 2.1 times greater than those for participants who did. Conclusion: Socioeconomic factors such as smoking, lack of access to a car for eye examinations, and living alone are associated with noncompliance to follow-up after glaucoma screening clinics. Identifying persons with these variables may facilitate improved compliance.

Combined endonasal and sublabial endoscopic transmaxillary approach to the pterygopalatine fossa and orbital apex - Alimohamadi, M; Hajiabadi, M; Gerganov, V; Fahlbusch, R; Samii, M (ACTA NEUROCHIRURGICA, 2015)
The pterygopalatine fossa (PPF) and inferomedial orbital apex are difficult regions for open neurosurgical access. The traditional extensive anterior approach (transfacial or transmandibular) and lateral/posterolateral (transcranial) approach were used to access the PPF. The combined endonasal and sublabial transmaxillary approach is a less invasive access route for these lesions. In this study, we present the technical and clinical details of our experience with the combined endoscopic endonasal and transmaxillary approach. A retrospective analysis of our patients operated on using a combined endoscopic endonasal and transmaxillary approach was done. The preoperative, intraoperative and postoperative images and all the clinical data were evaluated. The accessibility to the area and extent of surgical resection were reviewed. The surgery-related complications and postoperative morbidities were analyzed. The main items of interest were the exposure of the target area and possibility for safe removal. Five patients with pathologies located in the area of the PPF and orbital apex were operated on using the combined endoscopic sublabial and endonasal transmaxillary approach. The technique provided sufficient exposure of the area and allowed for safe removal of the preoperatively determined target in all of the patients. One patient developed dry eye and a neurotrophic corneal ulcer, and another patient developed temporary postoperative facial numbness. In the follow-up, only one patient with skull base chordoma had an asymptomatic tumor regrowth. The other patients had no recurrence or regrowth. The combined endoscopic sublabial and endonasal transmaxillary approach is a safe and effective method for resection of lesions in the PPF and inferomedial orbital apex.

A qualitative investigation into patients' views on visual field testing for glaucoma monitoring - Glen, FC; Baker, H; Crabb, DP (BMJ OPEN, 2014)
Objectives To investigate the views and experiences of patients regarding their glaucoma follow-up, particularly towards the type and frequency of visual field (VF) testing. Design A qualitative investigation using focus groups. The group discussion used broad open questions around the topics in a prompt guide relating to experiences of glaucoma follow-up, and in particular, VF monitoring. All the groups were taped, transcribed and coded using manual and computer-aided methods. Setting Three National Health Service (NHS) hospitals in England; two focus groups took place at each hospital. Participants 28 patients (mean (SD) age: 74 (9) years; 54% women) diagnosed with glaucoma for at least 2years. Each focus group consisted of 3-6 patients. Primary and secondary outcomes (1) Attitudes and experiences of patients with glaucoma regarding VF testing. (2) Patients' opinions about successful follow-up in glaucoma. Results These patients did not enjoy the VF test but they recognised the importance of regular monitoring for preserving their vision. These patients would agree to more frequent VF testing on their clinician's recommendation. A number of themes recurred throughout the focus groups representing perceived barriers to follow-up care. The testing environment, waiting times, efficiency of appointment booking and travel to the clinic were all perceived to influence the general clinical experience and the quality of assessment data. Patients were also concerned about aspects of patient-doctor communication, and often received little to no feedback about their results. Conclusions Patients trust the clinician to make the best decisions for their glaucoma follow-up. However, patients highlighted a number of issues that could compromise the effectiveness of VF testing. Addressing patient-perceived barriers could be an important step for devising optimal strategies for follow-up care.

Integrating Patient Education Into the Glaucoma Clinical Encounter: A Lean Analysis - Newman-Casey, PA; Musser, JA; Niziol, LM; Heisler, MM; Kamat, SS; Shah, MM; Patel, N; Cohn, AM (JOURNAL OF GLAUCOMA, 2019)
Purpose: The main purpose of this study was to use Lean analysis to identify how often and when wait times occur during a glaucoma visit to identify opportunities for additional patient engagement. Methods: This prospective observational time-motion study measured process and wait times for 77 patient visits from 12 ophthalmologists at an academic glaucoma clinic over a 3-month period. Value stream maps visually diagramed the process of a clinical visit from the patient's perspective. Descriptive statistics were calculated for process times, wait times, and the frequency of 10+ minute wait times during each part of the visit. Key stakeholders participated in a root cause analysis to identify reasons for long wait times. The main outcome measure was average times (hours: minutes: seconds) for process times and wait times. Results: Twenty-nine new visit (NV) patients and 48 return visit (RV) patients were included. Total time in clinic was 187.1 +/- 44.5 (mean +/- SD) minutes for NV patients and 102.0 +/- 44.7 minutes for RV patients. Wait time for NV patients was 63.7 +/- 33.4 minutes (33.1% of total appointment time) and for RV patients was 52.6 +/- 31.6 minutes (49.4% of the total appointment time). All NV patients and 87.5% of RV patients had at least one 10+ minute wait time during their clinic visit and the majority (75.9% NV, 60.4% RV) had >1. Conclusions: Currently, sufficient wait time exists during the visit for key portions of glaucoma education such as teaching eye drop instillation.

Adherence to Glaucoma Medication: The Effect of Interventions and Association With Personality Type - Lim, MC; Watnik, MR; Imson, KR; Porter, SM; Granier, AM (JOURNAL OF GLAUCOMA, 2013)
Purpose: To determine whether multiple interventions influence adherence to glaucoma medication and to study the relationship between personality type and adherence.Methods: Eighty patients with glaucoma using prostaglandin monotherapy were prospectively randomized to an intervention or a nonintervention group. Over a 5-month period, the intervention group received monthly automated telephone calls reminding them to take their glaucoma medications. At month 3, the intervention group had an office visit with their physician and received education regarding their disease and treatment. The nonintervention group returned at the end of the study period. Adherence was directly measured with an electronic monitoring cap. Outcome measures were adherence rate and therapeutic coverage. Patients completed the Minnesota Multiphasic Personality Inventory-2.Results: Thirty-eight patients were randomized to the intervention group and 42 were randomized to the nonintervention group. Mean adherence rate for the intervention group over 5 months was 76% and for the nonintervention group, 81%. For the intervention group, adherence did not change significantly after the midstudy visit (P=0.233). No difference existed between the intervention and nonintervention groups before (P=0.456) or after (P=0.134) the midstudy intervention visit. The Minnesota Multiphasic Personality Inventory-2 personality scales for depression (P=0.01) and hypochondriasis (P>0.0001) were significantly associated with poorer adherence.Conclusions: Monthly automated telephone reminders, a 1-time educational session, and increased contact with a physician did not improve adherence rate with glaucoma medications. Depression and hypochondriasis personality types were related to poor adherence and highlight the role of psychosocial factors in medication adherence.

Adherence and Persistence with Glaucoma Therapy - Schwartz, GR; Quigley, HA (SURVEY OF OPHTHALMOLOGY, 2008)
Adherence and persistence with chronic therapies is crucial to prevent disease progression, such as in glaucoma. Patients report high rates of adherence, which are not supported by pharmacy claims analysis. This article reviews the literature regarding methods to assess adherence and persistence and the patient behaviors that pose challenges to proper treatment. Rates for persistence are generally below 50% at 1 year. Differentiating efficacy of eyedrops from lack of adherence presently confounds ophthalmic treatment. Additionally, as intraocular pressure (IOP) can appear controlled by short-term adherence, the physician can be fooled into believing the patient's glaucoma is well-controlled. Likewise, when progressive worsening is noted despite good IOP control, it can be problematic whether the patient's target pressure needs to be lowered or adherence needs to be improved. White-coat adherence is common, in which patient adherence rises sharply 1 week before the appointment with the physician, then declines rapidly following the appointment. White-coat adherence may make it difficult to assess IOP control over the longer term; cycling behavior with medication use is well-documented. Adherence and persistence rates differ by class of drug, with higher rates associated with prostaglandin use. We review findings from The Glaucoma Adherence and Persistency Study that. identified behaviors associated with poor adherence. Greater physician awareness of adherence and persistence issues is necessary in order to help the patient become more adherent. (Surv Ophthalmol 53:S57-S68, 2008. (C) 2008 Elsevier Inc. All rights reserved.)

Efficacy and safety of latanoprost eye drops for glaucoma treatment: A 1-year study in Japan - Suzuki, M; Mishima, HK; Masuda, K; Araie, M; Kitazawa, Y; Azuma, I (JAPANESE JOURNAL OF OPHTHALMOLOGY, 2000)
Purpose: To evaluate the intraocular pressure (IOP)-lowering effect and safety of latanoprost, a prostaglandin analogue, in patients with primary open-angle glaucoma or ocular hypertension. Method: One hundred and twenty-four Japanese patients with primary open-angle glaucoma or ocular hypertension were enrolled in this open-labeled study and were treated with 0.005% latanoprost once daily for 1 year. Results: At all follow-up visits there was a significant (P < .001) reduction in IOP compared with the baseline value. After 1 year, the IOP was reduced by 5.4 +/- 2.9 (mean +/- SD) mm Hg from a baseline value of 23.5) 2.2 mm Hg. No evidence of an upward drift in the IOP was observed during the treatment period. The most frequently reported adverse ocular events were mild conjunctival hyperemia and iris pigmentation. Very few adverse systemic events were observed. Conclusions: Latanoprost eye drops showed a marked and stable IOP-lowering effect during the 1-year treatment period. Furthermore, latanoprost was well-tolerated and should be a valuable contribution to the management of glaucoma. (C) 2000 Japanese Ophthalmological Society.

Blind Spots: Gaps in Disease Knowledge and the Role of Patient Education for Canadians With Diabetic Macular Edema - Andrews, C; Yoganathan, P; Pereira, JA (CANADIAN JOURNAL OF DIABETES, 2021)

Improving Access to Eye Care among Persons at High-Risk of Glaucoma in Philadelphia - Design and Methodology: The Philadelphia Glaucoma Detection and Treatment Project - Hark, L; Waisbourd, M; Myers, JS; Henderer, J; Crews, JE; Saaddine, JB; Molineaux, J; Johnson, D; Sembhi, H; Stratford, S; Suleiman, A; Pizzi, L; et al. (OPHTHALMIC EPIDEMIOLOGY, 2016)
Purpose: The Wills Eye Glaucoma Research Center initiated a 2-year demonstration project to develop and implement a community-based intervention to improve detection and management of glaucoma in Philadelphia. Methods: The glaucoma detection examination consisted of: ocular, medical, and family history; visual acuity testing; corneal pachymetry; biomicroscopy of the anterior segment; intraocular pressure (IOP) measurement; gonioscopy; funduscopy; automated visual field testing; and fundus-color photography. Treatment included laser surgery and/or IOP-lowering medication. A cost analysis was conducted to understand resource requirements. Outcome measures included; prevalence of glaucoma-related pathology and other eye diseases among high-risk populations; the impact of educational workshops on level of knowledge about glaucoma (assessed by pre- and post-test evaluation); and patient satisfaction of the glaucoma detection examinations in the community (assessed by satisfaction survey). Treatment outcome measures were change in IOP at 4-6 weeks and 4-6 months following selective laser trabeculoplasty treatment, deepening of the anterior chamber angle following laser-peripheral iridotomy treatment, and rate of adherence to recommended follow-up examinations. Cost outcomes included total program costs, cost per case of glaucoma detected, and cost per case of ocular disease detected. Results: This project enrolled 1649 participants (African Americans aged 50+ years, adults 60+ years and individuals with a family history of glaucoma). A total of 1074 individuals attended a glaucoma educational workshop and 1508 scheduled glaucoma detection examination appointments in the community setting. Conclusions: The Philadelphia Glaucoma Detection and Treatment Project aimed to improve access and use of eye care and to provide a model for a targeted community-based glaucoma program.

Repeat Descemet Membrane Endothelial Keratoplasty after Complicated Primary Descemet Membrane Endothelial Keratoplasty - Baydoun, L; van Dijk, K; Dapena, I; Musa, FU; Liarakos, VS; Ham, L; Melles, GRJ (OPHTHALMOLOGY, 2015)
Purpose: To describe the clinical outcome and complications of repeat Descemet membrane endothelial keratoplasty (re-DMEK). Design: Retrospective case series study at a tertiary referral center. Participants: From a series of 550 consecutive DMEK surgeries with 6 months follow-up, 17 eyes underwent re-DMEK for graft detachment after initial DMEK (n = 14) and/or endothelial graft failure (n = 3). The outcomes were compared with an age-matched control group of uncomplicated primary DMEK surgeries. Methods: The re-DMEK eyes were evaluated for best-corrected visual acuity (BCVA), densitometry, endothelial cell density (ECD), pachymetry, and intraoperative and postoperative complications. Main Outcome Measures: Feasibility and clinical outcome of re-DMEK. Results: In all eyes, re-DMEK was uneventful. At 12 months, 12 of 14 eyes (86%) achieved a BCVA of >= 20/40 (>= 0.5); 8 of 14 eyes (57%) achieved >= 20/25 (>= 0.8), 3 of 14 eyes (21%) achieved >= 20/20 (>= 1.0), and 1 eye (7%) achieved 20/17 (1.2); 5 eyes were fitted with a contact lens. Average donor ECD decreased from 2580 +/- 173 cells/ mm(2) before to 1390 +/- 466 cells/mm(2) at 6 months after surgery, and pachymetry from 703 = 126 mm to 515 = 39 mm, respectively. No difference in densitometry could be detected between re-DMEK and control eyes (P = 0.99). Complications after re-DMEK included primary graft failure (n = 1), secondary graft failure (n = 2), graft detachment requiring rebubbling (n = 1), secondary glaucoma (n = 2), cataract (n = 1), and corneal ulcer (n = 1). One eye received tertiary DMEK. Conclusions: In the management of persistent graft detachment and graft failure after primary DMEK, re-DMEK proved a feasible procedure. Acceptable BCVA may be achieved, albeit lower than after DMEK in virgin eyes, and some cases may benefit from contact lens fitting. Complications after re-DMEK may be better anticipated than after primary DMEK because graft detachment and graft failure tended to recur, suggesting that intrinsic properties of the host eye play a role in graft adherence and graft failure. (C) 2015 by the American Academy of Ophthalmology.

Long-term effect of latanoprost/timolol fixed combination in patients with glaucoma or ocular hypertension: A prospective, observational, noninterventional study - Schwenn, O; Heckmann, B; Guzy, C; Miller, PJ (BMC OPHTHALMOLOGY, 2010)
Background: Prospective, observational studies that enroll large numbers of patients with few exclusion criteria may better reflect actual ongoing clinical experience than randomized clinical trials. Our purpose was to obtain efficacy and safety information from a cohort of subjects exposed to latanoprost/timolol fixed combination (FC) for >= 18 months using a prospective, observational design. Methods: In all, 577 office-based ophthalmologists in Germany switched 2339 patients with glaucoma or ocular hypertension to latanoprost/timolol FC for medical reasons. Follow-up visits were scheduled for every 6 months over 24 months; physicians followed usual care routines. Intraocular pressure (IOP), visual field status, optic nerve head findings, and adverse events were recorded. Efficacy parameters were evaluated for the per protocol (PP) population; the safety population included subjects receiving >= 1 drop of FC. Physicians rated efficacy, tolerability, and subject compliance at month 24. Results: Of the 2339 subjects switched to latanoprost/timolol FC (safety population), the primary reasons for switching were inadequate IOP reduction (78.2%) and desire to simplify treatment with once-daily dosing (29.4%; multiple reasons possible). In all, 1317 (56.3%) subjects completed the study, and 1028 (44.0%) were included in the PP population. Most discontinuations were due to loss to follow-up. Change in mean IOP from baseline to month 6 was -4.0 +/- 4.31 mmHg, a reduction that was maintained throughout (P < 0.05 for change at all time points). By investigator assessments, optic disc parameters and visual field were stable over 24 months, and there was no relationship between IOP reduction over 24 months and development of a visual field defect. More than 90% of physicians rated latanoprost/timolol FC as "very good" or "good" for efficacy (PP population), tolerability, and compliance. The FC was safe and well tolerated. No change in iris color was reported by most subjects (83.1%) at month 24. Conclusions: Over 24 months, latanoprost/timolol FC effectively lowers IOP levels and is well tolerated in patients with glaucoma or ocular hypertension who change from their previous ocular hypotensive therapy for medical reasons. Investigator assessments found optic disc parameters and visual field to be stable throughout 24 months of follow-up.

Long-term outcomes of cultivated cell sheet transplantation for treating total limbal stem cell deficiency - Shimazaki, J; Satake, Y; Higa, K; Yamaguchi, T; Noma, H; Tsubota, K (OCULAR SURFACE, 2020)
Purpose: This study was conducted to determine the long-term outcomes of cultivated cell sheet transplantation (CCST), and to clarify risk factors that affected the outcomes. Methods: We retrospectively analyzed the medical charts and photographs of 246 consecutive surgeries (162 eyes from 139 patients) that used CCST for treating total limbal stem cell deficiency. Deficiency types included Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (SJS/TEN; n = 80), ocular surface burns (Burn; n = 75), ocular cicatricial pemphigoid (OCP) or pseudo-OCP (n = 58), and others (n = 33). The methods of CCST included 103 cultivated limbal epithelial transplantations (28 autologous, 62 allogeneic, and 13 living-related relatives), and 143 cultivated oral mucosal epithelial transplantations. We analyzed the rate of successful ocular surface reconstruction, clear corneas, and best-corrected visual acuity equal to or better than 20/200. Results: With a mean observation period of 357 weeks, successful ocular surface reconstruction and clear corneas at last visit were achieved in 65.1% of the patients. Corrected visual acuity equal to or better than 20/200 was achieved in 19.0% of the patients. Eyes with SJS/TEN exhibited worse outcomes compared with the Burn group. Postoperative complications included corneal ulcerations or perforations (18.3%), glaucoma (13.8%), and infections (8.5%). Multivariate analyses using the logistic mixed-effects model indicated that the presence of preoperative corneal epithelial defects was a significant risk factor for postoperative failure. Conclusions: In this series, the success rate of CCST after a mean observation period of 357 weeks was 65.1%, and preoperative epithelial defect was the most relevant risk factor.

Improving Follow-up and Reducing Barriers for Eye Screenings in Communities: The SToP Glaucoma Study - Zhao, D; Guallar, E; Bowie, JV; Swenor, B; Gajwani, P; Kanwar, N; Friedman, DS (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2018)
PURPOSE: To evaluate factors associated with attendance to follow-up ophthalmic care, and to assess the impact of strategies to improve follow-up. DESIGN: Cross-sectional study. METHODS: This is an ongoing study to develop an eye screening paradigm, focusing on African Americans >= 50 years of age at multiple urban community sites in Baltimore, Maryland. Several strategies were employed aiming to increase follow-up attendance rates. Multivariable logistic regression was used to evaluate the associations between demographic, medical, and ocular factors with follow-up rate. RESULTS: The total number of referred patients presenting for a free eye examination (attendance rate) during the first phase, during the second phase, and overall was 686 (55.0%), 199 (63.8%), and 885 (57.0%), respectively. In fully adjusted models, the odds ratio (95% confidence intervals) for attending the follow-up visit was 1.82 (1.19, 2.79) for screening in second phase vs first phase, 0.62 (0.39, 0.99) for screening sites that were 3 to < 5 miles vs < 1 mile from the hospital, 1.70 (1.12, 2.59) in patients with body mass index >= 30 vs < 25 kg/m(2), 2.03 (1.28, 3.21) in patients with presenting visual acuity < 20/40 vs >= 20/40, and 2.32 (1.24, 4.34) for patients with an abnormal vs normal macula. CONCLUSIONS: Obesity, short distance between screening sites and hospital, poor presenting visual acuity in the better eye, and an abnormal macula on fundus photography were associated with increased follow-up rate. Implementation of a combination of strategies effectively increased the follow-up rate. Wider adoption of these strategies in other screening programs has the potential to reduce the burden of visual impairment. ((c) 2018 Elsevier Inc. All rights reserved.)

Knowledge about glaucoma and barriers to follow-up care in a community glaucoma screening program - Altangerel, U; Nallamshetty, HS; Uhler, T; Fontanarosa, J; Steinmann, WC; Almodin, JM; Chen, BH; Henderer, JD (CANADIAN JOURNAL OF OPHTHALMOLOGY-JOURNAL CANADIEN D OPHTALMOLOGIE, 2009)
Objective: To assess perceived barriers to glaucoma follow-up care, including the lack of glaucoma knowledge and the lack of health care access, among participants in a community glaucoma screening program. Design: Community survey. Participants: Two hundred forty-three consecutive participants in a series of free glaucoma screenings between November 2002 and August 2003. Methods:The survey consisted of 20 questions designed to elicit knowledge of glaucoma and perception of potential barriers to follow-up care. Our aim was to find correlations between patient demographics and knowledge of glaucoma as well as perceived potential barriers to follow-up care. The data were analyzed using SPSS, v. 10.1. Results: The average age of the respondents was 70 years, and females predominated (66%). About half of the respondents knew of an eye doctor in their neighborhood, and 60% had had an eye examination in the past year. Two hundred twenty-two (91%) indicated they could get to an eye doctor if the screening examination indicated they needed a follow-up examination. Two hundred twenty (90.5%) had medical insurance. One hundred seventy-eight (73%) of the participants had heard of glaucoma; 71 (29%) identified an accurate definition of glaucoma. The level of education and the language spoken at home were correlated with both glaucoma awareness (p<0.001; p<0.001) and knowledge of an accurate definition of glaucoma (p<0.001; p<0.025). Conclusions: In this population, a lack of adequate education about glaucoma may be more significantly associated with poor follow-up rates than a lack of access to care in those identified as glaucoma suspects.

Development and Validation of a Predictive Model for Nonadherence with Once-Daily Glaucoma Medications - Chang, DS; Friedman, DS; Frazier, T; Plyler, R; Boland, MV (OPHTHALMOLOGY, 2013)
Objective: To develop and validate a predictive model to estimate the probability of being nonadherent to topical glaucoma medications. Design: Prospective cohort study. Participants: Patients being treated with once-daily prostaglandin eye drops. Methods: A predictive model for nonadherence was developed from the Travatan Dosing Aid (TDA) study (n = 196) using stepwise logistic regression. The performance of the TDA-derived model was assessed using a separate cohort of subjects from the Automated Dosing Reminder Study (ADRS; n = 407). The assessment was based on regression coefficients, discrimination, and calibration. We also developed a scoring system from the TDA-derived model to simplify the estimation of risk for clinical use. Main Outcome Measures: Usage of drops was monitored electronically for 3 months in both studies. Adherence was calculated as the percentage of days on which a dose was taken within 4 hours of the average dosing time for that patient. Nonadherence was defined as taking <= 75% prescribed doses within a window starting 2 weeks after the baseline visit until 2 weeks before the follow-up visit. Results: Six factors, including younger age, black race, worse general health status, shorter duration of glaucoma medication therapy, lower self-reported adherence, and admitting to not following doctors' orders, were associated with being nonadherent and were included in the predictive model. The coefficients for the TDA-derived and the ADRS-derived predictive models were similar. The risk scoring system developed from the TDA study had good discrimination (area under the receiver operating characteristic curve of 0.80) and calibration (Hosmer-Lemeshow goodness-of-fit test, P = 0.102) when applied to the ADRS population. Conclusions: The TDA-derived predictive model for nonadherence performed well in an independent population. A risk scoring system was developed using demographic data and patient responses to 4 questions to provide an estimate of the probability of being nonadherent.

Compliance with medical treatment in primary open-angle glaucoma in Lome - Santos, MAK; Ayena, DK; Kuaovi, KR; Vonor, K; Djagnikpo, A; Balo, KP (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2016)
Objective. To assess the compliance rate among glaucoma patients with medical treatment, to investigate the factors influencing their attitude and survey their expectations vis-vis the doctor. Patients and methods. This is a prospective descriptive study conducted in four eye clinics in Lome from January 2013 to July 201]. It included all glaucoma patients aged 40 years and above who have been under medical treatment for at least 6 months, with no history of surgical treatment of glaucoma. The evaluation was performed on the basis of a questionnaire. Compliance was rated good, fair or poor according to the regularity of treatment, compliance with the prescribed dosage and schedule of instillations, good instillation technique and compliance with follow-up visits. Patients consented to participate in the survey. Results. A total of 107 patients responded to our questionnaire. There were 43 men and 64 women with a sex ratio (M/F) of 0.67. The mean age was 52.40 +/- 11.03 years. In total, 7.5% of patients were illiterate. Compliance rate was estimated good in 10.3% of cases, fair in 65.4% of cases, and poor in 24.3% of cases. Only the regularity of treatment, schedule adherence and good instillation technique, as well as compliance with monitoring visits were found as significant factors (P<0.05). Concerning patients' expectations vis-vis the doctor, 49.5% said they expected nothing from the doctor, 12.1% were hoping for advice and moral support, and 11.2% were hoping for the prescription of effective but less expensive eye drops. Conclusion. A good compliance rate was very low. The improvement of this compliance rate requires better information, education and communication for behavior change, and it also requires a higher quality of care and accessibility of anti-glaucoma drugs. (C) 2016 Elsevier Masson SAS. All rights reserved.

Michigan Screening and Intervention for Glaucoma and Eye Health Through Telemedicine (MI-SIGHT): Baseline Methodology for Implementing and Assessing a Community-based Program - Newman-Casey, PA; Musch, DC; Niziol, LM; Elam, AR; Zhang, J; Moroi, SE; Johnson, L; Kershaw, M; Saadine, J; Winter, S; Woodward, MA (JOURNAL OF GLAUCOMA, 2021)
Precis: The Michigan Screening and Intervention for Glaucoma and eye Health through Telemedicine (MI-SIGHT) program leverages community-engaged research, telemedicine, and health coaching to overcome key logistical and psychosocial barriers to improve glaucoma screening in underserved communities. Purpose: To describe the methodology of the implementation and evaluation of the MI-SIGHT Program. Methods: The MI-SIGHT Program uses community engagement, telemedicine, and health coaching to overcome key logistical and psychosocial barriers to glaucoma identification and care among underserved populations. The MI-SIGHT Program will be evaluated in 2 community clinics: Hamilton Community Health Network, a federally qualified health center in Flint, Michigan, and the Hope Clinic, a free clinic in Ypsilanti, Michigan. A Community Advisory Board including the research team and health care providers, administrators, and patients from both clinics will guide program implementation. An ophthalmic technician at the community clinics will conduct screening tests for glaucoma and eye disease. The data will be transmitted through electronic health record to be reviewed by an ophthalmologist who will make recommendations for follow-up care. The ophthalmic technician will conduct a return visit to fit low-or no-cost glasses, help arrange follow-up with an ophthalmologist, and provide education. Those diagnosed with glaucoma or suspected glaucoma will be randomized to standard education or personalized glaucoma education and coaching. Costs will be assessed. Results: The authors hypothesize that the MI-SIGHT Program will detect a higher prevalence rate of glaucoma than that found in the general population, improve upon presenting visual acuity, enhance vision-related quality of life, and demonstrate that personalized glaucoma education and coaching improve adherence to follow-up care. Conclusion: The MI-SIGHT Program may serve as a model for glaucoma screening and care in high-risk communities.

Preliminary survey of educational support for patients prescribed ocular hypotensive therapy - Gray, TA; Fenerty, C; Harper, R; Lee, A; Spencer, AF; Campbell, M; Henson, DB; Waterman, H (EYE, 2010)
Purpose To establish the impact of educational support on patients' knowledge of glaucoma and adherence, in preparation for an intervention study. Methods Structured observation encapsulated the educational support provided during clinical consultations and patient interviews captured the depth of glaucoma knowledge, problems associated with glaucoma therapy, and adherence issues. Results One hundred and thirty-eight patients completed the study. Education was didactic in nature, limited for many patients and inconsistent across clinics. Patients showed generally poor knowledge of glaucoma with a median score of 6 (range 0-16). A significant association was found between educational support and knowledge for newly prescribed patients (Kendall's tau =0.30, P = 0.003), but no association was found for follow-up patients (Kendall's tau = 0.11, P = 0.174). Only five (6%) patients admitted to a doctor that they did not adhere to their drop regimen, yet 75 (94%) reported at interview that they missed drops. Conclusions Although important, knowledge alone may not sufficiently improve adherence: a patient-centred approach based on ongoing support according to need may provide a more effective solution for this patient group. Eye (2010) 24, 1777-1786; doi:10.1038/eye.2010.121; published online 10 September 2010

Text Parsing-Based Identification of Patients with Poor Glaucoma Medication Adherence in the Electronic Health Record - Hamid, MS; Valicevic, A; Brenneman, B; Niziol, LM; Stein, JD; Newman-Casey, PA (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2021)
center dot PURPOSE: To assess the feasibility of automated text parsing screening of physician notes in the electronic health record (EHR) to identify glaucoma patients with poor medication compliance. center dot DESIGN: Cross-sectional study. center dot METHODS: An automated EHR extraction identified a cohort of patients at the University of Michigan with a diagnosis of glaucoma, & Dagger;40 years old, taking & Dagger;1 glaucoma medication, and having no cognitive impairment. Self reported medication adherence was assessed with 2 validated instruments: the Chang scale and the Morisky medication adherence scale. In tandem, a text parsing tool that abstracted data from the EHR was used to search for combinations of the following words in patient visit notes: & ldquo;not,& rdquo;& ldquo;non,& rdquo;& ldquo;n & rsquo;t,& rdquo;& ldquo;no,& rdquo;or & ldquo;poor & rdquo;accompanied by & ldquo;adherence,& rdquo;& ldquo;adherent, & ldquo;adhering,& rdquo;& ldquo;compliance,& rdquo;& ldquo;compliant,& rdquo;or & ldquo;complying.& rdquo;The proportion of patients with self-reported poor adherence was compared between the EHR extraction and text parsing identification using a Fisher exact test. center dot RESULTS: Among 736 participants, 20.0% (n = 147) self-reported poor adherence and 6.1% (n = 45) had EHR documentation of poor adherence (P < .0001). Using text parsing as a pre-screening tool, 22 of the 45 patients (48.9%) with non-adherence identified by text parsing also self-reported poor medication adherence compared to the 20.0% by self-report overall (P < .0001). center dot CONCLUSIONS: Text parsing physician notes to identify patients & rsquo; noncompliance to their medications identified a larger proportion of patients who then self reported poor medication adherence than an automated EHR pull alone but was limited by the small number of patients identified. Optimizing the documentation of medication adherence would maximize the utility of this automated approach to identify medication noncompliance. (Am J Ophthalmol 2021;222:54 & ndash;59. (c) 2020 Elsevier Inc. All rights reserved.)

Interventions to Promote Follow-up After Trabeculectomy Surgery in Rural Southern China A Randomized Clinical Trial - Yang, K; Jin, L; Li, L; Zeng, SM; Wei, RQ; Li, GR; Man, PY; Congdon, N (JAMA OPHTHALMOLOGY, 2016)
IMPORTANCE Follow-up after trabeculectomy surgery is important to surgical success, but little is known about the effect of interventions on improving follow-up in low-resource areas. OBJECTIVE To examine whether text message reminders and free eye medications improve follow-up after trabeculectomy in rural southern China. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial studied 222 consecutive patients undergoing trabeculectomy from October 1, 2014, through November 31, 2015, at 4 rural hospitals in Guangdong and Guangxi Provinces, China. Data from the intention-to-treat population were analyzed. INTERVENTIONS Patients undergoing trabeculectomy were randomized (1: 1) to receive text message reminders 3 days before appointments at 1 and 2 weeks and 1 month after surgery and free topical corticosteroid medication (US$5.30) at each visit or to standard follow-up without reminders or free medication. MAIN OUTCOMES AND MEASURE Follow-up at 1 month postoperatively. RESULTS Among 222 eligible patients, 13 (5.9%) refused and 209 (94.1%) were enrolled, with 106 (50.7%) randomized to the intervention group (mean [SD] age, 64.4 [12.7] years; 56 women [52.8%]) and 103 (49.3%) to the control group (mean [SD] age, 63.0 [12.7] years; 53 women [51.5%]). A total of 6 patients (2.9%) were unavailable for follow-up. Attendance at 1 month for the intervention group (59 of 102 [57.8%]) was significantly higher than for the control group (34 of 101 [33.7%]) (unadjusted relative risk [RR], 1.72; 95% CI, 1.13-2.63; P = .01). Factors associated with 1-month attendance in multiple regression models included intervention group membership (RR, 1.65; 95% CI, 1.08-2.53; P = .02) and being told to return for suture removal (RR, 1.80; 95% CI, 1.06-3.06; P = .03). One-month attendance among controls not told about suture removal was 3 of 31 (9.7%), whereas it was 44 of 68 (64.7%) among the intervention group with suture removal (unadjusted RR, 6.69; 95% CI, 2.08-21.6; P = .001). CONCLUSIONS AND RELEVANCE In this setting, low-cost interventions may significantly improve postoperative follow-up after glaucoma surgery, a potential opportunity for interventions known to improve surgical success.

Experience with Cosopt, the fixed combination of timolol and dorzolamide, after switch from free combination of timolol and dorzolamide, in Swiss ophthalmologists' offices - Gugleta, K; Orgul, S; Flammer, J (CURRENT MEDICAL RESEARCH AND OPINION, 2003)
Purpose: To analyse a response to the therapy switch from the concomitant application of beta-blocker and topical carbonic anhydrase inhibitor to the fixed combination of timolol and dorzolamide (Cosopt*) in glaucoma/ocular hypertensive patients under everyday, office-practice conditions. Patients and methods: The data source was a survey among practising ophthalmologists in Switzerland assessing their experience with glaucoma patients/ocular hypertensives put for the first time on the fixed combination of timolol and dorzolamide. A total of 98 patients underwent the therapy switch in at least one eye. The intraocular pressure (IOP) change between the baseline visit before switch to the timolol-dorzolamide fixed combination occurred, and the first follow-up control after the switch, served as an indicator of compliance. Results: The IOP decreased on average from 19.43+/-5.64 mmHg to 17.97+/-3.58 mmHg (p<0.01). The time to the follow-up visit ranged from 4 to 354 days, and the magnitude of IOP change demonstrated a significant dependence on the time to the follow-up visit, also when corrected for baseline 1013 level. A total of 87 (85.3%) continued on the timolol-dorzolamide fixed combination therapy after the first control visit. In 68 of these 98 patients the contralateral eyes underwent the same therapy switch, and their IOP followed an identical pattern of behaviour. Conclusion: The average IOP decrease of 1.5 mmHg upon therapy switch to the timolol-dorzolamide fixed combination suggests a better efficacy due to improved compliance. Shortterm compliance benefit seems to be more pronounced. The high timolol-dorzolamide fixed combination therapy continuation rate reflects an improvement in compliance and subjectively-perceived convenience.

Patient noncompliance in the managed care setting - The case of medical therapy for glaucoma - Gurwitz, JH; Yeomans, SM; Glynn, RJ; Lewis, BE; Levin, R; Avorn, J (MEDICAL CARE, 1998)
OBJECTIVES. The authors identify demographic and clinical characteristics associated with noncompliance in patients beginning medical therapy for the treatment of glaucoma in a managed care setting. METHODS. The authors describe a retrospective cohort study in a group-model health maintenance organization in Massachusetts. Patients were members of the health maintenance organization who were newly initiated on topical drug therapy to treat open-angle glaucoma during the period January 1, 1987 through December 31, 1990, who met eligibility requirements, and who had evidence of health services utilization for a 12-month follow-up period. For all study subjects, we determined the number of days without available therapy for glaucoma during the 12-month period. Study subjects who did not fill prescriptions adequate to provide medication to cover at least 80% of days during the study period were considered noncompliant. Logistic regression analysis was used to assess demographic and clinical factors independently associated with noncompliance among patients initiated on medical therapy for the treatment of glaucoma. RESULTS. Of 616 subjects who met inclusion criteria, 152 (24.7%; 95% confidence interval, 21.3%-28.1%) met the study definition for noncompliance. These patients had an average number of days without therapy during the 12-month study period of 103.9 +/- 70.0 days compared with 6.8 +/- 19.5 days for those categorized as compliant. Of a variety of selected demographic and clinical characteristics, having fewer visits with an ophthalmologist during the study period (<2) was most strongly related to noncompliance (odds ratio 2.99; 95% confidence interval 2.03, 4.40). There were no differences in average intraocular pressure between the compliant and noncompliant groups during the study period. CONCLUSIONS. Noncompliance with prescribed medical therapy for glaucoma was found to be common in a managed care setting characterized by essentially unrestricted access to health care and medications. It remains difficult to identify noncompliant patients based on demographic and clinical characteristics. The use of automated prescription data to identify noncompliant patients is feasible in large managed health care insurance programs where such data are collected routinely for administrative purposes.

Philadelphia Telemedicine Glaucoma Detection and Follow-up Study: Ocular Findings at Two Health Centers - Hark, L; Acito, M; Adeghate, J; Henderer, J; Okudolo, J; Malik, K; Molineaux, J; Eburuoh, R; Zhan, TT; Katz, LJ (JOURNAL OF HEALTH CARE FOR THE POOR AND UNDERSERVED, 2018)
Blindness from glaucoma can be prevented by early detection and treatment. Telemedicine improves access to treatment in high-risk populations that face barriers to receiving adequate ophthalmic care. We used a practice-based telemedicine screening model at two health centers. Telemedicine imaging of the fundus and optic nerve, followed by a complete eye exam at the same location for participants with abnormal findings, unreadable images, or ocular hypertension (OHTN), was performed. A total of 182 participants were screened, of whom 108 qualified for a complete eye exam. Of these, 62 (34.1%) had abnormal images, 12 (6.6%) had OHTN, and 34 (18.7%) had unreadable images. Eighty-nine of the 108 (82%) returned for the complete eye exam. Predominantly, participants were African American with glaucoma suspect and cataract. Screening location was an important factor for follow-up. Assessment of the fundus and optic disc using telemedicine resulted in early detection of glaucoma and other ocular pathology.

Risk Factors Associated with Progression to Blindness from Primary Open-Angle Glaucoma in an African-American Population - Pleet, A; Sulewski, M; Salowe, RJ; Fertig, R; Salinas, J; Rhodes, A; Merritt, W; Natesh, V; Huang, JY; Gudiseva, HV; Collins, DW; Chavali, VRM; et al. (OPHTHALMIC EPIDEMIOLOGY, 2016)
Purpose: To determine the risk factors associated with progression to blindness from primary open-angle glaucoma (POAG) in an African-American population. Methods: This study examined 2119 patients enrolled in the Primary Open-Angle African-American Glaucoma Genetics (POAAGG) study. A total of 59 eyes were identified as legally blind as a result of POAG (cases) and were age-and sex-matched to 59 non-blind eyes with glaucoma (controls). Chart reviews were performed to record known and suspected risk factors. Results: Cases were diagnosed with POAG at an earlier age than controls (p = 0.005). Of the 59 eyes of cases, 16 eyes (27.1%) presented with blindness at diagnosis. Cases had worse visual acuity (VA) at diagnosis (p < 0.0001), with VA worse than 20/40 conferring a 27 times higher risk of progression to blindness (p = 0.0005). Blind eyes also demonstrated more visual field defects (p = 0.01), higher pre-treatment intraocular pressure (IOP; p < 0.0001), and higher cup-to-disc ratio (p = 0.006) at diagnosis. IOP was less controlled in cases, and those with IOP 21 mmHg at more than 20% of follow-up visits were 73 times more likely to become blind (p < 0.0001). Cases missed a greater number of appointments per year (p = 0.003) and had non-adherence issues noted in their charts more often than controls (p = 0.03). However, other compliance data did not significantly differ between groups. Conclusion: Access to care, initial VA worse than 20/40, and poor control of IOP were the major risk factors associated with blindness from POAG. Future studies should examine earlier, more effective approaches to glaucoma screening as well as the role of genetics in these significantly younger patients who progress to blindness.

Barriers to follow-up for pediatric cataract surgery in Maharashtra, India: How regular follow-up is important for good outcome. The Miraj Pediatric Cataract Study II - Gogate, P; Patil, S; Kulkarni, A; Mahadik, A; Tamboli, R; Mane, R; Borah, R; Rao, GV (INDIAN JOURNAL OF OPHTHALMOLOGY, 2014)
Background: Regular follow up and amblyopia treatment are essential for good outcomes after pediatric cataract surgery. Aim: To study the regularity of follow-up after cataract surgery in children and to gauge the causes of poor compliance to follow up. Subjects: 262 children (393 cataracts) who underwent cataract surgery in 2004-8. Materials and Methods: The children were identified and examined in their homes and a "barriers to follow-up" questionnaire completed. Demographic data collected, visual acuity estimated, and ocular examination performed. Statistical Analysis: SPSS version 19. Results: Of the 262 children, only 53 (20.6%) had been regularly following up with any hospital, 209 (79.4%) had not. A total of 150 (57.3%) were boys and the average age was 13.23 years (Std Dev 5 yrs). Poor follow up was associated with the older age group (P < 0.001), less education of mother (P = 0.012), father's occupation (P = 0.031), how much money spent on travel (P = 0.033) and was it paid or free surgery (P = 0.001). It was not related to gender, numbers of children in family, ordinal status of child, and social strata. Distance and cost were major barriers, as was the inability of the eye care center to communicate the importance of follow up. A prospective follow-up visit showed that 93 children needed Nd: YAG LASER capsulotomy, 5 needed low vision aids, 4 contact lens, and 162 a change of spectacles. The average visual acuity improved in 150 (38.8%) eyes >1 line with regular follow-up. Conclusion: Regular follow-up is important and improves vision; eye care practitioners need to take special efforts to ensure better follow-up.

Cost of glaucoma treatment in a developing country over a 5-year period - Lazcano-Gomez, G; Ramos-Cadena, MD; Torres-Tamayo, M; de Oteyza, AH; Turati-Acosta, M; Jimenez-Roman, J (MEDICINE, 2016)
The aim of the study was to disclose a realistic estimate of primary open-angle glaucoma treatment, follow-up costs, and patients' monthly glaucoma-economic burden in an ophthalmology hospital in Mexico City. Prospective survey of 462 primary open-angle glaucoma patients from 2007 to 2012 was carried out. Costs from visits, glaucoma follow-up studies, laser, and glaucoma surgical procedures were obtained from hospital pricings. Education, employment, and monthly income were interrogated. Total cost was divided into hypotensive treatment cost, nonpharmacologic treatment cost (laser and surgeries), and follow-up studies and consults. Average wholesale price for drugs analyzed was obtained from IMS Health data; monthly cost was calculated using: Monthly cost =([average wholesale price/number of drops per eye dropper] x number of daily applications) x 30 days. Patients were classified according to their glaucoma severity, and data were analyzed based on monthly income (average annual exchange rate: 12.85 Mexican pesos = 1 USD). The mean age was 70 +/- 10 years, women = 81%, elementary school = 39%, and unemployed = 53%. Low-income group = 266 patients (57%), 146 with mild glaucoma; moderate-income group = 176 patients (38%), 81 with mild glaucoma; high-income group = 20 patients (4.3%), 10 with mild glaucoma. Patients' monthly average economic burden in glaucoma treatment: low-income patients = 61.5%, moderate-income patients = 19.5%, and high-income patients = 7.9%. Glaucoma-economic burden is substantial not only for health systems, but for the family and the patient. Therefore, screening plans for earlier diagnosis, and health policies that lessen the cost of disease management and increase adherence to treatment, and reduce the prevalence of blindness attributed to glaucoma are essential. These would improve quality of life, reduce personal and national expenditure, and help increase national economy.

The Wills Eye Glaucoma App: Interest of Patients and Their Caregivers in a Smartphone-based and Tablet-based Glaucoma Application - Waisbourd, M; Dhami, H; Zhou, C; Hsieh, M; Abichandani, P; Pro, MJ; Moster, MR; Katz, LJ; Hark, LA; Myers, JS (JOURNAL OF GLAUCOMA, 2016)
Purpose: To evaluate the interest of glaucoma patients and their caregivers in a smartphone-based and tablet-based glaucoma application (App), developed by the Wills Eye Glaucoma Research Center in collaboration with Drexel University. Materials and Methods: Cross-sectional survey of patients with glaucoma and their caregivers. Main outcome measures are answers to survey questions regarding how receptive participants are to using the Glaucoma App. Results: Fifty subjects completed the survey. The mean age (SD) was 59.5 (+/- 17.3) years. A total of 88.6% of the participants lived in a household with access to a smartphone or tablet. The majority (72.3%) of participants would consider downloading the Glaucoma App, and younger participants (< 65 y) were more likely to do so compared with their older (>= 65 y) counterparts, P=0.025. Participants were more likely to download the App if it was free of charge, compared with a version that costs $ 3, P=0.018. Although only about one third (37.8%) of participants used eye drop reminders, nearly 3 of 4 (72.9%) participants were receptive to using the automated reminder feature of the Glaucoma App. Conclusions: Glaucoma patients and their caregivers were very interested in using a Glaucoma App; however, many were not willing to spend $ 3 for an App they seem to value. The free Wills Eye Glaucoma App currently available on the Apple store, includes educational videos, eye drop and appointment reminders, medical and ocular data storage, visual field tutorial, and intraocular pressure tracker. These features aim to increase patients' level of knowledge about glaucoma and improve their adherence to medication and follow-up appointment recommendations.

Medication Adherence and Persistence of Open-Angle Glaucoma Patients in Korea: A Retrospective Study Using National Health Insurance Claims Data - Jang, Y; Jee, D; Lee, D; Choi, NK; Bae, S (INTERNATIONAL JOURNAL OF ENVIRONMENTAL RESEARCH AND PUBLIC HEALTH, 2021)
This study aimed to analyze medication adherence and persistence among open-angle glaucoma patients in Korea. A retrospective study was conducted using the Korean National Health Insurance (NHI) claims database from 2016 to 2019. Newly diagnosed open-angle glaucoma patients who were prescribed with the intraocular pressure (IOP)-lowering eyedrops were included. Adherence was measured using the medication possession ratio (MPR), and persistence was measured using the duration of therapy during the 24 month follow-up period. During the study period, 14,648 open-angle glaucoma patients were identified, and 3118 (21.3%) and 4481 patients (30.6%) were adherent to and persistent with their glaucoma treatment, respectively. The mean MPR was 48.8%, and the mean duration of therapy was 357.2 days. Logistic regression analysis showed that patients who are older, female, using prostaglandins as the index medication, and visiting secondary or tertiary hospitals were significantly associated with greater rates of adherence (odds ratio (OR) = 1.21, 1.12, 1.27, and 1.73, respectively) and persistence (OR = 1.11, 1.17, 1.16, 1.17, and 1.36, respectively) during the study period. Patients with open-angle glaucoma in Korea had substandard medication adherence and discontinued their treatment. Ophthalmologists should pay more attention to younger, male patients to improve adherence.

Potential Limitations of E-mail and Text Messaging in Improving Adherence in Glaucoma and Ocular Hypertension - Saeedi, OJ; Luzuriaga, C; Ellish, N; Robin, A (JOURNAL OF GLAUCOMA, 2015)
Purpose:To determine how receptive patients are to the use of e-mail and text message reminders for appointments and medications.Methods:We conducted a consecutive cross-sectional survey of eligible patients with glaucoma or ocular hypertension at a private glaucoma subspecialty practice with 3 locations from February 2011 to January 2012. Main outcome measures were answers to survey questions regarding how receptive patients are to e-mail and text messaging reminders for appointments and medications.Results:Of 989 patients, 404 (40.8%) patients reported that e-mail reminders would help remember appointments and 185 (18.7%) reported that they would help for medications. Among those with access to text messaging, 280 (68.9%) reported text messaging would help them remember appointments and 193 (47.5%) reported it would help with medications. Patients who reported e-mail would help them remember medications were more likely to live in an urban location [P=0.05, odds ratio (OR)=1.84], check the internet at least daily (P0.001, OR=1.04), check e-mail when not at home or the office (P=0.02, OR=1.62), and know how to open attachments (P=0.03, OR=1.87). Patients who reported that text messaging would help them remember their medications were more likely to be 40 or less (P0.001, OR=8.54) and African American (P<0.001, OR=2.59).Conclusions:E-mail and text messaging reminders currently may have a limited utility in improving adherence in the general glaucoma population but may be useful in younger patients with glaucoma.

Persistence of Topical Glaucoma Medication A Nationwide Population-Based Cohort Study in Taiwan - Hwang, DK; Liu, CJL; Pu, CY; Chou, YJ; Chou, P (JAMA OPHTHALMOLOGY, 2014)
IMPORTANCE Medication persistence is an important factor for treatment effect in patients with glaucoma. Evaluating risk factors for refill discontinuation might be helpful for improving persistence and preventing blindness in patients with glaucoma. OBJECTIVES To estimate the persistence rate with topical glaucoma medication 2 years after diagnosis and evaluate risk factors for nonpersistence among patients in Taiwan with open-angle glaucoma and ocular hypertension. DESIGN, SETTING, AND PARTICIPANTS A retrospective population-based study using claims data from the National Health Insurance Research Database. One million patients were randomly selected from the registered beneficiaries of the National Health Insurance Research Database in 2000. All patients with newly diagnosed open-angle glaucoma and ocular hypertension were included and followed up until December 31, 2008. Patients were included in the analysis only if they had follow-up data for more than 2 years after diagnosis. MAIN OUTCOMES AND MEASURES Nonpersistencewas defined as the patient not refilling any topical glaucoma medication for more than 90 days. Patient characteristics, prescription-related clinical factors, and physician and hospital characteristics were identified and considered in the analysis. The rate of persistence was estimated and risk factors for nonpersistence were investigated using Cox proportional regression models. RESULTS A total of 3134 patients were identified and observed in the study. After a 2-year follow-up, 759 patients (24.2%) persisted with their glaucoma medications. Multivariate analysis showed that patients' living or working areas (P<.001), number of glaucoma medications (P<.001), prescription of pilocarpine hydrochloride (adjusted ratio of persistence = 0.72; 95% CI, 0.59-0.88) or prostaglandin analogs (adjusted ratio of persistence = 2.04; 95% CI, 1.82-2.33), the year in which glaucoma diagnosis was made (adjusted ratios of persistence for patients whose condition was diagnosed after 2004 = 1.18; 95% CI, 1.09-1.27), sex of the main physicians (adjusted ratios of persistence for male ophthalmologists = 0.82; 95% CI, 0.74-0.90), treatment in hospitals (P<.001), and continuity of care index (P<.001) were associated with patients' persistence with glaucoma medications. CONCLUSIONS AND RELEVANCE The rate of persistence for glaucoma medications is low in Taiwan, although health care costs, including the cost of medication, are mostly covered by the nationwide health insurance system. This study suggests that factors other than cost, such as physician-patient relationship and patient education, may play an important role in the persistence of topical glaucoma medication. Copyright 2014 American Medical Association. All rights reserved.

Determinants of Medication Adherence to Topical Glaucoma Therapy - Dreer, LE; Girkin, C; Mansberger, SL (JOURNAL OF GLAUCOMA, 2012)
Introduction/Purpose: To determine the associations between medical, demographic, socioeconomic, and ocular factors and adherence to topical glaucoma ocular hypotensive therapy. Methods: One hundred sixteen patients with ocular hypertension or open-angle glaucoma from 2 tertiary glaucoma services participated in this prospective study. Adherence to ocular hypotensive therapy was measured using an electronic dose monitor (Travatan Dosing Aid, Alcon Laboratories Inc., Fort Worth, TX) and collected data at 3 months after enrollment. We used 3 different definitions of adherence: 1) Definition 1: the proportion of days taking the prescribed number of drops within 3 hours of the prescribed dosing time; 2) Definition 2: the proportion of days taking any drops within 3 hours of the prescribed dosing time; and 3) Definition 3: the proportion of days taking any drops within 6 hours of the prescribed dosing time. Univariate and multivariate models were used to determine the association between the 3 adherence definitions, medical, demographic, socioeconomic, and ocular factors at 3-month follow-up. The main outcome measures for this study were risk factors for poor objective medication adherence. Results: Adherence, using Definition 1, Definition 2, and Definition 3, was 64%, 75%, and 80%, respectively. Age, total number of other eye diseases, and race were significantly associated with full treatment adherence (Definition 1), with race alone significantly predicting 11% of full treatment adherence. For Definition 2, age, income, level of education, and total number of eye diseases were significantly associated with partial adherence (3 h), again race alone significantly predicted 15% of partial adherence (any drops within 3 h). For Definition 3, race, income, level of education, and total number of other eye diseases significantly predicted partial adherence (any drops within 6 h), both race and income predicted 19% of partial treatment adherence. Significant differences for adherence rates between patients of European descent and those of African descent were found for all 3 definitions with those who were less adherent more likely to be of African descent. Conclusions: Electronic dose monitors provide important information regarding adherence to topical ocular hypotensive medications in glaucoma patients. Electronic dose monitors show low adherence in a significant number of participants. Future studies are needed to determine the reasons for these differences in health behaviors related to glaucoma treatment, which should guide treatment of poor adherence with glaucoma therapy.

Primary open angle glaucoma in northern Nigeria: stage at presentation and acceptance of treatment - Abdull, MM; Gilbert, CC; Evans, J (BMC OPHTHALMOLOGY, 2015)
Background: To determine the stage of primary open angle glaucoma at presentation at a tertiary eye unit, to assess patient's knowledge of glaucoma and acceptance and subsequent adherence to treatment. Method: Information collected prospectively on new glaucoma patients aged 30 or more years included distance from residence and what they knew about glaucoma and its treatment. Treatment offered took account of disease severity and socioeconomic factors. Reasons for not accepting surgery were recorded. At follow up intraocular pressure (IOP) was measured and adherence to medication assessed verbally. Four categories of severity were defined based on visual acuity and visual fields defects in the worse eye. Results: 131 patients were recruited (mean age 52.8 years; 62 % male). Most attended because of symptoms (70 %). Mean IOP in affected eyes was 31.9+/-SD 12.4 and mean vertical cup: disc ratio was 0.8. 99 eyes (47 %) had a visual acuity of light perception or worse. Risk factors for advanced/end-stage disease were age > 50 years, living > 10 km from the hospital, some awareness of glaucoma, not being literate, being unemployed and presenting with symptoms. In multivariable analysis older age and poor knowledge of glaucoma remained independent risk factors. 75 were offered trabeculectomy: five agreed but only one underwent surgery. Reasons for rejecting surgery were fear (37 %), preferred medical treatment (27 %) and cost (15 %). 32/85 (24 %) participants started on topical medication attended follow up. 72 % reported excellent compliance but only 56 % of glaucomatous eyes had IOPs less than 21mmHg. Conclusions: To prevent glaucoma blindness strategies are required which promote earlier detection, with counselling to promote acceptance of and adherence to treatment.

Preoperative characteristics and compliance with follow-up after trabeculectomy surgery in rural southern China - Yang, K; Jin, L; Li, L; Zeng, SM; Dan, AH; Chen, TT; Wang, XQ; Li, GR; Congdon, N (BRITISH JOURNAL OF OPHTHALMOLOGY, 2017)
Purpose To evaluate preoperative characteristics and follow-up in rural China after trabeculectomy, the primary treatment for glaucoma there. Methods Patients undergoing trabeculectomy at 14 rural hospitals in Guangdong and Guangxi Provinces and their doctors completed questionnaires concerning clinical and sociodemographic information, transportation, and knowledge and attitudes about glaucoma. Follow-up after surgery was assessed as cumulative score (1 week: 10 points, 2 weeks: 7 points, 1 month: 5 points). Results Among 212 eligible patients, mean preoperative presenting acuity in the operative eye was 6/120, with 61.3% (n=130) blind (<= 6/60). Follow-up rates were 60.8% (129/212), 75.9% (161/212) and 26.9% (57/212) at 1 week, 2 weeks and 1 month, respectively. Patient predictors of poor follow-up included elementary education or less (OR=0.37, 95% CI 0.20 to 0.70, p=0.002), believing follow-up was not important (OR=0.62, 95% CI 0.41 to 0.94, p=0.02), lack of an accompanying person (OR=0.14, 95% CI 0.07 to 0.29, p<0.001), family annual income <US$800 (OR=0.28, 95% CI 0.11 to 0.72, p=0.008) and not requiring removal of scleral flap sutures postoperatively (OR=0.11, 95% CI 0.06 to 0.22, p<0.001). Age, sex, employment, travel distance/time/costs, patient preoperative clinical factors and physician factors were unassociated with follow-up. Conclusions Follow-up after 2 weeks was inadequate to provide optimal clinical care, and surgery is being applied too late to avoid blindness in the majority of patients. Earlier surgery, support for return visits and better explanations of the importance of follow-up are needed. Directing all patients to return for possible scleral flap suture removal may be a valid strategy to improve follow-up.

Adherence Studies with Short Follow-up Do Not Suffice for a Chronic Disease Like Open-Angle Glaucoma - Kashaf, MS; Jampel, HD (OPHTHALMOLOGY GLAUCOMA, 2020)

The Health Of Patients' Eyes (HOPE) Glaucoma study. The effectiveness of a 'glaucoma personal record' for newly diagnosed glaucoma patients: study protocol for a randomised controlled trial - Forbes, M; Fairlamb, H; Jonker, L (TRIALS, 2015)
Background: Glaucoma involves progressive optic nerve fibre loss, subsequently leading to irreversible and disabling visual field defects. In Europe, the prevalence of glaucoma is approximately 2.2 % of all people aged over 40 years; this equates to 12 million people. Glaucoma patients require regular lifelong follow-up, contributing to a large financial and resource burden for the National Health Service (NHS) in the UK. This study aims to determine whether providing newly diagnosed glaucoma patients with a personalised client-held eye health summary ('glaucoma personal record'), improves patients' knowledge of their glaucoma condition. A potential long-term benefit could be improved self-management and henceforth a slower rate of deterioration. Methods/Design: HOPE Glaucoma is a 3-year, prospective, parallel-group, pragmatic, single-centred, randomised controlled trial. An anticipated 122 adults, newly diagnosed with glaucoma (including ocular hypertension, suspected glaucoma and/or chronic open-angle glaucoma) will be recruited from a nurse-led ophthalmology outpatient clinic at a medium-sized NHS Trust. Participants will be randomly allocated to receive standard clinical care (control arm) or standard care plus a glaucoma personal record, detailing the current state of their condition (interventional arm). Participant assessments are designed to test whether provision of a glaucoma personal record 1) improves patient knowledge of glaucoma and 2) contributes to improvements in clinical outcomes, i.e. delay of visual field loss. The primary outcome measure is better client knowledge of glaucoma at the 9-12 month follow-up visit. Secondary outcome measures include the rate of visual field loss and patient-reported outcome measures on visual function (National Eye Institute VFQ - 25) measured at baseline, 9-12 months, 24 months and 36 months. Estimating a 20 % drop-out rate, the study will have 90 % power to detect a mean two-point difference in glaucoma knowledge score between groups at 5 % significance - based on two-sided Mann-Whitney U test. Discussion: If a glaucoma personal record is found to significantly improve glaucoma patients' knowledge of their condition, this intervention could potentially provide a low-cost, straightforward tool to educate and engage glaucoma patients. Subsequently, this could have the potential to increase patient self-management and therefore allow glaucoma patients to prolong their sight functionality for longer.

Pharmacotherapy Compliance in Patients with Ocular Hypertension or Primary Open-Angle Glaucoma - Traverso, CE; Walt, JG; Stern, LS; Dolgitser, M (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2009)
Purpose: The aim of this study was to compare rates of pharmacotherapy coverage in patients with ocular hypertension (OH) and patients with primary open-angle glaucoma (POAG). Methods: Retrospective cohort study analysis of a nationally representative, multimanaged health plan database (PharMetrics; 1998-2005) which included 4818 medicated OH patients and 52,985 medicated POAG patients with at least 1 year of continuous enrollment and at least one prescription for IOP-lowering medication during the first year of follow-up. Patients selected for the current study were nested within the cohort of OH patients (n = 36,767) and POAG patients (n = 72,412) previously reported. Of the previously reported OH cohort, only 13.1% of patients filled at least one prescription, as compared to 73.2% of the previously reported POAG cohort. Medication coverage was defined as the percent of days during which a patient was in possession of IOP-lowering therapy over the first year of follow-up (medication coverage = number of covered days/365). Compliant patients were defined as those with >= 75th percentile medication coverage. Results: POAG patients had slightly longer mean length of enrollment in the database (2.5 years, SD = 1.2) than did OH patients (2.4 years, SD = 1.1; P < 0.0001). The mean medication coverage was 50% for the POAG cohort (SD = 0.26) and 40% for the OH cohort (SD = 0.25; P < 0.0001). In multivariate models controlling for key covariates of interest, POAG patients were 1.9 (95% CI: 1.7 to 2.0) times more likely to be compliant with their pharmacotherapy than OH patients. Conclusion: In general, pharmacotherapy coverage was poor. Patients with POAG, a more severe condition, were significantly more covered with pharmacotherapies than patients with OH. It is important to implement strategies to help improve patient coverage prior to occurrence of more severe disease.

Laser iridotomy - Liebmann, JM; Ritch, R (OPHTHALMIC SURGERY AND LASERS, 1996)

Selective laser trabeculoplasty: Effect of number of preoperative topical glaucoma medications on pressure lowering and success rate - Bonnel, S; Fenolland, JR; Marill, AF; Gaillard, R; Rosenberg, R; Theillac, V; Mazharian, A; Giraud, JM; Renard, JP (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2017)
Purpose. - To evaluate the lowering of intraocular pressure (IOP) one year after SLT and to assess if differences are related to number of pre-SLT topical treatments in ocular hypertension (OHT) and primary open angle glaucoma (POAG) patients. Methods. - Retrospective review of 106 eyes of 13 OHT and 93 POAG patients treated by SLT for insufficient IOP control, allergy, discomfort or non-compliance to glaucoma medications, excluding patients with less than 1 year of follow-up after SLT. IOP was measured by applanation before and at 1, 6 and 12 months after SLT. Results. - Hundred and six eyes untreated (n = 13), or treated with one (n =25), two (n = 40) or three or more (n = 28) glaucoma medications were included. Mean IOP decreased from 19.4 +/- 3.6 mmHg preoperatively to 15.7+3.1 mmHg at 12 months, which corresponds to an average decrease of 18.8%. At 1 year, 62.2% (n = 66) were responders (IOP reduction >= 3 mmHg): 92.3% without medications (n = 12), 68% with one (n = 17), 57.5% with two (n = 23) and 50% with three or more medications (n = 14). Their average IOP decreased from 20.7 +/- 3.4 to 15.2 +/- 2.9 mmHg (26.6%), respectively from 20.8 +/- 2.6 to 15.8 +/- 3.2 (25%) without medications, 20.6+3.2 to 14.9+3.7 (27.3%) with one, 20.8 +/- 4.1 to 15.5 +/- 3.3 (25.1%) with two and 20.7 +/- 3.2 to 14.4 +/- 2.4 mmHg (29.7%) with three medications. Conclusions. - The number of responders seems to be greater in OHT and POAG patients without or with few glaucoma medications, but the IOP reduction seems to be similar regardless of the number of glaucoma medications. (C) 2016 Elsevier Masson SAS. All rights reserved.

Patient Question-Asking About Glaucoma and Glaucoma Medications During Videotaped Medical Visits - Sleath, B; Sayner, R; Blalock, SJ; Carpenter, DM; Muir, KW; Hartnett, ME; Tudor, G; Lawrence, S; Giangiacomo, AL; Robin, AL (HEALTH COMMUNICATION, 2015)
We applied the ecologic model of communication in medical consultations to examine how patient, physician, and situational/contextual factors are associated with whether patients ask one or more questions about glaucoma and glaucoma medications during visits to ophthalmologists. Patients with glaucoma who were newly prescribed or already on glaucoma medications were recruited at six ophthalmology clinics. Patients' visits with their doctors were video-recorded and patients were interviewed after visits. Generalized estimating equations were used to analyze the data. Two hundred and seventy-nine patients participated. Patients asked one or more questions about glaucoma during 59% of visits and about glaucoma medications during 48% of visits. Patients who were newly prescribed glaucoma medications were significantly more likely to ask one or more questions about glaucoma and glaucoma medications. Whether providers asked patients if they had questions was not significantly associated with patient question-asking. Patients were significantly more likely to ask older providers questions about glaucoma medications and female providers questions about glaucoma. Eye care providers should encourage glaucoma patients to ask questions during their medical visits.

Noncompliance with medical treatment among glaucoma patients in Oman - A cross-sectional descriptive study - Khandekar, R; Shama, ME; Mohammed, AJ (OPHTHALMIC EPIDEMIOLOGY, 2005)
Purpose: Glaucoma is a priority eye disease in Oman. In order to revise the existing policies for eye care, a study was conducted to review the noncompliance rates among glaucoma patients. Methods: Using the random method, we selected 105 glaucoma patients from among those visiting glaucoma clinics during 2003. They were interviewed by trained health professionals. A closed-ended questionnaire with 42 questions was used to note their responses. The questions dealt with their personal characteristics along with the patients' glaucoma treatment and their knowledge of and attitudes towards different components of noncompliance with medical treatment. The field staffs also observed the 'practice' of instilling placebo eyedrops. The responses were analyzed to grade the compliance, knowledge, attitude and practice of each patient. Results: Excellent compliance was found in 26 patients. Discontinuation of medication in the past was reported by 87 patients. Missing instillation of eyedrops and irregular visits to the ophthalmologist were noted in 10 and 14 patients, respectively. Adequate knowledge about glaucoma and its complications was negatively associated with noncompliance [RR 2.05 (95% CI 1.07-3.93)]. Conclusions: The high rates of noncompliance among glaucoma patients in Oman demand a systematic programmed approach. Longitudinal studies are needed to confirm the causal association between noncompliance and Knowledge, Attitude and Practice. Health education, communication while dispensing medication, reducing the frequency of medication and using devices for the easy administration of eyedrops could further improve compliance.

Socioeconomics of long-term glaucoma therapy in India - Nayak, B; Gupta, S; Kumar, G; Dada, T; Gupta, V; Sihota, R (INDIAN JOURNAL OF OPHTHALMOLOGY, 2015)
Purpose: To determine the socioeconomic impact of long-term glaucoma therapy. Materials and Methods: One hundred and fifty consecutive glaucoma patients on medical therapy, following up at our glaucoma service for at least 6 months were recruited. A questionnaire regarding monthly income, cost of glaucoma medications prescribed, availability of medications, travel time, time spent in review clinics, compliance, education status, medical insurance and systemic or local side-effects was administered. Results: The patients seen at the tertiary government hospital had an average monthly income of Rs. 10,912/- (range: Rs. 500/- to Rs. 50,000/-) with approximately 56% of the patients having an income of less than Rs. 5000/month. The expenditure on anti-glaucoma medications ranged from 0.3% in high income group to 123% of their monthly gross income in low income group (P < 0.0001). The total expenditure including travel, stay, and loss of wages of patients and accompanying persons ranged from 1.6% in high income group to 137% of the monthly income in low income group (P < 0.0001). Mean time required for a glaucoma clinic visit was 15.66 h, (range: 6-96 h/month). About 2.7% experienced systemic side-effects and 21.3% had complaints of ocular adverse effects. About 90% of the patients were compliant. 92% were not covered by any insurance plan/government reimbursement for their treatment. Conclusions: Medical therapy for glaucoma is an economic burden to many patients and should be individualized, according to the socioeconomic status, availability of drugs and the required distance to travel to reach the specialist clinics.

Association of an Electronic Health Record-Linked Glaucoma Medical Reminder With Patient Satisfaction - Varadaraj, V; Friedman, DS; Boland, MV (JAMA OPHTHALMOLOGY, 2019)
IMPORTANCE While dosing reminders for glaucoma medications have been shown to increase drug adherence, an outstanding limitation preventing broad adoption is difficulty linking reminders to medication in each patient's electronic health record (EHR). OBJECTIVE To examine the feasibility of implementing an EHR-linked, automated reminder system for glaucoma medications and assess patient satisfaction with it. DESIGN, SETTING. AND PARTICIPANTS In this prospective, cross-sectional study, patients receiving glaucoma medications were recruited from a university-based glaucoma clinic from April 2017 to January 2018. Analysis began in February 2018. EXPOSURES A web-based application was added to the EHR patient portal, allowing patients to configure telecommunication-based reminders for their glaucoma medications. For all potential participants, basic information was collected to determine risk of nonadherence with glaucoma medications. Those consenting to participate then answered questions on medication adherence, reminders, and their likelihood of using EHR-linked reminders. They then configured reminders using the EHR patient portal. After 3 months, they answered questions about their satisfaction with the system. MAIN OUTCOMES AND MEASURES Proportions of patients and high-risk patients willing to use the reminders, and patient satisfaction with the system. RESULTS Of 147 patients approached, 100 (68%) agreed to participate, of whom the majority were men (54 [54%]) and white (51 [51%]), with a mean (SD) age of 65 (12.4) years. There were no differences between those willing and unwilling to participate, except for a slightly lower self-reported medication adherence rate among those who participated (mean [SD], 91% [13.6%] vs 97% [6.0%]). Based on a previously validated risk assessment score, 9% (9 of 100) of participants were categorized as being at high risk for poor adherence (>= 50% probability of nonadherence) compared with 11% (5 of 47) of nonparticipants. Of 100 participants, 94 ultimately configured reminders, of whom 89 (95%) completed follow-up. On follow-up, 74% (n = 66; 95% CI, 65-83) of participants found the reminders to be useful, 15% (n = 13) were neutral, and 11% (n = 10) found them not useful. Most participants (72 [81%]; 95% CI, 77-85) had help configuring reminders. CONCLUSIONS AND RELEVANCE Electronic health records-linked reminders had good uptake and were well received among patients at a tertiary glaucoma clinic. These portals may represent a new and convenient method of allowing patients to link their glaucoma medications to automated reminders, although the generalizability of these results and the effect on glaucoma outcomes remains unknown.

Contact lens complications among wearers in Ghana - Kobia-Acquah, E; Akowuah, PK; Antwi-Adjei, EK; Forkuo, PM; Koomson, NY; Odotei, SO; Alabi, E; Donkor, R (CONTACT LENS & ANTERIOR EYE, 2021)
Purpose: Contact lens (CL) practice is relatively new in Ghana; a country where the geographical location (warm climate) lends itself to harsh environmental conditions (high humidity) known to influence CL wear. Recent studies suggest an increase in CL wear (corrective and cosmetic), yet, there are no studies about CL-related complications. This study sought to determine the complications associated with CL wear in Ghana. Methods: This was a retrospective cohort study. The medical records of contact lens wearers from five CL clinics in the two largest metropolises in Ghana, Accra and Kumasi, were reviewed. Included in the study were records of individuals who visited the clinics within the period of 2013-2016. Data on patients with contact lens-related complications were analyzed. Results: The prevalence of CL complications was 29.06 %. The mean +/- SD age of patients with CL complications was 35 +/- 15 years. Contact lens complications were more common in females (52.90 %). The majority of complications were in soft contact lens wearers (82.35 %). Refractive error correction was the most common indication for CL wear (61.76 %) among those with complications, followed by keratoconus (14.71 %), scarred blind eye (14.71 %), corneal ulcer (5.88 %) and anterior staphyloma (2.94 %). Contact lens complications reported were giant papillary conjunctivitis (41.18 %), corneal infiltrates (23.53 %), bacterial keratitis (14.71 %), corneal abrasion (11.76 %), dry eye (5.88 %) and corneal oedema (2.94 %). The causes of CL complication were inappropriate lens cleaning (29.41 %), poor hygiene (23.53 %), overnight contact lens wear (17.64 %), poor lens fit (14.71 %) and reaction to contact lens solution (14.71 %). Conclusion: Contact lens complications were more common in soft contact lens wearers in Ghana. Giant papillary conjunctivitis was the most common contact lens complication reported. Adherence to CL wear care regimen and good personal hygiene may prevent the majority of CL complications observed in Ghana.

Monitoring adherence rates in glaucoma patients using the Travatan Dosing Aid. A 6-month study comparing patients on travoprost 0.004% and patients on travoprost 0.004%/timolol 0.5% fixed combination - Rossi, GCM; Pasinetti, GM; Scudeller, L; Tinelli, C; Milano, G; Bianchi, PE (EXPERT OPINION ON PHARMACOTHERAPY, 2010)
Research Design and Methods: Sixth-month cohort study; fifty-six Caucasian, primary open-angle glaucoma patients on travoprost (T) or travoprost/timolol fixed combination (TTFC) monotherapy were submitted to four visits: at baseline and months 1, 3 and 6 (M1, M3, M6). Adherence was recorded with TDA and classified as 'high' if greater than 90%. Self-reported and physician-presumed adherence data were collected. Kruskall-Wallis and Fisher's exact tests were applied. Results: Thirty-two patients (54.2%) were treated with T. Age, sex, level of schooling, presence of systemic comorbidities, duration of current therapy and IOP were similar between T and TTFC. Seventeen subjects (30.3%) recorded high adherence at every visit, 13 (23.2%) at two visits, 26 (46.4%) otherwise. Adherence was maintained over time with a slight decrease from month 1 to month 6 without statistical differences within and between groups. Adherence was statistically influenced by age (p = 0.007) and duration of therapy (p = 0.004). Conclusion: The typical nonadherent patient is elderly. TDA records indicate that only a minority of patients are really adherent: predictive models to screen for poor adherence are needed.

Compliance With Primary Open-angle Glaucoma and Primary Open-angle Glaucoma Suspect Preferred Practice Patterns in a Retail-based Eye Clinic - Stanley, J; Huisingh, CE; Swain, TA; McGwin, G; Owsley, C; Girkin, CA; Rhodes, LA (JOURNAL OF GLAUCOMA, 2018)
Purpose: To determine the level of adherence to the American Academy of Ophthalmology preferred practice pattern (PPP) guidelines for quality primary open-angle glaucoma (POAG) and POAG suspect (POAGS) care among retail-based optometrists. Methods: Patients with a diagnosis of POAG or POAGS who participated in a telemedicine pilot project were included. Patients' charts were evaluated for 15 elements of PPP guidelines for glaucoma care. Results were further stratified by number of follow-up visits and diagnosis. Results: Of 360 identified patients, 10 elements were documented in over 98%. Documentation of the remaining 5 components was as follows: dilated fundus examination 91.1%, central corneal thickness (CCT) 88.6%, visual field 78.9%, gonioscopy 47.5%, and target intraocular pressure (IOP) 15.6%. in total, 32.8% of patients were seen once, whereas the remaining 67.2% had multiple visits. In patients with multiple visits, providers were more likely to document systemic history (100.0% vs. 97.5%; P=0.0346), review of systems (100.0% vs. 97.5%; P=0.0346), gonioscopy (60.0% vs. 22.0%; P<0.001), CCT (94.2% vs. 77.1%; P<0.001), visual field (97.5% vs. 40.7%; P<0.001), and target IOP (22.4% vs. 1.7%; P<0.001) compared with single visit patients. In stratifying results by diagnosis, POAG patients more often received visual field testing (92.7% vs. 68.9%; P<0.001) and had an established target IOP (35.1% vs. 1.4%; P<0.001) compared with POAGS patients. Conclusions: Compliance with PPP guidelines for glaucoma care was very high for most elements but lower for performing dilated fundus examination, CCT, visual field, gonioscopy, and target IOP. This study highlights deficiencies in care likely to hamper the detection of glaucoma progression.

Philadelphia Telemedicine Glaucoma Detection and Follow-up Study: confirmation between eye screening and comprehensive eye examination diagnoses - Hark, LA; Myers, JS; Ines, A; Jiang, A; Rahmatnejad, K; Zhan, TT; Leiby, BE; Hegarty, S; Fudemberg, SJ; Mantravadi, AV; Waisbourd, M; Henderer, JD; et al. (BRITISH JOURNAL OF OPHTHALMOLOGY, 2019)
Aims To evaluate agreement between ocular findings of a telemedicine eye screening (visit 1) with diagnoses of a comprehensive eye examination (visit 2). Methods A primary care practice (PCP)-based telemedicine screening programme incorporating fundus photography, intraocular pressure (IOP) and clinical information was conducted. Eligible individuals were African American, Hispanic/Latino or Asian over the age of 40; Caucasian individuals over age 65; and adults of any ethnicity over age 40 with a family history of glaucoma or diabetes. Participants with abnormal images or elevated IOP were invited back for a complete eye examination. Both visit 1 and visit 2 were conducted at participants' local PCP. Ocular findings at visit 1 and eye examination diagnoses at visit 2 are presented, including a cost analysis. Results Of 906 participants who attended visit 1, 536 were invited to visit 2 due to ocular findings or unreadable images. Among the 347 (64.9%) who attended visit 2, 280 (80.7%) were diagnosed with at least one ocular condition. Participants were predominately women (59.9%) and African American (65.6%), with a mean age (+/- SD) of 60.6 +/- 11.0 years. A high diagnostic confirmation rate (86.0%) was found between visit 1 and visit 2 for any ocular finding. Of 183 with suspicious nerves at visit 1, 143 (78.1%) were diagnosed as glaucoma or glaucoma suspects at visit 2. Conclusions This screening model may be adapted and scaled nationally and internationally. Referral to an ophthalmologist is warranted if abnormal or unreadable fundus images are detected or IOP is >21 mm Hg.

Surgical Outcomes of a New Low-Cost Nonvalved Glaucoma Drainage Device in Refractory Glaucoma: Results at 1 Year - Ray, VP; Rao, DP (JOURNAL OF GLAUCOMA, 2018)
Purpose: The purpose of this study was to report the early outcomes in terms of efficacy and safety of a new, indigenously manufactured, low-cost nonvalved drainage device [AADI (Aurolab Aqueous Drainage Implant)] in the management of refractory glaucoma in the Indian population. Methods: Retrospective review of consecutive patients older than 12 years, who underwent glaucoma drainage device surgery (GDD) using AADI, by a single fellowship-trained surgeon, between January 2014 and December 2016, who had at least 3 months of documented post-op follow-up. Outcome measures: Primary-intraocular pressure (IOP). Secondary-number of antiglaucoma medication (AGM), LogMAR best corrected visual acuity (BCVA), and complications. Complete success was defined as IOP >= 5 mm Hg and <= 21 mm Hg or reduction of IOP by >= 20% from baseline without AGM; qualified success with use of AGM. Failure was defined as inability to meet IOP criteria, loss of perception of light, explantation or any additional glaucoma surgery. Results: A total of 54 eyes of 51 patients were included. Mean follow up was 12.1 +/- 6.3 months. The IOP and number of AGM required was significantly lower at every visit postoperatively (P<0.001). Median LogMAR BCVA remained unchanged (P=0.5). Complications occurred in 22 patients (40.7%). Complete success was seen in 66.6%; overall success was 92.6%. Conclusions: New nonvalved GDD (AADI) surgery is effective in reducing IOP and need for AGM with a safety profile similar to published reports of prevailing GDDs. It thus has the ability to breach the cost barrier in low-to-middle income countries; further follow-up is required to determine sustainability over time.

Cost Effectiveness of Travoprost versus a Fixed Combination of Latanoprost/Timolol in Patients with Ocular Hypertension or Glaucoma Analysis Based on the UK General Practitioner Research Database - De Natale, R; Lafuma, A; Berdeaux, G (CLINICAL DRUG INVESTIGATION, 2009)
Objective: This study aimed to compare the cost effectiveness of travoprost versus a fixed combination of latanoprost/timolol as first-line therapies for ocular hypertension or glaucoma. Methods: Patient charts were extracted from the UK General Practitioner Research Database. Patients with ocular hypertension or glaucoma who received first-line treatment with either travoprost or latanoprost/timolol and were followed up for > 6 months were included. Treatment failure was defined as a treatment change or a glaucoma intervention (laser therapy or surgery). Time to treatment failure was compared using a Cox model and adjusted by the propensity score method. Results: Eligible patients received either travoprost (n = 639) or latanoprost/ timolol (n = 176). Their mean age was 70 years at diagnosis and 48.2% of patients were male. Patient characteristics did not differ significantly between treatment groups. Treatment failure rates at 1 year were 31.3% (travoprost) and 39.4% (latanoprost/timolol) and yielded a hazard ratio for failure in favour of travoprost (0.75; p < 0.04) after adjusting for age, sex, co-morbidities and duration of follow-up. Adjusted annual costs of glaucoma management were significantly (p < 0.001) less with travoprost (215.86) pound than with latanoprost/timolol (327.83) pound. Conclusions: In everyday practice, travoprost was maintained longer than latanoprost/timolol as first-line therapy for glaucoma. The mean daily costs of travoprost were 50.8% less per patient than those of latanoprost/timolol. Despite adjustments, these results might be confounded, at least partially, by disease severity.

Characterization of patients who report compliant and non-compliant overnight wear of soft contact lenses - Jansen, ME; Chalmers, R; Mitchell, GL; Kinoshita, BT; Lam, DY; McMahon, TT; Richdale, K; Sorbara, L; Wagner, H (CONTACT LENS & ANTERIOR EYE, 2011)
Purpose: To describe compliant and non-compliant overnight wear (EW) of soft contact lenses from a large observational study. Methods: A retrospective chart review of 3211 SCL patients with known EW status (aged 8-33 yrs, SCL power +8.00 to -12.00 D) captured data from 10,516 clinical visits (2006-2009). Status of EW was either daily wear (DW), compliant EW (overnight wear of US Food & Drug Administration (US FDA) EW-approved lenses), non-compliant EW (overnight wear of DW-approved lenses). The effect of demographic and clinical characteristics on the likelihood of reporting EW was examined using logistic regression. Additionally, the effect of these same characteristics on the likelihood of non-compliant EW was assessed with logistic models. Results: Eight-hundred and eight patients (25.2%) reported EW. Non-compliant EW was reported by 6% of wearers (13 hydrogel, 2 silicone hydrogel brands) In multivariate models, patient age and lens replacement schedule were significant factors for EW (vs. DW) and for non-compliant (vs. compliant) EW (p < 0.0001). Other factors significantly related to EW were gender, smoking, lens material, sphere power, and years of CL wear (p < 0.007, all). Conclusions: Young people (ages 18-25 yrs), males, smokers, myopes, silicone hydrogel lens wearers and patients with >1 yr of CL wear were significantly more likely to report EW. Non-compliant EW occurred often in young people and daily disposable wearers, though many brands had non-compliant EW use. Understanding who is likely to wear EW and non-compliant EW will help clinicians pointedly counsel patients more at risk on best practices with EW. (C) 2011 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.

Changes in adherence and associated factors among patients on newly introduced prostaglandin analog and timolol fixed-combination therapy - Hasebe, Y; Kashiwagi, K; Tsumura, T; Suzuki, Y; Yoshikawa, K; Suzumura, H; Maeda, T; Takeda, R; Saito, H; Araie, M (PATIENT PREFERENCE AND ADHERENCE, 2018)
Purpose: We investigated patient adherence and factors related to a newly introduced prostaglandin analog and timolol fixed-combination eye drops (PGTFC). Patients and methods: The Glaucoma Research on Adherence to fixed-Combination Eye drops in Japan (GRACE) study group performed a nationwide prospective questionnaire survey. Participants in this study were patients with glaucoma who were scheduled to receive any type of PGTFC for the first time. The participants answered a questionnaire on the day of PGTFC introduction and again at a return visit 4-6 weeks after PGTFC introduction. The physicians in charge were asked to complete a separate questionnaire on the day of PGTFC introduction. One of two leaflets was randomly delivered to each participant before the description of the PGTFC. One leaflet explained how to correctly instill the eye drops, and the other explained the clinical meaning of intraocular pressure reduction in addition to explaining how to correctly instill the eye drops. Nonadherence was defined as forgetting to instill the eye drops one or more times during the week before the return visit. Results: In total, 3,597 patients (age, 68.4 +/- 12.2 years) met the study protocol requirements. PGTFC introduction significantly reduced the number of antiglaucoma eye drops from 1.93 +/- 0.78 to 1.34 +/- 0.54 (P<0.0001) and significantly improved adherence (P<0.00001). Factors significantly associated with nonadherence at the return visit included a history of nonadherence as reported by either the patient or their physician before introduction, acceptable instillation times as reported by the patient, and burdensome eye drop instillation as reported by the patient. No significant difference was observed between the two leaflets in terms of their effects on adherence. Conclusion: PGTFC significantly improved adherence and some of the factors that were significantly associated with adherence.

Silicone punctal plugs as an adjunctive therapy for open-angle glaucoma and ocular hypertension - Opitz, DL; Tung, S; Jang, US; Park, JJ (CLINICAL AND EXPERIMENTAL OPTOMETRY, 2011)
Background: Primary open-angle glaucoma is a progressive optic neuropathy that can cause an irreversible loss of vision. A reduction in intraocular pressure (IOP) is beneficial in slowing or halting its progression. Once-per-day monotherapy glaucoma medications, such as prostaglandin analogues, are effective in lowering IOP while maintaining patients' adherence. Achieving the desired target IOP often requires multiple medications. The present study evaluates punctal occlusion of both the inferior and superior puncta as an adjunctive therapy to travoprost ophthalmic solution 0.004% for patients with primary open-angle glaucoma or ocular hypertension in order to reduce IOP. Methods: Thirteen patients who were using travoprost 0.004% ophthalmic solution for the treatment of open-angle glaucoma or ocular hypertension received silicone punctal plugs in the superior and inferior puncta of one eye. After one month, the IOP was remeasured. The percentage change of the IOP from the baseline was analysed by using a paired sample t-test. Results: The mean baseline IOP was 19.82 +/- 1.19 mmHg in the test eyes and 18.32 +/- 1.11 mmHg in the control eyes. The mean IOP at the one-month visit was 18.23 +/- 1.17 mmHg in the test eyes and 18.45 +/- 1.04 mmHg in the control eyes. The test eyes demonstrated a decrease in IOP of 1.59 (+/- 0.95) mmHg from the baseline, or a 6.82 per cent decrease in the IOP from the baseline. The control eyes had an increase in IOP of 0.14 +/- 0.77 mmHg from the baseline, or a 1.91 per cent increase in the IOP. The relative difference in the IOP between the test eyes and the control eyes at the one-month visit was 1.73 mmHg, or 8.74 per cent. Conclusion: Based on the results of this study, punctal occlusion offers a statistically and clinically significant decrease in IOP when it is used as an adjunctive therapy to travoprost 0.004% for patients who are suffering from open-angle glaucoma or ocular hypertension.

Long-term follow-up after implantation of a telemetric intraocular pressure sensor in patients with glaucoma: a safety report - Koutsonas, A; Walter, P; Roessler, G; Plange, N (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2018)
ImportanceTo investigate the long-term safety of a novel intraocular telemetric pressure sensor. BackgroundAcquisition of accurate intraocular pressure (IOP) data is vital for sufficient medical care of glaucoma patients. Non-invasive self-tonometry with a telemetric IOP sensor can provide important information regarding the individual IOP profile. DesignRetrospective analysis of long-term follow-up data assessed during outpatient visits in a university hospital. ParticipantsSix patients with open-angle glaucoma were included. Unfortunately, one patient passed away shortly after completion of the original 1-year study. MethodsWithin the scope of a prospective 1-year pilot clinical trial, a telemetric IOP sensor was inserted into the ciliary sulcus after intracapsular lens implantation during planned cataract surgery. Patients were regularly examined as outpatients even beyond the duration of the 1-year study. Data concerning sensor functionality, safety parameters and home self-tonometry were assessed. Main Outcome MeasuresLong-term sensor functionality and safety. ResultsSensor measurements were always successful in every patient. Additionally, home self-tonometry was conducted without any problems by every patient. The average follow-up period was 37.5 months (21-50months). During this period, the average number of IOP measurements performed per patient was 1273 (223-2884 measurements). No severe adverse events were reported. A varying degree of pupillary distortion was observed after 6-12months in every patient; this remained unchanged thereafter with only one exception. Conclusions and RelevanceTelemetric IOP sensors showed good functionality and tolerability during long-term follow-up. Non-invasive self-tonometry with a telemetric IOP sensor can provide useful additional data for future monitoring of patients with glaucoma.

Lifetime visual disability in open-angle glaucoma and ocular hypertension - Forsman, E; Kivela, T; Vesti, E (JOURNAL OF GLAUCOMA, 2007)
Purpose: To study how many of the patients with treated glaucoma or ocular hypertension go blind during their lifetime and which factors are associated with blindness. Patients: The data on 106 consecutive patients who had died between 1991 and 2002 was retrospectively evaluated. At diagnosis 39 patients had primary open-angle glaucoma, 27 had exfoliation glaucoma, and 40 had ocular hypertension. Methods: Clinical records and causes of death were reviewed. Visual disability at the last visit before death was evaluated. Outcome measures were visual handicap and blindness based on visual acuity and/or visual fields. Results: At the last visit, 17 patients [16%, 95% confidence interval (CI) 9-23] were visually handicapped. Thirteen patients (14%) were bilaterally blind. Glaucoma was the cause of blindness in one or both eyes in 16 patients (15%, 95% CI 8-22) and in both eyes in 6 patients (6%, 95% CI 1-10). In the analysis of only I eye of each patient, the cumulative incidence of glaucoma-caused blindness was 6% (95% CI 2-11) at 5 years, 9% (95% CI 4-15) at 10 years, and 15% (95% CI 9-23) at 15 years. An advanced stage of glaucoma at diagnosis, fluctuation in intraocular pressure during treatment, the presence of exfoliation syndrome, and poor patient compliance increased the occurrence of blindness. Positive family history of glaucoma and vascular causes of death had no effect on visual outcome. Conclusions: Glaucoma-caused blindness was associated with an advanced stage of glaucoma at diagnosis, fluctuation of intraocular pressure during treatment, the presence of exfoliation syndrome, and poor patient compliance. The risk of going blind from glaucoma in both eyes was 6%.

Prescribing Trends in a Glaucoma Clinic and Adherence to EGS Guidelines: A Retrospective, Non-Interventional, Single-Center UK Study - Fajgenbaum, M; Ansari, E (ADVANCES IN THERAPY, 2017)
Introduction: The purpose of this study was to determine prescribing trends in a specialist glaucoma clinic in the UK. Specifically, the aims were to determine which drugs were prescribed as first-, second-, and third-line treatment, the persistence of first-, second-, and third-line treatment regimens, and the proportion of treatment decisions conforming to the European Glaucoma Society (EGS) guidelines. A retrospective, non-interventional, single-center, case-note review was performed on a cohort of consecutive patients presenting to a specialist glaucoma clinic for follow-up. Inclusion criteria for the study were (1) a diagnosis of primary open-angle glaucoma or ocular hypertension, (2) glaucoma management entirely within the unit, and (3) minimum of 2 years of follow-up. A total of 114 case notes met the inclusion criteria. Mean age was 71 years (range 40-95 years). Mean length of follow-up was 56 months (range 24-180 months). Prostaglandin analogues (PGA) were the most popular first-line treatment in 73% of patients. As second-line treatment, PGA were again the predominant class, prescribed in 87% of cases, whereas beta-blockers (BB) were prescribed in 70% of cases. Carbonic anhydrase inhibitors (CAI) and alpha-2 agonists (AA) were more popular in third-line regimens. Second-line treatment was introduced at a mean of 28.0 months after first-line treatment (range 1-120 months, 95% CI 22.1-33.9 months). Third-line treatment was introduced at a mean of 22.9 months after second-line treatment (range 1-96 months, 95% CI 17.1-28.8 months). Breaches to EGS guidelines were most common for third-line treatment and included duplication of drug classes. There was a clear hierarchy of PGA as first-line, BB as second-line, while CAI and AA were considered third-line choices. First-line choices were generally in line with EGS guidelines. There was a tendency to breach guidelines by escalating treatment in dual steps rather than single steps (especially in third-line treatment). Combination drops were popular. In third-line treatment there was an increased incidence of prescribing errors. This data is important in terms of informing patients of the expected treatment course, to remind clinicians about best practice, and also to guide comparisons of cost-effectiveness with other treatment modalities.

The impact of SIGN glaucoma guidelines on false-positive referrals from community optometrists in Central Scotland - Sii, S; Nasser, A; Loo, CY; Croghan, C; Rotchford, A; Agarwal, PK (BRITISH JOURNAL OF OPHTHALMOLOGY, 2019)
Background Since the introduction of National Institute for Health and Care Excellence glaucoma guidelines 2009, the number of referrals from community optometrists to hospital eye services has increased across the UK, resulting in increase in first visit discharge rates (FVDRs). Aim To assess the impact of Scottish Intercollegiate Guidelines Network (SIGN) 144 on quality of referrals from community optometrists. Methodology A retrospective study of patient records who attended as new adult glaucoma referrals to clinics in Princess Alexandra Eye Pavilion, Edinburgh, and in Greater Glasgow and Clyde, was carried out across October-November 2014 (group 1) and September-October 2016 (group 2), before and after the introduction of SIGN 144. The primary outcome of this study is FVDRs. A secondary outcome is the extent of compliance to referral recommendations by SIGN guidelines. Results Three hundred and twelve and 325 patients were included in groups 1 and 2, respectively. There was a significant decline in FVDRs between these two periods from 29.2% to 19.2%. (p= 0.004) (OR 0.58 (95% CI 0.40 to 0.84)). Post-SIGN guidelines, 87% of referrals were compliant to SIGN referral criteria while 13% remained non-compliant. The main reasons for non-compliance were no repeatable visual field defects (42.0%) and referrals due to high intraocular pressure were either not repeated or not interpreted in the context of age and central corneal thickness (36.8%). Conclusion Patients referred after the introduction of SIGN guidelines were 33.5% less likely to be discharged at the first visit. Although compliance to most recommendations in SIGN guidelines has improved, there is still a need to improve adherence to referral criteria

Patient-Physician Communication on Medication Cost during Glaucoma Visits - Slota, C; Davis, SA; Blalock, SJ; Carpenter, DM; Muir, KW; Robin, AL; Sleath, B (OPTOMETRY AND VISION SCIENCE, 2017)
SIGNIFICANCE This article is the first to investigate the nature of medication cost discussions between ophthalmologists and glaucoma patients. Only 87 of the 275 office visits analyzed had a discussion of medication cost. Providers should consider discussing medication cost with patients to identify potential cost-related barriers to medication use. PURPOSE Glaucoma is an incurable chronic eye disease affecting a growing portion of the aging population. Some of the most commonly utilized treatments require lifelong use, requiring high patient adherence to ensure effectiveness. There are numerous barriers to glaucoma treatment adherence in the literature, including cost. The aim of this secondary analysis was to describe the frequency and nature of patient-physician communication regarding medication cost during glaucoma office visits. METHODS This was a mixed-methods secondary analysis of video-recorded participant office visits (n = 275) from a larger observational study of glaucoma communication. We analyzed medical information, demographic characteristics, and interviewer-administrated questionnaires, as well as verbatim transcripts of interviews. RESULTS Only 87 participants discussed medication cost during their glaucoma office visit. The majority of the subjects who discussed cost had mild disease severity (51%), took one glaucoma medication (63%), and had Medicare (49%) as well as a form of prescription insurance (78%). The majority of glaucoma office visits did not discuss medication cost, and providers often did not ask about cost problems. Of the few conversations related to cost, most focused on providers offering potential solutions (n = 50), medical and prescription service coverage (n = 41), and brand or generic medication choices (n = 41). CONCLUSIONS Our findings are similar to previous studies showing few patients have conversations with providers about the cost of glaucoma medications. Providers should consider bringing up medication cost during glaucoma office visits to prompt a discussion of potential cost-related barriers to medication use.

Prospective Evaluation of Two iStent((R)) Trabecular Stents, One iStent Supra((R)) Suprachoroidal Stent, and Postoperative Prostaglandin in Refractory Glaucoma: 4-year Outcomes - Myers, JS; Masood, I; Hornbeak, DM; Belda, JI; Auffarth, G; Junemann, A; Giamporcaro, JE; Martinez-de-la-Casa, JM; Ahmed, IIK; Voskanyan, L; Katz, LJ (ADVANCES IN THERAPY, 2018)
This study evaluates long-term outcomes of two trabecular micro-bypass stents, one suprachoroidal stent, and postoperative prostaglandin in eyes with refractory open angle glaucoma (OAG). Prospective ongoing 5-year study of 80 eligible subjects (70 with 4-year follow-up) with OAG and IOP >= 18 mmHg after prior trabeculectomy and while taking 1-3 glaucoma medications. Subjects received two iStent(A (R)) trabecular micro-bypass stents, one iStent Supra(A (R)) suprachoroidal stent, and postoperative travoprost. Postoperative IOP was measured with medication and annually following medication washouts. Performance was measured by the proportion of eyes with >= 20% IOP reduction on one medication (the protocol-specified prostaglandin) versus preoperative medicated IOP (primary outcome); and the proportion of eyes with postoperative IOP <= 15 and <= 18 mmHg on one medication (secondary outcome). Additional clinical and safety data included medications, visual field, pachymetry, gonioscopy, adverse events, visual acuity, and slit-lamp and fundus examinations. Preoperatively, mean medicated IOP was 22.0 +/- 3.1 mmHg on 1.2 +/- 0.4 medications, and mean unmedicated IOP was 26.4 +/- 2.4 mmHg. Postoperatively, among eyes without later cataract surgery, mean medicated IOP at all visits through 48 months was >= 13.7 mmHg (>= 37% reduction), and annual unmedicated IOP was <= 18.4 mmHg (reductions of >= 30% vs. preoperative unmedicated IOP and >= 16% vs. preoperative medicated IOP). At all postoperative visits among eyes without additional surgery or medication, >= 91% of eyes had >= 20% IOP reduction on one medication versus preoperative medicated IOP. At month 48, 97 and 98% of eyes achieved IOP <= 15 and <= 18 mmHg, respectively, on one medication. Six eyes required additional medication, no eyes required additional glaucoma surgery, and safety measurements were favorable throughout follow-up. IOP control was achieved safely with two trabecular micro-bypass stents, one suprachoroidal stent, and postoperative prostaglandin. This microinvasive, ab interno approach introduces a possible new treatment option for refractory disease. NCT01456390. Glaukos Corporation.

Manhattan Vision Screening and Follow-Up Study in Vulnerable Populations: 1-Month Feasibility Results - Hark, LA; Tan, CS; Kresch, YS; De Moraes, CG; Horowitz, JD; Park, L; Auran, JD; Gorroochurn, P; Stempel, S; Maruri, SC; Besagar, S; Saaddine, JB; et al. (CURRENT EYE RESEARCH)
Purpose/Aim: In the United States, high rates of vision impairment and eye disease disproportionately impact those who lack access to eye care, specifically vulnerable populations. The objective of our study was to test instruments, implement protocols, and collect preliminary data for a larger 5-year study, which aims to improve detection of eye diseases and follow-up eye care in vulnerable populations using community health workers (CHW) and patient navigators. In the study, trained CHWs conducted vision screening and patient navigators scheduled on-site eye exams and arranged appointments for those referred to ophthalmology to improve adherence to follow-up eye care. Materials and Methods: Eligible individuals age 40-and-older were recruited from the Riverstone Senior Center in Upper Manhattan, New York City. Participants underwent on-site vision screening (visual acuity with correction, intraocular pressure measurements, and fundus photography). Individuals who failed the vision screening were scheduled with an on-site optometrist for an eye exam; those with ocular pathologies were referred to an ophthalmologist. Participants were also administered the National Eye Institute Visual Function Questionnaire-8 (NEI-VFQ-8) and Stopping Elderly Accidents, Deaths, and Injuries (STEADI) test by community health workers. Results:Participants (n = 42) were predominantly older adults, with a mean age of 70.0 +/- 9.8, female (61.9%), and Hispanic (78.6%). Most individuals (78.6%, n = 33) failed vision screening. Of those who failed, 84.8% (n = 28) attended the on-site eye exam with the optometrist. Ocular diagnoses: refractive error 13/28 (46.4%), glaucoma/glaucoma suspect 9/28 (32.1%), cataract 7/28 (25.0%), retina abnormalities 6/28 (21.4%); 13 people required eyeglasses. Conclusion: This study demonstrates the feasibility of using CHWs and patient navigators for reducing barriers to vision screening and optometrist-based eye exams in vulnerable populations, ultimately improving early detection of eye disease and linking individuals to additional eye care appointments. The full five-year study aims to further examine these outcomes.

Efficacy of a Novel Retrobulbar Extension Shunt to Rescue Eyes with Fibrotic Encapsulated Blebs and Uncontrolled Ocular Hypertension - Sponsel, WE; Groth, S; de Ribot, FM; Ramos, H; Puig, M (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2019)
PurposeRetrobulbar glaucoma shunts are large-bore fenestrated silicone stents that redirect aqueous humor into the retrobulbar space. They were designed to rescue failed standard tube shunts with fibrotic encapsulation in patients with intractable ocular hypertension. This article evaluates longer-term outcomes of a larger population undergoing retrobulbar aqueous redirection.MethodsOutcomes of all retrobulbar shunts wereplaced among this progressive-entry surgical population over an 8-year interval. Implants were produced by New World Medical (NWM) in Rancho Cucamonga, California, and AJL in Bilbao, Spain. Mean and percentage IOP reduction and medications required were evaluated at annual intervals, along with pre-operative and final visual acuity. Significance of change was assessed by two-tailed paired t-test. Failure was designated as any eye requiring placement of another shunt or diode-cyclophotocoagulation. All data are included in this analysis regardless of outcome.ResultsThirty-five retrobulbar shunts were implanted (18M, 17F; mean 54.3years; mean follow-up 32.5months). Short-term AJL shunt performance was comparable to that of the 26 NWM shunts, for which there was longer-term follow-up. Three shunts (9%) failed: Two eyes required diode at 6months, one another standard shunt after >2years. Preoperativemedications averaged 2.6, reduced to 0.4-0.75 medications at each annual assessment (P<0.0001). IOP was substantially reduced (by 53-57% from mean baseline 29.9-32.5mmHg to 16.4-18.4mmHg; P<0.0008) at every annual follow-up. Visual acuity remained stable (baseline mean VA 0.27, final VA 0.30; P=0.68).ConclusionRetrobulbar extension shunts can convert tube shunt failures, with high success rate, to eyes with IOP control comparable to successful primary filtration surgery.

Safety and effectiveness of primary transscleral diode laser cyclophotoablation for glaucoma in Nigeria - Abdull, MM; Broadway, DC; Evans, J; Kyari, F; Muazu, F; Gilbert, C (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2018)
Importance To investigate the safety, effectiveness and follow-up rates after transscleral diode laser cyclophotocoagulation as primary treatment for seeing eyes with primary open angle glaucoma in Bauchi, Nigeria. Background There is a high prevalence of primary open angle glaucoma in Africa where adherence to medical treatment and acceptance of surgery are poor. Design Prospective case series. Participants New glaucoma patients where surgical intervention was recommended. Methods A diode 810 nm laser G-probe was used under retrobulbar anaesthesia to deliver approximately 20 shots for 2000 ms, titrating the power. If both eyes were treated the first was the study eye. Repeat treatment offered if the intraocular pressure (IOP) was >21 mmHg on two consecutive visits. Main Outcome Measures IOP < 22 mmHg, change in >= 2 lines of Snellen visual acuity (VA), and complications. Results 201 out of 204 eyes with complete data analysed. Mean age 52 years, 17 (8.3%) eyes were re-treated. Mean pre-treatment IOP was 39 (SD 11) mmHg. 106 (53%) attended at 12 months when the mean IOP was 19 (7-45) mmHg; 77 (73%) had IOP < 22 mmHg. VAs were better in 13 (12.3%) and worse in 23 (21.7%) eyes. Postoperative complications included mild uveitis (5.5%), corneal oedema (2.5%), severe uveitis (0.5%) and transient hypotony (2.0%). No hypotony at 12 months. Conclusions and Relevance Transscleral diode laser cyclophotocoagulation controlled IOP in almost three quarters of eyes at 12 months with short-term preservation of vision and minimal complications. Poor follow-up in this setting highlights the need for an effective, safe and acceptable treatment where regular follow-up is less critical.

Compliance with antihypertensive therapy among elderly Medicaid enrollees: The roles of age, gender, and race - Monane, M; Boh, RL; Gurwitz, JH; Glynn, RJ; Levin, R; Avorn, J (AMERICAN JOURNAL OF PUBLIC HEALTH, 1996)
Objectives. This study measured compliance and related demographic factors in a retrospective cohort of 4068 elderly outpatients newly starting antihypertensive therapy from 1982 through 1988. Methods. Logistic regression modeling of data from the New Jersey Medicaid program was used. Results. These patients filled antihypertensive prescriptions covering an average of only 179 days in the 365-day follow-up period (49%). Good compliance (greater than or equal to 80%) was associated with advanced age (odds ratio [OR] = 2.12, for patients 85 or older) and White race (OR = 0.55 for Blacks). There was no relationship between compliance and gender. Conclusions. Despite the efficacy of antihypertensive therapy in preventing cardiovascular morbidity, such high rates of noncompliance may contribute to suboptimal patient outcomes.

Individualised patient care as an adjunct to standard care for promoting adherence to ocular hypotensive therapy: an exploratory randomised controlled trial - Gray, TA; Fenerty, C; Harper, R; Spencer, AF; Campbell, M; Henson, DB; Waterman, H (EYE, 2012)
Purpose To evaluate the impact of individualised patient care, as an adjunct to standard care, on adherence to ocular hypotensive therapy. Methods A two-arm, single-masked exploratory randomised controlled trial recruited patients newly prescribed ocular hypotensive therapy. The intervention involved an individual assessment of health-care needs and beliefs and a 1-year follow-up period according to need. The primary outcome was refill adherence, measured by collating prescription and dispensing data for 12 months. Secondary outcomes included self-reported adherence, glaucoma knowledge, beliefs about illness and medicines, quality of care, intraocular pressure (IOP) fluctuation, and changes in clinical management assessed at 12 months. The strength of the intervention was measured following withdrawal by reviewing clinical outcomes for a further 12 months. Results In all, 127 patients were recruited (91% response rate). Intervention-arm patients collected significantly more prescriptions than control-arm patients. Self-report adherence was significantly better in the intervention-arm for patients who forgot drops and those who intentionally missed drops. The intervention group demonstrated significantly more glaucoma knowledge, expressed a significantly stronger belief in the necessity of eye drops and believed that they had more personal control over managing their condition. Control-arm patients had more IOP fluctuation and changes in clinical management. However, this finding only reached significance at 24 months. Conclusion Modelling patient care according to health-care needs and beliefs about illness and medicines can have a significant impact on improving adherence to therapy for this patient group, with the potential benefit of improving clinical outcomes. Eye (2012) 26, 407-417; doi: 10.1038/eye.2011.269; published online 18 November 2011

Assessment of the Anterior Chamber Flare and Macular Thickness in Patients Treated with Topical Antiglaucomatous Drugs - Selen, F; Tekeli, O; Yanik, O (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2017)
Purpose: To determine the changes in the anterior chamber flare and central macular thickness (CMT) under topical antiglaucomatous therapy. Methods: This study included 121 eyes of 73 patients and 36 eyes of 18 controls. Glaucoma patients were divided into 3 groups (timolol maleate, latanoprost, and bimatoprost). Control eyes did not receive any medications. Flare and CMT measurements were performed at baseline and follow-up visits (15th day, and 1st, 3rd, 6th, and 12th month). Results: Statistically significant increases were detected in the flare values in the bimatoprost and latanoprost groups (P < 0.001, P = 0.011, respectively). Significant increases were also found in CMT values measured in these 2 groups (P < 0.001, P = 0.002, respectively). However, increased flare and CMT values were not clinically manifested as uveitis and macular edema. Flare and CMT values did not change statistically in the timolol maleate and control groups. Conclusions: Although the use of prostaglandin (PG) analogs was found to be associated with increased flare and CMT, these increases were not clinically significant. PG analog monotherapy may be safely and effectively used in the treatment of glaucoma.

Exploring the frequency and location of prescribing errors in the use of topical glaucoma medications - Lakhani, BK; King, AJ (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2018)
ImportanceVery little is known about health-care professional related prescribing errors within the glaucoma setting. BackgroundThis study aims to quantify these errors and to explore where they occur along the prescribing pathway. DesignCross-sectional study of patients attending a specialty glaucoma clinic over a 5-month period. ParticipantsData was collected for 109 patients. MethodsWe compared glaucoma drop regimes from four different sources: As documented in the hospital notes for the last appointment, the letter sent to the General Practitioner (GP), patient's self-reporting and bottles/prescriptions brought to the clinic appointment. Main Outcome MeasuresDiscrepancies were identified and errors were grouped into one of four categories depending on where in the prescribing pathway they occurred: Incorrect prescribing of the drops by the clinician, incorrect prescribing of the drops by the GP/failure to provide a repeat prescription, incorrect dispensing of the drops by the pharmacist and possible non-adherence by the patient. ResultsThere was a total of 217 individual prescription items involving 266 active ingredients. Seventy-one prescription items out of 217 (33%) had an error, of this 53 (75%) were due to possible patient non-adherence and 18 (25%) were process related errors made by health-care professionals. Conclusions and RelevanceAn error was identified in 33% of prescriptions. About 8.3% of prescriptions had a health-care professional related process error. These errors are preventable and recognition of these is important to maximize drop adherence and minimize disease progression, requiring increased consultations and interventions with quality of life and health economic consequences.

Endothelial keratoplasty in the management of irido-corneal endothelial syndrome - Chaurasia, S; Ramappa, M; Garg, P; Murthy, SI; Senthil, S; Sangwan, VS (EYE, 2013)
Purpose To describe the results of endothelial keratoplasty (EK) in the management of irido-corneal endothelial (ICE) syndrome. Design Retrospective, consecutive, interventional case series. Methods Eight eyes of seven patients underwent EK for corneal edema owing to ICE syndrome. Simultaneous cataract surgery was performed in five eyes. The charts were reviewed for demographics, clinical findings, and outcomes after EK. Results Mean age was 50.4 years (range 35-59 years). Mean follow-up was 12.5 months (range 6-24 months). Corneal clarity was restored in all eyes and was maintained till the last follow-up. Four patients had acute rise in the intraocular pressure in the post-operative period, which was well controlled on medical treatment. One patient who was non-compliant with medications and regular follow-up advice had progression of glaucomatous disc changes and visual field loss. The best-corrected visual acuity ranged from 20/50-20/30. Conclusions EK is a viable option in ICE syndrome. Adequate control of glaucoma is the paramount factor in maintaining good visual acuity in these eyes. Eye (2013) 27, 564-566; doi:10.1038/eye.2012.298; published online 25 January 2013

Eye Care Quality and Accessibility Improvement in the Community (EQUALITY) for adults at risk for glaucoma: study rationale and design - Owsley, C; Rhodes, LA; McGwin, G; Mennemeyer, ST; Bregantini, M; Patel, N; Wiley, DM; LaRussa, F; Box, D; Saaddine, J; Crews, JE; Girkin, CA (INTERNATIONAL JOURNAL FOR EQUITY IN HEALTH, 2015)
Background: Primary open angle glaucoma is a chronic, progressive eye disease that is the leading cause of blindness among African Americans. Glaucoma progresses more rapidly and appears about 10 years earlier in African Americans as compared to whites. African Americans are also less likely to receive comprehensive eye care when glaucoma could be detected before irreversible blindness. Screening and follow-up protocols for managing glaucoma recommended by eye-care professional organizations are often not followed by primary eye-care providers, both ophthalmologists and optometrists. There is a pressing need to improve both the accessibility and quality of glaucoma care for African Americans. Telemedicine may be an effective solution for improving management and diagnosis of glaucoma because it depends on ocular imaging and tests that can be electronically transmitted to remote reading centers where tertiary care specialists can examine the results. We describe the Eye Care Quality and Accessibility Improvement in the Community project (EQUALITY), set to evaluate a teleglaucoma program deployed in retail-based primary eye care practices serving communities with a large percentage of African Americans. Methods/ Design: We conducted an observational, 1-year prospective study based in two Walmart Vision Centers in Alabama staffed by primary care optometrists. EQUALITY focuses on new or existing adult patients who are at-risk for glaucoma or already diagnosed with glaucoma. Patients receive dilated comprehensive examinations and diagnostic testing for glaucoma, followed by the optometrist's diagnosis and a preliminary management plan. Results are transmitted to a glaucoma reading center where ophthalmologists who completed fellowship training in glaucoma review results and provide feedback to the optometrist, who manages the care of the patient. Patients also receive eye health education about glaucoma and comprehensive eye care. Research questions include diagnostic and management agreement between providers, the impact of eye health education on patients' knowledge and adherence to follow-up and medication, patient satisfaction, program cost-effectiveness, and EQUALITY's impact on Walmart pharmacy prescription rates. Discussion: As eye-care delivery systems in the US strive to improve quality while reducing costs, telemedicine programs including teleglaucoma initiatives such as EQUALITY could contribute toward reaching this goal, particularly among underserved populations at-risk for chronic blinding diseases.

Compliance and hygiene behaviour among soft contact lens wearers in the Maldives - Gyawali, R; Mohamed, FN; Bist, J; Kandel, H; Marasini, S; Khadka, J (CLINICAL AND EXPERIMENTAL OPTOMETRY, 2014)
BackgroundSignificant levels of non-compliance and poor hygiene among contact lens wearers have been reported previously from different parts of the world. This survey aimed at identifying the scope of hygiene and non-compliant behaviour of soft contact lens wearers in the Maldives. MethodsEstablished soft lens wearers attending two eye clinics in Male' city, were interviewed in office or via telephone. A set of interviewer-administered questions was used to access the subjective response on compliance and hygiene behaviour (hand and lens case hygiene, water exposure, adherence to lens replacement schedule, dozing and overnight wear, awareness of aftercare visits and reuse of disinfecting solution). Participants were also asked to rate themselves as a contact lens user based on their perceived compliance and hygiene practices. ResultsOut of 107 participants, 79 (74.8 per cent) were interviewed in the office and the rest via telephone. The majority of lens wearers were female, office workers and students, with a mean age of 20.64 4.4 years. Mean duration of lens wear was 28.04 +/- 8.36 months. Most of them were using spherical lenses (86.9 per cent) on a daily wear basis (96.3 per cent). Major reported forms of non-compliance were poor hand hygiene (60.7 per cent), lack of aftercare awareness (39.3 per cent), water exposure (35.5 per cent) and over-use of lenses (24.3 per cent). While females were more likely to overuse their lenses than males (p < 0.005), other socio-demographic factors were not associated with reported non-compliance. Although around 90 per cent of the participants considered themselves average or good contact lens wearers, most exhibited some form of non-compliant and poor hygienic behaviour. ConclusionA significant number of Maldivian contact lens wearers exhibited poor levels of hygiene and compliance with contact lenses and lens care systems. An effective educational reinforcement strategy needs to be developed to modify lens wearers' non-compliance.

The Effectiveness of a Tailored Intervention to Increase Follow-Up Adherence in Patients with Glaucoma - Tran, J; Waisbourd, M; Weiss, D; Murchison, AP; Katz, LJ; Spaeth, GL; Haller, JA; Hark, LA (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2014)

10-YEAR-RESULTS OF ARGON-LASER TRABECULOPLASTY - MOULIN, F; HAUT, J (JOURNAL FRANCAIS D OPHTALMOLOGIE, 1994)
To appreciate the current place of argon laser trabeculoplasty (ALT) in the therapeutic armamentarium of primary open-angle glaucoma (POAG), the first 211 photocoagulated phakic eyes were analysed. 159 eyes had a 5 year-follow-up, 147 eyes had a 8 year-follow-up and 127 eyes had a minimal 10 year-follow-up. These eyes corresponded to an initial group of 151 patients : 76 women and 75 men with a mean age of 66 years. We decided, arbitrarily, to assess trabeculoplasty results according to three combined criteria of failure (insufficient or transient intraocular pressure drop (less-than-or-equal-to 3 mmHg), progression of visual field loss and need of filtrating surgery) and to various expected goals : prevent an increase of drugs with their subsequent side effects, taper a non tolerated medical treatment and, lastly, try to cease all medical treatment in non compliant patients. According to those criteria, during the first five years, the cumulative failure rate in the 159 eyes rose steadily from 19 % (31 eyes) in the first year to 52 % (82 eyes) in the fifth year. In the 147 eyes with a 8 year-follow-up 25 eyes (17 %), and in the 127 eyes with a 10 year-follow-up 14 eyes (11 %) were still controlled. At the 10 year-follow-up, the surgical failure rate was 35 % (40 eyes in 113), quite similar to the rate at 5 years : 33 % (27 in 82). Thirty eyes excluded in the study belonged to patients who died during the follow-up. Their mean age at the time of ALT was 76 years. The low success rate at 10 years was forseeable according to the 10 % new failure cases per year encountered in the five year-data. Despite this high long-term failure rate, making laser efficiency comparable with drugs, trabeculoplasty is still useful in the current therapeutic armamentarium of POAG, not as a rival procedure of invasive filtrating operation reserved to presurgical glaucomas, but as a complementary treatment of the intermediate stages of the disease for which its efficacy was found to be better in the current study and for patients with a short life expectancy.

Comparison of adverse events with daily disposable hydrogels and spectacle wear - Results from a 12-month prospective clinical trial - Sankaridurg, PR; Sweeney, DF; Holden, BA; Naduvilath, T; Velala, I; Gora, R; Krishnamachary, M; Rao, GN (OPHTHALMOLOGY, 2003)
Objective: To evaluate the type and incidence of adverse events seen with daily disposable hydrogel contact lens wear compared with a control (spectacle) group over 12 months. Design: Prospective, randomized, observer-masked, comparative clinical trial. Participants: Two hundred eighty-one myopes with no prior contact lens wear experience were enrolled from August to December 1996. Subjects were 16 to 35 years old and had refractive errors ranging from a -0.75-diopter (D) sphere to a -6.00-D sphere with a cylinder less than -1.00 D. Intervention: Each subject was randomly assigned to wear either bilateral disposable hydrogels on a daily disposable wear schedule or spectacles. Main Outcome Measure: Type and incidence of adverse events from each group. Adverse events were categorized as serious, significant, and nonsignificant based on the potential to cause vision impairment, severity at event, and level of clinical concern. Results: At baseline, 1.6% of eyes had asymptomatic infiltrates that were nonsignificant. During the study, asymptomatic infiltrates were seen in both contact lens and spectacle groups at 20.5 events versus 11.3 events per 100 eyes per year of wear. No significant events were seen with the spectacle group. With the contact lens group, the type and incidence of significant events per 100 eyes per year of lens wear were corneal peripheral ulcer, 2.5 events; infiltrative keratitis, 1.5 events; and papillary conjunctivitis, 1 event. The incidence of both significant and nonsignificant events was greater with the contact lens group (P<0.05). No serious events (i.e., microbial keratitis) were seen in either group. A greater number of subjects were lost to follow-up or permanently discontinued from the contact lens group relative to the spectacle group (33% vs. 17%, P = 0.002). Lens-related problems such as dryness, discomfort, and difficulty with insertion and removal accounted for 27% of discontinuations from the contact lens group. Poor compliance (40%) was the greatest reason for discontinuations from the spectacle group. Conclusions: No clinically serious events were seen with either group. Only a small percentage of contact lens-wearing eyes presented with significant events, which is promising for daily disposable lens wear. Far more contact lens subjects were lost to follow-up or discontinued. Small, asymptomatic, subepithelial corneal infiltrates of unknown significance were seen in both contact lens- and spectacle-wearing eyes. (C) 2003 by the American Academy of Ophthalmology.

Ocular Hypertension after Pediatric Cataract Surgery: Baseline Characteristics and First-Year Report - Lin, HT; Chen, WR; Luo, LX; Zhang, XY; Chen, JJ; Lin, ZL; Qu, B; Zhan, J; Zheng, DY; Zhong, XJ; Tian, Z; Liu, Y; et al. (PLOS ONE, 2013)
Monitoring intraocular pressure (IOP) is essential for pediatric cataract treatment but always difficult due to lack of cooperation in young children. We present the baseline characteristics and the first-year results of a long-term prospective cohort study, which are aimed to determine the relationship of the incidence of ocular hypertension (OH) in children after cataract surgery during the first-year period and the risk of developing late-onset glaucoma. Children were included with the following criteria: they were <= 10 years old and scheduled to undergo cataract surgery with/without intraocular lens implantation; they were compliant with our follow-up protocol, which included monitoring IOP using a Tono-Pen under sedation or anesthesia. Incidence of OH, peak OH value, OH onset time and OH duration within a 12-month period following surgery were measured. In brief, 206 patients (379 eyes) were included and OH developed in 66 of 379 (17.4%) eyes. The mean follow-up period was 14.0 +/- 3.2 months (median, 12 months; range, 10-16 months). Moreover, 33 of 196 (16.8%) aphakic eyes and 33 of 183 (18.0%) IOL eyes were diagnosed with OH. The peak OH onset times were at 1-week (34/66, 51.5%) and 1-month (14/66, 21.2%) appointments postsurgery. The peak IOP value in the OH eyes was 29.9 +/- 7.5 mmHg (median, 29 mmHg; range, 21-48 mmHg). The duration of OH was 30.9 +/- 31.2 days (median, 30 days; range, 3-150 days). OH recurred in 13 eyes with a history of OH diagnosed within 1 month postsurgery (13/54, 24.1%), which needed temporary or long term use of antiglaucoma medications. In conclusion, the incidence of OH in children after cataract surgery was 17.4% during the first-year period. Children who have suffered elevated IOP in the first year after cataract surgery should be followed closely to determine if there is an increased risk of developing late-onset glaucoma.

A Comparative Effectiveness Analysis of Visual Field Outcomes After Projected Glaucoma Screening Using SD-OCT in African American Communities - Blumberg, DM; Vaswani, R; Nong, E; Al-Aswad, L; Cioffi, GA (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2014)
PURPOSE. To assess the impact on visual function of community glaucoma screening in an African American population using spectral-domain optical coherence tomography (SD-OCT). METHODS. Using a Monte Carlo microsimulation model with a 10-year time horizon, we analyzed the efficacy of SD-OCT screening on visual field outcomes in a population of African Americans who are not otherwise seeking office-based care. Outcomes included classification of visual field severity, quality-adjusted life years, and direct health care costs. RESULTS. Assuming a 60% follow-up rate, screening decreased the prevalence of undiagnosed glaucoma from 75% to 38%, and decreased the prevalence of severe visual field loss in patients with glaucoma from 29.1% to 23.9%. Conversely, screening increased the prevalence of mild visual field loss in patients with glaucoma from 9.2% to 18.7%. From initial screening through confirmatory eye examination, the screening program ("screen only'') cost $98 per screened individual, and $2561 per new diagnosis of glaucoma. When considering the costs of initial screening though the resultant treatment, the screening program ("screen and treat'') had an average annual cost of $79 and $2138, respectively, over a 10-year time period. The cost of one quality-adjusted life year (QALY) gained by screening, including management and treatment, in comparison with opportunistic case finding, ranged from $46,416 to $67,813. CONCLUSIONS. Our findings suggest that community SD-OCT screening in an African American population will minimize glaucoma-related visual morbidity. Ideally, strategies to maximize treatment efficacy through improved medication adherence and improved compliance with follow-up should be identified and implemented before instituting a screening program.

Comparison of the Efficacy and Safety of Fixed Combination Travoprost/Timolol and Dorzolamide/Timolol in Patients with Primary Open-Angle Glaucoma and Ocular Hypertension - Babic, N; Andreic, V; Miljkovic, A; Grkovic, D; Jovanovic, P (SRPSKI ARHIV ZA CELOKUPNO LEKARSTVO, 2013)
Introduction Combining two medications in one bottle may improve compliance by reducing the time required to administer drops and the frequency of the total number of medication bottles. Objective To compare the efficacy of reduced intraocular pressure (IOP) and safety of fixed combination travoprost 0.004%/timolol 0.5% vs. fixed combination dorzolamide 2%/timolol 0.5% in patients with primary open-angle glaucoma or ocular hypertension. Methods Prospective randomized clinical study included 60 patients divided into 2 groups. Follow-up was done at day 14 and 45 and month 3. IOP measurements were taken at each follow-up examination at 8 am, 10 am and 4 pm. Results Both fixed combinations reduced IOP significantly compared to initial values at all follow-ups (p<0.001). Mean pooled IOP at all visits and time points was slightly lower in the travoprost/timolol group compared with the dorzolamide/timolol group (16.13 mmHg vs. 16.15 mmHg). Mean IOP reduction from baseline ranged from -7.46 mmHg to -9.92 mmHg in the travoprost/timolol group and from -6.93 mmHg to -8.93 mmHg for the dorzolamide/timolol group. Mean (standard error of the mean) reduction in diurnal IOP from baseline to 3rd month was 8.96 +/- 2.79 in the travoprost/timolol group versus 8.07 +/- 2.91 in patients receiving dorzolamide/timolol fixed combination (p=0.196). The most frequent treatment-related adverse events were conjunctival hyperemia in the travoprost/timolol group, and dry eye and foreign body sensation in the dorzolamide/timolol group. Conclusion Travoprost/timolol fixed combination was slightly more effective than dorzolamide/timolol fixed combination in reducing mean diurnal IOP. Travoprost/timolol group resulted in an IOP reduction for up to 1.07 mmHg higher than dorzolamide/timolol group. Both fixed combinations were well tolerated and safe.

Adherence with Topical Glaucoma Medication Monitored Electronically The Travatan Dosing Aid Study - Okeke, CO; Quigley, HA; Jampel, HD; Ying, GS; Plyler, RJ; Jiang, Y; Friedman, DS (OPHTHALMOLOGY, 2009)
Purpose: To assess patient adherence and behaviors with topical once-daily therapy for glaucoma. Design: Prospective, observational cohort study. Participants: One hundred ninety-six patients with glaucoma who were being treated with a prostaglandin analog in 1 or both eyes at the Scheie or Wilmer Eye Institutes between August 2006 and June 2007. Methods: Detailed medical history was obtained from each patient. All subjects used the Travatan Dosing Aid (DA; Alcon, Fort Worth, TX) to administer travoprost as prescribed. Devices were collected at 3 months and the data of drop usage was downloaded using software provided with the dosing aid. Data were analyzed for the 8-week period starting 2 weeks after the enrollment visit and ending 2 weeks before the 3-month visit. Main Outcome Measures: Assessment: of adherence and patterns of drop usage as indicated by the DA. Results: A total of 282 subjects consented to be in the study and 86 (30%) withdrew before study completion or had device errors, leaving 196 subjects (70%) with evaluable data at 3 months. The overall mean (+/- standard deviation) adherence rate was 0.71 (+/- 0.24), ranging from 0.02 to 0.97. One hundred nine of these patients (55.6%) took greater than 75% of the expected doses. Those with adherence of less than 50% of expected doses showed substantially increarsed dose taking immediately after the office visit and just before the return visit at 3 months (P = 0.03). The mean adherence rate estimates of the physician and patient self-report were 0.77 and 0.95, respectively. The agreement between the physician assessment and DA-recorded adherence rate showed poor correlation for individual cases (intraclass correlation coefficient, 0.09; 95% confidence interval, 0.00-0.19). Conclusions: Nearly 45% of patients using art electronic monitoring device who knew they were being monitored and were provided free medication used their drops less than 75% of the time. Patients reported far higher medication use than their actual behavior. The ability of the physician to identify which persons are poorly adherent from their self-report or from other subjective clues is poor. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references. Ophthalmology 2009;116:191-199 (C) 2009 by the American Academy of Ophthalmology.

Is Patient Knowledge of Glaucoma Improved by Using a Glaucoma Logbook? - Daly, R; Agarwal, PK (JOURNAL OF GLAUCOMA, 2018)
Aims: Patient-held records are becoming more commonly used in health care, particularly in chronic diseases like glaucoma. There is a lack of evidence to support their use, however. This study examines the change in knowledge scores within a group following the introduction of a newly designed glaucoma logbook. Methods: This analysis uses a test and retest method where patients undergoing treatment for glaucoma or ocular hypertension were assessed using a validated knowledge questionnaire. They were then given a personalized glaucoma logbook and their knowledge scores retested after 4 to 8 weeks. The change in knowledge score was examined using a Wilcoxon signed-rank test. Results: A total of 56 patients were recruited and 35 completed both questionnaires equating to a 62.5% retention rate. The analysis showed a significant increase in the knowledge score attained following introduction of the questionnaire (Z=-4.176, P<0.001). Conclusions: In this format, the glaucoma logbook has a positive impact on patient knowledge. Further research will be necessary to show if this result is maintained in a larger sample group and to investigate whether this improvement in knowledge is associated with any improvement in long-term structural and functional outcomes.

Preservative-free bimatoprost 0.03% in patients with primary open-angle glaucoma or ocular hypertension in clinical practice - Pillunat, LE; Eschstruth, P; Hasemeyer, S; Thelen, U; Foja, C; Leaback, R; Pfennigsdorf, S (CLINICAL OPHTHALMOLOGY, 2016)
Background: Intraocular pressure (IOP)-lowering medications for primary open-angle glaucoma and ocular hypertension commonly contain preservatives that can cause ocular surface damage in many patients. The purpose of this study was to evaluate the efficacy and tolerability of, and compliance to, preservative-free (PF) bimatoprost 0.03% in patients with primary open-angle glaucoma or ocular hypertension (IOP >= 18 mmHg) in a clinical practice setting. Methods: This open-label study observed patients who were switched to PF bimatoprost 0.03% for medical reasons. IOP was measured at baseline and similar to 12 weeks later at the final visit, and the change in IOP was calculated. Tolerability and continuation of therapy were assessed at two follow-up visits. Results: A total of 1,830 patients were included in the study, and complete IOP data were available for 1,543 patients. Mean IOP was reduced by 23% from 21.64 mmHg to 16.59 mmHg (P<0.0001). In subgroup analyses, the mean IOP was significantly reduced compared with baseline, regardless of prior therapy, including those previously treated with PF monotherapy. A total of 85.7% of physicians reported the IOP-lowering efficacy of PF bimatoprost 0.03% to be as expected or better than expected. Adverse events (AEs) were experienced by 5.7% of patients, and there were no serious AEs reported. The most common AEs were eye irritation (1.7%) and hyperemia (1.4%). Physician-reported treatment compliance was reported as better than (48.7%) or equal to (43.6%) prior treatment in most patients. Most patients (82%) were expected to continue PF bimatoprost 0.03% after the end of the study. Conclusion: This observational study showed that, in clinical practice, switching to PF bimatoprost 0.03% was associated with a significant IOP reduction from baseline. There was a low AE rate. PF bimatoprost 0.03% may, therefore, be an effective treatment option for patients who are intolerant of preservatives or have an inadequate response to prior IOP-lowering treatments.

Patterns of care for glaucoma patients in Korea from 2002 to 2013 using the national health insurance service claims data - Choi, S; Choi, JA; Kwon, JW; Park, SM; Jee, D (MEDICINE, 2018)
Due to the rapidly increasing life-expectancy, the prevalence of glaucoma has increased steadily in recent years. We aimed to evaluate the patterns of care and primary treatment strategy patterns in Korea according to glaucoma subtypes to assess the quality of care for glaucoma patients. In this serial cross-sectional survey, the claims data from the Korean National Health Insurance Service was used to identify and group glaucoma patients into primary open-angle glaucoma (POAG), primary angle-closure glaucoma (PACG), other types of glaucoma, and ocular hypertension from 2002 to 2013. Records for outpatient visits, hospitalizations, drug prescriptions, admissions, and surgical interventions were used to determine the patterns of care and identify primary treatment strategies. Both the prevalence (0.11% in 2002 to 0.43% in 2013) and incidence rates (0.06% in 2003 to 0.11% in 2013) for glaucoma increased over time. The mean number of outpatient visits increased (4.9-6.0 visits per year), while the proportion of hospitalized patients (2.3-1.0% of patients) and duration of hospital stay (4.5-3.4 days among hospitalized patients) decreased between 2002 and 2013 for patients with POAG. The proportion of patients not being managed by medication or surgery decreased, with POAG and PACG patients receiving medications increasing from 70.9% and 59.2% in 2002 to 88.4% and 63.3% in 2013, respectively. Finally, while the proportion of trabeculectomy decreased (22.2% to 10.0% of surgical procedures in 2002 and 2013, respectively), more patients with PACG have received iridectomy (59.3% to 86.0% of surgical procedures in 2002 and 2013, respectively). Between 2002 and 2013, the pattern of care for both patients with POAG and PACG has shifted toward management by outpatient visits and intervention with anti-glaucoma medications in Korea.

A comparison of measures used to describe adherence to glaucoma medication in a randomised controlled trial - Cate, H; Bhattacharya, D; Clark, A; Holland, R; Broadway, DC (CLINICAL TRIALS, 2015)
Background: Understanding the magnitude of non-adherence in pre-marketing clinical trials and clinical practice is essential. However, accurately measuring non-adherence to medication is problematic, and the variety of adherence measures and/or calculation methods has led to highly variable results. Purpose: To compare commonly used methods for measuring adherence to eye drop therapy in order to assess which methods achieve the most complete datasets over an 8-month monitoring period, to quantify the magnitude of variance in adherence estimations and to review the different methods used to calculate or interpret adherence data. Methods: Adherence was measured electronically for 8 months by participants administering eye drops using a Travalert((R)) dosing aid. The mean number of Travalert dosing aid recorded doses administered over the monitoring period was used to calculate a percentage adherence score. In addition, the value of graphically presenting Travalert dosing aid data to classify patterns of adherence behaviour was explored. The validated Morisky Measure of Adherence Scale and questions requesting participants to report the Frequency of Missed Doses were two measures of self-reported adherence calculated for each participant. Finally, medication possession ratio was calculated from expected repeat prescription orders compared with actual repeat prescription orders. Results: For the 208 recruited participants, self-reported adherence was the most reliable method of collecting complete datasets over the 8-month period; 16% of self-reported adherence data were missing compared with 45% of Travalert dosing aid data missing at 8 months. The mean adherence measured over the monitoring period by the Travalert dosing aid was 77%. When adherence measures were dichotomised into adherent and non-adherent groups, the Travalert dosing aid found 54% of participants were adherent, compared to 60% Morisky Measure of Adherence Scale and 57% Frequency of Missed Dose self-report measures. However, there was poor agreement between the Travalert dosing aid measured adherence and self-report measures. Medication possession ratio was not a reliable measure of persistence with medication. Graphical Travalert dosing aid data presentation provided additional information about participant behaviour by indicating that most non-adherence was due to participants taking drug holidays rather than missing occasional doses. Conclusion: The analysis provided evidence about the inconsistencies between different monitoring strategies and adherence measures. Furthermore, the analysis highlighted the difficulties in collecting complete data for studies investigating chronic, slowly progressive conditions that require long-term follow-up. Future adherence studies could use multiple methods for quantifying and classifying adherence in parallel, both to maximise precision of adherence estimates and to facilitate comparison between studies. However, the authors are cautious of the effect of using multiple adherence measures on participant behaviour and their potential reactivity effects is an area for future research.

Evaluation of eye drop administration technique in patients with glaucoma or ocular hypertension - Schwartz, GF; Hollander, DA; Williams, JM (CURRENT MEDICAL RESEARCH AND OPINION, 2013)
Objective: To evaluate eye drop administration by patients at multiple visits in the setting of a randomized controlled trial. Study design and methods: Patients with glaucoma or ocular hypertension were randomized to 12 weeks of treatment with topical ocular hypotensive medication in a multicenter, investigator-masked trial. At baseline, patients were given a questionnaire for self-assessment of difficulty with drop administration. At baseline and 12 weeks, patients demonstrated drop instillation using a bottle of artificial tears. Main outcome measures: Patient self-assessment of difficulty with drop administration and observed patient difficulty with drop administration, defined as bottle touching eye/adnexa, drop missing the ocular surface, or administering more than 1 drop. Results: Of 164 enrolled patients, 50% had previously been treated with ocular hypotensive medication for >= 3 years. Only 11.4% of patients reported difficulty with eye drop administration at study entry. At baseline, 18.2% of patients touched their eye/adnexa with the bottle and 10.3% missed the eye. At 12 weeks, 18.5% and 8.6% of patients, respectively, had similar difficulties. Overall, difficulty with drop instillation was observed in 42.1% of patients. Difficulty at both visits was seen in 35.3% of patients who reported difficulty at entry and in 17.2% of patients who denied difficulty. The relative risk of demonstrating difficulty at either visit was 2.0 times greater for patients who self-reported difficulty at study entry (P 0.004). The relative risk of demonstrating difficulty at week 12 was 3.8 times greater for patients with observed difficulty at baseline (P<0.001). Limitations of the study design included self-administration of drops to the eye of the patient's choice and observation in an office setting. Conclusions: Patients with experience instilling topical glaucoma medications continue to have difficulties with eye drop administration, including patients who do not self-report difficulty. The risk of difficulty with eye drop administration is increased in patients who self-report difficulty and in patients who have been previously observed to have difficulty.

Clinical factors favoring excessive subconjunctival fibroblastic proliferation after glaucoma surgery - Bresson-Dumont, H; Lehoux, A; Baroux, C; Foucher, J; Santiago, PY (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2008)
Purpose: To understand risk factors for failure of glaucoma filtering surgery. Patients: A retrospective study of 67 eyes (16 nonpenetrating trabeculectomies, 51 trabeculectomies [31 with 5FU and 20 with mitomycin)) of 61 patients in whom 5FU bleb revision was needed because of increasing intraocular pressure. Postoperative incidents were analyzed to explain excessive subconjunctival fibroblastic proliferation. Results: in eight cases, IOP increased after 6.16 months (+/- 2) and for 59 eyes, after 33.5 days after surgery (+/- 11.4). Postoperative incidents were 24 (35.9%) bleb leaks, nine cases (13.4%) of hypotony with choroidal detachment, six (9.0%) iris incarcerations, seven (10.4%) cystic blebs, and 21 (31.3%) inflammatory flat blebs. After a mean follow-up of 27 months 18, the success of bleb 5FU revision was 84.6% for nonpenetrating trabeculectomy (without glaucoma treatment, 69.2%, with medical treatment, 15.4%) and 73.9% for trabeculectomy (47.8% and 32.6%). Conclusion: Postoperative outcomes favor an inner or outer obstacle to conjunctival filtration. Aqueous humor can no longer remain in the subconjunctival spaces, increasing the risk of glaucoma surgery failure, Early follow-up of glaucoma surgery is crucial to obtaining long-lasting filtration.

Clinical Characteristics of Allergy to a Brinzolamide 1.0%/Brimonidine 0.2% Fixed Combination in Korean Glaucoma Patients - Park, IK; Bae, SH; Kim, KW; Chun, YS (JOURNAL OF THE KOREAN OPHTHALMOLOGICAL SOCIETY, 2020)
Purpose: We describe the clinical aspects of allergy to a brinzolamide 1.0%/brimonidine 0.2% fixed combination (BBFC) in Korean patients with glaucoma. Methods: The medical records of 117 glaucoma patients treated with BBFC were retrospectively analyzed in terms of sex, age, glaucoma type, follow-up period after prescription of eyedrops, number of eyedrop preparations used, allergy onset, and clinical characteristics. Results: The incidence of ocular allergy during BBFC use was 12.8%. Allergy developed after an average of 8.58 months (range, 0.93-25.80 months); half of all allergies were evident within the first 5 months. The most common type of allergy was follicular conjunctivitis (53.4%), followed by papillary conjunctivitis and blepharoconjunctivitis. Systemic side-effects and eye discomfort (0.09%) were largely confined to non-allergic patients. Conclusions: An understanding of the clinical pattern of BBFC allergy in Korean glaucoma patients could facilitate treatment compliance and patients' education.

Effect of Beclomethasone Nasal Spray on Intraocular Pressure in Ocular Hypertension or Controlled Glaucoma - Yuen, D; Buys, YM; Jin, YP; Alasbali, T; Trope, GE (JOURNAL OF GLAUCOMA, 2013)
Purpose: To evaluate the effect of 6 weeks administration of beclomethasone nasal spray on intraocular pressure (IOP) in patients with ocular hypertension or controlled primary open-angle glaucoma. Patients and Methods: Randomized double-masked controlled trial. Patients were randomized to twice daily beclomethasone versus placebo saline nasal spray. There were a total of 4 study visits: baseline and weeks 2, 4, 6 after starting the spray. Each study visit was at the same time within a 1-hour time window. Primary outcome measure was IOP. Secondary measures included visual acuity, anterior segment changes, patient reported side effects, and compliance. Study endpoint was 6 weeks from the start of treatment or an IOP increase of > 20% from baseline. A sample size calculation suggested that 8 patients in each arm would be sufficient to detect a difference of 3.2mm Hg with a power of 80%. Results: Nineteen consecutive consenting patients completed the study-9 in the steroid arm and 10 in the placebo arm. There were no statistically significant differences between groups in baseline characteristics, IOP at each study visit, or change in IOP from baseline at any time point. At 6 weeks, the change in mean IOP from baseline was + 0.50 +/- 1.52 versus + 0.70 +/- 1.44 mm Hg in the steroid and saline nasal spray groups, respectively (P=0.77). Conclusions: Patients with ocular hypertension and primary open-angle glaucoma showed no evidence of IOP elevation after 6 weeks use of beclomethasone nasal spray.

Adherence with Medical Therapy for Primary Open-Angle Glaucoma in Kenya - A Pilot Study - Murdoch, I; Nyakundi, D; Baker, H; Dulku, S; Kiage, D (PATIENT PREFERENCE AND ADHERENCE, 2020)
Background/Objectives: Adherence is a major challenge in topical glaucoma therapy, particularly in an African context. We report a pilot study assessing adherence independently for the first time in an African context. Subjects/Methods: Participants with newly diagnosed open-angle glaucoma received a weighed bottle of Lumigan 0.01% with counselling on therapy. The bottles were returned monthly for renewal and weighed on return to estimate drops taken during the period. Data collection was for one year with a short compliance questionnaire. Results: 11 patients participated. 5 (45%) failed to complete one full year of topical therapy. The overall mean number of drops per eye per day was 1.74 (SD 0.69) for the 6 with one year of monthly returned bottles and controlled IOPs at each visit. Self-perception of compliance in these patients was good. Conclusion: The signs of poor adherence based on both self-report (previous literature), and in this small-scale study of an objective measure suggest medication may not be the first-line treatment of choice in this environment. Our report does, however, raise the possibility that those patients who return for repeat prescriptions and review are indeed adhering to their treatment regimens.

Real-life experience study of the safety and efficacy of travoprost 0.004%/timoptol 0.50% fixed combination ophthalmic solution in intraocular pressure control - Olali, C; Malietzis, G; Ahmed, S; Samaila, E; Gupta, M (NIGERIAN JOURNAL OF CLINICAL PRACTICE, 2011)
Purpose: To evaluate the safety and efficacy of timolol 0.5%/travoprost 0.004% combination (duotrav) as observed in primary open-angle glaucoma (POAG), ocular hypertension (OHT) and normal tension glaucoma (NTG) in real-life conditions. Materials and Methods: Patients with uncontrolled intraocular pressure (IOP) on other medication and no contraindication to beta-blockers were switched to duotrav in 56 eyes of 28 patients. The drop in IOP was the primary outcome measured. Results: Switch to duotrav provided an additional IOP reduction after 3-month follow-up that was statistically significant for those on latanoprost (P=0.02857), bimatoprost (P=0.0497 8) and travoprost (P=0.0078). Patients on latanotrost had an additional 25.9% drop 3 months after switching to duotrav while those on bimatoprost and travatan had 18.04% and 17.59% drop, respectively, after the switch. It was effective in lowering the IOP to clinically significant levels of <= 18.5 mmHg in POAG, NTG and OHT (12.5-17.9% drop), but not in chronic angle closure glaucoma. Conclusion: Duotrav was well-tolerated and produced significant additional IOP reduction when switched from other anti-glaucoma drugs in patients with uncontrolled glaucoma. It also achieved IOP of <= 18.5 mmHg in glaucoma patients.

Patients' acceptance of a switch from dorzolamide to brinzolamide for the treatment of glaucoma in a clinical practice setting - Barnebey, H; Kwok, SY (CLINICAL THERAPEUTICS, 2000)
Background: The first topically active carbonic anhydrase inhibitor, dorzolamide, was developed to circumvent the adverse systemic effects of oral carbonic anhydrase inhibitors. However, its use has been associated with ocular discomfort. Objective: The present study examined the acceptability of brinzolamide, as measured by patients' ratings and stated preferences, in patients with glaucoma previously treated with dorzolamide in the clinical practice setting. Methods: This was a prospective, open-label, noncomparative study conducted shortly after the approval of brinzolamide. Ophthalmologists in private practice in the continental United States were asked to select patients currently using dorzolamide as their sole or combination therapy for glucoma. Patients underwent a screening assessment in which they were asked to rate their ocular comfort with dorzolamide on a scale from 1 to 6. Brinzolamide was,then substituted for dorzolamide, and patients returned for a follow-up visit similar to1 to 3 months later. At this visit, patients were asked about ocular comfort, their preferred medication, and whether they thought ocular comfort influenced their adherence to treatment. Intraocular pressure (IOP) was measured at both visits. Results: Valid visit dates (ie, both baseline and follow-up dates) were available for 447 of 501 patients from 68 of 73 sites (range, 1-40 patients per site). Because not all measurements were available for all patients at each visit, the sample size varied for each measurement. Demographic data were not available. The switch to brinzolamide resulted in a mean decrease in IOP of similar to0.8 mm Hg (P < 0.001, paired t test). Sixty-nine percent of patients (274/397) reported an improvement of <greater than or equal to>1 grade in their comfort rating with brinzolamide versus dorzolamide. The mean (+/- SD) improvement in comfort rating was 1.43 +/- 1.48 grades (P < 0.001, Wilcoxon rank sum test). When patients were asked whether their adherence to treatment was affected by the occurrence of burning and stinging, 43% (173/399) answered affirmatively Fifty-nine percent (251/424) preferred brinzolamide to dorzolamide. At the end of the study, based on patient preference, physician judgment, and other factors, 73% of responding patients (301/410) continued with brinzolamide therapy. Conclusions: In this study, the switch from dorzolamide to brinzolamide resulted in overall improvements in comfort and ocular hypotensive efficacy. However, studies using a more rigorous randomized, controlled, crossover design are needed to support these observations.

Impact of patient-held record on knowledge at 1-year follow-up for glaucoma patients: single-center randomized controlled trial - Forbes, M; Fairlamb, H; Jonker, L (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2017)
Purpose: To assess whether provision of a personalized patient-held eye health summary (glaucoma personal record) improves patients' knowledge of glaucoma at 1-year follow-up. The National Institute for Clinical Excellence has recommended such an approach to ascertain if this may ultimately help slow disease progression. Methods: Recruited patients, newly diagnosed with glaucoma conditions, were randomly allocated to receive standard clinical care or an additional glaucoma personal record, detailing the current state of each individual's eye condition. Mann-Whitney U test was applied for comparison of knowledge scores between groups at 1-year follow-up, using a validated questionnaire. Multiple linear regression analysis was applied to detect any factors significantly associated with a difference in glaucoma knowledge. Results: A total of 122 patients were recruited; 57 controls and 44 intervention patients were tested for their glaucoma knowledge, equating to 83% retention rate. Out of a maximum available 100% converted score, the median scores were 58% and 53% for the control and intervention arm, respectively (p = 0.85). Regression analysis showed that age (p = 0.015) had a negative association and level of education (p = 0.002) had a positive association with glaucoma knowledge. Conclusions: The glaucoma personal record does not impact on a patient's knowledge of glaucoma in either a positive or negative way. Other approaches to improve health literacy among glaucoma patients, particularly for patients who are elderly or have a limited educational background, must be considered to improve patients' awareness and knowledge of their own condition.

Efficacy of Single Glaucoma Medication in Combined Latanoprost and Timolol XE Therapy in Patients with Open-Angle Glaucoma and Ocular Hypertension: A Discontinuation Study - Kobayashi, H (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2012)
Purpose: To study the effect of single drug discontinuation in combined timolol XE 0.5% and latanoprost 0.005% treatment. Methods: Fifty patients with open-angle glaucoma or ocular hypertension who had received both latanoprost and timolol XE for at least 6 months were enrolled in this study. Timolol XE and latanoprost were administered once daily, timolol XE in the morning and latanoprost in the evening. Twenty-five patients discontinued timolol XE and the remaining 25 patients discontinued latanoprost. Either latanoprost or timolol XE was discontinued and 8 weeks later it was resumed. A change in intraocular pressure (IOP) was studied. Results: All patients had complete follow-up visits. A significant increase in mean IOP was found following drug discontinuation in the 2 groups. Mean change in IOP 8 weeks after discontinuation of the drug was + 1.6 +/- 1.2mmHg (10.3%+/- 8.0%) in the timolol XE group and + 4.3 +/- 1.6mmHg (+ 27.2% +/- 11.8%) in the latanoprost group. The change in the latanoprost group was significantly greater compared with that in the timolol XE group (P < 0.0001). There was no significant difference in mean IOP between before drug discontinuation and at 8 weeks after drug resumption in any group. Conclusions: There was a significant increase in IOP from discontinuation of timolol XE and latanoprost. The hypotensive effect of latanoprost in the combined drug therapy is significantly greater compared with timolol XE.

Patient satisfaction with care in an urban tertiary referral academic glaucoma clinic in the US - Peterson, KM; Huisingh, CE; Girkin, C; Owsley, C; Rhodes, LA (PATIENT PREFERENCE AND ADHERENCE, 2018)
Background: The purpose of this study was to determine the factors associated with glaucoma patients' satisfaction with their medical care by fellowship-trained glaucoma specialists in an urban tertiary referral clinic in the US. Methods: A total of 110 established patients aged ?60 years with a diagnosis of either primary open angle glaucoma, glaucoma suspect, or ocular hypertension monitored by an ophthalmologist with fellowship training in glaucoma were enrolled at an academic, urban, tertiary referral eye clinic. Enrolled patients were administered a general demographics questionnaire along with a Patient Satisfaction Questionnaire-18 (PSQ-18), a Likert scale validated tool. The seven dimensions of patient satisfaction from the PSQ-18 were summarized for the sample overall and by the patients' age, race, employment status, education level, distance travelled from home address to clinic, and glaucoma therapy type. Two-sample t-tests were used to compare group means. Spearman correlation coefficients were used to correlate satisfaction scores with peripheral vision and visual acuity function. Results: Overall, the general satisfaction scores were high (mean 4.62). Patients >= 70 years of age had lower general satisfaction with their care (mean 4.5 vs 4.8, p=0.03), the interpersonal manner of their appointment (mean 4.7 vs 4.9, p=0.009), and with their time spent with their doctor (mean 4.4 vs 4.7, p=0.03) than patients aged 60-69 years. Non-European descent patients (47% African descent and 1% other of sample) were more satisfied with the time they spent with the doctor (mean 4.7 vs 4.4, p=0.04) and with the communication during the appointment (mean 4.8 vs 4.6, p=0.04) than European descent patients (52% of sample). Patients with a higher level of education (>high school degree) were less satisfied with the accessibility and convenience of the appointment (mean 4.3 vs <= high school, 4.6, p=0.02). There were no statistically significant differences in patient satisfaction based upon employment status, distance travelled to clinic, prior glaucoma therapy, or visual function. Conclusion: Overall, across all dimensions of the PSQ-18, patients were highly satisfied with the care they received at the urban tertiary care glaucoma clinic.

Argon laser trabeculoplasty and reduction of ocular hypotensive medication used by glaucoma patients - Vaidergorn, PG; Susanna, R (CANADIAN JOURNAL OF OPHTHALMOLOGY-JOURNAL CANADIEN D OPHTALMOLOGIE, 2006)
Background: We studied the effect of argon laser trabeculoplasty (ALT) on medically controlled, pressure-stable glaucoma patients to verify whether it is possible to reduce ocular hypotensive medication after ALT while keeping intraocular pressure levels similar to those observed before the procedure. Methods: Seventy-one consecutive chronic glaucoma patients, all of whom were taking ocular hypotensive medication and had intraocular pressure at adequate levels, underwent ALT. After the laser procedure, each patient discontinued one hypotensive drug. Mean follow-up was 16.39 +/- 5.39 months. We performed diurnal pressure curves on each patient before and after trabeculoplasty to determine the effect on intraocular pressure. Results: In 39 (54.9%) patients, it was possible to reduce ocular hypotensive medication and still maintain intraocular pressure levels similar to those achieved before ALT. Interpretation: For some medically controlled, chronic glaucoma patients, ALT can reduce the amount of ocular hypotensive medication without significantly altering intraocular pressure.

A survey of attitudes of glaucoma subspecialists in England and Wales to visual field test intervals in relation to NICE guidelines - Malik, R; Baker, H; Russell, RA; Crabb, DP (BMJ OPEN, 2013)
Objectives: To establish the attitudes of glaucoma specialists to the frequency of visual field (VF) testing in the UK, using the NICE recommendations as a standard for ideal practice. Design: Interview and postal survey. Setting: UK and Eire Glaucoma Society national meeting 2011 in Manchester, UK, with a second round of surveys administered by post. Participants: All consultant glaucoma specialists in England and Wales were invited to complete the survey. Primary and secondary outcome measures: (1) Compliance of assigned follow-up VF intervals with NICE guidelines for three hypothetical patient scenarios, with satisfactory treated intraocular pressure and (a) no evidence of VF progression; (b) evidence of VF progression and (c) uncertainty about VF progression, and respondents were asked to provide typical follow-up intervals representative of their practice; (2) attitudes to research recommendations for six VF in the first 2 years for newly diagnosed patients with glaucoma. Results: 70 glaucoma specialists completed the survey. For each of the clinical scenarios a, b and c, 14 (20%), 33 (47%) and 28 (40%) responses, respectively, fell outside the follow-up interval recommended by NICE. Nearly half of the specialists (46%) agreed that 6 VF tests in the first 2 years was ideal practice, while 16 (28%) said this was practice 'not possible', with many giving resources within the NHS setting as a limiting factor. Conclusions: The results from this survey suggest that there is a large variation in attitudes to follow-up intervals for patients with glaucoma in the UK, with assigned intervals for VF testing which are, in many cases, inconsistent with the guidelines from NICE.

Trabeculectomy in Patients With Glaucoma Over 80 Years of Age: Relatively Short-term Outcomes - Duman, F; Waisbourd, M; Faria, B; Addis, V; Hsieh, M; Ekici, F; Hark, LA; Spaeth, GL (JOURNAL OF GLAUCOMA, 2016)
Purpose: To compare the surgical outcomes of trabeculectomy performed in elderly patients (above 80 y) with those of younger controls. Materials and Methods: We retrospectively reviewed the charts of patients who underwent trabeculectomy from January 1, 2009 through April 30, 2011 at the Wills Eye Hospital. Patients over 80 years of age were compared with younger controls. Outcome measures included intraocular pressure (IOP), visual acuity, number of glaucoma medications, surgical complications, and surgical failure. Surgical failure was defined as when IOP > 21 mm Hg or < 20% reduction below baseline or IOP < 5 mm Hg or reoperation for glaucoma, or loss of light perception. Results: Eighty-six eyes of patients over 80 years of age (range, 81 to 94 y) were compared with 86 eyes of younger controls (range, 22 to 79 y). Mean follow-up time was 23.9 +/- 8.0 and 25.1 +/- 8.0 months for each group, respectively. After 1 year, the failure rate was 31.3% in the elderly group, compared with 29.5% in the control group (P = 0.98). At last follow-up visit, the rate of failure between the groups was similar (P = 0.35). Postoperative complications were similar between the groups (P = 0.25). Conclusions: The surgical outcomes of trabeculectomy in patients older than 80 years were found to be similar to those of younger controls. Taking into consideration elderly glaucoma patients' general health condition and life expectancy, age alone may not be a barrier to performing glaucoma filtration surgery.

Factors associated with intraocular pressure before and during 9 years of treatment in the collaborative initial glaucoma treatment study - Musch, DC; Gillespie, BW; Niziol, LM; Cashwell, F; Lichter, PR; Collaborative Initial Glaucoma Tre (OPHTHALMOLOGY, 2008)
Purpose: To evaluate, both at initial glaucoma diagnosis and during treatment, the role of demographic and clinical factors on intraocular pressure (IOP). Design: Cohort study of patients enrolled in a randomized clinical trial. Participants: Six hundred seven patients with newly diagnosed open-angle glaucoma (OAG) were enrolled at 14 centers in the United States. Methods: After randomization to initial surgery or medications, patients were followed at 6-month intervals. Intraocular pressure was measured by Goldmann applanation tonometry. Predictive factors for IOP at baseline and during follow-up were analyzed using linear mixed models. Main Outcome Measure: Intraocular pressure at baseline and during follow-up. Results: The mean baseline IOP was 27.5 mmHg (standard deviation, 5.6 mmHg). Predictive factors for higher baseline IOP included younger age (0.7 mmHg per 10 years), male gender (2.4 mmHg higher than females), pseudoexfoliative glaucoma (5.4 mmHg higher than primary OAG), and pupillary defect (2.2 mmHg higher than those without a defect). During 9 years of follow-up, both surgery and medications dramatically reduced IOP from baseline levels, but the extent of IOP reduction was consistently greater in the surgery group. Over follow-up years 2 through 9, mean IOP was 15.0 versus 17.2 mmHg for surgery versus medicine, respectively. Predictive associations with higher IOP during follow-up included higher baseline IOP (P<0.0001), worse baseline visual field (mean deviation; P<0.0001), and lower level of education (P = 0.0019). Treatment effect was modified by smoking status: nonsmokers treated surgically had lower IOP than smokers treated surgically (14.6 vs. 16.7 mmHg, respectively; P = 0.0013). Clinical center effects were significant (P<0.0001) in both the baseline and follow-up models. Conclusions: In this large cohort of newly diagnosed glaucoma patients, predictors of pretreatment IOP and IOP measurements over 9 years of follow-up were identified. Our findings lend credence to the postulate that sociodemographic, economic, compliance, or other environmental influences play a role in IOP control during treatment.

Cost-effectiveness of monitoring glaucoma patients in shared care: an economic evaluation alongside a randomized controlled trial - Holtzer-Goor, KM; van Sprundel, E; Lemij, HG; Plochg, T; Klazinga, NS; Koopmanschap, MA (BMC HEALTH SERVICES RESEARCH, 2010)
Background: Population aging increases the number of glaucoma patients which leads to higher workloads of glaucoma specialists. If stable glaucoma patients were monitored by optometrists and ophthalmic technicians in a glaucoma follow-up unit (GFU) rather than by glaucoma specialists, the specialists' workload and waiting lists might be reduced. We compared costs and quality of care at the GFU with those of usual care by glaucoma specialists in the Rotterdam Eye Hospital (REH) in a 30-month randomized clinical trial. Because quality of care turned out to be similar, we focus here on the costs. Methods: Stable glaucoma patients were randomized between the GFU and the glaucoma specialist group. Costs per patient year were calculated from four perspectives: those of patients, the Rotterdam Eye Hospital (REH), Dutch healthcare system, and society. The outcome measures were: compliance to the protocol; patient satisfaction; stability according to the practitioner; mean difference in IOP; results of the examinations; and number of treatment changes. Results: Baseline characteristics (such as age, intraocular pressure and target pressure) were comparable between the GFU group (n = 410) and the glaucoma specialist group (n = 405). Despite a higher number of visits per year, mean hospital costs per patient year were lower in the GFU group ((sic) 139 vs. (sic) 161). Patients' time and travel costs were similar. Healthcare costs were significantly lower for the GFU group ((sic) 230 vs. (sic) 251), as were societal costs ((sic) 310 vs. (sic) 339) (p < 0.01). Bootstrap-, sensitivity- and scenario-analyses showed that the costs were robust when varying hospital policy and the duration of visits and tests. Conclusion: We conclude that this GFU is cost-effective and deserves to be considered for implementation in other hospitals.

Improving adherence to glaucoma medication: a randomised controlled trial of a patient-centred intervention (The Norwich Adherence Glaucoma Study) - Cate, H; Bhattacharya, D; Clark, A; Fordham, R; Holland, R; Broadway, DC (BMC OPHTHALMOLOGY, 2014)
Background: Improving adherence to ocular hypertension (OH)/glaucoma therapy is highly likely to prevent or reduce progression of optic nerve damage. The present study used a behaviour change counselling intervention to determine whether education and support was beneficial and cost-effective in improving adherence with glaucoma therapy. Methods: A randomised controlled trial with a 13-month recruitment and 8-month follow-up period was conducted. Patients with OH/glaucoma attending a glaucoma clinic and starting treatment with travoprost were approached. Participants were randomised into two groups and adherence was measured over 8 months, using an electronic monitoring device (Travalert (R) dosing aid, TDA). The control group received standard clinical care, and the intervention group received a novel glaucoma education and motivational support package using behaviour change counselling. Cost-effectiveness framework analysis was used to estimate any potential cost benefit of improving adherence. Results: Two hundred and eight patients were recruited (102 intervention, 106 control). No significant difference in mean adherence over the monitoring period was identified with 77.2% (CI, 73.0, 81.4) for the control group and 74.8% (CI, 69.7, 79.9) for the intervention group (p = 0.47). Similarly, there was no significant difference in percentage intraocular pressure reduction; 27.6% (CI, 23.5, 31.7) for the control group and 25.3% (CI, 21.06, 29.54) for the intervention group (p = 0.45). Participants in the intervention group were more satisfied with information about glaucoma medication with a mean score of 14.47/17 (CI, 13.85, 15.0) compared with control group which was 8.51 (CI, 7.72, 9.30). The mean intervention cost per patient was GB 10.35 pound (<US$16) and not cost-effective. Conclusions: Adherence with travoprost was high and not further increased by the intervention. Nevertheless, the study demonstrated that provision of information, tailored to the individual, was inexpensive and able to achieve high patient satisfaction with respect to information about glaucoma medication. Measurement of adherence remains problematic since awareness of study participation may cause a change in participant behaviour.

A Clinician's Guide to the Assessment and Management of Nonadherence in Glaucoma - Budenz, DL (OPHTHALMOLOGY, 2009)
Purpose: To apply lessons learned in the treatment of systemic hypertension to the problem of nonadherence in glaucoma medical therapy. Clinical Relevance: Although physicians recognize that nonadherence with glaucoma medication is a problem, most lack the skill set to identify nonadherent patients, to identify the causes of nonadherence, and to provide solutions to address nonadherence. Methods: A PubMed search was conducted using the terms "adherence" OR "compliance" AND "hypertension," with the following limitations: title, English language, humans, from 2000 through 2009. Other studies identified outside of the PubMed search were included if relevant. Results: Studies from the systemic hypertension literature suggest that simplifying medication regimens, lowering costs, and patient education about the disease and the importance of taking medications are successful strategies for improving adherence. In addition, good family or social support, frequent physician visits, and pairing medication administration with specific activities (such as meals or brushing one's teeth) can help improve adherence. Conclusions: The body of literature on adherence interventions in chronic diseases such as systemic hypertension shows that although many interventions have been tested and evaluated, only some are successful. Paradigms derived from behavioral medicine and nursing offer valuable lessons on how to motivate patients to change behavior, but these activities require skill sets not traditionally taught in medical school. Just as there are myriad causes of nonadherence, the interventions most likely will need to be multifaceted and tailored to the individual patient. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references. Ophthalmology 2009; 116:S43-S47 (C) 2009 by the American Academy of Ophthalmology.

Evaluation of compliance with the EGS Guidelines in Spain, using Achievable Benchmarks of Care (ABC (R)) methodology: The IMCA Study - Castejon-Cervero, MA; Jimenez-Parras, R; Fernandez-Arias, I; Teus-Guezala, MA; IMCA Study Grp (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2011)
PURPOSE. To evaluate compliance with diagnostic and therapeutic recommendations of the European Glaucoma Society (EGS) for the management of glaucoma in Spain, as determined using the Achievable Benchmarks of Care approach. METHODS. A panel of 3 experts extracted quality and process-of-care indicators from the EGS guidelines. Investigators from all over the country, representative of Spanish ophthalmologists, were invited to participate in the study, completing a questionnaire on quality indicators (pertaining to the center) and process-of-care indicators (pertaining to all patients) for the first, diagnostic visit (retrospective) and the study visit. RESULTS. A total of 495 Spanish ophthalmologists included 5,060 patients with glaucoma or intraocular hypertension. The treatment was initiated with monotherapy in 88.5% of the patients. Overall, the percentage compliance with diagnostic examinations was 84.6% for intraocular pressure measurement, 96.3% for optic nerve head evaluation, 76.6% for visual field evaluation, 29.5% for central corneal thickness evaluation, and 49.3% at the study visit. The benchmark performance was close to 100% for most examinations. Only 32.8% of the centres had a written protocol for the management of the patients with glaucoma, and in these centers the recommendations of the EGS were followed in a higher proportion (p < 0.0001) than in the rest. CONCLUSIONS. The use of local protocols for the management of glaucoma seems to enhance compliance. Benchmark performance was close to 100% in most indicators, suggesting that EGS recommendations are attainable in Spain. The overall performance suggests that certain diagnostic procedures are, in practice, not as widely used as recommended.

The Rationale for Selective Laser Trabeculoplasty in Africa - Realini, T; Olawoye, O; Kizor-Akaraiwe, N; Manji, S; Sit, A (ASIA-PACIFIC JOURNAL OF OPHTHALMOLOGY, 2018)
Glaucoma is the leading cause of irreversible blindness in Africa. The condition is treatable but not curable. There are numerous obstacles to glaucoma care in Africa, including availability, accessibility and affordability of treatments, as well as medication nonadherence among patients. Medical therapy is costly relative to the average income in Africa and it requires daily self-dosing by patients. Surgery is of limited availability in many regions in Africa, and a high proportion of patients refuse surgery because it is expensive. Selective laser trabecu-loplasty (SLT) proves to be a favorable alternative to medical or surgical care, as it is highly effective and safe in people of African descent, more cost-effective than medical therapy, quick and easy to perform, and portable. The procedure also requires no postoperative care, thus obviates the issue of nonadherence. In uncontrolled studies, SLT has a high response rate and it lowers intraocular pressure by 30% to 40%, which exceeds the goal in international guidelines for initial therapies. The African Glaucoma Consortium (AGC), a member-driven stakeholder collective, has been formed in part to develop the infrastructure for continent-wide improvements in glaucoma care. It embraces SLT as a potential key tool in their development plans. The mission of AGC includes improving clinical care by educating existing and new health care professionals to expand the provider network, by conducting trials to identify optimal care strategies for glaucoma in Africa, and by facilitating the development of an integrated network of Centers of Excellence to bring SLT and other crucial glaucoma therapies to communities throughout Africa.

Glaucoma Disease Characteristics and Outpatient Visit Adherence Among Prisoners - Tiwana, MS; Kanu, L; Dikopf, M; Edward, D (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)

Identifying risk factors for blindness from primary open-angle glaucoma by race: a case-control study - Williams, AM; Huang, W; Muir, KW; Stinnett, SS; Stone, JS; Rosdahl, JA (CLINICAL OPHTHALMOLOGY, 2018)
Purpose: To examine the factors associated with blindness from primary open-angle glaucoma (POAG) among black and white patients at our institution. Patients and methods: For this retrospective, case-control study, patients legally blind from POAG ("cases") were matched on age, race, and gender with non-blind POAG patients ("controls"). Thirty-seven black case-control pairs and 19 white case-control pairs were included in this study. Clinical variables were compared at initial presentation and over the course of follow-up. Results: Black case-control pairs and white case-control pairs had similar characteristics at presentation, including cup-to-disc ratio and number of glaucoma medications. However, over the course of follow-up, black cases underwent significantly more glaucoma surgeries than matched controls (2.4 versus 1.2, p=0.001), whereas white cases and controls had no significant difference in glaucoma operations (0.9 versus 0.6, p=0.139). Our analysis found that glaucoma surgery is associated with blindness in black patients (odds ratio [OR] 1.6, 95% CI 1.1-2.2) but not in white patients (OR 1.5, 95% CI 0.7-3.2). Conclusion: Black and white case-control pairs with POAG shared similar risk factors for blindness at presentation. However, over the follow-up period, black cases required significantly more glaucoma surgeries compared to black controls, whereas there was no significant difference in surgery between white cases and controls. There was no difference in medication changes in either case-control set.

Ophthalmologist-Patient Communication, Self-efficacy, and Glaucoma Medication Adherence - Sleath, B; Blalock, SJ; Carpenter, DM; Sayner, R; Muir, KW; Slota, C; Lawrence, SD; Giangiacomo, AL; Hartnett, ME; Tudor, G; Goldsmith, JA; Robin, AL (OPHTHALMOLOGY, 2015)
Objective: To examine the associations of providerepatient communication, glaucoma medication adherence self-efficacy, and outcome expectations with glaucoma medication adherence. Design: Prospective, observational cohort study. Participants: Two hundred seventy-nine patients with glaucoma who were newly prescribed or taking glaucoma medications were recruited at 6 ophthalmology clinics. Methods: Patients' visits were video recorded and communication variables were coded using a detailed coding tool developed by the authors. Adherence was measured using Medication Event Monitoring Systems for 60 days after their visits. Main Outcome Measures: The following adherence variables were measured for the 60-day period after their visits: whether the patient took 80% or more of the prescribed doses, percentage of the correct number of prescribed doses taken each day, and percentage of the prescribed doses taken on time. Results: Higher glaucoma medication adherence self-efficacy was associated positively with better adherence with all 3 measures. Black race was associated negatively with percentage of the correct number of doses taken each day (beta = -0.16; P < 0.05) and whether the patient took 80% or more of the prescribed doses (odds ratio, 0.37; 95% confidence interval, 0.16-0.86). Physician education about how to administer drops was associated positively with percentage of the correct number of doses taken each day (beta = 0.18; P < 0.01) and percentage of the prescribed doses taken on time (beta = 0.15; P < 0.05). Conclusions: These findings indicate that provider education about how to administer glaucoma drops and patient glaucoma medication adherence self-efficacy are associated positively with adherence. (C) 2015 by the American Academy of Ophthalmology.

Clinical efficacy analysis of Ahmed glaucoma valve implantation in neovascular glaucoma and influencing factors: A STROBE-compliant article - He, Y; Tian, Y; Song, WT; Su, T; Jiang, HB; Xia, XB (MEDICINE, 2017)
This study aimed to evaluate the efficacy of Ahmed glaucoma valve (AGV) implantation in treating neovascular glaucoma (NVG) and to analyze the factors influencing the surgical success rate.This is a retrospective review of 40 eyes of 40 NVG patients who underwent AGV implantation at Xiangya Hospital of Central South University, China, between January 2014 and December 2016. Pre- and postoperative intraocular pressure (IOP), visual acuity, surgical success rate, medications, and complications were observed. Surgical success criteria were defined as IOP 21 and >6 mm Hg with or without additional medications. Kaplan-Meier survival curves and Multivariate cox regression analysis were used to examine success rates and risk factors for surgical outcomes.The mean follow-up period was 8.883.12 months (range: 3-17). IOP declined at each visit postoperatively and it was statistically significant (P<.001). An average of 3.55 +/- 0.86 drugs was applied preoperatively, while an average of 0.64 +/- 0.90 drugs was used postoperatively, with the difference being of statistical significance (P<.05). The complete surgical success rate of 3, 6, and 12 months after the operation was 85%, 75%, and 65%, respectively. Meanwhile, the qualified success rate of 3, 6, and 12 months after the operation was 85%, 80%, and 77.5%, respectively. The multivariate cox regression analysis showed that age (hazard ratio: 3.717, 7.246; 95% confidence interval: 1.149-12.048, 1.349-38.461; P=.028, .021) was influencing factors for complete success rate and qualified success rate among all NVG patients. Gender, previous operation history, primary disease, and preoperative IOP were found to be not significant.AGV implantation is an effective and safe surgical method to treat NVG. Age is an important factor influencing the surgical success rate.

Long-term benefit of reduced intraocular pressure in primary open-angle glaucoma patients in Ethiopia - Alemu, AM; Kristoffersen, CJ; Kristoffersen, MS; Stewart, JA; Stewart, WC (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2010)
PURPOSE. To determine the incidence of progression of primary open-angle glaucoma at individual levels of mean intraocular pressure (IOP) in patients in Ethiopia. METHODS. A retrospective, multicenter, cohort analysis of patient records with at least 5 years of potential follow-up were evaluated for risk factors associated with progressive optic disc and visual field loss. RESULTS. There were 300 patients with the potential of 5 years of follow-up. In total, 166 patients progressed before 5 years and 134 remained stable for the full 5-year follow-up period. Of the total sample, 84% of patients with IOPs <= 19 (n = 117/139), 53% of patients with IOPs of 20 (n = 9/17), 14% of patients with IOPs of 21-24 (n = 9/63), and 0% of the patients with IOPs of >= 25 mmHg (n = 0/79) remained stable over at least 5 years. The mean IOP was 17.4 +/- 2.1 in the stable group and 25.0 +/- 5.9 mmHg in the progressed group (p < 0.0001). The highest average peak IOP was 24.5 +/- 4.5 in the stable group and 29.0 +/- 6.1 mmHg in the progressed group (p < 0.0001). A multivariant regression analysis to determine risk factors for progression was positive for mean IOP (p = 0.0097). CONCLUSIONS. This study suggests that IOP reduction in a developing country, despite potential limitations in diagnostic techniques, follow-up, and compliance, can be effective in reducing the risk of glaucomatous progression over long-term follow-up. (Eur J Ophthalmol 2010; 20: 310-5)

Glistenings in a large series of hydrophobic acrylic intraocular lenses - Colin, J; Orignac, I; Touboul, D (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2009)
PURPOSE: To evaluate the incidence and severity of glistenings in hydrophobic acrylic intraocular lenses (IOLs) and assess the potential correlation between glistenings and clinical and demographic factors. SETTING: Service d'Ophtalmologie, Centre Hospitalier et Universitaire Bordeaux, Bordeaux, France. METHODS: Eligible patients received an AcrySof IOL between September 2000 and December 2007 and had a routine ophthalmic visit between January 2007 and March 2008. The incidence and severity of glistenings were graded subjectively and analyzed in relation to patient age and sex, length of follow-up, IOL model, IOL power, neodymium:YAG laser capsulotomy, corrected distance visual acuity (CDVA), spherical equivalent (SE), and selected ocular and systemic diseases and medications. RESULTS: Glistenings occurred in 157 (60.4%) of the 260 eyes; they were absent in 103 eyes (39.6%). Glistenings were of grade 1 severity in 87 eyes (33.5%) and of grade 2 severity in 70 eyes (26.9%). CONCLUSIONS: The results suggest a potential association between the incidence of glistenings and IOL power and glaucoma, but not between glistenings and age, sex, IOL model, length of follow-up, CDVA, SE, or most ocular and systemic diseases and medications.

Characteristics and Treatment Patterns of Newly Diagnosed Open-Angle Glaucoma Patients in the United States - Schwartz, GF; Patel, A; Naik, R; Lunacsek, O; Ogbonnaya, A; Campbell, J (OPHTHALMOLOGY GLAUCOMA, 2021)
Purpose: To characterize newly diagnosed primary open-angle glaucoma (OAG) patients and to describe their treatment journey in United States clinical practice according to the use of topical therapy, laser trabeculoplasty, and surgical procedures. Design: Retrospective claims database study. Participants: Patients with at least 2 diagnoses of OAG 7 days or more apart and within 1 year, with the first (index) diagnosis in 2010, at least 30 months of continuous enrollment before index diagnosis with no OAG diagnosis or medication (exception for ocular hypertension diagnosis), and 48 months of continuous enrollment. Methods: Analysis of United States healthcare insurance claims database (July 2007-December 2014). Main Outcome Measures: Treatment patterns and ophthalmology visits were evaluated over 48 months in 4 cohorts based on initial therapy after the index diagnosis: (1) drug monotherapy, (2) combination drug therapy, (3) glaucoma procedure, or (4) no claims for treatment. Treatment modification was defined as an addition to or change in drug therapy or procedure. Results: In total, 83.0% of patients (5120/6172) began a drug therapy (69.5%) or underwent a procedure initially (13.5%); topical prostaglandin analogs (n = 2887/5120 [56.4%]) and laser trabeculoplasty (n = 705/5120 [13.8%]) were the most common. During the 4-year follow-up, 58.3% of patients (2109/3620) who began drug monotherapy experienced no further treatment modification. Over this period, 43.8% of patients who began treatment (2242/5120) experienced a treatment modification to the first treatment. Two thirds (1505/2242 [67.1%]) of these patients subsequently underwent a third treatment modification. Ophthalmology visits declined over time regardless of initial therapy, with the greatest decrease among the untreated and first-treatment procedure cohorts. Conclusions: The high rates of 2 or 3 treatment modifications over the 4-year period suggest an unmet need for glaucoma therapies with durable and predictable actions. Ophthalmology Glaucoma 2021;4:117-125 (C) 2020 by the American Academy of Ophthalmology.

The Efficacy of the After-visit Summary in Medication Recall Among Glaucoma Patients - Hirabayashi, KJ; Pomerantz, M; Radell, JE; Chadha, N; Thomas, S; Serle, JB (JOURNAL OF GLAUCOMA, 2020)
Precis: To assess the after-visit summary (AVS) as a tool for glaucoma medication recall. Medication recall was associated with level of education and complexity of medication regimen. Receiving an AVS was not associated with better medication recall. Purpose: The purpose of this study was to determine whether patients given the AVS have better or worse glaucoma medication recall. Materials and Methods: Observational clinical study. Adults on >= 1 glaucoma medications examined between June 30, 2017 and August 2, 2017. Data collection: in-person questionnaire and retrospective chart review. Self-reported glaucoma medications compared with prescribed glaucoma medication regimen verified by electronic medical record. Medication recall assessed using 3-point scoring: 1 point each for; (1) name or color of bottle or cap; (2) treatment eye(s); and (3) dosing regimen. Data analysis: 2-sample Welchttest, 2-proportionz-test, analysis of variance, univariate, and multivariate regression. Results: A total of 118 patients enrolled: age 69.7 +/- 12.9 years (mean +/- SD), 55.9% of patients had received an AVS at the previous visit. Of these, 33.3% reported receiving an AVS, 51.2% reported not receiving one (15.1% did not recall or respond). Patients who had received AVSs had lower medication recall scores than those who did not (2.4 +/- 1.0 vs. 2.7 +/- 0.6,P=0.04). Receipt of an AVS was associated with having Nisha Chadha as their provider (P=0.01), fewer days since prior visit (P=0.0001), and medication regimen change at prior visit (P<0.0001). Multivariate analysis revealed completion of associate's degree or higher and fewer prescribed medications to be independent predictors of higher recall score (P=0.0002 and 0.002). Conclusions: AVSs were conceived to enhance patient care. This study indicates this goal is not achieved consistently. Less education and more complex medication regimens were identified as barriers to medication recall. Additional investigations should explore if modifying this document and enhanced explanation of its use will impact medication recall and health outcomes.

Evaluation of practice patterns for the care of open-angle glaucoma compared with claims data - The glaucoma adherence and persistency study - Quigley, HA; Friedman, DS; Hahn, SR (OPHTHALMOLOGY, 2007)
Objective: To perform a chart review to measure the validity of large claims databases in estimating patient cooperation with eyedrop therapy and to assess physician adherence with guidelines for a preferred practice pattern (PPP) using a new metric. Design: Claims database analysis, chart review, and telephone survey. Participants: From 10 260 persons who were recently prescribed a prostaglandin eyedrop for open-angle glaucoma (OAG), a sample of 300 charts (3650 visits) was selected for detailed abstraction. Methods: Database review of pharmacy refill, diagnostic testing, and visit information, with chart review of a sample of patients from the database and interviews with an overlapping sample of patients and physicians. Main Outcome Measures: The individual patient medication possession ratio (MPR), an index estimating the proportion of time that patients have prescribed drug available for use, frequency of examination findings present in charts, and associations between MPR and physician adherence to a PPP. Results: Chart data confirm that the claims database accurately identified the specific glaucoma eyedrop prescribed, but often identified long-term OAG patients as being new to treatment. Physicians frequently used billing codes for OAG in patients with normal visual field tests. Physicians varied dramatically in their adherence to the PPP, performing intraocular pressure measurements, disc evaluations and imaging, and visual field tests on 90% of OAG patients, but carrying out gonioscopy, central corneal thickness measurement, and setting of target intraocular pressure (IOP) on half of patients. Conclusions: Large claims databases permit conclusions regarding patient cooperation with glaucoma eyedrop therapy, but they should be used cautiously in imputing severity of disease and prior treatment history. Physician adherence to practice guidelines varied substantially; thus, scoring systems for physician behavior have promise in measuring outcome improvements related to better care.

Do adherence rates and glaucomatous visual field progression correlate? - Rossi, GCM; Pasinetti, GM; Scudeller, L; Radaelli, R; Bianchi, PE (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2011)
PURPOSE. To assess the relation between visual field progression and adherence rate in patients with glaucoma using Travatan Dosing Aid (R) (TDA). METHODS. In this 36-month retrospective. study, 35 patients with primary open-angle glaucoma on travoprost or travoprost/timolol fixed combination monotherapy were submitted to ophthalmic examination and to visual field (VF) test from 2007 to 2009. Adherence was recorded with TDA. The association between VF progression (from 2007 to the end of the follow-up period) and a number of predictors (adherence rates at 12 months) was tested by means of chi-square test (or Fisher exact test) or Mann-Whitney test as appropriate. RESULTS. The mean (+/- SD) adherence rates were 71.9%+/- 27.8% after 1 month of follow-up and 76.8%+/- 20.9% at 12 months. A total of 25 (71.4%) patients with stable VF had a median adherence rate (IQR) of 85% (75%-97%); patients who worsened (n=10; 28.6%) recorded a median (IQR) adherence of 21% (9%-45%) (p < 0.001). No association was found between VF progression and any of the other variables (age, sex, schooling, visual acuity, intraocular pressure (IOP) at baseline and over time, other ocular diseases, time since diagnosis and actual therapy, number of concomitant systemic therapies). Patients who were at least 90% adherent did not progress, while 43.5% of the patients with lower adherence worsened (p=0.01). CONCLUSIONS. Our data suggest that adherence rate may play a role in glaucomatous damage and/or progression; the target IOP therefore should be adjusted by adherence rates. Monitoring tools, educational programs, use of videos, a better doctor-patient relationship, or other means to improve adherence are desirable and necessary to preserve visual function.

Transscleral Cyclophotocoagulation as Primary Surgical Intervention in Glaucoma - Winkler, NFK; Funk, J (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2013)
Background: The gold standard of surgical interventions in medically uncontrolled glaucoma is trabeculectomy. Cyclophotocoagulation is often performed only as a secondary/tertiary surgery. Since trabeculectomy demands a high degree of postsurgical compliance to achieve satisfying results, some patients do not qualify for trabeculectomy. Patients and Methods: During cyclophotocoagulation, the ciliary processes were coagulated using a transscleral diode laser. 49 eyes of 47 patients (25 women and 22 men) were included in our study. Patients were regularly followed up for 24 months. During follow-up, IOP, best corrected visual acuity and number of antiglaucoma drugs were recorded. Results: The mean age was 69.27 +/- 14.45 years. The diagnosis was open-angle glaucoma in 15 eyes, pseudoexfoliative glaucoma in 12 eyes, secondary rubeotic glaucoma in 7 eyes and secondary glaucoma without further specification in 15 eyes. On average, cyclophotocoagulation reduced intraocular pressure by 14.45 +/- 11.77 mmHg (-42.7%, p < 0.001). Medication could be reduced by 1.31 +/- 1.27 (-52%, p < 0.001). On average, visual acuity deteriorated by 0.383 LogMAR (+/- 0.848, p = 0.004). Conclusion: For selected glaucoma patients, cyclophotocoagulation could be an option as primary surgical intervention to lower intraocular pressure.

Microinvasive Glaucoma Stent (MIGS) Surgery With Concomitant Phakoemulsification Cataract Extraction: Outcomes and the Learning Curve - Al-Mugheiry, TS; Cate, H; Clark, A; Broadway, DC (JOURNAL OF GLAUCOMA, 2017)
Purpose: To evaluate learning effects with respect to outcomes of a microinvasive glaucoma stent (MIGS) inserted during cataract surgery in glaucoma patients. Patients and Methods: Single surgeon, observational cohort study of 25 consecutive Ivantis Hydrus microstent insertions, with a minimum follow-up of 12 months. A learning curve analysis was performed by assessing hypotensive effect, adverse effects, and surgical procedure duration, with respect to consecutive case number. Success was defined with respect to various intraocular pressure (IOP) targets (21, 18, 15mmHg) and reduction in required antiglaucoma medications. Complete success was defined as achieving target IOP without antiglaucoma therapy. Results: No clinically significant adverse events or learning effects were identified, although surgical time reduced with consecutive case number. Mean follow-up was 16.8 months. At final follow-up the mean IOP for all eyes was reduced from 18.1 (+/- 3.6) mm Hg [and a simulated untreated value of 25.9 (+/- 5.2) mm Hg] to 15.3 (+/- 2.2) mm Hg (P = 0.007; < 0.0001) and the mean number of topical antiglaucoma medications was reduced from 1.96 (+/- 0.96) to 0.04 (+/- 0.20) (P < 0.0001). Complete success (IOP < 21 mm Hg, no medications) was 96% at final follow- up. Complete success (IOP < 18 mm Hg, no medications) was 80% at final follow-up, but only 32% with a target IOP of < 15 mm Hg (no medications). Conclusions: No significant learning curve effects were observed for a trained surgeon with respect to MIGS microstent insertion performed at the time of cataract surgery. Adjunctive MIGS surgery was successful in lowering IOP to <18 mm Hg and reducing/abolishing the requirement for antiglaucoma medication in eyes with open-angle glaucoma, but less successful at achieving low IOP levels (< 15 mm Hg).

Awareness and Adherence in Young and Older Glaucoma Patients who Live in European Side of Istanbul - Tarakcioglu, HN; Yildiz, AM; Sonbahar, O; Yigit, U; Ozkaya, A (MEDICAL JOURNAL OF BAKIRKOY, 2019)
Objective: We aimed to compare the demographics, awareness about glaucoma, and adherence to the treatment between the young and old population of primary open angle glaucoma (POAG) patients. Methods: The POAG patients who were under follow-up in Bakirkoy Training and Research Hospital Ophthalmology Clinic and were using medication since at least one year and volunteered for our survey were included this cross-sectional study between April and May 2018. Two surveys which included 13 questions and were used in previous studies were enriched with 6 additional questions and applied to the patients. The patients were divided into two groups according to the World Health Organization's classification in regard to age as <= 65 years (young patients) and >65 years (old patients) and compared in regards to the survey questions. Results: There was not statistically significant between the two groups in regards to gender, general awareness about glaucoma, regular follow-up, regular drug use, family history of glaucoma, disability in hand and arm movements, duration of glaucoma (p>0.05 for all). There was a statistical difference between the two groups in regards to the education level (the patients <= 65 years were more educated, p=0.03), awareness of blindness secondary to the disease (more frequent in the patients <= 65 years old, p=0.02), awareness of drug's brand (more frequent in the patients <= 65 years old, p=0.003), requiring assistance while using the drugs (more frequent in the group of patients >65 years-old, p=0.01), monthly number of forgetting the drug doses (more frequent in the group of patients >65 years-old, p=0.006), living alone (more frequent in the group of patients >65 years-old, p=0.02), and the number of used drugs (more frequent in the group of patients >65 years-old, p=0.03). Conclusion: It is obvious that the patients who are >65 years old will be less adherent to glaucoma treatment as they more frequently require assistance for drug use and live alone.

Efficacy and safety of latanoprost in eyes with uveitic glaucoma - Markomichelakis, NN; Kostakou, A; Halkiadakis, I; Chalkidou, S; Papakonstantinou, D; Georgopoulos, G (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2009)
To compare the efficacy and safety of latanoprost against a fixed combination of dorzolamide and timolol in eyes with elevated intraocular pressure (IOP) or glaucoma and anterior or intermediate uveitis. Fifty-eight patients with anterior or intermediate uveitis and elevated IOP or glaucoma presented or followed up in the Ocular Inflammation and Immunology Service of General Hospital of Athens were randomly assigned to receive treatment either with latanoprost (30) or with dorzolamide/timolol (28). The main outcome measures were inflammatory relapses and IOP response to treatment. Ten patients (34%) in the latanoprost group and sixteen patients (57%) in the dorzolamide/timolol group experienced relapses of anterior uveitis (p = 0.93). There was no statistical difference between the two groups in respect of inflammatory relapses (p = 0.21). Twenty-one patients were followed up before starting latanoprost. The number of recurrences of anterior uveitis per patient per year before treatment with latanoprost was 0.82 +/- 1.2. The rate of relapses per patient per year after starting latanoprost was 0.39 +/- 0.7 for these patients (p = 0.038). After 1 year of treatment, intraocular pressure was dropped from 27.8 +/- 8.4 mmHg to 18.6 +/- 5.3 mmHg (p < 0.001) in the latanoprost group and from 28.2 +/- 8.1 mmHg to 22.6 +/- 10.1 mmHg (p < 0.001) in the dorzolamide/timolol group. Four patients during treatment with latanoprost and five patients during treatment with dorzolamide/timolol developed macular edema. Latanoprost is safe and equally effective to a fixed combination of dorzolamide and timolol in the treatment of uveitic glaucoma.

Detection of Non-Glaucomatous Ocular Pathology and Barriers to Follow-Up in a Community Glaucoma Detection Program - Hu, WD; Hu, CX; Tran, J; Pequignot, E; Waisbourd, M; Hark, LA; Katz, LJ (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2014)

Outcomes of Combined iStent Trabecular Micro-Bypass and Cataract Surgery for the Treatment of Open-Angle Glaucoma in a Saudi Population - Al Habash, A; Khan, O (CLINICAL OPHTHALMOLOGY, 2020)
Purpose: To assess the effectiveness and safety of a single iStent trabecular micro-bypass stent implantation in combination with cataract surgery in lowering the intra ocular pressure (IOP) and number of anti-glaucoma medications in Saudi patients with open-angle glaucoma (OAG). Setting: King Fahad Hospital of the University, Al Khobar, Saudi Arabia. Design: Prospective, non-comparative, uncontrolled, non-randomized interventional case series. Methods: One iStent was implanted during phacoemulsification cataract surgery for adult patients with OAG by a single surgeon over a period of 3 years. Main outcome measures include number of anti-glaucoma medications, IOP, corrected distance visual acuity (CDVA) and complications. Results: Thirty-six eyes of 33 patients with OAG underwent the surgery. The pre-operative mean IOP and mean anti-glaucoma medications were 17.47 +/- 5.44 mmHg and 2.69 +/- 0.92, respectively. At 1 year of follow-up mean, IOP decreased to 13.44 +/- 1.99 (23.1% reduction) (P<0.001) and mean anti-glaucoma medications decreased to 1.47 +/- 1.13 (45.4% reduction) (P<0.001). Conclusion: After 12-month follow-up, phacoemulsification with the implantation of a single iStent seems to be an effective and safe procedure to lower IOP and the number of anti-glaucoma medications, and to overcome the problems associated with medication nonadherence in OAG patients with cataracts.

12-week study comparing the fixed combination of brimonidine and timolol with concomitant use of the individual components in patients with glaucoma and ocular hypertension - Goni, FJ; Brimonid Timolol Fixeed Study Grp (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2005)
PURPOSE. To evaluate the efficacy and safety of fixed-combination brimonidine tartrate 0.2%/timolol 0.5% ophthalmic solution dosed BID and demonstrate non-inferiority to concomitant use of brimonidine tartrate 0.2% BID and timolol 0.5% BID in glaucoma and ocular hypertension patients with intraocular pressure (10P) uncontrolled on monotherapy. METHODS. Randomized, multicenter, double-masked, parallel-group study involving 371 patients with inadequate IOP control (IOP from 22 to 34 mmHg) after >= 3 weeks of run-in on any monotherapy. Patients were treated with fixed-combination brimonidine/timolol BID (fixed-combination group, n=188) or concomitant brimonidine BID and timolol BID (concomitant group, n=183). IOP was assessed pre-dose and 2 hours after morning dosing at weeks 2, 6, and 12. RESULTS. A total of 355 patients (96%) completed the study. Patient demographics, run-in monotherapy, and baseline mean IOP on monotherapy were comparable between treatment groups. During follow-up, the mean reduction from baseline IOP was significant (p<0.001) at all time points and ranged from 4.4 to 5.3 mmHg in each group. Brimonidine/timolol fixed combination was as effective as concomitant therapy with respect to mean IOP and mean change from baseline IOP at all time points and visits. Between-group differences were <= 0.35 mmHg for mean IOP and <= 0.30 mmHg for, mean change from baseline IOP; none were significant. No unexpected side effects were associated with the fixed combination. Both treatments were well tolerated with no difference in adverse events between groups. CONCLUSIONS. Brimonidine/timolol fixed-combination therapy is as safe and effective as concomitant treatment with the individual components. Its simplified dosing regimen has the potential to improve compliance.

LONG-TERM SURGICAL OUTCOMES OF PRIMARY CONGENITAL GLAUCOMA IN CHINA - Zhang, XL; Du, SL; Fan, Q; Peng, SX; Yu, MB; Ge, J (CLINICS, 2009)
OBJECTIVE: To evaluate the long-term outcomes of three surgical procedures for the treatment of primary congenital glaucoma (PCG). INTRODUCTION: PCG is one of the main causes of blindness in children. There is a paucity of contemporary data on PCG in China. METHODS: A retrospective study of 48 patients (81 eyes) with PCG who underwent primary trabeculectomy, trabeculotomy, or combined trabeculotomy and trabeculectomy (CTT). RESULTS: All patients were less than 4 years (yrs) of age, with a mean age of 2.08 +/- 1.23 yrs. The mean duration of follow-up was 5.49 +/- 3.09 yrs. The difference in success rates among the three surgical procedures at 1, 3, 6 and 9 yrs was not statistically significant (p = 0.492). However, in patients with over 4 yrs of follow-up, Kaplan-Meier survival analysis revealed that the success rates of trabeculectomy and CTT declined more slowly than that of trabeculotomy. Among the patients, 66.22% acquired good vision (VA >= 0.4), 17.57% acquired fair vision (VA = 0.1 - 0.3), and 16.22% acquired poor vision (VA < 0.1). The patients with good vision were mostly in the successful surgery group. Myopia was more prevalent postoperatively (p = 0.009). Reductions in the cup-disc ratio and corneal diameter were only seen in the successful surgery group (p = 0.000). In addition, the successful surgery group contained more patients that complied with a regular follow-up routine (p = 0.002). DISCUSSION: Our cases were all primary surgeries. Primary trabeculectomy was performed in many cases because no treatment was sought until an advanced stage of disease had been reached. CONCLUSIONS: In contrast to most reports, in the present study, trabeculectomy and CTT achieved higher long-term success rates than trabeculotomy. The patients with successful surgical results had better vision. Compliance with a routine of regular follow-up may increase the chances of a successful surgical outcome.

Comparison of the intraocular pressure-lowering effect and safety of brimonidine/timolol fixed combination and 0.5 % timolol in normal-tension glaucoma patients - Kim, JM; Kim, TW; Kim, CY; Kim, HK; Park, KH (JAPANESE JOURNAL OF OPHTHALMOLOGY, 2016)
Purpose To compare the therapeutic efficacy and safety of brimonidine/timolol fixed-combination (BTFC) and 0.5 % timolol ophthalmic solution in normal-tension glaucoma (NTG) patients. Methods This was a multi-institution, randomized, active-controlled, open-label, parallel-group study. After a full ophthalmic and glaucoma examination, a total of 110 NTG patients-55 undergoing therapy with BTFC and 55 0.5 %, with timolol-participated in this study. Among them, 1 failed to meet the inclusion/exclusion criteria, 10 revoked their consent to participate in the study, 3 had adverse reactions, and 1 had a drug adherence rate of less than 70 %. Ultimately, a total of 95 patients-48 in the BTFC group and 47 in the 0.5 % timolol group-completed the study. The study visits took place at baseline and at 4 and 12 weeks. Diurnal IOP was measured at 9 a.m., 11 a.m., and 5 p.m. during the baseline visit and the visit at 12 weeks after eye-drop instillation. At each follow-up visit, compliance was assessed. Throughout the study, all adverse events were recorded and monitored by the investigators. Results The average difference in IOP change measured at 11 a.m. 12 weeks after administration between the two groups was 2.10 +/- 2.59 mmHg. The BTFC group had a better IOP-lowering effect at all time points than did the 0.5 % timolol group. The ratio of patients whose average IOP had decreased by[20 % after 4 and 12 weeks was 50 and 56 % in the BTFC group, respectively, whereas it was 29.41 and 23.53 % in the 0.5 % timolol group, respectively (p = 0.034, <0.001). Conclusions BTFC has a superior IOP-lowering effect than 0.5 % timolol in NTG patients.

Trabectome surgery for primary and secondary open angle glaucomas - Jordan, JF; Wecker, T; van Oterendorp, C; Anton, A; Reinhard, T; Boehringer, D; Neuburger, M (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2013)
In most forms of open angle glaucoma, the trabecular meshwork is the main barrier for aqueous humor outflow, causing elevated intraocular pressure (IOP). The Trabectome is a minimal invasive device for the surgical treatment of open angle glaucoma, particularly eliminating the juxtacanalicular meshwork. This study was conducted to compare the effectiveness and complication profile among different glaucoma subgroups. Single center prospective observational study. There were 557 consecutive eyes of 487 patients included in this study. Trabectome surgery was performed either alone or in combination with cataract surgery. Intraoperative and postoperative complications were documented systematically. Main outcome measures were IOP reduction over time and the preoperative and postoperative number of IOP-lowering medications. Due to subgroup sizes, only data from eyes with primary open angle glaucoma and pseudoexfoliation glaucoma were processed for statistical analysis. For the 261 eyes classified as primary open angle glaucoma, preoperative IOP was 24 +/- 5.5 mmHg (mean +/- SD) under 2.1 +/- 1.3 IOP-lowering medications. After a mean follow-up of 204 +/- 238 days, IOP was reduced to 18 +/- 6.1 mmHg, and medication was reduced to 1.2 +/- 1.1. For the 173 eyes classified as pseudoexfoliation glaucoma, after a mean follow-up of 200 +/- 278 days, IOP was reduced from 25 +/- 5.9 mmHg to 18 +/- 8.2 mmHg, and medication was reduced from 2.0 +/- 1.2 to 1.1 +/- 1.1. A Cox proportional hazards model hinted forward superiority of the combined surgery cases (Trabectome + Phaco + intraocular lens) in comparison to Trabectome surgery only in phakic or pseudophakic eyes. No serious complications were observed. Minimal invasive glaucoma surgery with the Trabectome seems to be safe and effective. The subgroup analysis of different kinds of open angle glaucomas presented in this study may help in first-line patient selection. The lack of ocular surface alterations makes it a valuable addition to glaucoma surgery.

Barriers to glaucoma case finding as perceived by optometrists in Ireland - Barrett, C; O'Brien, C; Butler, JS; Loughman, J (CLINICAL AND EXPERIMENTAL OPTOMETRY, 2018)
BackgroundThis research was designed to provide an in-depth exploration of the perceptions of optometrists relating to the challenges of glaucoma case finding in the Irish health-care system. MethodsA survey was developed, piloted and distributed for anonymous completion by optometrists registered to practise in Ireland. The survey included 10 five-level Likert items exploring potential barriers to glaucoma detection and a free-text box for participants to comment more broadly. ResultsOne hundred and ninety-nine optometrists (27 per cent of registrants) responded to the survey. Among the barriers identified, there was notable agreement (71 per cent) with the need for extra training on glaucoma detection. Logistic regression showed that optometrists without postgraduate qualifications were more likely to agree with the need for extra training (OR 3.2, 95 per cent CI 1.3-8.1). Respondents largely agreed (61 per cent) that patient unwillingness to pay additional fees for supplementary glaucoma-specific tests was also a barrier. Appointment times of less than 30 minutes were significantly associated with six of the 10 proposed barriers to glaucoma detection. A logistic regression analysis (n = 179) confirmed that the time allotted per appointment was a significant predictor of the agreement time of optometrists as a barrier ((2) [1] = 13.52, p < 0.001). Multiple linear regression showed that optometrists with less experience, charging lower fees, and working in large multiples or franchised practices have the shortest appointment times. ConclusionThe strong link found between postgraduate education and the confidence of optometrists in detecting glaucoma indicates that optometrists wishing to increase their scope of practice in the new legislative environment in Ireland may more actively seek training in areas of interest. The responses also indicate a lack of funding for the level of diagnostic testing required for accurate glaucoma diagnosis. Recent increases in the state's eye examination fees look likely to address the identified time and financial barriers to glaucoma detection in Ireland. Future work should look to analyse the effects of increased funding on optometric case finding for glaucoma.

Exploring the influence of patient-provider communication on intraocular pressure in glaucoma patients - Carpenter, DM; Tudor, GE; Sayner, R; Muir, KW; Robin, AL; Blalock, SJ; Hartnett, ME; Giangiacomo, AL; Sleath, BL (PATIENT EDUCATION AND COUNSELING, 2015)
Objective: We examined whether six patient-provider communication behaviors directly affected the intraocular pressure (IOP) of glaucoma patients or whether patient medication adherence and eye drop technique mediated the relationship between self-efficacy, communication, and IOP. Methods: During an 8-month, longitudinal study of 279 glaucoma patients and 15 providers, two office visits were videotape-recorded, transcribed, and coded for six patient-provider communication behaviors. Medication adherence was measured electronically and IOP was extracted from medical records. We ran generalized estimating equations to examine the direct effects of communication on IOP and used bootstrapping to test whether medication adherence and eye drop technique mediated the effect of communication on IOP. Results: Provider education about medication adherence (B = -0.50, p < 0.05) and inclusion of patient input into the treatment plan (B = -0.35, p < 0.05) predicted improved IOP. There was no evidence of significant mediation. Conclusion: The positive effects of provider education and provider inclusion of patient input in the treatment plan were not mediated by adherence and eye drop technique. Practice Implications: Providers should educate glaucoma patients about the importance of medication adherence and include patient input into their treatment plan. (C) 2015 Elsevier Ireland Ltd. All rights reserved.

Functional health literacy in patients with glaucoma in urban settings - Juzych, MS; Randhawa, S; Shukairy, A; Kaushal, P; Gupta, A; Shalauta, N (ARCHIVES OF OPHTHALMOLOGY, 2008)
Objective: To assess the relationship between health literacy and compliance, disease awareness, and disease progression in patients with glaucoma. Methods: A cross-sectional observational study of 204 English-speaking patients treated for glaucoma for at least 1 year at Kresge Eye Institute was conducted. Health literacy was assessed using the standardized Test of Functional Health Literacy in Adults (TOFHLA). An oral questionnaire assessed patients' demographic information and glaucoma understanding. A retrospective medical record review was conducted to record parameters indicating glaucoma severity. Results: One hundred two participants (50%) were categorized as having poor functional health literacy ( mean [SD] TOFHLA score, 18.4 [7.5]) and 102 participants ( 50%) had adequate health literacy ( mean [ SD] TOFHLA score, 42.8 [5.1]). The poor health literacy group showed significant differences in income, education, medication compliance, glaucoma understanding, and missed appointments compared with the adequate health literacy group ( P <. 001). Patients with poor health literacy showed a greater visual field loss on initial presentation ( mean deviation [SD], -10.58 [9.3] dB) compared with the adequate health literacy group ( mean deviation [ SD], -7.79 [6.9] dB; P=.02) and significantly worse visual field parameters when comparing pattern SDs on the recent and the initial visual fields ( pattern SD change [ SD], 0.19 [2.5] dB in the poor health literacy group vs -0.7 [2.2] dB in the adequate health literacy group; P=.02). Conclusions: Patients with poor health literacy had poorer compliance, worse disease understanding, and greater disease progression compared with the adequate health literacy group, highlighting the need to promote health literacy in patients with glaucoma.

Considerations in developing model-based economic evaluations of glaucoma treatment - Althin, R; Grima, DT; Dhawan, R; Bernard, LM (JOURNAL OF GLAUCOMA, 2006)
Purpose: To facilitate future glaucoma model development and to provide guidance for decision-makers evaluating them, we provide an overview of an innovative glaucoma model and highlight important modeling considerations. Considerations: The considerations that were addressed include: disease outcome that is both relevant and meaningful to current clinical practice; diversity in treatment options and practices; incorporation of therapy discontinuation; and consideration of the variability in patient response to treatment. Model Scope: A state-transition, Monte Carlo simulation model was developed to simulate the management and treatment of patients with glaucoma and/or ocular hypertension. The model examines strategies involving sequential use of up to 6 pharmacologic interventions. Transitions are based on the monthly probability that a patient is no longer "successfully maintained" on therapy, which can be a consequence of lack of intraocular pressure control, adverse events, lack of compliance, or lack of persistence. Outputs of the model include months on each treatment, frequency of therapy switches, days of intraocular pressure control, frequency of ophthalmologist visits, frequency of surgery, and glaucoma-related costs. The model allows the user to specify country-specific treatment strategies, survival on therapy, surgical rates, practice patterns, and costs. Concept Application: The model presented offers insights into accommodating patient and clinician variability through the use of persistence distributions. It will facilitate future glaucoma model development and provide insight for decision-makers who must evaluate model-based analyses of the economic value of glaucoma interventions.

Non-compliance with lens care and maintenance in diabetic contact lens wearers - O'Donnell, C; Efron, N (OPHTHALMIC AND PHYSIOLOGICAL OPTICS, 2004)
We hypothesize that diabetic contact lens wearers may represent a special group displaying higher levels of compliance with their lens care regimens as a result of learned behaviour relating to maintenance of their diabetic condition. To test this hypothesis, a prospective, single Centre, controlled, masked study was performed whereby 29 diabetic contact lens patients and 29 nondiabetic control subjects were issued with disposable hydrogel contact lenses and a multipurpose lens care regimen. All participants were given identical instruction on lens care and maintenance. Compliance levels were assessed at a 12-month aftercare appointment by demonstration and questionnaire. Twenty-four different aspects of compliance were scored, 12 by observation and 12 by questionnaire report, of which only two showed a significant difference between the diabetic and control groups. Although the combined population of contact lens wearers was generally compliant, there were examples of non-compliance in both groups. Neither the duration of diabetes nor the degree of metabolic control appeared to have a significant effect on compliance. The results suggest that eye care practitioners cannot assume that diabetic patients will be more compliant with contact lens care and maintenance than non-diabetic patients.

Notable role of glaucoma club on patients' knowledge of glaucoma - Chen, XL; Chen, YH; Sun, XH (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2009)
P>Purpose: To assess how general glaucoma patients understand their disease compared with patients from the Shanghai Glaucoma Club and various influencing factors as well. Shanghai Glaucoma Club was further evaluated to determine its efficacy on its members' understanding and knowledge of glaucoma. Methods: A total of 301 glaucoma patients in Shanghai Glaucoma Club and 314 general glaucoma patients were investigated by a questionnaire, composed of three parts and consisting of 20 questions. The first part asked questions about 'level of cognition about glaucoma', the second part was about 'compliance of medication and follow-up', and the third part was about 'life style and habit'. Answers were graded on each question and scores were summed up separately for each part and as a total. Differences of scores and influencing effects were analysed using multivariate linear regression (stepwise) between the two groups. Results: The average total scores of the general glaucoma patients and the glaucoma club members were 19.6 +/- 5.4 and 23.8 +/- 4.0 (t = -11.14 P < 0.01), respectively. After multivariate linear regression adjustment for the effects of age, diagnosis and educational level glaucoma club members still had 3.73 points edge over the general patients.(t = 8.14, P < 0.01). The club was shown to be the strongest positive factor influencing patients' cognition. Patients in Shanghai Glaucoma Club understood the nature and course of glaucoma significantly better than the general glaucoma patients (t = 10.97, P < 0.01) and also lived healthier lives (t = 7.55, P < 0.01). The level of background education was found to be a positive influencing factor although age was negatively correlated with total score. Primary glaucoma patients demonstrated better cognition of their diseases compared with secondary glaucoma patients, and those patients unaware of their type of glaucoma produced lower scores. Conclusions: This study demonstrated significant differences regarding the basic understanding of glaucoma between two groups: general glaucoma patients and members of the Shanghai Glaucoma Club. Club members presented with better cognition of glaucoma and self-management compared with general glaucoma patients. Therefore, the Shanghai Glaucoma Club is an effective medium to improve patients' knowledge of disease and compliance for medication.

Safety and efficacy of microinvasive glaucoma surgery with cataract extraction in patients with normal-tension glaucoma - Chang, EK; Gupta, S; Chachanidze, M; Hall, N; Chang, TC; Sola-Del Valle, D (SCIENTIFIC REPORTS, 2021)
This study assesses the safety and efficacy of microinvasive glaucoma surgery (MIGS) with cataract extraction in patients with normal-tension glaucoma (NTG). In our sample of 45 NTG patients, mean intraocular pressure (IOP) decreased from 13.7 to 12.3 mmHg at 2.5 years, and mean medication burden decreased from 2.0 to 1.1 at 1.5 years. For success defined as IOP reduction >= 30% from baseline IOP with medication burden reduction from preoperative levels, success probability was 5.4% at 1.5 years. For success defined as medication burden reduction with an IOP reaching goal IOP as determined by the glaucoma specialist, success probabilities were 67.2% at 1.5 years and 29.4% at 2.5 years. At the last follow-up visit, eyes with two MIGS procedures with different mechanisms of action achieved successful medication reduction 68.8% of the time versus 35.7% achieved by a single MIGS procedure (p=0.052). At their last visit, visual acuity was unchanged or improved in all eyes (100%). MIGS with cataract surgery results in modest reductions in IOP and medication burden in NTG patients, which may lead to lower costs and better therapeutic compliance. A combination of two MIGS procedures with different mechanisms of action may potentially be more effective in reducing medication burden than a single MIGS procedure in NTG patients. Further research is necessary to ascertain whether MIGS for NTG patients may help decrease medication burden while helping achieve goal IOP.

The physician-patient relationship in glaucoma - Hamelin, N (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2008)
Healthcare of chronic pathologies, especially in glaucoma, which is asymptomatic for a long period of time, is based on a good, confident relationship between physicians and patients. This relationship has to be created, maintained, and reinforced throughout follow-up, The patient's information source is to a large extent the physician, who must provide all the necessary information concerning the disease, including the definition, prognosis, follow-Lip, and treatment. How the information is transmitted should be personally adapted to patients, taking into account their own and their family's psychological reactions. It is also important to keep in mind the factors influencing poor compliance when talking to our patients.

Glaucoma care and follow-up in sub-Saharan Africa: Is there a need for modification of counselling practices to improve awareness, knowledge and treatment acceptance profiles? A prospective cross-sectional study - Uche, NJ; Udeh, NN; Chuka-Okosa, CM; Kizor-Akaraiwe, NN; Uche, EO (INTERNATIONAL OPHTHALMOLOGY, 2020)
Background Blindness from glaucoma is prevalent in parts of Africa. Lack of awareness, late diagnosis, poor acceptance and compliance to treatment as well as unorthodox care practices are among many contributing factors. Strategies that improve glaucoma awareness and treatment acceptance are required to resolve this trend. Purpose To evaluate the influence of counselling on glaucoma awareness, willingness to accept glaucoma surgery and eye care practices among primary open-angle glaucoma patients on medical treatment. Methods A prospective cross-sectional interviewer-administered questionnaire-based study evaluating the demographics, glaucoma awareness, acceptance of operative care and use of traditional eye medications among patients with primary open-angle glaucoma on medical treatment followed up over a 12-month period. Results A total of 120 eligible participants were recruited. Glaucoma awareness and basic knowledge were 93.3 and 12%, respectively. Educational attainment and positive family history were associated with glaucoma awareness (p = 0.027 and p = 0.042, respectively). Seventy-five (62.5%) participants accepted glaucoma surgery as a treatment option. However, the duration of medical treatment was inversely related to the acceptance of glaucoma surgery (odds ratio = - 0.390, p = 0.009). Twelve (10.5%) participants use traditional eye medication for their current eye problem. Conclusion Glaucoma counselling should be performed with a content template that delivers all relevant information to patients and caregivers. This will bridge gaps in knowledge and improve the early presentation, acceptance of glaucoma surgery and eye care practices.

A Randomized Controlled Trial to Determine the Effect of Inhaled Corticosteroid on Intraocular Pressure in Open-Angle Glaucoma and Ocular Hypertension: The ICOUGH Study - Moss, EB; Buys, YM; Low, SA; Yuen, D; Jin, YP; Chapman, KR; Trope, GE (JOURNAL OF GLAUCOMA, 2017)
Purpose: The purpose of this study was to determine the risk of a steroid pressure response from inhaled corticosteroids. Patients and Methods: This randomized, double-masked, placebo-controlled trial included 22 adults with well-controlled open-angle glaucoma or ocular hypertension. Consenting participants were randomized to a 6-week course of twice-daily fluticasone propionate 250-mu g metered-dose inhaler or saline placebo metered-dose inhaler. Biweekly clinic visits included masked Goldmann applanation tonometry and assessment to identify adverse effects. Primary outcome was mean intraocular pressure (IOP) at week 6. Secondary outcomes included IOP elevation of >20% at 2 consecutive visits, adherence, side effects, and logMAR visual acuity. Results: A total of 10 patients in each arm completed the study. There were no statistically significant differences in IOP between groups at baseline (14.3 +/- 3.0 and 15.6 +/- 3.6mm Hg in steroid and placebo groups, respectively, P=0.39) or at week 6 (14.7 +/- 2.4 and 14.8 +/- 3.8mm Hg in steroid and placebo groups, respectively, P=0.92). Adherence was >80% for all participants. There were no statistically significant differences between groups in any secondary measures. One patient in the steroid group met the secondary end point of >20% elevation in IOP (IOP increased from baseline of 9 to 11mm Hg at weeks 2 and 4). Conclusions: We found no clinically significant increase in mean IOP in patients with well-controlled open-angle glaucoma and ocular hypertension after 6 weeks of twice-daily inhaled fluticasone propionate compared with inhaled placebo. No participants exceeded their individualized target IOP. There were no differences in secondary outcomes.

Patients' and physicians' perceptions of the travoprost dosing aid: An open-label, multicenter study of adherence with prostaglandin analogue therapy for open-angle glaucoma or ocular hypertension - Flowers, B; Wand, M; Piltz-Seymour, J; Berke, SJ; Day, D; Teague, J; Smoot, TM; Landry, TA; Bergamini, MVW; Mallick, S; Travatan Dosing Study Grp (CLINICAL THERAPEUTICS, 2006)
Objective: This Study describes patients' and physicians' Perceptions of issues related to dosing adherence with topical therapies for lowering Intraocular pressure before and after use of the travoprost dosing aid (Travatan (TM) Dosing Aid, Alcon Research Ltd., Fort Worth, Texas). Methods: The Study had an open-label, multicenter, single-treatment-arm design that included sequential patients with open-angle glaucoma (with or without pigment dispersion or pseudoexfoliation component) or ocular hypertension who were taking any prostaglandin analogue monotherapy. Ten participating physicians were chosen on the basis of factors Such as their experience, qualifications, and previous clinical study participation. The study consisted of 2 visits: screening and week 4. Patients were asked to complete a survey about their medication adherence before study entry at the screening visit and at study exit during the week-4 visit. In addition, each Physician was asked to complete an entry and exit survey on each patient as well as a survey to provide feedback on the travoprost dosing aid. Results: Of the 87 enrolled patients, 6 did not complete the exit survey; therefore, 81 patients were included in the intent-to-treat analysis. Mean (SD) age at enrollment was 65.4 (11.6) years; 61.7% (50/81) of the patients were women and 60.5% (49/81) were white. Most patients (96.3% [78/81]) had open-angle glaucoma. Participating physicians perceived that problems involving dosing and adherence were reduced after patients used the dosing aid. Physicians indicated that they would recommend Continued use of the travoprost dosing aid for 91.3% (73/80) of patients. All 10 participating physicians said that they Would recommend the dosing aid to patients in the future. Of the 81 patients, the majority (68.8% vertical bar 55/80 vertical bar) indicated that they would like to continue using the travoprost dosing aid. For 67.5'% (54/80) of patients, dosing adherence as recorded by the travoprost dosing aid was > 70%. The dosing lever (39.7%, vertical bar 31/78 vertical bar) and the visual alarm (29.5% vertical bar 23/78 vertical bar) were the 2 most favored features of the dosing aid reported by all evaluable patients. The majority of patients (58.8% vertical bar 47/80 vertical bar) indicated that they were "relieved" or "very relieved" that the doctor was able to monitor when they dosed their medication; few (7.5% [6/80]) were "concerned" or "very concerned" that the doctor was able to monitor their dosing. Conclusions: The travoprost dosing aid was perceived to be effective in reminding this group of patients to take their medication as prescribed. In this Study, the device was well accepted by both patients and physicians. (Clin Ther. 2006;28:1803-1811) Copyright (c) 2006 Excerpta Medica, Inc.

First-year treatment patterns among new initiators of topical prostaglandin analogs - Schmier, JK; Covert, DW; Robin, AL (CURRENT MEDICAL RESEARCH AND OPINION, 2009)
Objective: To evaluate treatment patterns and costs among new initiators of topical prostaglandin analogs in a managed-care population. Research design and methods: Annual costs were modeled using multiple inputs. A retrospective cohort design was used to identify treatment patterns for pharmacotherapy. The study population was identified from pharmacy claims for patients who met study inclusion criteria (patients initiating prostaglandin analog monotherapy). Published studies were used to estimate visit-related resource use and costs were obtained from published and standard sources. Results: In the cohort analysis, a total of 12202 patients met study criteria: 2275 received bimatoprost, 7347 received latanoprost and 2580 received travoprost (1808 used the original formulation and 772 used the newer preservative formulation). Of patients meeting study criteria, 50% stopped all glaucoma therapy, 6% switched from their initial prostaglandin therapy, and the remaining 44% stayed on their initial prostaglandin for 1 year. Of patients remaining on prostaglandin analog monotherapy for 1 year, 22.7% of bimatoprost patients, 19.8% of latanoprost patients and 17.9% of travoprost patients (19.7% for the original formulation and 13.7% for the new formulation) required adjunctive therapy. Of those requiring adjunctive therapy, the median number of days until starting adjunctive therapy was 53 days for bimatoprost patients, 63 days for latanoprost patients and 83 days for travoprost patients (70.5 days for the original formulation and 109 days for the new formulation). The resources used at each visit were estimated at $424 for an initial visit and $70 for follow-up visits. Estimated first-year costs were $1294, $1199, and $1186 for patients initiating therapy with bimatoprost, latanoprost, and travoprost, respectively. Estimated travoprost costs were higher for the original formulation ($1203) than for the new formulation ($1160). Sensitivity analyses suggested that the cost estimates are robust to changes in costs and use of adjunctive therapies. Limitations: The use of a claims database without compliance data or clinical outcomes and the selection of new initiators of topical prostaglandin analogs limits the findings and does not allow projecting outcomes to all glaucoma patients. Conclusions: Use of adjunctive therapy in glaucoma is an important driver of glaucoma management costs. Based on the results of this study, it is possible that longer duration of monotherapy with prostaglandin analogs may be associated with lower annual costs. Further study should be conducted to validate these findings.

Diagnostic accuracy of the iCare rebound tonometer compared to the Perkins applanation tonometer in assessing intraocular pressure in rural patients - Li, YF; Carpenter, CR; Nicholson, K; Milne, WK (DIAGNOSIS, 2015)
Background: Vision health is recognized as a critical unmet need in North America. The ocular morbidity associated with glaucoma results from increased intraocular pressure (IOP) and early detection is crucial for the management of glaucoma. Our objective was to find a diagnostically accurate screening tool for intraocular hypertension that can be used in rural communities. We sought to validate the diagnostic accuracy of the iCare rebound tonometer against the gold standard Perkins applanation tonometer (PAT) in measuring IOP. Methods: Patients from two rural communities in Ontario, Canada visiting their optometrists for routine appointments had their IOP measured by a non-contact tonometer (NCT), an iCare rebound tonometer, and a Perkins applanation tonometer (PAT). Values of sensitivity, specificity, and likelihood ratios for a positive and negative result were calculated for the iCare and the NCT. Results: Complete data was collected from 209 patients. Overall, the iCare tonometer had high levels of validity, as compared to the gold standard PAT. The iCare tonometer displayed excellent sensitivity of 98.3% (90-99%, 95% CI) and excellent negative likelihood ratio of 0.024 (0.0088-0.066, 95% CI) which is useful for ruling out intraocular hypertension. Conclusions: The iCare tonometer is a reasonably valid tool for detecting elevated IOP. Its ease of use, simplicity, and accessibility makes it a good screening tool to improve eye health in rural areas.

Boston Keratoprosthesis Outcomes and Complications - Chew, HF; Ayres, BD; Hammersmith, KM; Rapuano, CJ; Laibson, PR; Myers, JS; Jin, YP; Cohen, EJ (CORNEA, 2009)
Purpose: To evaluate the outcomes of the Boston Keratoprosthesis (KPro) at our institution. Methods: A computerized database retrospectively identified all patients who received a Boston KPro from August 2005 to October 2007. Results: There were 37 patients, 24 (65%) were male. Mean age was 66.3 years (median 69 years, range: 24-93 years; SD = 18.1 years). Mean follow-up was 16 months (range: 6-28 months; SD = 6.0 months). There were 36 type 1 (97%) and I type 2 (3%) KPros. The primary indication was failed penetrating keratoplasty in 29 patients (78%)-22 (59%) from multiple failures, Preoperative comorbidities included glaucoma [27 patients (73%)] and limbal stern cell deficiency [13 patients (35%)]. No intraoperative complications occurred. Postoperative complications included retroprosthetic membrane [24 patients (65%)], increased intraocular pressure [14 patients (38%)], glaucoma progression [5 patients (13.5%)], and endophthalmitis [4 patients (11%)-3 who discontinued prophylactic antibiotics secondary to compliance]. Thirty-six KPros (97%) were retained-1 type 2 KPro (3%) in a patient with ocular cicatricial pemphigoid extruded and was replaced. Mean best-corrected visual acuities were counting fingers preoperatively (range: light perception to 20/100) and 20/90 at last follow-up (range: light perception to 20/25). At last follow-up, 31 patients (84%) improved 2 lines or greater-3 patients (8%) had worse vision. Conclusions: Retention rates were excellent, and best-corrected Visual acuities improved in the vast majority of patients. Complications can occur and require frequent follow-up to monitor and treat glaucoma progression, endophthalmitis, and inflammation. Patient compliance is of paramount importance. Despite the potential complications, the Boston KPro provides visual improvement in patients with an otherwise poor prognosis.

Improving patient education and attitudes toward compliance with instructions for contact lens use - McMonnies, CW (CONTACT LENS & ANTERIOR EYE, 2011)
Aims: To examine reasons for non-compliance with recommended methods of successful contact lens wear and care, and to use that analysis to improve instruction as well as to apply the principles of social influence and other methods of behaviour modification to improve patient understanding of and attitudes toward compliance. Methods: A review of studies of non-compliance and an analysis of educational methods, content and sequencing. Results: The high prevalence of intentional and unintentional non-compliance confirms the need for improved methods of education and attitudes toward compliance. Education may be unsuccessful because of auditory processing disorders and reading disability syndromes. Methods which appear likely to contribute to improved compliance include: keeping records of the progress made through a comprehensive syllabus, commencing education at the prescribing visit, postponing non-urgent components to aftercare visits, compensating for patient shortcomings in the areas of understanding verbal instructions and reading support literature, and improving frequency and impact of communications with patients. Conclusions: In addition to improved instruction, there is an indication for using behaviour modification techniques, such as the principles of social influence, to achieve changes in patient attitudes toward compliance. For example, patient attitudes toward compliance may be improved by understanding why so many people continue to wear and benefit from the many advantages of contact lens corrections, as well as appreciating how too many patients become contact lens failures due to non-compliance. There is a strong indication for progressive monitoring of compliance but the methods used should avoid confrontation with and any offence to patients. (C) 2011 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.

The interrelation between hypothyroidism and glaucoma: a critical review and meta-analyses - Thvilum, M; Brandt, F; Brix, TH; Hegedus, L (ACTA OPHTHALMOLOGICA, 2017)
Data on the association between hypothyroidism and glaucoma are conflicting. We sought to shed light on this by conducting a critical review and meta-analyses. The meta-analyses were conducted in adherence with the widely accepted MOOSE guidelines. Using the Medical Subject Heading (MeSH) terms: hypothyroidism, myxoedema and glaucoma or intraocular pressure, case-control studies, cohort studies and cross-sectional studies were identified (PubMed) and reviewed. Using meta-analysis, the relative risk (RR) of coexistence of glaucoma and hypothyroidism was calculated. Based on the literature search, thirteen studies fulfilled the inclusion criteria and could be categorized into two groups based on the exposure. The designs of the studies varied considerably, and there was heterogeneity related to lack of power, weak phenotype classifications and length of follow-up. Eight studies had glaucoma (5757 patients) as exposure and hypothyroidism as outcome. Among these, we found a non-significantly increased risk of hypothyroidism associated with glaucoma (RR 1.65; 95% confidence interval [CI]: 0.97-2.82). Based on five studies (168006 patients) with hypothyroidism as exposure and glaucoma as outcome, we found the risk of glaucoma to be significantly increased (RR 1.33; 95% CI: 1.13-1.58). Based on these meta-analyses, there seems to be an association between hypothyroidism and glaucoma, which does not seem to be the case between glaucoma and hypothyroidism. However, larger scale studies with better phenotype classification, longer follow-up and taking comorbidity and other biases into consideration are needed to address a potential causal relationship.

Using soft computing to define standards of care in glaucoma monitoring - Ulieru, M; Crichton, ACS; Rizzi, M; Karanicolas, C (SOFT COMPUTING, 2004)
A fuzzy knowledge base encapsulating core expert rules for glaucoma follow up is developed and subsequently refined into a standard of care by reconciling several expert opinions. The Learning from Examples (LFE) [1] technique is used in addition to expert interviews to generate fuzzy rules from numerical data, and soft competition defines a fuzzy consensus metrics for the expert opinions. Web-based extension of this system into a comprehensive set of e-Health services for the glaucoma community enables, besides wide accessibility of the expert knowledge, continuous improvement of the core rule set (standard of care) with the perspectives of several experts.

Long-term follow-up after transscleral diode laser photocoagulation in refractory glaucoma - Pucci, V; Tappainer, F; Borin, S; Bellucci, R (OPHTHALMOLOGICA, 2003)
Background and Objective: Patients affected by glaucoma refractory to medical or surgical treatment are difficult to treat. The aim of this study was to evaluate the long-term effect of contact transscleral diode laser cyclo-photocoagulation (DLPC) on intraocular pressure (IOP) and on visual acuity of these patients. Patients and Methods: One hundred and twenty eyes of 107 patients suffering from refractory glaucoma and treated with DLPC were followed at the Eye Clinic of Verona University for an average of 26 8 months. Mean age was 57 26 years. IOP, visual acuity, and ocular complications were analyzed. Results: A total of 207 treatments were given. More than one treatment was given in 55 eyes (45.8%). Mean pretreatment IOP was 30.4 +/- 3.1 mm Hg. At the last follow-up, mean IOP was 20.3 +/- 1.8 mm Hg. Mean total medications were reduced from 4.5 +/- 0.5 to 2.3 +/- 0.3. No serious complications occurred in the 207 treatments. Visual acuity remained stable in 66 eyes (55%), improved in 25 eyes (20.8%), and decreased in 29 eyes (24.2%). Conclusions: DLPC was effective in lowering IOP in eyes with refractory glaucoma. It also served to reduce the number of antiglaucoma medications, thus improving both the quality of life of the patients and their compliance to therapy. This procedure is relatively safe, very fast and easy to learn. However, careful attention is required to determine the exact position of the ciliary body in malformative glaucoma. Multiple treatments may be required to control IOP. Copyright (C) 2003 S. Karger AG, Basel.

Influence of Cost of Care and Adherence in Glaucoma Management: An Update - Meier-Gibbons, F; Toteberg-Harms, M (JOURNAL OF OPHTHALMOLOGY, 2020)
The costs for glaucoma care are rising worldwide. The main reason is the increase of life expectancy and the increasing variety of diagnostic tests and therapeutically options by implants and devices. How can we influence the increase in costs? Does a relationship exist between the rising costs and the behavior of patients especially in regard to adherence of patients to the prescribed therapy? Are there ways to improve adherence? The costs of a disease can be estimated by adding the direct costs and the indirect costs deriving from the disease. Many studies have been looking at the direct costs, for example, the costs of diagnostic tests and treatment modalities. Unfortunately, not many studies investigated the indirect costs, i.e., costs related to the need of a person to accompany the patient during his or her outpatient visits or the costs deriving from loss of work capacity because of the disease itself or the outpatient visits. Adherence or the synonym compliance has been discussed since many years, and it seems that it remains a major problem in the management of many chronic diseases. Despite all efforts to improve adherence, the adherence rate in chronic diseases such as glaucoma or arterial hypertension remains considerably low. One of the main factors in improving adherence is raising patient's awareness of the disease by providing general understanding of their disease. Other important factors are simplified therapeutic regimens, e.g., fixed combination drops, sustained drug release techniques, or new glaucoma surgical procedures with a more favorable risk profile.

Corneal Pseudodendritic Lesions Masquerading as Herpetic Keratitis in a Patient With Tyrosinemia Type I - Sevim, DG; Gumus, K; Cavanagh, HD (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2017)
Objective: To describe the clinical findings of a patient with tyrosinemia type I with noncompliance to a protein-restricted diet, treated with 2-(2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione (NTBC). Methods: Clinical findings at the initial examination and after strict compliance to a protein-restricted diet after 4 weeks follow-up are described in a patient with tyrosinemia type I on NTBC treatment, who had been treated with presumed herpetic keratitis. Results: A 10-year-old girl diagnosed with hereditary tyrosinemia type I and on NTBC treatment presented with photophobia and ocular discomfort in both eyes. An ophthalmologic examination demonstrated bilateral dendritiform epithelial lesions in the central cornea, staining faintly with fluorescein. These lesions were subsequently intermittently treated with topical antivirals for presumed herpes simplex virus keratitis and lubricant eye drops for 9 months without resolution; however, when strict compliance with a protein-restricted diet was instituted, nearly a complete resolution of the lesions was noted at the 4-week follow-up. Conclusions: Although type II tyrosinemia is known to have corneal involvement, the natural course of tyrosinemia type I has not been shown to have corneal involvement. Corneal involvement in type I tyrosinemia may be an indicator of dietary noncompliance and may show complete resolution with a strict compliance to protein-restricted diet only.

PSEUDOPHAKIC PUPILLARY-BLOCK GLAUCOMA IN CHILDREN - VAJPAYEE, RB; ANGRA, SK; TITIYAL, JS; SHARMA, YR; CHABBRA, VK (AMERICAN JOURNAL OF OPHTHALMOLOGY, 1991)
We studied 16 children, ranging in age between 3 and 8 years, who had posterior chamber intraocular lens implantation and developed inflammatory pupillary-block glaucoma. Prophylactic peripheral iridectomy had not been performed in any of the eyes. The patients were treated medically, and YAG laser iridotomy was performed successfully one week after initial control of intraocular pressure. Of 16 eyes in which intraocular pressure remained uncontrolled, trabeculectomy was necessary in three eyes and irreversible glaucomatous visual loss occurred in two eyes. Our data demonstrate the need for stringent and more frequent postoperative follow-up of children after intraocular lens implantation, especially during the first four postoperative weeks. Careful long-term follow-up for treatment after cataract is mandatory to prevent development of amblyopia.

Costs and persistence of carbonic anhydrase inhibitor versus alpha-2 agonists, associated with beta-blockers, in glaucoma and ocular hypertension: an analysis of the UK-GPRD database - Lafuma, A; Berdeaux, G (CURRENT MEDICAL RESEARCH AND OPINION, 2008)
Objective: To compare the effectiveness and associated costs of carbonic anhydrase inhibitors + beta-blocker versus alpha-2 adrenergic agonists + beta-blocker in glaucoma therapy, as documented by The United Kingdom General Practitioner Research Database (UK-GPRD). Research Design: Patient chart analysis. Methods: Patient records were screened for diagnoses of ocular hypertension or glaucoma, and for surgery, laser therapy or medication specific to glaucoma. Selected patients were those prescribed either carbonic anhydrase inhibitors + beta-blocker or alpha-2 adrenergic agonists + beta-blocker. Treatment failure was defined as a glaucoma prescription change, i.e. addition, cessation or replacement of medication, surgery or laser therapy. Times to treatment failure were compared with an adjusted Cox model. Main outcome measures: Treatment persistence and cost. Results: Included patients were those treated with either carbonic anhydrase inhibitors + beta-blocker (n = 5581) or alpha-2 adrenergic agonists + beta-blocker (n = 1164). The average age at diagnosis was 68.1 years and 48.2% were male. Treatment failure at one year was significantly (p < 0.001) less frequent after carbonic anhydrase inhibitors + beta-blocker (57% of patients) than after alpha-2 adrenergic agonists + beta-blocker (64.3%). The hazard ratio for failure was lower (0.82: p < 0.0001) with carbonic anhydrase inhibitors + beta-blocker following adjustment for age, gender, comorbidities and duration of follow-up. Adjusted annual costs of glaucoma management were 348.04 pound for carbonic anhydrase inhibitors + beta-blocker and 356.80 pound for alpha-2 adrenergic agonists + beta-blocker. Conclusions: According to UK-GPRD information, glaucoma therapy with carbonic anhydrase inhibitors + beta-blocker is more persistent than with alpha-2 adrenergic agonists + beta-blocker at a similar cost.

Prospective evaluation of penetrating deep sclerectomy in advanced open-angle glaucoma: Filtration surgery adapted to resource scarcity in developing countries - Kalala, A; Gillmann, K; Mermoud, A (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2020)
Purpose. Two of the hurdles that are facing ophthalmologists in developing countries are scarcity of resources and patient follow-up. Deep sclerectomy (DS) has proven less costly and more effective than topical therapies and has a more favorable safety profile than trabeculectomy. The main factors preventing its use in developing countries are the need to perform laser goniopuncture in 40-80% of cases to maintain filtration and the risk of postoperative iris incarceration. The purpose of this study is to assess the efficacy and safety profile in advanced open -angle glaucoma of a relatively new surgical technique designed to overcome this limitation: penetrating DS. Setting. This was an investigator -initiated, prospective, interventional study, conducted at a single ophthalmology center in Kinshasa, Congo. The study was conducted in full compliance with the Declaration of Helsinki. Methods. Fifty-one eyes (34 patients) with uncontrolled advanced primary open -angle glaucoma (visual field mean deviation < 10 dBs) were enrolled between October 2012 and June 2016. Age, gender, comorbidities (hypertension/diabetes), best -corrected visual acuity, topical medications, medicated and unmedicated intraocular pressure (10P) were recorded. All patients underwent penetrating DS, during which, following standard dissection of the scleral flaps, the anterior chamber was penetrated through the trabeculo-Descemet membrane and an iridectomy was performed. Patients attended postoperative appointments at months 1, 3, 6 and 12. Surgical success was defined as a 20% reduction of 10P from baseline in conjunction with a 12 -month unmedicated 10P < 12 mm Hg. Results. The mean age was 64.5 + 14.0 years (44.1% female, 100% African). Mean 10P decreased from 20.2 6.1 (medicated) and 30.7+9.8 mm Hg (unmedicated) preoperatively to 12.1+4.1 at 12 months. Concomitantly, the number of topical medications decreased from 1.5 0.7 to 0.0. Complete surgical success was achieved in 64.7%. Four eyes (7.8%) were considered surgical failures due to uncontrolled 10P. None of the eyes lost light perception or required additional surgery. A significant association between surgical failure and hypertension was observed (HR = 1.49; P=0.008). There were no intraoperative complications. Postoperatively, 4 bleb encapsulations (7.8%) and 1 iris incarceration (2%) were observed. Conclusions. The present study demonstrates that penetrating DS achieved similar efficacy and safety results to traditional non -penetrating DS. In addition, it showed a lower potential for intraoperative complications, which might be associated with a more benign surgical learning curve. Finally, the rates of serious postoperative complications (iris incarceration, choroidal effusion and hypotony) were significantly lower than in DS and trabeculectomy, and this technique does not require subsequent Nd: YAG laser goniopuncture to maintain filtration, making frequent follow-up visits less critical. In view of these findings, perforating deep sclerectomy could offer a viable option for glaucoma management in developing countries as well as worldwide. (C) 2020 Elsevier Masson SAS. All rights reserved.

Eye Care Quality and Accessibility Improvement in the Community (EQUALITY): impact of an eye health education program on patient knowledge about glaucoma and attitudes about eye care - Rhodes, LA; Huisingh, CE; McGwin, G; Mennemeyer, ST; Bregantini, M; Patel, N; Saaddine, J; Crews, JE; Girkin, CA; Owsley, C (PATIENT-RELATED OUTCOME MEASURES, 2016)
Purpose: To assess the impact of the education program of the Eye Care Quality and Accessibility Improvement in the Community (EQUALITY) telemedicine program on at-risk patients' knowledge about glaucoma and attitudes about eye care as well as to assess patient satisfaction with EQUALITY. Patients and methods: New or existing patients presenting for a comprehensive eye exam (CEE) at one of two retail-based primary eye clinics were enrolled based on >= 1 of the following at-risk criteria for glaucoma: African Americans >= 40 years of age, Whites >= 50 years of age, diabetes, family history of glaucoma, and/or preexisting diagnosis of glaucoma. A total of 651 patients were enrolled. A questionnaire was administered prior to the patients' CEE and prior to the patients receiving any of the evidence-based eye health education program; a follow-up questionnaire was administered 2-4 weeks later by phone. Baseline and follow-up patient responses regarding knowledge about glaucoma and attitudes about eye care were compared using McNemar's test. Logistic regression models were used to assess the association of patient-level characteristics with improvement in knowledge and attitudes. Overall patient satisfaction was summarized. Results: At follow-up, all patient responses in the knowledge and attitude domains significantly improved from baseline (P<0.01 for all questions). Those who were unemployed (odds ratio =0.63, 95% confidence interval =0.42-0.95, P=0.026) or had lower education (odds ratio =0.55, 95% confidence interval =0.29-1.02, P=0.058) were less likely to improve their knowledge after adjusting for age, sex, race, and prior glaucoma diagnosis. This association was attenuated after further adjustment for other patient-level characteristics. Ninety-eight percent (n=501) of patients reported being likely to have a CEE within the next 2 years, whereas 63% (n=326) had a CEE in the previous 2 years. Patient satisfaction with EQUALITY was high (99%). Conclusion: Improved knowledge about glaucoma and a high intent to pursue eye care may lead to improved detection of early disease, thus lowering the risk of blindness.

Re-irradiation of adenoid cystic carcinoma: Analysis and evaluation of outcome in 52 consecutive patients treated with raster-scanned carbon ion therapy - Jensen, AD; Poulakis, M; Nikoghosyan, AV; Chaudhri, N; Uhl, M; Munter, MW; Herfarth, KK; Debus, J (RADIOTHERAPY AND ONCOLOGY, 2015)
Background: Treatment of local relapse in adenoid cystic carcinoma (ACC) following prior radiation remains a challenge: without the possibility of surgical salvage patients face the choice between palliative chemotherapy and re-irradiation. Chemotherapy yields response rates around 30% and application of tumouricidal doses is difficult due to proximity of critical structures. Carbon ion therapy (C12) is a promising method to minimize side-effects and maximize re-treatment dose in this indication. We describe our initial results for re-irradiation in heavily pre-treated ACC patients. Methods: Patients treated with carbon ion therapy between 04/2010 and 05/2013 (N= 52 pts, median age: 54 a) were retrospectively evaluated regarding toxicity (NCI CTC v.4), tumour response (RECIST) and control rates. 48 pts (92.3%) received carbon ions only, 4 pts received IMRT plus C12. Results: 4 pts were treated following R1-resection, 43 pts for inoperable local relapse. Most common tumour sites were paranasal sinus (36.5%), parotid (19.2%), and base of skull (17.3%). Pts received a median dose of 51 GyE C12/63 Gy BED and cumulative dose of 128 Gy BED [67-182 Gy] after a median RT-interval of 61 months. Median target volume was 93 ml [9-618 ml]. No higher-grade (>degrees II) acute reactions were observed, 7 pts showed blood-brain-barrier changes (degrees I/II: 8 pts; degrees III: 2 pts), 1 pt corneal ulceration, xerophthalmia 7 pts, degrees IV bleeding 1 pt, tissue necrosis 2 pts, otherwise no significant late reactions. Objective response rate (CR/PR) was 56.6%. With a median follow-up of 14 months [1-39 months] local control and distant control at la are 70.3% and 72.6% respectively. Of the 18 pts with local relapse, 13 pts have recurred in-field, 1 pt at the field edge, 3 pts out of field, and one in the dose gradient. Conclusion: Despite high applied doses, C12 re-irradiation shows moderate side-effects, response rates even in these heavily pre-treated patients are encouraging and present a good alternative to palliative chemotherapy. Though most local recurrences occur within the high-dose area, further dose escalation should be viewed with caution. (C) 2015 The Authors. Published by Elsevier Ireland Ltd.

Comparison of Prostaglandin Analog Treatment Patterns in Glaucoma and Ocular Hypertension - Heo, JH; Rascati, KL; Wilson, JP; Lawson, KA; Richards, KM; Nair, R (JOURNAL OF MANAGED CARE & SPECIALTY PHARMACY, 2019)
BACKGROUND: Prostaglandin analogs (PGAs) are considered an initial therapy to manage increased intraocular pressure (10P) for patients with glaucoma. When the initial PGA treatment fails to lower 10P adequately, the patient may add or change medications or have surgery/laser treatment. OBJECTIVE: To compare medication adherence, duration of therapy, and treatment patterns among 3 PGAs-latanoprost, travoprost, and bimatoprost-as initial therapies for patients with glaucoma or ocular hypertension. METHODS: This was a retrospective cohort study using administrative claims data. The cohort consisted of patients newly diagnosed with glaucoma or ocular hypertension with at least 1 prescription claim for latanoprost, travoprost, or bimatoprost and enrolled in a Medicare Advantage plan between 2007 and 2012. The 24-month medication possession ratio (MPR) was used to measure medication adherence. Discontinuation of first line PGA therapy was defined as nonpersistence (90-day gap allowance) of the index PGA or a change in therapy during the 24-month follow-up period. Types of second-line therapy (i.e., switch, addition, and surgery) were identified. The 1:1:1 propensity score matching was used. RESULTS: Patients who met the inclusion criteria were propensity score matched, resulting in 1,296 patients per PGA group. Latanoprost users showed higher adherence (50.1%) than travoprost (48.8%) and bimatoprost (43.0%) users. The latanoprost and travoprost groups had significantly higher MPRs than bimatoprost (P< 0.0001). The latanoprost group showed significantly longer duration of first-line therapy (372 days) than the bimatoprost group (343 days; P= 0.003) but not the travoprost group (361 days). After controlling for demographic and clinical characteristics, a Cox proportional hazards model showed that the travoprost and bimatoprost groups had a higher risk of discontinuation of first-line therapy than the latanoprost group (P< 0.0001). The percentage of patients continuing on the index PGA without treatment pattern change (i.e., switches, additions, and surgery) was higher for latanoprost users (52.9%) compared with travoprost (39.0%) or bimatoprost users (42.1%; P< 0.001). CONCLUSIONS: Patients who used latanoprost as their initial therapy were more likely to adhere and persist to the index PGA compared with bimatoprost users. The latanoprost group demonstrated a lower risk of discontinuing first-line therapy than the travoprost and bimatoprost groups. The results may assist ophthalmologists in determining the optimal management of this patient population with respect to treatment patterns. Copyright (C) 2019, Academy of Managed Care Pharmacy. All rights reserved.

Trends in and Predictors of Depression Among Participants in the Collaborative Initial Glaucoma Treatment Study (CIGTS) - Musch, DC; Niziol, LM; Janz, NK; Gillespie, BW (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2019)
PURPOSE: To characterize longitudinal trends and factors predictive of depressive symptoms following glaucoma diagnosis in Collaborative Initial Glaucoma Treatment Study (CIGTS) participants. DESIGN: Cohort study using follow-up data from a clinical trial. METHODS: A total of 607 participants with newly diagnosed open-angle glaucoma were enrolled at 14 clinical centers in the United States from October 1993 through April 1997, randomized to treatment with medication or surgery, and followed every 6 months through 2004. The 8-item Center for Epidemiologic Studies Depression Scale (CESD) was administered at baseline and follow-up visits. Three outcome measures were investigated: overall CES-D depression score, presence of mild or worse depression (CES-D score Z 7), and number of depressive symptoms endorsed. RESULTS: The average baseline CES-D score was 2.4 (SD = 3.8), 12.5% of subjects reported symptoms associated with mild or worse depression, and 55.3% reported at least 1 depressive symptom. By 1 year posttreatment, depression measures decreased (1.5, 6.7%, and 38.4%, respectively), with modest decreases thereafter. Baseline factors predictive of mild or worse depression included worse vision-related quality of life (VRQOL) (odds ratio [OR] = 2.41), female sex (OR = 1.42), younger age (OR per 10 years younger = 1.24), and less than high school education (OR = 2.93); other outcomes showed similar results. CONCLUSIONS: Depressive symptoms decreased considerably during the first year after treatment initiation, but were elevated in those with impaired VRQOL. Given the potential of depression to reduce treatment adherence and thus increase the risk of glaucoma progression, eye care providers should ask patients about depressive symptoms, provide reassurance when appropriate, and make referrals as necessary. (C) 2018 Elsevier Inc. All rights reserved.

Glaucoma screening: current trends, economic issues, technology, and challenges - Nduaguba, C; Lee, RK (CURRENT OPINION IN OPHTHALMOLOGY, 2006)
Purpose of review Glaucoma is one of the leading causes of irreversible blindness worldwide. Early glaucoma detection and treatment are currently the only known methods for preventing blindness and low vision resulting from this frequently asymptomatic disease. Recent findings New technologies for detecting early glaucomatous damage are important in diagnosing optic nerve disease, not only in community screening settings but also in clinics. Imaging of the optic nerve head and macula and retinal nerve fiber layer analysis can provide quick, automated, and quantitative measurements in agreement with clinical estimates of optic disc structure and visual function. In the area of perimetry, frequency-doubling. technology is a promising and feasible mass-screening method with reasonable sensitivity for detecting visual field loss. Central corneal thickness has emerged as a new risk factor for the development and progression of glaucoma, thereby complicating the role of tonometry and measurement of intraocular pressure as screening parameters for glaucoma. Along with technological advances, strides are also, being made with public policy and legislative efforts to bring glaucoma onto the national and global health care agenda. These initiatives incorporate vision-screening goals into national disease prevention programs emphasizing the need for early glaucoma detection and treatment. Summary Glaucoma awareness needs to be increased through better education, and compliance with follow-up care needs to be improved to decrease the economic and social costs from glaucoma. In addition, screening models need to be developed that will be effective in developing countries where the risk of blindness from glaucoma is highest.

Interventions for improving adherence to ocular hypotensive therapy - Waterman, H; Evans, JR; Gray, TA; Henson, D; Harper, R (COCHRANE DATABASE OF SYSTEMATIC REVIEWS, 2013)
Background Poor adherence to therapy is a significant healthcare issue, particularly in patients with chronic disease such as open-angle glaucoma. Treatment failure may necessitate unwarranted changes of medications, increased healthcare expenditure and risk to the patient if surgical intervention is required. Simplifying eye drop regimes, providing adequate information, teaching drop instillation technique and ongoing support according to the patient need may have a positive effect on improving adherence. Objectives To summarise the effects of interventions for improving adherence to ocular hypotensive therapy in people with ocular hypertension (OHT) or glaucoma. Search methods We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2012, Issue 6), MEDLINE (June 1946 to June 2012), EMBASE (June 1980 to June 2012), Cumulative Index to Nursing and Allied Health Literature (CINAHL) (June 1937 to June 2012), PsycINFO (1806 to June 2012), PsycEXTRA (1908 to June 2012), Web of Science (1970 to June 2012), ZETOC (1993 to June 2012), OpenGrey (System for Information on Grey Literature in Europe) (www.opengrey.eu/), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com), ClinicalTrials.gov (www.clinicaltrials.gov) and the WHO International Clinical Trials Registry Platform(ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. The electronic databases were last searched on 26 June 2012. We did not search the National Research Register (NNR) as this resource has now been now archived. We contacted pharmaceutical manufacturers to request unpublished data and searched conference proceedings for the Association for Research in Vision and Ophthalmology (ARVO), and the Annual Congress for the Royal College of Ophthalmologists (RCO). Selection criteria We included randomised controlled trials (RCTs) and quasi-RCTs that compared interventions to improve adherence to ocular hypotensive therapy for patients with OHT or glaucoma. Data collection and analysis At least two authors independently assessed the search results for eligibility and extracted data for included trials onto specifically designed forms. We did not pool data due to clinical and methodological heterogeneity. Main results Sixteen trials (1565 participants) met the inclusion criteria. Seven studies investigated some form of patient education. In six of these studies this education was combined with other behavioural change interventions including tailoring daily routines to promote adherence to eye drops. Eight studies compared different drug regimens (one of these trials also compared open and masked monitoring) and one study investigated a reminder device. The studies were of variable quality and some were at considerable risk of bias; in general, the length of follow-up was short at less than six months with only two studies following up to 12 months. Different interventions and outcomes were reported and so it was not possible to produce an overall estimate of effect. There was some evidence from three studies that education combined with personalised interventions, that is, more complex interventions, improved adherence to ocular hypotensive therapy. There was less information on other outcomes such as persistence and intraocular pressure, and no information on visual field defects, quality of life and cost. There was weak evidence as to whether people on simpler drug regimens were more likely to adhere and persist with their ocular hypotensive therapy. A particular problem was the interpretation of cross-over studies, which in general were not reported correctly. One study investigated a reminder device and monitoring but the study was small and inconclusive. Authors' conclusions Although complex interventions consisting of patient education combined with personalised behavioural change interventions, including tailoring daily routines to promote adherence to eye drops, may improve adherence to glaucoma medication, overall there is insufficient evidence to recommend a particular intervention. The interventions varied between studies and none of the included studies reported on the cost of the intervention. Simplified drug regimens also could be of benefit but again the current published studies do not provide conclusive evidence. Future studies should follow up for at least one year, and could benefit from standardised outcomes.

Glaucoma Diagnoses and Legal Blindness from Glaucoma among Bedouin Patients of Central Saudi Arabia: A Hospital-Based Study - Al-Najmi, Y; Kirat, O; Elsayed, MA; Albeedh, M; Al-Rashed, D; Al-Mohammed, A (MIDDLE EAST AFRICAN JOURNAL OF OPHTHALMOLOGY, 2021)
PURPOSE: The current study aims to know the glaucoma diagnoses and legal blindness from glaucoma among a tertiary referral center in Riyadh (King Abdulaziz Medical City [KAMC]-Riyadh patients). METHODS: This is a retrospective cohort study on chart review, where all eligible glaucoma patients attending the ophthalmology clinic at KAMC-Riyadh, between 2018 and 2019; were included. RESULTS: A total of 248 patients were included in the study; 142 patients (57.3%) were females and 106 (42.7%) were males. The mean age of the patients was 62.2 +/- 18 years and most of them (93.5%) did not have a family history of glaucoma. Nearly one-quarter (26.6%; n = 66) of the included patients were legally blind, out of those, 36.4% had their right eye affected, 34.8% had their left eye affected, and 28.8% had both eyes affected. Legally, blind patients (LBGs) did not show a statistically significant reduction in the intraocular pressure (IOP) in the right eye (P = 0.103), on comparing the IOP in both visits. Nevertheless, there was a statistically significant reduction in the IOP of the left eye among the LBGs in both visits (P = 0.016). Regarding the nonblind group of patients, there were highly statistically significant reductions in both eyes (P < 0.001). CONCLUSION: The present findings show a high prevalence rate of legal blindness among glaucoma patients, with IOP reduction, age, and glaucoma diagnoses being the most important predictors among the study population.

Long-term visual outcome of congenital cataract at a Tertiary Referral Center from 2004 to 2014 - Rajavi, Z; Mokhtari, S; Sabbaghi, H; Yaseri, M (JOURNAL OF CURRENT OPHTHALMOLOGY, 2015)
Purpose: To assess the long-term visual acuity (VA) outcome after congenital cataract surgery at Imam Hossein Medical Center (Tertiary Referral Center) (2004-2014). Methods: In this descriptive study, records of 120 patients with a history of congenital cataract surgery were studied. Those with traumatic, metabolic cataract, aged <5 years at the last visit who were not able to respond VA testing accurately and follow-up <6 months were excluded. Cases with incomplete files were recalled and reexamined. Finally, the records of 42 patients (71 eyes) were included. Results: In this study, 20 males and 22 females with a mean age of 11.80 +/- 6 years at their last visit were studied. Bilateral and unilateral cataract was seen in 69% and 31% of cases, respectively. Posterior and anterior subcapsular opacity was the most common (53.70%) and rarest (1.90%) type of congenital cataract, respectively. The mean age at the time of operation and surgical interval was 65 +/- 66.6 (range: 1-200) and 12.9 +/- 23.5 (range: 0-96) months, respectively. The most common method of refractive error correction was pseudophakia plus glasses (56.3%) with the mean best corrected visual acuity (BCVA) of 0.29 +/- 0.28 LogMAR., The mean BCVA was 0.7 +/- 0.53 LogMAR for aphakic patients correcting by glasses. In our study, amblyopia (56%), glaucoma (23.90%), and posterior capsular opacity (16.40%) were observed during their follow-ups on an average of 76 +/- 65 months (median: 60, range: 6-240). Unilateral cataract, aphakia, nystagmus, female gender, and strabismus were risk factors of VA loss. Conclusion: Based on our results, 56% of cases showed amblyopia. It could be due to late operation (especially in unilateral cases), longer surgical interval between two eyes, and no compliance of amblyopia therapy. Early detection through screening may reduce the rate of amblyopia. Refractive errors, visual acuity, amblyopia, glaucoma, posterior capsular opacity, and compliance of amblyopia therapy should be checked regularly at follow-up visits. Copyright (C) 2015, Iranian Society of Ophthalmology. Production and hosting by Elsevier B.V.

Safety and efficacy of brimonidine in children with glaucoma - Enyedi, LB; Freedman, SF (JOURNAL OF AAPOS, 2001)
Purpose: Brimonidine is a relatively selective (x-agonist, which reduces intraocular pressure (IOP) by decreasing aqueous production and increasing uveoscleral outflow. Brimonidine passes through the blood-brain barrier, potentially causing central nervous system (CNS) toxicity. There have been reports of bradycardia, hypotension, hypothermia, hypotonia, and apnea in infants after topical brimonidine. Methods: We reviewed the IOP data and side effects of children at the Duke University Eye Center placed on brimonidine from June 1997 to October 2000. Brimonidine 0.2% was used for patients whose glaucoma was uncontrolled on maximal tolerated medical therapy. A monocular trial was performed whenever possible, and brimonidine was not prescribed for infants. Included were 32 eyes of 30 patients with uncontrolled IOP and varied glaucoma diagnoses. Results: The mean patient age was 10.5 years, with a mean follow-up on brimonidine of 10.8 months. Most patients were on other glaucoma medications. In 11 of the 32 eyes the IOP data could be interpreted, and in these eyes the IOP decreased from a mean of 22.5 +/- 4.9 mm Hg to a mean of 20.8 +/- 4.0 mm Hg (a mean decrease of 6.7% +/- 10%, P = .04) on brimonidine after a mean follow-up of 11.0 +/- 6.9 months. Two young children (ages 2.4 and 3.7 years) repeatedly were unarousable soon after the administration of brimonidine. Five other children experienced extreme fatigue after brimonidine administration. All symptoms resolved after brimonidine was discontinued. Discussion/Conclusions: Brimonidine should be used with caution in young children because of the potential for CNS depression. In selected patients, brimonidine has a substantial ocular hypotensive effect.

Provider Education about Glaucoma and Glaucoma Medications during Videotaped Medical Visits - Sleath, B; Blalock, SJ; Carpenter, DM; Muir, KW; Sayner, R; Lawrence, S; Giangiacomo, AL; Hartnett, ME; Tudor, G; Goldsmith, J; Robin, AL (JOURNAL OF OPHTHALMOLOGY, 2014)
Objective. The purpose of this study was to examine how patient, physician, and situational factors are associated with the extent to which providers educate patients about glaucoma and glaucoma medications, and which patient and provider characteristics are associated with whether providers educate patients about glaucoma and glaucoma medications. Methods. Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited and a cross-sectional study was conducted at six ophthalmology clinics. Patients' visits were videotape recorded and patients were interviewed after visits. Generalized estimating equations were used to analyze the data. Results. Two hundred and seventy-nine patients participated. Providers were significantly more likely to educate patients about glaucoma and glaucoma medications if they were newly prescribed glaucoma medications. Providers were significantly less likely to educate African American patients about glaucoma. Providers were significantly less likely to educate patients of lower health literacy about glaucoma medications. Conclusion. Eye care providers did not always educate patients about glaucoma or glaucoma medications. Practice Implications. Providers should consider educating more patients about what glaucoma is and how it is treated so that glaucoma patients can better understand their disease. Even if a patient has already been educated once, it is important to reinforce what has been taught before.

Diagnosis and therapy of pseudoexfoliation glaucoma - Junemann, AGM (OPHTHALMOLOGE, 2012)
Pseudoexfoliation (PEX) glaucoma is the most frequent and most important type of secondary glaucoma, accounting for approximately 25% of open angle glaucoma worldwide and currently representing the most common identifiable cause of glaucoma overall. Due to high intraocular pressure levels, marked diurnal pressure fluctuations and spikes, and rapid optic nerve damage and visual field loss, PEX glaucoma represents a relatively severe and progressive type of glaucoma. Therefore, hard and fast lowering of intraocular pressure is necessary. Fixed combinations in medical therapy and early glaucoma surgery are recommended. When considering a surgical procedure (e.g. selective laser trabeculoplasty, bleb-dependent or bleb-independent surgery) the timing of cataract surgery plays a major role. Pathogenesis, clinical characteristics and therapeutic aspects of PEX glaucoma are described in the following article.

Increasing Engagement of African American Patients with Glaucoma during Medical Encounters: Creation of a Pre-visit Video - Sleath, B; Davis, SA; Carpenter, DM; Robin, AL; Muir, KW; Lee, C; Garcia, N; Budenz, DL (OPTOMETRY AND VISION SCIENCE, 2020)
SIGNIFICANCE The developed video can be accessed by African American patients with glaucoma from across the United States on YouTube to learn why it is important to ask eye care providers any questions they might have about glaucoma and/or its treatment. PURPOSE Our objective was to develop an educational video for African Americans with glaucoma to watch before their ophthalmology office visits to help motivate them to be actively involved in their care. METHODS The Social Cognitive Theory guided the development of the video. We conducted three focus groups with African American patients with glaucoma and three focus groups with providers who care for African American patients with glaucoma. The research team reviewed the transcripts of the focus groups and then developed a plan for video production. RESULTS The themes that both patients and providers felt should be covered in the video to motivate patient question-asking included the following: what is glaucoma, glaucoma treatment, glaucoma testing, and treatment adherence. Based on focus group results, the resulting video had one male African American physician and four African American patients covering the themes that emerged. CONCLUSIONS Ophthalmologists and African Americans with glaucoma gave us excellent insight into developing videos to increase patient involvement during their visits.

Effects on IOP restoration and blood-aqueous barrier after long term treatment with latanoprost in open angle glaucoma and ocular hypertension - Linden, C; Nuija, E; Alm, A (BRITISH JOURNAL OF OPHTHALMOLOGY, 1997)
Aims - To evaluate whether long term treatment with the prostaglandin analogue latanoprost has a deleterious effect on the blood-aqueous barrier (BAB) and to determine the duration of the effect on intraocular pressure (IOP) after withdrawal of treatment. Methods - Patients with ocular hypertension or glaucoma were topically treated with latanoprost 50 mu g/ml once daily for 6-12 months. In 26 patients IOP was followed for 14 days after withdrawal of treatment. Aqueous flare was measured with a laser hare meter during 6-12 months' treatment in 16 patients. Results - On the last day of treatment IOP was 6.9 mm Hg (95% CI 5.3-8.5) lower than before treatment. It increased slowly during the follow up period but was still 1.3 mm Hg (95% CI 0.2-2.5) lower than pretreatment IOP 14 days after cessation of treatment. No change in aqueous flare was seen throughout the study. Conclusion - Latanoprost has no clinically significant effect on the permeability of the BAB and IOP will return to pretreatment levels within a few weeks, indicating that latanoprost is safe for long term treatment.

Predictors of visual impairment in primary and secondary glaucoma in a tertiary institute in North India - Raj, S; Savla, LP; Thattaruthody, F; Seth, NG; Kaushik, S; Pandav, SS (EUROPEAN JOURNAL OF OPHTHALMOLOGY, 2020)
Aim: To find out and compare various predictors of glaucoma-related visual impairments in primary and secondary glaucoma. Methods: A prospective observational study of patients, who were above 30 years of age. They were diagnosed as primary/secondary glaucoma with visual acuity <20/200 Snellen's/visual field showing less than 20 degrees isopter in at least one eye, with a minimum follow-up of one year at a tertiary center. Patients were classified into advanced and end-stage glaucoma and outcome was assessed according to visual acuity and visual fields to see predictors of visual impairments. Results: There were 169 (99 primary/70 secondary) glaucoma patients with mean age of 62.67 +/- 11.9 and 54.65 +/- 15.26 years, respectively. Trauma (21.4%), complicated cataract surgery (15.7%), and silicon oil tamponade (14.3%) were common causes of secondary glaucoma. There was significant delay in diagnosis in primary compared to secondary glaucoma (57.57% vs 32.85%) and non-compliance was significantly higher in primary glaucoma (34.3% vs 17.1%, p = 0.01). In univariate analysis, literacy, income status, locality, and delayed or missed diagnosis were found to be significant (p < 0.05) according to visual acuity criteria. Out of the 33 patients who had undergone glaucoma filtration surgery, 18 (54.5%) were in the end-stage group. While 105 (77.2%) of 136 patients who were not subjected to any glaucoma filtration surgery reached end-stage glaucoma as per visual fields criteria (p = 0.011). Conclusion: Lack of awareness, delayed diagnosis, low literacy, and income were associated with poor visual outcome. Patients who underwent glaucoma filtration surgery had significantly better visual outcome in comparison to patients managed medically.

Determinants of medication adherence to topical ocular hypotensives and application of health belief model among glaucoma patients visiting a tertiary care hospital in coastal Karnataka, India - Kaup, S; Oomman, SS; Shivalli, S (INDIAN JOURNAL OF OPHTHALMOLOGY, 2018)

Comparison of the Intraocular Pressure-Lowering Effect and Safety of Preservative-Free And Preservative-Containing Brimonidine/Timolol Fixed-Combination Ophthalmic Solutions in Patients with Open-Angle Glaucoma - Kim, JM; Kim, TW; Park, SW; Park, HYL; Hwang, YH; Jeoung, JW; Kim, CY (SEMINARS IN OPHTHALMOLOGY, 2021)
Purpose: To compare the therapeutic efficacy and safety of newly developed preservative-free (PF) brimonidine/timolol fixed-combination (BTFC) ophthalmic solutions and a preservative-containing (PC) BTFC ophthalmic solution in patients with open-angle glaucoma. Methods: This study was conducted as a multicenter, randomized, open-label, parallel-group clinical trial to evaluate the efficacy and safety of PF BTFC as compared with PC BTFC in adult patients (aged >= 19 years) with open-angle glaucoma (OAG) and ocular hypertension (OHT). A total of the 106 patients were enrolled, with 53 patients each randomized to the two treatment groups and included in the analysis of the safety set (SS). After a washout period, patients with an IOP below 35 mmHg at 9 a.m. were enrolled. After a full ophthalmic and glaucoma examination, a total of 106 OAG and OHT patients were randomized to the PF group or PC group. All subjects were examined 4 and 12 weeks after first administration. At each follow-up visit, IOP was measured at 9 a.m. and 11 a.m. and the efficacy, safety, and compliance were evaluated. Throughout the study, all adverse events were recorded and monitored by the investigators. Results The mean IOP changes from baseline to 12 weeks at 11:00 a.m. were -3.45 +/- 2.53 mmHg in the PF group and -3.65 +/- 2.76 mmHg in the PC group (p < .0001 for both). The difference in mean IOP change between the two groups was 0.20 +/- 2.65 mmHg, which was not significantly different. The proportion of patients with IOP reductions of >= 15% and >= 20% and IOP at all-time points in the PF group were not significantly different when compared with in the PC group. There were no specific differences between the two groups regarding the incidence of adverse events. Conclusions PF BTFC ophthalmic solution shows a similar efficacy and safety profile to that of PC BTFC.

The efficacy and safety of unfixed and fixed combinations of latanoprost and other antiglaucoma medications - Higginbotham, EJ; Diestelhorst, M; Pfeiffer, N; Rouland, JF; Alm, A (SURVEY OF OPHTHALMOLOGY, 2002)
Adjunctive therapy for the management of glaucoma is commonly used. Unfixed combinations of the prostaglandin analog latanoprost and other glaucoma medications have been demonstrated to effectively lower intraocular pressure (IOP). The range of reported additional reductions in IOP compared to a monotherapy baseline are as follows: latanoprost-timolol (13-37%), latanoprost-pilocarpine 2% (7-14%), latanoprost and carbonic anhydrase inhibitors (15-24.1%), and latanoprost and dipivefrin (15-28%). There is a fixed combination of latanoprost (0.005%) and timolol (0.5%) that has been investigated in Phase III trials in Europe and the United States. In these trials, it was noted that the efficacy of the fixed combination was superior to either of the monotherapy components. After 12 months of follow-up of patients on fixed combination, there was no evidence of long-term drift. The new formulation appears to be safe and does not demonstrate any more side effects than either of the components. The convenience of a fixed combination may enhance patient compliance. Unfixed combination therapy with latanoprost and other antiglaucoma medications and the fixed combination formulation of latanoprost and timolol provide an effective and safe option for lowering IOP in glaucoma patients.

The effect of prophylactic topical carbonic anhydrase inhibitors in canine primary closed-angle glaucoma - Stavinohova, R; Newton, JR; Busse, C (JOURNAL OF SMALL ANIMAL PRACTICE, 2015)
OBJECTIVESTo determine the effect of 1% brinzolamide, 2% dorzolamide hydrochloride or combination 2% dorzolamide hydrochloride/0 5% timolol to delay the elevation of the intraocular pressure in second eyes of dogs with primary closed-angle glaucoma. METHODSAnalysis of retrospectively collated data from 40 dogs with primary closed-angle glaucoma, where the non-affected eye was treated prophylactically with brinzolamide (n = 10), dorzolamide (n = 18) or combination dorzolamide/timolol therapy (n = 12). RESULTSThe 40 treated dogs (median age of 76 2 months) comprised 25 females/15 males, 19 entire/21 neutered. Twenty dogs developed glaucoma in the contralateral eye (median time of 9 2 months). No statistically significant difference was identified during treatment failure between the treatment groups (P = 0 66). The second eye remained normotensive in 20 dogs; four dogs until the conclusion of the study (median: 27 0 months), three dogs until death (median: 15 4 months), seven dogs until lost to follow-up (median: 11 6 months). Out of these 20 dogs, treatment was discontinued because of lack of owner compliance in two dogs and following a local drug reaction in four dogs (median: 8 9 months). CLINICAL SIGNIFICANCEThere was no evidence that the tested drugs delayed elevation of intraocular pressure in contralateral eyes of dogs with primary closed-angle glaucoma.

Patterns and rate of adherence to glaucoma therapy using an electronic dosing aid - Ajit, RR; Fenerty, CH; Henson, DB (EYE, 2010)
Aims and purpose To identify patterns and rates of adherence with travoprost eye drops using the Travatan dosing aid (TDA) and to present a method for graphically presenting adherence data. Methods A prospective observational cohort study of patients on travoprost (prostaglandin) monotherapy. Patients were dispensed a TDA and followed up after approximately 3 months of usage. Data were downloaded from the TDA into a computer for analysis. Analysis used inter-dose intervals (the time between each dosing) to look at adherence between days 4 and 75. Results In all, 100 patients were invited to participate, 53 agreed and complete TDA data sets were obtained from 37. In total 23 of the complete data sets showed good adherence (dosing within +/- 4 h of the agreed dosing time on 480% of occasions), 3 patients discontinued usage before 75 days, 4 showed frequent drug holidays (no dosing for >= 8 days) and 7 frequently missed doses with adherence rates of <60%. Of the 16 patients for whom no TDA data was obtained, 5 were lost to follow-up, 4 had faulty/damaged TDAs, 3 changed medication, 3 preferred not to use the TDA, and 1 was hospitalized. Conclusions There were four easily defined patterns of adherence; (1) good adherence; (2) discontinued usage; (3) frequent drug holidays; and (4) frequent missed doses with low adherence rates. A new method for graphically presenting adherence data helps clinicians identify the pattern of usage and is a valuable aid to the overall management of patients on travoprost therapy. Eye (2010) 24, 1338-1343; doi:10.1038/eye.2010.27; published online 26 March 2010

Assessing the Role of the Family/Support System Perspective in Patients With Glaucoma - Shtein, RM; Newman-Casey, PA; Herndon, L; Coleman, AL; Lee, PP (JOURNAL OF GLAUCOMA, 2016)
Purpose: To investigate the role of the family/friends support system for patients with glaucoma and their perspective on barriers to effective glaucoma management. Methods: Six focus groups were conducted in 3 geographically and ethnically diverse areas of the United States (Los Angeles, CA; Rochester, MN; Durham, NC) that included 31 participants; 68% (21/31) were family members and friends of glaucoma patients with poor vision and 32% (10/31) were support system individuals of patients with good vision. Content analysis was used to identify important themes. Semiquantitative analysis was used to measure the frequency of each theme. Results: A total of 134 relevant comments were made in the 6 focus groups and 72% of relevant comments were made by individuals providing support for patients with poor vision. Family members and friends mentioned the following areas of concern regarding patients' glaucoma care: patient education (19.4%), doctor-patient relationship (17.9%), their own lack of involvement in the patient's medical care (17.2%), frustration with glaucoma and with the patient (14.9%), patient dependency on caregivers (14.9%), patient frustration with the disease (10.4%), and sex differences in coping mechanisms (5.2%). Conclusions: Support system individuals tend to be minimally involved in the patient's glaucoma status and care. This is especially true for support system members of patients with glaucoma who maintain good vision and those who do not have any other personal experiences with difficulties from glaucoma. Many of these family members express an interest in acquiring more education about glaucoma and becoming more involved in the patient's glaucoma care.

Costs and effectiveness of travoprost versus a dorzolamide plus timolol fixed combination in first-line treatment of glaucoma: analysis conducted on the United Kingdom General Practitioner Research Database - Lafuma, A; Berdeaux, G (CURRENT MEDICAL RESEARCH AND OPINION, 2007)
Objective: To compare the effectiveness and associated costs of travoprost versus a fixed combination of dorzolamide + timolol as first-line therapy for glaucoma according to data collected by the United Kingdom General Practitioner Research Database (UK-GPRD). Methods: Patients with a diagnosis of ocular hypertension, glaucoma, or who had been treated topically by surgery or laser therapy were selected. Patients starting first-line treatment with travoprost or a fixed dorzolamide + timolol combination were included. Times to treatment failure were compared with an adjusted Cox model. Main outcome measures: Cost and treatment failure defined as a prescription change (adding or removing a topical treatment, or initiating laser therapy or surgery). Results: 56 612 patients were extracted from the database and 39 808 patients received at least one topical prescription for IOP-lowering (intraocular pressure) therapy. Of these, 639 were treated with travoprost and 387 with dorzolamide + timolol, as first-line therapies. No significant difference was found between patient characteristics. Patients were aged 70.0 years and 48.5% were male. At 1 year, treatment failure was experienced by 30.4% of patients receiving travoprost and 49.4% receiving dorzolamide + timolol (p < 0.001). The hazard ratio for failure was 0.79 (p < 0.03) less with travoprost, after adjusting on age, gender, comorbidities and duration of follow-up. Adjusted annual costs of glaucoma management were significantly (p < 0.001) lower with travoprost (198.31) pound than with dorzolamide + timolol (312.21) pound. Conclusion: This retrospective costs and consequences analysis study showed that travoprost is more efficient than dorzolamide + timolol as first-line therapy for glaucoma patients. Patients continued longer with first-line treatment when prescribed travoprost at a lower cost.

Trabecular micro-invasive glaucoma surgery. Procedures and clinical results - Junemann, AGM; Rejdak, R; Hohberger, B (OPHTHALMOLOGE, 2018)
The management of glaucoma therapy to reduce intraocular pressure commonly consists of a gradual approach with local monotherapy, combined therapy, laser surgery and finally filtration surgery. The local side effects of glaucoma medications and the lack of adherence and persistence to the medical therapy as well as the complication profile of the established glaucoma surgical techniques justify the introduction of new surgical procedures. Micro-invasive glaucoma surgery (MIGS) is a promising new surgical approach. Microstents can reduce the medication burden and prolong the need for filtration surgery. This review article presents the different trabecular implants (iStent, iStent inject, Hydrus (TM) Microstent) in detail and discusses the effectiveness and safety of the procedures based on the currently available data.

Outcomes of surgical interventions for primary childhood glaucoma in Northern Tanzania - Fiess, A; Furahini, G; Bowman, R; Bauer, J; Dithmar, S; Philippin, H (BRITISH JOURNAL OF OPHTHALMOLOGY, 2017)
Aim To evaluate goniotomy, trabeculotomy, transscleral cyclophotocoagulation (TSCPC) and trabeculectomy as initial procedures in children with primary childhood glaucoma from Northern Tanzania. Methods A retrospective analysis of consecutive interventions for primary childhood glaucoma from 2000 to 2013 was conducted at the Kilimanjaro Christian Medical Centre. Success was defined as postoperative intraocular pressure (IOP) below 22 mmHg. Success rates, IOP, visual acuity (VA), subsequent interventions and potential risk factors for failure were reported for the respective interventions. Results The study included 116 eyes of 70 children (age 4.6 +/- 5.9 years) with primary childhood glaucoma; 46 (65.7%) children were male. The preoperative IOP was 33.1 +/- 10.2 mmHg, the preoperative cup/disc (CD) ratio 0.71 +/- 0.3 and the corneal diameter 13.3 +/- 1.4 mm. As a primary intervention, 61 (52.6%) eyes underwent goniotomy, 10 (8.6%) eyes trabeculotomy, 12 (10.3%) TSCPC and 33 (28.4%) trabeculectomy. Follow-up data after 12 months were available for 63 (54.3%) eyes. Success rates at 12 months were 38% (goniotomy), 30% (trabeculotomy), 17% (TSCPC) and 64% (trabeculectomy). All interventions achieved a statistically significant IOP reduction at 3, 6 and 12 months, except for trabeculotomy after 6 months and TSCPC at all time points. Postoperative endophthalmitis occurred in one child treated with trabeculectomy. VA in 82% of all eyes was maintained or had improved after 12 months. Conclusions Based on the success rates of this retrospective analysis, goniotomy or trabeculotomy for younger and trabeculectomy for older children can be recommended in our setting to reduce IOP. Late presentation in combination with advanced glaucomatous damage as well as erratic postoperative follow-up and treatment were likely factors that compromised overall success rates. More efforts are necessary to detect the blinding disease earlier and improve adherence to follow-up.

Provider Use of Collaborative Goal Setting with Glaucoma Patients - Sleath, B; Slota, C; Blalock, SJ; Sayner, R; Carpenter, DM; Muir, KW; Hartnett, ME; Robin, AL (OPTOMETRY AND VISION SCIENCE, 2014)
Purpose The purpose of this preliminary study was to describe the extent to which providers used collaborative goal setting and individualized assessment with patients who were newly prescribed glaucoma medications. Methods English-speaking glaucoma suspect patients from six ophthalmology clinics who were newly prescribed glaucoma medications had their medical visits videotaped and were interviewed after the visits. The videotapes were transcribed and coded to examine provider use of collaborative goal setting and individualized assessment. Results Fifty-one patients seeing 12 ophthalmologists participated. Providers gave patients glaucoma treatment options during 37% of the visits; only five providers gave patients treatment options Providers asked for patient treatment preferences in less than 20% of the visits; only two providers asked for patient treatment preferences. Providers were significantly more likely to ask African American patients for their preferences or ideas concerning treatment than non-African American patients (Pearson (2) = 4.1, p = 0.04). Providers were also significantly more likely to ask African American patients about their confidence in using glaucoma medication regularly than non-African American patients (Pearson (2) = 8.2, p = 0.004). Providers asked about patient views about glaucoma in less than 20% of the visits; five providers asked patients their views on glaucoma and its treatment. Providers were significantly more likely to ask African American patients about their views on glaucoma than non-African American patients (Pearson (2) = 5.62, p = 0.02). Conclusions Eye care providers often did not use collaborative goal setting or conduct individualized assessments of patient views on glaucoma when prescribing treatment for the first time.

A Retrospective Comparison of Primary Baerveldt Implantation versus Trabeculectomy with Mitomycin C - Panarelli, JF; Banitt, MR; Gedde, SJ; Shi, W; Schiffman, JC; Feuer, WJ (OPHTHALMOLOGY, 2016)
Purpose: To compare the safety and efficacy of Baerveldt implantation (Abbott Medical Optics, Santa Ana, CA) and trabeculectomy with mitomycin C (MMC) in patients who have not undergone prior incisional ocular surgery. Design: Retrospective, comparative case series. Participants: A total of 125 patients with low-risk glaucoma undergoing primary glaucoma surgery, including 55 patients who received a 350-mm(2) Baerveldt glaucoma implant and 70 patients who underwent trabeculectomy with MMC. Methods: Eligible patients were identified using Current Procedural Terminology codes, and their medical records were reviewed retrospectively. Main Outcome Measures: The primary outcome measure was surgical success (intraocular pressure [IOP] <= 21 mmHg and reduced >= 20% from baseline, IOP >5 mmHg, no reoperation for glaucoma, no loss of light-perception vision). Secondary outcome measures included visual acuity, IOP, number of glaucoma medications, and complications. Results: The cumulative probability of success at 3 years with or without medical therapy was 87% in the Baerveldt group and 76% in the trabeculectomy group (P = 0.23). Postoperative complications occurred in 11 patients (20%) in the Baerveldt group and 20 patients (29%) in the trabeculectomy group (P = 0.27). Mean follow-up +/- standard deviation was 27 +/- 19 months in the Baerveldt group and 34 +/- 20 months in the trabeculectomy group (P = 0.053). Conclusions: Similar rates of surgical success and postoperative complications were observed in patients undergoing trabeculectomy with MMC and in those undergoing Baerveldt implantation during 3 years of follow-up. Both are viable primary glaucoma procedures in patients who have not undergone prior ocular surgery. (C) 2016 by the American Academy of Ophthalmology.

Establishing a Regional Glaucoma Physician Collaborative to Improve Quality of Care - Ehrlich, JR; Wentzloff, JN; Imami, NR; Blachley, TS; Stein, JD; Lee, PP; Weizer, JS (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2017)
PURPOSE: Improving adherence to practice guidelines can improve patient safety and quality of care. We sought to establish a regional glaucoma physician collaborative to evaluate and improve adherence to the American Academy of Ophthalmology's Primary Open-angle Glaucoma (POAG) Preferred Practice Pattern (PPP) guidelines. DESIGN: Prospective interventional study. METHODS: The collaborative consisted of 13 glaucoma specialists from 3 practices in Michigan. All consecutive POAG new patient visits were reviewed from each study site to determine physician adherence to the 13 major examination elements of the PPP. In phase 1 of the study, physician adherence rates for each of the recommended examination elements were combined and averaged for all groups. Averages for the collaborative were reported to each site, and each physician received his or her individual adherence rates. Physicians discussed strategies to improve overall adherence to the PPP. Adherence rates were collected in phase 2 to determine if feedback and sharing of strategies resulted in improved adherence. RESULTS: A total of 274 new POAG patient visits from phase 1 and 280 visits from phase 2 were reviewed. After accounting for multiple comparisons, overall improvement approached statistical significance for the evaluation of visual function (91.2% to 96.1%, P <.02) and target intraocular pressure determination (73.7% to 83.2%, P <.01). Improvement for other measures that had a high rate of adherence at baseline (eg, ocular history, pupil examination, and central corneal thickness measurement) was not statistically significant. CONCLUSIONS: It is feasible to establish a regional glaucoma physician collaborative to improve standardiza-tion of care for patients with newly diagnosed POAG. (C) 2017 Elsevier Inc. All rights reserved.

Relationship with the glaucomatous patient: how to announce glaucoma to the patient? - Ginies, P (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2009)
Announcement of a chronic disease, always, is a difficult task in the physician professional activity. For glaucoma, its possible impact on their vision and quality of life are a source of anxiety for most patients. The message should be simple and comprehensible, but accurate, to ensure tong term compliance to follow-up and treatment. Announcement should be tailored to the patient personality and psychological profile. The clinician should know his own personality, but his patient's personality also, to guarantee successful information and communication and a good quality patient-clinician relationship. Simple rules to be applied are described. (C) 2009 Elsevier Masson SAS. All rights reserved.

Development and pilot-testing of patient decision aid for use among Chinese patients with primary open-angle glaucoma - Shum, JWH; Lam, WWT; Choy, BNK; Chan, JCH; Ho, WL; Lai, JSM (BMJ OPEN OPHTHALMOLOGY, 2017)
Background A patient decision aid (PDA) is a tool for shared decision making (SDM), which emphasises patient empowerment. It is useful in chronic diseases and when there are multiple, no best single treatment option. Although SDM is prevalent in Western countries, its use is limited in Chinese societies, where the adoption of a paternalistic approach is strong. Here, we report the development, acceptance and pilot test results of a PDA targeted at Chinese patients with primary open-angle glaucoma (POAG). Methods We developed a PDA designed for use in Chinese patients with POAG. Recruited subjects were given our PDA. Baseline evaluation included decision conflict scale (DCS), validated glaucoma adherence questionnaires and glaucoma knowledge questionnaire. Subjects were briefed through the PDA and instructed to read it that day. Three to four weeks later, follow-up questionnaire as described above were conducted with the addition of acceptance questionnaires. Results Data from 65 subjects were available. The PDA was well received among subjects. DCS improved from 48.9 +/- 20.4 at baseline to 34.3 +/- 20.3 during follow-up, with P<0.01. Validated medication adherence questionnaires and knowledge showed improvement from baseline, which was statistically significant. Conclusions The use of PDA among Chinese subjects with POAG demonstrated positive reception and acceptance. Evaluation of its initial effects shows improvement in DCS, medication adherence and glaucoma knowledge. The implementation of SDM and PDA among Chinese subjects with POAG is encouraged. Future studies with randomised design and later evaluation time points can further reveal the impacts of PDA among Chinese subjects with POAG.

Willingness to Use Mobile Health in Glaucoma Patients - Dai, MM; Xu, JA; Lin, JL; Wang, ZH; Huang, WM; Huang, JJ (TELEMEDICINE AND E-HEALTH, 2017)
Introduction: Development of mobile health (m-health) in China carries tremendous potential, especially for glaucoma, one of the major chronic ophthalmic diseases afflicting millions of people. However, little research has been undertaken to investigate the willingness of glaucoma patients to use m-health and the factors influencing their decisions. Subjects and Methods: This was a cross-sectional study. A self-administered or face-to-face interview survey was performed on 1,487 patients with glaucoma at the outpatient glaucoma service, Zhongshan Ophthalmic Center, Sun Yatsen University. Questionnaires captured patients' demographic data, WeChat access, and willingness to receive m-health. The data were analyzed by single factor chi-square test. Multiple logistic regression revealed the motivators and barriers to accept m-health adoption. Results: One thousand ninety-seven valid questionnaires were obtained. Seven hundred twenty-five respondents (66.1%) were willing to participate in m-health programs. 65.4% were younger than 60 years old. 40.9% had travel time from home to hospital of > 3 h. 63.6% had more than four followup visits for glaucoma. 86.5% experienced trouble events during clinic visits. The overall We Chat usage rate was 61.7%. Age, travel time, number of visits, trouble events in clinic, and We Chat access in patients with glaucoma were related to the willingness to use m-health (p < 0.05). Conclusions: Most patients with glaucoma were willing to participate in m-health programs, which are essential to increasing and improving access to care.

Outcomes Following Implantation of Two Second-Generation Trabecular Micro-Bypass Stents in Patients with Open-Angle Glaucoma on One Medication: 18-Month Follow-Up - Lindstrom, R; Lewis, R; Hornbeak, DM; Voskanyan, L; Giamporcaro, JE; Hovanesian, J; Sarkisian, S (ADVANCES IN THERAPY, 2016)
The study objective was to evaluate the intraocular pressure (IOP) and medication-lowering effect of 2 second-generation trabecular micro-bypass stents in eyes with open-angle glaucoma (OAG) on one preoperative medication. Fifty-seven qualified phakic eyes with OAG on 1 medication, preoperative medicated IOP of 18-30 mmHg, and preoperative unmedicated (post-washout) IOP of 22-38 mmHg underwent implantation of 2 second-generation trabecular micro-bypass stents in a standalone procedure. Evaluations included IOP, best-corrected visual acuity, medication use, fundus and slit lamp examinations, visual field, cup to disc ratio, pachymetry, and complications and interventions. Subjects have been followed for 18 months, and follow-up is ongoing. At Month 12 postoperative, 100% of eyes had achieved an IOP reduction aeyen20% (100% had IOP aecurrency sign18 mmHg and 67% had IOP aecurrency sign15 mmHg) without medication versus preoperative unmedicated IOP, and 75% had IOP reduction aeyen20% without medication versus preoperative medicated IOP. The Month 12 mean unmedicated IOP had decreased by 42%, to 14.2 +/- 1.9 mmHg vs 24.4 +/- 1.3 mmHg preoperatively, and this reduction was maintained through 18 months (14.4 +/- 2.1 mmHg). A high safety profile was observed. In this prospective, open-label, single-arm study, the standalone implantation of two second-generation trabecular micro-bypass stents in OAG patients on 1 preoperative medication resulted in IOP reduction to aecurrency sign15 mmHg and elimination of medication through 18 months, with favorable safety. ClinicalTrials.gov identifier, NCT02868190. Glaukos Corporation, San Clemente, CA.

Two-Year Outcomes of the New Low-cost Nonvalved Aurolab Aqueous Drainage Implant in Refractory Glaucoma - Ray, VP; Rao, DP (JOURNAL OF GLAUCOMA, 2020)
Purpose: This study aimed to report the 2-year surgical outcomes in terms of efficacy and safety of the relatively new, indigenously manufactured, low-cost nonvalved drainage device Aurolab Aqueous Drainage Implant (AADI) in the management of refractory glaucomas in the Indian population. Methods: A retrospective review of consecutive patients older than 12 years, who underwent nonvalved glaucoma drainage device surgery via AADI, was performed by a single fellowship-trained surgeon, between January 2014 and January 2018, who had at least 12 months of documented postoperative follow-up. Outcome Measures: Primary-intraocular pressure (IOP). Secondary-number of antiglaucoma medication (AGM), LogMAR best-corrected visual acuity and complications. Complete success was defined as IOP >= 5 and <= 21 mm Hg; qualified success was defined as fulfilling the above criteria with the use of AGM. Failure was defined as the inability to fulfill the IOP criteria, loss of perception of light, explantation, or any additional glaucoma surgery. Results: A total of 48 eyes of 46 patients were included with a median follow-up of 24 months (quartile 1=16, quartile 3=31.25; interquartile range=15.25) (mean=24.9 mo; SD=10.1). The IOP and number of AGM required was significantly lower at every timepoint postoperatively (P<0.001). The median LogMAR best-corrected visual acuity remained unchanged (P=0.307). Complications occurred in 21 patients (43.7%); some eyes had >1 complication. Complete success was seen in 56.3%; overall success was 87.5%. Conclusions: The safety and efficacy of the new nonvalved glaucoma drainage device, AADI, remain in its second year after implantation. Still further follow-up is recommended, as it has the ability to breach the cost barrier in newly industrialized nations worldwide

Effects of Polyquaternium- and Benzalkonium-Chloride-Preserved Travoprost on Ocular Surfaces: An Impression Cytology Study - Akcay, BIS; Guney, E; Bozkurt, TK; Topal, CS; Akkan, JCU; Unlu, C (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2014)
Purpose: To compare the toxicity effect of polyquaternium (PQ) and benzalkonium chloride (BAK) preservation of travoprost on the ocular surface. Methods: This prospective study included 44 eyes of 44 patients with newly diagnosed glaucoma. Twenty-two patients used PQ-preserved travoprost (PQ group) and 22 patients used BAK-preserved travoprost (BAK group). To investigate the effect on the ocular surface, conjunctival impression cytology (IC) was performed at baseline and the 1- and 6-month follow-up visits. Additionally, the ocular surface disease index (OSDI) questionnaire, Schirmer I test, and tear break-up time (TBUT) measurement were administered at baseline, and at 1-, 3-, and 6-month follow-up visits. Results: While both groups showed statistically significant IC grade increases at 1 and 6 months when compared with baseline measurements, IC grades were significantly higher for patients using PQ-preserved travoprost compared with patients using BAK-preserved travoprost. The Schirmer I test and TBUT scores were not statistically significant between group 1 and BAK group at baseline and at 1-, 3-, and 6-month visits (P > 0.05). OSDI scores did not statistically differ at baseline and the 1-month measurements between the 2 groups (P > 0.05), but the 3- and 6-month OSDI scores were significantly higher for BAK group (P = 0.001). Differences in OSDI and Schirmer I test scores were statistically significant at 1, 3, and 6 months in both groups as compared with baseline values (P < 0.05). Statistically significant differences in the TBUT scores were seen for both groups at 3 and 6 months, while BAK group, but not PQ group, had insignificant score differences at 1 month as compared with baseline values of PQ group (P = 0.083). Conclusion: PQ-preserved travoprost was found to be safer and better-tolerated than BAK-preserved travoprost. PQ-preserved travoprost provided better ocular surface comfort, and therefore a better patient experience, which would likely result in higher treatment compliance.

Is there a need for a therapeutic education with patients suffering with open-angle glaucoma? Preliminary inquiry regarding knowledge and patient adherence - Dugast, P; Thiboust, P; Blumen-Ohana, E; Nordmann, JP (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2016)
Purpose. - To evaluate the knowledge and compliance of patients with open-angle glaucoma in order to propose an approach by therapeutic education, validated for other chronic pathologies. Methods. - A questionnaire-based interview of all patients in the waiting room of the glaucoma center is performed by the same health care professional. Results. - Out of 200 patients, 73% know they will need to be treated throughout their lives and 95% are aware of the risk of blindness in the absence of appropriate treatment. However, 16% respond that they can be cured, and 54% believe that treatment can save their eyesight. Knowledge increases with the length of follow-up of patients at the glaucoma center beyond one year, but the progress is still insufficient in their confidence that treatment can save their eyesight (36% to 57%), and in the decrease in the number of patients who forget their treatment (56% to 30%). Conclusion. - Cognitive knowledge is insufficient to encourage the patient to comply with treatment. It is necessary to consider therapeutic patient education (TPE) techniques, such as described by WHO, in group and/or individual sessions, aimed at building the patient's confidence that treatment can delay the progression of the disease and blindness, strengthening his/her capacity to properly administer the eye drops, managing his/her treatment and coping with frequent side effects. Within this framework, our knowledge of the patients' representations of their glaucoma and its treatment must improve. (C) 2016 Elsevier Masson SAS. All rights reserved.

Personalized approaches for the management of glaucoma - Balendra, SI; Zollet, P; Casasca, GCADE; Cordeiro, MF (EXPERT REVIEW OF PRECISION MEDICINE AND DRUG DEVELOPMENT, 2020)
Introduction: Personalized medicine is the future goal across all specialties. Accurate prediction of optimal treatment beneficial and adverse effects could transform patient management. This is of particular importance in chronic conditions, where a 'trial and error' approach over months and years can contribute to significant morbidity. Glaucoma is a chronic irreversible progressive optic neuropathy, a leading cause of blindness worldwide. An ideal personalized approach in glaucoma clinic would be to answer the inevitable question in a patient's first visit: 'Which treatment option will work best for me so that I won't go blind?' Areas covered: This review will give an overview of the knowledge we have acquired to achieve this goal, particularly discussing using patient's individual risk factors, their genetic profile, and different treatment modalities, including therapy compliance, to personalize care. Expert opinion: Pharmacogenomics and genetic profiling are the most tangible ways in which glaucoma management can be personalized. Future challenges will include developing realistic animal models to reflect the underlying genetic patterns in glaucoma to investigate their interaction with different treatments.

Electronic medical record and glaucoma medications: connecting the medication reconciliation with adherence - Bacon, TS; Fan, KC; Desai, MA (CLINICAL OPHTHALMOLOGY, 2016)
Purpose: To evaluate consistency in documentation of glaucoma medications in the electronic medical record and identify which regimen patients adhere to when inconsistencies exist. Factors contributing to medication nonadherence are also explored. Methods: Retrospective chart review of medication adherence encompassing 200 patients from three glaucoma physicians at a tertiary referral center over a 1-month period. Adherence was determined by the consistency between a patients stated medication regimen and either the active medication list in the electronic medical record, or the physicians planned medication regimen in the preceding clinic visit. Patient charts were also reviewed for patient sex, age, primary language, race, and total number of medications. Results: A total of 160 charts showed consistency in documentation between the physician note and electronic medication reconciliation. Of those patients, 83.1% reported adherence with their glaucoma medication schedule. When there was a discrepancy in documentation (40 charts), 72.5% patients followed the physician-stated regimen vs 20% who followed neither vs 7.5% who followed the medical record (P<0.01). No difference in adherence was observed based on sex (P=0.912) or total number of medications taken (P=0.242). Language, both English- (P=0.075) and Haitian (P=0.10) -speaking populations, as well as race, Caucasian (P=0.31), African-American (P=0.54), and Hispanic (P=0.58), had no impact on medication adherence. Patients over 80 years of age were more nonadherent as compared to other decades (P=0.04). Conclusion: Inconsistent documentation between the electronic medical record physician note and medication regimen may contribute to patient medication nonadherence. Patients over 80 years of age were associated with higher rates of nonadherence, while sex, total number of medications, race, and language had no interaction with medication adherence.

Assessment of compliance with contact lens wear and care among university -based population in Jordan - Bakkar, MM; Alzghoul, EA (CONTACT LENS & ANTERIOR EYE, 2020)
Purpose: this survey aimed to assess levels of compliance with contact lens wear and care among university student ?s population in Jordan. Methods: An interviewer -administered questionnaire was used to assess the extent of compliance among contact lens wearers toward contact lens care in a university population. The questionnaire included 12 questions re- garding compliance with contact lens care, lens case/solution replacement, general hygiene procedures related to contact lens and adherence to aftercare visits. Results: 210 contact lens wearers were interviewed. Of the study population 187 (89 %) were females and 23 (11 %) were males. The average age of the study group was 22.35 ( ? 3.77) years and all the study population were students (undergraduate or postgraduate).The average compliance rate of the study population was 75 %. High level of compliance was noticeable in the following aspects; not sharing lenses with others, not sleeping while wearing lenses, hand washing before lens use and not using water to clean lenses. Moderate level of compliance was reported in the following aspects; showering/swimming with lenses, using lenses longer than recommended replacement schedule and all behaviours related to contact lens care solution. However, low levels of compliance were reported in relation to cleaning and rinsing lens case and adherence to aftercare visits. Conclusion: High to moderate levels of compliance were reported generally by participants. However, better strategies are recommended to further increase levels of compliance among contact lens wearers in Jordan related to adherence to aftercare visits. While this study is targeted contact lens wearers from a university student ?s population, a future study is recommended to include larger sample of contact lens wearers from the general lay population.

Current Knowledge and Attitudes Concerning Cost-Effectiveness in Glaucoma Pharmacotherapy: A Glaucoma Specialists Focus Group Study - Feldman, RM; Cioffi, GA; Liebmann, JM; Weinreb, RN (CLINICAL OPHTHALMOLOGY, 2020)
Background: Rising healthcare costs motivate continued cost-reduction efforts. To help lower costs associated with open-angle glaucoma (OAG), a prevalent, progressive disease with substantial direct and indirect costs, clinicians need to understand the cost-effectiveness of intraocular pressure (IOP)-lowering pharmacotherapies. There is little published information on clinicians' knowledge and attitudes about cost-effectiveness in glaucoma treatment. Purpose: This pilot focus group study aimed to explore clinician attitudes and perspectives around the costs and cost drivers of glaucoma therapy; the implementation of costeffectiveness decisions; the clinical utility of cost-effectiveness studies; and the costeffectiveness of available treatments. Methods: Six US glaucoma specialists participated in two separate teleconferencing sessions (three participants each), managed by an independent, skilled moderator (also a glaucoma specialist) using a discussion guide. Participants reviewed recent publications (n=25) on health economics outcomes research in glaucoma prior to the sessions. Results: Participants demonstrated a clear understanding of the economic burden of glaucoma therapy and identified medications, diagnostics, office visits, and treatment changes as key cost drivers. They considered cost-effectiveness an appropriate component of treatment decisionmaking but identified the need for additional data to inform these decisions. Participants indicated that there were only a few recent studies on health economics outcomes in glaucoma which evaluate parameters important to patient care, such as quality of life and medication adherence, and that longitudinal data were scant. In addition to efficacy, participants felt patient adherence and side-effect profile should be included in economic evaluations of glaucoma pharmacotherapy. Recently approved medications were evaluated in this context. Conclusion: Clinicians deem treatment decisions based on cost-effectiveness data as clinically appropriate. Newer IOP-lowering therapies with potentially greater efficacy and favorable side-effect and adherence profiles may help optimize cost-effectiveness. Future studies should include: clinicians' perspectives; lack of commercial bias; analysis of long-term outcomes/costs; more comprehensive parameters; real-world (including quality-of-life) data; and a robust Markov model.

Medical decision, persistence of initial treatment, and glaucoma progression in a Brazilian reference hospital - Paula, JS; Ramos, JA; Cecchetti, DFA; Nagatsuyu, DT; Rodrigues, MDV; Rocha, EM (ARQUIVOS BRASILEIROS DE OFTALMOLOGIA, 2010)
Purpose: To evaluate the initial medical decision regarding primary open-angle glaucoma (POAG) treatment in a referral center, and to assess the relationship between the persistence of treatment and the disease progression in cases managed exclusively with medication. Methods: A retrospective chart review was performed for 65 patients with primary open-angle glaucoma referred to a tertiary hospital. The following clinical data were analyzed: initial medication, persistence of treatment, best corrected visual acuity, visual field mean deviation index, cup/disc ratio, and intraocular pressure. Patients were classified into four categories in order to verify the clinical evolution. Results: The mean number of visits/year was 4.4 +/- 3.5, and the follow-up period was 40.7 +/- 22.8 months. Mean persistence time was 12.9 +/- 13.9 months. By six and twelve months, respectively, 39.1% and 62.5% of patients had discontinued the initially prescribed regimen, mainly by adding to (42%) or changing (26%) the course of treatment. Thirteen patients (21%) were reclassified to a worse category of primary open-angle glaucoma, however, despite this trend, no significant correlation was found between shorter persistence and primary open-angle glaucoma worsening. Conclusions: Persistence rates with initial therapy schemes were low, as measured by medical decisions to change the course of treatment. Therefore, improvement in the initial medical decision is crucial in order to offer a more stable and effective treatment for primary open-angle glaucoma.

Knowledge of medications among patients with glaucoma in Taiwan - Ko, ML; Wei, KL; Ho, YJ; Peng, PH; Lu, HHS (JOURNAL OF THE FORMOSAN MEDICAL ASSOCIATION, 2019)
Background/Purpose: To investigate the knowledge and learning ability of glaucoma patients regarding their anti-glaucoma topical medications. Methods: Patients on regular follow-up at the Glaucoma Clinic at Hsin-Chu General Hospital were recruited. After detailed ocular examinations, the participants were asked to recall and identify their glaucoma eye drops. The same test was repeated 3 months later. The results of both tests, the learning ability of patients regarding their glaucoma drugs, and the relationship between learning ability and demographic variables were evaluated. Results: Two hundred eighty-seven glaucoma patients participated in this study. Of the study population, 25.8% and 57.1% could recall their topical mediation at the first and second tests, whereas 72.1% and 88.5% could identify their prescribed eye drops at the first and second tests, respectively. Approximately 34% of the participants showed improved knowledge at the repeat test, whereas 40% of the participants showed no improvement. Participants with a better learning ability were more likely to be younger, with a higher level of education, and with less visual field impairment. Conclusion: The knowledge of glaucoma patients regarding their prescribed medication was deficient in Taiwan. Physician effort could improve knowledge on the prescribed drugs. Patient-centered education should be considered, targeting elderly individuals, illiterate individuals, and those with loss of visual function to increase compliance with glaucoma medication. Copyright (C) 2018, Formosan Medical Association. Published by Elsevier Taiwan LLC.

A STROBE-compliant case-control study Effects of cumulative doses of topical atropine on intraocular pressure and myopia progression - Yu, TC; Wu, TE; Wang, YS; Cheng, SF; Liou, SW (MEDICINE, 2020)
Topical atropine has become a mainstream treatment of myopia throughout East and Southeast Asia, but it is uncertain whether long-term topical atropine therapy induces intraocular pressure (IOP) elevation and subsequent development of glaucoma. We then prospectively examined the effects of long-term atropine treatment on IOP. Our case series collected 186 myopic children who were younger than 16 years of age. Complete ocular examination data, IOP and refractive status measurements beginning in 2008 were collected for all participants. Participants were divided into two groups: 121 children who received atropine therapy at various concentrations were classified as the treated group, whereas 65 children who did not receive atropine therapy were classified as the untreated (reference) group. In the treated group, clinicians prescribed different concentrations of atropine eye drops according to their discretion with regard to the severity of myopia on each visit of the patient. We then calculated the cumulative dose of atropine therapy from 2008 to the patients' last follow-up in 2009. Furthermore, the treated group was then further divided into low- and high-refractive-error groups of nearly equal size for further analysis. There were no significant differences for the baseline refractive errors and IOPs between the treated and untreated groups. Both the low- and high-cumulative atropine dosage subgroups showed significantly lower myopic progression than the untreated group, but there was no significant difference between the two subgroups in terms of different cumulative dosages. All groups, including the untreated group, showed an increase of mean IOP at the last follow-up, but both low- and high-cumulative atropine dosage subgroups experienced a smaller increase of IOP. The mean IOP of all atropine-treated groups showed no significant increase in either low- or high-refractive-error eyes. This study revealed that topical atropine eye drops do not induce ocular hypertension and are effective for slowing the progression of myopia. The treatment effects are not correlated with the cumulative atropine dosages.

Interventions Improve Poor Adherence with Once Daily Glaucoma Medications in Electronically Monitored Patients - Okeke, CO; Quigley, HA; Jampel, HD; Ying, GS; Plyler, RJ; Jiang, YZ; Friedman, DS (OPHTHALMOLOGY, 2009)
Purpose: To investigate the impact of an intervention program to improve adherence with topical, once daily therapy for glaucoma. Design: Randomized controlled clinical trial. Participants: Sixty-six patients with glaucoma being treated with a prostaglandin analog in 1 or both eyes at the Scheie Eye Institute or Wilmer Eye Institute between November 2006 and June 2007. Methods: In an observational study, participants who took 75% or fewer doses (as measured using the travoprost Dosing Aid [DA]) during an initial 3-month period were randomized into 2 groups. The intervention group watched an educational video, reviewed current barriers to drop-taking and possible solutions with a study coordinator, received regular phone call reminders, and had audible and visible reminders activated on their DA devices. The control group was told to take drops as prescribed and received no additional intervention. Main Outcome Measures: Change in drop use adherence as determined by the DA device. Results: In the 3-month observation period before randomization, intervention group patients had used a mean of 54 +/- 17% of scheduled doses, and this increased to 73 +/- 22% during the following 3-month period (P<0.001, n = 35). The control mean adherence rate of 46 +/- 23% at baseline was statistically unchanged during the follow-up observation period (51 +/- 30%, P = 0.16, n = 31). In a multivariate analysis, intervention, baseline compliance rate of <50%, and white ethnicity were predictors of improved adherence during the 3 months of intervention. The intraocular pressure (IOP) of the intervention and control groups did not change between months 3 and 6 after intervention (P = 0.96, 0.34, respectively), and there was no correlation of IOP change with adherence rate change between both groups (Pearson correlation r = 0.06, P = 0.51). Conclusions: A multifaceted intervention significantly increased adherence with glaucoma medications. Those with improved adherence were in the intervention group, had very low adherence rates at baseline, and were white. IOP did not correlate with adherence. Further research is needed to determine which components of this intervention were most effective.

Referral to community care from school-based eye care programs in the United States - Shakarchi, AF; Collins, ME (SURVEY OF OPHTHALMOLOGY, 2019)
Approximately 25% of school-aged children in the United States have vision abnormalities, most commonly refractive error that can be corrected with spectacles. Limited follow-up adherence after failed school-based vision screening led to an increase in school-based eye care programs that provide screening, eye examinations, and spectacle prescription at the school. These programs address the access barrier and often provide the first point of contact between children and eye care. Nevertheless, several lower prevalence conditions, such as amblyopia, strabismus, and glaucoma, cannot be adequately treated in the school setting, and some require frequent and long-term follow-up, necessitating referral to eye care providers in the community. We conducted a literature review and identified 10 programs that provided school-based screening, examinations, and spectacle prescription and reviewed their referral rates, criteria, mechanisms, adherence, ocular findings at referral, and long-term care plans. Most programs referred 1% to 5% of screened children. Most communicated with parents or guardians through referral letters and used various strategies to incentivize adherence. Referral adherence was 20-50% in the four programs that reported these data. School-based eye care programs rarely referred children for long-term follow-up care needs, such as updating spectacle prescriptions annually. (C) 2019 Elsevier Inc. All rights reserved.

Effectiveness of long-term infliximab use and impact of treatment adherence on disease control in refractory, non-infectious pediatric uveitis - Utz, VM; Bulas, S; Lopper, S; Fenchel, M; Sa, T; Mehta, M; Ash, D; Lovell, DJ; Kaufman, AH (PEDIATRIC RHEUMATOLOGY, 2019)
Background Refractory non-infectious uveitis is a serious condition that leads to ocular complications and vision loss and requires effective systemic treatment to control disease. The effectiveness of long-term infliximab [IFX] in refractory non-infectious childhood uveitis and the impact of treatment adherence on disease control were evaluated. Methods Retrospective, single-center study between December 2002 and April 2016 of 27 children with refractory non-infectious uveitis [17 with juvenile idiopathic arthritis, JIA] treated with long-term IFX [9+ months]. Disease activity was assessed prior to and while on IFX using the Standardization of Uveitis Nomenclature [SUN]. Number of visits per year with active uveitis was analyzed by repeated measures logistic regression analysis from 2 years prior to IFX initiation or from onset of uveitis until most recent visit on IFX. Incomplete treatment adherence was assessed for each visit and defined as any deviance in corticosteroid use, prescribed infusion frequency, and/or follow-up examination frequency. Results Primary outcomes were sustained uveitic and systemic disease control prior to and during IFX treatment and the impact of incomplete adherence on uveitic disease control while on IFX. Secondary outcomes included corticosteroid and glaucoma medication requirement, ocular complications and need for surgical intervention. Mean age at IFX initiation was 10.4 +/- 4.5 years; initial mean dose was 6.6 +/- 2.2 mg/kg [and given at weeks 0, 2, 4 and q4 weeks thereafter for 93%]. Median duration on IFX was 35 [range 9-128] months. Prior to IFX, 14/27 patients had failed adalimumab +/- methotrexate [MTX]; 21/27 failed MTX. IFX led to uveitis control in 89% and arthritis control in 76% (13/17). The odds ratio of having controlled disease after IFX was 4.1 (2.6, 6.4) compared to pre-treatment visits. Topical corticosteroids and glaucoma medications were statistically decreased (p = 0.007 right eye [OD], 0.003 left eye [OS] and p = 0.001 OD, p = 0.028 OS respectively). Incomplete adherence to treatment showed 10.3 times greater odds (7.1, 15.0) of having disease activity than full adherence. Conclusions This study adds significantly to the IFX literature by documenting outstanding uveitis control with long-term IFX treatment in non-infectious pediatric uveitis patients. Higher dosage and shorter interval were utilized without adverse effects. Importantly, this is the first study, to our knowledge, to document the significant impact of treatment adherence on uveitis control.

Real-world assessment of topical glaucoma medication persistence rates based on national pharmaceutical claim data in a defined population - Zhu, ZT; Jiang, Y; Wang, W; Scheetz, J; Shang, XW; Zhang, L; He, MG (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2019)
Importance The rate and determinants of persistence to topical glaucoma medications are important for identifying patients at high risk of discontinuing medications and designing targeted approaches to improve persistence. Background To evaluate the rate and determinants of persistence to topical glaucoma medications among middle-aged and older Australian adults. Design Population-based cohort study. Participants Participants in need of persistent topical glaucoma medications in the 45 and Up Study. Methods The 45 and Up Study is a large-scale population-based cohort study. Participants were classified as needing persistent topical glaucoma medications if at least three claims with related prescriptions were recorded. Persistence was defined as topical glaucoma medications were filled within 90 days. Main Outcome Measures The rates and determinants of medication persistence at 2-year follow-up. Results A total of 12 899 patients requiring persistent topical glaucoma medications were identified. Among them, 9019 (69.9%) had persisted with their glaucoma medications for at least 2 years. Multiple logistic regression analysis documented significant effects of patient-related factors (gender, socioeconomic status, language spoken at home, lifestyle and comorbidities) and drug-related factors (total number and drug class) on the persistence rate. Those most at risk groups of non-persistence were those patients living in remote areas (odds ratio, OR: 0.59, 95% confidence interval, CI: 0.37-0.92), having family income over 70 000 AUD/year (OR: 0.53, 95% CI: 0.45-0.62), speaking other languages at home (OR: 0.61, 95% CI: 0.53-0.68), and using cholinergic classes of medications (OR: 0.55, 95% CI: 0.38-0.79). Conclusions and Relevance Our data has shown a medium level of persistence to topical glaucoma medication among middle-aged and older Australian adults. However, efforts are still needed to improve the rate of persistence.

Drug-Free, Nonsurgical Reduction of Intraocular Pressure for Four Months after Suprachoroidal Injection of Hyaluronic Acid Hydrogel - Chae, JJ; Jung, JH; Zhu, W; Gerberich, BG; Fard, MRB; Grossniklaus, HE; Ethier, CR; Prausnitz, MR (ADVANCED SCIENCE, 2021)
Glaucoma is the leading cause of irreversible blindness. Current treatments use drugs or surgery to reduce intraocular pressure (IOP). In this study, a drug-free, nonsurgical method is developed that lowers IOP for 4 months without requiring daily patient adherence. The approach involves expanding the suprachoroidal space (SCS) of the eye with an in situ-forming hydrogel injected using a microneedle. This study tests the hypothesis that SCS expansion increases the drainage of aqueous humor from the eye via the unconventional pathway, which thereby lowers IOP. SCS injection of a commercial hyaluronic acid (HA) hydrogel reduces the IOP of normotensive rabbits for more than 1 month and an optimized HA hydrogel formulation enables IOP reduction for 4 months. Safety assessment by clinical ophthalmic examinations indicate the treatment is well tolerated. Histopathology shows minor hemorrhage and fibrosis at the site of injection. Further analysis by ultrasound biomicroscopy demonstrates a strong correlation of IOP reduction with SCS expansion. Outflow facility measurements show no difference in pressure-dependent outflow by the conventional pathway between treated and untreated eyes, supporting the hypothesis. In conclusion, SCS expansion with an in situ-forming hydrogel can enable extended IOP reduction for treating ocular hypertension and glaucoma without drugs or surgery.

Modern aqueous shunt implantation: future challenges - Barton, K; Heuer, DK (GLAUCOMA: AN OPEN WINDOW TO NEURODEGENERATION AND NEUROPROTECTION, 2008)
The aqueous shunts that are currently available are based on the principles of the Molteno implant, i.e., a permanent sclerostomy, routing of aqueous to the equatorial subconjunctival space, and an end plate to prevent obstruction, and also to determine the surface area for absorption. While the Ahmed Glaucoma Valve appears to have improved the predictability of early intraocular pressure (IOP) control, the Baerveldt Glaucoma Implant has a tendency towards a lower rate of long-term excessive encapsulation. As a result of improvements in predictability, shunts are used more widely. Because of these positive factors, and ongoing concerns regarding the bleb-related problems associated with mitomycin C trabeculectomy, there is an increasing interest in the use of shunts as primary surgical management for primary glaucoma. At present, the main barrier to wider use of shunts in less-complicated glaucomas will probably be the unknown long-term effect on corneal endothelium, an issue that has not yet been properly addressed.

The Effect of Health Education Video on Ocular Massage After Trabeculectomy - Liu, H; Lv, YJ; Zhao, JS; Cao, W (CIN-COMPUTERS INFORMATICS NURSING, 2014)
The aim of this study was to investigate the effect of different ocular massage health education methods on ocular massage in glaucoma patients after trabeculectomy. Eighty-six patients with glaucoma after trabeculectomy (86 eyes) were randomly divided into two health education groups. One group was a watch video group (43 patients, 43 eyes), while the other was an orally taught health education group (43 patients, 43 eyes). Patients were followed up for 1 week, 1 month, and 3, 6, and 12 months after discharge. Records of the patient responses after health education, compliance of patients with follow-up, and intraocular pressure were determined. Measurements included intraocular pressure and differences between the watch video and orally taught health education groups. The differences between the watch video group and orally taught health education group were not statistically significant at 1 week and 1 month, while the differences were statistically significant at 3, 6, and 12 months. The results indicated that health education videos can enable glaucoma patients to have a better mastery of ocular massage after trabeculectomy. According to the needs of patients, health education video use produced good results and should be promoted.

The course of glaucoma during pregnancy - A retrospective case series - Brauner, SC; Chen, TC; Hutchinson, T; Chang, MA; Pasquale, LR; Grosskreutz, CL (ARCHIVES OF OPHTHALMOLOGY, 2006)
Objective: To better understand the course of glaucoma during pregnancy in women with preexisting disease. Methods: Retrospective case series of 28 eyes of 15 women with glaucoma followed up during pregnancy. Data were analyzed for age, race/ethnicity, medications, glaucoma type, intraocular pressure (IOP), and visual fields before, during, and after pregnancy. Results: In 16 (57.1%) of 28 eyes, IOP was stable during pregnancy, with no progression of visual field loss. In 5 eyes (17.9%), visual field loss progressed during pregnancy, while IOP remained stable or increased. In 5 eyes (17.9%), IOP increased during pregnancy, but there was no progression of visual field loss. In 2 eyes (7.1%), data were inconclusive because of medication noncompliance and preexisting severe visual field loss. Glaucoma medications were used by 13 of 15 patients to control glaucoma during pregnancy. The classes of medications used most frequently were beta-blockers, alpha(2)-adrenergic agents, cholinergic agents, and topical carbonic anhydrase inhibitors. Conclusions: The course of glaucoma during pregnancy is variable, and women must be monitored closely during pregnancy. Medications may be necessary to control IOP and to prevent vision loss during pregnancy.

Evolution of Glaucoma Surgery in the Last 25 Years - Bar-David, L; Blumenthal, EZ (RAMBAM MAIMONIDES MEDICAL JOURNAL, 2018)
Glaucoma is a chronic neurodegenerative optic nerve disease. Treatment is intended to prevent the development and progression of optic nerve damage by lowering intraocular pressure (IOP). Current therapy options include topical/systemic drugs that increase aqueous humor outflow or decrease its production, laser therapy that targets the trabecular meshwork and ciliary body, and incisional surgery. Trabeculectomy as well as glaucoma drainage devices are often performed, given their high efficacy in lowering IOP. However, the significant risk profile with potential sight-threatening complications has motivated glaucoma experts to create alternative surgeries to treat glaucoma. Minimally invasive glaucoma surgery (MIGS) is defined by: micro-invasive approach, minimal tissue trauma, high safety profile, and rapid recovery. The new devices might promote an earlier transition from medical/laser therapy to surgery, and therefore decrease the side effects associated with long-term use of topical medications as well as deal with the limited adherence of patients to their regimens. This review presents the surgical options available for glaucoma patients and their evolution over the past 25 years.

Decreasing Avoidable Vision Loss: Identifying Antecedents of Adherence - Morse, AR; Seiple, WH (CLINICAL OPHTHALMOLOGY, 2020)
Adherence to medication treatment protocols and active participation by individuals in their medical care are important for all patients, but especially for those with chronic conditions such as vision loss. Adherence is crucial for decreasing avoidable vision loss. Failure to take medications as prescribed and keep scheduled appointments reduces treatment effectiveness, increases complications and results in poorer outcomes. Reasons for nonadherence vary by diagnosis and include not understanding the importance of adherence, low health literacy, lack of adequate self-efficacy, low level of activation and behavioral issues including depression. Patients may lack information about their condition and its prognosis, available treatment alternatives, and other essential information such as how to monitor their eye condition, what to do if vision deteriorates and how to get needed community-based help. Each of these factors impedes patients' ability to engage with their physician and participate in their own care. The ability of individuals with vision loss to actively and effectively manage their health care, ie, activation, has been understudied. When patients are involved with their own care, their care experience, and most importantly, their outcomes, are improved. Identifying antecedents of adherence may help provide disease- and patient-specific pathways to reduce avoidable vision loss.

Medical management of glaucoma: Principles and practice - Singh, K; Shrivastava, A (INDIAN JOURNAL OF OPHTHALMOLOGY, 2011)
Glaucoma care is more an art than science. The introduction of several new classes of glaucoma medications and the completion of many large randomized clinical trials have not changed this fact. While we now have better choices when initiating glaucoma therapy relative to our predecessors, the principles of glaucoma therapy have not changed much during this period. Debates continue regarding the utility of concepts such as "the monocular therapeutic trial," "target intraocular pressure (IOP)," and "maximal medical therapy." Our tools for detecting and following glaucomatous disease have improved but are not precise enough for us to prospectively predict which patients will do better or worse than others. Much attention has been given to disease stage, rate of progression, and compliance with medications but regular patient follow-up, an area that has received little attention, may be among the most important predictors of patient outcomes.

Interventions for improving adherence to ocular hypotensive therapy - Gray, TA; Orton, LC; Henson, D; Harper, R; Waterman, H (COCHRANE DATABASE OF SYSTEMATIC REVIEWS, 2009)
Background Poor adherence to therapy is a significant healthcare issue, particularly in patients with chronic disease such as open angle glaucoma. Treatment failure may necessitate unwarranted changes of medications, increased healthcare expenditure and risk to the patient if surgical intervention is required. Simplifying eye drop regimes, providing adequate information and ongoing support according to patient need, may have a positive effect on improving adherence. Objectives To summarise the effects of interventions for improving adherence to ocular hypotensive therapy in people with ocular hypertension (OHT) or glaucoma. Search strategy We searched CENTRAL, MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, ZETOC and OpenSIGLE. In addition, we searched research registers of ongoing studies. We contacted pharmaceutical manufacturers to request unpublished data and searched conference proceedings for the Association for Research in Vision and Ophthalmology (ARVO), and the Annual Congress for the Royal College of Ophthalmologists (RCO). There were no language or date restrictions in the search for trials. The electronic databases were last searched on 15 January 2009. Selection criteria We included randomised controlled trials (RCTs) and quasi RCTs that compared interventions to improve adherence to ocular hypotensive therapy for patients with OHT or glaucoma. Data collection and analysis At least two authors independently assessed the search results for eligibility and extracted data for included trials onto specifically designed forms. We calculated the mean difference for continuous data and relative risks for dichotomous data. Where appropriate, we pooled data using a fixed-effect model. Main results Eight trials met the inclusion criteria. There was considerable heterogeneity of interventions and reported outcome measures and therefore, meta-analysis was limited to two studies. Overall, studies were not of high quality due to small sample sizes, missing data and short term follow-up. Three of five drug comparison studies provided evidence that reducing the frequency of drops can improve adherence. However, the study that compared the least frequent regime with one of the most complicated, showed no difference in reported adherence. A small study of thirteen patients found a reminder device beneficial to adherence levels yet only one of two studies involving education and individualised care planning was found to be successful. Authors' conclusions Interventions involving simplified dosing regimes, reminder devices, education and individualised care planning, did show improvements in adherence rates. However, due to inadequate methodological quality and heterogeneity of study design we are unable to advocate any particular interventions at this time.

Post-operative rehabilitation of functional amblyopia in primary infantile glaucoma: 11 year-follow-up - Boulze-Pankert, M; Zanin, E; Matonti, F; Benso, C; Toesca, E; Denis, D (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2012)
Purpose. - To evaluate the efficacy of functional amblyopia treatment in children having undergone surgery for primary infantile glaucoma. Patients and method. - Parameters studied included: age at surgery, current age, visual acuity (VA) (initial and most recent acuity), refraction, alignment, adherence to amblyopia treatment, condition of the cornea (Haab striae, stromal scarring, pachymetry, cell count), condition of the optic disc (cupping, RNFL OCT) and intraocular pressure. Pearson's p-value was fixed at 5%. Results. - Retrospective study of 29 eyes; average age at surgery was four months, mean follow-up was 11.2 years. Initial VA averaged 4.5 over 10, most recent VA 7 over 10, i.e. a gain of 2.3 over 10. Refraction revealed 37.9% myopia, 10.3% emmetropia, 48.2% hyperopia and an average astigmatism of 2.14 D. A negative correlation was found between astigmatism and most recent VA (rho = -0.7; P < 0.001). A positive correlation was found between the quality of the occlusion therapy and the recovery of VA with a gain of 3.2 over 10 (P = 0.001). A strong positive correlation was found between the cylinder power and the number of Haab striae [rho 0.702, P < 0.0001]; final VA is best when the striae show no organized scar formation (P = 0.04). Conclusion. - This study underlines the necessity of prolonged treatment of functional amblyopia in primary infantile glaucoma for the best possible visual rehabilitation. (C) 2012 Elsevier Masson SAS. All rights reserved.

Glaucoma patient-provider communication about vision quality-of-life - Sleath, B; Sayner, R; Vitko, M; Carpenter, DM; Blalock, SJ; Muir, KW; Giangiacomo, AL; Hartnett, ME; Robin, AL (PATIENT EDUCATION AND COUNSELING, 2017)
Objective: The purpose of this study was to: (a) describe the extent to which ophthalmologists and glaucoma patients discuss vision quality-of-life during office visits, and (b) examine the association between patient and ophthalmologist characteristics and provider-patient communication about vision quality-of-life. Methods: Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited at six ophthalmology clinics. Patients' visits were video-tape recorded and quality-of-life communication variables were coded. Generalized estimating equations were used to analyze the data. Results: Two hundred and seventy-nine patients participated. Specific glaucoma quality-of-life domains were discussed during only 13% of visits. Older patients were significantly more likely to discuss one or more vision quality-of-life domains than younger patients. African American patients were significantly less likely to make statements about their vision quality-of-life and providers were less likely to ask them one or more vision quality-of-life questions than non-African American patients. Conclusion: Eye care providers and patients infrequently discussed the patient's vision quality-of-life during glaucoma visits. African American patients were less likely to communicate about vision quality-of-life than non-African American patients. Practice implications: Eye care providers should make sure to discuss vision quality-of-life with glaucoma patients. (C) 2016 Elsevier Ireland Ltd. All rights reserved.

Referral to Low Vision Services for Glaucoma Patients: Referral Criteria and Barriers - Kaleem, MA; West, SK; Im, L; Swenor, BK (JOURNAL OF GLAUCOMA, 2018)
Purpose:To determine what criteria are being used by glaucoma specialists to refer patients to low vision services (LVS) and to identify potential barriers to LVS referral.Methods:A survey was emailed to members of the American Glaucoma Society (AGS). The number and percentage of responses to each survey question were examined.Results:Reported criteria for referral included difficulty performing activities related to vision (78%), degree of visual field loss (63%), and difficulty with orientation and mobility (27%). Reported barriers to LVS referral included patients not expressing difficulty with activities related to vision (34%), not having enough time to counsel patients during clinic visits (32%), and perceiving that patients would not be able to afford LVS even if they were referred (31%).Conclusions:Among glaucoma specialists, patient-reported difficulties with vision-related activities were the most common criteria used for LVS referral. Reported barriers to LVS referral, including perceived patient economic restraints and insufficient time to counsel patients during clinic visits, need to be addressed through appropriate interventions.

A longitudinal observation of a patient with normal tension glaucoma - Sithole, HL (AFRICAN VISION AND EYE HEALTH JOURNAL, 2017)
Normal tension glaucoma (NTG) is a disease associated with normal intraocular pressure (10 mmHg - 21 mmHg) that may lead to irreversible blindness if misdiagnosed or left untreated over a period of time. The author observed a patient with NTG over a period of 5 years (from 2013 to 2017). The initial visual field analysis results (2014) showed mild visual field defects because of NTG at the start of the 5-year period. Although the patient was also diagnosed with hydrocephalus, a condition associated with optic nerve head damage, following years of noncompliance to treatment of NTG and follow-up eye examination schedules, the patient's visual field defects were found to have progressed by the year 2017. It is therefore important for optometrists to apply due diligence when examining patients with NTG in order to expedite intervention and prevention of visual impairment and blindness.

Risk Factors for Poor Adherence to Eyedrops in Electronically Monitored Patients with Glaucoma - Friedman, DS; Okeke, CO; Jampel, HD; Ying, GS; Plyler, RJ; Jiang, YZ; Quigley, HA (OPHTHALMOLOGY, 2009)
Purpose: To identify risk factors for poor adherence to topical once daily therapy for glaucoma. Design: Prospective, observational cohort study. Participants: A total of 196 patients with glaucoma who were being treated with a prostaglandin analog in 1 or more eyes at the Scheie or Wilmer Eye Institutes between August 2006 and June 2007. Methods: Demographics, ocular history, and responses to interview questions about glaucoma knowledge, health beliefs, and drop-taking behaviors were obtained from each patient. All patients used the Travatan Dosing Aid (DA; Alcon Laboratories Inc., Fort Worth, TX) to administer travoprost as prescribed. Devices were collected at 3 months, and the data of drop use were downloaded using software provided with the DA. Patients taking <= 75% doses during the 8-week period starting 2 weeks after the enrollment visit and ending 2 weeks before the 3-month visit were compared with those taking >75% of doses. Main Outcome Measures: Risk factors for poor adherence. Results: Eighty-seven patients (44.4% of the 196 subjects with evaluable data at 3 months) used the DA on 75% or less of the monitored days. In univariate analysis, poorer adherers were more likely to be <50 or a >= 80 years of age, to be African American, to report less than excellent health, to report higher amounts of depression, to have lower income, and to be treated at the Scheie Eye Institute. Multivariate analysis (adjusting for education and income) found that age, race/ethnicity, and less than excellent health were associated with poor adherence. Conclusions: Those who failed to take more than 75% of eyedrop doses were more likely to be African American and to report poor health. Those in the youngest and oldest age groups were less adherent, although this finding was not always statistically significant. Further research into the factors driving these associations and into developing predictive models to assist in screening for low adherence are warranted. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references. Ophthalmology 2009; 116:1097-1105 (C) 2009 by the American Academy of Ophthalmology.

Ahmed Valve, Suture-less Implantation: A New Approach to an Easier Technique - Garcia-Delpech, S; Sanz-Marco, E; Martinez-Castillo, S; Lopez-Prats, MJ; Udaondo, P; Salom, D; Diaz-Llopis, M (JOURNAL OF GLAUCOMA, 2013)
Purpose:Tissue adhesives have been used in ophthalmology instead of sutures to minimize the operating time. This case series investigated the effectiveness and safety of use of cyanoacrylate in Ahmed valve implantation through pars plana for refractory glaucoma.Patients and Methods:Seventeen eyes of 17 patients with refractory glaucoma underwent Ahmed valve scleral suture-less implantation through pars plana with a cyanoacrylate suture of the plate. Refractory glaucoma was defined as intraocular pressure (IOP) 21 mm Hg with antiglaucoma eye drops, good adherence to treatment, and no previous glaucoma surgery. IOP control and development of complications were evaluated during the follow-up (mean follow-up, 13.23 mo, 6 to 28 mo).Results:IOP control, defined as IOP21 mm Hg with or without antiglaucoma eye drops, was achieved in 82.2% of patients, and 58.8% were able to eliminate antiglaucoma eye drops. Mean surgical time was 9.762.60 and 6 +/- 0.81 minutes in patients with previous vitrectomy (4 cases). Postoperative complications included transiently increased IOP, transient hyphema, early postoperative hypotony (4 cases), and tube block by the vitreous (2 cases): 1 resolved by Nd:YAG and the other by second vitrectomy. No cases of tube or plate extrusion, plate migration, choroidal or retinal detachment, or vitreous hemorrhage were observed.Conclusions:These results are promising and demonstrate a safe and effective alternative to the traditional scleral suture. Our data suggest that Ahmed valve implantation through pars plana with cyanoacrylate is a safe and effective method for refractory glaucoma. Further studies are needed to confirm our observation.

Adherence With the Use of Target Intraocular Pressure for Glaucoma Patients in a Large University Practice - Solano-Moncada, F; Dymerska, M; Jefferys, JL; Quigley, HA (JOURNAL OF GLAUCOMA, 2016)
Purpose: To determine how often glaucoma specialists set a target intraocular pressure (IOP) and how they respond when the target is not achieved. Methods: We reviewed 250 randomly selected charts of glaucoma patients seen by 5 glaucoma specialists to identify whether a target IOP was specifically set and to detail the plan of action when the target was exceeded. Results: A target IOP was present for at least 1 eye in 66% of patients (165/250). Among the patients of 5 physicians, the percentage with a target IOP for both eyes ranged from 90% to 34%. Half of eyes with no target had an explaining feature, whereas the other half did not. The study visit IOP exceeded the target in at least 1 eye in 29% (50/173) of patients. When the target was not met, 66% (33/50) had a notation of action taken, with no significant difference among physicians in whether any action was taken (P = 0.64). The significant differences among the 5 physicians in the use of target IOP were potentially associated with patient demographic and clinical features, such as age, race, treatment intensity, and visual field damage, which differed among the 5 practices (all P < 0.05). Conclusions: Target IOP was recorded in the large majority of patient charts, but its use varied by physician and patient characteristics. On nearly one third of visits, IOP exceeded the target, indicating the need for active decision-making and management changes.

Postoperative Trendelenburg Position for Graft Adherence After Descemet Stripping Automated Endothelial Keratoplasty - Belkin, A; Nesher, R; Segev, F (CORNEA, 2013)
Purpose:To present a case of repeated graft dislocation after Descemet stripping automated endothelial keratoplasty (DSAEK) in a post-trabeculectomy eye and to suggest a simple postoperative maneuver to minimize this occurrence.Methods:A 61-year-old woman presented to our cornea clinic with pseudophakic bullous keratopathy in her left eye 13 years after a trabeculectomy had been performed. After the DSAEK was performed, repeated graft dislocations were observed. When air was seen in the filtering bleb in the immediate postoperative period, it was assumed that it had escaped from the air bubble remaining in the anterior chamber at the end of the surgery. The patient was thus placed in the Trendelenburg position immediately after performing a rebubbling procedure to retain the air bubble in the anterior chamber and away from the filtering bleb.Results:The corneal graft remained centered and clear at postoperative day 1 and remained so at the last follow-up visit 8 months after the surgery had taken place. The patient's intraocular pressure was well controlled with a functional filtering bleb.Conclusions:Postoperative Trendelenburg positioning is an easily applied maneuver that may promote graft adherence after performing a DSAEK in eyes that have undergone glaucoma surgery.

Illness perceptions in people newly diagnosed with glaucoma and ocular hypertension - McDonald, L; Boodhna, T; Ajtony, C; Turnbull, P; Bourne, RRA; Crabb, DP (BRITISH JOURNAL OF OPHTHALMOLOGY, 2020)
Background/aims To determine whether self-reported illness perceptions in newly diagnosed patients with primary open-angle glaucoma (POAG) and ocular hypertension (OHT) are more negative compared with peers who have lived with their diagnosis for more than 2 years. Methods A cross-sectional study of 58 newly diagnosed patients with POAG and OHT recruited at their first clinic visit. Electronic patient records were used to identify similar patients (n=58, related by age and severity of visual field loss) who had their diagnosis for >2 years. All participants completed the Brief Illness Perception Questionnaire (BIPQ), EQ5D general health measure and Type D Personality Scale (DS14). Results Average BIPQ scores were similar for people newly diagnosed with POAG and POAG diagnosed >2 years and were no different to newly diagnosed OHT and OHT diagnosed >2 years POAG (p=0.46). An analysis correcting for personality type (DS14) and general health (EQ5D) indicated newly diagnosed patients with POAG to have marginally better illness perceptions on individual BIPQ items quantifying impact on life in general, experience of symptoms and 'understanding' of their condition (all p<0.01). In contrast, patients with POAG with a diagnosis >2 years understood better their condition to be long-term (p<0.01). Conclusions Some illness perceptions differed between newly diagnosed people and patients living with their diagnosis for >2 years. Illness perception for people with manifest glaucoma and at risk of glaucoma (OHT) were similar; the latter might benefit from an intervention at diagnosis that highlights the better prognosis for OHT compared with POAG.

Longitudinal rates of annual eye examinations of persons with diabetes and chronic eye diseases - Lee, PP; Feldman, ZW; Ostermann, J; Brown, DS; Sloan, FA (OPHTHALMOLOGY, 2003)
Objective: To assess the rate of annual eye examinations over time among older Americans with diabetes and chronic eye diseases. Design: Longitudinal analysis of Medicare claims data. Participants: Random sample of Medicare beneficiaries aged 65 years or older. Methods: Beneficiaries were followed between 1991 and 1999, unless mortality or enrollment in a health maintenance organization for > 6 months in a given 12-month period intervened. All claims data (both physician and facility) during this time were analyzed for the presence of International Classification of Diseases 9 codes consistent with 1 of the 3 study conditions and the performance of eye examinations. Main Outcome Measures. Claims submitted by optometrists, ophthalmologists, or other providers of eye care for subjects with diabetes, glaucoma, or age-related macular degeneration (ARMD). Rates were calculated on the basis of a 15-month time window for annual examinations rather than for 12 months to allow for less than full compliance with the guidelines for various reasons (e.g., bad weather). Results: Among those with diabetes in this population, 50% to 60% had annual eye examinations in a 15-month period. Of those followed for at least 75 months after diagnosis, about three quarters had one or more 15-month gaps between visits. For subjects diagnosed with glaucoma, most visit rates were in the 70% to 90% range per 15-month period. The percentage of subjects with at least one 15-month period with no visits was considerably lower than for diabetes. The patterns for those with ARMD were in between those for diabetes and glaucoma. Over a nine-year period, only slightly over half of persons with at least one of the study conditions complied with practice guidelines. Conclusions: Annual eye examinations for persons diagnosed with diabetes, glaucoma, and ARMD are important for detecting potentially treatable vision loss among those already diagnosed with these conditions. Currently, actual rates of eye examinations for persons diagnosed with the study conditions fall far short of recommended rates. As such, approaches to enhancing longitudinal follow-up of those already in the eye care system are needed. (C) 2003 by the American Academy of Ophthalmology.

A combined analysis of four observational studies evaluating the intraocular pressure-lowering ability and tolerability of bimatoprost 0.01% in patients with primary open-angle glaucoma or ocular hypertension - Stevens, A; Iliev, ME; de Jong, L; Grobeiu, I; Hommer, A (CLINICAL OPHTHALMOLOGY, 2016)
Objective: Combine and evaluate data from four clinical practice studies investigating the intraocular pressure (IOP)-lowering ability, tolerability of and patient adherence to bimatoprost 0.01% therapy in patients with primary open-angle glaucoma or ocular hypertension. Methods: Data were combined from four multicenter, prospective, observational studies. Patients (n=2,593) were recruited from 328 sites in Austria, Belgium, Switzerland, and the Netherlands. Assessments were at study entry (baseline) and after 10-14 weeks. Results: Bimatoprost 0.01% lowered mean IOP by 5.0 mmHg from baseline to final visit (P<0.0001). Individual IOP goals were achieved in 75.5% of patients. Results were similar in right and left eyes; right-eye data are presented here for brevity. The greatest mean IOP reduction was 6.7 +/- 4.7 mmHg (28.8% reduction from baseline to final visit, P<0.0001) in treatment-naive patients. Switching to bimatoprost 0.01% monotherapy from previous monotherapy reduced mean IOP by a further 3.2 +/- 3.6 mmHg (17.2%, P<0.0001). Switching to bimatoprost 0.01% from previous prostaglandin monotherapy reduced mean IOP by 2.9 +/- 3.5 mmHg (15.5%), including by 3.1 +/- 3.4 mmHg (15.8%) and 3.3 +/- 4.1 mmHg (16.9%) for previous latanoprost and travoprost treatment, respectively (all P<0.0001). IOP reduction in patients previously treated with a fixed combination was 2.7 +/- 4.0 mmHg (14.2%, P<0.0001). The most commonly reported adverse events were conjunctival hyperemia (5.2%) and eye irritation (4.7%). Tolerability was rated as "very good" or "good" by 90.1% of patients. Adherence was rated by physicians as "better than" or "equal to" previous treatment in 97.2% of patients. Conclusion: The combined studies demonstrated in a clinical practice setting, bimatoprost 0.01% lowered IOP effectively in treatment-naive and previously treated ocular hypertension and primary open-angle glaucoma patients, and was associated with good tolerability and patient adherence over 12 weeks.

Programs to optimize adherence in glaucoma - Kowing, D; Messer, D; Slagle, S; Wasik, A; V-POAG Study Grp (OPTOMETRY-JOURNAL OF THE AMERICAN OPTOMETRIC ASSOCIATION, 2010)
PURPOSE: This study was designed to raise awareness of the materials, devices, and Internet resources available to improve adherence to use of medications for the treatment of glaucoma and to review new devices under development. METHODS: A review of current indexed literature and Internet resources was conducted. RESULTS: A variety of educational brochures, pamphlets, and fact sheets promoting adherence to ocular hypotensive medications are available through multiple organizations and are easily accessed and ordered on the Internet. Video and Web-based patient educational tools have been designed to support patient adherence to glaucoma management plans and promote open dialogue between patients and providers. Reminder and recall systems that integrate with office software can be sent to cell phones as well as e-mails and personal digital assistant (PDAs), alerting patients to upcoming appointments and reminding them to instill their drops. Bottle devices with dosing support (timers with audible and visual signals and dispensing aids) and electronic monitoring have been shown to promote adherence. New products currently under development to improve the delivery of medications include nanoparticles, punctal plugs, and contact lenses that release glaucoma medications. CONCLUSIONS: Many educational materials, services, Internet resources, and devices are available to optometrists to encourage patient adherence to glaucoma treatment and management. Optometry 2010;81:339-350

Changing Initial Glaucoma Medical Therapy Increases Healthcare Resource Utilization - Trese, MGJ; Lewis, AW; Blachley, TS; Stein, JD; Moroi, SE (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2017)
Purpose: To determine the frequency and economic impact of changing initial glaucoma therapy for patients with newly diagnosed open-angle glaucoma (OAG) or ocular hypertension (OHT). Methods: This retrospective longitudinal cohort study identified individuals within a large managed care network in the United States, who were newly diagnosed with OAG or OHT from 2001 to 2012 and were prescribed either a topical beta blocker (BB) or a prostaglandin analog (PGA). Claims data were analyzed over the 12-month period following their index prescription to determine physician prescribing habits, healthcare resource utilization patterns, and sociodemographic factors which may have contributed to changing the initial treatment strategy. Results: A total of 15,019 beneficiaries were identified with newly diagnosed OAG or OHT and whose index therapy was either a topical BB or PGA. Among these enrollees 80.9% were started on PGAs, while 19.1% were started on BBs. Of these beneficiaries, 29.2% of those started on PGAs and 39.5% of those started on BBs underwent a change in therapy within 12 months of their index prescription. Those in the topical BB treatment group had a 38% increased odds of changing glaucoma therapy relative to those started on PGAs (odds ratio [OR] 0.61, 95% CI:0.56-0.68). Patients who changed therapy required more frequent office visits (P<0.0001) and incurred higher median eye care related charges (P<0.0001) compared to those who remained on the index therapy unchanged. Conclusions: Changing initial ocular hypotensive therapy is common. Individuals who undergo a change in therapy required more frequent face-to-face monitoring and incurred higher healthcare related costs. Identifying strategies capable of optimizing the process of initiating ocular hypotensive therapy are appealing and possess the potential to improve patient outcomes and reduce healthcare costs.

Tele-glaucoma versus clinical evaluation: The New Jersey Health Foundation Prospective Clinical Study - Chandrasekaran, S; Kass, W; Thangamathesvaran, L; Mendez, N; Khouri, P; Szirth, BC; Khouri, AS (JOURNAL OF TELEMEDICINE AND TELECARE, 2020)
Introduction Glaucoma, the second most common cause of blindness, is normally detected in clinic. With technological improvements, tele-glaucoma exams can identify these changes off-site. The quality of tele-glaucoma exams needs to be compared with that of traditional exams. This study's purpose was to validate the tele-glaucoma programme, which allows a physician comprehensive access to patients' data, by comparing results to clinical examinations. Methods A prospective study of 107 subjects evaluated in clinic and then tele-glaucoma stations, which consisted of non-mydriatic fundus photography, puff-tonometry, auto-refraction and Optical Coherence Tomography (OCT). The OCT captured central corneal thickness, angle anatomy, cup-to-disc ratio (CDR), retinal nerve fibre layer distribution and posterior-pole ganglion cell complex data. Results Intraocular pressure (IOP) comparisons between clinical and tele-glaucoma exams had strong positive Pearson correlation coefficients (0.8248 OD, 0.8672 OS). Strong positive correlations were seen for CDR (0.7835 OD, 0.8082 OS) as well as diagnosis (glaucoma, no glaucoma or glaucoma suspect). A moderate positive correlation was seen for return to clinic time (RTC). Tele-glaucoma had an average lower RTC (2.7 vs 3.9 months). Tele-glaucoma was more likely to elicit a non-glaucomatous diagnosis not found in clinic vs a diagnosis found only in clinic (18% vs 5% of subjects). Discussion Tele-glaucoma allows for detecting glaucoma remotely. These advancements alleviate patient difficulties with obtaining adequate glaucoma screenings and helps ophthalmologists triage patients with more severe pathology. Our study indicates that our tele-glaucoma protocol is comparable to a clinical exam in its ability to detect glaucoma. Further studies will be needed for off-site testing and transferring data separately for analysis.

One-year outcomes following implantation of second-generation trabecular micro-bypass stents in conjunction with cataract surgery for various types of glaucoma or ocular hypertension: multicenter, multi-surgeon study - Clement, CI; Howes, F; Ioannidis, AS; Shiu, M; Manninge, D (CLINICAL OPHTHALMOLOGY, 2019)
Purpose: To assess the utility and safety of implanting two second-generation trabecular micro-bypass stents following cataract surgery in eyes with mild to advanced glaucoma or ocular hypertension (OHT). Patients and methods: Retrospective study of iStent (R) inject trabecular micro-bypass implantation with cataract surgery by five surgeons at five sites in Australia. Eyes had mild to advanced glaucoma (predominantly primary open-angle, appositional angle-closure, or pseudoexfoliative glaucoma) or OHT and cataract requiring surgery. Effectiveness measures included intraocular pressure (IOP); medication burden; and proportions of eyes with no medications, >= 2 medications, stable or decreased medications vs preoperative, and IOP <= 18 mmHg. Safety measures included visual acuity, cup-to-disc ratio (CDR), visual field (VF), complications, adverse events, and secondary surgical interventions. Patients have been followed for 12 months, and follow-up is ongoing. Results: Of the 290 total eyes that underwent surgery, 165 eyes had 12-month outcomes at the time of data collection and are included in this report. In these eyes, mean Month 12 IOP reduced by 23.2% from 18.27 +/- 5.41 mmHg preoperatively to 14.04 +/- 2.98 mmHg (P<0.001), with 95.8% of eyes achieving Month 12 IOP of <= 18 mmHg vs 60.6% preoperatively. Mean number of medications at 12 months decreased by 71.5%, 0.47 +/- 0.95 vs 1.65 +/- 1.28 preoperatively; 76.4% of eyes were on zero medications vs 17.6% preoperatively (P<0.001); 14.5% of eyes were on >2 medications vs 46.7% preoperatively (P<0.001); and 98.2% of eyes maintained or reduced medications vs their preoperative regimen. Favorable safety included no stent-related intraoperative complications; limited and transient postoperative adverse events; and stable CDR, VF, and visual acuity. Three eyes with more advanced disease underwent additional glaucoma surgeries. Conclusion: iStent inject implantation with cataract surgery significantly and safely reduced medications and IOP in eyes with various types and severities of glaucoma within a multicenter, multi-provider, real-life setting.

Treatment Outcomes in the Primary Tube Versus Trabeculectomy Study after 1 Year of Follow-up - Gedde, SJ; Feuer, WJ; Shi, W; Lim, KS; Barton, K; Goyal, S; Ahmed, IIK; Brandt, J; Primary Tube Versus Trabeculectomy (OPHTHALMOLOGY, 2018)
Purpose: To report 1-year treatment outcomes in the Primary Tube Versus Trabeculectomy (PTVT) Study. Design: Multicenter, randomized clinical trial. Participants: Two hundred forty-two eyes of 242 patients with medically uncontrolled glaucoma and no previous incisional ocular surgery, including 125 in the tube group and 117 in the trabeculectomy group. Methods: Patients were enrolled at 16 clinical centers and assigned randomly to treatment with a tube shunt (350-mm(2) Baerveldt glaucoma implant) or trabeculectomy with mitomycin C (MMC; 0.4 mg/ml for 2 minutes). Main Outcome Measures: Intraocular pressure (IOP), glaucoma medical therapy, visual acuity, visual fields, surgical complications, and failure (IOP of more than 21 mmHg or reduced by less than 20% from baseline, IOP of 5 mmHg or less, reoperation for glaucoma, or loss of light perception vision). Results: The cumulative probability of failure during the first year of follow-up was 17.3% in the tube group and 7.9% in the trabeculectomy group (P = 0.01; hazard ratio, 2.59; 95% confidence interval, 1.20-5.60). Mean +/- standard deviation IOP was 13.8 +/- 4.1 mmHg in the tube group and 12.4 +/- 4.4 mmHg in the trabeculectomy group at 1 year (P = 0.01), and the number of glaucoma medications was 2.1 +/- 1.4 in the tube group and 0.9 +/- 1.4 in the trabeculectomy group (P < 0.001). Postoperative complications developed in 36 patients (29%) in the tube group and 48 patients (41%) in the trabeculectomy group (P = 0.06). Serious complications requiring reoperation or producing a loss of 2 Snellen lines or more occurred in 1 patient (1%) in the tube group and 8 patients (7%) in the trabeculectomy group (P = 0.03). Conclusions: Trabeculectomy with MMC had a higher surgical success rate than tube shunt implantation after 1 year in the PTVT Study. Lower IOP with use of fewer glaucoma medications was achieved after trabeculectomy with MMC compared with tube shunt surgery during the first year of follow-up. The frequency of serious complications producing vision loss or requiring reoperation was lower after tube shunt surgery relative to trabeculectomy with MMC. (C) 2018 by the American Academy of Ophthalmology

Risk of aphakic glaucoma after pars plana-lensectomy with and without removal of the peripheral lens capsule - Stech, M; Grundel, B; Daniel, M; Bohringer, D; Joachimsen, L; Gross, N; Wolf, C; Link, H; Gilles, U; Lagreze, WA (EYE, 2019)
Background The etiology of aphakic glaucoma is unclear. It has been suggested that remaining lens epithelium releases cytokines transducing trabecular meshwork cells. Therefore, we compared two cohorts of children undergoing lensectomy. In cohort 1, the entire lens including its capsule was removed, in cohort 2 the peripheral lens capsule was left intact, also to facilitate secondary intraocular lens implantation later on. Methods We included children with uni- or bilateral congenital cataract who underwent lensectomy during the first year of life with subsequent contact lenses fitting. Group 1 comprised 41 eyes, group 2 comprised 33 eyes. In group 1, the median age at surgery was 4.0 months in unilateral and 3.0 months in bilateral cases 1, in group 2, 8.1 months and 2.4 months, respectively. The mean follow-up was 12.8 years in group 1 and 9.3 years in group 2. All cases were analyzed for the prevalence of aphakic glaucoma, for visual acuity and for compliance in visual rehabilitation (contact lens/occlusion therapy). Results We found no significant difference in glaucoma prevalence between group 1 and group 2 (p = 0.68). The overall glaucoma rate was 26% after the mean follow-up of 11 years in both groups. In unilateral cases, the median visual acuity was logMAR 0.7 in both groups. In bilateral cases it was logMAR 0.4 in group 1 and logMAR 0.2 in group 2 (p = 0.05). Conclusions Leaving the peripheral lens capsule intact had no negative effect on the incidence of glaucoma and on resulting visual acuity.

The effect of a reminder short message service on the uptake of glaucoma screening by first-degree relatives of glaucoma patients: A randomized controlled trial - Salihu, DK; Adenuga, OO; Wade, PD (MIDDLE EAST AFRICAN JOURNAL OF OPHTHALMOLOGY, 2019)
PURPOSE: The purpose of this study was to determine the role of a reminder short message service (SMS) on the uptake of glaucoma screening by first-degree relatives (FDRs) of patients with primary open-angle glaucoma (POAG) in North-central Nigeria following a telephone invitation for screening. MATERIALS AND METHODS: A randomized controlled trial was conducted in the eye clinic of a tertiary hospital in Jos, North-central Nigeria. Two hundred FDRs of patients with POAG were invited through phone for free glaucoma screening and randomly allocated into two groups. The intervention group received a reminder SMS, whereas the control group did not receive a reminder. Those who failed to turn up for screening were contacted through phone to determine the reasons for their nonattendance. Chi-square test and bivariate analysis were used to compare attendance rate between the two groups. RESULTS: Sending a reminder SMS following a telephone invitation had no effect on the uptake of glaucoma screening. The response rate was lower in the phone call plus reminder SMS group (43.0% vs. 53.0%) though the difference was not statistically significant (P = 0.157). Competing needs such as work and lack of transport fare were the most common reasons given for not attending the screening. CONCLUSION: A reminder text message is not an effective tool for increasing the uptake of glaucoma screening in at-risk individuals in North-central Nigeria. Existing barriers to health care in the country need to be addressed before mobile phone technology can be effectively used in increasing the utilization of any free eye screening service.

Effect of heparin-surface-modified intraocular lenses on postoperative inflammation after phacoemulsification - A randomized trial in a United States patient population - Trocme, SD; Li, H; Heparin Surface Modified Lens Stu (OPHTHALMOLOGY, 2000)
Objective: To compare postoperative inflammation occurring with heparin-surface-modified (HSM) versus non-HSM polymethyl methacrylate intraocular lenses (IOLs) after phacoemulsification, Design: Randomized, double-masked, multicenter, parallel trial. Participants: A total of 367 patients, consisting of routine (n = 220), glaucoma (n = 58), and diabetes (n = 89) patients, from eight US medical centers. Methods: Patients were observed for 1 year after phacoemulsification and lens implantation (week 1, months 1, 3, 6, 12), Main Outcome Measures: Primary measures of postoperative inflammation defined as the presence of giant cells on the lens surface via specular micrography and cellular deposits via slit-lamp examination. Results: The cross-sectional analyses showed that consistently fewer routine patients with HSM lens implants had giant cells on the IOL than those with non-HSM lens implants across all follow-up visits. The statistical significance (P < 0.05) was observed at all visits except month 12 for routine patients. The diabetes patients also demonstrated the same giant cell difference, and the statistical significance was observed at all visits including month 12. A similar trend was also observed in the glaucoma patients, with statistical significance only at the 3-month visit. For cell deposits, significant differences in favor of the HSM lens.(P < .0.05). were observed at 3 months among routine and diabetes patients, and at 3 and 6 months among glaucoma patients. A longitudinal data analysis using the generalized estimating equation approach indicated statistically significant treatment effect of HSM lenses in reducing inflammation in all patients except for cellular deposits in diabetes patients, In all patient groups, sight-threatening complications were not reported either more frequently or with more severity than normally expected for patients who have undergone cataract extraction and IOL implantation. Conclusions: The present study, the only one to have used phacoemulsification in virtually all patients (211/220 [96%] routine, 57/58 [98%] glaucoma, and 84/89 [94%] diabetes) is the largest to evaluate and compare concurrently routine, glaucoma, and diabetes patients. It is also the first US patient population study to document that heparin surface modification reduces postoperative inflammatory responses, as measured by specular micrography and slit-lamp examination, especially in the early postoperative period. Ophthalmology 2000;107: 1031-1037 (C) 2000 by the American Academy of Ophthalmology.

Intravitreal Bevacizumab for Neovascular Glaucoma - Vasudev, D; Blair, MP; Galasso, J; Kapur, R; Vajaranant, T (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2009)
Purpose: To report 6-month and 1 year outcomes of eyes treated for neovascular glaucoma (NVG) with intravitreal bevacizumab injection and panretinal laser (PRP) compared to those receiving PRP alone. Design: retrospective, consecutive case series. Methods: Charts of patients with NVG from retinal ischemia and at least 6 months of follow-up were reviewed. Patients were treated with one injection of 1.25 mg intravitreal bevacizumab followed by PRP or with PRP alone. The primary outcome was the long-term angle anatomy. Secondary measures included intraocular pressure (IOP), visual acuity, patient compliance, and control of systemic diseases. Results: Fourteen eyes of 12 patients treated with bevacizumab and PRP and 15 eyes of 11 patients treated with PRP alone were included in the study. Mean sectors of open angle at baseline was 1.31 in the bevacizumab group and 1.47 in the retinal ablation group (P = 0.73). Mean sectors of open angle was 2.14 and 1.18 in the bevacizumab and retinal ablation groups, respectively (P < 0.05) at 6-month follow-up, and 2.27 and 1.18, respectively (P < 0.05) at 1-year follow-up. Mean baseline IOP was 32.3 mmHg (+/- 14.8) in the bevacizumab group and 31.8 mmHg (+/- 13) in the PRP group (P = 0.75). At 6-month follow-up, the mean IOP was 18.28 mmHg (+/- 10) in the bevacizumab group and 23.33 mmHg (+/- 14.6) in the PRP group (P = 0.05), and 19.12 mmHg (+/- 6.8) and 26.2 mmHg (+/- 18) (P = 0.1), respectively at 1-year follow-up. Nineteen patients were judged to be noncompliant, 10 had uncontrolled diabetes and 7 had uncontrolled hypertension. Conclusions: This study documents better long-term preservation of open angle and IOP control in eyes receiving bevacizumab along with PRP. We stress that NVG is still associated with poor visual acuity outcomes.

Facilitators and Barriers to Glaucoma Screening Identified by Key Stakeholders in Underserved Communities: A Community-engaged Research Approach - Ballouz, D; Cho, J; Woodward, MA; Elam, AR; Musch, DC; Zhang, J; Moroi, SE; Johnson, L; Cederna, J; Newman-Casey, PA (JOURNAL OF GLAUCOMA, 2021)
Precis: Community-engaged research (CER) enables researchers to identify community-specific barriers and facilitators to program implementation. Broadly applicable barriers to glaucoma care, such as Cost, Transportation, and Trust, and community-specific barriers, such as Language and Convenience/Access, were identified. Purpose: The aim was to identify the facilitators and barriers to implementing glaucoma screening programs in 2 community clinics. Methods: A concurrent mixed-methods process analysis using CER. Key stakeholders-including patients, providers, and staff members-from 2 community clinics were interviewed using a semistructured interview guide. Interviews had 2 parts: (1) asking patients about community-based facilitators and barriers to implementing glaucoma screening and care and (2) eliciting feedback about a personalized coaching program. The transcripts were coded using Grounded Theory. Number of participants and number of representative citations were counted per theme. The qualitative analysis was coded using Dedoose 8.3.17 (Los Angeles, CA). Results: Thematic saturation was reached after coding 12 interviews. 30 participants were interviewed, 13 from Hamilton Clinic (Flint, MI; 8 patients, 5 providers and staff members) and 17 from Hope Clinic (Ypsilanti, MI; 6 patients, 11 providers and staff members). The most commonly cited themes were: Priorities (98 citations, 30 participants), Knowledge (73, 26) Transportation (63, 26), Cost (60, 23), and Convenience/Access (63, 22). Broadly applicable barriers to glaucoma care, such as Cost, Transportation, and Trust were identified alongside community-specific barriers such as Language and Convenience/Access. Participants rated their likelihood to follow up with an ophthalmologist after participating in the personalized coaching program at a mean of 8.83 (on a scale of 1 to 10 with 10 being the most confident). Conclusions: CER enables researchers to identify community-specific barriers and facilitators, allowing more effective program implementation.

Outcomes of complex Descemet Stripping Endothelial Keratoplasty performed by cornea fellows - Daubert, J; O'Brien, TP; Adler, E; Spierer, O (BMC OPHTHALMOLOGY, 2018)
BackgroundA major obstacle that academic institutions face is the steep learning curve for cornea fellows initially learning to perform Descemet Stripping Endothelial Keratoplasty (DSEK). The purpose of this study is to evaluate the outcomes of complex DSEK performed by cornea fellow supervised by an attending surgeon at an academic institution.MethodsPatients who underwent a complex DSEK procedure performed by a cornea fellow during the years 2009-2013 were included. All the surgeries were supervised by the same cornea attending. All patients had a minimum follow-up of 6months. Charts were reviewed for demographic data, intraoperative and postoperative complications and clinical outcomes. Corneal graft survival was calculated using the Kaplan-Meier analysis.ResultsFifty-seven eyes of 55 patients (mean age 77.58.5years) were included in the study with a mean follow-up time of 16.4 +/- 15.6months. Previous graft failure, presence of a tube and history of trabeculectomy were the leading diagnoses to define the surgery as complex. No intraoperative complications occurred. In 21.1% of cases a corneal graft detachment was documented in the first postoperative day. Mean visual acuity improved from 1.06 LogMAR (20/230) preoperatively to 0.39 LogMAR (20/50, p<0.001) by the sixth postoperative month and to 0.52 LogMAR (20/65, p<0.001) at the last follow-up visit. Graft failure rate was 29.8%. Kaplan-Meier analysis found a 67.2% graft survival rate at 20months.Conclusions Complex DSEK can be performed successfully with an acceptable postoperative complication rate by cornea fellows during their training period when supervised by an experienced attending.

A Retrospective Comparison of Trabeculectomy, Baerveldt Glaucoma Implant, and Microinvasive Glaucoma Surgeries in a Three-Year Follow-Up - Nuzzi, R; Gremmo, G; Toja, F; Marolo, P (SEMINARS IN OPHTHALMOLOGY)
Purpose: This retrospective study aimed to evaluate the safety and efficacy of MIGS (Xen (R) and Cypass (R)) compared to trabeculectomy and Baerveldr implants. Patients and Methods: This single-center study included patients from the Ophthalmic Hospital of Turin between January 2015 and 2018. Efficacy was assessed based on the intraocular pressure and the number of medications necessary to control IOP at 1, 3, 6, 12, 24, and 36 months and the potential complications. Complete surgical success was defined as IOP <= 21 mmHg, with no medication or additional glaucoma surgery. Qualified success was defined as IOP <= 21 mmHg with the reintroduction of topical medications. Our third measure of success was a delta IOP reduction greater than 20% compared to baseline. Results: The delta IOP compared to the baseline was significant at every instance, except in the Xen (R) implant group. The average IOP distribution at different time points was significant, except at 1 and 12 months. The delta of the medication number compared to the baseline was significant at every instant. All three methods of success were analyzed using a Kaplan-Meier survival curve that identified a significant difference on the success rates of Xen (R)-trabeculectomy, Xen (R)-Baerveldt (R), and Cypass (R) Baerveldt (R). Conclusion: MIGS can reduce the number of medication classes, thus increasing patient compliance and reducing topical ocular toxicity and general costs. Trabeculectomy remains the most effective option but still presents a percentage of failures that might increase during follow-up.

Glaucoma, "the silent thief of sight": patients' perspectives and health seeking behaviour in Bauchi, northern Nigeria - Abdull, MM; Chandler, C; Gilbert, C (BMC OPHTHALMOLOGY, 2016)
Background: In Nigeria, glaucoma has a high prevalence and is the second cause of blindness among adults after cataract. People with glaucoma frequently present very late with advanced disease, and acceptance of and adherence to treatment is low. The purpose of the study was to explore how patients' understand and respond to glaucoma in order develop an intervention to improve adherence to treatment. Method: Hospital based qualitative study. Six focus group discussions were held with patients with advanced disease and who had either undergone glaucoma surgery, were receiving medical treatment, or had neither surgery nor medical treatment. Two traditional healers who treat eye conditions were interviewed. Audio files were transcribed, translated into English and recurring themes coded and categorized as the impact of vision loss, and understandings of the disease and its management. Results: Visual loss impacted significantly on the lives of people with glaucoma in many ways. Many heard the term "glaucoma" for the first time during the study. Local terms to describe the symptoms included Hawan jinin ido ("hypertension of the eye"). Patients sought treatment in pharmacies, or with traditional healers who had different interpretations of glaucoma and its treatment to biomedical understandings. Cost and forgetfulness were the main reasons for low adherence to treatment while fear was a reason for not accepting surgery. Lack of money and negative staff attitudes were reasons for low follow up. Conclusion: Halting the progression of glaucoma is possible with treatment but the condition will remain a "silent thief of sight" in West Africa unless awareness, uptake of services and adherence to treatment improve. Understanding how glaucoma is locally conceptualised, lived with and responded to by patients is essential to aid the design of interventions to prevent glaucoma blindness in Africa. Findings have been used to adapt a motivational interviewing intervention, which is being evaluated in a clinical trial.

Two-Year Multicenter Outcomes of iStent inject Trabecular Micro-Bypass Stents Combined with Phacoemulsification in Various Types of Glaucoma and Ocular Hypertension - Clement, C; Howes, F; Ioannidis, AS; Shiu, M; Manning, D; Lusthaus, J; Lim, R; Skalicky, SE; Goodwin, T (CLINICAL OPHTHALMOLOGY, 2020)
Purpose: This multicenter study evaluated 2-year effectiveness and safety following implantation of two second-generation trabecular micro-bypass stents (iStent inject (R)) with phacoemulsification. Materials and Methods: This was a retrospective study of iStent inject implantation with phacoemulsification by nine surgeons across Australia. Eyes had mild to advanced glaucoma (predominantly primary open-angle/POAG, appositional angle-closure/ACG, or normal-tension /NTG) or ocular hypertension (OHT), and cataract Evaluations included intraocular pressure (TOP); medications; proportions of eyes with 0 or >= 2 medications, reduced/stable medications versus preoperative, and TOP <= 15 mmHg; visual acuity; cup-to-disc ratio (CDR); visual fields (VF); adverse events; and secondary surgery. Results: A total of 340 eyes underwent surgery and had 24-month follow-up data. At 24 months, mean IOP decreased by 16% from 16.4 +/- 4.7 mmHg preoperatively to 13.7 +/- 3.1 mmHg (p<0.001), and 77% of eyes achieved IOP of <= 15 mmHg versus 49% preoperatively (p<0.001). Mean number of medications decreased by 67% to 0.49 +/- 0.95 versus 1.49 +/- 1.20 preoperatively (p<0.001), with 74% of eyes medication-free versus 25% preoperatively (p<0.001), and 14% of eyes on >= 2 medications versus 46% preoperatively (p<0.001). Medication burden was reduced or stable in 98% of eyes versus preoperative. Stratified analyses showed significant IOP and medication reductions across glaucoma subtypes (POAG, ACG, NTG, OHT): 13-22% for IOP (p<0.01 for all) and 62-100% for medication (p<0.001 for all). Favorable safety included few adverse events; stable CDR, VF, and visual acuity; and filtering surgery in only 8 eyes (2.4%) over 2 years. Conclusion: This 340-eye multicenter dataset provides robust evidence of the safety and efficacy of iStent inject implantation with phacoemulsification, with significant and sustained IOP and medication reductions through 2 years. Results were similarly favorable across glaucoma subtypes (including POAG, ACG, NTG, OHT) and were attained across various glaucoma severities, clinical sites, and surgeons, highlighting the real-world versatility and utility of this treatment modality.

Surgical removal of intraocular antibiotic ointment after routine cataract phacoemulsification - Wong, JG; Bank, A (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2006)
We report surgical removal of a droplet of intraocular chloramphenicol ointment in a 70-year-old man who had routine small-incision phacoemulsification. A spherical droplet of ointment adherent to the intraocular lens was noted 2 months postoperatively. The source was considered to be the immediate postoperative conjunctival fornix chloramphenicol ointment. Gonioscopy revealed tiny droplets adherent to the peripheral iris and angle. The droplet was surgically explanted using a minimally traumatic technique with a lens glide and ophthalmic viscosurgical device through an enlarged clear corneal incision and sent intact for laboratory biochemical analysis. The patient maintained good vision without evidence of uveitis or secondary glaucoma at I year of follow-up. This uncommon case also raises issues about the need for immediate postoperative antibiotic ointment for endophthalmitis prophylaxis and phacoemulsification thermal wound effects on the integrity of self-sealing clear corneal incisions.

European study of the efficacy of a cross-linked gel stent for the treatment of glaucoma - Fea, AM; Bron, AM; Economou, MA; Laffi, G; Martini, E; Figus, M; Oddone, F (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2020)
Purpose: To investigate the efficacy and safety of a cross-linked gel stent (XEN45) with or without cataract surgery in the treatment of glaucoma patients. Setting: Five university hospitals. Design: Prospective multicenter clinical trial. Methods: Patients with glaucoma inadequately controlled by treatment or poor compliance or intolerance to topical therapy were included. Patients were divided into those who had an implant only (Solo Group; phakic and pseudophakic patients) and those who had an implant combined with cataract surgery (Combo Group). Differences in mean intraocular pressure (IOP) and number of medications between the baseline preoperative visit and study end (12 months), and the rate of qualified and complete success, were evaluated. Results: The Solo Group comprised 115 glaucoma patients (43 phakic and 72 pseudophakic) and the Combo Group comprised 56 patients. Comparedwith baseline, mean IOP (23.9 +/- 7.6 to 15.5 +/- 3.9) and number of medications (3.0 +/- 1.1 to 0.5 +/- 1.0) decreased significantly at 12-month follow-up (P <.001 for both). A >20% and >30% reduction in IOP from baseline was achieved by 72.3% and 52.6% of patients, respectively. IOP at 1 week postoperatively was a predictor of success, and the needling rate was inversely correlated with early postoperative IOP. The number of preoperative medications and patient age were not significantly associated with failure. Conclusions: Insertion of a cross-linked gel stent alone or combined with phacoemulsification might be effective and safe in the treatment of open-angle glaucoma, with a substantial reduction in IOP and number of medications. Copyright (C) 2020 Published by Wolters Kluwer on behalf of ASCRS and ESCRS.

Intraocular pressure related to uveitis - Pleyer, U; Ruokonen, P; Heinz, C; Heiligenhaus, A (OPHTHALMOLOGE, 2008)
Glaucoma, a common and potentially devastating complication of intraocular inflammation, remains a considerable therapeutic challenge. During uveitis, breakdown of the blood-ocular barrier occurs with subsequent influx of proteins as well as inflammatory and immunocompetent cells. These mediators, including cytokines and chemokines, are considered to have a major impact on secondary elevated intraocular pressure (IOP). Several mechanisms are involved in the pathogenesis of inflammatory glaucoma, including obstruction of the trabecular meshwork by inflammatory cells and proteins, trabeculitis, formation of anterior and/or posterior synechiae, pupillary block, neovascularization, and anterior rotation of the lens-iris diaphragm. In addition, the use of steroids to control intraocular inflammation may cause secondary elevation of IOP. The management of uveitic glaucoma requires a careful balance between adequate anti-inflammatory therapy and appropriate lowering of IOP to prevent long-term visual loss. Despite the availability of many new medical treatments for both conditions, control of IOP in these patients remains challenging.

5-YEAR AND 8-YEAR RESULTS OF TRABECULOPLASTY - MOULIN, F; AMELINE, B; REDOR, Y; BOUMERZAG, AB; HAUT, J (JOURNAL FRANCAIS D OPHTALMOLOGIE, 1992)
To appreciate the current place of argon laser trabeculoplasty (ALT) in the therapeutic armamentarium of primary open-angle glaucoma (POAG), the first 211 photocoagulated phakic eyes were analysed. One hundred and fifty-nine eyes had a 5 year-follow-up and 147 eyes had a minimal 8 year-follow-up. These eyes came from an initial group of 151 patients: 76 women and 75 men with a mean age of 66 years. We decided, arbitrarily, to assess trabeculoplasty results according to three combined criteria of failure (insufficient or transient intraocular pressure drop (3 mmHg), progression in visual field loss and need for a filtrating surgery) and to various expected goals: prevent an increase of drugs with their subsequent side effects, taper a non tolerated medical treatment and, lastly, try to cease all medical treatment in non compliant patients. According to these criteria, during the first five years, the cumulative failure rate in the 159 eyes rose steadily from 19 % (31 eyes) in the first year to 52 % (82 eyes) in the fifth year. The initial mean intraocular pressure (27.22 mmHg) of 7 failures operated on during the first 2 months and that of all 27 operated on failures (24.41 mmHg) was higher than the initial mean intraocular pressure of the 77 successful cases (22.67 mmHg). In the 77 eyes still controlled at 5 years, the intraocular pressure drop was 6.57 mmHg. In the 31 failures encountered during the first year after laser treatment, there was a greater percentage requiring surgery : 52 % (16 trabeculectomies in 31 failures) than in the 51 failures found during the four following years : 22 % (11 trabeculectomies in 51 failures). In the course of the five year-follow-up, ALT was able to alleviate a non tolerated medical treatment in 77.8 % of the cases, prevented an increase of drugs in 62.5 % of the cases but was able to delay a filtration surgery in only 48 % of the cases. In the 147 eyes studied with a 8 year-follow-up, only 25 eyes (17 %) were still controlled. This low success rate at 8 years was forseeable according to the 10 % new failure cases per year encountered in the five year-data. Despite this important failure rate on the long run, making laser efficacy comparable with drugs, trabeculoplasty is still useful in the current therapeutic armamentarium of POAG, not as a rival procedure of invasive filtrating operation reserved to presurgical glaucomas, but as a complementary treatment of the intermediate stages of the disease for which its efficacy was found to better in the present study.

Elevation of Intraocular Pressure in Glaucoma Patients After Automated Visual Field Testing - Ni, NN; Tsai, JC; Shields, MB; Loewen, NA (JOURNAL OF GLAUCOMA, 2012)
Purpose: To examine whether automated visual field (VF) testing may exert a short-term influence on subsequent intraocular pressure (IOP) measurement during the same visit. Methods: We reviewed patients with primary open-angle glaucoma whose most recent visit occurred at a major academic institution from July to December 2009 and who had 3 visits without intervening changes in glaucoma management within the previous 5 years. Exclusion criteria were patient admittance of nonadherence with medical therapy and documented difficulty of IOP measurement. One hundred nine right eyes from 109 patients were included. IOP obtained within 30 minutes after VF testing was compared with IOP from the previous and next visits without VF testing. Subgroup analyses included the role of reliability of VF test performance, surgical versus medical IOP control, and different topical medications. Results: The average IOP measured after VF testing was 14.9 +/- 4.7 mm Hg, higher than both the previous (13.7 +/- 4.4 mm Hg, P < 0.001) and next visits without VF examination (13.8 +/- 4.4 mm Hg, P < 0.001). A total of 22.9% of patients experienced a more than 20% increase of IOP. Eyes with surgical control had less IOP elevation than eyes with medical control (3.1% +/- 15.9% vs. 11.7% +/- 17.4%, P = 0.009). Users of beta-blockers or alpha-2-agonists had less IOP elevation than eyes controlled with prostaglandins or carbonic anhydrase inhibitors (0.9% +/- 15.1% vs. 9.0% +/- 12.3%, P = 0.030). Conclusions: This retrospective study suggests that patients with primary open-angle glaucoma experience a small and transient increase in IOP after VF testing and that this effect may be lower after surgical pressure control.

Minimally invasive glaucoma surgery as primary stand-alone surgery for glaucoma - Kerr, NM; Wang, J; Barton, K (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2017)
Recently, many new devices and procedures have been developed to lower intraocular pressure in a less invasive and purportedly safer manner than traditional glaucoma surgery. These new devices might encourage an earlier transition to surgery and reduce the long-term commitment to topical glaucoma medications with their associated compliance and intolerance issues. Although often seen as an adjunct to cataract surgery, a growing body of evidence suggests that primary minimally invasive glaucoma surgery may be a viable initial treatment option. New studies have shown that primary ab interno trabeculectomy (Trabectome, NeoMedix Inc., Tustin, CA, USA), trabecular micro-bypass stent insertion (iStent and iStent Inject, Glaukos Corporation, Laguna Hills, CA, USA), canalicular scaffolding (Hydrus, Invantis Inc., Irvine CA, USA), the ab interno gel Implant (XEN, Allergan, Dublin, Ireland) or supraciliary stenting (CyPass Micro-Stent, Alcon, Fort Worth, TX, USA) may lower the lowering intraocular pressure and/or topical medication burden in phakic or pseudophakic patients with glaucoma. This effect seems to last at least 12months but reliable cost-effectiveness and quality of life indicators have not yet been established by investigator-initiated randomized trials of sufficient size and duration.

The Choice of Drainage Device in Complicated Glaucomas: Comparing Ahmed and Baerveldt Implants - Moschos, MM; Nitoda, E; Gouliopoulos, N; Androudi, S; Damaskos, C; Laios, K; Bagkli, E; Garmpis, N; Kitsos, G (IN VIVO, 2019)
Background/Aim: Glaucoma is a chronic and progressive optic neuropathy which leads to deterioration of visual function. It is estimated to be the second leading cause of severe vision loss and blindness worldwide. Failure of anti-glaucoma medication to sufficiently reduce intraocular pressure (IOP) and poor compliance with medication are indications for glaucoma surgery, for example using glaucoma drainage devices. Our aim was to compare the surgical outcomes following the implantation of Ahmed FP7 and Baerveldt 350 drainage devices. Patients and Methods: Five hundred and fifty-two patients with primary or secondary glaucoma were enrolled in the study. All patients had a history of failed trabeculectomy or other intraocular surgery, and IOP >= 18 mm Hg. The implantation of Ahmed (266 patients) or Baerveldt (286 patients) devices was randomly performed in the patients, who were subsequently examined for a period of 5 years. Follow-up visits were scheduled 1 day; 1 week; 1, 3 and 6 months; and 1, 1.5, 2, 3, 4 and 5 years postoperatively. Results: Significant reduction of IOP was achieved in both groups. Ahmed valve (28.3 +/- 9.3 ,13.4 +/- 6.9,14.2 +/- 6 and 12.7 +/- 4.5 mmHg at baseline, 1, 3, and 5 years postoperatively, respectively) resulted in significantly greater IOP reduction compared to Baerveldt implant (29.6 +/- 10.1, 15.4 +/- 5 .5, 14.5 +/- 5 .5 and 14.7 +/- 4.4 mmHg at baseline, 1, 3, and 5 years postoperatively, respectively). A significantly lower number of medications was required in the Ahmed group in comparison to the Baerveldt one (Ahmed group: 1.5 +/- 1.4, 1.4 +/- 1.5 and 1.8 +/- 1.5; Baerveldt group: 1.9 +/- 1.3, 1.9 +/- 1.3 and 2.2 +/- 1.4, respectively). The incidence of treatment failure and the rate of glaucoma reoperation were significantly higher in the Baerveldt group (40%) compared to the Ahmed group (17%). Conclusion: Ahmed drainage implantation seemed to outclass that using the Baerveldt device in our study, in terms of efficacy and success rate.

The impact of glaucoma referral refinement criteria on referral to, and first-visit discharge rates from, the hospital eye service: the Health Innovation & Education Cluster (HIEC) Glaucoma Pathways project - Ratnarajan, G; Newsom, W; French, K; Kean, J; Chang, L; Parker, M; Garway-Heath, DF; Bourne, RRA (OPHTHALMIC AND PHYSIOLOGICAL OPTICS, 2013)
Purpose To assess the impact of referral refinement criteria on the number of patients referred to, and first-visit discharges from, the Hospital Eye Service (HES) in relation to the National Institute for Health & Clinical Excellence (NICE) Glaucoma Guidelines, Joint College Group Guidance (JCG) and the NICE commissioning guidance. Methods All low-risk (one risk factor: suspicious optic disc, abnormal visual field (VF), raised intra-ocular pressure (IOP) (2228mmHg) or IOP asymmetry (>5mmHg) and high-risk (more than one risk factor, shallow anterior chamber or IOP >28mmHg) referrals to the HES from 2006 to 2011 were analysed. Low-risk referrals were seen by Optometrists with a specialist interest in glaucoma and high-risk referrals were referred directly to the HES. Results Two thousand nine hundred and twelve patient records were analysed. The highest Consultant first-visit discharge rates were for referrals based on IOP alone (45% for IOP 2228mmHg) and IOP asymmetry (53%), VF defect alone (46%) and for abnormal IOP and VF (54%). The lowest first-visit discharge rates were for referrals for suspicious optic disc (19%) and IOP >28mmHg (22%). 73% of patients aged 6580 and 60% of patients aged >80 who were referred by the OSI due to an IOP between 2228mmHg would have satisfied the JCG criteria for non-referral. For patients referred with an IOP >28mmHg and an otherwise normal examination, adherence to the NICE commissioning guidance would have resulted in 6% fewer referrals. In 2010 this scheme reduced the number of patients attending the HES by 15%, which resulted in a saving of 16258 pound (13%). Conclusion The results support that referrals for a raised IOP alone or in combination with an abnormal VF be classified as low-risk and undergo referral refinement. Adherence to the JCG and the NICE commissioning guidance as onward referral criteria for specialist optometrists in this referral refinement scheme would result in fewer referrals.

Prophylaxis and management of complications in penetrating keratoplasty - Seitz, B; El-Husseiny, M; Langenbucher, A; Szentmary, N (OPHTHALMOLOGE, 2013)
Besides routine postoperative follow-up the prophylaxis of complications in penetrating keratoplasty (PKP) includes special preoperative and intraoperative aspects. Preoperative prophylaxis consists of the therapy of systemic diseases and eyelid abnormalities, determining individual optimal graft size, avoiding PKP in cases of uncontrolled intraocular pressure, avoiding PKP in cases of corneal hydrops, pretreatment of vascularized cornea, amniotic membrane transplantation before PKP in cases of ulcerative keratitis, quality controlled organ-cultured transplants and preoperative counselling by the surgeon to ensure patient compliance. Intraoperative prophylaxis consists of controlled arterial hypotension and complete relaxation during general anesthesia, avoidance of decentration, horizontal torsion and vertical tilt using a non-contact trephination technique (preferably excimer laser) with double-running cross-stitch sutures and application of Flieringa rings in aphakic vitrectomized eyes. Postoperatively, periodical control examinations using fluorescein and blue light are indispensable. All loose sutures have to be removed as early as possible. In cases of herpetic eye disease 2 x 400 mg of oral acyclovir should be administered for at least 1 year. In cases of therapy-resistant epithelial defects 100 % autologous serum eyedrops or amniotic membrane patches are valid options. Immune reactions must be diagnosed and treated immediately with high doses of corticosteroids.

CO2 laser-assisted sclerectomy surgery compared with trabeculectomy in primary open-angle glaucoma and exfoliative glaucoma. A 1-year follow-up - Jankowska-Szmul, J; Dobrowolski, D; Wylegala, E (ACTA OPHTHALMOLOGICA, 2018)
PurposeTo report on the efficacy and safety of CO2 laser-assisted sclerectomy surgery (CLASS) compared with trabeculectomy in primary open-angle glaucoma and exfoliative glaucoma. MethodsOne hundred and thirty-one patients underwent CLASS (66 patients) or trabeculectomy (65 patients) and were followed up for 12months. Complete success' was defined as intraocular pressure (IOP) between 10 and 18mmHg and reduced by at least 30% from the baseline without medications, while qualified success' was compliant with the above criteria with or without the medications. ResultsComparing CLASS with trabeculectomy at 1year, the mean IOP reduction rate was 32.610.8% versus 40.6 +/- 15.9% (p<0.001) and the average use of medications was 1.4 +/- 1.4 versus 0.7 +/- 1.1 (p<0.05). At 12months, the complete success rate was 35% for CLASS versus 60% for trabeculectomy (p<0.01), while the qualified success rate was 74% versus 75%, respectively, with no significant difference in qualified success rate between the groups at any time-point (p>0.05). Compared with CLASS, patients after trabeculectomy developed a higher rate of early complications (9.1% versus 29.2%, p=0.004), higher endothelial cell density (ECD) loss (1.4 +/- 1.4% versus 6.5 +/- 4.8%, p<0.001), higher astigmatism (0.0 +/- 0.1 versus 0.1 +/- 0.2, p<0.001) and significant visual acuity deterioration (0.1 +/- 0.1; range 0-2 lines versus 0.4 +/- 0.6; range 0-3 lines, p=0.016). ConclusionAlthough CLASS shows a less potent hypotensive effect, it is similar to trabeculectomy in the qualified success rate and offers the reduction in medications up to 12months. With a more attractive complications profile, CLASS may be an alternative to trabeculectomy, especially at the earlier glaucoma stage and in patients with a low ECD.

Health literacy and glaucoma - Muir, KW; Christensen, L; Bosworth, HB (CURRENT OPINION IN OPHTHALMOLOGY, 2013)
Purpose of review This review discusses the concept and measurement of health literacy, with a focus on the care of patients with glaucoma. Recent findings Nearly one-fourth of adults in the USA lack the skills needed to fully comprehend and act on verbal or written information in the healthcare environment. This problem, referred to as poor health literacy, is associated with worse health-related outcomes in many chronic diseases, including glaucoma. Patients with glaucoma and poor literacy skills are less likely to refill their prescribed medications and miss more scheduled appointments than their more literate peers. Moreover, ophthalmic educational materials are often written at a level of readability that surpasses the skills of many patients with glaucoma. Summary Patients with chronic eye diseases such as glaucoma and limited health literacy skills are vulnerable to poor visual outcomes. Attention to health literacy may improve the care and outcomes of these patients.

Contact lens user profile, attitudes and level of compliance to lens care - Wu, Y; Carnt, N; Stapleton, F (CONTACT LENS & ANTERIOR EYE, 2010)
Purpose: To identify the demographics profile of lens wearers, and to evaluate the scope and level of noncompliant, behaviours in lens wearers. Methods: 210 contact lens wearers who attended an optometry clinic at an education and research institute, were surveyed using a self-administered questionnaire. The questionnaire was constructed to gather information regarding contact lens wearer demographics, contact lens hygiene behaviours and, attitudes toward lens care. Multivariate testing between lens wearers' demographic, hygiene, behaviours and attitude to aftercare visit were analysed. Results: One hundred and eleven (62%) of participants responded, with a mean age of 33.8 +/- 12 years. 55% of the respondents were female. Major non-compliance aspects identified were poor hand hygiene (11%), inadequate cleaning of lenses (13%) and lens storage cases (61%), and wearers not remembering how often they were advised to return for an aftercare (50%). Lens wearers who purchased contact lenses, from the internet were 3.8 times more likely to forget their aftercare schedule than those who purchased contact lenses from the optometrists (95% CI = 1.2-12.2, p = 0.024). Conclusion: Poor hand hygiene, inadequate lens care, and not remembering when to come back for after-cares are the common non-compliant behaviours in lens wearers. Purchase of lenses via the internet was associated with lack of awareness of aftercare visit. (C) 2010 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.

Resident Compliance With the American Academy of Ophthalmology Preferred Practice Patterns for Primary Open-Angle Glaucoma Suspect - Mihlstin, M; Juzych, MS; Kromrei, HT; Hwang, FS; Yin, J (JOURNAL OF GLAUCOMA, 2016)
Purpose:To study resident compliance with the American Academy of Ophthalmology (AAO) Preferred Practice Patterns (PPPs) for primary open-angle glaucoma suspect (POAGS) in a resident ophthalmology clinic.Patients and Methods:Two hundred charts were selected for analysis of adult patients with the International Classification of Diseases diagnosis code for POAGS during their initial visit between November 2, 2010 and May 6, 2014 at the Kresge Eye Institute resident clinic. Electronic medical records of clinic visits for POAGS patients were evaluated for documentation and compliance with 17 elements of AAO PPPs.Results:The overall mean compliance was 73.8% for all charts (n=200), 74.4% for first-year residents (n=53), 74.5% for second-year residents (n=38), and 73.3% for third-year residents (n=109). Documentation rates were high (>90%) for 9 elements, which included most elements of physical examination and history. Documentation of ocular history, central corneal thickness, gonioscopy, optic nerve head and retinal nerve fiber layer analysis, and visual field ranged from 40% to 80%. Documentation was lowest for patient education elements which ranged from 0% to 10%. Compliance was not significantly different (P>0.05) between residents or between different resident years for any element.Conclusions:Residents' compliance was high for most elements of the PPPs for POAGS. We identified elements with poor compliance especially regarding patient education. Adherence to AAO PPPs can be a helpful method of assessing resident performance.

FACTORS ASSOCIATED WITH VISUAL-LOSS IN PATIENTS WITH ADVANCED GLAUCOMATOUS CHANGES IN THE OPTIC-NERVE HEAD - STEWART, WC; CHORAK, RP; HUNT, HH; SETHURAMAN, G (AMERICAN JOURNAL OF OPHTHALMOLOGY, 1993)
We evaluated factors associated with decreased or stable visual function in 72 patients with primary open-angle glaucoma and complete cupping of the optic disk who were followed up five years or more. We found a significantly lower mean (15.4 +/- 2.7 mm Hg) and peak (24.5 +/- 6.9 mm Hg) intraocular pressure in those patients whose vision remained stable vs those whose vision decreased (21.3 +/- 3.2 and 39.2 +/- 11.0 mm Hg, respectively) (t-test, P < .001). Additionally, the variance of each patient's individual intraocular pressure readings measured during the follow-up period was lower in the group with stable vision (4.5 mm Hg) than in those in whom vision decreased (9.0 mm Hg) (F test, P < .001). Stepwise discriminant analysis disclosed that mean intraocular pressure, variance of an individual's intraocular pressure measurements over time, history of argon laser trabeculoplasty, and compliance with therapy discriminated 92.9% of patients (52 of 56) whose vision remained stable and 87.5% of patients (14 of 16) whose vision decreased. Reduction of intraocular pressure and compliance with therapy are important in patients with complete glaucomatous cupping of the optic disk.

A Prospective Randomized Trial Comparing Hydrus and iStent Microinvasive Glaucoma Surgery Implants for Standalone Treatment of Open-Angle Glaucoma The COMPARE Study - Ahmed, IIK; Fea, A; Au, L; Ang, RE; Harasymowycz, P; Jampel, H; Samuelson, TW; Chang, DF; Rhee, DJ; COMPARE Investigators (OPHTHALMOLOGY, 2020)
Purpose: To compare the efficacy of different microinvasive glaucoma surgery (MIGS) devices for reducing intraocular pressure (IOP) and medications in open-angle glaucoma (OAG). Design: Prospective, multicenter, randomized clinical trial. Participants: One hundred fifty-two eyes from 152 patients aged 45 to 84 years with OAG, Shaffer angle grade best-corrected visual acuity (BCVA) 20/30 or better, and IOP 23 to 39 mmHg after washout of all hypotensive medications. Eyes with secondary glaucoma other than pseudoexfoliative or pigmentary glaucoma, angle closure, previous incisional glaucoma surgery, or any significant ocular pathology other than glaucoma were excluded. Intervention: Study eyes were randomized 1:1 to standalone MIGS consisting of either 1 Hydrus Microstent (Ivantis, Inc, Irvine, CA) or 2 iStent Trabecular Micro Bypass devices (Glaukos Inc, San Clemente, CA). Follow-up was performed 1 day, 1 week, and 1, 3, 6, and 12 months postoperatively. Main Outcome Measures: Within-group and between-group differences in IOP and medications at 12 months and complete surgical success defined as freedom from repeat glaucoma surgery, IOP 18 mmHg or less, and no glaucoma medications. Safety measures included the frequency of surgical complications, changes in visual acuity, slit-lamp findings, and adverse events. Results: Study groups were well matched for baseline demographics, glaucoma status, medication use, and baseline IOP. Twelve-month follow-up was completed in 148 of 152 randomized subjects (97.3%). At 12 months, the Hydrus had a greater rate of complete surgical success (P < 0.001) and reduced medication use (difference = -0.6 medications, P = 0.004). More Hydrus subjects were medication free at 12 months (difference = 22.6% P = 0.0057). Secondary glaucoma surgery was performed in 2 eyes in the 2-iStent group (3.9%) and in none of the Hydrus eyes. Two eyes in the Hydrus group and 1 in the 2-iStent group had BCVA loss of >= 2 lines. Conclusion: Standalone MIGS in OAG with the Hydrus resulted in a higher surgical success rate and fewer medications compared with the 2-iStent procedure. The 2 MIGS devices have similar safety profiles. (C) 2019 by the American Academy of Ophthalmology

The Modified Cincinnati Procedure: Combined Conjunctival Limbal Autografts and Keratolimbal Allografts for Severe Unilateral Ocular Surface Failure - Chan, CC; Biber, JM; Holland, EJ (CORNEA, 2012)
Purpose: To describe the technique and present the outcomes of combined conjunctival limbal autografts (CLAU) and keratolimbal allografts (KLAL) for the treatment of unilateral severe ocular surface failure. Methods: Interventional case series. Eleven eyes of 11 patients who sustained chemical burns (4 alkali and 2 acid) and combined chemical/thermal burns (5 eyes) from firework explosions had combined CLAU/KLAL surgery. Keratoplasty was performed subsequently for residual corneal stromal scarring limiting visual acuity. Inclusion criteria included eyes with severe unilateral total ocular surface failure, controlled glaucoma, and reasonable eyelid apposition with no exposure. Exclusion criteria included patients with any ocular surface abnormality in the fellow eye and those with contraindications to systemic immunosuppression (SI). Outcome measures included Snellen best-corrected visual acuity (BCVA), ocular surface stability, SI exposure, and complications. Results: Preoperative BCVA was 20/400 or worse in all eyes. At the final follow-up (mean, 35.8 months; range, 12.1-105.9 months), 73% (8 of 11) eyes had BCVA of 20/80 or better (range, 20/25 to counting fingers), and ocular surface was stable in 82% (9 of 11). Ninety-one percent (10 of 11) had additional penetrating keratoplasty (PK) with a 60% (6 of 10 eyes) success rate. Three cases had subsequent Boston type 1 keratoprosthesis implantation after PK failure, and the fourth patient, at the time of his last follow-up visit, did not want further intervention for his edematous PK, which was a result of noncompliance-related corneal rejection. In eyes with more than 2 years of follow-up, SI was tapered at a mean of 16 months (range, 8-28 months). There were no intraoperative complications. No secondary tumors, cardiac events, or deaths occurred while patients were on SI. One patient developed secondary glaucoma refractory to medical management after subsequent PK, requiring cyclodiode laser. Conclusions: Combined CLAU/KLAL and staged keratoplasty is effective in improving vision and maintaining long-term ocular surface stability in patients with severe unilateral ocular surface disease and conjunctival deficiency.

Contact Lens Compliance With Ophthalmologists and Other Health Professionals - Taslipinar, AG; Uzel, MM; Yuksel, N; Akcay, EK (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2018)
Purpose: To assess the compliance with contact lens (CL) use among ophthalmologists and other health professionals, and to identify the main noncompliant behaviors. Methods: A cross-sectional, comparative study was designed for soft CL wearers. Twenty-five ophthalmologists, 24 medical doctors other than ophthalmologists, 20 nurses (health professionals), and 52 lay people (members of the public) subjects were included in the interview. The compliance rate for each behavior were determined and compared. Users were asked to rate their subjective use to calculate self-evaluation scores. Results: The compliance rate was found to be the highest among ophthalmologists; however, the difference was not significant (P=0.083). Although the level of compliance was not associated with the subjects' age, duration of lens wear, or wearing days per week (P>0.05), an association was found with the number of wearing hours per day (P=0.010). Increased wearing hours per day was found to increase the rate of poor compliance (P=0.010). Significant differences were found between the groups in storing lenses in fresh solution, lens wearing time according to the ophthalmologist recommendation, and follow-up visits according to ophthalmologist recommendation (P<0.001, P=0.036, P=0.001, respectively). Self-evaluation scores among ophthalmologists, health professionals, and the lay people were 7.5 +/- 60.86, 7.59 +/- 1.29, and 7.67 +/- 1.60, respectively, and no significant differences existed between the groups (P=0.930). Conclusion: No differences were evident between the groups in terms of good compliance with CL wear and care practices. As this result shows that compliance with CL wear and care practices is not only related to the level of knowledge, different methods should be developed to increase compliance.

Differences in Neuroticism Between Patients with Glaucoma Who Have Discontinued Visits to Ophthalmologists and Those Who Make Regular Visits: Implications for Adherence to Topical Glaucoma Medications - Nakano, T; Kodaka, F; Tsuneoka, H (OPHTHALMOLOGY AND THERAPY, 2016)
Neuroticism is a personality trait often described in individuals with glaucoma (GLC), but is not necessarily representative of the total population of patients. There is a population of patients with GLC who are invisible to clinical ophthalmologists; in other words, those who once have been diagnosed with GLC, but spontaneously stop visiting an ophthalmologist. Little is known about their neuroticism personality trait. In the present study, the authors compared the level of neuroticism between patients no longer visiting an ophthalmologist and those who continue visit them regularly. Patients were assigned to two groups according to the duration of their last visit to an ophthalmologist: the Discontinued group included those patients who had not visited an ophthalmologist for the last 6 months, and the Regular Visitor group included those patients who continued to make regular visits to an ophthalmologist. The Japanese version of Ten Items Personality Inventory (TIPI-J), a questionnaire specifically used to assess the Big Five personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness), was completed by patients through a dedicated website. Three-hundred and seventy-three patients with GLC were recruited. The neuroticism score from the TIPI-J in the Discontinued group was significantly lower than that in the Regular Visitor group (7.63 +/- 2.23 vs. 8.23 +/- 2.21, respectively; P = 0.01). No significant difference was found in the other TIPI-J sub-item scores between the Discontinued and the Regular Visitor groups. In this study, the authors showed that neuroticism trait in patients with GLC who have discontinued visiting their ophthalmologists was lower than that in patients who regularly visited them, on the basis of the Big Five personality traits as measured by the TIPT-J. Santen Pharmaceutical Co., Ltd.

Patients' perspectives on the barriers to referral after telescreening for diabetic retinopathy in communities - Zhu, XF; Xu, Y; Lu, LN; Zou, HD (BMJ OPEN DIABETES RESEARCH & CARE, 2020)
ObjectiveTo understand the referral completion and explore the associated barriers to the referral after telescreening for diabetic retinopathy (DR) among people with vision-threatening DR (VTDR).Research design and methodsAll participants with VTDR after DR telescreening in the communities completed the self-reported questionnaires to assess referral completion and their perspectives on referral barriers. Sociodemographic characteristics and perceived barriers related to incomplete referrals were identified by conducting univariate analysis and multiple logistic regression model. The final model was then built to predict incomplete referral.ResultsOf the 3362 participants, 46.1% had incomplete referral. Old age and lower education level showed significant association with incomplete referral. Almost all participants had at least one barrier during the referral process. Knowledge-related and attitude-related barriers, including 'Too old to want any more treatment', 'Difficulty in getting time to referral', 'No serious illness requiring treatment at present', 'My eyes are okay', 'Distrust the recommended hospital' and 'Have not been diagnosed or treated before', and logistics-related barrier 'Mobility or transportation difficulties' showed significant association with incomplete referral.ConclusionsThe issue of incomplete referral after DR telescreening is serious among individuals with VTDR, particularly in the elder and low education level population. The negativity of knowledge-related and attitude-related factors might be more prominent than logistic barriers in predicting incomplete referral. Therefore, new strategies to improve the compliance with referral assist in optimizing the referral accessibility, and the ongoing educational support to improve the awareness of disease and increase the effectiveness of physician-patient communication.

Overuse and Underuse of Visual Field Testing Over 15 Years - Ben-Artsi, E; Goldenfeld, M; Zehavi-Dorin, T; Cohen, A; Porath, A; Levkovitch-Verbin, H (JOURNAL OF GLAUCOMA, 2019)
Precis: A 15-year analysis of 198,843 visual field (VF) tests revealed a growing trend for their performance for nonglaucoma indications. Adherence to glaucoma management guidelines was suboptimal. Guidelines for referral to VF assessments should be established. Purpose: The purpose of this study was to identify trends in VF assessments over 15 years among patients with and without suspected or confirmed glaucoma, in a large healthcare maintenance organization. Methods: This was a population-based retrospective cohort study, conducted by means of electronic medical database analyses. Study population: Maccabi Healthcare Services is an healthcare maintenance organization that insures 2 million members constituting 25% of the population. All members who underwent at least 1 VF test between January 2000 and December 2014 were included. In addition, all members with glaucoma or suspected glaucoma diagnosis or who were prescribed with antiglaucoma medications were evaluated. Main outcome measures: VF performance rates. Results: A total of 93,617 Maccabi Healthcare Services members underwent 198,843 VF tests; of whom 47.9% involved patients without any glaucoma-related conditions. There was a growing trend over time toward more of those members to undergo VF tests and, by 2014, non-glaucoma-related members comprised 74.0% of new VF assessments. In contrast, 32.3% of glaucoma-related patients did not perform even 1 VF test throughout the entire study period. Although over 2 years (25.95 +/- 6.33 mo) passed between the first glaucoma-related diagnosis and first VF test, once a patient underwent the first VF test, an average once-a-year VF follow-up (0.95 +/- 0.37 annual tests) began. Conclusion: There is a growing trend for VF tests being apparently overused for indications other than glaucoma. Concurrently, adherence to glaucoma management guidelines on VF tests is suboptimal, leading to discernible underuse. Guidelines for VF assessments in nonglaucoma patients should be established. Adherence to existing glaucoma management guidelines should be improved.

Does TRABECULECTOMY meet the 10-10-10 challenge in PACG, POAG, JOAG and Secondary glaucomas? - Sihota, R; Shakrawal, J; Sidhu, T; Sharma, AK; Dada, T; Pandey, V (INTERNATIONAL OPHTHALMOLOGY, 2020)
Purpose Evaluation of the intraocular pressure (IOP) lowering efficacy of trabeculectomies over > 10 years and their ability to stabilize glaucomatous optic neuropathy. Methods In total, 181 eyes (136 patients), which underwent trabeculectomy (10 min surgery) at least 10 years prior and were on regular follow-up, were evaluated. Qualified/complete success was taken as criteria A: IOP <= 12 mmHg, B: IOP <= 15 mmHg and C: IOP <= 18 mmHg, with all > 5 mmHg, with/without medications. Target IOP in advanced glaucoma is about 10 mmHg, therefore trabeculectomy 10-10-10 challenge! Results The mean age of patients was 46.32 +/- 11.50 years. Absolute success was 50.27%, 54.14% and 59.66% according to criteria A, B and C at last follow-up, while qualified success was 70.11%, 81.77% and 96.13%. An IOP of <= 12 mmHg was noted in 34, 64.15%, PACG eyes, 14, 73.68%, POAG, 15, 65.22%, JOAG and 64, 74.42%, secondary glaucoma eyes. The reduction in IOP overall was 64.83 +/- 16.80% at last review and was 59.47 +/- 16.07% in PACG, 62.40 +/- 17.72% in POAG, 71.89 +/- 8.50% in JOAG and 67.74 +/- 18.10% in secondary glaucoma eyes. "Target" IOP was achieved in 97.29% of early glaucoma, 85.71% moderate glaucoma and 70% severe glaucoma eyes. 97.24% of patients were perimetrically stable. 2.21% of eyes post-trabeculectomy had a shallow anterior chamber needing surgical intervention. Visual acuity was maintained or better in 93.92% of patients, with a cataract surgery performed in 6.63% eyes. A repeat trabeculectomy was performed in 3.31% of eyes. Conclusion Trabeculectomy 10-10-10 is achievable in the long term, with few complications or repeat surgical interventions in the majority of POAG, PACG, JOAG and secondary glaucomas. Therefore, trabeculectomy should not be relegated to a last resort, but should be undertaken as soon as possible, if medical therapy is inadequate, unaffordable or compliance is an issue.

A Service Coverage Analysis of Primary Congenital Glaucoma Care Across the United - Vu, DM; Stoler, J; Rothman, AL; Chang, TC (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2021)
PURPOSE: To assess the number of infants at risk of delayed primary congenital glaucoma (PCG) evaluation due to long travel times to specialists. DESIGN: Cross-sectional geospatial service coverage analysis. METHODS: All American Glaucoma Society (AGS) and American Association for Pediatric Ophthalmology and Strabismus (AAPOS) provider locations were geocoded using each organization's member directory. Sixty-minute drive time regions to providers were generated using ArcGIS Pro (Esri). The geographic intersection of AGS and AAPOS service areas was computed because patients typically require visits to both types of specialists. American Community Survey data were then overlaid to estimate the number of infants within and beyond the AGS/AAPOS service areas. RESULTS: One thousand twenty-nine AGS and 1,040 AAPOS provider locations were geocoded. The analysis yielded 944,047 infants age 0-1 year (23.6%) who live beyond the AGS/AAPOS service areas. Therefore, approximately 14-94 new PCG cases/year may be at risk of delayed diagnosis as a result of living in a potential service desert. Compared with children living within the AGS/AAPOS service areas, children aged <6 years in these potential service deserts were more likely to live in households earning below the US federal poverty level, lack health insurance, and live in a single-parent home. These communities are disproportionately likely to experience other rural health disparities and are more prevalent across the Great Plains. CONCLUSION: Service coverage analysis is a useful tool for identifying underserved regions for PCG referrals and evaluation. These data may assist in targeting screening programs in low access areas for pediatric glaucoma care. (Am J Ophthalmol 2021;224:112-119. (c) 2020 Elsevier Inc. All rights reserved.)

Influence of switching to travoprost on intraocular pressure of uncontrolled chronic open-angle glaucoma patients compliant to previously-used topical medication - Hollo, G; Vargha, P; Kothy, P (CURRENT MEDICAL RESEARCH AND OPINION, 2005)
Objective:To investigate the influence of switching to travoprost on intraocular pressure (IOP) of chronic open-angle glaucoma (COAG) patients. Research design and methods: Multicentre, open-label, non-comparative, 12-week, phase IV study conducted at 10 academic and hospital centres in Hungary. Patients' compliance to use of the pre-study medication was confirmed at a visit 10 days before the baseline measurements, and compliance was monitored throughout the study period. Results: Of the 203 COAG patients three (1.48%) ceased travoprost medication due to ocular hyperaemia, and one subject was lost from follow-up. Self-reported compliance was optimal except for two patients. For the per-protocol analysis 197 patients were evaluable. IOP of the 37 per-protocol patients receiving additional travoprost medication decreased from 23.1 +/- 3.2 mmHg (mean +/- SD) to 17.3 +/- 2.6 mmHg at week 12 (p < 0.001). Switching the 121 per-protocol patients from latanoprost to travoprost IOP decrease 20.8 +/- 3.5 mmHg to 17.7 +/- 2.4 mmHg (p < 0.001). IOP of the 11 patients switched from topical nonselective beta-blockers to travoprost decreased from 20.1 +/- 2.1 mmHg to 15.7 +/- 1.5 mmHg (p < 0.001). For the whole per-protocol population (n = 197) IOP decreased from 21.0 +/- 3.4 mmHg to 17.4 +/- 2.4 mmHg (p < 0.001). Defining responders as having an IOP decrease > 2.0 mmHg or >= 5 mmHg at week 12, the responder rate was respectively 62.9% or 31 % for the total study population; 86.5% or 54.1 % when travoprost was added to the established therapy; 54.5% or 24.0% if latanoprost was switched to travoprost; and 90.9% or 36.4% for those who switched from beta-blockers. Conclusion: Travoprost provided a clinically and statistically significant IOP decrease in uncontrolled COAG patients whose self-reported compliance to their previous topical medication was optimal. Our results suggest that the IOP reduction found after switching to travoprost is not explainable by improved compliance due to the clinical study situation.

Compliance of medical treatment in primitive glaucoma open angle - Wane, AM; Ndiaye, MR; Wade, A; Ndiaye, PA; Ba, EA; de Medeiros, ME; Ndoye, PA; Ndiaye, CS; Kameni, A (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2003)
Introduction: Compliance to medical treatment expresses the patient's perception of the disease and the treatment prescribed by the doctors. Lack of compliance endangers chronic glaucoma care, which explains the importance it has been given these last years. The objectives 14 of this survey were to evaluate the compliance of adult patients suffering from primary open angle glaucoma to discover the influential factors. Materials and methods: We conducted a survey at the ophthalmology clinic of Le Dantec Hospital from January 1997 to May 1998 among 31 adults being treated for primary open angle glaucoma. An indirect evaluation of the patients' compliance was made on the basis of a questionnaire after examination of their medical files. It was deemed good, average, or bad depending on: regularity of the patient's visits to the doctors, regularity of the treatment, respect of the doctor's prescription and the prescribed times for taking the medicine. The Chi square independence test was used to study the influence of the following factors: age, sex, residence, socioeconomic status, duration of symptom progression, level of instruction, counseling, and treatment. Results: The patients' mean age was 60.5 years. Compliance was deemed good for 29% of the total cases, average for 32.3%, and bad for 38.7%. Only factors such as the regular visits to the doctor, the regularity of the treatment, and respect of the doctor's prescription and the prescribed times for taking the medicine were found to be influential (p<0.05). Conclusion: The medical treatment of-primary open angle glaucoma, whether temporary or permanent, with a maximum of efficacy and a minimum of side-effects requires good compliance on the part of the patient. This compliance in turn requires a good doctor-patient relationship based on effective repeated counseling to educate patients, help them understand the disease, and act on the influential factors.

When Is Evidence Enough Evidence? A Systematic Review and Meta-Analysis of the Trabectome as a Solo Procedure in Patients with Primary Open-Angle Glaucoma - Chow, JTY; Hutnik, CML; Solo, K; Malvankar-Mehta, MS (JOURNAL OF OPHTHALMOLOGY, 2017)
The purpose of this systematic review and meta-analysis was to examine the availability of evidence for one of the earliest available minimally invasive glaucoma surgery (MIGS) procedures, the Trabectome. Various databases were searched up to December 20, 2016, for any published studies assessing the use of the Trabectome as a solo procedure in patients with primary open-angle glaucoma (POAG). The standardized mean differences (SMD) were calculated for the change in intraocular pressure (IOP) and number of glaucoma mediations used at 1-month, 6-month, and 12-month follow-up. After screening, three studies and one abstract with analyzable data were included. The meta-analysis showed statistically significant reductions in IOP and number of glaucoma medications used at all time points. Though the Trabectome as a solo procedure appears to lower IOP and reduces the number of glaucoma medications, more high-quality studies are required to make definitive conclusions. The difficulty of obtaining evidence may be one of the many obstacles that limit a full understanding of the potential safety and/or efficacy benefits compared to standard treatments. The time has come for a thoughtful and integrated approach with stakeholders to determine optimal access to care strategies for our patients.

Doctor-patient communication, health-related beliefs, and adherence in glaucoma - Friedman, DS; Hahn, SR; Gelb, L; Tan, J; Shah, SN; Kim, EE; Zimmerman, TJ; Quigley, HA (OPHTHALMOLOGY, 2008)
Objective: To use multiple data sources to determine drivers of patient adherence to topical ocular hypotensive therapy. Design: Retrospective database and chart reviews in combination with prospective patient surveys. Diverse medical environments where insured patients in the research database seek care. Participants: Three hundred patients with a new claim diagnosis for open-angle glaucoma who initially were prescribed one of three prostaglandins and 103 physicians participating in the same medical plans. Methods: A structured interview addressing self-reported adherence, experiences with medication, communication with the physician, and health-related beliefs associated with adherence behavior was administered to surveyed patients. Phone interviews were conducted with participating ophthalmologists. Main Outcome Measure: Of adherence, medication possession ratio. Results: Eight variables were associated independently with a lower medication possession ratio: (1) hearing all of what you know about glaucoma from your doctor (compared with some or nothing); (2) not believing that reduced vision is a risk of not taking medication as recommended; (3) having a problem paying for medications; (4) difficulty while traveling or away from home; (5) not acknowledging stinging and burning; (6) being nonwhite; (7) receiving samples; and (8) not receiving a phone call visit reminder. The multivariate model explained 21% of the variance. Conclusions: These findings indicate that doctor-patient communications and health-related beliefs of patients contribute to patient adherence. Patient learning styles that are associated with less concern about the future effects of glaucoma and the risks of not taking medications are associated with lower adherence. Specifically, knowledge about potential vision loss from glaucoma is a critical element that tends to be missed by more passive doctor-dependent patients who tend to be poorly adherent. These findings suggest that educational efforts in the office may improve patient adherence to medical therapies.

A gap analysis approach to assess patient persistence with glaucoma medication - Lee, PP; Walt, JG; Chiang, TH; Guckian, A; Keener, J (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2007)
PURPOSE: To develop an alternative method for analysis of patient persistence with prescribed medications using the prostaglandin class of intraocular pressure (IOP)-lowering drugs as a model. DESIGN: A retrospective study of prescription refill patterns. METHODS: Patients with a pharmacy claim for a 2.5 ml bottle of latanoprost, travoprost, or bimatoprost between September 1, 2002 and December 31, 2002 were identified from a retail pharmacy database and were followed up for 12 months. Three separate analyses defined gaps in therapy as spans in excess of 45, 60, or 120 days without a refill for the same medication. Patients were categorized by the number of gaps in therapy and the Cumulative length of gaps. A Kaplan-Meier analysis was conducted using a 120-day allowable refill period. RESULTS: For refill periods of 45, 60, and 120 days, 10.6%, 28.6%, and 77.5% of patients, respectively, had no gaps in therapy, and 32.6%, 53.4%, and 86.5%, respectively, had 30 days or fewer off therapy annually. According to the 45-day threshold analysis, 50.7% of patients had three or more gaps vs 18.5% in the 60-day analysis and none in the 120,day analysis. The KaplanMeier curve shows 88.6% and 76.1% of patients were persistent for 120 days and one year, respectively. CONCLUSIONS: Compared with Kaplan-Meier survival curves, the gap analysis approach may better parallel clinical experience with patient persistence, in which patients stop and restart medications for a variety of reasons over time. This method also may help to identify avenues for investigation of lack of persistency among many patients.

Newly Diagnosed Primary Open-Angle Glaucoma Randomized to 2 Trabecular Bypass Stents or Prostaglandin: Outcomes Through 36 Months - Vold, SD; Voskanyan, L; Tetz, M; Auffarth, G; Masood, I; Au, L; Ahmed, IIK; Saheb, H (OPHTHALMOLOGY AND THERAPY, 2016)
To examine outcomes through 36 months in phakic eyes with newly diagnosed primary open-angle glaucoma (POAG) na < ve to therapy randomized to treatment with two trabecular micro-bypass stents or topical prostaglandin. Subjects with POAG na < ve to therapy, with intraocular pressure (IOP) ae 21 and ae 40 mmHg, were randomized to implantation of two stents or travoprost. Additional medication was to be prescribed post-treatment for elevated IOP or glaucomatous optic nerve findings. Of 101 randomized subjects, 100 subjects were followed for 24 months and 73 subjects were followed for 36 months. Follow-up on all subjects is ongoing. In this randomized cohort of 101 POAG subjects, 54 subjects underwent 2-stent surgery and 47 received topical travoprost. Mean pre-treatment IOP was 25.5 +/- 2.5 mmHg in stent-treated eyes and 25.1 +/- 4.6 mmHg in medication-treated eyes. By 3 years, mean IOP was 14.6 mmHg in stent eyes (with medication added in 6 eyes) and 15.3 mmHg in travoprost eyes (with a second medication added in 11 eyes). In the subset of eyes that did not require additional medical therapy, mean IOP was 14.5 mmHg and 15.7 mmHg in the respective groups. Ninety-one percent of stent eyes had 3-year IOP ae 18 mmHg without additional therapy (62% ae 15 mmHg) and 79% of travoprost eyes had 3-year IOP ae 18 mmHg (21% ae 15 mmHg). Safety was favorable in both groups. In this prospective, randomized comparison of subjects with newly diagnosed POAG na < ve to therapy, substantial IOP reduction with a favorable low complication rate was shown through 3 years after either 2 trabecular stents implanted as the sole procedure or topical travoprost therapy. These data suggest 2-stent implantation may be a viable initial treatment option comparable to topical prostaglandin in newly diagnosed POAG patients. Trial registration: ClinicalTrials.gov identifier, NCT01443988. Glaukos Corporation, Laguna Hills, CA.

Impact of a Brief Educational Intervention on Glaucoma Persistence: A Randomized Controlled Clinical Trial - Djafari, F; Lesk, MR; Giguere, CE; Siam, G; Freeman, EE (OPHTHALMIC EPIDEMIOLOGY, 2015)
Purpose: To determine whether two sessions of a glaucoma educational intervention resulted in better persistence to glaucoma eye drop therapy compared to normal care.Methods: A total of 165 patients newly diagnosed with glaucoma who required eye drop therapy were recruited into a randomized clinical trial from the glaucoma clinic at Maisonneuve-Rosemont Hospital in Montreal, Canada. Patients were randomized to either an immediate intervention or normal care. The intervention consisted of two 60-90 minute sessions of education on glaucoma and its management, given in a small group format by a non-practicing ophthalmologist. Persistence to glaucoma medication was examined for 1 year by the use of Hospital medical records and by pharmacy claims records from the Regie de l'assurance maladie du Quebec (Quebec Health Insurance Program). A questionnaire was administered, and medication possession ratio calculated. The primary outcome was persistence, defined as having medication available at least 75% of the time. Secondary outcomes included eye drop instillation technique and perception of the importance of eye drop therapy.Results: The intervention group achieved better persistence to eye drop therapy, as 77% of controls and 89% of people receiving the intervention were persistent (p=0.049). The intervention also resulted in better eye drop instillation technique (p<0.001) and greater perception of the importance of eye drop therapy (p<0.001).Conclusions: Brief instructional sessions offered to newly diagnosed glaucoma patients can result in better persistence rates over 1-year follow-up. Strategies to permanently offer these types of initiatives should be considered.

INDICATIONS AND EFFICACY OF COMBINED TRABECULECTOMY AND EXTRACAPSULAR CATARACT-EXTRACTION WITH INTRAOCULAR-LENS IMPLANTATION IN CATARACT PATIENTS WITH COEXISTING OPEN-ANGLE GLAUCOMA - STORRPAULSEN, A; PERRIARD, A; VANGSTED, P (ACTA OPHTHALMOLOGICA SCANDINAVICA, 1995)
In an observational study 19 eyes with cataract and coexisting primary open angle glaucoma were scheduled to undergo combined procedure with ECCE-IOL and trabeculectomy. The aim of the present study was to investigate the results and the efficacy of combined surgery, when we extended the indication for surgery. Thus the surgical decision making was not based solely upon IOP readings, but also involved social/psychological factors. Median decrease in IOP (IOPpost - IOPpre) was significant through a 12-month observation period, p < 0.001. The number of medications dropped from 1.74 to 0.21, p < 0.01. Complication rate during operation and in the postoperative follow-up period was low. We conclude that it seems justified to extend the indication for combined surgery in cataract patients with coexisting open angle glaucoma in case of uncontrolled IOP, poor compliance, inability of sufficient medical care, or unacceptable medication. We recommend careful monitoring of the early postoperative IOP, even if hypotensive agents are given prophylactically.

A three-month, multicenter, double-masked study of the safety and efficacy of travoprost 0.004%/timolol 0.5% ophthalmic solution compared to travoprost 0.004% ophthalmic solution and timolol 0.5% dosed concomitantly in subjects with open angle glaucoma or ocular hypertension - Hughes, BA; Bacharach, J; Craven, ER; Kaback, MB; Mallick, S; Landry, TA; Bergamini, MVW (JOURNAL OF GLAUCOMA, 2005)
Purpose: The primary objective of this study was to compare the intraocular pressure (IOP)-lowering efficacy of travoprost 0.004%/timolol 0.5% fixed combination to the concomitant administration of travoprost 0.004% (TRAVATANg) and timolol 0.5% in subjects with open angle glaucoma or ocular hypertension. Methods: This was a randomized, multicenter, double-masked, active-controlled, parallel group study. Three hundred sixteen patients with open angle glaucoma or ocular hypertension were randomly assigned to travoprost 0.004%/timolol 0.5% ophthalmic solution fixed combination once daily in the morning or concomitant administration of timolol 0.5% once daily in the morning and travoprost 0.004% ophthalmic solution once daily in the evening. The efficacy and safety of the fixed combination were compared with concomitant therapy over three months. The primary efficacy outcome measure was mean intraocular pressure. Results: Both travoprost 0.004%/timolol 0.5% fixed combination and the concomitant administration of travoprost 0.004% and timolol 0.5% produced statistically significant reductions from baseline in IOP, with mean IOP ranging from 15.2 to 16.5 mm Hg in the patients using travoprost 0.004%/timolol 0.5% fixed combination compared with 14.7 to 16.1 mm Hg in the concomitant group. The upper 95.1% confidence limit for the differences in mean IOP (fixed combination minus concomitant) was <= 1.5 mm Hg at 7 of 9 visits, including all three 8 AM time points, 24-hours post-dose. Mean IOP reductions from baseline ranged from 7.4 to 9.4 mm Hg in the fixed combination group compared with 8.4 to 9.4 mm Hg with concomitant therapy. Safety analysis demonstrated equivalent safety between the two treatment groups. Conclusions: A fixed combination of travoprost 0.004% and timolol 0.5% produced clinically relevant IOP reductions in patients with open angle glaucoma or ocular hypertension that were comparable to concomitant therapy with its components. Safety and tolerability of the fixed combination were also equivalent to concomitant therapy. Travoprost 0.004%/timolol 0.5% fixed combination offers IOP reduction equivalent to concomitant therapy, with potential benefits that include convenience (fewer bottles and drops per day), improved compliance, cost savings (based on fewer co-payments), and elimination of potential washout effects.

A 6-month assessment of bimatoprost 0.03% vs timolol maleate 0.5%: hypotensive efficacy, macular thickness and flare in ocular-hypertensive and glaucoma patients - Martin, E; Martinez-De-La-Casa, JM; Garcia-Feijoo, J; Troyano, J; Larrosa, JM; Garcia-Sanchez, J (EYE, 2007)
Aim: To compare 6 months of treatment with bimatoprost and timolol in terms of their hypotensive efficacy and secondary effects, including changes in macular thickness and the inflammatory reaction induced in the anterior chamber. Methods: A prospective, randomized, parallel-group trial performed on 30 eyes of 30 patients per group. The main outcome measure was the difference between the IOP value taken between the baseline visit and the 6-month-visit. Macular thickness determined through optical coherence tomography and anterior chamber inflammation estimated using the laser flare meter was also evaluated. Adverse events were recorded during the study period. Results: Bimatoprost treatment gave rise to a significantly lower mean IOP than timolol in all follow-up visits as from the first month (P = 0.05). Bimatoprost achieved high percentage IOP reductions from baseline in a significantly higher proportion of patients (P = 0.05). Macular thickness and anterior chamber flare failed to vary significantly both between the two groups and within each group during the 6-month evaluation (P > 0.05). Conclusions: Bimatoprost 0.03% once daily showed a greater efficacy then timolol 0.05% twice daily in patients with elevated IOP. No significant differences were detected in macular thickness or anterior uveitis using optical coherence tomography and laser flare photometry.

The effect of glaucoma treatment using high-intensity focused ultrasound on total and corneal astigmatism: a prospective multicentre study - Marques, RE; Sousa, DC; Vandewalle, E; Somers, A; Melamed, S; Nardi, M; Figus, M; Stalmans, I; Pinto, LA (ACTA OPHTHALMOLOGICA, 2020)
Purpose Ultrasound cycloplasty (UCP) acts through the selective coagulation of the ciliary body using high-intensity focused ultrasound (HIFU) technology. The aim of this study was to investigate whether the application of ultrasound beams targeting the ciliary body using an external probe influences astigmatism. Methods Multicentre, prospective, single-arm, open-label study in adult patients with primary open-angle glaucoma and moderately uncontrolled intraocular pressure (IOP) under glaucoma medication. The primary outcome was induced corneal astigmatism, calculated from topography, and assessed statistically through vector analysis. Secondary outcomes included induced total astigmatism and mean changes from baseline in best-corrected visual acuity (logMAR) and IOP. Subgroup analysis was performed to assess the impact of device centring on corneal and total induced astigmatism. Results Fifty eyes were enrolled. Mean age was 69.6 +/- 11.3 years. At 1, 3 and 6 months postprocedure, HIFU-induced corneal astigmatism was 0.88 D x 93 degrees, 0.87 D x 106 degrees and 1.16 D x 97 degrees, respectively, while induced total astigmatism was 0.62 D x 103 degrees, 0.42 x 106 degrees and 0.39 x 107 degrees. By the last follow-up, the percentage of patients with <0.50, <1.00, <1.50 and <2.00 D of induced corneal versus total astigmatism was 8.3% versus 46%, 29% versus 66%, 62.5% versus 88% and 79% versus 94%. Visual acuity was statistically significantly impaired at 1 month, but no difference remained by 3 and 6 months postprocedure. Conclusion Ultrasound cycloplasty procedure is associated with increased corneal astigmatism. However, its impact on total refractive astigmatism is less pronounced.

Comparison of EX- PRESS Shunt and Trabeculectomy With Mitomycin- C in Congenital and Juvenile Glaucoma - Nash, DL; Crouch, ER; Crouch, ER (JOURNAL OF GLAUCOMA, 2017)
) Purpose: To compare efficacy and safety of EX-PRESS mini glaucoma shunt (Alcon) and trabeculectomy with mitomycin-C (MMC) in the management of pediatric glaucoma. Methods: The authors retrospectively reviewed patients from a single pediatric ophthalmology practice with either congenital or juvenile glaucoma who underwent surgical treatment with either trabeculectomy or EX-PRESS shunt insertion with MMC. Postoperative intraocular pressure at 6, 18, and 36 months, medication requirements, visual acuities, postoperative interventions, complications, and noncompliance with medications or follow-up was reviewed. Results: A total of 42 cases of glaucoma with either trabeculectomy or EX-PRESS shunt were identified for review (n trabeculectomy = 25, n EX-PRESS = 17). At 6 months, 62.5% of trabeculectomies and 94.1% of EX-PRESS shunts met criteria for success (P = 0.0281). At 18 months, 38.1% of trabeculectomies and 81.3% of EX-PRESS shunts met criteria for success (P = 0.0178). At 36 months, trabeculectomies had a success rate of 33.3% versus 66.7% for EX-PRESS shunts (P = 0.321). The average decrease in medications postoperatively was 0.375 and 1.63 for trabeculectomy and EX-PRESS shunt, respectively (P = 0.06). Preoperative visual acuities compared with postoperative best-corrected visual acuities before additional surgery demonstrated a slight average worsening of 0.11 logMAR in trabeculectomy patients and an average improvement of 0.56 logMAR in EX-PRESS shunt patients (P = 0.0037). Conclusions: In this review, patients with pediatric glaucoma managed with EX-PRESS shunt with MMC compared with trabeculectomy with MMC appear to have better intraocular pressure control, better visual acuities, and fewer complications and reoperations.

Alabama Screening and Intervention for Glaucoma and Eye Health Through Telemedicine (AL-SIGHT): Study Design and Methodology - Rhodes, LA; Register, S; Asif, I; McGwin, G; Saaddine, J; Nghiem, VH; Owsley, C; Girkin, CA (JOURNAL OF GLAUCOMA, 2021)
Precis: This paper presents the methods and protocol of a community-based telemedicine program to identify glaucoma and other eye diseases. Purpose: To describe the study rationale and design of the Alabama Screening and Intervention for Glaucoma and eye Health through Telemedicine project. Methods: The study will implement and evaluate a telemedicine-based detection strategy for glaucoma, diabetic retinopathy, and other eye diseases in at-risk patients seen at federally qualified health centers located in rural Alabama. The study will compare the effectiveness of the remote use of structural and functional ocular imaging devices to an in-person examination. Study participants will receive a remote ocular assessment consisting of visual acuity, intraocular pressure, visual field testing, and imaging of the retina and optic nerve with spectral-domain optical coherence tomography, and the data will be reviewed by an ophthalmologist and optometrist. It will also compare the effectiveness of financial incentives along with a validated patient education program versus a validated patient education program alone in improving follow-up adherence. Finally, cost and cost-effectiveness analyses will be performed on the telemedicine program compared with standard in-person care using effectiveness measured in numbers of detected eye disease cases. Conclusions: The study aims to develop a model eye health system using telemedicine to prevent vision loss and address eye health among underserved and at-risk populations.

A Geodemographic Service Coverage Analysis of Travel Time to Glaucoma Specialists in Florida - Rothman, AL; Stoler, JB; Vu, DM; Chang, TC (JOURNAL OF GLAUCOMA, 2020)
Precis: Approximately 1 in 9 Florida residents over the age of 65 years (438,642 people) live more than an hour away from a glaucoma specialist, which represents a significant barrier to care. Purpose: To describe access to glaucoma care for Florida's elderly population using travel time to American Glaucoma Society (AGS) member offices. Methods: For this cross-sectional service coverage analysis, a list of AGS member locations was extracted from the AGS website, and addresses were geocoded using ArcGIS Online. Driving time regions were created using the service area tool in ArcGIS Pro 2.4 and overlaid with 2010 United States Census and 2016 American Community Survey data for all Florida residents age 65 or older. Results: Fifty-eight AGS member providers with 65 locations were identified and geocoded. There were 3,797,625 individuals aged over 65 years in Florida, of which 1,153,320 (30.4%) lived within 15 minutes of driving time from an AGS provider's office, 2,586,825 (68.1%) within 30 minutes, 3,358,983 (88.4%) within 60 minutes, and 3,491,815 (91.9%) within 120 minutes. The areas with the lowest access include rural areas near Lake Okeechobee and the Florida Panhandle. The population living beyond a 60-minute drive was more likely to be White, non-Hispanic and older, but less likely to be living below the federal poverty level or receiving public assistance than the population living within a 60-minute drive. Conclusions: There is a significant travel burden for the elderly community of Florida to reach AGS providers. Additional studies could help identify other social barriers to accessing glaucoma providers in Florida and beyond in an effort to improve patient compliance and, ultimately, vision outcomes.

Cost of the medical management and prescription pattern for primary open angle glaucoma (POAG) in Ghana-a retrospective cross-sectional study from three referral facilities - Ocansey, S; Kyei, S; Diafo, A; Darfor, KN; Boadi-Kusi, SB; Aglobitse, PB (BMC HEALTH SERVICES RESEARCH, 2016)
Background: Glaucoma is the leading cause of irreversible blindness globally, and treatment involves considerable cost to stakeholders in healthcare. However, there is infrequent availability of cost information and patterns of management, especially in developing countries. This study determined the cost of the medical management of POAG, adherence, and pattern of medication prescription in Ghana. Methods: A retrospective cross-sectional study involving 891 Primary Open Angle Glaucoma (POAG) cases seen in the year 2012 at three referral facilities. Demographics, ocular history, resource consumption, medication, test, surgery and other related cost were extracted from 84 patients who had fully complied with their treatment to calculate total cost (TC) based on 2012 estimates. Glaucoma drugs prescribed to patients who had adhered to all their review visits within the period evident from case folders were recorded and analysed for the prescription pattern. Results: Out of 891 POAG cases seen in 2012, 351(39.4 %) attended all the required review visits, but only 84 (9.4) had fully and continually adhered to all their treatment regimes. They comprised 41(48.8 %) males and 43(51.2 %) females with a mean age of 65 +/- 14.8. Majority of the respondents were elderly above 60 year of age (65.5 %). The total estimated cost for the 84 cases in the year was GH cent 81,237 ($ 40,619), comprising GH cent 72,193 ($ 36,097) direct medication cost and GH cent 9,045 ($ 4,523) direct non-medication cost (surgery and test cost), and an average of GH cent 967 ($ 484) for a mean visit of 5.6 +/- 1.1 in the year. A total of 673 glaucoma medications had been prescribed for 351 patients for the year, with timolol being the most prescribed (64.19 %) and monotherapy as the most adopted form of therapy (61.06 %). Age and income showed concurrent increase with cost (P <= 0.05). Conclusions: Cost of managing glaucoma constitutes a substantial financial burden and influenced the pattern of medication prescription.

Life Experiences of Patients With Glaucoma: A Phenomenological Study - Iyigun, E; Tastan, S; Ayhan, H; Coskun, H; Kose, G; Mumcuoglu, T (JOURNAL OF NURSING RESEARCH, 2017)
Background: Studies that describe the experiences of patients with glaucoma from different cultures may help health professionals gain a broader perspective on this issue. Currently, few qualitative studies describe how patients with glaucoma in Turkey cope with daily life. Purpose: The aim of this study was to explore the experiences of patients with glaucoma. Method: This descriptive phenomenological study used purposive sampling to enroll 20 patients with glaucoma. A qualitative, in-depth, face-to-face interview technique was used to collect data during January and February 2014. The data were analyzed using to the Van Kaam method. Results: Seven themes were identified, including confirming the diagnosis by acute symptoms or unrelated symptoms, grateful to God for having a non-life-threatening disease, feeling happy after receiving more accurate information, coping with the disease by using eye drops and attending follow-up examinations regularly, managing daily life to avoid further damage to eyesight, emotional reactions related to going blind, and urging family members or friends to attend regular glaucoma checkups. Conclusions: Patients with glaucoma experience physiological and psychological problems throughout the course of their disease. Being informed and cultural practices such as "praising God" and "resignation" helped patients cope with the disease. Furthermore, because of the cultural characteristic of social collectivism, participants acted to protect the health of others by informing them about glaucoma. Implications for Practice: Understanding the experiences of patients with glaucoma is important for nursing practice. Nurses should be encouraged to take a greater role in the care of patients with glaucoma by becoming the primary source of glaucoma disease, treatment, and care-related information.

SELF-TONOMETRY - TECHNICAL ASPECTS OF CALIBRATION AND CLINICAL-APPLICATION - GROENHOFF, S; DRAEGER, J; DEUTSCH, C; WIEZORREK, R; HOCK, B (INTERNATIONAL OPHTHALMOLOGY, 1992)
Self-tonometry could be established as an important diagnostic tool in the early diagnosis and follow-up of glaucoma provided that a self-tonometer is precise, safe and easy to use. Furthermore, it has to comply with the legal standards for tonometer calibration. A new software-controlled detection system for the self-tonometer permits the evaluation of external factors during the measurement which influence the precision of the tonometric readings. The updated version of the self-tonometer (ST) was compared to the Draeger hand-held applanation tonometer (HAT) in a clinical study with 82 patients (151 eyes). The results show a regression line characterized by a slope of 0.99, an y interception of 1.41, a correlation coefficient of 0.96 and a standard deviation for the ST readings of +/- 1.78 mmHg. Self-tonometry improves the IOP monitoring as well as patient compliance and therefore is a potential diagnostic tool in the management of glaucoma.

Predictors of Success in Selective Laser Trabeculoplasty: Data From the Lausanne Laser Trabeculoplasty Registry - Elahi, S; Rao, HL; Dumitru, A; Mansouri, K (JOURNAL OF GLAUCOMA, 2020)
Purpose: The purpose of this study was to determine the factors associated with the outcomes of selective laser trabeculoplasty (SLT). Patients and Methods: This was a database analysis (Lausanne Laser Trabeculoplasty Registry) of patients who had SLT between 2015 and 2017. Exclusion criteria were age below 40 years and diagnosis other than ocular hypertension and open-angle glaucoma. Intraocular pressure (IOP) and number of medications were recorded before and at various follow-ups after laser treatment. Success was defined as "complete" if an IOP reduction of at least 20% was observed at a given time, and "qualified" if any reduction of IOP was observed with either at least a 20% difference from baseline or a reduction in IOP-lowering medications. Associations of complete and qualified success with patients' baseline characteristics, laser settings, and clinical examination findings were studied using multivariate regression and survival analysis. Results: A total of 170 eyes (126 patients) were included. Mean age was 68.3 +/- 12.2 years and 57.9% of the study cohort were female individuals. Average baseline IOP was 18.7 +/- 4.8 mm Hg, and average IOP reduction was 3.3 +/- 4.3 (-17.6% from baseline) and 3.5 +/- 3.9 mm Hg (-18.7% from baseline) at years 1 and 2, respectively. Male sex [odds ratio (OR)=2.79,P=0.02], baseline IOP (OR=1.15,P<0.01), and medical treatment before SLT (OR=2.57,P=0.03) were positive predictors of success. Total energy was associated with the duration of success. SLT outcome was strongly correlated to the outcome of the fellow eye, which represented the strongest predictor (OR=17.33,P<0.01). Conclusions: SLT achieved good IOP-lowering in a majority of patients with mild-to-moderate glaucoma, while it was inefficient in up to 35% of eyes. SLT success in the fellow eye was a strong predictive factor.

The Glaucoma Intensive Treatment Study (GITS), a randomized clinical trial: design, methodology and baseline data - Bengtsson, B; Heijl, A; Johannesson, G; Andersson-Geimer, S; Aspberg, J; Linden, C (ACTA OPHTHALMOLOGICA, 2018)
Purpose The primary objective of the ongoing Glaucoma Intensive Treatment Study (GITS) is to evaluate the effectiveness of immediate intensive treatment in comparison with the commonly recommended stepped regimen on the predicted visual field. The two treatment arms are also being compared regarding quality of life (QoL), intraocular pressure (IOP) reduction, frequency of reported side-effects, adverse events and adherence to prescribed treatment. DesignParticipantsA randomized, two-centre, prospective open-labelled treatment trial for open-angle glaucoma. Individuals aged 40-78years with previously untreated and newly diagnosed glaucoma with early to moderate visual field loss were eligible. MethodsResultsPatients were randomized to initial treatment either using drug monotherapy in accordance with common glaucoma guidelines or using a more intensive approach including eyedrops containing drugs from three different classes combined with 360 degrees laser trabeculoplasty. The patients are to be followed for 5years at visits including standard automated perimetry, optical coherence tomography (OPT) and tonometry. Change of treatment is allowed and decided upon jointly with the patient as in conventional glaucoma management. Main outcome: The estimated predicted preserved visual field and QoL at end of expected lifetime. A total of 242 patients, 45% females, mean age 68years, were randomized. The median untreated IOP was 24mm Hg, and the median visual field index (VFI), indicating the percentage of a full field, was 92%. ConclusionGlaucoma Intensive Treatment Study is a clinical trial in which two groups of patients randomized to different initial intensities of IOP-reducing treatment are being compared with regard to rate of visual field progression and prediction of serious glaucomatous visual field loss at estimated at end of life.

Patterns of adherence to NICE Glaucoma Guidance in two different service delivery models - Chawla, A; Patel, I; Yuen, C; Fenerty, C (EYE, 2012)
Purpose To assess adherence patterns to the UK National Institute of Health and Clinical Excellence (NICE) guidelines on glaucoma management (2009) in a tertiary referral centre shared care setting and in a district general hospital (DGH) setting. Method We performed a retrospective case note analysis of 200 patients from two centres between January and June 2010. The two centres involved were a consultant-guided teaching hospital optometry-led shared care setting (setting 1) and a consultant-led DGH clinic setting (setting 2). The main outcome measures were compliance with eight of the main NICE guidelines on glaucoma diagnosis and management (2009). Results Both centres showed good adherence to the guidelines regarding the choice of initial treatment (96% vs 100%, settings 1 and 2, respectively) and arranging appropriate monitoring intervals (92% vs 86%). However, significant differences were seen when assessing whether an optic disc image was obtained at the initial visit (74% vs 10%), whether an appropriate initial assessment was performed (96% vs 58%), whether patients' review interval complied with the NICE guidance regardless of hospital cancellations (92% vs 66%), and whether concordance with medication was checked (88% vs 24%) (settings 1 and 2, respectively, P <0.01-Fisher's exact test). Conclusion Our study provides evidence to suggest that a hospital-based shared care service with trained optometrists using assessment sheets compares favourably to non-specialist glaucoma care delivered by ophthalmologists. Eye (2012) 26, 1412-1417; doi:10.1038/eye.2012.171; published online 31 August 2012

Anti-Vascular Endothelial Growth Factor Therapy for Diabetic Retinopathy: Consequences of Inadvertent Treatment Interruptions - Wubben, TJ; Johnson, MW; Sohn, EH; Peairs, JJ; Kay, CN; Kim, SJ; Gardner, TW; Paulus, YM; Zacks, DN; Steinle, NC; Avery, RL; Berrocal, MH; et al. (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2019)
PURPOSE: To illustrate that patients with diabetic retinopathy who are treated exclusively with anti-vascular endothelial growth factor (VEGF) therapy and have an interruption in treatment may experience marked progression of disease with potentially devastating visual consequences. DESIGN: Retrospective, multicenter, case series. METHODS: Retrospective review of patients treated exclusively with anti-VEGF therapy for proliferative diabetic retinopathy (PDR) or nonproliferative diabetic retinopathy (NPDR), with or without diabetic macular edema (DME), and temporarily lost to follow-up. Baseline disease characteristics, cause and duration of the treatment interruption, and resulting disease progression, complications, and outcomes were assessed. RESULTS: Thirteen eyes of 12 patients with type 2 diabetes were identified. The mean age was 57 +/- 10 years, and 50% were women. Anti-VEGF therapy was indicated for PDR with DME in 7 (54%) eyes, PDR without DME in 3 (23%) eyes, and moderate to severe NPDR with DME in 3 (23%) eyes. Eight eyes had visual acuity (VA) of 20/80 or better before treatment interruption. The median duration of treatment hiatus was 12 months. Reasons for treatment interruption included intercurrent illness (31%), noncompliance (31%), and financial issues (15%). Complications upon follow-up included vitreous hemorrhage (9 eyes), neovascular glaucoma (5 eyes), and traction retinal detachment (4 eyes). Despite treatment of these complications, 77% of eyes lost >= 3 lines of VA, with 46 /o of eyes having a final VA of hand motion or worse. CONCLUSIONS: Diabetic patients are subject to significant lapses in follow-up because of illness, financial hardship, or noncompliance. In patients with diabetic retinopathy, especially PDR, who are managed with anti-VEGF therapy alone, unintentional treatment interruptions can result in irreversible blindness. (Am J Ophthalmol 2019;204:13-18. (C) 2019 Elsevier Inc. All rights reserved.)

The impact of educational workshops on individuals at risk for glaucoma in the Philadelphia Glaucoma Detection and Treatment Project - Johnson, DM; Stratford, S; Shyu, AP; Sembhi, H; Molineaux, J; Reamer, C; Spaeth, GL; Myers, JS; Hark, LA; Katz, LJ; Waisbourd, M (PATIENT EDUCATION AND COUNSELING, 2016)
Objectives: The purpose of this study was to investigate the impact of educational workshops, led by community health educators, on the level of knowledge, perceived risk of glaucoma, and rate of attendance in a subsequent glaucoma detection examination. Methods: Participants attended an educational workshop about glaucoma and completed an 8-question pre- and post-test to assess knowledge. A paired samples t-test assessed mean differences in composite pre- and post-test scores, correct responses for each question, and perceived risk of glaucoma after the workshop. Results: Seven hundred and seven (707) pre- and post-test surveys were completed. There was a significant increase in the level of knowledge about glaucoma as reflected in the pre- and post-test composite scores (M = 3.86, SD = 1.95 vs. M = 4.97, SD = 1.82, P < 0.001). In the 5 largest community sites, 44% (n = 221/480) of the participants who attended an educational workshop scheduled a glaucoma detection examination appointment and 76% (n = 160/211) of these participants completed this eye examination in the community setting. Conclusions: Educational workshops increased knowledge and awareness about glaucoma and were helpful in recruiting patients for community-based glaucoma detection examinations. Practice implications: We recommend including educational workshops when conducting community-based outreach programs. (C) 2015 Elsevier Ireland Ltd. All rights reserved.

Topical Fk506 in inflammatory corneal and conjunctival diseases - A pilot study - Reinhard, T; Reis, A; Mayweg, S; Oberhuber, H; Mathis, G; Sundmacher, R (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2002)
Background: Topical corticosteroids are the only effective measure in serious inflammatory corneal and conjunctival diseases. Although results obtained with topical cyclosporin A are encuraging it is not effective in all patients. The mode of action of Fk506 is similar to that of cyclosporin A, i.e. it exerts an inhibitory effect on transcription of interleukin 2 in T lymphocytes. The immunosuppressive potential of Fk506, however, is much larger. Furthermore, it penetrates more easily into cornea and conjunctiva. To find out whether the theoretical advantages of topical Fk506 can be translated into clinical practice, a selected group of patients refractory to conventional therapy was treated in this pilot study. Patients and methods: Fk506 0.06% was administered initially three times daily in 15 patients with atopic blepharokeratoconjunctivitis, Mooren's ulcer, ocular pemphigoid, Thygeson's superficial punctate keratitis, nummular adenoviral keratitis, graft-versus-host reaction of the conjunctiva and steroid response glaucoma after penetrating keratoplasty. Results: Within a follow-up of 26 15 weeks improvement was recorded in 5/15 patients and stabilization in 5/15 patients. In two patients progression of the disease was noted (one patient with progression of ocular pemphigoid, another patient with suspected automutilation). Premature withdrawal the drug was judged to be necessary in two patients with ocular surface disorders and in one patient with non-compliance. Conclusions: Topical Fk506 seems to be a promising new immunosuppressive drug for patients with atopic blepharokeratoconjunctivitis, Thygeson's superficial punctate keratitis and nummular adenoviral keratitis. Exact efficacy in these and other corneal and conjunctival inflammatory diseases has to be determined in randomised clinical studies. Before these studies may start the risk of side-effects must be reduced via an improvement of the drops.

The long-term safety and efficacy of brinzolamide 1.0% (Azopt) in patients with primary open-angle glaucoma or ocular hypertension - March, WF; Ochsner, KI; Brinzolamide Long-Term Therapy Stu (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2000)
PURPOSE: Oral carbonic anhydrase inhibitors used to treat glaucoma have significant systemic side effects. Brinzolamide 1.0%, a new topical ocular carbonic anhydrase inhibitor, is effective apparently without significant systemic side effects. This study was performed to establish the long-term safety and efficacy of brinzolamide 1.0% two and three times daily for primary open-angle glaucoma and ocular hypertension. METHODS: An 18-month, multicenter, double-masked, parallel, controlled study was conducted. Patients were randomized to brinzolamide two or three times daily or timolol 0.5% twice daily in a 2:2:1 ratio (n = 150, 153, and 75, respectively). Intraocular pressure was measured at 8:00 AM at eligibility and months 1, 3, 6, 9, 12, 15, and 18. Efficacy was based on intraocular pressure reduction from baseline. Safety was also evaluated. RESULTS: All regimens produced clinically relevant and statistically significant (P < .05) intraocular pressure reductions from baseline. Mean changes in intraocular pressure trough measurements ranged from -2.7 to -3.9 mm Hg with brinzolamide twice-daily dosing and -2.8 to -3.8 mm Hg three times daily dosing compared with -4.7 to -5.6 mm Hg with timolol. The intraocular pressure reductions with brinzolamide two and three times daily were clinically and statistically equivalent. One hundred forty-four patients were discontinued from the study after randomization with the most common reasons being the occurrence of an adverse event (46), inadequate intraocular pressure control (23), patient decision unrelated to study medication (11), lost to follow-up (16), and noncompliance (9). Adverse events were nonserious and resolved without sequelae. There were no clinically relevant changes in safety parameters. Brinzolamide produced less ocular discomfort (burning/stinging) than timolol, and total carbonic anhydrase inhibition levels remained below that known to cause systemic side effects. CONCLUSION: Brinzolamide produced significant and equivalent reductions in intraocular pressure when dosed two and three times daily for 18 months. Brinzolamide was safe and well tolerated by patients, with minimal ocular discomfort. (Am J Ophthalmol 2000;129:136-143. (C) 2000 by Elsevier Science Inc. All rights reserved.)

SIDE-EFFECTS OF TOPICAL TREATMENT IN PIGMENTARY GLAUCOMA - LEHTO, I (ACTA OPHTHALMOLOGICA, 1992)
A series of 35 patients with pigmentary glaucoma were asked to report possible side effects of topical glaucoma medication using a multiple-choice questionnaire. Of the 31 patients (89%) returning the forms, 22 (71%) were men and 9 (29%) women with a mean age of 45.1 years, range 23 to 72 years. The mean follow-up time of their glaucoma was 10.7 years, range 2 to 30 years. A mild burning feeling (in 50% in all treatment groups) and redness of the eyes (in 42% treated with timolol alone and in 50% with timolol combined with dipivephrine, pilocarpine or both) were the main complaints, followed by a slight reduction of vision (in 17% in the timolol group and in 56% with combined treatment) and mild watering of the eyes (in 42% of the timolol and in 31% of the combined treatment groups). Twenty-three percent of the patients did not have any side effects from their topical medication. Patients who admitted defaulting their topical treatment once a month amounted to 43% and once a week to 17%. Patients who admitted to never having missed a drop amounted to 40% of the sample; forgetfulness and haste were the main reasons for not applying the drops.

Prospective evaluation of microinvasive glaucoma surgery with trabecular microbypass stents and prostaglandin in open-angle glaucoma - Ahmed, IIK; Katz, LJ; Chang, DF; Dormenfeld, ED; Solomon, KD; Voskanyan, L; Samuelson, TW (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2014)
PURPOSE: To evaluate the intraocular pressure (IOP) lowering effect of 2 trabecular microbypass stents and postoperative travoprost in patients with open-angle glaucoma (OAG) not controlled on 2 medications preoperatively. SETTING: S.V. Malayan Ophthalmology Centre, Yerevan, Armenia. DESIGN: Prospective open-label nonrandomized study. METHODS: This prospective pilot study involved 39 qualified phakic patients with OAG, medicated IOP between 18 mm Hg and 30 mm Hg, and unmedicated baseline (after washout) IOP between 22 mm Hg and 38 mm Hg. Patients received 2 stents (iStent) through a clear corneal incision and were prescribed travoprost starting the night of postoperative day 1. Intraocular pressure, complications, and various safety measures were assessed at examinations through 18 months and planned for every 6 months thereafter until month 60. A washout of medications was performed 13 months postoperatively. RESULTS: All patients achieved an IOP reduction of 20% or more from baseline to 12 months with reduction of 1 medication and with IOP 18 mm Hg or less. Follow-up through 18 months showed that medicated IOP decreased from 22.2 mm Hg +/- 2.0 (SD) on 2 medications preoperatively to 14 mm Hg or less on 1 medication at the postoperative visits. The mean unmedicated IOP decreased from 25.3 +/- 1.8 mm Hg preoperatively to 17.1 +/- 2.2 mm Hg 13 months postoperatively. No intraoperative or serious device-related adverse events occurred. CONCLUSIONS: Patients with OAG treated with 2 trabecular microbypass stents and 1 presumptive postoperative medication achieved a significant and sustained reduction in IOP and medication through 18 months.

Cost Analysis of Commonly used Combination of Drugs in Primary Open Angle Glaucoma - Kumbar, SK; Mirje, M; Moharir, G; Bharatha, A (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2015)
Background: Glaucoma is second cause of blindness in the world. The financial burden on the patient during long-term treatment is immense and affects the compliance to medications, thus visual morbidity. Objective: To analyse economic impact of three commonly used drug combinations (Dorzolamide + Timolol = DT; Brimonidine + Timolol = BT; Latanoprost+ Timolol = LT) in primary open angle glaucoma. Materials and Methods: This observational, prospective study was undertaken at M & J Institute of Ophthalmology, Civil Hospital, Ahmedabad, a western regional institute of Ophthalmology. A total of 257 patients were included in the study. Only101 patients could complete the 6 month follow-up, of which 35, 34 and 32 patients belonged to DT, BT and LT group respectively. Cost of drug, details of the transportation were noted at every visit. Total cost incurred per patient/eye was calculated. Cost effectiveness was calculated by cost per mm Hg IOP (Intra-Ocular Pressure) reduction. Results: Treatment with DT, BT & LT group consumed 8.6%, 4.6% and 7.7% of the per annum income of the family, respectively. Cost of medications per annum (in INR)/eye for DT, BT & LT group were 2562 +/- 15.74, 1544 +/- 32.06, 3876 +/- 73.68 (Mean +/- SEM) respectively. Additional cost of travelling was different for patients coming from Ahmedabad (Locals) and outsiders (patients coming outside Ahmedabad, India). Outsiders has to bear the brunt of higher transport charges, where they spent an average of Rs. 914, 856 & 933 per annum (5 follow-ups), whereas, Locals spent an average of Rs. 104, 112, 100 for DT, BT & LT group respectively. Conclusion: Treatment with BT was found to be most cost-effective among three groups. Drug therapy takes substantial amount from per annum income of family and was an important compliance factor in the treatment of POAG.

Does Training Clinic Nurses to Test Pinhole Visual Acuity as a Screen for Glaucoma Increase Glaucoma Referrals to Eye Care Professionals? A Pilot Study in Malawi - Dean, WH; Courtright, P; Cook, C (OPHTHALMIC EPIDEMIOLOGY, 2012)
Purpose: To test whether general nurses, trained in screening for glaucoma, can increase the number of glaucoma cases seen by eye-care professionals in a rural setting in Africa. Methods: In two districts in Malawi, 87 clinic nurses and two ophthalmic clinical officers were trained in case detection and referral of patients with suspect glaucoma. Data were collected on the number of patients screened and referred over a 12-month period. The clinic nurses and ophthalmic clinical officers received supportive supervision four times during the period and interviews were used to elicit their perspectives on the training and referral procedures. Results: The 87 nurses screened 294 people (mean 3.4 per nurse) and referred 147 (50%) of them. Of the 147 referred, 56 (38%) were seen by the ophthalmic clinical officers who referred 15 (27%) to the ophthalmologist. Only two people were seen by the ophthalmologist. Testing visual acuity in people over 40 years of age was not seen as a priority by primary level clinic nurses. Nurses reported that cost and distance were barriers precluding attendance by patients at the next level. Women were two times less likely to be referred. About one quarter of patients who were offered surgery refused. Fewer than half the patients who had surgery attend for follow-up. Conclusions: Training general nurses to screen for and refer suspect glaucoma cases did not lead to increased glaucoma service delivery. Other strategies to identify high risk patients need to be tested.

Conjunctival Pyogenic Granuloma after Sub-tenon's Block - Lee, SH; Kim, KW; Chun, YS (JOURNAL OF THE KOREAN OPHTHALMOLOGICAL SOCIETY, 2021)
Purpose: We report a case of conjunctival pyogenic granuloma that developed after sub-Tenon's block at the inferotemporal conjunctival quadrant during cataract surgery. Case summary: A 74-year-old male patient with senile cataract, diabetic retinopathy and open-angle glaucoma, who was using a combination of timolol/tafluprost and brimonidine eyedrops, underwent uneventful cataract surgery after sub-Tenon's block at the inferotemporal conjunctival quadrant of his right eye. Moxifloxacin, 1% prednisolone acetate and 0.1% bromfenac sodium hydrate were administered daily for 1 month post-surgery, by which time a pink-colored, oval-shaped granulomatous mass had developed on the inferotemporal conjunctiva, at the site of the sub-Tenon's block. Dexamethasone and antibiotic combination eye drops were administered without resection of the mass, which had markedly regressed after 2 weeks and disappeared completely 6 weeks after treatment. Conclusions: Patients should be informed of the possibility of conjunctival pyogenic granuloma prior to cataract surgery using sub-Tenon's block, and it is important to carefully check the block site and compliance with eyedrops at follow-up visits. Conjunctival pyogenic granuloma can be successfully treated with topical steroids.

Four-Year Outcomes of Two Second-Generation Trabecular Micro-Bypass Stents in Patients with Open-Angle Glaucoma on One Medication - Lindstrom, R; Sarkisian, SR; Lewis, R; Hovanesian, J; Voskanyan, L (CLINICAL OPHTHALMOLOGY, 2020)
Introduction: This study evaluated long-term reductions in intraocular pressure (IOP) and medication following implantation of 2 second-generation trabecular micro-bypass stents (iStent inject (R)) in eyes with open-angle glaucoma (OAG) not controlled on 1 preoperative medication. Material and Methods: In this prospective interventional multi-surgeon study, standalone implantation of 2 iStent inject stents was performed in 57 eyes of 57 subjects with OAG, preoperative IOP of 18-30 mmHg on 1 medication, and preoperative post-washout IOP of 22-38 mmHg The main outcome measures included the proportions of eyes achieving medication-free IOP <= 18 mmHg, IOP <= 15 mmHg, or >= 20% IOP reduction versus preoperative unmedicated IOP. Assessments included IOP, medications, visual acuity, visual field, pachymetry, complications, and interventions. Subjects were followed for 48 months with follow-up continuing in all eyes. Results: At Month 48 (n=57), 95% of eyes achieved an IOP reduction of >= 20% without medication versus preoperative washout IOP; and although they had eliminated medication, 81% of eyes still had an IOP reduction of >= 20% versus preoperative IOP on 1 medication. Mean 48-month unmedicated IOP decreased by 46% to 13.2 +/- 1.6 mmHg vs 24.4 +/- 1 3 mmHg preoperatively (p<0.0001), with 95% of medication-free eyes having IOP <= 18mmHg and 82% having IOP <= 15mmHg Over the course of follow-up, 3 eyes had medication added and 1 eye underwent a secondary glaucoma surgery, and safety parameters were favorable. Discussion: Standalone iStent inject implantation in OAG patients on 1 preoperative medication resulted in average IOP reduction to <= 15 mmHg with the elimination of medication and favorable safety through 48 months.

Cataract and glaucoma surgery in pseudoexfoliation syndrome: a review - Drolsum, L; Ringvold, A; Nicolaissen, B (ACTA OPHTHALMOLOGICA SCANDINAVICA, 2007)
Pseudoexfoliation syndrome is a risk factor in cataract surgery because of the increased weakness of zonular apparatus and reduced pupillary dilatation. The surgical outcome of using phacoemulsi. cation in the central zone, inducing minimal stress on the zonules, inserting a capsular tension ring in selected cases, and stretching the pupil mechanically in eyes with miotic pupils, may turn out to be uneventful in most cases. Postoperative fibrosis with subsequent shrinkage of the capsule is increased in these eyes, and these centripetal forces will further loosen the zonular fibres. Late in-the-bag intraocular lens dislocation is therefore anticipated to become a growing problem in the future. Despite the dysfunctioning of the blood-aqueous barrier in eyes with pseudoex-foliation syndrome, the frequency of postoperative inflammatory reaction is low due to the improvements made in surgical technique and equipment in recent years. Glaucoma frequently occurs in eyes with pseudoexfoliation syndrome. Compared with primary open-angle glaucoma, optic damage is more pronounced in these eyes at the time of diagnosis and response to medical therapy is poorer. Although responses to argon laser therapy and filtering surgery are roughly similar between the two types of glaucoma, there are indications that primary laser trabeculoplasty has a higher success rate in pseudoexfoliation glaucoma than in primary open-angle glaucoma.

Applying RE-AIM to evaluate two community-based programs designed to improve access to eye care for those at high-risk for glaucoma - Sapru, S; Berktold, J; Crews, JE; Katz, LJ; Hark, L; Girkin, CA; Owsley, C; Francis, B; Saaddine, JB (EVALUATION AND PROGRAM PLANNING, 2017)
Introduction: Glaucoma is a leading cause of vision loss and blindness in the U.S. Risk factors include African American race, older age, family history of glaucoma, and diabetes. This paper describes the evaluation of a mobile eye health and a telemedicine program designed to improve access to eye care among people at high-risk for glaucoma. Methods: The RE-AIM (reach, efficacy, adoption, implementation, and maintenance) evaluation framework was used to harmonize indicators. Both programs provided community-based eye health education and eye services related to glaucoma detection and care. Each program reported data on participants and community partners. An external evaluator conducted site visit interviews with program staff and community partners. Quantitative and qualitative data were integrated and analyzed using the RE-AIM dimensions. Discussion: By targeting high-risk populations and providing comprehensive eye exams, both programs detected a large proportion of new glaucoma-related cases (17-19%) a much larger proportion than that found in the general population ( < 2%). The educational intervention increased glaucoma knowledge; evidence that it led people to seek eye care was inconclusive. Conclusions: Evaluation findings from the mobile eye health program and the telemedicine program may provide useful information for wider implementation in public health clinics and in optometrist clinics located in retail outlets.

A multicentre evaluation of the effect of patient education on acceptance of hyperaemia associated with bimatoprost therapy for glaucoma or ocular hypertension - Trattler, W; Noecker, RJ; Earl, ML (ADVANCES IN THERAPY, 2008)
Introduction: The aim of this study was to evaluate the incidence of hyperaemia in patients using bimatoprost and to determine if simple interventions result in increased understanding of glaucoma and hyperaemia. Methods: This was a multicentre, open-label, evaluator-masked clinical trial of 106 patients. Prior to enrolling in the trial, patients were washed out from any ocular hypotensive medications and prescribed bimatoprost daily in the evening for 6 weeks. Patients were randomised to one of two groups: intervention and no intervention. Patients in the intervention group (n=63) were given a fact sheet explaining the importance of reducing intraocular pressure (IOP) and the efficacy of bimatoprost, while patients in the no intervention group (n=43) were instructed only to instil bimatoprost daily and were given no additional instructions. Results: As graded by the masked investigators, conjunctival hyperaemia peaked 1 day after commencing bimatoprost, with a mean of 1.2 (0=none, 0.5=trace, 1=mild, 2=moderate, 3=severe). By day 7, hyperaemia levels were approximately trace (0.79) and continued to decrease throughout the study. There were no significant differences between groups in mean conjunctival hyperaemia at any study visit (P=0.215). At every visit, patients in the intervention group were significantly more likely than patients in the no intervention group to report that lowering IOP was very important for preserving vision (P=0.001). At week 6, 98% of patients in the intervention group reported that IOP-lowering was very important for preserving vision, compared with 76% of patients who did not receive the intervention (P=0.001). Patients in the intervention group were more likely than patients in the no intervention group to be willing to continue to use bimatoprost, despite hyperaemia. This difference was statistically significant at day 1 (P=0.003). Conclusion: Patients were not bothered by the trace-mild hyperaemia associated with bimatoprost therapy. Patient education can improve patient acceptance of a prescribed regimen and potentially increase compliance.

Effect of benzalkonium chloride-free travoprost on intraocular pressure and ocular surface symptoms in patients with glaucoma previously on latanoprost: an open-label study - Lopes, JF; Hubatsch, DA; Amaris, P (BMC OPHTHALMOLOGY, 2015)
Background: Prostaglandin analogs reduce intraocular pressure (IOP) in patients with open-angle glaucoma or ocular hypertension; however, these medications may affect the ocular surface and elicit ocular discomfort when preserved with benzalkonium chloride (BAK). Methods: This was an open-label, single-arm study conducted in Latin America from February 2012 to May 2013. Patients with open-angle glaucoma or ocular hypertension who were intolerant of latanoprost 0.005 % were transitioned to receive once-daily BAK-free travoprost 0.004 % containing polyquaternium-1 (Travatan (R) preserved with POLYQUAD (R) [PQ], Alcon Laboratories, Inc; Fort Worth, TX) for 12 weeks. Mean change in IOP from baseline (primary efficacy endpoint) and the percentage of patients who achieved a target IOP of <= 18 mmHg were evaluated at all on-therapy visits. Ocular hyperemia, patient preference, and self-projected adherence were assessed at week 12. Adverse events (AEs) were monitored throughout the study. Results: All enrolled patients were included in the analysis (n = 191); the majority of patients (90.6 %, n = 173/191) completed the study. Mean (SD) patient age was 67.5 (11.3) years, and mean baseline IOP was 14.8 mmHg. Mean IOP was reduced by 0.94 mmHg at week 6 and by 1.09 mmHg at week 12 (P < 0.001 for both). A greater percentage of patients achieved a target IOP of <= 18 mmHg at week 6 (93.1 %; n = 163/175) and week 12 (93.3 %; n = 166/178) compared with baseline (89.5 %; n = 171/191). There was a 10.5 % increase in the percentage of patients with "none/trace" amounts of hyperemia. Most patients preferred the study medication (81.5 %; n = 141/173) and were confident that they would adhere to their preferred medication (90.8 %; n = 157/173). No serious AEs were reported, and eye irritation (3.7 %; n = 7/191) was the most common treatment-related AE. Conclusions: Transitioning from BAK-containing latanoprost 0.005 % to BAK-free travoprost 0.004 % preserved with PQ reduced IOP in patients with open-angle glaucoma or ocular hypertension who were intolerant of latanoprost. BAK-free travoprost 0.004 % is a viable alternative for patients who require switching their IOP-lowering medications because of tolerability issues.

First-year treatment costs among new initiators of topical prostaglandin analog identified from November 2007 through April 2008 - Schmier, JK; Covert, DW; Robin, AL (CURRENT MEDICAL RESEARCH AND OPINION, 2010)
Objective: Ocular surface disease (OSD) is a common side effect of ophthalmic medications containing the preservative benzalkonium chloride (BAK). Little is known whether and how glaucoma treatment patterns and annual costs vary based on the presence of BAK. The objective of this analysis was to estimate first-year treatment costs among new initiators of topical prostaglandin analogs in a managed care population. Research design and methods: A model was developed to estimate first-year direct medical costs associated with glaucoma prescriptions and outpatient ophthalmic care. Patients were identified from a pharmacy claims database, covering more than 75 million individuals, if they initiated therapy with one of three prostaglandin analog products between November 1, 2007 and April 30, 2008. Patients needed to have at least 6 months of prior claims data in which there were no glaucoma therapy claims and at least 12 months of follow-up data available after the initial claim. Patients were excluded if they were not continuously eligible for pharmacy benefits throughout this 18-month period. Published studies were used to estimate outpatient visit-related health care resource use, and costs for prescription medications and health care resource use were derived from standard, published benchmarks. Results: The database analysis identified 9398 patients meeting study criteria, 45% (n = 4230) of whom remained on their initial prostaglandin therapy for 12 months after initiation. Adjunctive intraocular pressure lowering therapy was needed in 23.6%, 18.5%, and 13.3% of bimatoprost, latanoprost, and BAK-free travoprost patients, respectively. Median numbers of days to the first prescription filled for adjunctive therapy (if required) were 72.5, 74.0, and 125.0 for patients initiating on bimatoprost, latanoprost, and BAK-free travoprost. Total estimated first-year costs were $1973, $1807, and $1739 for patients initiating therapy with bimatoprost, latanoprost, and BAK-free travoprost. Findings were consistent through sensitivity analysis. Conclusions: A BAK-free prostaglandin analog may permit longer duration of monotherapy and be associated with lower first-year direct treatment costs. Use of a claims database and the selection of new initiators of prostaglandin analogs limit projecting findings to all glaucoma patients.

Assessing Health Care Burden in Glaucoma Patients with and Without Physical or Mental Comorbidities - Serbin, M; Devine, B; Campbell, J; Basu, A (JOURNAL OF MANAGED CARE & SPECIALTY PHARMACY, 2020)
BACKGROUND: Glaucoma is a collection of eye diseases that damage the eye's optic nerve resulting in vision loss and blindness. Treatment for glaucoma is primarily pharmacologic; however, studies have shown patients have difficulty adhering to topical regimens. The reasons for potentially poor adherence are numerous, including influence from a myriad of either physical or mental comorbid conditions faced by many glaucoma patients. Neither adherence nor associated outcomes have been estimated in these 2 groups of glaucoma patients. OBJECTIVES: To (a) characterize glaucoma patients with and without select physical or mental comorbidities and (b) estimate differences between the 2 groups for 3 types of outcomes: health care resource use (HCRU; office-based/outpatient-based provider visits, emergency room visits, inpatient stays, home health provider days, prescription fills); health care expenditures; and health-related quality of life (HRGIoL) as measured by the physical and mental component scores of the Short Form-12. METHODS: We used first-year data from each glaucoma patient's 2-year panel survey in the Medical Expenditure Panel Survey (MEPS) database, 2003-2014. Two groups were created using ICD-9-CM codes collected by MEPS to compare glaucoma patients with and without at least 1 selected physical or mental comorbid condition. Between-group comparisons in the outcomes of interest (HCRU, expenditure, HROoL) were estimated using multivariable regression analyses while adjusting for socio-demographic and clinical characteristics at baseline. RESULTS: We identified 2,928 unique glaucoma patients during the 11 years of collected data, including 1,539 (53%) who had at least 1 physical or mental comorbid condition of interest. Comparing those with at least 1 select physical or mental comorbidity to those without (n =1,389), unadjusted HCRU and expenditures were greater in patients with a physical or mental comorbidity (all P < 0.05). After adjustment, significant associations with increased HCRU remained for office-based provider visits and home health provider days (each P < 0.01). Average total expenditures were $12,324 in those with comorbidities and $8,590 for those without. HRQoL (unadjusted and adjusted) was lower in those with a physical or mental comorbid condition (all P < 0.05). CONCLUSIONS: Some differences in HCRU and expenditures were accounted for by differences in baseline characteristics between those with and those without 1 or more physical or mental comorbid conditions, but differences remained after adjustment. Results suggest that glaucoma patients with physical and mental comorbidities may experience greater HCRU and associated expenditures, and lower HROoL, when compared with glaucoma patients without these comorbidities With this knowledge, future work may include estimating the effect of the number of these comorbid conditions on each of the 3 types of outcomes. Copyright (C) 2020, Academy of Managed Care Pharmacy. All rights reserved.

Pseudoexfoliation and the cataract surgeon: Preoperative, intraoperative, and postoperative issues related to intraocular pressure, cataract, and intraocular lenses - Shingleton, BJ; Crandall, AS; Ahmed, IIK (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2009)
This review provides a comprehensive assessment of intraocular pressure (IOP), phacoemulsification techniques, and intraocular lenses (IOLs) in pseudoexfoliation (PXF) eyes having cataract surgery. Pseudoexfoliation is ubiquitous and the most common cause for open-angle glaucoma worldwide. Cataracts occur with increased frequency in PXF eyes, and surgery is potentially complicated by the presence of small pupils and zonule laxity and significantly affects IOP in these eyes. Preoperative evaluation and the options for intraoperative management of cataract are presented with recommendations for the use of adjunctive pupil and zonule support devices. Postoperative complications such as capsule contraction and IOL instability are discussed and laser and surgical options to manage these special problems presented.

Treatment Complexity in Primary Open-Angle Glaucoma (POAG): Perspectives on Patient Selection in Micro-Invasive Glaucoma Surgery (MIGS) Using Stents - Helbig, C; Wollny, A; Altiner, A; Diener, A; Kohlen, J; Ritzke, M; Frech, S; Guthoff, RF (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2021)
Background Primary open-angle glaucoma (POAG) is still one of the most common causes of impaired vision worldwide, despite the further development of therapy options, and can lead to blindness. Micro-invasive glaucoma surgery (MIGS) using stents aims at reducing intraocular pressure (IOP), as it is the main risk factor. With regard to adherence and adverse drug reactions it also aims at reducing the drug burden on patients. The study investigates under everyday conditions the criteria according to which ophthalmologists in Germany select patients for MIGS using stents. In addition, it will be investigated which patients (could) benefit most from the therapy. Material and Methods In this qualitative study, 11 narrative interviews were conducted between May 2017 and July 2018 with ophthalmologists working in the hospital or in a private practice. They were interviewed on their experiences in the treatment of POAG with microstents. The interviews were analysed by an interdisciplinary team using the qualitative content analysis. Results The stages of therapy escalation form the frame of reference for patient selection in MIGS using stents. Only if the IOP cannot be sufficiently reduced by drop therapy or when this causes drug-related side effects that are intolerable for the patients, stents are apparently used as the next higher escalation stage. The intensive post-operative medication and the frequent check-up appointments are perceived as barriers by the interviewees, especially for people with or without disabilities, who are dependent on external help and/or those living in rural areas. The active cooperation of the patients in the demanding aftercare seems to be indispensable for the ophthalmologists. In addition, necessary revisions are sometimes stressful for patients (physical/psychological) and doctors (work organisation/therapy). Against the background of the organisational and economic challenges in the outpatient spectrum of tasks, especially physicians in private practice seem to weigh up carefully for which patients microstent therapy would be reasonable. Conclusion In view of the therapeutic requirements, the current microstent therapy seems to be used in a selected, adherent patient group. Further qualitative and quantitative studies (in other health care regions and structures) are necessary to verify and extend the available results.

Doctor-Patient Communication in Glaucoma Care Analysis of Videotaped Encounters in Community-Based Office Practice - Friedman, DS; Hahn, SR; Quigley, HA; Kotak, S; Kim, E; Onofrey, M; Eagan, C; Mardekian, J (OPHTHALMOLOGY, 2009)
Purpose: To assess doctor-patient communication in patients with glaucoma. Design: Observational cohort study. Participants: Twenty-three ophthalmologists and 50 patients with glaucoma. Methods: Doctor-patient encounters were audio- and videotaped and analyzed using validated sociolinguistic approaches. After the visit, the doctor and the patient completed questionnaires, and patients were interviewed using a semistructured, patient-centered protocol. Main Outcome Measures: Summary statistics about doctor-patient encounters, assessment of alignment of attitudes between patients and doctors, and patient admission to missing doses. Results: Physicians spent an average of 8.0 (standard deviation [SD], 3.1; median, 7.8) minutes in the room with the patient and an average of 5.8 (SD, 2.4; median, 7.5) minutes talking with the patient, delivering 70% of all spoken words and asking two thirds of all questions. Glaucoma-related discussion occupied 50% of talk time and was focused primarily on examinations and treatment (25%). One third of discussions addressed ocular issues other than glaucoma. Virtually all physician questions (94%) were closed ended. Most patient questions were about intraocular pressure (20% of visits), details of the medication regimen (20%), disease status (14%), and testing (12%). Although physicians and patients were aligned in believing that the physician should control the visit agenda, physicians tended to support greater physician control of decision making than did patients. Physicians failed to identify most patients who admitted to missing doses, a surrogate for nonadherence, stating that 10 of 13 in this category were taking drops "all" or "most" of the time. Physician interviews detected 3 of the 11 patients whose postvisit questionnaire indicated missing a dose in the last week compared with 11 of the 11 detected by the postvisit research interview. Patients who stated they had missed doses recently reported being less satisfied with the doctor-patient encounter than those who did not. Conclusions: Doctor-patient dialogue was universally physician centered; physicians spoke 70% of the words and asked closed-ended questions that restricted the patient's contribution to "yes/no" or brief responses. A minority of physicians ever asked patients if they had questions. In contrast with the patient-centered research interview, doctors' physician-centered communication failed to identify most patients who had missed doses.

Estimated first-year costs of prostaglandin analogs with/without adjunctive therapy for glaucoma management: a United States perspective - Schmier, JK; Covert, DW; Robin, AL (CURRENT MEDICAL RESEARCH AND OPINION, 2007)
Objective: To evaluate costs associated with prostaglandin analogs among newly-diagnosed glaucoma patients in a managed-care population. Research design and methods: A cost minimization model compared annual costs for patients initiating therapy with one of the three prostaglandin analogs (bimatoprost, latanoprost, travoprost). The study cohort was identified from pharmacy claims and eligibility files of patients who met study inclusion criteria. Annual costs were estimated for patients initiating therapy with each prostaglandin based on treatment patterns and medication use over the year. Costs for outpatient physician visits and medications were estimated from standard sources. Results: A total of 4444 patients met study criteria: 674 received travoprost, 729 received bimatoprost, and 3041 received latanoprost. More than 80% stayed on monotherapy for 1 year (82.9% of travoprost patients, 82.8% of bimatoprost patients, and 80.5% of latanoprost patients). Of those who required adjunctive therapy, the average number of days until starting adjunctive therapy was 130 days for travoprost patients, 94 days for bimatoprost patients, and 104 days for latanoprost patients. Average annual costs were $1198, $1290, and $1217 for patients treated with travoprost, bimatoprost, and latanoprost, respectively. Conclusions: The use of adjunctive therapy in glaucoma is an important driver of glaucoma management costs. This study demonstrates that the longer duration of monotherapy and the likelihood to use single rather than combination adjunctive agents contribute to lower annual costs among patients starting on travoprost compared with the other available prostaglandin analogs. Study limitations include the lack of clinical indicators in the study database; further, results may not be generalizable to patients who discontinue prostaglandin analogs or to the population of patients with glaucoma as a whole. Future studies with clinical and compliance indicators would further identify distinctions among treatment regimens.

Safety and efficacy of switching from dorzolamide 1.0%/timolol maleate 0.5% eye drops to brinzolamide 1.0%/timolol maleate 0.5% eye drops - Inoue, K; Shiokawa, M; Ishida, K; Tomita, G (CLINICAL OPHTHALMOLOGY, 2015)
Purpose: To evaluate the safety and efficacy of switching from dorzolamide 1.0%/ timolol maleate 0.5% fixed-combination (DTFC) eye drops to brinzolamide 1.0%/ timolol maleate 0.5% fixed-combination (BTFC) eye drops in patients with primary open-angle glaucoma or ocular hypertension. Methods: A total of 35 eyes of 35 patients with primary open-angle glaucoma or ocular hypertension using DTFC eye drops were included. Participants discontinued DTFC drops and immediately began using BTFC drops. All other eye drops currently being used were continued. Intraocular pressure (IOP) 1 and 3 months after switching medications was compared with baseline IOP. One month after switching medications, participant preference and adherence were evaluated. Adverse reactions were monitored at each study visit. Results: The IOP was 17.9 +/- 2.6 mmHg at baseline and 18.3 +/- 4.1 mmHg and 17.8 +/- 3.4 mmHg 1 month and 3 months after switching medications, respectively (P=0.633). The frequency of missing a dose was not different before (6.1%) and after (6.1%) switching to BTFC. Significantly fewer participants reported stinging after switching to BTFC (15.2%) than while using DTFC (51.5%, P < 0.01). Blurred vision was reported with the same frequency before (39.4%) and after (42.4%) switching to BTFC. A total of 33.3% and 27.3% of patients preferred DTFC and BTFC, respectively. Several patients withdrew from the study because of discomfort (n=2, 5.7%), discharge (n=1, 2.9%), dizziness (n=1, 2.9%), or increased IOP (n=2, 5.7%). Conclusion: Switching from DTFC to BTFC was well tolerated and did not result in IOP changes or a decreased patient adherence. When glaucoma patients complain of stinging with DTFC administration, switching to BTFC is an acceptable treatment option.

Evaluating Eye Drop Instillation Technique and Its Determinants in Glaucoma Patients - Gao, XB; Yang, QM; Huang, WM; Chen, TT; Zuo, CG; Li, XY; Gao, WY; Xiao, HM (JOURNAL OF OPHTHALMOLOGY, 2018)
Aim. To evaluate eye drop instillation technique and to explore its determinants in glaucoma patients. Methods. One hundred and thirteen patients diagnosed with glaucoma and self-administering topical antiglaucoma eye drops for at least 1 month were evaluated. All patients instilled artificial tear solution in one eye as they would do at home. The whole process was evaluated by two study staff. A comprehensive score system associated with eye drop instillation techniques was used to quantify the instillation technique and explore its determinants such as demographic and clinical characteristics. Results. Half of the patients (48.67%) finished the administration of eye drop on first attempt. 1.7 eye drops were squeezed out on average. 43 patients (37.17%) got contact with ocular surface or adnexa. Only 19.7% patients had eye drop instillation techniques being defined as well. 11 patients (9.7%) had prior instruction regarding using eye drops, while only 4 patients knew to occlude the tear duct by pressing the dacryocyst area. Older age and worse visual acuity were found to be independent risk factors for worse instillation technique. Conclusions. Eye drop instillation technique in glaucoma patients deserves great attention from eye care practitioners during their lifelong follow-up, especially those aged older and have worse visual acuity.

The role of social deprivation in severe neovascular age-related macular degeneration - Sharma, HE; Mathewson, PA; Lane, M; Shah, P; Glover, N; Palmer, H; Haque, MS; Denniston, AK; Tsaloumas, MD (BRITISH JOURNAL OF OPHTHALMOLOGY, 2014)
Background/aims Advances in therapy have improved outcomes for patients with neovascular age-related macular degeneration (nAMD). Prompt access to treatment is a priority and may be used as a key performance indicator. In this study, we investigate how social deprivation may impact on access to services, treatment and visual impairment registration. Methods Patients were identified retrospectively through the Certificate of Visual Impairment system for the University Hospitals Birmingham Medical Retina service. The Index of Multiple Deprivation (IMD) 2007 score was calculated for each patient. The impact of deprivation, age, gender and ethnicity on key stages in the care pathway was assessed. Results 120 patients were identified. Patients with greater social deprivation were under-represented, had worse visual acuity at first presentation (correlation of the better-seeing eye with IMD 0.225 (p=0.013)) and had sight-impairment registration earlier (correlation -0.246; p=0.007). Deprivation did not affect time to first appointment, and was not associated with a higher rate of non-attendance. Conclusions The late presentation and under-representation of patients with greater social deprivation is a serious concern. Our study strongly suggests that this vulnerable group is encountering barriers in accessing treatment in nAMD, and that these occur prior to entry into the Hospital Eye Service.

CORNEAL ENDOTHELIAL CELL DENSITY AFTER VITRECTOMY WITH SILICONE OIL FOR COMPLEX RETINAL DETACHMENTS - Goezinne, F; Nuijts, RM; Liem, AT; Lundqvist, IJ; Berendschot, TJ; Cals, DW; Hendrikse, F; La Heij, EC (RETINA-THE JOURNAL OF RETINAL AND VITREOUS DISEASES, 2014)
Purpose: To evaluate the endothelial cell density changes in eyes with silicone oil tamponade after vitrectomy for complex rhegmatogenous retinal detachment. Methods: A prospective controlled study with 81 eyes with complex rhegmatogenous retinal detachment undergoing vitrectomy and silicone oil tamponade. Fellow eyes that fulfilled specific inclusion criteria served as controls. Endothelial cell density (in cells per square millimeter), coefficient of variance (standard deviation per mean cell area x 100), percentage of hexagonal cells, and corneal thickness were documented preoperatively and compared with values obtained at 3, 6, and 12 months postoperatively. For the purpose of the study analysis, all study eyes were divided into 5 groups, according to their lens status during the follow-up. Results: High endothelial cell density loss was found in Group 3, (eyes that underwent an additional phacoemulsification procedure) and Group 4 (eyes that underwent lens and/or intraocular lens removal during the follow-up) at 12 months with a mean cell loss of 19% and 39%, respectively (P < 0.001). Conclusion: An intact natural or artificial lens-iris diaphragm may provide a protective barrier against corneal endothelial cell damage from long-term silicone oil tamponade.

Implantation of two second-generation trabecular micro-bypass stents and topical travoprost in open-angle glaucoma not controlled on two preoperative medications: 18-month follow-up - Berdahl, J; Voskanyan, L; Myers, JS; Hornbeak, DM; Giamporcaro, JE; Katz, LJ; Samuelson, TW (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2017)
ImportanceAdditional data are sought regarding treatment options for glaucoma, a major cause of global blindness. BackgroundThe study assessed outcomes following standalone implantation of two second-generation trabecular micro-bypass stents and postoperative topical prostaglandin in eyes with open-angle glaucoma not controlled on two preoperative medications. DesignThe study design is a prospective, nonrandomized, open-label study at a tertiary-care ophthalmology centre. ParticipantsSubjects had open-angle glaucoma with preoperative intraocular pressure of 18-30mmHg on two medications, a medication washout phase, and post-washout intraocular pressure of 22-38mmHg. All subjects (N=53) have been followed for 18months. MethodsOne day following implantation of two second-generation trabecular micro-bypass stents, subjects started topical travoprost. Medication washout was repeated at month 12. Main Outcome MeasuresThe main outcome measure was the proportion of eyes with intraocular pressure reduction 20% versus medicated baseline intraocular pressure with reduction of one medication at 12months. ResultsAt 12months, 91% of eyes achieved intraocular pressure reduction 20% with reduction of one medication. All eyes had intraocular pressure 18mmHg with reduction of one medication, and 87% had intraocular pressure 15mmHg. Mean intraocular pressure on one medication was 13.0mmHg (34% reduction) through 18months. Mean post-washout intraocular pressure at month 13 was 33% lower than preoperative unmedicated intraocular pressure. No adverse events occurred through 18months. Conclusions and RelevanceIn open-angle glaucoma eyes on two preoperative medications, treatment with two second-generation trabecular stents and one postoperative prostaglandin resulted in mean intraocular pressure 13mmHg with reduction of one medication, with favourable safety. These findings show the utility of second-generation trabecular bypass with postoperative prostaglandin in patients with open-angle glaucoma.

So let me find my way, whatever it will cost me, rather than leaving myself in darkness: experiences of glaucoma in Nigeria - Kyari, F; Chandler, CI; Martin, M; Gilbert, CE (GLOBAL HEALTH ACTION, 2016)
Background: Blindness from glaucoma is associated with socio-economic deprivation, presumed to reflect poor access to care and poor adherence to treatment. Objectives: To determine why people with glaucoma are presenting late for treatment and to understand access to glaucoma care. Additionally, we sought to identify what patients and the community know, do and think about the condition and why the poor are the most affected with glaucoma blindness. Design: Study participants were from four communities and two hospitals in Abuja-FCT and Kaduna State, Nigeria. A total of 120 participants were involved, including 8 focus group discussions, 7 in-depth interviews with blind/visually impaired glaucoma patients, 5 rapid direct observation visits with these patients and 13 exit interviews of glaucoma patients in the hospital. The data were analysed using content analysis, interpreting participant experiences in terms of three key steps conceptualised as important in the care pathway: what it takes to know glaucoma, to reach a diagnosis and to access continued care. Results: This article presents multiple narratives of accessing and maintaining glaucoma care and how people manage and cope with the disease. People may be presenting late due to structural barriers, which include lack of knowledge and awareness about glaucoma and not finding an appropriately equipped health care facility. What keeps glaucoma patients within the care pathway are a good hospital experience; a support structure involving family, counselling and shared patients' experiences; and an informed choice of treatment, as well as agency. The high cost of purchasing care is a major factor for patients dropping out of treatment. Conclusion: The findings suggest the need to address economic and social structural drivers as glaucoma presents another case study to demonstrate that poverty is a strong driver for blindness. There is also a need for clear glaucoma care pathways with early case finding in the community, two-way referral/feedback systems, well-equipped glaucoma care hospitals and better eye health care financing.

Fuchs' heterochromic iridocyclitis: A review of 26 cases - Velilla, S; Dios, E; Herreras, JM; Calonge, M (OCULAR IMMUNOLOGY AND INFLAMMATION, 2001)
Fuchs' heterochromic iridocyclitis (FHI), an unusual form of uveitis of unknown etiology, is frequently misdiagnosed. Purpose: To report the analysis Of 26 patients (27 eyes) with FHI who were diagnosed and observed over a period of 1-7 years (mean: 3.42 +/-2.2 years). Methods: Ocular and systemic examinations were performed on all patients. Results: The most common presenting symptom was visual deterioration (42.3%); one patient was affected bilaterally. Characteristic keratic precipitates (100%), cataracts (77.8%), and heterochromia (70.4%) were the major signs. Eleven eyes (40.7%) required cataract surgery. At the initial examination, four eyes (14.8%) had glaucoma, and no new cases of glaucoma developed during the follow-up period. One eye required filtration surgery. Vitrectomy was performed in two eyes (7.4%) because of vitreous opacities. Most patients (73.0%) did not require active treatment; pre- and postoperative anti-inflammatory treatment for cataract extraction was performed successfully to minimize the risk of inflammation. No severe uveitis was seen in any patient after surgery, but visual acuity did not improve greatly after cataract extraction; 54.5% eyes had visual acuity better than 20/40 before surgery, and 45.4% postoperatively. Conclusion: Posterior capsule opacification, glaucoma, and vitreous opacity were the major obstacles to visual rehabilitation after cataract surgery in patients with this type of uveitis.

Tele-ophthalmology and conventional ophthalmology using in remote Greece a mobile medical unit - Labiris, G; Fanariotis, M; Christoulakis, C; Petounis, A; Kitsos, G; Aspiotis, M; Psillas, K (JOURNAL OF TELEMEDICINE AND TELECARE, 2003)
We evaluated the quality of medical services delivered to remote glaucoma patients from a mobile unit. A four-wheel-drive vehicle containing the necessary equipment visited five different remote locations in Greece. During a three-year prospective study, 1205 patients were examined, of whom 230 had glaucoma. The majority of the subjects were examined by the unit's medical staff using the available instrumentation (e.g. slit-lamp and tonometer), while 56 glaucoma subjects were telemedically examined by consultants at the Patissia General Hospital, in Athens. Control data were obtained from a random sample of 260 urban glaucoma patients. A significantly greater proportion of the remote patients had an inadequate awareness of glaucoma (77%) compared with the urban patients (20%). Significantly more remote patients had poorer compliance (68%) in comparison with urban patients (23%). A significantly larger proportion of the remote patients had high intra-ocular pressure (21%) compared with the urban patients (5%). Technical difficulties occurred in the 13 of the 56 telemedical examinations. Mobile medical units can enhance access to medical services and contribute to the health-care of under-served populations.

Randomised clinical trial of lensectomy versus lens aspiration and primary capsulotomy for children with bilateral cataract in south India - Eckstein, M; Vijayalakshmi, P; Gilbert, C; Foster, A (BRITISH JOURNAL OF OPHTHALMOLOGY, 1999)
Aims-The primary objective was to determine which surgical technique gave the best long term visual outcome for infants and young children with bilateral symmetrical cataract in south India. Secondary objectives were to assess complications and the need for further surgical intervention. Methods-A randomised controlled clinical trial was undertaken. 65 children under 10 years old with bilateral cataract had one eye treated by lensectomy and the other by aspiration with primary capsulotomy. Results-56 children (86%) with a mean age at surgery of 53 months were reviewed 3 years after surgery. The overall binocular acuity was 6/18 or better in 57.1% and 6/60 or better in 94.6%. There was no difference in visual acuity between the matched pairs of eyes undergoing aspiration or lensectomy at the third year of follow up (p=0.57). Aspiration eyes were more likely to require a secondary procedure to restore vision than lensectomy eyes (66.1% v 1.8%). Conclusion-Aspiration with primary capsulotomy gives an acceptable visual outcome in this part of India providing that there is good follow up to manage capsule opacification. If secondary intervention is not possible owing to poor compliance with follow up, then lensectomy is likely to give better long term visual rehabilitation providing there is good maintenance and technical support for the lensectomy equipment.

Endoscopic laser cyclophotocoagulation in pediatric glaucoma with corneal opacities - Al-Haddad, CE; Freedman, SF (JOURNAL OF AAPOS, 2007)
INTRODUCTION Endoscopic diode cycloablation (ECP) has shown modest efficacy for the management of pediatric glaucomas. Eyes with pediatric glaucoma and corneal opacities pose obstacles to intraocular surgery. We examined the role of ECP in lowering intraocular pressure (IOP) as well as that of endoscopy in facilitating tube shunt placement in these eyes. METHODS Retrospective chart review of 12 eyes (11 patients) with glaucoma and corneal opacities from 12/99 to 9/05. ECP was performed for IOP control with success defined as postoperative IOP <= 21 mm Hg, with or without medications and without procedure-related complications. Success of ECP, repeat ECP, and endoscopically guided tube shunt placement was studied. RESULTS Diagnoses included the following: Peters/anterior segment dysgenesis in nine eyes and corneal scar/failed corneal graft in three. Patients included eight females and three males with median age 3 years (0.5 to 10.3) at treatment. Median number of prior surgeries was three; median time to failure was 7.8 months (0.3 to 3 8). Ten eyes had prior external cycloablation(s). Success of first ECP (mean 6.1 clock hours) was 2/12 (17%), with Kaplan-Meier median survival 12 months. Two treatment failures had repeat ECP, and both failed. Four treatment failures had subsequent tube shunt surgery (three with endoscopic assistance), and all were successful at median follow-up of 33 months (11 to 63). Baseline IOP was 36.8 +/- 11 mm Hg before ECP versus 28.2 +/- 16 mm Hg after first treatment (p = 0.07). Procedure-related complications included chorioretinal detachment in one eye. CONCLUSIONS ECP had limited success in children with refractory glaucoma. However, with anatomic limitations, endoscopy itself was valuable in facilitating subsequent successful tube shunt surgery.

Validation of the Glaucoma Filtration Surgical Mouse Model for Antifibrotic Drug Evaluation - Seet, LF; Lee, WS; Su, R; Finger, SN; Crowston, JG; Wong, TT (MOLECULAR MEDICINE, 2011)
Glaucoma is a progressive optic neuropathy, which, if left untreated, leads to blindness. The most common and most modifiable risk factor in glaucoma is elevated intraocular pressure (IOP), which can be managed surgically by filtration surgery. The postoporative subconjunctival scarring response, however, remains the major obstacle to achieving long-term surgical success. Antiproliferatives such as mitomycin C are commonly used to prevent postoperative scarring. Efficacy of these agents has been tested extensively on monkey and rabbit models of glaucoma filtration surgery. As these models have inherent limitations, we have developed a model of glaucoma filtration surgery in the mouse. We show, for the first time, that the mouse model typically scarred within 14 d, but when augmented with mitomycin C, more animals maintained lower intraocular pressures for a longer period of time concomitant with prolonged bleb survival to beyond 28 d. The morphology of the blebs following mitomycin C treatment also resembled well-documented clinical observations, thus confirming the validity and clinical relevance of this model. We demonstrate that the antiscarring response to mitomycin C is likely to be due to its effects on conjunctival fibroblast proliferation, apoptosis and collagen deposition and the suppression of inflammation. Indeed, we verified some of these properties on mouse conjunctival fibroblasts cultured in vitro. These data support the suitability of this mouse model for studying the wound healing response in glaucoma filtration surgery, and as a potentially useful tool for the in vivo evaluation of antifibrotic therapeutics in the eye. (C) 2011 The Feinstein Institute for Medical Research, www.feinsteininstitute.org

Cost-effectiveness and cost utility of community screening for glaucoma in urban India - John, D; Parikh, R (PUBLIC HEALTH, 2017)
Objectives: Population-based screening for glaucoma has been demonstrated to be cost-effective if targeted at high-risk groups such as older adults and those with a family history of glaucoma, and through use of a technician for conducting initial assessment rather than a medical specialist. This study attempts to investigate the cost-effectiveness of a hypothetical community screening and subsequent treatment programme for glaucoma in comparison with current practice (i.e. with no screening programme but with some opportunistic case finding) in the urban areas of India. Study design: A hypothetical screening programme for both primary open-angle glaucoma and angle-closure disease was built for a population aged between 40 and 69 years in the urban areas of India. Methods: Screening and treatment costs were obtained from an administrator of a tertiary eye hospital in India. The probabilities for the screening pathway were derived from published literature and expert opinion. The glaucoma prevalence rates for urban areas were adapted from the Chennai Glaucoma Study findings. A decision-analytical model using TreeAge Pro 2015 was built to model events, costs and treatment pathways. One-way sensitivity analyses were conducted. Results: The introduction of a community screening programme for glaucoma is likely to be cost-effective, the estimated incremental cost-effectiveness ratio (ICER) values being (sic)10,668.68 when compared with no screening programme and would treat an additional 4443 cases and prevent 1790 person-years of blindness over a 10-year period in the urban areas of India. Sensitivity analyses revealed that glaucoma prevalence rates across various age groups, screening uptake rate, follow-up compliance after screening, treatment costs and utility values of health states associated with medical and surgical treatment of glaucoma had an impact on the ICER values of the screening programme. Conclusions: In comparison with current practice (i.e. without a screening programme but with some opportunistic case finding), the introduction of a community screening programme for glaucoma for the 40-69 years age group is likely to be relatively cost-effective if implemented in the urban areas of India. (C) 2017 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved.

Second-Generation Trabecular Micro-Bypass Stents as Standalone Treatment for Glaucoma: A 36-Month Prospective Study - Hengerer, FH; Auffarth, GU; Riffel, C; Conrad-Hengerer, I (ADVANCES IN THERAPY, 2019)
IntroductionTo evaluate long-term outcomes following stand-alone implantation of two second-generation trabecular micro-bypass stents (iStent inject((R)), Glaukos Corp., San Clemente, CA, USA) in eyes with predominantly primary open-angle glaucoma (POAG) and considerable preoperative disease burden.MethodsEyes with POAG, pseudoexfoliative glaucoma (PXG), appositional narrow-angle glaucoma (NAG, with open-angle configuration in the area of implantation), or secondary glaucoma were included in this prospective, non-randomized, consecutive case series. All eyes underwent ab interno iStent inject implantation as a sole procedure. Assessments through 36months included IOP, medications, corrected distance visual acuity (CDVA), secondary glaucoma surgeries, and complications and adverse events.ResultsTwo iStent inject stents were implanted in 44 consecutive eyes (POAG=38, PXG=4, appositional NAG=1, secondary neovascular glaucoma=1) of 31 patients, and 33 eyes had 36-month follow-up data. Preoperative mean IOP was 25.36.0mmHg on a mean of 2.980.88 medications, with 75% of eyes on 3-5 medications, no eyes medication-free, and 50% of eyes with history of prior glaucoma surgery. At 36months postoperatively, mean IOP reduced by 42% to 14.6 +/- 2.0mmHg (p<0.0001) and 87.9% of eyes achieved an IOP reduction of >= 20% versus preoperatively. In addition, 97% of eyes reached IOP <= 18mmHg (vs. 9.1% preoperatively; p<0.0001) and 70.0% of eyes reached IOP <= 15mmHg (vs. 2.3% preoperatively; p<0.0001). Mean medication burden decreased by 82% to 0.55 +/- 0.79 (p<0.0001), and 61% of eyes became medication-free. All eyes maintained or decreased their 36-month medication burden versus preoperatively. Safety was favorable, including minimal adverse events and stable CDVA through 36months postoperatively.Conclusion This real-world cohort of glaucomatous eyes with substantial preoperative disease burden experienced significant, sustained, safe IOP and medication reductions through 36months following stand-alone iStent inject implantation.Funding Article processing charges and writing assistance were provided by Glaukos Corp. (San Clemente, CA, USA).

Association of Visit Adherence and Visual Acuity in Patients With Neovascular Age-Related Macular Degeneration Secondary Analysis of the Comparison of Age-Related Macular Degeneration Treatment Trial - Ramakrishnan, MS; Yu, YX; VanderBeek, BL (JAMA OPHTHALMOLOGY, 2020)
This secondary analysis of the Comparison of Age-Related Macular Degeneration Treatment Trial randomized clinical trial assesses the association of patient adherence and visual acuity in individuals with neovascular age-related macular degeneration. Importance Visit adherence has been shown to play a significant role in patient health outcomes. The effect of missing visits on visual acuity (VA) in individuals with neovascular age-related macular degeneration has yet to be characterized. Objective To quantify the association between patients' adherence to randomized clinical trial visits and VA in individuals with neovascular age-related macular degeneration based on 4 visit adherence metrics. Design, Setting, and Participants This is a secondary analysis of the Comparison of Age-Related Macular Degeneration Treatment Trial randomized clinical trial. Individuals with age-related macular degeneration were recruited from 44 clinical centers in the United States between February 2008 and December 2009. The 2-year study protocol required 1 visit every 4 weeks (every 21-35 days for a total of 26 visits) for monthly vs pro re nata treatments of bevacizumab vs ranibizumab. Analysis took place from November 2018 through May 2019. Exposures Visit adherence was measured in 4 ways: total number of missed visits, average number of days (avg days) between each visit, longest duration in days (max days) between visits, and visit constancy (the tally of 3-month periods with at least 1 visit attended). Average and max days were also categorized as on time (28-35 days), late (36-60 days), and very late (>60 days). Main Outcomes and Measures Change in Early Treatment Diabetic Retinopathy Study VA between the baseline and the last visit. Linear multivariate regression models were applied to analyze the association between visit adherence and change in VA, controlling for age, sex, baseline VA, anti-vascular endothelial growth factor drug, number of injections, and dosing regimen. Results Of 1178 patients, the mean (SD) age was 79.1 (7.3) years, and 727 (61.7%) were women. The mean (SD) number of missed visits was 2.4 (3.1). Overall, 1091 patients (92.6%) had complete visit constancy during the entire study period. Average days were categorized with 1060 patients (90.0%) classified as on time, 108 (9.2%) were late, and 10 (0.8%) were very late. For max days between visits, 197 patients (16.7%) were on time, 773 (65.6%) were late, and 208 (17.7%) were very late. After controlling for covariates, the late (avg days = -6.1; max days = -2.0) and very late (avg days = -12.5; max days = -5.9) groups saw fewer letters in both the avg and max days categories than patients in the on-time group (P < .001). Conclusions and Relevance These results provide evidence to support the concept that visit adherence contributes to VA outcomes in neovascular age-related macular degeneration. The magnitude of the association of visit adherence with VA outcomes in this clinical scenario suggests that substantial effort should be expended to strive for visit adherence or therapeutic strategies that reduce the visit burden without compromising VA outcomes. Question What is the association between visit adherence and visual outcomes in individuals with neovascular age-related macular degeneration? Findings In a secondary analysis of the Comparison of Age-Related Macular Degeneration Treatment Trial randomized clinical trial of 1178 individuals, patients were expected to attend visits every 4 weeks; each missed visit was associated with an average visual acuity letter score decline of 0.7. Compared with patients who were on time, those who averaged between 36 and 60 days and more than 60 days between visits lost 6.1 and 12.5 letters, respectively. Meaning Visit adherence may contribute to visual acuity outcomes in neovascular age-related macular degeneration.

Cost-effectiveness and budget impact analysis of a patient visit support system for blindness reduction in Japanese patients with glaucoma - Yamada, M; Nakano, T; Matsuda, H; Kim, SW; Takagi, Y (JOURNAL OF MEDICAL ECONOMICS, 2020)
Aim To evaluate the cost-effectiveness (CE) and budget impact (BI) of introducing a patient visit support system (ACT Pack) along with standard of care (SoC), in glaucoma treatment in Japan. Methods A Markov model was designed to estimate the CE and BI of introducing the support system from Japanese payer and governmental perspective, respectively. Inputted data for CE and BI analysis were referred from published literature and based on medical specialists' inputs. Base case scenario for CE considered the support system cost of 30,000 yen per patient per year and a time horizon of 45 years. BI analysis compared the financial impact due to introduction of support system with SoC compared to SoC alone scenario on Japanese healthcare system with a time horizon of 20 years. Results The base case of CE analysis showed the incremental cost per quality-adjusted life years (QALYs) gained with the support system was 3,241,729 yen/QALY (29,470 USD/QALY). The sensitivity analysis showed that the probability of this support system being cost-effective at a threshold of 5 million yen/QALY (45,455 USD/QALY) was 53.26%. Blindness reduction after introduction of this support system was 8.68%. The BI analysis showed that the introduction of support system will lead to a cumulative cost savings of 1,132 billion yen (10 billion US dollars) for Japanese healthcare system over 20 years of time horizon. Limitation Due to paucity of similar comparative studies, some assumptions were made based on medical specialists' inputs. Death status was not considered in the analysis. Conclusion Introduction of this support system with SoC is cost-effective and will lead to blindness reduction in Japanese patients with glaucoma. Over a 20 year period, it will lead to an overall cost savings of 1,132 billion yen (10 billion US dollars) for the Japanese healthcare system.

iStent as a Solo Procedure for Glaucoma Patients: A Systematic Review and Meta-Analysis - Malvankar-Mehta, MS; Chen, YN; Iordanous, Y; Wang, WW; Costella, J; Hutnik, CML (PLOS ONE, 2015)
Background Glaucoma is a leading cause of irreversible blindness. It is firmly entrenched in the traditional treatment paradigm to start with pharmacotherapy. However, pharmacotherapy is not benign and has been well documented to have a number of significant challenges. Minimally invasive glaucoma surgery (MIGS) that targets the outflow pathway with minimal to no scleral dissection has resulted in the need to reconsider the glaucoma treatment paradigm. Purpose To perform a systematic review and meta-analysis to evaluate and quantify the effect on post-operative intraocular pressure (IOP) and number of topical glaucoma medications, in patients receiving the iStent MIGS device as the solo procedure without concurrent cataract surgery. Methods A systematic review was conducted by searching various databases between January 1, 2000, and June 30, 2014. Studies reporting up to a maximum follow-up period of 24 months were retrieved and screened using the EPPI-Reviewer 4 gateway. Percentage reduction in IOP (IOPR%), and mean reduction in topical glaucoma medications after surgery were computed. Meta-analysis was performed using STATA v. 13.0. The standardized mean difference (SMD) was calculated as the effect size for continuous scale outcomes. Heterogeneity was determined using the I-2 statistics, Z-value, and chi(2) statistics. Fixed-effect and random-effect models were developed based on heterogeneity. Sub-group analysis was performed based on the number of iStents implanted and the follow-up period. The outcome measures were changes in the IOP and number of glaucoma medications. Results The search strategy identified 105 records from published literature and 9 records from the grey literature. Five studies with 248 subjects were included for quantitative synthesis. A 22% IOP reduction (IOPR%) from baseline occurred at 18-months after one iStent implant, 30% at 6-months after two iStents implantations, and 40% at 6-months after implantation of three iStents. A mean reduction of 1.2 bottles per patient of topical glaucoma medications occurred at 18-months after one iStent implant, 1.45 bottles per patient at 6-months after two iStents, and one bottle of medication per patient was reduced at 6-months following placement of three iStents implants. Meta-analysis results showed a significant reduction in the IOP after one iStent (SMD = -1.68, 95% CI: [-2.7, -0.61]), two iStents (SMD = -1.88, 95% CI: [-2.2, -1.56]), and three iStents (SMD = -2, 95% CI: [-2.62, -1.38]) implantation. Results showed a significant drop in the topical glaucoma medications after one iStent (SMD = -2.11, CI: [-3.95, -0.27]), two iStent (SMD = -1.88, CI: [-2.20, -1.56]), and three iStents (SMD = -2.00, CI: [-2.62, -1.38]) implantation. The maximum reduction in IOP occurred at 12-months (SMD = -2.21, CI: [-2.53, -1.88]) and a significant reduction in post-operative topical glaucoma medications occurred even after 18-months of iStent implantation (SMD = -0.71, CI: [-1.15, -0.26]). Conclusion iStent implantation as a solo procedure without concurrent cataract extraction does lower IOP, and reduces the dependency on glaucoma medications. This effect seems to last at least 18 months.

Intraocular pressure reduction in the untreated fellow eye after selective laser trabeculoplasty - Rhodes, KM; Weinstein, R; Saltzmann, RM; Aggarwal, N; Kooner, KS; Petroll, WM; Whitson, JT (CURRENT MEDICAL RESEARCH AND OPINION, 2009)
Objective: To investigate the effect of selective laser trabeculoplasty (SLT) on the intraocular pressure (IOP) of untreated fellow eyes in patients with open-angle glaucoma. Study design: Retrospective chart review. Patients and methods: Charts of all patients who underwent SLT at the University of Texas Southwestern Medical Center at Dallas between September 2003 and May 2006 were reviewed. Each patient had IOP measurements by Goldmann applanation tonometry in both eyes preoperatively, and at 1 hour, 2 weeks, 3 months, and 6 months postoperatively. Patient age, gender, diagnosis, central corneal thickness (CCT), previous intraocular surgeries, and degrees of laser treatment were tabulated for each patient. Patients with a history of previous glaucoma surgery in either eye were excluded as were those who underwent any change in glaucoma medications or further laser or surgical intervention in either eye within 6 months of SLT. Data were analyzed using a paired two-tailed t-test, an unpaired two-tailed t-test, ANOVA, and linear regression. Results: A total of 43 patients were included through 6 months of follow-up. Mean reduction in IOP in the treated eye was 3.9 +/- 0.6 mmHg or 18.8% (p<0.001) at final exam. Mean IOP reduction in the fellow untreated eye was 2.1 +/- 0.5 mmHg or 11.2% (p<0.01). Patients with higher preoperative IOPs had a greater reduction in IOP in both eyes (p<0.001 for treated eyes, and p=0.02 for untreated eyes). Patients who were on a larger number of glaucoma medications preoperatively had a greater response in both eyes (treated eye p=0.002, untreated eye p=0.008). There was no significant difference in IOP response in either eye based on age, gender, CCT, degrees of treatment, or phakic status. Conclusions: SLT produces a sustained and statistically significant IOP reduction in the fellow untreated eyes of patients with open-angle glaucoma. The results of our study support a biological mechanism of action for SLT. Limitations of this study include its retrospective design, relatively small sample size, a possible effect of increased compliance with medical therapy following SLT, and an inherent bias of excluding patients who underwent a change in medications or further laser or surgical therapy during the period under review.

Effectiveness of Intraocular Pressure-Lowering Medication Determined by Washout - Jampel, HD; Chon, BH; Stamper, R; Packer, M; Han, Y; Nguyen, QH; Ianchulev, T (JAMA OPHTHALMOLOGY, 2014)
IMPORTANCE While medication efficacy is well documented in clinical trials, less is known of medication effectiveness in real-world clinical settings. OBJECTIVE To assess the effectiveness of intraocular pressure (IOP)-lowering medications in patients with open-angle glaucoma. DESIGN, SETTING, AND PARTICIPANTS Prospective, multicenter, interventional cohort from the prerandomization phase of a randomized clinical trial at multiple ophthalmology clinics. A total of 603 patients (603 eyes) with primary open-angle glaucoma who were using up to 3 glaucoma medications were included. INTERVENTIONS One IOP measurement was made while the patient was using his or her usual medications to lower IOP (ON IOP). Eligible participants underwent washout of all IOP-lowering drops, and the diurnal IOP was measured 2 to 4 weeks later (OFF IOP). MAIN OUTCOMES AND MEASURES Difference between OFF IOP and ON IOP. The hypothesis was formulated after data collection. RESULTS The mean (SD) ON IOPs for participants using 0 (n = 102), 1 (n = 272), 2 (n = 147), or 3 (n = 82) medications were 24.2 (3.2), 17.5 (3.2), 17.2 (3.1), and 17.2 (3.1) mm Hg, respectively. Patients not using medication had a mean (SD) IOP decrease of 0.2 (2.8) mm Hg at the OFF visit. Patients using 1, 2, and 3 medications had mean (SD) IOP increases of 5.4 (3.0), 6.9 (3.3), and 9.0 (3.8) mm Hg, respectively, at the OFF visit. The percentages of patients with less than a 25% increase in IOP were 38%, 21%, and 13% for those using 1, 2, and 3 medications, respectively. CONCLUSIONS AND RELEVANCE Discontinuation of 1, 2, and 3 medications was associated with a clinically significant increase in IOP, although with smaller effects for the second and third medications compared with the first medication. A substantial proportion of patients showed only small changes in IOP after medication washout, suggesting either that they were not using the medication effectively or that the medication itself, although used properly, was not lowering the IOP.

A Population-based Study of Care-seeking Behavior in Rural Tanzanians With Glaucoma Blindness - Lewallen, S; Hassan, HG; Al Attas, AH; Courtright, P (JOURNAL OF GLAUCOMA, 2011)
Purpose: To describe the care-seeking behavior of a representative sample of rural Africans blind from glaucoma. Patients and Methods: Patients blind from posterior segment diseases (including diseases affecting the retina or optic nerve) were identified though a population-based survey in Kilimanjaro Region, Tanzania in 2007. A year later they were traced to their homes to detail the diagnoses with more thorough examination. In-depth interviews were conducted to determine healthcare sought and received and symptoms which prompted this. Data were analyzed by framework analysis. Results: Of 30 patients previously identified, 20 were found and interviewed, 4 had died, 2 had moved, 2 lived too far to trace, and 2 could not be located. The average age was 77 years. Few patients could give a clear temporal history of how their vision failed or a sequential description of visits made to healthcare facilities over the years. However, every patient had sought eye care and most made numerous visits. Understanding of the disease and treatment was uniformly limited. Most received topical medicines and the histories of nonglaucoma and glaucoma blind were similar except that 5 glaucoma patients had received surgery. Patients described obstacles to care including poverty and other lack of support. Conclusions: These findings contrast to previous which showed that most rural Africans blind from glaucoma have not sought or received treatment. It is likely that this is partly the result of widely accessible services offered in Kilimanjaro Region. However, the challenges in treating this chronic disease are highlighted.

Blood-aqueous barrier changes after the use of prostaglandin analogues in patients with pseudophakia and aphakia - A 6-month randomized trial - Arcieri, ES; Santana, A; Rocha, FN; Guapo, GL; Costa, VP (ARCHIVES OF OPHTHALMOLOGY, 2005)
Objectives: To investigate the effects of prostaglandin analogues on the blood-aqueous barrier and to evaluate the occurrence of cystoid macular edema in aphakic or pseudophakic patients with glaucoma. Methods: in this randomized, masked-observer, 6-month clinical trial, patients with primary open-angle, pseudophakic, or aphakic glaucoma were treated once daily with bimatoprost (n = 16), latanoprost (n = 15), or travoprost (n = 17) or twice daily with unoprostone (n = 16) or lubricant drops (control group) (n = 16). Blood-aqueous barrier status, which was assessed using a laser flare meter; intraocular pressure; the occurrence of angiographic cystoid macular edema; and conjunctival hyperemia were evaluated. Results: Mean flare values were significantly higher in the bimatoprost, latanoprost, and travoprost groups throughout follow-up (P < .02). Four latanoprost-treated eyes, 1 bimatoprost-treated eye, and 1 travoprost-treated eye developed cystoid macular edema; all cases resolved after discontinuation of the prostaglandin analogue and treatment with topical diclofenac sodium. Mean intraocular pressure reductions after 6 months were higher for the latanoprost (26%), bimatoprost (28%), and travoprost (29%) groups than for the control (3%) and unoprostone (14%) groups (P < .05). Bimatoprost induced significantly higher hyperemia scores than latanoprost, unoprostone, and placebo (P < .01). Conclusion: Bimatoprost, latanoprost, and travoprost use may lead to disruption of the blood-aqueous barrier in patients with pseudophakia and aphakia.

Disorder of blood-aqueous barrier following Ahmed Glaucoma Valve implantation - Zhou, MW; Wang, W; Chen, SD; Huang, WB; Zhang, XL (CHINESE MEDICAL JOURNAL, 2013)
Background Ahmed Glaucoma Valve implantation (AGVI) is used to treat refractory glaucoma. Breakdown of the blood-aqueous barrier (BAB) has been noted after some surgical techniques. The current study was designed to assess BAB disruption after AGVI. Methods Anterior chamber protein content was measured by the laser flare cell photometry in 22 eyes of 22 patients with refractory glaucoma before AGVI and at each postoperative visit up to 1 month. Results Before AGVI the mean aqueous flare values in all eyes were (15.17 +/- 9.84) photon counts/ms. After AGVI, the values significantly increased at day 1, day 3, and week 1 compared to those before AGVI (all P <0.05) with a peak at day 3. They returned to pre-operative levels at week 2, and were lower than preoperative level at month 1. Eyes with previous intraocular surgery history had greater aqueous flare values than those without previous intraocular surgery history, but there were no significant differences at all time points postoperatively (all P >0.05). Furthermore, eyes with shallow anterior chambers had greater aqueous flare values at day 3 and week 1 (all P <0.05). When comparing eyes with other refractory glaucoma conditions, neovascular glaucoma combined with intravitreal bevacizumab injection resulted in lower aqueous flare values after AGVI, but no significant differences were observed at all time points, postoperatively (all P >0.05). Conclusions The BAB was impaired and inflammation was present in the anterior chamber in refractory glaucomatous eyes following AGVI. However, such conditions were resolved within 1 month postoperatively. Intravitreal bevacizunnab treatment in neovascular glaucoma eyes before AGVI may prevent BAB breakdown.

NONCONTACT TONOMETRY IN CHILDREN - BUSCEMI, M; CAPOFERRI, C; GARAVAGLIA, A; NASSIVERA, C; NUCCI, P (OPTOMETRY AND VISION SCIENCE, 1991)
A hand-held noncontact tonometer (Pulsair, Keeler Ltd., UK) was tested in 42 children, from 5 months to 12 years of age. At least 1 intraocular pressure (IOP) reading was obtained in all of the 84 eyes studied, whereas with a Goldman applanation tonometer measurements could be obtained in only 26 eyes (14 subjects). Time required for examination with the Pulsair was quite variable and related to age (p < 0.0001). Compliance in children was reported as "good" in the majority of cases; it was also age-related (p < 0.005). Although its reliability could not be definitely evaluated, the results of this study indicate that this instrument may be a valuable choice for screening and follow-up purposes in childhood.

Long-term surgical and visual outcomes in primary congenital glaucoma: 360 degrees trabeculotomy versus goniotomy - Mendicino, ME; Lynch, MG; Drack, A; Beck, AD; Harbin, T; Pollard, Z; Vela, MA; Lynn, MJ (JOURNAL OF AAPOS, 2000)
Purpose: To compare the visual outcome and refractive status of children with primary congenital glaucoma who underwent 360 degrees trabeculotomy or goniotomy as an initial surgical procedure. Methods: This retrospective study describes 24 eyes (15 patients) with primary congenital glaucoma that underwent 360 degrees trabeculotomy as the initial procedure and 40 eyes (23 patients) that underwent goniotomy as the initial procedure. Inclusion criteria were. (1) diagnosis of primary congenital glaucoma and initial angle surgery before 1 year of age, (2) no other ocular or systemic diseases, (3) 360 degrees trabeculotomy or goniotomy as the first surgical procedure, and (4) ability to obtain an Alien or Snellen visual acuity. A postoperative vision of 20/50 or better was considered good. Surgical success was defined as an intraocular pressure (IOP) less than 22 mm Hg with or without medication and without evidence of a progressive optic neuropathy. Results: The IOP was successfully controlled in 92% of eyes in the trabeculotomy group and in 58% of eyes in the goniotomy group (P = .004). Of eyes in the trabeculotomy group, 79% had vision of 20/50 or better compared with 53% in the goniotomy group (P = .03). High myopia was more prevalent in the goniotomy group, but this difference was not statistically significant (P = .16). A poor visual outcome was associated with failure of the angle surgery or poor compliance with follow-up and amblyopia therapy. Conclusion: For primary congenital glaucoma, 360 degrees trabeculotomy is a highly effective procedure that results in excellent pressure control and is at least as successful as multiple standard procedures. In this study, 360 degrees trabeculotomy resulted in better vision than what is reported in the literature for standard angle procedures.

A Study of Initial Therapy for Glaucoma in Southern India: India Glaucoma Outcomes and Treatment (INGOT) Study - Congdon, NG; Krishnadas, R; Friedman, DS; Goggins, W; Ramakrishnan, R; Kader, MA; Gilbert, D; Tielsch, J; Quigley, HA (OPHTHALMIC EPIDEMIOLOGY, 2012)
Purpose: To compare initial glaucoma therapy with medications and trabeculectomy in southern India. Methods: Patients aged >= 30 years newly diagnosed with glaucoma were randomized to trabeculectomy with 5-fluorouracil or medical therapy. Subjects with best-corrected vision <6/18 due to cataract underwent phacoemulsification (phaco/intraocular lens, IOL). Intraocular pressure (IOP), vision and visual function were assessed at 12 months. Results: Patients assigned to medications and surgery received the expected therapy in 86% (172/199) and 64% (126/199) of cases, respectively. Forty patients (20%) assigned to surgery refused any treatment and 33 (17%) received medications. Among 199 patients randomized to medications, 52 (26.1%) underwent phaco/IOL, as did 89/199 (43.7%) of patients randomized to trabeculectomy. Baseline parameters of the two groups did not differ, nor did 1-year follow-up rates (medication 65%, trabeculectomy 58%, P = 0.15). Final IOP was lower with randomization to trabeculectomy (16.3 +/- 5.1 mmHg) than medication (18.8 +/- 6.7 mmHg, P < 0.0001). In regression models, randomization to trabeculectomy (P < 0.0001) was associated with lower IOP, and simultaneous trabeculectomy and cataract surgery was associated with higher IOP (P = 0.008) than trabeculectomy alone. Subjects receiving Phaco/IOL had significantly better final acuity (P < 0.0001) and visual function (P = 0.035), despite concurrent glaucoma treatment. Final visual acuity was worse in those receiving trabeculectomy in addition to cataract surgery, but this was of borderline significance (P = 0.06). Conclusions: Trabeculectomy lowered IOP significantly more than medical treatment, but with slightly greater loss of visual acuity. Combined phaco/IOL and trabeculectomy improved visual acuity with substantial IOP lowering.

Phase 3, Randomized, 20-Month Study of Bimatoprost Implant in Open-Angle Glaucoma and Ocular Hypertension (ARTEMIS 1) - Medeiros, FA; Walters, TR; Kolko, M; Coote, M; Bejanian, M; Goodkin, ML; Guo, Q; Zhang, J; Robinson, MR; Weinreb, RN; ARTEMIS 1 Study Grp (OPHTHALMOLOGY, 2020)
Purpose: To evaluate the intraocular pressure (IOP)-lowering efficacy and safety of 10- and 15-mg bimatoprost implant in subjects with open-angle glaucoma (OAG) and ocular hypertension (OHT) after initial and repeated administrations. Design: Randomized, 20-month, multicenter, subject- and efficacy evaluator-masked, parallel-group, phase 3 clinical study. Participants: Adults with OAG or OHT in each eye, open iridocorneal angle inferiorly in the study eye, and study eye baseline IOP (hour 0; 8 AM) of 22-32 mmHg after washout. Methods: Study eyes received bimatoprost implant 10 mg (n = 198) or 15 mg (n = 198) on day 1 with readministration at weeks 16 and 32, or twice-daily topical timolol maleate 0.5% (n = 198). Intraocular pressure was measured at hours 0 and 2 at each visit. Main Outcome Measures: Primary end points were IOP and change from baseline IOP through week 12. Safety measures included treatment-emergent adverse events (TEAEs) and corneal endothelial cell density (CECD). Results: Both dose strengths of bimatoprost implant were noninferior to timolol in IOP lowering after each administration. Mean diurnal IOP was 24.0, 24.2, and 23.9 mmHg at baseline and from 16.5-17.2, 16.5-17.0, and 17.1-17.5 mmHg through week 12 in the 10-mg implant, 15-mg implant, and timolol groups, respectively. The incidence of corneal and inflammatory TEAEs of interest (e.g., corneal endothelial cell loss, iritis) was higher with bimatoprost implant than timolol and highest with the 15-mg dose strength. Incidence of corneal TEAEs increased after repeated treatment; with 3 administrations at fixed 16-week intervals, incidence of >= 20% CECD loss was 10.2% (10-mg implant) and 21.8% (15-mg implant). Mean best-corrected visual acuity (BCVA) was stable; 3 implant-treated subjects with corneal TEAEs had >2-line BCVA loss at their last visit. Conclusions: Both dose strengths of bimatoprost implant met the primary end point of noninferiority to timolol through week 12. One year after 3 administrations, IOP was controlled in most subjects without additional treatment. The risk-benefit assessment favored the 10-mg implant over the 15-mg implant. Ongoing studies are evaluating other administration regimens to reduce the potential for CECD loss. The bimatoprost implant has potential to improve adherence and reduce treatment burden in glaucoma. (C) 2020 by the American Academy of Ophthalmology.

Long-Term Visual Outcomes of Secondary Intraocular Lens Implantation in Children with Congenital Cataracts - Rong, XF; Ji, YH; Fang, YW; Jiang, YX; Lu, Y (PLOS ONE, 2015)
Aim The aim of this study was to evaluate the long-term visual outcomes and factors affecting visual results in children undergoing secondary intraocular lens (IOL) implantation following primary congenital cataract extraction. Methods Children with congenital cataracts who underwent secondary IOL implantation for aphakia at the Eye and ENT Hospital of Fudan University between January 1, 2001, and December 31, 2007, were retrospectively reviewed. One eye was randomly selected in children with bilateral cataracts. Laterality, type of cataract (total or partial opacity), sex, age at primary and secondary surgeries, visual axis opacity (VAO), compliance with amblyopia therapy, postoperative ocular complications, refractive error, ocular alignment, and best corrected visual acuity (BCVA) at last follow-up were recorded; potential factors that might have affected the visual results were evaluated. Results Seventy-six bilateral and 34 unilateral congenital cataract cases were analyzed; the mean ages of the children were 12.70 +/- 5.06 and 12.50 +/- 2.71 years at final follow-up, the mean follow-up periods from IOL implantation were 94.93 +/- 24.22 and 109.09 +/- 18.89 months, and the mean BCVA (Log MAR) values were 0.51 +/- 0.37 and 1.05 +/- 0.46, respectively. Final BCVA after secondary IOL implantation was significantly associated with laterality, type of cataract, age at primary cataract extraction, compliance with amblyopia therapy, and refractive correction after surgery. No significant associations were found between BCVA and sex, age at secondary IOL implantation, VAO, or other ocular complications. The most common ocular complications were VAO and elevated intraocular pressure after surgery. There were no other complications, with the exception of one eye with IOL dislocation. Conclusions The results indicate that the important determinants of long-term visual outcomes in children with congenital cataracts undergoing secondary IOL implantation are laterality, cataract type, age at initial cataract extraction, compliance with amblyopia therapy, and refractive error.

Surgical Management of Severe Complications Arising from Uveitis in Juvenile Idiopathic Arthritis - Langner-Wegscheider, BJ; de Smet, MD (OPHTHALMOLOGICA, 2014)
Purpose: Evaluate outcomes from severe ocular complications of juvenile idiopathic arthritis following surgery. Methods: Eleven eyes of 7 patients underwent complete vitrectomy and peeling of the inner limiting membrane. Inclusion criteria were: anteroposterior segment involvement, hypotony, inflammation control of less than 3 months, compliance issues, rapidly progressive disease. Phacoemulsification was allowed if the patient was >6 years old and inflammation free >3 months. The alternative was a complete lensectomy. Results: Visual acuity improved from a logMAR of 1.48 to 0.37 (p < 0.0001), and 0.20 at 6 and 12 months (p < 0.0001). No flare-up was observed within the first 6 months. Five eyes developed inflammation between 7 and 19 months. Glaucoma developed in 5 eyes at a median of 16 months. No patient developed cystoid macular edema. Conclusion: Extensive pars plana vitrectomy and cataract extraction can lead to significant improvement in visual acuity. Patients continue to require long-term immunosuppression and adequate follow-up. (C) 2014 S. Karger AG, Basel

Assessing the cost-effectiveness of switching from a beta-blocker to latanoprost in the treatment of ocular hypertension - Costagliola, C; Parmeggiani, F; Sebastiani, A (EXPERT OPINION ON PHARMACOTHERAPY, 2003)
Glaucoma is a pathological condition whose most important risk factor is increased intraocular pressure (IOP). The medical treatment of glaucoma essentially consists of compounds that are able to decrease the IOP. The compounds discussed in this review act in a different way, beta-blockers mainly inhibit the production of aqueous humor, whereas latanoprost decreases the resistance in the outflow channels. beta-Blockers are compounds with a well-known efficacy and safety profile and they are fairly inexpensive. Their systemic and local side effects are mainly cardiovascular and pulmonary adverse events, dry eye and keratopathy. Latanoprost, which has recently been introduced into the market, has been shown to be equally as effective, or better in lowering IOP in patients than timolol, although it is more expensive. Systemic reported side effects are anecdotal; local hyperaemia, keratopathy, hypertrichosis, increased pigmentation of eyelashes and iris, uveitis and cystoid macular oedema have been reported. A comparison of costs reveals that a 1-year therapy with timolol ophthalmic solution starts from Euro11.00 and can reach Euro146.00 for the most expensive preservative-free 1-day dispenser packages (similar to 13.5 times higher). For latanoprost once-daily administration, the cost for 1-years therapy is Euro98.55, approximately six times higher than generic or brand 0.5% timolol applied twice-daily. What are the factors influencing a change in therapy from beta-blockers to latanoprost? The only good reason is represented by a further deterioration in the visual field. This may occur, despite a significant reduction in IOP, because the reached IOP is not sufficient enough to avoid further deterioration because the patient's work or social activities do not allow a correct daily dosage of the compound (bad compliance); or as a result of treatment suspension, because of the development of systemic and/or local side effects. Changes in therapy must always be related,to a failing control of the disease, as any therapeutic modification leading to an increase in the number of visits and additional examinations, consequently enhances the costs.

Sociodemographic status of severely disabled and visually impaired elderly people in Turkey - Kivanc, SA; Akova-Budak, B; Olcaysu, OO; Cevik, SG (ARQUIVOS BRASILEIROS DE OFTALMOLOGIA, 2016)
Purpose: To identify the prevalence of ophthalmologic diseases in elderly patients who had been classified as severely disabled and to identify the ophthalmologic conditions leading to visual impairment and blindness. Methods: The medical records of 2806 patients who had applied to the Health Board of the Erzurum Region Training and Research Hospital between January 2011 and December 2012 were reviewed. One hundred ninety-nine patients aged >64 years who were classified as severely disabled with disability rates of over 50%, and who were unable to care for themselves or to move and/or communicate without help were included in the study. Results: The most frequently seen disabilities were neurological (47.2%) and those resulting from eye diseases (17.1%). The most common ophthalmologic diseases were cataract, glaucoma, and age-related macular degeneration. The mean right and left eye visual acuities were 1.17 +/- 1.10 logMAR and 1.13 +/- 1.0 logMAR, respectively. Of the 60 patients with ophthalmologic diseases or conditions, 33 were blind (visual acuity worse than 20/400) and 10 were visually impaired (visual acuity worse than 20/70 but better than 20/400). Cataracts were the main cause of blindness. The mean age of the patients who were still being followed up at the time of application to the disability board was significantly lower than that of the others (p=0.015). Seventy-nine percent of the blind patients were from rural areas, and 88% of these had no regular follow-up. Among the blind and visually impaired, significantly more patients from urban areas had social security insurance (SSI) than those from rural areas (p-0.043). Nearly 64% of the blind patients were women. The follow-up rate was significantly lower in women (p=0.025). According to multinomial logistic regression analysis, the visually impaired and blind patients were more likely to have lower follow-up rates than the other types of severely disabled patients (OR: 0.231, 95% CI: 0.077-0.688, p=0.009). Conclusions: Blindness gives rise to severe disability, and the most common ophthalmologic diseases that cause severe disabilities in elderly patients are cataract, glaucoma, and age-related macular degeneration. Sociodemographic factors that may affect the accessibility of visually impaired and blind people to health services include their place of residence and gender.

Minimally-invasive glaucoma surgeries (MIGS) for open angle glaucoma: A systematic review and meta-analysis - Lavia, C; Dallorto, L; Maule, M; Ceccarelli, M; Fea, AM (PLOS ONE, 2017)
Background MIGS have been developed as a surgical alternative for glaucomatous patients. Purpose To analyze the change in intraocular pressure (IOP) and glaucoma medications using different MIGS devices (Trabectome, iStent, Excimer Laser Trabeculotomy (ELT), iStent Supra, CyPass, XEN, Hydrus, Fugo Blade, Ab interno canaloplasty, Goniscopy-assisted transluminal trabeculotomy) as a solo procedure or in association with phacoemulsification. Methods Randomized control trials (RCT) and non-RCT (non randomized comparative studies, NRS, and before-after studies) were included. Studies with at least one year of follow-up in patients affected by primary open angle glaucoma, pseudoexfoliative glaucoma or pigmentary glaucoma were considered. Risk of Bias assessment was performed using the Cochrane Risk of Bias and the ROBINS-I tools. The main outcome was the effect of MIGS devices compared to medical therapy, cataract surgery, other glaucoma surgeries and other MIGS on both IOP and use of glaucoma medications 12 months after surgery. Outcomes measures were the mean difference in the change of IOP and glaucoma medication compared to baseline at one and two years and all ocular adverse events. The current meta-analysis is registered on PROSPERO (reference n degrees CRD42016037280). Results Over a total of 3,069 studies, nine RCT and 21 case series with a total of 2.928 eyes were included. Main concerns about risk of bias in RCTs were lack of blinding, allocation concealment and attrition bias while in non-RCTs they were represented by patients' selection, masking of participants and co-intervention management. Limited evidence was found based on both RCTs and non RCTs that compared MIGS surgery with medical therapy or other MIGS. In before-after series, MIGS surgery seemed effective in lowering both IOP and glaucoma drug use. MIGS showed a good safety profile: IOP spikes were the most frequent complications and no cases of infection or BCVA loss due to glaucoma were reported. Conclusions Although MIGS seem efficient in the reduction of the IOP and glaucoma medication and show good safety profile, this evidence is mainly derived from non-comparative studies and further, good quality RCTs are warranted.

Short-Term Efficacy and Safety of Switching from a Latanoprost/Timolol Fixed Combination to a Latanoprost/Carteolol Fixed Combination - Inoue, K; Piao, H; Iwasa, M; Ishida, K; Tomita, G (CLINICAL OPHTHALMOLOGY, 2020)
Purpose: To investigate the short-term intraocular pressure-lowering efficacy and safety of switching from a fixed combination of latanoprost/timolol to a fixed combination of latanoprost/carteolol. Patients and Methods: The subjects were 30 eyes of 30 adult patients with primary openangle glaucoma, normal-tension glaucoma, or ocular hypertension who were using a latanoprost-/timolol-fixed combination with insufficient intraocular pressure-lowering efficacy or adverse reactions. The subjects were switched from once-daily latanoprost/timolol to once-daily latanoprost/carteolol with no washout interval. Intraocular pressure, tear film break-up time, corneal epithelial defects, conjunctival hyperemia, blood pressure, and pulse rate were measured and compared before and 1 and 3 months after switching. Patients were monitored for adverse reactions at each visit, and dropouts were recorded. Results: The mean intraocular pressure at 1 month (15.9 +/- 3.1 mmHg) and 3 months (16.3 +/- 3.8 mmHg) was not significantly different from that at baseline (16.1 +/- 3.1 mmHg). The tear film break-up time and corneal epithelial defects were significantly improved after switching (p<0.01 and p<0.0001, respectively). There was a significant decrease in systolic blood pressure after 1 month and diastolic pressure after 3 months (p<0.05). There was no significant change in pulse rate during the study. Adverse reactions (blurred vision, blepharitis, and conjunctival hyperemia) occurred in 3 patients (10.0%). Four patients (13.3%) discontinued treatment during the 3-month study period. Conclusion: A switch from a fixed combination of latanoprost/timolol to that of latanoprost/carteolol can maintain intraocular pressure and adherence with once-daily administration while improving tear film break-up time and corneal epithelial defects.

A Phase 2, Randomized, Dose-Response Trial of Taprenepag Isopropyl (PF-04217329) Versus Latanoprost 0.005% in Open-Angle Glaucoma and Ocular Hypertension - Schachar, RA; Raber, S; Courtney, R; Zhang, M (CURRENT EYE RESEARCH, 2011)
Purpose: To evaluate the safety of escalating doses of taprenepag isopropyl (PF-04217329), a selective EP(2) receptor agonist administered as a topical ophthalmic solution, versus its vehicle (Stage I), and dose-response of taprenepag isopropyl alone and in unfixed combination with latanoprost ophthalmic solution 0.005% versus latanoprost alone (Stage II). Subjects and Methods: Randomized, vehicle-and active-controlled, double-masked, two-stage, dose-finding trial in primary open-angle glaucoma (POAG) or ocular hypertension; first taprenepag isopropyl study in patients (NCT00572455). Study eye: 26 mmHg <= intraocular pressure (IOP) <36 mmHg at 8 am and 22 mmHg <= IOP <36 mmHg at 10 am, 1 pm, 4 pm. Stage I: 3 cohorts (total n = 67) received 1 drop of taprenepag isopropyl unit dose formulation qPM/eye for 14 days: low dose: 0.0025%, 0.005%, vehicle; middle dose: 0.01%, 0.015%, vehicle; high dose: 0.02%, 0.03%, vehicle. Stage II: 7 groups (total n = 250) received 1 drop of taprenepag isopropyl multidose formulation qPM/eye for 28 days: 0.005%, 0.01%, 0.015% monotherapy; each in unfixed combination with latanoprost 0.005%, or latanoprost monotherapy. Main outcomes: mean change in diurnal IOP, baseline to last visit; adverse events. Results: Stage I at Day 14: statistically significantly greater IOP reductions were observed at all taprenepag isopropyl doses versus vehicle. Stage II at Day 28: statistically significantly greater IOP reductions were observed at all doses of the unfixed combination versus latanoprost monotherapy. At least 1 treatment-emergent adverse event reported for 29/67 (43.3%) subjects in Stage I and 158/250 (63.2%) in Stage II. Conclusions: Taprenepag isopropyl significantly reduces IOP in POAG and ocular hypertension. Taprenepag isopropyl monotherapy is comparable to latanoprost 0.005% in reducing IOP. As demonstrated in this report, the activity of taprenepag isopropyl is additive to that of latanoprost 0.005%. Further studies are required to determine whether it shows similar additivity when administered with other ocular antihypertensive medications.

THE EFFECT OF ARGON-LASER TRABECULOPLASTY ON THE BLOOD-AQUEOUS BARRIER AND INTRAOCULAR-PRESSURE IN HUMAN GLAUCOMATOUS EYES TREATED WITH DICLOFENAC 0.1-PERCENT - DIESTELHORST, M; THULL, D; KRIEGLSTEIN, GK (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 1995)
Background: We studied the effect of argon laser trabeculoplasty (ALT) on the blood-aqueous barrier (BAB) in 41 eyes of 41 patients with primary open-angle glaucoma, pseudoexfoliation glaucoma, or pigment dispersion glaucoma using the Fluorotron Master II. Methods: Fluorophotometry was performed the day before ALT and on the 3rd day after surgery at 30 and 60 min after intravenous injection of 7 mg/kg body weight sodium fluorescein 10%. Intraocular pressure (IOP) was measured using Goldmann applanation tonometry on the day before surgery and at 3rd days and 1 year (mean) after ALT. Patients were treated with argon laser by one surgeon (180 degrees, 0.1 s, 50 mu m 0.6-1.0 W, 56 laser burns). Eyes were randomly assigned to either diclofenac-sodium 0.1% eye drops or vehicle. Eye drops were applied six times 1 h before ALT into the operated eyes and five times daily for 3 days postoperatively. Results: On the 3rd day after ALT there was significant disruption of the BAB in the placebo-treated eyes compared to the diclofenac 0.1%-treated eyes. In the placebo-treated eyes as well as in diclofenac-sodium 0.1%-treated eyes there was a significant decrease of IOP postoperatively for up to 1 year. There was no significant difference concerning the IOP reduction after 1 year. Diclofenac-sodium 0.1% eye drops significantly stabilized the BAB on the 3rd day after ALT, compared to placebo, in this model. Conclusion: Diclofenac-sodium 0.1% significantly stabilized the disruption of the blood-aqueous barrier on the 3rd day after ALT. Concerning the IOP-lowering effect of ALT, the postoperative application of steroids should be avoided.

The Safety and Efficacy of Brinzolamide 1%/Timolol 0.5% Fixed Combination Versus Dorzolamide 2%/Timolol 0.5% in Patients With Open-angle Glaucoma or Ocular Hypertension - Manni, G; Denis, P; Chew, P; Sharpe, ED; Orengo-Nania, S; Coote, MA; Laganovska, G; Volksone, L; Zeyen, T; Filatori, I; James, J; Aung, T (JOURNAL OF GLAUCOMA, 2009)
Purpose: This study compared the intraocular pressure (IOP)lowering efficacy of 2 fixed combination products, brinzolamide 1%/timolol 0.5% suspension (Azarga, Brinz/Tim) and dorzolamide 2%/timolol 0.5% solution (Dorz/Tim), in patients with open-angle glaucoma or ocular hypertension who required a change in therapy due to elevated IOP while receiving IOP-lowering medication. Methods: This was a one-year, multicenter, randomized, double-masked. active-controlled, parallel-group trial of Brinz/Tim and Dorz/Tim. IOP assessments were taken at 8 and 10 Ant at week 2 and months 3 and 9, and at 8 AM, 10 AM, and 4 PM at months 6 and 12. Primary efficacy was a noninferiority comparison of mean IOP at the three month 6 time points. Results: Of the 437 patients enrolled. 220 dosed Brinz/Tim whereas 217 dosed Dorz/Tim twice daily. Brinz/Tim produced IOP-lowering efficacy comparable to Dorz/Tim, with the upper 95% confidence limits for the differences between groups within + 1.5 mm Hg at all assessment times, including the month 6 primary efficacy time points, establishing noninferiority. Differences in means numerically favored Brinz/Tim at 9 of 12 study visits and times. The IOP reductions ranged from 7.2 to 9.2 mm Hg for Brinz/Tim and from 7.4 to 8.9 mm Hg for Dorz/Tim. Although a similar overall safety profile was observed between the 2 treatment groups, Brinz/Tim showed significantly less ocular irritation (2.7% vs. 10.6%; P = 0.0009) than Dorz/Tim. Conclusions: Brinz/Tim suspension provides statistically significant and clinically relevant IOP-lowering efficacy that is noninferior to Dorz/Tim. Additionally, Brinz/Tim affords an ocular comfort advantage compared with Dorz/Tim.

Initial Clinical Experience With the CyPass Micro-Stent: Safety and Surgical Outcomes of a Novel Supraciliary Microstent - Hoeh, H; Vold, SD; Ahmed, IK; Anton, A; Rau, M; Singh, K; Chang, DF; Shingleton, BJ; Ianchulev, T (JOURNAL OF GLAUCOMA, 2016)
Purpose: To evaluate safety and clinical outcomes of a novel supraciliary device, the CyPass Micro-Stent, for surgical treatment of open-angle glaucoma when implanted in conjunction with cataract surgery. Patients and Methods: Subjects (n = 142) with open-angle glaucoma and cataract underwent combined phacoemulsification, with intraocular lens insertion, and microstent implantation into the supraciliary space of study eyes (n = 167). Two analysis cohorts were prespecified based upon medicated baseline intraocular pressure (IOP): >= 21 mm Hg (cohort 1, n = 65) or < 21 mm Hg (cohort 2, n = 102). Glaucoma medications were discontinued or tapered at surgery, and restarted at investigator discretion. The main postoperative outcome measures were adverse events, IOP changes, and number of IOP-lowering medications. Results: Mean +/- SD follow-up was 294 +/- 121 days. No major intraoperative or postoperative complications occurred. Preoperative baseline mean IOP was 20.2 +/- 6.0 mm Hg and mean number of IOP-lowering medications was 2.0 +/- 1.1. Cohort 1 showed a 35% decrease in mean IOP and a 49% reduction in mean glaucoma medication usage; cohort 2 demonstrated a 75% reduction in mean medication usage while maintaining mean IOP < 21 mm Hg. For all eyes, mean IOP at 12 months was 15.9 +/- 3.1mm Hg (14% reduction from baseline). Early and late postoperative IOP elevation occurred in 1.2% and 1.8% of eyes, respectively. Two subjects developed mild transient hyphema, and none exhibited prolonged inflammation, persistent hypotony, or hypotony maculopathy. Conclusions: CyPass Micro-Stent implantation, combined with cataract surgery, resulted in minimal complications and reduced IOP and IOP-lowering medication use at 12 months postoperatively.

Improvement of the visual field index in clinical glaucoma care - Cohen, SL; Rosen, AI; Tan, XM; Kingdom, FAA (CANADIAN JOURNAL OF OPHTHALMOLOGY-JOURNAL CANADIEN D OPHTALMOLOGIE, 2016)
Objective: This article investigates the prevalence and attributes of patients with open-angle glaucoma who exhibit improvement of visual field loss in a clinical setting. Design: We conducted a retrospective chart review of patients in a clinical glaucoma practice. Participants: We identified 719 glaucoma patients with at least 5 SITA strategy visual field tests and a minimum continuous follow-up period of 5 years. Methods: The change in the slope of the visual field index (VFI) over time was illustrated using histogram analysis for the study eye with the worst VFI at baseline. Multiple variables were analyzed to determine their impact on rates of visual field progression, including sex, age, disease staging, intraocular pressure (IOP), and incisional surgeries. Eyes with severe nonophthalmic and ophthalmic comorbidities were excluded. Results: Considering 582 eligible eyes, 232 (39.9%) showed significantly positive slopes of the VFI as a function of time, 76 (13.1%) showed nonsignificant slopes, and 276 (47.4%) showed significantly negative slopes. In all, 10 eyes (1.7%) demonstrated VFI slope improvement of >= 2% per year, whereas 21 (3.6%) demonstrated VFI slope reduction >= 2% per year. More advanced disease stage was significantly associated with a negative VFI slope (p < 0.0001). Trabeculectomy and poor compliance were not associated with a negative VFI slope, whereas cataract surgery correlated with higher odds of a negative VFI slope (p = 0.048). Conclusions: In a clinical setting, a significant VFI improvement over time was observed over an interval of greater than 5 years.

Hyperemia-Associated Costs of Medication Changes in Glaucoma Patients Treated Initially With Prostaglandin Analogs - Schwartz, GF; Tan, J; Kotak, S (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2009)
Aims: To develop a model to estimate and compare the cost of changing therapy due to hyperemia in glaucoma patients treated initially either with latanoprost, bimatoprost, or travoprost monotherapy. Methods: Data collected from the HealthCore Integrated Research Database, as part of the Glaucoma Adherence and Persistency Study (GAPS), were used to populate the model. Patients with a documented diagnosis of glaucoma who were newly treated (no ocular hypotensive medication and no glaucoma-related procedure during 6 months before first prescription) with latanoprost, bimatoprost, or travoprost monotherapy were identified. The time horizon for the base-case model was the duration of chart abstraction (mean = 4.1 years); a 3-month model also was developed. Physician-reported rates of hyperemia were obtained from chart reviews of 300 patients. Transition rates reflected events related to reports of hyperemia where a physician-driven change (switch or discontinuation) in therapy was documented. The per-patient direct cost (2008) due to hyperemia-driven change in therapy was calculated as the sum of the cost of the initial prescription plus the cost of the office visit where the patient was evaluated and the decision to change therapy was made. Costs were stratified by whether patients were hyperemia free or discontinued the initial therapy due to hyperemia. Results: From the sample of 13,977 newly treated patients, 8,743 patients were started on a prostaglandin monotherapy only. Of these, 5,726 received latanoprost, 1,633 were treated with bimatoprost, and 1,384 received travoprost index monotherapy. Across all treatment groups, costs among hyperemia-free patients were US$73.67 versus US$140.02 for those who discontinued the initial prostaglandin due to hyperemia. Per-patient costs were lowest in the group treated initially with latanoprost. For the base-case model, with latanoprost as the reference, total per-patient incremental costs due to hyperemia-driven change in therapy were US$5.92 for bimatoprost and US$5.43 for travoprost. Results were not highly sensitive to increases either in the incidence of hyperemia among latanoprost-treated patients or in the cost of latanoprost. Conclusions: Hyperemia results in increased overall costs in patients treated with latanoprost, bimatoprost, and travoprost. Treatment with latanoprost is associated with lower hyperemia-related costs than treatment with bimatoprost or travoprost.

Adherence to World Glaucoma Association Guidelines for Surgical Trials in the Era of Microinvasive Glaucoma Surgeries - Mathew, DJ; McKay, BR; Basilious, A; Belkin, A; Trope, GE; Buys, YM (OPHTHALMOLOGY GLAUCOMA, 2019)
Purpose: To determine how well microinvasive glaucoma surgical (MIGS) trials conform to the World Glaucoma Association (WGA) guidelines. Lack of well-designed MIGS studies hinders meaningful evaluation of these technologies. Design: Cross-sectional literature survey. Methods: Using a predefined search strategy, the following databases were searched for comparative trials involving MIGS in the English peer-reviewed literature from January 1, 2000, through June 21, 2018: Medline, EMBASE, BIOSIS, Cochrane, and Web of Science. From the WGA guidelines, 53 outcomes were selected for evaluation: methodology (n = 31), definition of success (n = 7), ethics (n = 10), postoperative complications (n = 1), economic evaluation (n = 1), and statistical reporting (n = 3). Each article was assessed by 2 reviewers; differences were resolved by consensus. Results: Twenty-five eligible publications were identified: 10 randomized controlled trials (RCTs) and 15 nonrandomized comparative trials (non-RCTs). The mean follow-up was 19.9 +/- 11.6 months (range, 6-48 months). The mean number of outcomes adhering to the WGA guidelines of the 53 evaluated was 24.2 +/- 6.1 (45.6% compliance): 28.0 +/- 6.2 (52.8%) and 21.6 +/- 4.7 (40.8%) for RCTs and non-RCTs, respectively (P = 0.01). Mean percent compliance for each subsection were: methodology, 48.8%; definition of success, 21.1 %; ethics, 55.6%; postoperative complications, 88%; economic evaluation, 0%; and statistical reporting, 37.3%. In 16 studies (64%), at least 1 author reported an association with the industry. Thirty-two percent of studies reported an author being a shareholder. Twenty-four percent of studies had an industry employee author. The primary intraocular pressure (IOP) end point was defined as both an upper limit and percentage reduction in only 4 studies (16%; 1 RCT, 3 non-RCTs). An IOP-based survival curve was provided in 7 studies (28%; none of the RCTs). Two studies (8%) included an IOP scatterplot. Twelve studies (48%) reported 95% confidence intervals. Only 4 studies (16%) used the mean of 3 diurnal IOP readings as the baseline IOP. Conclusions: Published comparative MIGS trials show low adherence (45.6%) to the WGA guidelines. Development of standardized methodology and outcomes could enhance interpretation and transparency of study results and facilitate comparisons between trials. Authors and journals should be encouraged to follow the WGA guidelines. (C) 2019 by the American Academy of Ophthalmology

A Systematic Review of End-of-Life Visual Impairment in Open-Angle Glaucoma: An Epidemiological Autopsy - Mokhles, P; Schouten, JSAG; Beckers, HJM; Azuara-Blanco, A; Tuulonen, A; Webers, CAB (JOURNAL OF GLAUCOMA, 2016)
Purpose: Glaucoma patients are still at risk of becoming blind. It is of clinical significance to determine the risk of blindness and its causes to prevent its occurrence. This systematic review estimates the number of treated glaucoma patients with end-of-life visual impairment (VI) and blindness and the factors that are associated with this. Methods: A systematic literature search in relevant databases was conducted in August 2014 on end-of-life VI. A total of 2574 articles were identified, of which 5 on end-of-life VI. Several data items were extracted from the reports and presented in tables. Results: All studies had a retrospective design. A considerable number of glaucoma patients were found to be blind at the end of their life; with up to 24% unilateral and 10% bilateral blindness. The following factors were associated with blindness: (1) baseline severity of visual field loss: advanced stage of glaucoma or substantial visual field loss at the initial visit; (2) factors influencing progression: fluctuation of intraocular pressure (IOP) during treatment, presence of pseudoexfoliation, poor patient compliance, higher IOP; (3) longer time period: longer duration of disease and older age at death because of a longer life expectancy; and (4) coexistence of other ocular pathology. Conclusions: Further prevention of blindness in glaucoma patients is needed. To reach this goal, it is important to address the risk factors for blindness identified in this review, especially those that can be modified, such as advanced disease at diagnosis, high and fluctuating IOP, and poor compliance.

Modeling a new dynamic approach to measure intraocular pressure with solitary waves - Nasrollahi, A; Rizzo, P (JOURNAL OF THE MECHANICAL BEHAVIOR OF BIOMEDICAL MATERIALS, 2020)
Glaucoma is an age-related disease and the second cause of blindness in the world. The measurement of intraocular pressure (IOP) is the cornerstone of glaucoma treatment because elevated IOP is the only risk factor that can be modified. Clinical evidences proved that single measurements obtained during office visits are neither sufficient to capture the circadian rhythm of IOP nor valid to demonstrate the effect of medication or patients' compliance to a given therapy. As such, patients would benefit from a device that they can self-administer to gage the IOP multiple times a day. In this paper, we present a numerical study on a new approach to measure IOP noninvasively using engineering principles never explored in ophthalmology. The method relies on the dynamical interaction between the solitary waves propagating within a chain of particles and the eye to be evaluated that is in contact with the end of the chain. In the study presented in this paper, a numerical model of such interaction was implemented to demonstrate the sensitivity of the proposed approach to the variation of IOP. The findings show that some features of the waves are monotonically dependent on the IOP. These findings may pave the way to the development of a new kind of tonometer that will enable millions of glaucoma patients to perform routine self-measurements of the eye pressure without clinical visits.

Indications and graft survival analysis in optical penetrating keratoplasty in a tertiary care center in North India: a 5-year study - Arya, SK; Raj, A; Bamotra, RK; Bhatti, A; Deswal, J; Sindhu, M (INTERNATIONAL OPHTHALMOLOGY, 2018)
To study the indications and variables correlating with graft survival in optical penetrating keratoplasty in a tertiary care hospital in north India. All patients who underwent optical keratoplasty, except those undergoing lamellar grafts, tectonic grafts transplants and penetrating keratoplasty done for therapeutic purposes were included in the study. Patients with follow-up less than 2 years were excluded from the study. Data were obtained by reviewing the records of 101 patients who underwent optical penetrating keratoplasty from 2008 to 2013 for various indications. Out of 101 patients who underwent optical penetrating keratoplasty, 71 were males and 30 were females. The mean age of the recipient was 48.53 years with range 1-82 years. The main indications were previous failed graft (29.7%), healed keratitis except HSV (15.8%), pseudophakic or aphakic bullous keratopathy (14.8%), corneal dystrophies/degenerations (12.9%), adherent leucoma (9.9%), post-HSV scars (8.9%), and others like anterior staphyloma, congenital corneal opacities, buphthalmos and keratoconus (7.9%). The graft survival rate was 67.33% at 1-year follow-up and 59.4% at 2-year follow-up. The mean survival time of the grafts was 22.42 months. The mean time for graft failure was 7.12 (+/- 0.9) months. One- and 2-year survival of grafts at our center is lower as compared to western studies, probably due to higher percentage of poor prognosis indications for surgery and a relative scarcity of excellent-quality donor corneas.

Quantification of blood-aqueous barrier breakdown after trabeculectomy: Pseudoexfoliation versus primary open-angle glaucoma - Nguyen, NX; Kuchle, M; Martus, P; Naumann, GOH (JOURNAL OF GLAUCOMA, 1999)
Purpose: Impairment of the blood-aqueous barrier in unoperated eyes with pseudoexfoliation syndrome has been demonstrated by fluorescein angiography, fluorophotometry, measurement of aqueous flare, and determination of aqueous protein. We performed noninvasive quantification of aqueous flare using the laser flare-cell meter to compare blood-aqueous barrier breakdown after trabeculectomy in eyes with primary open-angle glaucoma (POAG) and in eyes with pseudoexfoliative glaucoma (PEX). Methods: Twenty eyes with PEX and 20 eyes with POAG were included in the study. Trabeculectomy was performed by two surgeons according to a standard trabeculectomy technique. Intra- and postoperative treatments were identical in both groups. Aqueous flare was quantitatively determined using the laser flare-cell meter FC-1000 (Kowa, Tokyo, Japan) before and 3, 5, 7, and 9 days after trabeculectomy. Absolute flare and difference between post- and preoperative flare values were statistically analyzed using the Mann-Whitney U-Test for independent samples. Results: Before surgery, aqueous flare values were significantly higher in PEX than in POAG. On days 3, 5, 7 and 9 after surgery, flare values were significantly higher in eyes with PEX than in eyes with POAG. Absolute differences between post- and preoperative flare values also were significantly higher in eyes with PEX, but this was not true for percentage values. Conclusion: These results show that substantial blood-aqueous barrier breakdown occurs in eyes with PEX after trabeculectomy. These alterations may contribute to early or late complications of trabeculectomy and indicate the need for close postoperative follow-up evaluation in eyes with PEX.

Does the Use of Preoperative Antiglaucoma Medications Influence Trabeculectomy Success? - Ozturker, ZK; Ozturker, C; Bayraktar, S; Altan, C; Yilmaz, OF (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2014)
Purpose: To investigate the influence of preoperative antiglaucoma medications on trabeculectomy outcome. Methods: Two hundred fifteen eyes, which underwent primary trabeculectomy, were retrospectively analyzed. The average follow-up was 39.8 +/- 30.3 months. The only cases of primary open-angle glaucoma, with or without pseudoexfoliation (PXF), were included. "Complete success'' was defined as intraocular pressure (IOP) < 18mmHg without glaucoma medications, whereas relative success was defined as the same IOP target with medications. The influence of the preoperatively used glaucoma medications on surgical success was analyzed by univariate Pearson correlation and multivariate (ordinal) regression analysis. Results: There were 118 male (54.9%) and 97 female (45.1%) patients with a mean age of 66.9 +/- 9.3 years. PXF glaucoma (PXFG) was present in 93 eyes (43.3%). In 33 patients (15.3%), diabetes mellitus (DM) was present. Complete success was achieved in 116 eyes (54%), relative success in 81 eyes (37.6%), and failure in 18 eyes (8.4%). Neither the total number nor the duration of glaucoma medications used before trabeculectomy was found to have any statistically significant influence on surgical success. In statistical analysis, a combination of topical beta-blocker and carbonic anhydrase inhibitor (BB+CAI) used before surgery was found to be associated with statistically better outcome, whereas the preoperative use of topical beta-blockers alone could have a negative influence on success. PXF was shown to be independently associated with trabeculectomy outcome on multivariate regression analysis. Conclusion: The glaucoma medications used preoperatively were not found to have any statistically significant negative influence on the trabeculectomy outcome and use of the combined BB+CAI preparation could have a positive influence, whereas the use of topical beta-blockers alone could have a negative influence on success, although not statistically significant. The presence of PXF was independently associated with a better surgical outcome.

Keratoplasty in children Indications and results - Lang, SJ; Bohringer, D; Reinhard, T (OPHTHALMOLOGE, 2020)
Penetrating keratoplasty in children is associated with very specific difficulties for the surgeon as well as for the patient and the parents. Special features are specific pediatric indications, which do not occur in adults, a more difficult examination and treatment adherence depending on the parents. Diseases with a favorable prognosis include keratoconus and herpetic keratitis. Especially sclerocornea and the Peters' anomaly often have a limited prognosis regarding vision and graft survival due to secondary malformations of the eye. In addition, younger age represents a risk factor. This is most likely due to the impaired examination during follow-up and reduced compliance. For successful penetrating keratoplasty in children the timing for the operation, in which the risk for the graft is weighed up against the risk for amblyopia, is crucial.

Persistence of Glaucoma Therapy and Visual Field Progression - de Leon, JMS; Quek, DT; Htoon, HM; Perera, SA; Lamoureux, EL; Aung, T (JOURNAL OF GLAUCOMA, 2016)
Purpose: To determine the association of visual field (VF) progression with medication persistence in a cohort on glaucoma therapy. Patients and Methods: Pharmacy records were examined over 3 years for patients started on glaucoma monotherapy. A patient was persistent if a prescription was refilled for the same medication < 90 days after the previous prescription had lapsed; otherwise was nonpersistent. Only patients with > 5 reliable VFs within 1-year pretherapy and 6-year posttherapy were included. Progression was analyzed with pointwise linear regression and defined using 2 criteria: (A) >= 2 adjacent progressing points (slope P < 0.01) in 1 hemifield; and (B) >= 3 progressing points (slope P < 0.01). The mean number and mean slope of progressing points and the mean global slopes were determined. Results: Of 1206 patient eyes (131 persistent, 1075 nonpersistent), 941 were excluded leaving 175 (47 persistent and 128 nonpersistent) for analysis. The mean follow-up durations were 59.3 +/- 10.9 and 58.2 +/- 9.7 months (P = 0.07) for persistent and nonpersistent eyes, respectively. Overall, 2/47 (4.3%) and 10/128 (7.8%) eyes progressed among persistent and nonpersistent patients, respectively (P = 0.52) using criterion A and 1/47 (2.1%) and 12/128 (9.4%; P = 0.19) eyes using criterion B. Mean number of progressing points (0.3 +/- 0.9 vs. 0.7 +/- 1.8; P = 0.17), mean slope of progressing points (-2.2 +/- 1.1 vs. -2.8 +/- 1.3 dB/y; P = 0.27), and mean global slope (0.7 +/- 0.5 vs. -0.1 +/- 0.8 dB/y; P = 0.07) were similar for persistent and nonpersistent patients, respectively. Conclusion: There were small but appreciable differences in VF progression rates between persistent and nonpersistent patient eyes on glaucoma drops, but differences were not significant.

Implementation of a vision-screening program in rural northeastern United States - Tsui, E; Siedlecki, AN; Deng, J; Pollard, MC; Cha, S; Pepin, SM; Salcone, EM (CLINICAL OPHTHALMOLOGY, 2015)
Background: Rural populations comprise almost 20% of the US population and face unique barriers in receiving health care. We describe the implementation of a medical student-run free vision-screening clinic as a strategy to overcome barriers in accessing eye care in New Hampshire and Vermont. Methods: Medical students were trained by an ophthalmologist to administer screening eye examinations. Patients from New Hampshire and Vermont were enrolled through a free community clinic. Screening included a questionnaire, distance and near visual acuity, extraocular movements, confrontational visual fields, and Amsler grid. Patients who met predetermined screening criteria were referred to an ophthalmologist or optometrist for further evaluation. Data including patient demographics, appointment attendance, level of education, and diagnoses were recorded and analyzed. Results: Of 103 patients (mean age of 45.5 +/- 12.3 years, 63% female), 74/103 (72%) were referred for further evaluation, and 66/74 (89%) attended their referral appointments. Abnormal ophthalmologic examination findings were observed in 58/66 (88%) patients who attended their referral appointment. Uncorrected refractive error was the most common primary diagnosis in 38% of referred patients. Other diagnoses included glaucoma suspect (21%), retinal diseases (8%), amblyopia (8%), cataract (6%), others (6%), and normal examination (12%). Of the 8/74 (11%) referred patients who did not attend their appointments, reasons included patient cancellation of appointment, work conflicts, or forgetfulness. Patients traveled a mean distance of 16.6 miles (range: 0-50 miles) to attend screening examinations. Mean time for patients' last effort to seek eye care was 7.1 years (range: 1-54 years). Conclusion: This study underscores the high prevalence of unmet eye care needs in a rural population. Furthermore, it demonstrates that using community health centers as a patient base for screening can yield a high referral attendance rate for this at-risk population and facilitate entrance into the eye care system in a rural setting.

VISUAL REHABILITATION ACHIEVED BY RECONSTRUCTIVE SURGERY OF THE ANTERIOR SEGMENT OF THE EYE - BIALASIEWICZ, AA; FORSTER, W; BUSSE, H (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 1993)
Background The potential benefits of anterior segment surgery to achieve visual rehabilitation in severely compromised eyes subsequent to infectious complications in the anterior segment remain a subject of controversy. Patients and Methods Anterior segment reconstructive surgery was performed on twelve patients (12 eyes) with infectious adherent leukoma and extensively damaged intraocular structures. Nine patients (nine eyes) were followed up over a period of two years (20-26 months) and three over a period of nine months (8-11 months). Results Simultaneous and consecutive surgical interventions including corneal grafting, anterior chamber reconstruction and posterior chamber lens implantation combined with antimicrobial and antiviral prophylaxis as well as corticosteroid treatment resulted in visual recovery in nine eyes, and in four in a visual acuity of 0.4 or better (reading VA). Conclusions Surgery for optic reasons due to infectious adherent leukoma does not seem to be completely unsuccessful with respect to the low complication rate despite proven retrocorneal membranes in this study.

Cataract surgery with trabecular micro-bypass stent implantation in patients with mild-to-moderate open-angle glaucoma and cataract: Two-year follow-up - Craven, ER; Katz, LJ; Wells, JM; Giamporcaro, JE; iStent Study Grp (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2012)
PURPOSE: To assess the long-term safety and efficacy of a single trabecular micro-bypass stent with concomitant cataract surgery versus cataract surgery alone for mild to moderate open-angle glaucoma. SETTING: Twenty-nine investigational sites, United States. DESIGN: Prospective randomized controlled multicenter clinical trial. METHODS: Eyes with mild to moderate glaucoma with an unmedicated intraocular pressure (IOP) of 22 mm Hg or higher and 36 mm Hg or lower were randomly assigned to have cataract surgery with iStent trabecular micro-bypass stent implantation (stent group) or cataract surgery alone (control group). Patients were followed for 24 months postoperatively. RESULTS: The incidence of adverse events was low in both groups through 24 months of follow-up. At 24 months, the proportion of patients with an 10P of 21 mm Hg or lower without ocular hypotensive medications was significantly higher in the stent group than in the control group (P=.036). Overall, the mean 10P was stable between 12 months and 24 months (17.0 mm Hg +/- 2.8 [SD] and 17.1 +/- 2.9 mm Hg, respectively) in the stent group but increased (17.0 +/- 3.1 mm Hg to 17.8 +/- 3.3 mm Hg, respectively) in the control group. Ocular hypotensive medication was statistically significantly lower in the stent group at 12 months; it was also lower at 24 months, although the difference was no longer statistically significant. CONCLUSIONS: Patients with combined single trabecular micro-bypass stent and cataract surgery had significantly better 10P control on no medication through 24 months than patients having cataract surgery alone. Both groups had a similar favorable long-term safety profile. Financial Disclosure: Dr. Craven was an investigator in the clinical trial of the iStent. Dr. Katz is a consultant to Glaukos and was the medical monitor for the clinical trial of the iStent. Dr. Katz is a stockholder in Glaukos. Mr. Wells and Ms. Giamporcaro are employees of Glaukos. J Cataract Refract Surg 2012; 38:1339-1345 (C) 2012 ASCRS and ESCRS

Three-year outcomes of combined trabecular micro-bypass and phacoemulsification in a predominantly Hispanic population with primary open-angle glaucoma - Gallardo, MJ; Supnet, RA (CLINICAL OPHTHALMOLOGY, 2019)
Purpose: To present long-term, real-world outcomes after implanting one trabecular micro-bypass stent with cataract surgery for primary open-angle glaucoma (POAG) in a predominantly Hispanic patient population. Patients and methods: This retrospective, consecutive case series evaluated intraocular pressure (RR), medications, and safety through 36 months after implanting one iStent (R) during phacoemulsification cataract surgery. Eyes were stratified into 2 subgroups classified by preoperative IOP and surgical goal. The Controlled Group had IOP <18 mmHg on >= 1 medications, and goal to reduce medications. The Uncontrolled Group had IOP >= 18 mmHg and/or maximum tolerated medication load, and goal to reduce IOP. Assessments included IOP, medications, visual fields (VF), retinal nerve fiber layer thickness (RNFL), adverse events, and secondary surgeries. Results: Of 168 total operated eyes, 87 eyes (49 Controlled, 38 Uncontrolled) completed 36 months of follow-up and comprise the Consistent Cohort in this report. At baseline, 79.6% (39/49) of Controlled eyes and 71.1% (27/38) of Uncontrolled eyes were from Hispanic patients. In the Controlled Group desiring medication reduction, mean medications were reduced by 77.3% (2.6 medications preoperatively vs 0.6 at 36 months; p<0.001. All Controlled eyes maintained or reduced medications versus preoperative; no eyes were on >= 3 medications (vs 61.2% preoperatively); and 58.3% were medication-free (vs 0% preoperatively). In the Uncontrolled Group desiring IOP reduction, mean IOP decreased by 31.2% (19.4 mmHg preoperatively vs 13.4 mmHg at 36 months; p<0.001), 91.7% of eyes achieved IOP <= 18 mmHg, 69.4% reached IOP <= 15 mmHg, and 77.8% decreased IOP >= 20% vs baseline. Uncontrolled eyes also experienced a 45.3% medication reduction (2.2 medications preoperatively vs 1.2 at 36 months; p<0.001). Favorable safety included no intraoperative complications, and stable VF and RNFL through 36 months. Conclusion: In this predominantly Hispanic patient cohort, significant IOP and medication reductions were sustained safely through 36 months after iStent implantation during cataract surgery.

Comparing the effectiveness of selective laser trabeculoplasty with topical medication as initial treatment (the Glaucoma Initial Treatment Study): study protocol for a randomised controlled trial - Lamoureux, EL; Mcintosh, R; Constantinou, M; Fenwick, EK; Xie, J; Casson, R; Finkelstein, E; Goldberg, I; Healey, P; Thomas, R; Ang, GS; Pesudovs, K; et al. (TRIALS, 2015)
Background: Glaucoma is the leading cause of irreversible blindness in the world. Estimated to affect 60 million people worldwide, this figure is expected to rise to 80 million by 2020. Untreated, glaucoma leads to visual decay and eventually to blindness, and can significantly reduce quality of life. First-line treatment in patients with primary open-angle glaucoma and exfoliative glaucoma is topical medical therapy with ocular hypotensives as eye drops. However, eye drops have several disadvantages including cost, possible local and systemic side effects, and adherence and perseverance issues. Randomised controlled trials have demonstrated that selective laser trabeculoplasty is equally as effective in lowering intraocular pressure as eye drops. However, the impact of these two treatment modalities from the patient and economic perspectives has not been adequately determined. Thus, it remains unclear whether topical medical therapy or selective laser trabeculoplasty should be recommended as first-line treatment for glaucoma. Methods/Design: This protocol describes an international, multi-centre, randomised controlled trial to determine the optimum first-line therapy for people with primary open-angle glaucoma and exfoliative glaucoma. This study will compare the effect of selective laser trabeculoplasty and topical medication with respect to patients' generic and glaucoma-specific quality of life. The trial will also provide a detailed cost-effectiveness analysis and compare the clinical effectiveness with respect to the degree of intraocular pressure lowering and rates of treatment failure. Research coordinators in each centre will identify and recruit previously untreated patients with primary open-angle glaucoma and exfoliative glaucoma. Those who meet the eligibility criteria will be invited to enter a randomised controlled trial with either selective laser trabeculoplasty or topical ocular hypotensive therapy, according to a stepped regimen. Outcome assessment will be measured at 6 weeks and at 6, 12, and 24 months post-treatment. Regular clinic follow-ups will continue as clinically indicated between study outcome visits. Discussion: The Glaucoma Initial Treatment Study is the first multi-centred RCT to determine the optimum first-line therapy for people with glaucoma. Our trial will have an unprecedented capacity to meaningfully transform the treatment and management of glaucoma in Australia and overseas.

Efficacy of two trabecular micro-bypass stents combined with topical travoprost in open-angle glaucoma not controlled on two preoperative medications: 3-year follow-up - Chang, DF; Donnenfeld, ED; Katz, LJ; Voskanyan, L; Ahmed, IIK; Samuelson, TW; Giamporcaro, JE; Hornbeak, DM; Solomon, KD (CLINICAL OPHTHALMOLOGY, 2017)
Purpose: To evaluate the long-term intraocular pressure (IOP)-lowering effect and safety parameters following treatment with two trabecular micro-bypass stents and topical prostaglandin in phakic eyes with open-angle glaucoma (OAG) not controlled on two preoperative medications. Methods: This prospective, single-arm, unmasked study enrolled 39 qualified phakic eyes with OAG not controlled on 2 medications, preoperative medicated IOP of 18-30 mmHg, and IOP following medication washout of 22-38 mmHg. Two trabecular micro-bypass stents were implanted as a standalone procedure, and travoprost was started on postoperative day 1. Evaluations included IOP, best-corrected visual acuity, medication use, fundus and slit-lamp examinations, visual field, cup: disc ratio, central corneal thickness, and ocular complications. Data through 18 months were summarized previously. Thirty-seven of the original 39 subjects have been followed for 3 years postoperatively; follow-up is continuing for 5 years. Results: At 3 years postoperative, 97% of eyes had achieved an IOP reduction of >= 20% from baseline with a reduction of 1 medication. Eighty-six percent of eyes had IOP of <= 18 mmHg with a reduction of 1 medication. Mean medicated IOP decreased to 14.0 +/- 2.6 mmHg on 1 medication versus 22.4 +/- 2.3 mmHg on 2 medications preoperatively. The mean unmedicated IOP decreased to 17.7 +/- 1.7 mmHg at 37 months from 25.3 +/- 1.9 mmHg preoperatively. Longterm postoperative adverse events included cataract surgery in 3 eyes due to cataract progression, and trabeculectomy in 1 eye due to uncontrolled IOP of 23 mmHg. No intraoperative or device-related adverse events occurred. Conclusion: Significant and sustained reduction in IOP and medications with a favorable safety profile was shown through 3 years after implantation of 2 trabecular micro-bypass stents combined with postoperative travoprost in phakic OAG eyes uncontrolled on 2 preoperative medications. These findings demonstrate the long-term performance and safety of trabecular bypass stents in combination with topical prostaglandin for OAG patients.

Three-Year Findings of the HORIZON Trial A Schlemm Canal Microstent for Pressure Reduction in Primary Open-Angle Glaucoma and Cataract - Ahmed, IIK; Rhee, DJ; Jones, J; Singh, IP; Radcliffe, N; Gazzard, G; Samuelson, TW; Ong, J; Singh, K; HORIZON Investigators (OPHTHALMOLOGY, 2021)
Purpose: To report 3-year outcomes of the HORIZON study comparing cataract surgery (CS) with Hydrus Microstent (Ivantis, Inc) implantation versus CS alone. Design: Multicenter randomized clinical trial. Participants: Five hundred fifty-six eyes from 556 patients with cataract and primary open-angle glaucoma (POAG) treated with 1 or more glaucoma medication, washed out diurnal intraocular pressure (IOP) of 22 to 34 mmHg, and no prior incisional glaucoma surgery. Methods: After phacoemulsification, eyes were randomized 2:1 to receive a Hydrus Microstent or no stent. Follow-up included comprehensive eye examinations through 3 years. Main Outcome Measures: Outcome measures included IOP, medical therapy, reoperation rates, visual acuity, adverse events, and changes in corneal endothelial cell counts. Results: Three hundred sixty-nine eyes were randomized to microstent treatment and 187 to CS only. Preoperative IOP, medication use, washed-out diurnal IOP, and glaucoma severity did not differ between the two treatment groups. At 3 years, IOP was 16.7 +/- 3.1 mmHg in the microstent group and 17.0 +/- .4 mmHg in the CS group (P = 0.85). The number of glaucoma medications was 0.4 +/- 0.8 in the microstent group and 0.8 +/- 1.0 in the CS group (P < 0.001), and 73% of microstent group eyes were medication free compared with 48% in the CS group (P < 0.001). The microstent group included a higher proportion of eyes with IOP of 18 mmHg or less without medications compared with the CS group (56.2% vs. 34.6%; P < 0.001), as well as IOP reduction of at least 20%, 30%, or 40% compared with CS alone. The cumulative probability of incisional glaucoma surgery was lower in the microstent group (0.6% vs. 3.9%; hazard ratio, 0.156; 95% confidence interval, 0.031-0.773; P = 0.020). No difference was found in postoperative corneal endothelial cell loss between groups. No procedureor device-related serious adverse events resulting in vision loss occurred in either group. Conclusions: Combined CS and microstent placement for mild to moderate POAG is safe, more effective in lowering IOP with fewer medications, and less likely to result in further incisional glaucoma filtration surgery than CS alone at 3 years. (C) 2020 by the American Academy of Ophthalmology

Fluocinolone acetonide (0.19 mg) intravitreal implant reduces treatment burden and improves practice resource utilisation for patients with diabetic macular oedema - Byun, M; Osher, J; Riemann, CD (BMJ OPEN OPHTHALMOLOGY, 2020)
Objective Patients with diabetic macular oedema (DME) are known to have significantly greater medical treatment burden than patients with non-DME. Frequent injections and office visits can have a substantial impact on patient adherence and quality of life. This analysis assesses the impact of the 0.19 mg fluocinolone acetonide (FAc) implant (or injection) on treatment burden and practice resource utilisation in patients with DME. Methods and analysis This study is a single-centre retrospective chart review of 30 eyes (23 patients) that received a single FAc implant. Data was collected for a 12-month period pre-injection and post-injection of the FAc implant. Primary outcomes included the frequency of injections and ophthalmology office visits. Secondary outcomes included visual acuity (VA), intraocular pressure (IOP) and central subfield thickness (CSFT). Results The injection frequency significantly decreased from one injection every 2.6 months pre-injection to one injection every 8.8 months post-injection of the FAc implant (p<0.001). Sixty-three percent of the subjects did not require additional injections post-FAc implant. The mean number of ophthalmology office visits significantly decreased from 12.7 visits pre-FAc to 9.3 visits post-FAc implant (p<0.001). The mean VA (p=0.24) and CSFT (p=0.39) showed a mild numerical improvement that was not statistically significant. Thirty-seven percent of the eyes required additional IOP lowering drops. No eyes required incisional glaucoma surgeries. Conclusions The FAc implant significantly decreased the treatment burden and improved practice resource utilisation while maintaining or improving VA and CSFT. IOP events were mostly well-controlled with drops and no eyes required incisional glaucoma surgery.

The differences between patient and optometrist experiences of contact lens hygiene education from the perspective of a Scottish university teaching hospital - Hind, J; Williams, O; Oladiwura, D; Macdonald, E (CONTACT LENS & ANTERIOR EYE, 2020)
Background: Contact lens related keratitis is a frequent presentation to acute ophthalmology services. Patients often do not recall being counselled regarding the safe use of contact lenses therefore fail to comply with guidance. This study aimed to identify the content and format of advice given to patients with contact lens keratitis concerning appropriate hygiene practices, determine their compliance with this and finally characterise optometrist practices regarding contact lens advice provided to patients. Methods: All adult patients presenting with contact lens related keratitis to the acute ophthalmology clinic were asked to complete a survey. Information was collected on lens type, format of advice received and compliance. Community optometrists were asked to complete an electronic survey on their contact lens review practices and routine patient education. Results: All patients surveyed recalled counselling on initiation of contact lenses; however 12% (6/50) were given no advice on return visits. This advice was in written format for 20% (10/50) of patients on initiation increasing to 32% (16/50) on renewal. Many patients slept (22%), showered (44%) or swam (36%) in lenses. 92% cleaned their contact lenses appropriately, but cases were washed infrequently (19% of cases cleaned < monthly) or with tap water (27%). All optometrists surveyed claimed to provide advice to patients in either written or verbal format for new and returning contact lens users. 49% (16/33) of optometrists gave written advice to patients on initial contact lens fitting, but only 1/33 continued with written advice for repeat customers. Conclusion: This study identified that although most patients were informed of appropriate hygiene requirements, compliance was poor. Optometrists regularly provide verbal advice but do not routinely offer written support and there is a mismatch between patient recollection and self-reported optometrist practice. It is suggested that patient education needs greater emphasis and both verbal and written information should be regularly provided on initial review and follow up assessments.

The efficacy and safety of once-daily versus once-weekly latanoprost treatment for increased Intraocular pressure - Kurtz, S; Shemesh, G (JOURNAL OF OCULAR PHARMACOLOGY AND THERAPEUTICS, 2004)
We evaluated the efficacy and safety of latanoprost eye drops once-weekly, compared to once-daily for improving patient compliance. Twenty (20) patients (11 women and 9 men), 12 with ocular hypertension and 8 with early glaucoma, were studied after washout of the antiglaucoma treatment. One (1) group was treated with latanoprost once-daily (control). The other group was treated once-weekly (study group). Intraocular pressure (IOP) was measured at baseline and on the 2nd, 4th, 6th, and 9th day after the last drop in the study group, and for 3 months on the same schedule thereafter. The mean baseline IOP was 24.3 +/- 3.9 mmHg in the study group (range, 18-29) and 24.4 +/- 4.4 mmHg in the control group (range, 17-32). The average IOP at all time points of post-treatment was 17.7 +/- 1.5 mmHg (range, 14-23) and 16.9 +/- 2.30 mmHg (range, 13-21), respectively. Latanoprost significantly lowered IOP in both groups (study group, p = 0.005; controls, p = 0.0019). The difference between post-treatment IOP was insignificant in both groups at each time point. The study group had fewer minor side effects than the control group (1/10 versus 6/10, respectively). Latanoprost treatment once-weekly was as effective, and bore fewer minor side effects, as once-daily treatment after 3 months of follow-up.

Willingness to use follow-up eye care services after vision screening in rural areas surrounding Chennai, India - Su, Z; Wang, BQ; Staple-Clark, JB; Buys, YM; Forster, SH (BRITISH JOURNAL OF OPHTHALMOLOGY, 2014)
Aims To assess the willingness to utilise follow-up eye care services among participants of community vision screenings in rural villages surrounding Chennai. Methods Vision screening participants aged >= 40 years were selected by systematic sampling and were invited to respond to a pretested verbal survey with close-ended questions before undergoing screening. Results Two hundred and ninety-two people responded. Among the respondents, 50.3% reported experiencing an eye problem, and 53% of these individuals had never had an eye examination. Acceptance rate for eye surgery, medications, and eyeglasses among the respondents was 59.2%, 52.7% and 90.8%, respectively. These acceptances were not associated with sex, age, or employment; medication acceptance was inversely associated with literacy. Surgery acceptance and medication acceptance were associated with area of residence. Presence of another chronic disease was a predictor for surgery acceptance among respondents experiencing eye problems. Conclusions Maintaining consistent quality of services delivered is crucial for increasing uptake of existing eye care services. Educational interventions may increase eye care service usage by targeting all demographic subgroups of rural populations equally. Additional interventions should be offered to patients without previous exposure to the healthcare system.

Assessment of retinal nerve fiber layer using optical coherence tomography and scanning laser polarimetry in progressive glaucomatous optic neuropathy - Sehi, M; Greenfield, DS (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2006)
PURPOSE: To describe a case of progressive glaucomatous optic neuropathy using scanning laser polarimetry with fixed (SLP-FCC) and variable corneal compensation (SLP-VCC) and optical coherence tomography (OCT). DESIGN: Observational case report. METHODS: A 21 year-old male with juvenile primary open,angle glaucoma developed progression because of noncompliance with therapy. The patient underwent dilated stereoscopic examination and photography of the optic disk, standard automated perimetry (SAP), OCT, and SLP imaging with FCC and VCC at the baseline examination and after four years of follow-up. RESULTS: Optic disk, retinal nerve fiber layer (RNFL) atrophy, and SAP progression was observed. Reduction in mean RNFL thickness (average, superior, inferior) was 18, 18, and 27 microns (OCT); 22, 40, and 17 microns (SLP-FCC); and 6, 12, and 12 microns (SLP-VCC), respectively. CONCLUSIONS: This case demonstrates that digital imaging of the peripapillary RNFL is capable of documentation and measurement of progressive glaucomatous RNFL atrophy.

Statins and the risk of lung, breast, and colorectal cancer in the elderly - Setoguchi, S; Glynn, RJ; Avorn, J; Mogun, H; Schneeweiss, S (CIRCULATION, 2007)
Background - Although most randomized trials and meta-analyses suggest a slight or no increase in the risk of cancer in statin users, results from observational studies have been conflicting, and some have even suggested a large protective effect of statins on certain cancers. Long-term statin users tend to be healthier, less frail, and more adherent to therapy than nonusers, however. This could explain such apparent "protective" effects. Methods and Results - We conducted the present cohort study by linking data from a large state drug benefit program with cancer registry data and Medicare healthcare utilization data. We identified all initiators of statins; initiators of glaucoma medications, another preventive drug, served as a comparison group. Outcomes included all registry-identified cases of colorectal, lung, and breast cancer. Multivariable Cox proportional models were used to adjust for confounding. Patient characteristics were similar in both groups, but statin initiators (n = 24 439) were slightly younger and used some services more frequently than glaucoma drug initiators (n = 7284). The mean follow-up was 2.9 years, with the longest follow- up being 8.4 years. Incidence rates of colorectal, lung, and breast cancers in both groups were very similar to rates in the general population. Adjusted hazard ratios were 0.96 (95% CI, 0.70 to 1.31) for colorectal cancer, 1.11 (95% CI, 0.77 to 1.60) for lung cancer, and 0.99 (95% CI, 0.74 to 1.33) for breast cancer. Conclusions - These data from a large population of typical older patients who began using statins indicate that it is unlikely that statins confer a clinically important decrease or increase in the risk of colorectal, lung, or breast cancer over the durations studied.

One-Year Outcomes of Second-Generation Trabecular Micro-Bypass Stents (iStent Inject) Implantation with Cataract Surgery in Different Glaucoma Subtypes and Severities - Salimi, A; Lapointe, J; Harasymowycz, P (OPHTHALMOLOGY AND THERAPY, 2019)
Purpose To assess the 1-year efficacy and safety of the implantation of two second-generation trabecular micro-bypass stents (iStent Inject) with concomitant cataract surgery in various subtypes and severities of glaucoma. Methods This single-surgeon, consecutive case series from a Canadian academic ophthalmology center included subjects with cataract, glaucoma, and the need to reduce intraocular pressure (IOP) and/or medications. The 12-month outcomes included mean IOP and medication burden as well as the proportions of eyes with IOP <= 18, <= 15, and <= 12 mmHg compared to baseline. Other measures included corrected distance visual acuity (CDVA), cup-to-disc ratio (CDR), visual field mean deviation (VF MD), retinal nerve fiber layer (RNFL) thickness, ganglion cell inner plexiform layer (GCIPL) thickness, and adverse events. Results In 118 eyes, mean IOP reduced from 17.00 +/- 3.82 mmHg preoperatively to 13.97 +/- 2.65 mmHg at the 12-month follow-up mark (17.8% reduction, p < 0.001), and mean medication burden decreased from 2.31 +/- 1.33 preoperatively to 1.03 +/- 1.10 medications (56% reduction, p < 0.001). After 12 months, 93% of eyes achieved IOP <= 18 mmHg (versus 69% preoperatively), 70% of eyes achieved IOP <= 15 mmHg (versus 42% preoperatively), and 29% of eyes achieved IOP <= 12 mmHg (versus 7% preoperatively). For all eyes, topical medications were either maintained or decreased from baseline, with >= 1 medication eliminated from the preoperative regimen for 83% of eyes and >= 2 medications eliminated for 36% of eyes. Visual acuity improved significantly, consistent with expectations for cataract surgery, while CDR, VF MD, and RNFL and GCIPL thicknesses remained stable. Safety was favorable, with no intraoperative complications and few transient adverse events postoperatively. Conclusion iStent Inject implantation with cataract surgery safely reduced IOP and medication burden in a real-world clinical population with mild to severe glaucoma, and stabilized visual field, as well as RNFL and GCIPL thicknesses on OCT. Funding The Rapid Service Fees were funded by Glaukos Corporation.

Persistence on prostaglandin ocular hypotensive therapy: an assessment using medication possession and days covered on therapy - Reardon, G; Schwartz, GF; Kotak, S (BMC OPHTHALMOLOGY, 2010)
Background: Prior research has demonstrated that medication persistence (continued acquisition of therapy over time) is far from optimal among patients with glaucoma. The purpose of the present study was to evaluate persistence with prostaglandin analogs among glaucoma patients in the first therapy year using a modification of a previously published technique. Methods: This retrospective analysis of medical and pharmacy claims database included treatment-naive patients dispensed bimatoprost, latanoprost, or travoprost between 1/1/04-12/31/04. "Index agent" was defined as the first agent filled; "index date" was defined as the fill date. Follow-up continued for 358 days. Persistence measures for first therapy year were: (1) whether last fill had sufficient days supply to achieve medication possession at year's end, and (2) number of days for which the index agent was available (days covered). Associations between index agent and medication possession (logistic regression) and days covered (linear regression) were evaluated. Models were adjusted for gender, age, and previous ocular hypertension diagnosis. Results: 7873 patients met inclusion criteria (bimatoprost, n = 1464; latanoprost, n = 4994; travoprost, n = 1415). Medication possession was 28% and days covered was 131 when using the unadjusted (pharmacy-reported) days supply estimates and rose to 47-48% and days covered to 228-236 days when days supply was imputed. Compared to latanoprost, odds of achieving medication possession at first year's end were 26-34% lower for bimatoprost and 34-36% lower for travoprost (p <= 0.001 for all comparisons). Days covered in the first year were 21-29 days lower for bimatoprost and 33-42 days lower for travoprost (p <= 0.001 for all comparisons). Failure to refill the index agent within the initial 90 days was a strong predictor of poor persistence. Conclusions: Persistence with ocular prostaglandin therapy remains a problem. Latanoprost users had greater odds of achieving medication possession and had more days covered during the first therapy year.

Management of Corneal Bee Sting Injuries - Rai, RR; Gonzalez-Gonzalez, LA; Papakostas, TD; Siracuse-Lee, D; Dunphy, R; Fanciullo, L; Cakiner-Egilmez, T; Daly, MK (SEMINARS IN OPHTHALMOLOGY, 2017)
Purpose: To review the management of keratitis after corneal bee stings and to report a case of deep stromal corneal infiltrate secondary to a retained bee stinger managed conservatively in a patient who presented three days after unsanitary manipulation of the stinger apparatus. Methods: Case report and review of literature. Results: A 57-year-old male beekeeper was evaluated for pain, blurry vision, and photosensitivity after a corneal bee sting. Of note, the venom sac had been removed with dirty tweezers three days prior to his visit. On exam, a focal infiltrate with diffuse edema was seen surrounding a retained bee stinger in the peripheral cornea. Trace cells in the anterior chamber were also noted. Based on a high suspicion for infectious keratitis, a conservative treatment strategy was elected. Administration of broad-spectrum topical antibiotics with concomitant abstention of corticosteroids led to rapid resolution of the symptoms. Over 16 months of follow-up, the stinger has remained in situ without migration and the patient has maintained 20/20 visual acuity without complications. There is debate on the preferred method for the management of corneal injury secondary to bee stings, especially when it is associated with a retained stinger. We herein present our findings in our appraisal of reported cases. Conclusion: In the aftermath of an ocular bee sting, close surveillance for inflammation and infection is essential. Individual manifestations of these injuries vary in timing, type, and severity; therefore, the accessibility of the stinger and the evolving clinical picture should guide therapeutic decisions.

The Effect of Compliance on Contact Lens Case Contamination - Tilia, D; de la Jara, PL; Zhu, H; Naduvilath, TJ; Holden, BA (OPTOMETRY AND VISION SCIENCE, 2014)
Purpose To determine the efficacy of written instructions on contact lens case hygiene and to quantify the effect of noncompliance on contact lens case contamination. Methods Data were retrospectively analyzed from 16 prospective, 3-month daily-wear studies during which six commercially available silicone hydrogel contact lenses and seven lens care solutions (LCS) were tested following a similar protocol. Verbal instructions regarding case hygiene (rinse case with LCS, not tap water) were given in nine studies, while the same instructions were given verbally and in written format in seven studies. A survey on contact lens, LCS, and lens case hygiene was completed at 1- and 3-month visits and compliance with case hygiene instructions was determined. Regular contact lens cases were used for 1 month and collected for microbial analysis at the 1- and 3-month visits. The rate of case contamination and the types of microbes contaminating cases were evaluated. Results Participants given verbal and written instructions were more likely to be compliant with case hygiene instructions than those just given verbal instructions (odds ratio [OR]: 2.19, p < 0.001, 95% confidence interval [CI]: 1.40-3.44). The overall case contamination rate was 79%. Use of tap water to rinse contact lens cases was associated with significantly more cases contaminated with Gram-negative bacteria (GNB) (30% vs. 10%, p < 0.001), a greater risk of GNB case contamination (OR: 2.91, p < 0.001. 95% CI: 1.72-4.92), and a higher quantity of GNB in cases (mean colony-forming unit/case SD: 28,286 +/- 131,935 vs. 6477 +/- 60,447, p < 0.001). Conclusions Lens case hygiene can be improved by effective communication of instructions. Contact lens wearers should be actively discouraged from rinsing contact lens cases with tap water because of the increased risk of GNB contamination.

INTOLERANCE OF PRESERVATIVE-CONTAINING EYE DROPS IN A GLAUCOMA PATIENT: DIAGNOSTIC AND THERAPEUTIC CHALLENGES - Frolov, MA; Kazakova, KA; Dushina, GN; Frolov, AM; Gonchar, PA (BULLETIN OF RUSSIAN STATE MEDICAL UNIVERSITY, 2020)
A patient presented to our clinic with stage Ia open-angle glaucoma of the right eye and stage IIa surgically corrected open-angle glaucoma of the left eye. The condition of the ocular surface was interpreted as toxic/allergic conjunctivitis provoked by brimonidine 0.15 %. Brimonidine was substituted with non-selective 0.5%; additionally, topical steroids were prescribed. After steroids were discontinued, some of the symptoms came back, including moderate hyperemia and conjunctival edema, which was interpreted as intolerance to a preservative contained in the eye drops. A decision was made to switch from the beta-blocker to its preservative-free formulation; regular IOP monitoring was continued. IOP measured during the next visit was above tolerated, so a preservative-free form of the ocular hypotensive combination drug (an analog of prostaglandin 0.005% with non-selective beta-blocker 0.5%) was introduced to the regimen, with further IOP monitoring. Because the initial diagnosis was wrong, damage to the ocular surface had been aggravated by inadequate therapy. Preservative-free hypotensive eye drops are beneficial for the corneal surface and have a positive effect on a patient's adherence to the regimen.

Clinico-biochemical Correlation of the Effect of Subconjunctival Bevacizumab for Corneal Neovascularization - Agarwal, S; Angayarkanni, N; Iyer, G; Srinivasan, B; Natarajan, R; Charola, S; Arumugam, S; Padmanabhan, P (CORNEA, 2014)
Purpose: The aim of this study was to evaluate the effect of clinical and biochemical effects of subconjunctival bevacizumab injection in eyes with corneal neovascularization (CNV) due to varied etiologies. Methods: This prospective interventional case series included 12 eyes of 12 patients with CNV after failed therapeutic penetrating keratoplasty (4 eyes), viral keratitis (4 eyes), adherent leucoma (2 eyes), and pseudophakic bullous keratopathy (2 eyes). Each eye received 3 doses of 1.25 mg (0.05 mL) of bevacizumab at 1-month intervals. Morphological changes in neovascularization were evaluated at each visit by slit-lamp examination and corneal digital photography. Corneal buttons of 4 eyes that underwent optical penetrating keratoplasty after bevacizumab injections were analyzed for vascular endothelial growth factor (VEGF) expression and were compared with untreated vascularized and normal cadaveric donor corneas. Results: Of the 12 patients, 10 were males and 2 were females. Four eyes received injections in the early phase of vascularization (<12 weeks of onset) of which 3 showed regression of vessels. Eight eyes received bevacizumab in the mature phase (>12 weeks) of which 5 showed regression. The follow-up ranged from 1 to 16 months. Five eyes underwent optical penetrating keratoplasty after receiving the last dose of bevacizumab and maintained graft clarity with no episodes of rejection over a mean follow-up of 9.8 months. Four of these 5 corneal buttons analyzed for VEGF expression revealed clinically significant lower levels of expression as compared with the vascular untreated corneas. No local or systemic adverse effects were noted in any patient. Conclusions: Subconjunctival bevacizumab helps to regress CNV due to a decrease in corneal VEGF levels and might prove beneficial for use in clinical conditions leading to CNV.

Selective Laser Trabeculoplasty for Primary Angle Closure With Persistently Elevated Intraocular Pressure After Iridotomy - Ho, CL; Lai, JSM; Aquino, MV; Rojanapongpun, P; Wong, HT; Aquino, MC; Gerber, Y; Belkin, M; Barkana, Y (JOURNAL OF GLAUCOMA, 2009)
Purpose: To determine whether selective laser trabeculoplasty (SLT) can lower intraocular pressure (IOP) in eyes with chronic primary angle Closure, elevated IOP, and it patent iridotomy. Patients and Methods: Patients with chronic angle closure who had underwent iridotomy. had an IOP greater than 21 mm fig and a gonioscopically visible pigmented trabecular meshwork for at least 90 degrees were enrolled. SLT was applied to open angle segment. Duration of follow-up was 6 months. Results: Sixty eyes of 60 patients were enrolled. The mean baseline IOP was 24.6 +/- 2.5 mm HP. At 6 months, IOP reduction of >= 3 mm Hg or 4 in in H v, was measured in 82%, and 72% of eyes, respectively, and IOP reduction of >= 20% or 30% was measured in 54% and 24% of eyes, respectively. When only eyes that were treated with the same number or fewer medications were considered, these IOP reductions were measured in 67%, 58%, 43%, and 15%. respectively. During the study period 1 eye (1.7%) required trabeculectomy owing to IOP elevation shortly after the SLT. There were no other significant complications attributable to SLT. Conclusions: SLT seems to be a safe and effective method of reducing IOP in many eyes with primary angle closure and a patent iridotomy in which there is a sufficient extent of visible trabecular meshwork

Early outcomes of primary pediatric keratoplasty in patients with acquired, atraumatic corneal pathology - Ganekal, S; Gangangouda, C; Dorairaj, S; Jhanji, V (JOURNAL OF AAPOS, 2011)
PURPOSE To evaluate the early outcomes of pediatric corneal transplantation in patients with acquired, nontraumatic corneal pathology. METHODS In this retrospective series, the records of children 15 years of age or younger who underwent optical penetrating keratoplasty for acquired nontraumatic corneal pathologies between December 2008 and June 2010 were reviewed. Demographic features, etiology of opacification, visual acuity, and other clinical findings were recorded. RESULTS Nineteen eyes of 19 children (10 females) were included. Mean age at time of surgery was 9.1 +/- 3.01 years (range, 5-15 years). Adherent leukoma secondary to healed infectious keratitis (n = 12, 63%) and keratoconus (n = 7, 37%) were the leading indications for surgery. The mean follow-up period was 10.2 +/- 3.3 months (range, 6-18 months). Postoperatively, clear grafts were seen in 15 cases (79%). Graft failure was noted in 4 eyes secondary to allograft rejection (n = 1), graft infection (n = 1), primary graft failure (n = 1), and uncontrolled glaucoma (n = 1). The most common cause of moderate or poor visual outcome was amblyopia (80%). Overall, 13 patients (68%) had postoperative visual acuity better than the preoperative vision. CONCLUSIONS Penetrating keratoplasty can yield good anatomic results in children with acquired, nontraumatic causes of corneal scarring, but amblyopia limits the visual outcomes. (J AAPOS 2011; 15:353-355)

Validation of a More Reliable Method of Eye Drop Self-Administration - Freddo, TF; Ho, DY; Steenbakkers, M; Furtado, N (OPTOMETRY AND VISION SCIENCE, 2020)
SIGNIFICANCE We propose an alternative method for eye drop self-administration. Similar IOP reductions were found with this method compared with clinician instillation. The alternative method of self-administration potentially benefits patients who have trouble successfully instilling drops. PURPOSE The purpose of this study was to validate the efficacy of an alternative method of drop instillation. METHODS This study is a randomized controlled crossover clinical trial. Thirty participants were recruited. A drop of 0.5% timolol maleate was instilled into subject's eye on two separate visits. On one visit, eye drop instillation was by a trained clinician, and on the other, self-instillation using an alternative method was used. The order was randomly chosen. Intraocular pressure was measured before drop instillation and 2 hours after drop instillation. The investigator was masked during measurement, and an observer recorded the IOP measurements. RESULTS Mean +/- SD IOP measurement before 0.5% timolol maleate instillation measured 13.89 +/- 2.29 mmHg. An average reduction 3.75 +/- 2.36 mmHg was found with clinician administration, and an average reduction of 3.32 +/- 2.31 mmHg was recorded with the new method. No significance was found in IOP reduction between two groups P < .45. Percent reduction was 25.17 +/- 16.21% and 24.38 +/- 16.31% in clinician instillation and alternative instillation method group, respectively. No significant difference was found. This percentage reduction was similar to previously reported studies. No reported cases of eye infection or irritation were found in any case, within a 3-month follow-up period. CONCLUSIONS We have proposed a more reliable method for instillation that provides a larger area for instillation and lessen the risk of contamination and patient's fear for eye drops. Similar efficacy was found compared with that of having a clinician directly administer the drop. This alternative method could potentially benefit patients who require topical eye drop therapy and result in increased compliance.

iStent inject trabecular micro-bypass stents with topical prostaglandin as standalone treatment for open-angle glaucoma: 4-year outcomes - Berdahl, J; Voskanyan, L; Myers, JS; Katz, LJ; Samuelson, TW (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2020)
Importance Long-term data are needed regarding effective and safe glaucoma treatment modalities. Background This study evaluated 4-year outcomes of second-generation trabecular micro-bypass stent implantation (iStent inject) combined with topical travoprost in open-angle glaucoma (OAG). Design Prospective, non-randomized, multi-surgeon study at a tertiary care ophthalmology centre. Participants OAG subjects with preoperative intraocular pressure (IOP) 18 to 30 mmHg on two medications and 22 to 38 mmHg post-washout. Methods Subjects (n = 53) underwent standalone iStent inject implantation and started travoprost on postoperative Day 1. Measures included IOP, medications, comprehensive ophthalmic examinations and testing, and adverse events (AEs). Annual medication washouts were performed. Main Outcome Measures Mean medicated and unmedicated IOP; and proportions of eyes with IOP <= 18mmHg, <= 15 mmHg, or >= 20% reduced while on travoprost vs screening IOP on two medications. Results At 48 months postoperative, 85% of eyes reduced IOP >= 20% on travoprost vs screening IOP on 2 medications; 92% of eyes had IOP <= 18 mmHg on travoprost; and 83% had IOP <= 15 mmHg on travoprost. At Month 49 (post-washout), 90% of eyes reduced IOP >= 20% vs preoperative washout IOP. Throughout follow-up, mean IOP on travoprost was 11.9 to 13.0 mmHg (34%-40% reduced vs 19.7 mmHg on 2 medications preoperatively; P < .0001 throughout), and post-washout IOP was 16.5 to 17.7 mmHg (28%-34% reduced vs 24.9 mmHg preoperatively; P < .0001 throughout). Favourable safety included minimal AEs; stable visual acuity, cup-to-disc ratio and visual fields; and no secondary surgeries. Conclusions and Relevance Combining iStent inject implantation with topical prostaglandin produced significant and safe 4-year IOP and medication reductions in OAG.

Policy implications of regional variations in eye disease detection and treatment on Prince Edward Island: a repeated cross-sectional analysis, 2010-2012 - Khan, AM; Trope, GE; Wedge, R; Buys, YM; El-Defrawy, S; Chen, Q; Jin, YP (BMC HEALTH SERVICES RESEARCH, 2018)
Background: In Canada, government insurance covers eye care services provided by ophthalmologists and other physicians. However, government coverage for services provided by optometrists, non-medical school trained primary eye care providers, varies regionally. Little is known about the impact of a funding model in which ophthalmologist services are government-insured but services provided by optometrists are not, on eye care utilization and eye disease detection and treatment. We aimed to address this question by examining geographic variations in eye care service utilization on Prince Edward Island (PEI). Methods: PEI physician-billing data from 2010 to 2012 was analyzed across five distinct geographic regions (Charlottetown, Summerside, Prince, Queens & Kings and Stratford). The residential location of patients and practice locations of eye care providers were identified using the first three digits of their respective postal code. Age-standardized rates were computed for comparisons across different regions. Results: There were six ophthalmologists practicing on PEI, five with offices in Charlottetown. Twenty optometrists practiced on the island with offices across the province. Stratford is closest and Prince farthest from Charlottetown. Age-standardized utilization rates of ophthalmologists per 100 populations were 10.44 in Charlottetown and 10.90 in Stratford, which was significantly higher than in other regions (7.74-8.92; p < 0.05). The disparities were most pronounced amongst the elderly. The prevalence of glaucoma visits was higher in Charlottetown (6.10%) and Stratford (6.38%) and lower in other regions. A similar pattern was observed for the prevalence of cataract visits. While the prevalence of diabetes visits was higher in Prince and Summerside, the utilization of ophthalmologists by people with diabetes was almost twice as high in Charlottetown (6.49%) than in Prince (3.88%). Conclusions: The observed discrepancies in vision care utilization across geographic regions were likely attributed to barriers in accessing government-insured, geographically concentrated ophthalmologists, as opposed to a reflection of the true differences in eye disease occurrence. The lower prevalence of glaucoma visits in regions farther away from ophthalmologist offices may result in delayed detection and blindness in this population. Encouraging ophthalmologists to work in other areas of the province and/or to publicly fund services provided by optometrists may mitigate the observed disparities.

Infectious Keratitis in Severe Limbal Stem Cell Deficiency: Characteristics and Risk Factors - Sandali, O; Gaujoux, T; Goldschmidt, P; Ghoubay-Benallaoua, D; Laroche, L; Borderie, VM (OCULAR IMMUNOLOGY AND INFLAMMATION, 2012)
Purpose: To evaluate the incidence, clinical and microbiological characteristics and risk factors of infectious keratitis in patients with limbal stem cell deficiency (LSCD). Methods: Retrospective comparative case series of 35 patients with severe LSCD. Results: The mean follow-up time was 46 months. Infectious keratitis were mainly caused by Gram positive bacteria (94%). Only 7 infections (37%) healed under fortified adapted antibiotics. In 8 cases (42%), amniotic membrane transplantation was required and in 4 cases (21%) "a chaud" keratoplasty was performed. Significant risk factors associated with infectious keratitis were: soft contact lens extended wear, history of persistent epithelial defects, number of quadrants of corneal vascularization, re-epithelialization time after amniotic membrane or corneal transplantation, and use of corticosteroid or cyclosporin eye drops. Conclusion: Infectious keratitis in LSCD is frequent and severe. The restoration of the epithelial barrier integrity and a careful use of therapeutic contact lenses may help to prevent infection.

Exfoliation syndrome - Ritch, R; Schlotzer-Schrehardt, U (SURVEY OF OPHTHALMOLOGY, 2001)
Exfoliation syndrome (XFS) is an age-related disease in which abnormal fibrillar extracellular material is produced and accumulates in many ocular tissues. Its ocular manifestations involve all of the structures of the anterior segment, as well as conjunctiva and orbital structures. Glaucoma occurs more commonly in eyes with XFS than in those without it; in fact, XFS has recently been recognized as the most common identifiable cause of glaucoma. Patients with XFS are also predisposed to develop angle-closure glaucoma, and glaucoma in XFS has a more serious clinical course and worse prognosis than primary open-angle glaucoma. There is increasing evidence for an etiological association of XFS with cataract formation, and possibly with retinal vein occlusion. XFS is now suspected to be a systelnic disorder and has been associated preliminarily with transient ischemic attacks, stroke, systemic hypertension, and myocardial infarction. Further ramifications await discovery. Deposits of white material on the anterior lens surface are the most consistent and important diagnostic feature of XFS. The classic pattern consists of three distinct zones that become visible when the pupil is fully dilated. Whereas the classic picture of manifest XFS has been often described, the early stages of beginning exfoliation have not been well defined. Next to the lens, exfoliation material is most prominent at the pupillary herder. Pigment loss from the iris sphincter region and its deposition on anterior chamber structures is a hallmark of XFS. Despite extensive research, the exact chemical composition of exfoliation material (XFM) remains unknown. An overproduction and abnormal metabolism of glycosaminoglycans have been suggested as one of the key changes in XFS. The protein components of XFM include both noncollagenous basement membrane components and epitopes of the elastic fiber system such as fibrillium. Regardless of etiology, typical exfoliation fibers have been demonstrated electron microscopically in close association with the pre-equatorial lens epithelium, the nonpigmented ciliary epithelium, the iris pigment epithelium, the corneal endothelium, the trabecular endothelium, and with almost all cell types of the iris stroma, such as fibrocytes, melanocytes, vascular endothelial cells, pericytes, and smooth muscle cells. The presence of XFS should alert the physician to the increased risks of intraocular surgery, most commonly zonular dehiscence, capsular rupture, and vitreous loss during cataract extraction. Heightened awareness of this condition and its associated clinical signs are important in the detection and management of glaucoma, and preoperative determination of those patients at increased risk for surgical complications. (C) 2001 Elsevier Science Inc. All rights reserved.

Living with glaucoma: a qualitative study of functional implications and patients' coping behaviours - Glen, FC; Crabb, DP (BMC OPHTHALMOLOGY, 2015)
Background: Sight loss from glaucoma can have a significant impact on functioning and performing everyday activities, but this varies between patients. The purpose of this study was to explore whether patients with glaucoma use different coping strategies in response to their vision loss. Methods: Audio-recorded semi-structured interviews were conducted with 16 patients (median age: 71 [interquartile range [IQR]: 68 to 77 years]; 50 % female) about their experiences of living with glaucoma. Patients had their glaucoma diagnosis for at least 5 years (range: 6 to 29 years) and had a range of disease severities (median best eye Mean Deviation was -9.1 dB [IQR: -12.9 to -4.1 dB]). A framework approach to analysis was taken whereby data was indexed using manual and computer-assisted methods, with codes applied to depict areas of functioning perceived to be impacted by glaucoma and coping behaviours used in response to these difficulties. Results: In order to maintain independence, some patients increased confidence by making practical changes such as adjusting lighting, using handrails and magnifying glasses, or actively changed aspects of their behaviour such as moving their head and eyes towards known areas of vision loss. Support from friends and family was often used, although some people worried about becoming a burden. Others imposed self-restrictions or gave up activities, thus compromising well-being and independence. Certain coping strategies were linked to time since diagnosis and location of vision loss. The type and quality of information received during clinical appointments, and the potential benefits of communication with other patients, emerged as other important themes. Conclusions: Results from this qualitative study suggest that the adoption of certain coping behaviours and techniques may help some glaucomatous patients to adapt to their condition. An awareness of coping and adaptive strategies, in addition to the usual clinical tests, may provide a better insight into the impact of disease and help inform future educational and management strategies for glaucoma.

Alterations in the aqueous humor proteome in patients with a glaucoma shunt device - Anshu, A; Price, MO; Richardson, MR; Segu, ZM; Lai, XY; Yoder, MC; Price, FW (MOLECULAR VISION, 2011)
Purpose: To investigate whether implantation of a glaucoma shunt device leads to inappropriate accumulation of plasma derived proteins in the aqueous humor. Methods: Aqueous humor samples were collected from 11 patients (study group) with a glaucoma shunt device undergoing either cataract surgery or a corneal transplant and 11 patients (control) with senile cataract undergoing routine cataract extraction. Of the study group, 9 had an Ahmed valve implant and 2 eyes had a Baerveldt implant. Tryptic digests of the mixture of proteins in aqueous humor (AH) were analyzed using Liquid Chromatography/Mass Spectrometry (LC-MS/MS). Proteins were identified with high confidence using stringent criteria and compared quantitatively using a label-free platform (IdentiQuantXL (TM)). Results: We identified 135 proteins in the albumin-depleted fraction in both the study and control group AH. Using stringent criteria, 13 proteins were detected at a significantly higher level compared to controls. These proteins are known to play a role in oxidative stress, apoptosis, inflammation and/or immunity and include gelsolin (p=0.00005), plasminogen (p=0.00009), angiotensinogen (p=0.0001), apolipoprotein A-II (p=0.0002), beta-2-microglobulin (p=0.0002), dickkopf-3 (DKK-3; p=0.0002), pigment epithelium-derived factor (p=0.0002), RIG-like 7-1 (p=0.0002), afamin (p=0.0003), fibronectin 1 (FN1; p=0.0003), apolipoprotein A-I (p=0.0004), activated complement C4 protein (C4a; p=0.0004) and prothrombin (p=0.0004). Many of the identified proteins were novel proteins that have not been associated with glaucoma in prior studies. All but C4a (complement C4 is a plasma protein but not in an activated form) are known plasma proteins and the elevated levels of these proteins in the aqueous humor suggests a breach in the blood-aqueous barrier with passive influx into the anterior chamber of the eye. Conclusions: The presence of these proteins in the aqueous humor suggests that glaucoma shunt device causes either a breach in blood-aqueous barrier or chronic trauma, increasing influx of oxidative, apoptotic and inflammatory proteins that could potentially cause corneal endothelial damage.

Factors Associated with Patient Satisfaction in an Outpatient Glaucoma Population - Rahmatnejad, K; Myers, JS; Falls, ME; Myers, SR; Waisbourd, M; Hark, LA (SEMINARS IN OPHTHALMOLOGY, 2018)
Purpose: To determine what metrics might impact satisfaction survey responses. Methods: A 37-question survey was administered to 249 participants. Responses were correlated to demographics, clinical factors, weather conditions, and examination timing. Results: Sample consists of 55.4% female and 73.9% white, and mean age was 65.1 years. Participants were assigned to: completely satisfied (77.9%) or not completely satisfied (22.1%) groups based on their rating of glaucoma specialist on a scale of 1-10, while 10 considered "completely satisfied" and less than 10 "not completely satisfied." Complete satisfaction was associated with ability to schedule appointments early, phone calls answered/returned same day, shorter perceived wait time, and better communication skills of ophthalmologist (p < 0.05). Completely satisfied participants reported their ophthalmologist spent enough time with them, listened carefully, and communicated in an understandable way (p < 0.05). Conclusions: The majority of factors found to be associated with patient satisfaction were related to characteristics of the ophthalmologists and their office.

Menstrual cycle-dependent changes in white-on-white visual field analysis of diabetic women - Akar, ME; Apaydin, KC; Taskin, O; Akar, Y; Trak, B (GYNECOLOGIC AND OBSTETRIC INVESTIGATION, 2005)
Aim: To determine the effect of the menstrual cycle on white-on-white perimetry (WWP) tests of diabetic women. Subjects and Methods: Left eyes of 129 normally menstruating women (81 type 1 diabetes mellitus (DM) with mild (n = 43) and severe (n = 38) non-proliferative diabetic retinopathy (NPDR), and 48 healthy control females) were included in the study. All subjects underwent complete ocular examination and WWP tests both in the follicular (7-10th day of the cycle) and luteal phases (days 3-7 before the bleeding) of two consecutive menstrual cycles. WWP was performed using Humphrey Field Analyzer II with SITA Standard, central 30-2 program. Mean sensitivity (MS) of points located at central 3, 9, 15, 21 and 27 degrees retinal locations (4, 12, 18, 24 and 16 points, respectively) were calculated in all menstrual phases. Results: The mean age of diabetic patients with mild and severe NPDR and control subjects were 28.8 +/- 4.7, 30.1 +/- 5.9 and 29.4 +/- 5.1 years, respectively (p > 0.05). Their mean MS values were 30.7 +/- 1.0, 30.4 +/- 1.0 and 30.8 +/- 0.8 dB, respectively (p > 0.05). Diabetic patients with severe NPDR demonstrated significant decreases in mean MS values of peripheral 21 and 27 degrees visual field locations in the luteal phase (p < 0.05). However, changes in that of the locations within central 15 degrees visual field were non-significant (p > 0.05). Diabetic patients with mild NPDR and control subjects demonstrated no significant changes in mean MS values of any of the visual field locations (p > 0.05). Conclusion: Peripheral, rather than central, locations of central visual field of diabetic women with severe NPDR demonstrated a significant retinal sensitivity loss in the luteal phase. These findings should be taken into consideration during the clinical follow-up of diabetic women at risk of glaucoma and ocular hypertension. Copyright (C) 2005 S. Karger AG, Basel.

Case Report: Clinical Remission in a Cat With Severe Bilateral Eosinophilic Keratitis Receiving Combined Immunosuppressive Therapy (Triamcinolone Acetonide and Tacrolimus) - Romaneck, AK; Sebbag, L (FRONTIERS IN VETERINARY SCIENCE, 2021)
A 2-year-old domestic shorthair cat was examined for severe keratitis of 10 months duration, non-responsive to 0.1% dexamethasone q8-12h. Patient and owner compliance were poor given ocular discomfort and hiding behavior. On presentation, both eyes (OU) had severe ulcerative keratitis that masked examination of deeper structures and resulted in absent menace response OU. Corneal cytology was consistent with eosinophilic keratitis (EK) OU. Initial therapy included subcutaneous triamcinolone acetonide injection (0.2 mg/kg), 0.3% ciprofloxacin OU q12h, and two compounded drugs started 5 days later upon receipt: 0.5% tacrolimus OU q6h, 0.5% cidofovir OU q12h. Visual behavior and ocular comfort were reportedly much improved within 24 h. At the first recheck (Day 11), patient and owner compliance were reported to be excellent, menace response was positive OU, and keratitis was dramatically reduced OU with absent fluorescein uptake. Subcutaneous triamcinolone acetonide was repeated (0.2 mg/kg), ciprofloxacin was discontinued, cidofovir was continued q12h, and tacrolimus was slowly tapered (q8h x 3 weeks then q12h). Keratitis was nearly 100% resolved at the second recheck (Day 38); cidofovir was discontinued and tacrolimus was slowly tapered (q12h x 1 week, q24h x 4 weeks, q48h x 4 weeks) then discontinued. A third recheck (Day 101) confirmed clinical remission OU, and disease did not reoccur within a 1 year follow up period (photographic documentation by owner). In sum, adjunct use of triamcinolone acetonide greatly improved therapeutic compliance and helped control severe EK in a rapid and effective manner.

Blindness in patients with treated open-angle glaucoma - Chen, PP (OPHTHALMOLOGY, 2003)
Purpose: To investigate blindness in patients with treated open-angle glaucoma (OAG) and risk factors for blindness. Design: Retrospective observational case series. Participants: One hundred eighty-six patients seen between April and November 2000 at the University of Washington Medical Center Eye Clinic, diagnosed in 1975 or later, and treated for at least 2 years for OAG. Methods: Chart review with evaluation of visual acuity and visual field. Kaplan-Meier survival analysis was used to estimate the risk of blindness in one and both eyes. Variables considered to be possible risk factors foe blindness were evaluated using chi-square test, t test, and Cox proportional hazards regression analysis. Main Outcome Measures: Blindness, defined as visual acuity of 20/200 or worse, and/or continuous constriction of the visual field to 20degrees or less in all four quadrants with a size III4e Goldmann stimulus or the equivalent on automated perimetry, allowing a higher threshold level on one point in one quadrant on automated perimetry. Results: The mean duration of disease was 10.2 +/- 4.9 years. Twelve patients were blind in at least one eye from OAG at diagnosis. Nineteen other patients became blind in at least one eye from OAG, and three patients became bilaterally blind from OAG. The Kaplan-Meier estimate for blindness at 15 years in one eye was 14.6%, and in both eyes was 6.4%. Noncompliance with the treatment regimen (P = 0.016) and worse initial visual field loss (P < 0.0001) were significantly associated with development of blindness. Nonwhite race was associated with blindness (P = 0.014) when all blindness, including that found at diagnosis, was considered in the analysis. Conclusions: Bilateral blindness from chronic OAG was uncommon in this population of treated patients diagnosed in 1975 or later. Of patients with a blind eye, 39% were blind at diagnosis, and worse visual field loss at diagnosis and noncompliance were associated with development of blindness. (C) 2003 by the American Academy of Ophthalmology.

Preservative-free fixed combination of tafluprost 0.0015% and timolol 0.5% in patients with open-angle glaucoma and ocular hypertension: results of an open-label observational study - Pillunat, LE; Erb, C; Ropo, A; Kimmich, F; Pfeiffer, N (CLINICAL OPHTHALMOLOGY, 2017)
Background: Efficacy, tolerability and safety of the novel preservative-free fixed combination of tafluprost 0.0015%/ timolol 0.5% (Taptiqom (R)) were investigated in an observational study in Germany. Objective: To assess efficacy, tolerability and safety of the preservative-free fixed combination of tafluprost 0.0015%/ timolol 0.5% in a real-life setting. Methods: Intraocular pressure (IOP) was recorded for each eye at baseline (any previous therapy or untreated) and 4-16 weeks after changing medical treatment to or initiating treatment with the preservative-free fixed combination of tafluprost 0.0015%/ timolol 0.5%. Change in IOP was evaluated over the study period for all patients and for specific pretreatment subgroups. Clinical signs such as conjunctival hyperemia and lid-parallel conjunctival folds (LIPCOF) were recorded using standardized comparative photographs. Corneal staining, subjective symptoms and local comfort were measured using a four-step scale. All adverse events were recorded. Results: Among 1,157 patients enrolled, 1,075 patients were treated with the preservative-free fixed combination as the only medication at the final visit. Medical treatment was initiated in 741 patients because of an insufficient IOP-lowering effect of the prior medication. In 343 patients, medication was changed because of tolerability issues. The preservative-free fixed combination lowered IOP significantly in the subgroup of naive patients, all subgroups with prior monotherapy and patients with prior fixed combinations: naive patients: -8.9 mmHg, alpha-2-agonists: -6.4 mmHg, beta-blockers: -5.7 mmHg, carbonic anhydrase inhibitors: -5.2 mmHg, prostaglandins: -4.7 mmHg, fixed-combination prostaglandins/timolol: -2.4 mmHg. At the final visit, clinical signs and subjective symptoms were improved in patients with prior medical therapy. Local comfort was rated as "very good" or "good" by 89.1% of patients at the final visit. Only few adverse events occurred during the treatment period. Conclusion: The preservative-free fixed combination of tafluprost 0.0015%/timolol 0.5% was effective, well tolerated and showed a good safety profile.

Non-Compliance and Microbial Contamination in Orthokeratology - Cho, P; Boost, M; Cheng, R (OPTOMETRY AND VISION SCIENCE, 2009)
Purpose. To determine the rates of microbial contamination of solutions and lens accessories of existing ortho-k lens wearers and-the effect on contamination rates of monthly replacement and warnings. To investigate self-reported levels of compliance with care of the lenses and lens accessories and correlation of these levels with the rates of microbial contamination. Methods. Asymptomatic ortho-k lens wearers with at least 6-month successful use were requested to bring their lenses, solutions, and accessories to their next aftercare visit. All items, except the lenses, were replaced at each data collection visit. Samples collected from the lens surface, solution, and accessories were Cultured for pathogens. These procedures were repeated twice at 1-month intervals. At the first visit, each subject and/or parent was interviewed about the care/use of the lens and accessories. Results. Thirty-eight subjects completed the study. Initial contamination rates of the lenses, lens cases, and tweezers were 29, 34, and 46%, respectively. Rates of contamination dropped for lenses, suction holders, and tweezers during the three-visit intervention. Contact lens solutions, except lens cleaner were contaminated on all occasions with the most contaminated product being artificial tears [33% (n = 18)]. There was no improvement in the contamination rate of the lens cases. The most common pathogens isolated were Staphylococcus aureus and Serratia marcescens. Compliance was lowest for care of lens cases and highest for care of lenses. However, correlation between reported compliance and presence of pathogens failed to reach significance. Conclusions. Subjects' awareness of the importance of lens cleanliness is high and can be improved by regular reinforcements. However, attitudes toward cleaning of accessories was far less satisfactory and while replacement and warnings resulted in significant improvements of contamination rates of tweezers and suction holders, more emphasis should be placed on educating patients on correct care of lens accessories. (Optom Vis Sci 2009;86:1227-1234)

Five-Year Outcomes Prospective Study of Two First-Generation Trabecular Micro-Bypass Stents (iStent (R)) in Open-Angle Glaucoma - Saheb, H; Donnenfeld, ED; Solomon, KD; Voskanyan, L; Chang, DF; Samuelson, TW; Ahmed, IIK; Katz, LJ (CURRENT EYE RESEARCH, 2021)
Purpose To assess 5-year effectiveness and safety of 2 iStent (R) trabecular micro-bypass stents in eyes with open-angle glaucoma (OAG) not controlled on 1 medication. Materials and Methods This prospective, interventional, single-arm, multi-surgeon study (NCT #1252862, clinicaltrials.gov) enrolled eyes with OAG, preoperative intraocular pressure (IOP) of 18-30 mmHg on 1 ocular hypotensive medication, and 22-38 mmHg after medication washout. Eyes underwent standalone implantation of 2 iStent devices and were followed through 60 months postoperatively. Efficacy was quantified by mean diurnal IOP and medication usage. Efficacy endpoints included the proportion of eyes with >= 20% IOP reduction versus baseline unmedicated IOP (primary efficacy), and the proportion of eyes with IOP <= 18 mmHg (secondary efficacy) without medication or secondary glaucoma surgery. Safety parameters included visual acuity, cup-to-disc ratio, visual field, and complications and adverse events. Results Preoperative mean IOP on 1 medication was 20.6 +/- 2.0 mmHg and post-washout unmedicated IOP was 24.1 +/- 1.4 mmHg (n = 39). At 5 years postoperative, medication-free mean diurnal IOP reduced to 14.5 +/- 2.2 mmHg, constituting a 40% decrease versus preoperative washed-out IOP (p< .0001). In addition, this 5-year medication-free IOP constituted a 30% decrease versus preoperative IOP on 1 medication (p< .0001). At Month 60, 89.7% (26/29) of eyes achieved the primary efficacy endpoint of >= 20% IOP reduction versus baseline unmedicated IOP, and 86.2% (25/29) of eyes achieved the secondary efficacy endpoint of IOP <= 18 mmHg, without medication or secondary glaucoma surgery. Throughout follow-up, 89.7-91.3% of eyes were on no medications. Favorable safety included no secondary glaucoma surgeries, minimal adverse events, and stable visual acuity, cup-to-disc ratio, and visual fields through 5 years postoperative. Conclusions This prospective interventional study demonstrates persistent 5-year reductions in IOP and freedom from medications, together with favorable safety, following implantation of 2 first-generation trabecular micro-bypass stents in eyes with OAG on 1 preoperative medication.

Dry eye specific quality of life in veterans using glaucoma drops - Camp, A; Wellik, SR; Tzu, JH; Feuer, W; Arheart, KL; Sastry, A; Galor, A (CONTACT LENS & ANTERIOR EYE, 2015)
Purpose: To evaluate the frequency of ocular surface symptoms and their potential impact on dry eye specific quality of life (QoL) in patients using versus not using glaucoma medications. Material and methods: The study was a single-center, cross-sectional survey of patients seen at the Miami Veterans Affairs (VA) ophthalmology and optometry clinics from June to August, 2010. Patients were invited to complete the Dry Eye Questionnaire 5 (DEQ5) and the Impact of Dry Eye on Everyday Life (IDEEL) at their visit. Of 1348 patients seen in the Miami VA eye clinics during this three-month period, 467 patients completed the DEQ5 and 391 responded to both questionnaires. Outcome measures comprised ocular surface symptoms and their impact on dry eye specific QoL in patients using versus not using glaucoma drops. Results: An increasing number of glaucoma drops was significantly associated with an increased percentage of severe dry eye symptoms: no medications, 25% (n = 89/353); 1 or 2 medications, 27% (n = 17/62); 3 or more medications, 40% (n = 21/52); p = 0.03 (Armitage's test for linear-trend in proportions). There was an association between increasing number of drops and decreasing emotional well-being scores (linear p < 0.001; quadratic p = 0.029). Black patients had higher dry eye symptoms and lower emotional QoL scores compared to white patients at every level of medication use. Conclusion: An increasing number of glaucoma medications were associated with an increased frequency of severe dry eye symptoms and decreased emotional QoL. Additionally, dry eye specific emotional QoL was more severely affected in black versus white patients. Published by Elsevier Ltd on behalf of British Contact Lens Association

How glaucoma patient characteristics, self-efficacy and patient-provider communication are associated with eye drop technique - Sayner, R; Carpenter, DM; Robin, AL; Blalock, SJ; Muir, KW; Vitko, M; Hartnett, ME; Lawrence, SD; Giangiacomo, AL; Tudor, G; Goldsmith, JA; Sleath, B (INTERNATIONAL JOURNAL OF PHARMACY PRACTICE, 2016)
Objectives The objective of this study was to examine the extent to which patient characteristics, eye drop technique self-efficacy, and ophthalmologist-patient communication about eye drop administration are associated with glaucoma patients' ability to instil a single drop, have the drop land in the eye, and avoid touching the applicator tip of the medication bottle to the eye or face while self-administering eye drops. Methods Glaucoma patients (n = 279) were recruited from six ophthalmology clinics. Medical visits were videotape-recorded. Afterwards, patients were interviewed and demonstrated administering an eye drop on a videotaped-recording. Generalized estimating equations were used to analyse the data. Key findings Ophthalmologists provided eye drop administration instruction to 40 patients. Patients with more years of education were significantly more likely to both instil a single drop (P = 0.017) and have the drop land in their eye (P = 0.017). Women were significantly more likely to touch the applicator tip to their eyes or face (P = 0.014). Patients with severe glaucoma (P = 0.016), women (P = 0.026), and patients who asked at least one eye drop administration question (P = 0.001) were significantly less likely to instil a single drop. Patientswith arthritis were significantly less likely to have the drop land in their eye (P = 0.008). African American patients were significantly less likely to touch the applicator tip to their eyes or face (P = 0.008). Conclusions Some glaucoma patients have a difficult time self-administering eye drops. As so few patients received eye drop administration instruction from their providers, there is an opportunity for pharmacists to complement care.

Patient attitudes and behavior regarding hygiene and replacement of soft contact lenses and storage cases - Hickson-Curran, S; Chalmers, RL; Riley, C (CONTACT LENS & ANTERIOR EYE, 2011)
Purpose: To review important aspects of contact lens compliance and to survey contact lens replacement frequency, steps in lens care and hygiene and replacement of the lens storage case via online surveys. Methods: Random US samples (n = 645 and 787) of frequent replacement contact lens wearers answered questions on contact lens wear in online, sponsor-masked surveys. Results: Wearers of lenses prescribed by their practitioner for 2 weekly replacement reported that they replaced lenses as follows: within 2 weeks 45%, within 3 weeks (minor stretching) 68%, within 4 weeks 89%, >= 8 weeks (extreme stretching) 4%, compared to Monthly wearers who reported: within 4 weeks 37%, within 5 weeks (minor stretching) 57%, >= 8 weeks 23% (>= 8 weeks extreme stretching, Chi-square p = 0.001). Median frequency for cleaning lens storage case was 2-3 times per week, while 33% reported cleaning monthly or less often. Median lens storage case replacement was every 4-6 months, while 48% reported annual replacement or less often. Most patients cleaned their lens case with hot or cold tap water (72%). Conclusions: These internet surveys revealed significant non-compliance with lens care steps, case hygiene and lens replacement schedule. More than half of the contact lens wearers surveyed were not compliant with their 2-weekly or monthly schedule. Lenses prescribed for longer replacement intervals can lead to more extreme stretching of lens life. To encourage better patient habits, eye care providers should reinforce their recommended frequency of replacement of lenses and storage cases and should reinforce care and hygiene steps at each patient visit. (C) 2010 Published by Elsevier Ltd on behalf of British Contact Lens Association.

The value of corneal transplantation in reducing blindness - Garg, P; Krishna, PV; Stratis, A; Gopinathan, U (EYE, 2005)
Purpose To analyse the role of keratoplasty in reducing world blindness due to corneal diseases. Methods Review of published literature. We collected and analysed articles published in the English language literature related to the prevalence and causes of blindness in different parts of the world, causes of corneal blindness, and outcome of corneal transplantation for various corneal diseases. Results A total of 80% of the world's blind live in developing countries. Retinal diseases are the most important causes of blindness (40-54%) in established economy nations while cataract (44-60%) and corneal diseases (8-25%) are the most common causes of blindness in countries with less developed economies. Keratitis during childhood, trauma, and keratitis during adulthood resulting in a vascularized corneal scar and adherent leucoma are the most frequent causes of corneal blindness in developing countries. Corneal diseases are responsible for 20% of childhood blindness. Nearly 80% of all corneal blindness is avoidable. The outcome of keratoplasty for vascularized corneal scar and adherent leucoma is unsatisfactory, necessitating repeat surgery in a high proportion of these cases. Other barriers for keratoplasty in these nations are suboptimal eye banking, lack of trained human resources, and infrastructure. Conclusions Since the developing world carries most of the load of corneal blindness and the major causes of corneal blindness are corneal scar and active keratitis, development of corneal transplantation services need a comprehensive approach encompassing medical standards in eye banking, training of cornea specialists and eye banking personnel and exposure of ophthalmologists to care of corneal transplants for better follow-up care. However, concerted efforts should be made to develop and implement prevention strategies since most corneal blindness is preventable.

Remote eye care screening for rural veterans with Technology-based Eye Care Services: a quality improvement project - Maa, AY; Wojciechowski, B; Hunt, K; Dismuke, C; Janjua, R; Lynch, MG (RURAL AND REMOTE HEALTH, 2017)
Context: Veterans are at high risk for eye disease because of age and comorbid conditions. Access to eye care is challenging within the entire Veterans Hospital Administration's network of hospitals and clinics in the USA because it is the third busiest outpatient clinical service and growing at a rate of 9% per year. Issue: Rural and highly rural veterans face many more barriers to accessing eye care because of distance, cost to travel, and difficulty finding care in the community as many live in medically underserved areas. Also, rural veterans may be diagnosed in later stages of eye disease than their non-rural counterparts due to lack of access to specialty care. In March 2015, Technology-based Eye Care Services (TECS) was launched from the Atlanta Veterans Affairs (VA) as a quality improvement project to provide eye screening services for rural veterans. Lessons learned: By tracking multiple measures including demographic and access to care metrics, data shows that TECS significantly improved access to care, with 33% of veterans receiving same-day access and >98% of veterans receiving an appointment within 30 days of request. TECS also provided care to a significant percentage of homeless veterans, 10.6% of the patients screened. Finally, TECS reduced healthcare costs, saving the VA up to US$ 148 per visit and approximately US$ 52 per patient in round trip travel reimbursements when compared to completing a face-to-face exam at the medical center. Overall savings to the VA system in this early phase of TECS totaled US$ 288,400, about US$ 41,200 per month. Other healthcare facilities may be able to use a similar protocol to extend care to at-risk patients.

Viscocanalostomy for open-angle glaucoma in black African patients - Stegmann, R; Pienaar, A; Miller, D (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 1999)
Purpose: To study the clinical effectiveness of viscocanalostomy in a population of black African patients with open-angle glaucoma that was uncontrolled on medical treatment. Setting: Department of Ophthalmology, Medical University of Southern Africa, MEDUNSA, South Africa. Methods: In this prospective study, viscocanalostomy was performed in 214 eyes of 157 black African patients with open-angle glaucoma that was poorly controlled by medical therapy. The procedure involves the production of superficial and deep scleral flaps. The deep flap is dissected to the plane of Schlemm's canal. From this plane, an intact window in Descemet's membrane is created by gentle pressure at the level of Schwalbe's line using a cellulose sponge. Aqueous humor diffuses through this window into a subscleral space (lake). Reflection of the inner flap unroofs Schlemm's canal, creating a trough leading to 2 entrances into Schlemm's canal (surgical ostia). A delicate cannula is introduced into the entrance of Schlemm's canal left and right, and high-viscosity sodium hyaluronate is gently injected into the canal for 4 to 6 mm. The deeper scleral flap is excised (deep sclerectomy) and the superficial flap is sutured securely using 5, 11-0 polyester fiber (Mersilene(R)) sutures. High-viscosity sodium hyaluronate is then injected into the subscleral lake to act as a physical barrier to fibrinogen migration postoperatively. Results: Postoperative intraocular pressure (IOP) of 22 mm Hg or less was achieved without medical therapy in 82.7% of eyes. If a beta blocker was added to the cases not achieving 22 mm Hg or less postoperatively, the success rate increased to 89.0%. The average follow-up was 35 months (range 6 to 64 months). Conclusion: Viscocanalostomy produced an encouraging long-term reduction in the IOP of black African patients with glaucoma who would otherwise have had a poor prognosis.

Switching from systemic to the topical carbonic anhydrase inhibitor dorzolamide: Effect on the quality of life of glaucoma patients with drug-related side effects - Nesher, R; Ticho, U (ISRAEL MEDICAL ASSOCIATION JOURNAL, 2003)
Background: The frequent systemic side effects associated with the use of systemic carbonic anhydrase inhibitors have adversely affected the compliance to treatment in glaucoma patients, obviating their long-term use. The introduction of the topical CAI dorzolamide has further reduced their use. However, the tolerability of dorzolamide in patients who have been intolerant to systemic CAIs has not been evaluated prospectively. Objectives: To study the tolerability and efficacy of dorzolamide (a topical CAI) in a selected group of glaucoma and ocular hypertensive patients who have been intolerant to systemic CAI. Methods: A 3 month prospective study was conducted in 39 patients. Following recruitment, patients were evaluated on the day of switching from systemic CAI to dorzolamide and for five more visits. The SF-36 health assessment questionnaire was used to evaluate changes in well-being and quality of life, and the intraocular pressure was measured periodically. Results: Within 4 weeks of switching from systemic CAI to dorzolamide, the mean health assessment scores improved significantly in seven of the eight categories of the SF-36, and remained generally unchanged for the rest of the study. No significant differences were noted between the mean IOP on day 0 and the following measurements throughout the 84 days of dorzolamide therapy. Conclusion: In glaucoma patients who were intolerant to systemic CAI, topical CAI dorzolamide offers a similar efficacy and better tolerability.

Effect of written instructions on accuracy of self-reporting medication regimen in glaucoma patients - Kharod, BV; Johnson, PB; Nesti, HA; Rhee, DJ (JOURNAL OF GLAUCOMA, 2006)
Purpose: Our purpose was to evaluate the accuracy of self-reporting of the prescribed medication regimen in a glaucoma population, identify contributing factors, and assess the effect of written instructions. Methods and Materials: All patients at an urban resident glaucoma clinic were offered participation in this prospective, case-controlled study. Two trained interviewers administered a confidential questionnaire consisting of six questions regarding the name and dosage of ophthalmic medications, education level, ability to read, and age. A verbatim response for each question was recorded on the questionnaire. At the end of the visit, patients were given a written chart describing their ophthalmic medications, frequency, and dosage. At their next scheduled visit, the same questionnaire was repeated. The patients' responses from both visits were compared with the regimen they were prescribed and with each other. This information was used to determine the accuracy of reporting medications. Results: A total of 193 patients were enrolled in the study over a 10-month period; 164 patients completed both phases (85% completion rate). The study population consisted of 85 women and 79 men with a mean age of 68.40 +/- 11.6 years. Eighty-four patients had attained less than 12th grade education and 80 had completed high school. At the first visit, 66 patients (40%) showed less than 100% accuracy. Forty-nine of 84 (58%) patients who had not completed high school education showed less than 100% accuracy with a mean score of 65% (P = 0.001), whereas 17 of 80 (21%) of patients who had completed high school showed less than 100% accuracy with a mean score of 87% (P = 0.001). After written instruction, the accuracy of reporting improved by 23.36 +/- 30.8 percentile points in patients without completion of high school education and improved by 8.46 +/- 21.7 percentile points in patients who had completed high school (P < 0.001). The mean number of ophthalmic medications prescribed was 2.10 +/- 0.93 (range 1 to 4). Patients on one medication had 100% accuracy in reporting 82% of the time, whereas those with four medications had 100% accuracy 21% of the time. Gender, age, and race of the patient were not correlated with the accuracy of self-reporting (P > 0.05). Conclusion: The education level of the patient and the number of medications showed direct correlation with patients' ability to report medications accurately. Patients showed improvement in accuracy of reporting medications when given written instructions about their regimen, regardless of their level of education or number of medications.

History and symptom taking in contact lens fitting and aftercare - Wolffsohn, JS; Naroo, SA; Christie, C; Morris, J; Conway, R; Maldonado-Codina, C; Retalic, N; Purslow, C; BUCCLE (CONTACT LENS & ANTERIOR EYE, 2015)
Aim: To appraise history and symptom taking for contact lens consultations, to determine current practice and to make recommendations for best practice. Method: The peer reviewed academic literature was reviewed and the results informed a survey completed by 256 eye care practitioners (ECPs) on their current practice and influences. Results: The last eye-test date, last contact lens aftercare (for existing wearers) and reason for visit are key questions for most ECPs. Detailed use of contact lens questions are more commonly applied in aftercares than when refitting patients who have previously discontinued wear (87% vs 56% use), whereas questions on ocular and general history, medication and lifestyle were generally more commonly utilised for new patients than in aftercares (72% vs 50%). 75% of ECPs requested patients bring a list of their medication to appointments. Differential diagnosis questioning was thorough in most ECPs (87% of relevant questions asked). Attempts to optimise compliance included oral instruction (95% always) and written patient instructions (95% at least sometimes). Abbreviations were used by 39% of respondents (26% used ones provided by a professional body). Conclusion: There is scope for more consistency in history and symptom taking for contact lens consultations and recommendations are made. (C) 2015 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.

Special report: Noninvasive multi-parameter functional optical imaging of the eye - Nelson, DA; Krupsky, S; Pollack, A; Aloni, E; Belkin, M; Vanzetta, I; Rosner, M; Grinvald, A (OPHTHALMIC SURGERY LASERS & IMAGING, 2005)
Advancement in the treatment of blindness depends on the development of new technologies that enable early detection, follow-up, and treatment of disease. The authors describe direct, noninvasive imaging of four parameters: blood flow, blood oximetry, metabolic state, and hidden vasculature, particularly capillaries. These are functional parameters of the retina known to be degraded by retinal disease. The new Retinal Function Imager (Optical Imaging, Ltd., Rehovot, Israel) can image all four parameters as intrinsic reflectance intensity differences over the retina's surface. During, the past 2 decades, imaging of small optical signals has been a powerful tool for high-resolution functional mapping in the neocortex. In this article : this technology is applied to the retina and demonstrates a general tool for noninvasively probing retinal function in many modalities. Imaging functional changes before anatomic consequences arise holds promise as a powerful tool for early diagnosis and treatment of retinal disease.

Pseudoexfoliation syndrome and secondary cataract - Kuchle, M; Amberg, A; Martus, P; Nguyen, NX; Naumann, GOH (BRITISH JOURNAL OF OPHTHALMOLOGY, 1997)
Aim/background-The pseudoexfoliation (PEX) syndrome is frequently associated with impairment of the blood-aqueous barrier. This study analysed if this might stimulate secondary cataract following cataract extraction. Methods-This historical cohort study included 197 eyes of 197 patients (99 with and 98 without PEX) that underwent extracapsular cataract extraction with posterior chamber lens implantation (PMMA optic) between 1985 and 1991. Secondary cataract was defined as opacification of the axial posterior capsule and decrease of visual acuity by two or more lines. Mean follow up was 23.8 months. For statistical analysis, the Kaplan-Meier method and multivariate Cox regression analysis were used. Results-Secondary cataract was observed within 24 months in 35% (SD 7%) of all eyes, and was significantly more frequent in eyes with PEX (45 (11)%) than in eyes without PEX (24 (9)%, p<0.03). Eyes with diabetes mellitus (n=32) showed a significantly lower frequency of secondary cataract (11 (11)%) than eyes without diabetes mellitus (39 (8)%, p<0.01). The influences of sex, open angle glaucoma, type of cataract, surgeon, positioning of IOL, and phacoemulsification versus nuclear expression on secondary cataract did not reach statistical significance. Conclusion-The higher frequency of secondary cataract could be considered as another potential complication of cataract surgery in eyes with PEX.

INFLUENCE OF SILICONE OIL ON IRIS MICROANGIOPATHY IN DIABETIC VITRECTOMIZED EYES - AZZOLINI, C; BRANCATO, R; CAMESASCA, FI; CODENOTTI, M (OPHTHALMOLOGY, 1993)
Purpose: This study evaluates the influence of intraocular silicone oil on iris diabetic microangiopathy in diabetic vitrectomized eyes. Methods: The authors examined 20 eyes of 20 patients with diabetes undergoing primary vitrectomy for tractional diabetic retinal detachment, endophotocoagulation, and 1000 centistokes silicone oil tamponade. The vascular status of the iris in these eyes was examined by iris fluorescein angiography once before silicone oil injection and again when it was removed (mean follow-up, 8.3 months). Results: Iris diabetic microangiopathy, including breakdown of the blood-iris barrier and iris neovascularization, improved or remained stable in 40% of eyes. It worsened in 60% bf eyes, including all aphakic eyes. Neovascular glaucoma developed in one of them. A significant correlation was found between worsening of iris diabetic microangiopathy and both aphakia (P = 0.01) and severe immediate postvitrectomy inflammation (P = 0.02). Eyes with recurrent retinal detachment (n = 4) showed worsening of iris diabetic microangiopathy, but this was not significantly correlated. Conclusion: Aphakic vitrectomized eyes have a higher risk of iris diabetic microangiopathy developing, even after silicone oil tamponade. Immediate postoperative intraocular inflammation also is a risk factor for worsening of iris diabetic microangiopathy in phakic eyes. Recurrence of retinal detachment was not significantly correlated with worsening of iris status.

Intermediate Results of iStent or iStent inject Implantation Combined with Cataract Surgery in a Real-World Setting: A Longitudinal Retrospective Study - Guedes, RAP; Gravina, DM; Lake, JC; Guedes, VMP; Chaoubah, A (OPHTHALMOLOGY AND THERAPY, 2019)
IntroductionIn this real-world, retrospective, comparative study we evaluated 6-month performance and safety in consecutive eyes following implantation of the iStent (R) or iStent inject (R) trabecular micro-bypass device with concomitant cataract surgery.MethodsPerformance outcomes included intraocular pressure (IOP) reduction; glaucoma medication reduction; proportions of eyes achieving an IOP of<18,<16,<14, or<12mmHg; and proportions of eyes on 0, 1, 2, or3 medications. Safety outcomes included adverse events, secondary surgeries, and best-corrected visual acuity (BCVA).ResultsA totalof 73 eyes with open-angle glaucoma and cataract wereincluded in the study; of these, 38 eyes were implanted with the iStent device and 35 were implanted with the iStent inject device. The two groups of patients had similar baseline characteristics, with the exception of mean age and medication burden (both higher in patients receiving the iStent inject device); over 90% of eyes in both groups had early glaucoma. At 6months after surgery, mean IOP had fallen from 16.53.9 to 13.92.3mmHg in eyes with the iStent implant (p<0.001), and from 17.3 +/- 3.0 to 12.7 +/- 1.8mmHg in those with the iStent inject implant (p<0.001). This reduction was significantly greater in the iStent inject eyes than in the iStent eyes (26.6 vs. 15.8%) (p=0.005). Significantly more eyes receiving the iStent inject device compared to the iStent device achieved an IOP of<18mmHg at 6months post surgery (100 vs. 86.8%) (p=0.033). Average medication usage was reduced from 1.8 to 0.4 medications in iStent eyes (p<0.001) and from 2.3 to 0.4 medications in iStent inject eyes (p<0.001). Over 70% of eyes in both groups became medication-free by 6months post implantation. Adverse events in iStenteyes were mild and resulted in no sequelae; two iStent eyes underwent non-penetrating deep sclerectomy during follow-up. No complications or secondary surgeries were noted in iStent inject eyes. All eyes in both groups maintained or showed improved BCVA versus baseline.Conclusion p id=Par4 Significant and safe IOP and medication reductions were observed after iStent or iStent inject implantation withconcomitant cataract surgery. Trends toward greater effectiveness and fewer adverse events were observed with the iStent inject device compared with the iStent device.

Headaches and Vasculitis - Younger, DS (NEUROLOGIC CLINICS, 2014)
Vasculitis is a spectrum of clinicopathologic disorders defined by inflammation of arteries of veins of varying caliber with variable tissue injury. Headache may be an important clue to vasculitic involvement of central nervous system (CNS) vessels. CNS vasculitis may be primary, in which only intracranial vessels are involved in the inflammatory process, or secondary to another known disorder with overlapping systemic involvement. A suspicion of vasculitis based on the history, clinical examination, or laboratory studies warrants prompt evaluation and treatment to forestall progression and avert cerebral ischemia or infarction.

Minimally Invasive Surgery, Implantable Sensors, and Personalized Therapies - Gillmann, K; Mansouri, K (JOURNAL OF OPHTHALMIC & VISION RESEARCH, 2020)
Glaucoma management has changed dramatically over the last decades, through clinical advances and technological revolutions. This review discusses the latest innovations and challenges faced in the field around three major axes: minimally-invasive glaucoma surgery (MIGS), implantable sensors and injectable therapeutics. Indeed, the vast number of recently developed MIGS techniques has not only provided clinicians with a wide range of therapeutic options, but they have also enabled them to adjust their therapies more finely which may have contributed a more patient-centric decision-making process. Yet, despite considerable advances in the field, the wide heterogeneity in clinical trial designs blurs the surgical outcomes, specificities and indications. Thus, more high-quality data are required to make the choice of a specific MIGS procedure more than an educated guess. Beyond the scope of MIGS, the potential of IOP telemetry for self-assessment of IOP-control through implantable sensors is developing into a real option for clinicians and an empowering opportunity for patients. Indeed, providing patients with direct feedback enables them to take control and have a clearer representation of their care, in turn leading to a better control of the disease. However, there are potential issues with self-monitoring of IOP, such as increased anxiety levels induced by measured IOP fluctuations and peaks, leading to patients self-treating during IOP spikes and additional office visits. Furthermore, the advent of implantable therapeutics may soon provide yet another step towards personalized glaucoma treatment, by offering not only an efficient alternative to current treatments, but also a therapeutic option that may better adapt to patients' lifestyle. After several decades of relative stagnation through the last century, glaucoma has now entered what many view as a golden age for the specialty. Like every revolution, this one brings its fair share of uncertainty, clinical questioning and uneasy periods of adaptation to ever-changing expectations. Yet, while it is impossible to guess what the landscape of glaucoma surgery will be like in ten or fifteen years, data suggest a bright outlook both for patients and clinicians.

Foveal thickness after phacoemulsification in patients with pseudoexfoliation syndrome, pseudoexfoliation glaucoma, or primary open-angle glaucoma - Yuksel, N; Dogu, B; Karabas, VL; Caglar, Y (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2008)
PURPOSE: To use optical coherence tomography (OCT) to assess changes in foveal thickness after uneventful phacoemulsification in eyes with pseudoexfoliation syndrome (PXF), pseudoexfoliation glaucoma (PXG), or primary open-angle glaucoma (POAG). SETTING: Department of Ophthalmology, University of Kocaeli, Kocaeli, Turkey. METHODS: This prospective observational case series comprised 87 eyes (87 patients) that had phacoemulsification. Thirty-three were control eyes with cataract and no ocular disease, 15 eyes had POAG, 22 eyes had PXF, and 17 eyes had PXG. Foveal thickness was measured by OCT preoperatively and 1, 2, 4, and 8 weeks postoperatively. Intraocular pressure was recorded preoperatively and 8 weeks postoperatively. RESULTS: In all groups, the mean foveal thickness was statistically significantly greater at all postoperative visits than preoperatively. The mean change in foveal thickness was higher in the POAG group than in the PXF and control groups at 2 and 8 weeks. The mean increase in foveal thickness was greater in the PXG group than in the control group and the PXF group at 2 and 4 weeks. Three patients (1 patient in each group except PXF) developed clinically significant cystoid macular edema (CME); the incidence of CME was not statistically significant. CONCLUSION: Foveal thickness measured by OCT increased in patients with POAG and PXG and was higher than in the control group and the PXF group after uneventful phacoemulsification.

Cochlear implant in Cogan's syndrome - Vishwakarma, R; Shawn, TJ (EUROPEAN ARCHIVES OF OTO-RHINO-LARYNGOLOGY, 2007)
Post-lingual deafness is a stressful condition which is rendered even more painful by the sudden emotional isolation that the patient suffers. Cogan's syndrome is a rare autoimmune cause for post-lingual deafness characterized by non-syphilitic interstitial keratitis, bilateral audio vestibular deficiencies and systemic vasculitis. World over very few cases of Cogan's syndrome have been reported. Cochlear implant surgery in such a patient is a challenging but highly satisfactory experience due to the multitude of clinical problems the patient faces. This demands a proper work up, meticulous surgery and stringent post-operative follow-up. Here we present a patient with atypical Cogan's syndrome, diabetes mellitus and hypothyroidism. She went into a major depression with suicidal tendency following the complete loss of hearing. We performed cochlear implant surgery in this patient, but not before facing several clinical obstacles, helped by a dedicated team consisting of a rheumatologist, endocrinologist, neurophysician, psychiatrist, anaesthetists and audiologist. The results are extremely satisfying for the patient and all the people involved. This case underlines the prime importance of hearing in maintaining the psychological well being of a human being.

Infection immunology in silicone hydrogel contact lenses for continuous wear - A review - Bialasiewicz, AA (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2003)
Background: The patient's wish for permanent refractive solution and optimal comfort must be weighed against the risk of infections. In order to meet these wishes and the demand for minimising associated risks, hyperoxygen-transmissible silicone hydrogel contact lenses have been developed. Methods: Colonisation and sensitivity to antibiotics of bacteria in vitro, expression of bacterial ligands of the corneal epithelium (rabbit model), and the morphology of complications in patients have been reported to characterise HOTL. Results: Bacterial adherence to hydrophobic silicone elastomers is low. The reduction of sensitivity towards antibiotics is higher for PMMA-adherent bacteria with respect to the conventional antibiotics compared to the silicone-elastomer adherent bacteria. Colonising bacteria are not significantly different in asymptomatic CL wearers concerning CFU and species: asymptomatic: CNS (54 vs. 47%), propioni- (43 vs. 48%), coryne- (6 vs. 10%) and gram-negative bacteria (2 vs. 3%), S. aureus (2 vs. 1%), and in patients with keratitis are not significantly different concerning species: CLARE (H. influenzae, S. pneumoniae), CLPU (S. aureus, S. pneumoniae), IK (P. aeruginosa), however, concerning the CFU (gram-negative) 23.7% (keratitis) vs. 3.8%, (asymptomatic), S. pneumoniae 7.6% vs. 0.6%. The epithelial expression of bacterial ligands like WGA is lower for HOTL (3230 p/750 mu) than for low oxygen-transmissible (4611 p/750 mu) consistent with a decreased adherence of pseudomonas of 5.31-5.98 vs. 5.9-7.81 bacteria/cell. Asymptomatic morphological anomalies and keratitis are less frequent in HOTL. Apoptosis-induced desquamation and the central epithelial thickness decreased. In a one-year study of 504 patients wearing continuous wear HOTL for 30 days, corneal staining was seen in 10.6 vs. 10.5% 30-day 7 day extended wear, infiltrates in 2.3 vs. 4.6%, epithelial oedema in 3.6 vs. 2.0% und tarsal conjunctival anomalies in 3.0 vs. 1.6%. Individual reports on infectious keratitis in HOTL wearers have been published. Conclusions: Fewer morphological anomalies and a decreased incidence of infections (on the basis of duration of wear) can be associated with the higher oxygen transmission of HOTL. From the clinical point of view, colonisation of HOTL with the same bacterial species as in conventional biomaterials, and the extended wear demand clear patient counseling and vigilant follow-up by an ophthalmologist.

Phthisis Bulbi-a Clinicopathological Perspective - Tripathy, K; Chawla, R; Temkar, S; Sagar, P; Kashyap, S; Pushker, N; Sharma, YR (SEMINARS IN OPHTHALMOLOGY, 2018)
Phthisis bulbi denotes end-stage eye disease characterized by shrinkage and disorganization of the eye with the resultant functional loss. The major factors associated with the pathogenesis of phthisis are hypotony, deranged blood-ocular barriers, and inflammation. Common causes include trauma, surgery, infection, inflammation, malignancy, retinal detachment, and vascular lesions. A phthisical globe shows a small squared off shape, opaque and thickened cornea, thickened sclera, neovascularization of iris, cataract, cyclitic membrane, ciliochoroidal detachment, and retinal detachment. Microscopic features include internal disorganization, inflammatory reaction, a reactive proliferation of various cells, calcification, and ossification. Early treatment of the causative etiology is the best strategy available to avoid an eye from going into phthisis. A phthisical eye has no visual potential and cosmetic rehabilitation or symptomatic relief of pain remains the mainstay in the management. The authors present a comprehensive review of the etiopathogenesis, pathology, clinical features, and management of the end-stage ocular disease.

Glaucoma case finding: a cluster-randomised intervention trial - Theodossiades, J; Murdoch, I; Cousens, S (EYE, 2004)
Purpose To assess the effect of an intervention comprising training in optic disc assessment, explicit referral criteria and ophthalmologist feedback on referred patients, on the number of optometrist referrals for suspected glaucoma seen at a referral site and the positive predictive value of those referrals. Methods Optometric practices routinely referring to the Ealing Hospital Eye Clinic were randomly divided into two groups taking into consideration those practices, which shared an optometrist ( a cluster) and the number of optometrist days worked per week. One group of practices acted as controls, while the other practices were invited to receive the intervention. Data on 397 new patients referred and presenting to Ealing Hospital with suspected glaucoma were collected over a 20-month period. The data on patients who had failed to attend their appointment were collected over 7 months of this period. The number of referrals seen, the positive predictive value of those referrals, and the attendance rate were calculated. Optometrist's opinions of the intervention were assessed qualitatively. Data relating to optometrist compliance with the intervention were also collected. Results The number of glaucoma referrals presenting to Ealing Hospital from the intervention practices was almost double that from the control practices ( 210 vs 119). When cluster randomisation, the number of optometrist days per cluster and the number of assessed referrals in the preintervention period are taken into consideration, it is estimated that the intervention is associated with a 52% increase in the number of referrals reaching Ealing Hospital. However, the design effect resulting from the cluster randomisation was unexpectedly high ( of the order of 13 - 14) and so the confidence intervals around the estimate of 52% are very wide (95% c. i. 35% decrease to 253% increase, P = 0.34). There was no evidence of an association between optometrist compliance with the intervention and the number of referrals seen at Ealing Hospital. The positive predictive value (PPV) of referrals was similar for the intervention (0.49 ( 95% c. i. 0.42, 0.55)) and control groups (0.46 ( 95% c. i. 0.33, 0.60)). Optometrist opinions of the intervention were largely favourable. All expressed a willingness to participate in future programmes. Conclusion A large difference in the number of referrals between the practice groups was observed. Since the PPV of referral was unchanged, the potential impact of the intervention in terms of numbers of new cases of glaucoma detected in the community is substantial. However, because of its large design effect, this trial does not provide conclusive evidence of an impact of the intervention on referral numbers. A considerably larger trial will be required to produce conclusive evidence of an effect.

Increase of endothelin-1 concentration in aqueous humour induced by argon laser trabeculoplasty in the rabbit. A preliminary study - Hollo, G; Lakatos, P (ACTA OPHTHALMOLOGICA SCANDINAVICA, 1998)
Purpose: To investigate the impact of argon laser trabeculoplasty (ALT) on endothelin-1 (ET-1) concentration of aqueous humour and intraocular pressure (IOP) in the rabbit. Methods: Standard ALT was performed on one eye of 19 pigmented rabbits. A modified treatment in which the laser light was focused on the inner limbal surface (argon laser scleroplasty, ALS) was also performed on one eye of a further 15 rabbits. IOP was measured with a Tono-Pen-2 tonometer before treatment, under general anaesthesia, Post-laser IOP measurements followed by aqueous humour aspiration were performed under general anaesthesia 4, 24 and 120 hours after treatment. IOP readings were considered relative values, since the tonometer was calibrated to the human eye and not to the rabbit eyeball. Different groups of animals were used for the tests after each time period. The groups of 4 hours time consisted of 9 animals which had undergone ALT and 5 which had undergone ALS, All the other groups consisted of 5 animals each, Results: In the ALT group IOP decreased following treatment, and the IOP change (a relative change) showed a significant difference between the treated and the control eyes at all three follow-up times (paired t-test, p<0.05), and a significant interaction was found between treatment and follow-up time (ANOVA, p<0.05), Concentration of ET-1 in the aqueous humour of the treated eyes increased by about an order of magnitude 4 hours after ALT, compared to the contralateral control eyes (103.66 +/- 41.59 pg /ml versus 8.75 +/- 2.95 pg/ml, Wilcoxon matched pairs test, p<0.01), ET-1 concentration 24 and 120 hours after ALT, however, did not differ significantly from the corresponding contralateral control values. In the ALS group neither IOP change nor aqueous humour ET-1 concentration differed in a statistically significant manner between the treated and control eves, Conclusions: The results suggest that ALT is followed by an immediate and short-term increase of aqueous humour ET-1 concentration in the rabbit, probably due to leakage from the uveal tissue.

Pattern of Ocular Morbidity in the Elderly Population of Northern India - Baldev, VF; Chopra, R; Batra, N; Singh, S (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2017)
Introduction: The frequency of eye diseases has been suggested to start increasing around 40 years of age, with an even steeper increase beginning around 60 years of age. Health promotions and curative and rehabilitative services for the visually impaired elderly population should therefore be a priority in the coming years especially in low and middle income countries. Aim: To examine the changing pattern of ocular morbidity in the elderly population of Northern India and to determine the socioeconomic status in relation to ocular morbidities. Materials and Methods: A team from the Department of Ophthalmology and Department of Community Medicine, conducted house visits and did a complete eye examination of 450 elderly subjects. They were selected by systematic random sampling from the data base available in the Department of Community Medicine. Results: A total of 900 eyes were examined. Visual impairment and blindness was seen in 135 (30%) and 36 (8%) individuals respectively. The most common cause of blindness was cataract, followed by corneal opacity, glaucoma, refractive error, diabetic retinopathy, macular scar, age related macular degeneration, retinal detachment, retinitis pigmentosa. Visual impairment was more in individuals with low socioeconomic status. Conclusion: The results of this study suggest that though cataract remains the main cause of blindness, there is an increase in blindness and visual impairment due to corneal diseases and glaucoma which was not seen earlier. The availability and accessibility to eye care facilities particularly for corneal diseases and glaucoma should be increased to reduce blindness in Northern India.

Ocular Antihypertensive Medication Use After iStent Implantation Concurrent With Cataract Surgery vs Cataract Surgery Alone in a Large US Health Care Claims Database - Wang, SY; Singh, K; Stein, JD; Chang, RT (JAMA OPHTHALMOLOGY, 2019)
IMPORTANCE The iStent Trabecular Micro-Bypass (Glaukos Corporation) is a minimally invasive glaucoma implant used in conjunction with cataract surgery to lower intraocular pressure. OBJECTIVE To determine whether implantation of the iStent concurrent with cataract surgery is associated with reduced use of ocular antihypertensive medications in a US health care claims database. DESIGN, SETTING, AND PARTICIPANTS Retrospective, observational longitudinal cohort study of individuals enrolled in a US managed care network who underwent iStent implantation with cataract surgery (iStent/CEIOL) from 2012 to 2016 (n = 1509 bilateral and n = 1462 unilateral surgery). A control group of individuals who underwent bilateral cataract surgery only (CEIOL) were matched 1:1 to patients undergoing bilateral iStent/CEIOL on baseline demographic and clinical factors. Data were analyzed between November 1, 2017, and January 31, 2018. MAIN OUTCOMES AND MEASURES The number of topical ocular antihypertensive agents used postoperatively by patients undergoing iStent/CEIOL compared with baseline and with matched CEIOL control individuals, and hazard ratios with 95% confidence intervals for sustained reduced use of at least 1 topical ocular antihypertensive agent postoperatively. RESULTS Of the 2971 eligible enrollees, mean age at first surgery was 74.3 years, and 1659 (55.8%) were women. Patients undergoing iStent/CEIOL had diagnoses that included primary open-angle glaucoma (n = 2329; 78.4%), narrow angles (n = 381; 12.8%), and secondary glaucomas (n = 261; 8.8%). At baseline, 1223 (41.2%) were receiving no topical glaucoma agents; 876 (29.5%), 437 (14.7%), and 435 (14.6%) were receiving 1, 2, or at least 3 agents, respectively. Although only 678 persons (22.8%) completed at least 2 years of postoperative follow-up, the proportion of patients receiving no drops increased postoperatively (64.7%, 20-24 months, P < .001, chi(2)). Patients receiving at least 1 topical agent at baseline had mean reduction of 1.01 and 0.61 medications used at 20 to 24 months with bilateral or unilateral surgery, respectively (both P < .001, paired t). Sustained reduction in glaucoma medication use was more likely in patients receiving at least 3 vs 1 medication at baseline (hazard ratio, 1.68; 95% CI, 1.36-2.09). Compared with matched control individuals undergoing CEIOL, patients undergoing bilateral iStent/CEIOL had a greater mean reduction in drops used (0.99 vs 0.49; postoperative month 20-24; P < .001; paired t) and a higher proportion receiving no drops postoperatively (73.5% vs 55.3%, postoperative month 20-24; P < .001; chi(2)). CONCLUSIONS AND RELEVANCE Implantation of the iStent trabecular micro-bypass stent concurrent with cataract surgery was associated with moderately reduced use of topical ocular antihypertensive medication. Reduction in the use of glaucoma medications may lessen the burden of medication adverse effects and promote better adherence.

Combined anterior and posterior segment injuries in children: a review - Meier, P (GRAEFES ARCHIVE FOR CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2010)
Combined anterior and posterior segment injuries in children require special attention to the unique characteristics of children's eyes, including a pronounced tendency to scar formation and proliferation, adherence of the posterior vitreous, as well as the danger of amblyopia. This article reviews the current body of literature documenting the main aspects of surgical management, complications, and prognosis of combined anterior and posterior segment injuries in children. For optimal treatment success, special strategies are necessary with regard to: 1) comprehensive secondary operation for internal reconstruction, 2) encircling buckle surgery, 3) management of the lens, 4) use of a temporary keratoprosthesis, 5) endophthalmitis, and 6) late complications, e.g., secondary glaucoma, secondary strabismus, leukoma cornea, and phthisis bulbi. Further crucial prognostic factors were analyzed. Combined anterior and posterior segment injuries in children require optimal surgical treatment management that varies from adult treatment with regard to several essential aspects. Care should be provided by pediatric ophthalmology specialists with orthoptic follow-up as necessary, over many years.

Effects of one-week versus one-day preoperative treatment with topical 1% prednisolone acetate in dogs undergoing phacoemulsification - McLean, NJ; Ward, DA; Hendrix, DVH; Vaughn, RK (JAVMA-JOURNAL OF THE AMERICAN VETERINARY MEDICAL ASSOCIATION, 2012)
Objective-To compare the effects of 2 preoperative anti-inflammatory regimens on intraocular inflammation following phacoemulsification. Design-Randomized controlled trial Animals-21 dogs with immature cataracts. Procedures-All dogs had cataract surgery via phacoemulsification, and most received prosthetic intraocular lenses. Dogs were randomly divided into 2 groups. Group A dogs were treated topically with prednisolone acetate for 7 days prior to surgery, whereas prednisolone acetate treatment commenced the evening prior to surgery in group B dogs. Postoperative care was identical for both groups. Blood-aqueous barrier breakdown was quantified by use of anterior chamber fluorophotometry, with fluorescein entry into the anterior chamber measured 2 and 9 days after surgery compared with baseline scans obtained prior to surgery. Ophthalmic examinations were performed before surgery and 1 day, 9 days, 3 weeks, 7 weeks, 3 months, and 6 months after surgery. A subjective inflammation score was established at each examination. Intraocular pressures were measured 4 and 8 hours after surgery and at each follow-up examination. Results-There was no difference in the extent of blood-aqueous barrier disruption between the groups at 2 or 9 days after surgery. Subjective inflammation scores were also similar at most time points. Dogs in group A developed postoperative ocular hypertension at a higher frequency (60%) than did those in group B (18%). Conclusions and Clinical Relevance-In dogs that underwent cataract surgery via phacoemulsification, a full week of topical prednisolone acetate treatment prior to surgery did not decrease postoperative inflammation, compared with commencement of topical prednisolone acetate treatment the evening prior to surgery, and was associated with a greater incidence of postoperative ocular hypertension. (J Am Vet Med Assoc 2012;240:563-569)

Surgical management of epiretinal membrane in young patients - Benhamou, N; Massin, P; Spolaore, R; Paques, M; Gaudric, A (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2002)
Purpose: To report the outcome of epiretinal membrane (ERM) surgery in young patients. Design: Interventional case series study. Method: A retrospective review of 20 young patients who had undergone vitrectomy and epiretinal membrane removal. All patients had a preoperative examination, including fundus biomicroscopy, red free photographs, and fluorescein angiography. Results: Nine patients were males and 11 females (age: 7-26 years; mean: 16.3 years). Follow up ranged from 4-96 months (mean: 21.2 months). The 20 patients comprised 13 cases of idiopathic ERM, six cases in which ERM was associated with ocular inflammation and one case of combined hamartoma of the retina and retinal pigment epithelium (RPE). In 13 cases, the ERM was especially white, thick, and opaque, with localized constriction and severe retinal distortion. Final best,corrected visual acuity (VA) was significantly better than preoperatively (20/50 vs. 20/112), (P=0.0002). Mean improvement in VA was 4.25 lines and 17 patients gained two or more lines. This improvement was better in secondary than idiopathic ERM (6 lines vs. 3.3). During follow up, five cases of recurrence were observed (25%). In another case, postoperative persistent ocular hypertension required filtering surgery. Conclusion: The characteristics of ERM. in young patients are quite different in many cases from those in adults in terms of thickness and adherence. Removal of ERM in young patients is feasible and safe although the membrane may focally adhere strongly to retinal vessels. VA usually improves significantly after surgery, but recurrences are more frequent than in adults. (Am J Ophthalmol 2002;133:358-364. (C) 2002 by Elsevier Science Inc. All rights reserved.).

Giant Anterior Staphyloma After Bomb Explosion - Hassan, IA; Keinan, IA; Kadiye, MS; Kalayci, M (ISTANBUL MEDICAL JOURNAL, 2021)
A 64-year-old male patient was admitted to our clinic complaining of pain in his left eye. Three years ago, the patient was hit in the left eye by a metal object during an in-car bomb explosion. The patient had a giant anterior staphyloma in his left eye that prevented the eyelids from closing. In the shiotz tonometer measurement, the left intraocular pressure was 26 mmHg. In computed tomography, the distance between the staphyloma endpoint and the lens was 7.17 mm. After open glob trauma, patients should be checked at short intervals for regular follow-up for ocular surface infections. The ophthalmologist responsible for the patient should regularly assess the patient's compliance with the drug and the eye's response to the drug. Early surgery should be applied if necessary to prevent staphyloma and similar eye complications.

Intraocular Pressure Control with Latanoprost/Timolol and Travoprost/Timolol Fixed Combinations A Retrospective, Multicentre, Cross-Sectional Study - Denis, P; Lafuma, A; Jeanbat, V; Laurendeau, C; Berdeaux, G (CLINICAL DRUG INVESTIGATION, 2008)
Objective: The aim of this study was to confirm randomized clinical trial results showing that a fixed timolol/travoprost combination (TT; DuoTrav (R)) controls intraocular pressure (IOP) better than a fixed timolol/latanoprost combination (TL; Xalacom (R)) in everyday ophthalmic practice, when measured in the morning and >24 hours after instillation. Methods: Patients with ocular hypertension or primary open angle glaucoma stabilized on TT or TL were included in this retrospective cross-sectional study. Data on demographics, medical history and previous treatments were extracted from the patients' medical records. Last treatment instillation times and IOP values were recorded at clinic visits. Treatments were compared by analyses of variance, logistic regressions and propensity scores adjusted for confounding factors. Results: Out of 316 patients included, 124 instilled TT, 192 instilled TL and 266 (84.2%) overall had instilled their eye drops within 24 hours. The patients' mean age was 64.5 years and 51.6% were female. Treatment groups were comparable except for longer disease and treatment durations in TL recipients. Worse eye mean IOPs were 25.8 mmHg at diagnosis and 21.9 mmHg on starting their designated fixed combination treatment. The best IOP control was provided by Tr instillations (mean IOP 17.1 and 19.0 mmHg in the Tr and TL groups, respectively; p < 0.001). This difference was reinforced by results in the subgroup of patients who instilled treatment >24 hours prior to IOP measurement (mean IOP 17.0 and 20.3 mmHg in the TT and TL groups, respectively; p < 0.004). Also, 82.6% of TT patients satisfied their ophthalmologists' IOP targets versus 51.1% of TL patients (p < 0.001). All significant differences persisted after adjustment for confounding factors. Conclusion: This study, conducted in routine ophthalmic practice, confirmed published clinical trial results showing that TT provides better IOP control than TL when measured in the morning, and that travoprost has longer-lasting residual effects than latanoprost when IOP is measured >24 hours after instillation. However, readers should interpret these findings in the context of a cross-sectional observational study conducted in a naturalistic setting.

Unilateral Acanthamoeba Keratitis following the Use of Cosmetic Contact Lens - Agab, AW; Albuainain, AR; Al Bin Ali, G (BAHRAIN MEDICAL BULLETIN, 2017)
Colored lenses were first designed for patients with eye pathologies, such as aniridia or corneal opacity. However, in recent years they have become readily available over-the-counter as cosmetic accessories. Widespread use of these lenses has been noted among young adults. Acanthamoeba keratitis is a rare cause of corneal infection, which is associated with poor visual prognosis. Over the past ten years, improvements in the management of this infection have been documented, yet the best treatment is still primary prevention. Hence, contact lens wearers must be provided with proper instructions regarding contact lens hygiene. We present a case of unilateral Acanthamoeba keratitis in a cosmetic contact lens wearer who presented with a month history of right eye pain, photophobia, redness and blurred vision. The contact lenses were obtained over the counter, and a history of poor contact lens hygiene was found. The patient was started on empirical treatment initially. The treatment was modified once the diagnosis was confirmed via Giemsa Stain of corneal scrapings, which showed Acanthamoeba cysts. The patient improved markedly and was discharged from the hospital. The disease classically has a slowly progressive, chronic course, with frequent remission periods. Our patient was lost to follow-up due to poor compliance and failure to adhere to guidelines.

Vision Loss in Older Adults - Pelletier, AL; Rojas-Roldan, L; Coffin, J (AMERICAN FAMILY PHYSICIAN, 2016)
Vision loss affects 37 million Americans older than 50 years and one in four who are older than 80 years. The U.S. Preventive Services Task Force concludes that current evidence is insufficient to assess the balance of benefits and harms of screening for impaired visual acuity in adults older than 65 years. However, family physicians play a critical role in identifying persons who are at risk of vision loss, counseling patients, and referring patients for disease-specific treatment. The conditions that cause most cases of vision loss in older patients are age-related macular degeneration, glaucoma, ocular complications of diabetes mellitus, and age-related cataracts. Vitamin supplements can delay the progression of age-related macular degeneration. Intravitreal injection of a vascular endothelial growth factor inhibitor can preserve vision in the neovascular form of macular degeneration. Medicated eye drops reduce intraocular pressure and can delay the progression of vision loss in patients with glincoma, but adherence to treatment is poor. Laser trabeculoplasty also lowers intraocular pressure and preserves vision in patients with primary open-angle glaucoma, but long-term studies are needed to identify who is most likely to benefit from surgery. Tight glycemic control in adults with diabetes slows the progression of diabetic retinopathy, but must be balanced against the risks of hypoglycemia and death in older adults. Fenofibrate also slows progression of diabetic retinopathy. Panretinal photocoagulation is the mainstay of treatment for diabetic retinopathy, whereas vascular endothelial growth factor inhibitors slow vision loss resulting from diabetic macular edema. Preoperative testing before cataract surgery does not improve outcomes and is not recommended. Copyright (C) 2016 American Academy of Family Physicians.

Regular Examinations for Toxic Maculopathy in Long-term Chloroquine or Hydroxychloroquine Users - Nika, M; Blachley, TS; Edwards, P; Lee, PP; Stein, JD (JAMA OPHTHALMOLOGY, 2014)
IMPORTANCE According to evidence-based, expert recommendations, long-term users of chloroquine or hydroxychloroquine sulfate should undergo regular visits to eye care providers and diagnostic testing to check for maculopathy. OBJECTIVE To determine whether patients with rheumatoid arthritis (RA) or systemic lupus erythematosus (SLE) taking chloroquine or hydroxychloroquine are regularly visiting eye care providers and being screened for maculopathy. DESIGN, SETTING, AND PARTICIPANTS Patients with RA or SLE who were continuously enrolled in a particular managed care network for at least 5 years between January 1, 2001, and December 31, 2011, were studied. Patients' amount of chloroquine or hydroxychloroquine use in the 5 years since the initial RA or SLE diagnosis was calculated, along with their number of eye care visits and diagnostic tests for maculopathy. Those at high risk for maculopathy were identified. Logistic regression was performed to assess potential factors associated with regular eye care visits (annual visits in >= 3 of 5 years) among chloroquine or hydroxychloroquine users, including those at highest risk for maculopathy. MAIN OUTCOMES AND MEASURES Among chloroquine or hydroxychloroquine users and those at high risk for toxic maculopathy, the proportions with regular eye care visits and diagnostic testing, as well as the likelihood of regular eye care visits. RESULTS Among 18 051 beneficiaries with RA or SLE, 6339 (35.1%) had at least 1 record of chloroquine or hydroxychloroquine use, and 1409 (7.8%) had used chloroquine or hydroxychloroquine for at least 4 years. Among those at high risk for maculopathy, 27.9% lacked regular eye care visits, 6.1% had no visits to eye care providers, and 34.5% had no diagnostic testing for maculopathy during the 5-year period. Among high-risk patients, each additional month of chloroquine or hydroxychloroquine use was associated with a 2.0% increased likelihood of regular eye care (adjusted odds ratio, 1.02; 95% CI, 1.01-1.03). High-risk patients whose SLE or RA was managed by rheumatologists had a 77.4% increased likelihood of regular eye care (adjusted odds ratio, 1.77; 95% CI, 1.27-2.47) relative to other patients. CONCLUSIONS AND RELEVANCE In this insured population, many patients at high risk for maculopathy associated with the use of chloroquine or hydroxychloroquine are not undergoing routine monitoring for this serious adverse effect. Future studies should explore factors contributing to suboptimal adherence to expert guidelines and the potential effect on patients' vision-related outcomes.

The Effectiveness, cost-effectiveness and acceptability of Community versus Hospital Eye Service follow-up for patients with neovascular age-related macular degeneration with quiescent disease (ECHoES): a virtual randomised balanced incomplete block triald - Reeves, BC; Scott, LJ; Taylor, J; Hogg, R; Rogers, CA; Wordsworth, S; Townsend, D; Muldrew, A; Peto, T; Violato, M; Dakin, H; Cappel-Porter, H; et al. (HEALTH TECHNOLOGY ASSESSMENT, 2016)
Background: Patients with neovascular age-related macular degeneration (nAMD) usually attend regular reviews, even when the disease is quiescent. Reviews are burdensome to health services, patients and carers. Objectives: To compare the proportion of correct lesion classifications made by community-based optometrists and ophthalmologists from vignettes of patients; to estimate the cost-effectiveness of community follow-up by optometrists compared with follow-up by ophthalmologists in the Hospital Eye Service (HES); to ascertain views of patients, their representatives, optometrists, ophthalmologists and clinical commissioners on the proposed shared care model. Design: Community-based optometrists and ophthalmologists in the HES classified lesions from vignettes comprising clinical information, colour fundus photographs and optical coherence tomography images. Participants' classifications werevalidated against experts' classifications (reference standard). Setting: Internet-based application. Participants: Ophthalmologists had to have >= 3 years post-registration experience in ophthalmology, have passed part 1 of the Royal College of Ophthalmologists, Diploma in Ophthalmology or equivalent examination, and have experience in the age-related macular degeneration service. Optometrists had to be fully qualified, be registered with the General Optical Council for >= 3 years and not be participating in nAMD shared care. Interventions: The trial sought to emulate a conventional trial in comparing optometrists' and ophthalmologists' decision-making, but vignettes, not patients, were assessed; therefore, there were no interventions. Participants received training prior to assessing vignettes. Main outcome measures: Primary outcome-correct classification of the activity status of a lesion based on a vignette, compared with a reference standard. Secondary outcomes-frequencies of potentially sight-threatening errors, participants' judgements about specific lesion components, participant-rated confidence in their decisions and cost-effectiveness of follow-up by community-based optometrists compared with HES ophthalmologists. Results: In total, 155 participants registered for the trial; 96 (48 in each professional group) completed training and main assessments and formed the analysis population. Optometrists and ophthalmologists achieved 1702 out of 2016 (84.4%) and 1722 out of 2016 (85.4%) correct classifications, respectively [odds ratio (OR) 0.91, 95% confidence interval (CI) 0.66 to 1.25; p = 0.543]. Optometrists' decision-making was non-inferior to ophthalmologists' with respect to the pre-specified limit of 10% absolute difference (0.298 on the odds scale). Frequencies of sight-threatening errors were similar for optometrists and ophthalmologists [57/994 (5.7%) vs. 62/994 (6.2%), OR 0.93, 95% CI 0.55 to 1.57; p = 0.789]. Ophthalmologists assessed lesion components as present less often than optometrists and were more confident about their lesion classifications than optometrists. The mean care-pathway cost for assessment was very similar by group, namely 397.33 pound for ophthalmologists and 410.78 pound for optometrists. The optometrist-led monitoring reviews were slightly more costly and less effective than ophthalmologist-led reviews, although the differences were extremely small. There was consensus that optometrist-led monitoring has the potential to reduce clinical workload and be more patient-centred. However, potential barriers are ophthalmologists' perceptions of optometrists' competence, the need for clinical training, the ability of the professions to work collaboratively and the financial feasibility of shared care for Clinical Commissioning Groups. Conclusions: The ability of optometrists to make nAMD retreatment decisions from vignettes is non-inferior to that of ophthalmologists. Various barriers to implementing shared cared for nAMD were identified.

Pseudoexfoliation syndrome: pathological manifestations of relevance to intraocular surgery - Conway, RM; Schlotzer-Schrehardt, U; Kuchle, M; Naumann, GOH (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2004)
Pseudoexfoliation syndrome (PEX) is a common ocular condition often associated with the need for intraocular surgery. Although results of cataract and glaucoma filtering surgery in eyes with PEX in the early stages of the disease may be comparable to those in eyes without PEX, in the later stages morbidity is significantly increased due to periocular surgical complications and the outcome is worse. Surgical and postoperative difficulties are often multifactorial and are directly related to the pathological changes of PEX on intraocular structures. Recent years have seen a large increase in the understanding of the effects of PEX on the various ocular tissues. Although the visible areas of the anterior capsule are most obviously involved, this is only a small part of the picture and of least significance. Biomicroscopically invisible changes of the zonules and their attachments are of greatest consequence. There is also distinct, often active, involvement of almost all tissues of the anterior segment of the eye, many of which have important implications for the anterior segment surgeon including iridopathy, iris vasculopathy (including persistent breakdown of the blood-aqueous barrier and anterior segment hypoxia), ciliary body involvement and keratopathy. Trabecular dysfunction is evident by the deposition of PEX material derived from both in situ and extra-trabecular production as well as protein and melanin deposition. These changes should be kept in mind by all intraocular surgeons as a source of potential difficulties in the perioperative period. Additionally, in light of these changes, patients need to be given realistic expectations regarding the increased risk of complications and more prolonged expected recovery time. In this short review, current reports relating to PEX pathological changes of practical interest to the intraocular surgeon are summarized.

Treatment of proliferative feline eosinophilic keratitis with topical 1.5% cyclosporine: 35 cases - Spiess, AK; Sapienza, JS; Mayordomo, A (VETERINARY OPHTHALMOLOGY, 2009)
Proliferative feline eosinophilic keratitis is a chronic keratopathy caused by a suspected immune mediated response to an unknown antigenic stimulus. The purpose of this study is to demonstrate the efficacy of topical 1.5% cyclosporine solution in proliferative feline eosinophilic keratitis. Thirty-five cats were treated topically with 1.5% cyclosporine A between 1997 and 2007. Eosinophilic keratitis was diagnosed by clinical appearance and evidence of eosinophils and/or mast cells in corneal cytology. The patients were treated with topical cyclosporine (1.5%) twice (26 of 35, 74.3%) and three times (9 of 35, 25.7%) daily. The minimum period for follow-up was 5 months. The age of the patients ranged from 2 to 13 years with a mean age of 6.0 years. Twenty-two were neutered males, and 13 were females. The represented breeds were 30 DSH, 3 DLH, one Siamese and one Maine Coon. Cytologic examination of a corneal scrape revealed the presence of eosinophils in 34 of 35 specimens, and mast cells in 25 of 35 specimens. Improvement in the treated eyes was seen in 31 cats (88.6%). Four animals (11.4%) did not respond to the treatment with topical cyclosporine. Recurrences were seen in seven (22.6%) cases. Blepharitis was noted as an infrequent side effect. Based on our findings, topical cyclosporine (1.5%) is an effective treatment of proliferative feline eosinophilic keratitis in the vast majority of cases. Recurrences were mainly associated with poor owner compliance. Chronic, often lifelong therapy with medications is thus recommended.

Use of brimonidine 0.2% in treatment of glaucoma or ocular hypertony after poorly tolerated beta-blocker treatment - Titouamane, S; Baudouin, C (JOURNAL FRANCAIS D OPHTALMOLOGIE, 2002)
This study intended to evaluate the advantages of brimonidine tartrate 0.2% (Alphagan(R)), a selective alpha-2 receptor agonist, relaying a poorly tolerated beta-blocker treatment. Effectiveness, as assessed by intraocular pressure, local and general tolerance of the treatment, and the quality of life of the patients included in the study, was compared for these two eye drops. This multicenter and prospective study, performed by 450 ophthalmologists, included 807 adults presenting with glaucoma or ocular hypertony over 8 months. After a poorly tolerated beta-blocker treatment, which had started at least 6 months before, these patients received brimonidine over 8 weeks. At 3 successive visits, intraocular pressure, biomicroscopic examination results, and visual acuity were recorded. A quality-of-life questionnaire evaluating breathlessness, fatigue, depressive mood, loss of appetite, and satisfaction with the treatment was also given to patients. In the 731 patients observed in the study, the analysis concluded a statistically significant decrease in intraocular pressure (-2.5mmHg) and in the cardiovascular parameters during brimonidine treatment: blood pressure was reduced by 3mmHg and 1.1mmHg for systolic and diastolic pressure, respectively. The heart rate rose by 1.7 beats/min. The quality-of-life questionnaire revealed less breathlessness (-26%), fatigue (-24.9%), depressive mood (-19.3%), and better appetite (+8.2%). The feeling of satisfaction with the brimonidine treatment was significantly improved for 95 patients. However, 12% of all patients stopped their treatment because of adverse effects. Brimonidine improved the glaucomatous patients' quality of life, at least in some areas. Improved intraocular pressure could at least in part result from better compliance with the treatment. Brimonidine is an encouraging alternative after an unsatisfactory beta-blocker treatment.

A study of the relationship between the quality of lifestyle counselling and later adherence to the lifestyle changes based on patients with stroke and TIA - Oikarinen, A; Engblom, J; Kyngas, H; Kaariainen, M (CLINICAL REHABILITATION, 2018)
Objective: To identify associations between lifestyle counselling quality and adherence to lifestyle changes during the 12-month period after discharge. Setting: Neurology unit. Subjects: Stroke and transient ischaemic attack (TIA) patients (n = 98). Design: Longitudinal explorative study that utilized data initially collected for quasi-experimental study. Main measures: The exploratory measures of Counselling Quality were collected at the hospital on the day of discharge between January 2010 and October 2011, and the outcome measures of Adherence to Lifestyle Change and clinical values were collected 3, 6 and 12 months after discharge. Results: There were significant associations between the exploratory and outcome measures over time. Three of the counselling quality parameters, counselling interaction, advantages and resources, were found to be significantly associated with adherence to lifestyle change. In particular, counselling interactiveness was positively associated with physical activity at 3 (B = 0.31, SD = 0.10, P = 0.004) and 12 (B = 0.29, SD = 0.13, P = 0.030) months, as was advantages of following the advice at 3 (B = 0.33, SD = 0.11, P = 0.006) and 12 (B = 0.34, SD = 0.14, P = 0.021) months. Counselling resources were associated with lower body mass index throughout the entire follow-up period, that is, at 3 (B = -0.06, SD = 0.02, P = 0.006), 6 (B = -0.05, SD = 0.02, P = 0.040) and 12 months (B = -0.05, SD = 0.02, P = 0.022). Furthermore, all aspects of counselling quality were positively related to support from nurses. Conclusion: Adherence to lifestyle change is more likely to be attained if lifestyle counselling is interactive, the advantages of following the given advice are perceived as beneficial and the counsellor has sufficient resources.

Outcomes of Descemet Membrane Endothelial Keratoplasty in Bangkok, Thailand - Lekhanont, K; Pisitpayat, P; Cheewaruangroj, N; Jongkhajornpong, P; Nonpassopon, M; Anothaisintawee, T (CLINICAL OPHTHALMOLOGY, 2021)
Purpose: To investigate the medium-term clinical outcomes and risk factors for primary graft failure after Descemet membrane endothelial keratoplasty (DMEK) in Thai patients. Patients and Methods: This is a single-center retrospective cohort study. Sixty-two eyes of 62 patients who underwent DMEK at Ramathibodi Hospital, Bangkok, Thailand, with a minimum of 24-month follow-up were recruited. Preoperative donor and recipient characteristics, intraoperative data, and postoperative outcomes including best-corrected visual acuity (BCVA), graft clarity, endothelial cell density (ECD), central corneal thickness (CCT), and complications were evaluated at 1, 3, 6, 12, and 24 months after surgery. Results: The mean age of the patients was 67.2 +/- 9.9 years, and 52% were female. The mean follow-up time was 37.5 +/- 11.0 months. The most common indications for DMEK were Fuchs' endothelial corneal dystrophy (FECD) (53.2%) and pseudophakic bullous keratopathy (PBK) (17.7%). Nearly half of patients had triple-DMEK. The median preoperative BCVA was 20/400. Postoperative BCVA of >= 20/40 was reached in 37.1% and of >= 20/20 in 6.5% after 1 month which increased to 54.8% and 17.7% after 3 months; and to 67.7% and 27.4% after 24 months. Endothelial cell loss (ECL) at 3, 6, 12, and 24 months was 30.5%, 33.8%, 44.4%, and 45.9%, respectively. Graft diameter was the single factor, showing a significant relationship with postoperative ECD. Most frequent postoperative complications included graft detachment (22.6%), increased IOP/glaucoma (17.7%), and primary graft failure (16.1%). In univariate analysis, death-to-operation time and the diagnosis of PBK were significantly associated with the occurrence of primary graft failure. Conclusion: DMEK is a safe, effective, and feasible treatment for endothelial failure in Asian eyes. Careful case selection, use of relatively fresh donor tissues, and appropriate surgical techniques can prevent primary graft failure and facilitate optimal outcomes following surgery.

Descemet's stripping with endothelial keratoplasty in 200 eyes - Early challenges and techniques to enhance donor adherence - Price, FW; Price, MO (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2006)
PURPOSE: To describe early challenges and techniques to promote donor tissue adherence in Descemet's stripping with endothelial keratoplasty (DSEK). SETTING: Price Vision Group, Indianapolis, Indiana, USA. METHODS: The first 200 consecutive cases of DSEK performed by a single surgeon were analyzed retrospectively. Follow-up was 7 to 20 months for 124 eyes and 2 to 6 months for 76 eyes. The surgical technique consisted of stripping Descemet's membrane and endothelium from the recipient's central cornea and transplanting an 8.0 to 9.0 mm disc of donor endothelium and posterior stroma through a 5.0 mm incision, with sutures used only to close the incision. RESULTS: The most frequent challenge was inadequate donor attachment. Using techniques to remove fluid from the donor-recipient graft interface, the donor detachment rate in the last 64 cases was 6%, with half attributable to patient eye rubbing. Detached grafts were reattached by injecting an air bubble to press the donor against the recipient cornea. There were 7 primary graft failures, with only I occurring in the second 100 cases, which primarily used microkeratome-dissected donor tissue. Other complications were infrequent and included pupillary block glaucoma (1), aqueous misdirection syndrome (1), and cataract development in 2 of 27 phakic eyes. The DSEK procedure was performed safely before and after laser in situ keratomileusis (1 each). CONCLUSIONS: Early outcomes in the initial 200 consecutive DSEK procedures suggest the technique provides significant advantages over penetrating keratoplasty, including more rapid healing, more predictable refractive outcomes, and better retention of corneal strength and integrity. Although donor adherence was more challenging, DSEK was technically easier and should be less traumatic to anterior chamber structures than earlier posterior grafting techniques.

Microbial contamination of contact lens care accessories and compliance with care regimens in Nepal - Panthi, S; Paudel, P; Chaudhary, M; Sapkota, K; Shah, DN (CONTACT LENS & ANTERIOR EYE, 2014)
Purpose: To determine the rates of microbial contamination and identify contaminants associated with contact lens (CL) care accessories. To investigate self-reported compliance levels with care of CL accessories and its association with contamination level. Methods: A total of 46 CL cases and care solutions from asymptomatic soft contact lens wearers were collected. Samples from the CL cases and care solutions were cultured for microbiological identification and enumeration. A questionnaire regarding compliance to care and hygiene procedures were administered to each subject on their visit. Results: The percentage of microbial contamination for CL cases and care solutions was 50% and 10.9%, respectively. All the contaminants were bacterial. Staphylococcus aureus (37.0%, 17 of 46 cases) and Escherichia coli (8.7%, 4 of 46 cases) were the most common microorganisms detected in CL cases. In care solutions, S. aureus (8.7%, 4 of 46 samples), Pseudomonas aeruginosa (2.2%, 1 of 46 samples) were common contaminants. CL cases and care solutions that were used for <3 months were significantly less contaminated than those used for >3 months (10.9% versus 39.1%, p < 0.05). Polyquad and Aldox based MPS solution showed no contamination. Subjects with medium or low compliance had highly significant rates of contaminations both in CL cases and solutions than for subjects with high compliance (p<0.05). Conclusions: Nepalese Soft CL wearers are at high risk of developing ocular complications due to high CL case and solution contamination. Frequent replacement of CL cases and solutions, as well as good compliance is recommended to reduce risk of contamination. (C) 2013 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.

Causes of intrastromal corneal ring segment explantation: Clinicopathologic correlation analysis - Ferrer, C; Alio, JL; Montanes, AU; Perez-Santonja, JJ; del Rio, MAD; de Toledo, JA; Teus, MA; Jayaloy, J (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2010)
PURPOSE: To determine the main causes of intrastromal corneal ring segment (ICRS) explantation and the relationship with the microscopic findings on the ICRS surface. SETTING: Vissum Corporation-Instituto Oftalmologico de Alicante, Alicante, Spain. METHODS: This study evaluated ICRS that were explanted in centers in Spain from 2000 to 2008. Clinical data (reasons for explantation, date of implantation/explantation, tunnel creation technique, ICRS type) and scanning electron microscopy findings on the ICRS surface (adherent tissue-like material, cell deposits, protein) were documented. RESULTS: Intrastromal corneal ring segments were explanted from 58 eyes (47 patients). The main cause was extrusion (48.2% of explanted segments), followed by refractive failure (ie, poor refractive outcome) (37.9%), keratitis (6.8%; 3.7% culture positive), and corneal melting and perforation (6.8%). Scanning electron microscopy showed cells and cell debris on the ICRS explanted by extrusion, a clean surface on the ICRS explanted for refractive failure, and bacteria (cocci) in the case of proven infectious keratitis. CONCLUSIONS: The main cause of explantation was extrusion of the ICRS followed by refractive failure. There was a clear correlation between the cause of explantation and the microscopic findings on the ICRS. Extrusion was accompanied by inflammatory cells and cell debris on the ICRS surface. No inflammatory reaction was observed on the ICRS explanted for refractive failure.

Rethinking contact lens aftercare - Efron, N; Morgan, PB (CLINICAL AND EXPERIMENTAL OPTOMETRY, 2017)
The evolution of contact lens technology and clinical practice over the past three decades has been remarkable, with dramatic improvements in material biocompatibility, better lens designs and care systems, and more flexible and convenient modalities of wear. However, our approach to the aftercare examination has remained conservative, with the general modus operandi having not fully evolved from the difficult, early years of fitting non-regular replacement rigid and low water content hydrogel lenses. In this paper, we review current aftercare practice and in particular, the preferred frequency that lens wearers should return for routine visits and the appropriateness of regulations governing contact lens prescription expiry. Four key clinical reasons for conducting a routine aftercare visit are identified: preserving ocular health, maintaining good vision, optimising comfort and ensuring satisfactory lens fitting performance. Commercial reasons for conducting aftercare visits are also considered. A decision matrix is presented to help practitioners decide on an appropriate time interval between routine aftercare visits. The first aftercare visit should always take place within one to two weeks of lens dispensing. After this, the following time intervals between routine aftercare visits are advised as a general guideline: soft daily disposable, 24-months; soft daily reusable and rigid daily wear, 12-months; soft and rigid extended wear, six months. These aftercare visit frequencies may need to be adjusted when rapid rates of refractive change are anticipated, such as every six months during child/teenager myopic progression and every 12-months during the advancement of presbyopia. Numerous clinical caveats for varying these recommended aftercare frequencies are also discussed. Those new to lens wear should be seen within the first two months of lens dispensing. Regulatory authorities charged with the responsibility of stipulating the validity of a contact lens prescription should continue to allow optometrists to set an expiry date relevant to the circumstances of individual lens wearers.

Characteristics of Infectious Keratitis in Bandage Contact Lens Wear Patients - Zhu, BB; FLiu, YF; Lin, L; Huang, XD; Zhang, Y; Zheng, J; Jin, XM (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2019)
Objective: The aim of this study was to determine the characteristics of infectious keratitis in patients wearing bandage contact lenses (BCLs). Methods: The BCL-related infectious keratitis cases were reviewed at the eye center of the Second Affiliated Hospital at the Zhejiang University School of Medicine from January 2015 to August 2018. Detailed information about the patients with infectious keratitis was collected, including the age, gender, clinical characteristics, culture results, and other measures. All the data analyses were performed using IBM SPSS Statistics for Windows version 24.0. Results: From January 2015 until August 2018, 6,385 eyes of 6,188 patients, including 3,410 males and 2,778 females, received BCLs at our hospital. The mean age of these patients was 48.10 +/- 20.81 years (range=15-78 years). The mean BCL wearing time was 18.98 +/- 23.72 days (range=1-58 days). Eight patients (0.13%) with infectious keratitis were identified, and the mean age of these patients was 54.33 +/- 28.14 years (range=16-75 years). Seven of the infectious keratitis patients were older than 50 years, and one patient was 16 years old. The infectious keratitis incidence rate of the older patients (>= 50 years) was significantly higher than that of the young patients (<50 years) (chi(2)=9.647, P=0.002). There was a higher postkeratoplasty risk of BCL-related infectious keratitis than that in the corneal epithelial defect (chi(2)=21.371, P=0.000) and pterygium surgery (chi(2)=16.037, P=0.000) cases, but not in the corneal collagen cross-linking cases (chi(2)=1.792, P=0.181). The mean onset time of BCL-related infectious keratitis was 22.63 +/- 18.72 days (range=3-58 days) after wearing the BCLs. Among these 8 infected patients, 3 were noncompliant with their eye drop use and 2 extended their BCL wearing time past 30 days. Conclusion: Bandage CL-related infectious keratitis is more likely to occur in older patients. The most common risk factor for BCL-related infectious keratitis was postkeratoplasty use. Overall, appropriate indications, good compliance, and close follow-up attention are required for BCL wearers.

Comparison of peroperative subconjunctival injection of methylprednisolone and standard postoperative steroid drops after uneventful cataract surgery - Merkoudis, N; Matsson, AW; Granstam, E (ACTA OPHTHALMOLOGICA, 2014)
PurposeTo compare the safety and efficacy of a single subconjunctival injection of methylprednisolone and a standard postoperative steroid regimen in terms of intraocular inflammation and intraocular pressure (IOP) after uncomplicated phacoemulsification surgery. MethodsTwo groups of 25 patients each were included in this prospective randomized controlled trial. Patients in the injection group were given a subconjunctival injection of 20mg methylprednisolone and the topical group received the conventional postoperative care with steroid eye drops (dexamethasone 1mg/ml). The patients were examined 1week and 1month after surgery. Slit-lamp evaluation of anterior chamber inflammation and IOP were performed. Changes in IOP of 2.4mmHg were considered clinically relevant. ResultsIn the injection group, mean IOP decreased from 15.42.2mmHg (baseline) to 14.1 +/- 3.2mmHg at 1week (p=0.03). The topical group had a stable IOP at 1week (16.3 +/- 2.6mmHg) compared to baseline (16.1 +/- 2.7mmHg; p=0.74). At 1month, mean IOP was 14.3 +/- 2.6mmHg (p=0.03) in the injection group and 15.6 +/- 2.3mmHg (p=0.2) in the topical group. The intragroup changes were neither statistically significant nor clinically relevant at any postoperative visit. Both groups had the highest values of intraocular inflammation at the 1-week postoperative visit, followed by a decline to barely traceable levels at 1month. The difference was not clinically relevant at any postoperative visit. ConclusionsThe subconjunctival injection of methylprednisolone appears to be as safe and effective as the conventional treatment, and it might therefore be considered for treatment of individuals with compliance issues.

Compliance behaviour change in contact lens wearers: a randomised controlled trial - Arshad, M; Carnt, N; Tan, JE; Stapleton, F (EYE, 2021)
Background Water exposure during contact lens wear has been associated with contact lens disease including microbial keratitis and sterile corneal infiltrates. Despite the documented risks, water exposure is common amongst lens wearers. This study aimed to determine the effect of water education in the form of "no-water" lens case stickers on water-contact behaviours and storage case contamination. Methods In a prospective, masked, randomised controlled trial, 200 daily lens wearers were randomised to either receive a storage case with a "no-water" sticker (test) or without a "no-water" sticker (control). Both groups received written compliance information. Participants completed a self-administered lens hygiene questionnaire at baseline and after 6 weeks. Microbial analysis of used storage cases, collected at both study visits, was conducted using ATP and limulus amebocyte lysate (LAL) assays for overall microbial contamination and endotoxin levels, respectively. A one-way ANCOVA and multiple logistic regression determined the change in water-contact behaviours and storage case contamination over time. Results A total of 188 lens wearers completed both study visits; 128 females and 60 males; average age 29 +/- 13 (range 18-78 years); 95 test and 93 control participants. After 6 weeks, the overall water exposure score and endotoxin levels reduced significantly in the test group compared with the control group (p < 0.05). There were no significant changes in individual water-contact behaviours or overall storage case contamination. Conclusion A no-water infographic on the contact lens case improved overall water-contact behaviours and reduced storage case endotoxin. Refining the messaging may be beneficial in future to improve other aspects of compliance.

Eye Care Use Among Rural Adults in China: The Handan Eye Study - Peng, Y; Tao, QS; Liang, YB; Friedman, DS; Yang, XH; Jhanji, V; Duan, XR; Sun, LP; Wang, NL (OPHTHALMIC EPIDEMIOLOGY, 2013)
Purpose: To assess the use of eye care services in a rural population in North China and to analyze the factors associated with underuse of these services. Methods: In a cross-sectional population-based study, demographic, health and vision-related information including use of eye care services were determined during a face-to-face interview. A single visit to an eye care provider qualified as "use" of eye care services. Results: Of 6612 participants, 754 (11.4%, 95% confidence interval, CI, 8.7-14.1%) had used eye care services. The most common reason cited for not seeing an eye care provider was "no need" (n = 5754). Of the 5754 who thought that there was no need to see an ophthalmologist, 3458 (60.1%) were found to have one or more type of eye disease, including glaucoma (56, 1.0%), cataract (1056, 18.4%), age-related macular degeneration (AMD; 164, 2.9%) and refractive error (3048, 53.0%). Also, 74 (1.3%) and 409 (7.1%) of the 5754 participants had visual impairment (<20/60) according to best-corrected visual acuity and presenting visual acuity, respectively. In a multiple regression model, participants who had glaucoma (adjusted odds ratio, OR, 4.0, 95% CI 3.0-5.4), AMD (adjusted OR 1.6, 95% CI 1.2-2.3) or refractive error (adjusted OR 1.4, 95% CI 1.1-1.8), were more likely to visit an eye care provider. Conclusion: A high proportion of the Chinese rural population had never used eye care services although three fifths had eye diseases. Further efforts towards better education of the general population about common eye problems as well as increasing the number of ocular health providers would be necessary in future.

Medication Burden for Patients With Bacterial Keratitis - Ballouz, D; Maganti, N; Tuohy, M; Errickson, J; Woodward, MA (CORNEA, 2019)
Purpose: To understand medication use and patient burden for treatment of bacterial keratitis (BK). Methods: A retrospective study was conducted examining medical records of adult patients with BK in an academic cornea practice. Data collected included medications used in the treatment of BK, dosing of medications, and the number and total duration of clinical encounters. Costs of medications were estimated using the average wholesale pharmacy price. Linear regression analysis was used to investigate associations of medication use with patient demographics and corneal culture results and reported with beta estimates (beta) and 95% confidence intervals (95% CIs). Results: Forty-eight patients with BK (56% female) were studied. Patients were treated for a median of 54 days with 10 visits, 5 unique medications, 587 drops, and 7 prescriptions. The estimated median medication cost was $933 (interquartile range: $457-$1422) US dollars. Positive bacterial growth was significantly associated with more visits (beta: 6.16, 95% CI: 1.75-10.6, P = 0.007), more days of treatment (beta: 86.8, 95% CI: 10.8-163, P = 0.026), more prescribed medications (beta: 2.86, 95% CI: 1.04-4.67, P = 0.003), and more doses of medications (beta: 796, 95% CI: 818-1412, P = 0.012) compared with patients who did not undergo corneal scraping. Patients were prescribed 132 more drops of medication for every 10 years of older age (beta: 132, 95% CI: 18.2-246, P = 0.024). Sex and income were not associated with medication burden or treatment length. Conclusions: Older patients and those with positive cultures incur the most medication burden in treatment of BK. Providers should be aware of medication usage and cost burden as it may affect compliance with treatment.

Monitoring daily intraocular pressure fluctuations with self-tonometry in healthy subjects - Querat, L; Chen, E (ACTA OPHTHALMOLOGICA, 2017)
PurposeTo evaluate the accuracy of the intraocular pressure (IOP) measured by healthy subjects with icare((R)) Home and to observe the IOP fluctuation and pattern of IOP fluctuation in healthy subjects over three consecutive days. MethodsSixty healthy subjects were recruited to the study. IOP was measured by the subjects themselves and by study staff using icare((R)) Home tonometers on visits 1 and 2, as well as by study staff using Goldmann applanation tonometry (GAT). Furthermore, the subjects measured their IOP at home for three consecutive days. ResultsTwenty-three per cent of the study eyes were excluded in the statistical analysis due to dropout or non-compliance to the schedule. Approximately 70% of the icare((R)) Home measurements were within 3mmHg of the GAT measurements. Ten to 16% of the study eyes had IOP peaks outside office hours. Sixty-three per cent of the study eyes had different IOP patterns on consecutive days. ConclusionRebound self-tonometry appears to be accurate and could be used to monitor short- and long-term IOP variations. The difference between IOP patterns on consecutive days raises questions as to the certainty of a single IOP measurement as a measure of treatment effect.

Conjunctival dysfunction and mitomycin C-induced hypotony - Sihota, R; Dada, T; Gupta, SD; Sharma, S; Arora, R; Agarwal, HC (JOURNAL OF GLAUCOMA, 2000)
Purpose: To determine the role of a physically intact conjunctiva in the development of chronic hypotony after mitomycin C-enhanced trabeculectomy. Method: Three patients with mitomycin C-related hypotonic maculopathy, but without a leak on Siedel test, had a thorough evaluation of the bleb area and an anterior segment fluorescein angiography. The bleb was excised and a pedicle flap, rotated from the temporal conjunctiva, was sutured to cover the defect superiorly. The scleral flap and its sutures were not disturbed. The excised bleb was subjected to light and electron microscopy. Results: The Seidel test result was negative in all patients, but late phases of the anterior segment angiography showed a generalized seepage of aqueous from the bleb. After revision of the bleb, there was a gradual increase in the intraocular pressure, a reversal of the hypotonic maculopathy, and consequent improvement in visual acuity in all three patients, stable up to a minimum follow-up of 18 months. On histopathologic examination, the basement membrane was thickest under thin areas of the epithelium and thinnest below thicker epithelial layers. Conclusion: A dysfunctional conjunctival barrier, as evidenced by the "sweating" of the bleb and histopathologic alterations in the epithelial barrier, could be responsible for the hypotonic maculopathy in these patients. Excision of the conjunctiva alone and replacement by a pedicle conjunctival graft offers a safe and effective method of treating chronic hypotony after mitomycin C-augmented trabeculectomy in such patients.

Switching from concomitant therapy to tafluprost/timolol fixed combination - Inoue, K; Kawashima, T; Katakura, S; Shidara, K; Fujimoto, T; Kohmoto, H; Shiokawa, M; Moriyama, R; Okayama, R (CLINICAL OPHTHALMOLOGY, 2018)
Purpose: To evaluate the efficacy and safety of tafluprost/timolol fixed combination (TTFC). Study design: A prospective clinical study. Methods: Twenty-eight patients (28 eyes) with primary open-angle glaucoma, who had used tafluprost and timolol gel for at least 3 months with good adherence, were enrolled. Concomitant administration of tafluprost and timolol was switched to TTFC without a washout period. The intraocular pressure (IOP), blood pressure, pulse rate, and ocular signs were compared between before switching (baseline), and 4 and 8 weeks after switching. A questionnaire survey was also performed 4 weeks after switching to investigate ocular comfort and patient preferences. Results: The IOP showed no significant change after switching to TTFC (14.8 +/- 2.8, 14.6 +/- 3.4, and 14.8 +/- 3.7 mmHg at baseline, Week 4, and Week 8, respectively). The pulse rate and systolic blood pressure showed no changes, but diastolic blood pressure was significantly lower at Week 8. At baseline, fluorescein staining revealed corneal abnormalities in 3 patients, which resolved by Week 8 in 1 patient. Hyperemia was noted in 2 patients at baseline, and this also resolved by Week 8 in 1 patient. Three patients discontinued study treatment for the following reasons (1 patient each): blurred vision; ocular irritation, eyelid erythema, and asthenopia; and loss to follow-up from Week 8. The questionnaire survey revealed no significant differences between the 2 treatments, although more patients preferred TTFC. Conclusion: Among 28 patients enrolled, only 2 patients discontinued the study treatment due to adverse reactions. In patients whose adherence was considered relatively good to concomitant therapy, switching to TTFC achieved similar IOP control with good safety and a high level of patient acceptance.

Descemet Stripping Endothelial Keratoplasty After Ophtec 311 Iris Reconstruction Lens Implantation - Aldave, AJ; Baghdasaryan, E; Miller, KM (CORNEA, 2011)
Purpose: To describe the variations in intraoperative technique, postoperative complications, and visual outcomes associated with Descemet stripping endothelial keratoplasty (DSEK) after Ophtec iris reconstruction lens implantation. Design: Retrospective, interventional, consecutive case series. Participants: Patients who underwent DSEK after Ophtec 311 iris reconstruction lens implantation at the Jules Stein Eye Institute, University of California, Los Angeles. Methods: Medical records were reviewed for demographic information, ophthalmic history, DSEK surgical technique, and postoperative clinical course. Main Outcome Measures: Intraoperative and postoperative complications and visual outcomes. Results: Four patients were identified (1 man and 3 women, age: 43-78). Three of the eyes had undergone prior penetrating keratoplasty (PKP), and each of the eyes had a history of glaucoma, with previous glaucoma surgery having been performed in 2 of the eyes. No intraoperative complications were encountered during the procedures, although an unplanned anterior vitrectomy was required in a previously vitrectomized eye. In each case, a complete air fill of the globe was obtained to ensure adherence of the donor button, and in 3 of the 4 cases, the donor button was sutured to the recipient cornea to prevent potential posterior dislocation. None of the cases developed donor button dislocation or primary graft failure. Corrected distance visual acuities improved to 20/40-20/160, corresponding to a mean improvement of 0.25 (range, 0.12-0.40), limited by irregular corneal astigmatism and advanced glaucomatous optic neuropathy. During a mean follow-up period of 15.6 months (range, 4.9-24.8 months), graft rejection developed in 2 of the 3 eyes with a history of endothelial rejection after PKP (0.42 episode per eye-year). Both of these eyes developed secondary graft failure, which also developed 14 months after DSEK in the other eye with a history of PKP failure before DSEK. Conclusions: DSEK can be successfully performed in eyes with partial or complete aniridia, such as those after Ophtec iris reconstruction lens implantation. Modifications to the standard DSEK technique increase the probability of successful donor adherence and decrease the risk of posterior dislocation of the donor corneal button. However, endothelial rejection may occur at an increased frequency, resulting in secondary graft failure.

Panophthalmitis and Orbital Inflammation with Cavernous Sinus Thrombosis Following Cataract Surgery - Marinos, E; McCall, D; Tumuluri, K; Rowe, N; Do, H (INTERNATIONAL MEDICAL CASE REPORTS JOURNAL, 2020)
Background: Panophthalmitis is a severe inflammation of the globe that can result as a rare complication of ophthalmic surgery. In severe cases, it may also be associated with orbital inflammation and cavernous sinus thrombosis. Purpose: This case demonstrates a rare and life-threatening post-operative complication of cataract surgery. We also hope to highlight the importance of considering the relevant risk factors associated with developing potential infections after cataract surgery, including the use of corneal sutures, high-risk behaviours such as excessive eye-rubbing, and noncompliance with appointments and post-operative medications. Case Report: We report the case of a 35-year-old female with severe autism and developmental delay who developed panophthalmitis, orbital inflammation and cavernous sinus thrombosis 6 weeks post cataract surgery. The likely cause was corneal suture-related microbial keratitis, and the patient required enucleation due to sepsis. Conclusion: Post-surgical panophalmitis is a rapidly progressive disease that is not only sight- but life-threatening and demands urgent and intensive treatment. Consideration of early enucleation may be required to prevent deterioration in such patients.

Telemedicine-based diabetic retinopathy screening programs: an evaluation of utility and cost-effectiveness - Cuadros, JA (SMART HOMECARE TECHNOLOGY AND TELEHEALTH, 2015)
Diabetes is the main cause of blindness among working age adults, although treatment is highly effective in preventing vision loss. Eye examinations are recommended on a yearly basis for most patients for timely detection of retinal disease. Telemedicine-based diabetic retinopathy screening (TMDRS) programs have been developed to identify patients with sight-threatening diabetic eye disease because patients are often noncompliant with recommended live eye examinations. This article reviews the cost-effectiveness of the various forms of TMDRS. A review of relevant articles, mostly published since 2008, shows that societal benefits generally outweigh the costs of TMDRS. However, advances in technology to improve efficacy, lower costs, and broaden screening to other sight-threatening conditions, such as glaucoma and refractive error, are necessary to improve the sustainability of TMDRS within health care organizations. Patient satisfaction with these telemedicine programs is generally high. New models of shared care with primary care providers and staff are emerging to improve patient engagement and follow-up care when individuals are found to have sight-threatening eye disease. TMDRS programs are growing and provide valuable clinical benefit. The cost-utility is currently well proven in locations with limited access to regular eye care services, such as rural areas, poor communities, and prison systems; however, improvements over time are necessary for these programs to be cost-effective in mainstream medical settings in the future.

Ophthalmic Complications Following Treatment of Paranasal Sinus Rhabdomyosarcoma in Comparison to Orbital Disease - Gandhi, PD; Fleming, JC; Haik, BG; Wilson, MW (OPHTHALMIC PLASTIC AND RECONSTRUCTIVE SURGERY, 2011)
Purpose: To identify the type and frequency of ocular and orbital complications observed following treatment for primary rhabdomyosarcoma of the paranasal sinuses or the orbit. Methods: An institutional review board-approved, Health Insurance Portability and Accountability Act-compliant retrospective chart review was conducted to identify all patients treated at one institution from 1966 to 2005 with biopsy-proven primary paranasal sinus or orbital rhabdomyosarcoma. Pretreatment, treatment, and follow-up data were collected. Results: Forty-four patients (25 male) of a median age of 7.8 years (range 1.0-18.0 years) with primary paranasal sinus (17) or orbital (27) rhabdomyosarcoma were treated and followed for a median period of 5.3 years (range 0.6-32.0 years). The three most frequently observed ophthalmic complications were persistent eyelid erythema or cellulitis (12), epithelial keratitis (7), and conjunctival injection (6) in the paranasal sinus and epithelial keratitis (18), conjunctival injection (11), and cataract (10) in the orbit. Overall survival after treatment trended higher for the orbital rhabdomyosarcoma group (23 of 27) than the paranasal sinus group (9 of 17). Conclusions: The most frequently observed treatment-induced ophthalmic complications in the paranasal sinus group were manageable with minimal patient morbidity, as in the patients with orbital disease. Vision-threatening complications were infrequently encountered. Despite maximal therapy, the mortality rate was higher in the paranasal sinus rhabdomyosarcoma group than in the orbital rhabdomyosarcoma group.

iCareTrack: measuring the appropriateness of eyecare delivery in Australia - Ho, KC; Stapleton, F; Wiles, L; Hibbert, P; White, A; Jalbert, I (OPHTHALMIC AND PHYSIOLOGICAL OPTICS, 2020)
Purpose To meet the needs of an ageing population and optimise health expenditure, delivery of care should be based on evidence. However, the level of evidence-based care delivered to patients with eye conditions is rarely assessed. This study thus aimed to determine the percentage of eyecare encounters at which a sample of adult Australians received appropriate care (i.e., eyecare in line with evidence-based or consensus-based guidelines). Methods A cross-sectional retrospective review of optometry practice records was conducted using random stratified (by state) sampling in mainland Australia. Eighty-five clinical indicators were developed from evidence-based clinical practice guideline recommendations and refined by panels of experts using a modified Delphi process. Healthcare records of patients 18 years and over were examined against these indicators, representing appropriate care for three common eye conditions (preventative eyecare, glaucoma, and diabetic eyecare). Encounters occurred in optometry practices that were selected to be representative of the socioeconomic profile of Australian practices. The primary outcome measure was percentage compliance of eyecare delivery against the clinical indicators. Results From 426 optometry practices contacted by mail or telephone, 90 (21%) replied, 46 proved eligible and 42 were included in the study and visited for data collection. From these 1260 patient records were reviewed. Appropriate eyecare was received by Australian patients at an average of 71% (95%CI 70%, 73%) of eligible encounters. The percentage of appropriateness of eyecare at the condition level for preventative, glaucoma and diabetic eyecare was 81% (95%CI 79%, 83%), 63% (95%CI 61%, 64%), and 69% (95%CI 66%, 73%), respectively. Appropriateness of eyecare delivery was lowest for the domains of history taking and physical examination for all eye conditions. Conclusions There were pockets of excellence but consistent delivery of appropriate eyecare needs improvement, and gaps in eyecare delivery should be addressed.

The Role of Patient Inexperience in Medication Discontinuation: A Retrospective Analysis of Medication Nonpersistence in Seven Chronic Illnesses - Vanelli, M; Pedan, A; Liu, N; Hoar, J; Messier, D; Kiarsis, K (CLINICAL THERAPEUTICS, 2009)
Background: Previous studies have reported that patients who are medication naive In some medication classes have a higher risk of medication discontinuation during the first 30 days of treatment and shorter median times to discontinuation than do medication-experienced patients. Objectives: This study compared the risk of discontinuation during the first 30 days after the index fill and the median time to discontinuation for medication-naive and medication-experienced patients who were prescribed drugs for asthma, diabetes mellitus, high cholesterol, cardiovascular disease, breast cancer, glaucoma, or osteoporosis. Methods: Deidentified outpatient pharmacy records from 4 large US retail chains were searched for patients who had obtained a prescription for one of the index medications between January 1, 2007, and January 31, 2007. Included medication classes were asthma inhalers, asthma pills, oral breast-cancer agents, cardiovascular medications, oral antidiabetic medications, insulin, glaucoma drops, osteoporosis medications, and statins. Patients were divided into 2 groups: those for whom an in-class medication was not dispensed in the previous 180 days were identified as medication naive, and those for whom an in-class medication was dispensed during this period were identified as medication experienced. Discontinuation was defined as being > 30 days late for a scheduled refill. Time to discontinuation was measured using Kaplan-Meier analysis during a 360-day follow-up period. Results: Data for 2.17 million patients who received prescriptions from 3821 pharmacies were analyzed. During the first 30 days of therapy, rates of discontinuation for medication-naive patients were 17.4% to 42.6% higher than for medication-experienced patients, and their median times to discontinuation were 14.2% to 28.9% as long. The difference in persistence between medication-naive and medication-experienced patients emerged during the first 30 days of medication use, after which rates of discontinuation were relatively consistent. Patients prescribed nonoral medications for diabetes mellitus (insulin), asthma (inhalers), and glaucoma (drops) had an especially high risk of discontinuation during the first month of treatment. Conclusion: This study found that medication-naive patients had a higher risk of discontinuation during the first 30 days of therapy than did medication-experienced patients, regardless of the medication class prescribed, leading to shorter median times to discontinuation. (Clin Ther. 2009;31:2628-2652) (C) 2009 Excerpta Medica Inc.

Ab interno trabecular bypass surgery with iStent for open-angle glaucoma - Le, JT; Bicket, AK; Wang, L; Li, TJ (COCHRANE DATABASE OF SYSTEMATIC REVIEWS, 2019)
Background Glaucoma is a leading cause of irreversible blindness worldwide. In early stages, glaucoma results in progressive loss of peripheral (side) vision; in later stages, it results in loss of central vision leading to blindness. Elevated intraocular pressure (TOP) is the only known modifiable risk factor for glaucoma. Minimally invasive glaucoma surgical (MIGS) techniques, such as ab interno trabecular bypass surgery with iStent (Glaukos Corporation, Laguna Hills, CA, USA), have been introduced as a new treatment modality for glaucoma. However, the effectiveness of MIGS on keeping people 'drop-free' (i.e. not having to use eye drops to control IOP) and other outcomes is uncertain. Objectives To assess the effectiveness and safety of ab interno trabecular bypass surgery with iStent (or iStent inject) for open-angle glaucoma in comparison to conventional medical, laser, or surgical treatment. Search methods Cochrane Eyes and Vision's Information Specialist searched the following databases on 17 August 2018: the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Trials Register; 2018, Issue 7), MEDLINE Ovid, Embase Ovid, the ISRCTN registry, ClinicalTrials.gov, and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP). We applied no date or language restrictions. We searched the reference lists of reports from included studies. Selection criteria We included randomized controlled trials (RCTs) that had compared iStent or iStent inject to medical therapy, laser treatment, conventional glaucoma surgery (trabeculectomy), or other MIGS procedures. We included RCTs that had compared iStent or iStent inject in combination with phacoemulsification to phacoemulsification alone. Data collection and analysis We used standard methodological procedures expected by Cochrane. Two review authors independently screened search results, assessed risk of bias, and extracted data from reports of included RCTs using an electronic data collection form. Main results We included seven RCTs (765 eyes of 764 participants; range per study 33 to 239 participants) that evaluated iStent in people with open-angle glaucoma. We also identified 13 studies that are ongoing or awaiting publications of results. Most participants in the included studies were women (417/764 (55%) participants) and older age (age range: 49 to 89 years). We assessed most trials at unclear or high risk of bias: four trials did not clearly report the method of generating the random sequence or concealing allocation; five were unmasked, open-label studies, which we assessed at high risk of bias for performance and detection bias. All seven trials were funded by the Glaukos Corporation. We graded the certainty of evidence as very low. Four RCTs compared iStent in combination with phacoemulsification to phacoemulsification alone. The summary estimate which we derived from two of the four RCTs suggested that participants in the iStent in combination with phacoemulsification group were 1.38 times more likely to be drop-free between six and 18 months than those in the phacoemulsification alone group (risk ratio (RR) 1.38, 95% confidence interval (CI) 1.18 to 1.63, I-2 = 67%). Data from two RCTs also suggested that iStent in combination with phacoemulsification compared to phacoemulsification alone may have offered a small reduction in number of TOP-lowering drops (mean difference (MD) -0.42 drops, 95% CI -0.60 to -0.23). It is uncertain whether there was any difference in terms of mean reduction in TOP from baseline (no meta-analysis). Two RCTs compared treatment with iStent to medical therapy; one of the two trials used the iStent inject. We determined the two trials to be clinically and methodologically heterogeneous and did not conduct a meta-analysis; however, the investigators of both trials reported that over 90% of participants in the treatment groups were drop-free compared to no participants in the medical therapy groups at six to 18 months. One RCT compared treatment with one versus two versus three iStents. There was no difference in terms of participants who were drop-free at 36 months or less; however, at longer follow-up (i.e. at 42 months) participants in the one iStent treatment were less likely to be drop-free than those in the two iStent (RR 0.51, 95% CI 0.34 to 0.75) or three iStent (RR 0.49, 95% CI 0.34 to 0.73) treatment groups. The study did not report the mean change in number of TOP-lowering drops. The type and timing of complications reported varied by RCTs. Similar proportions of participants who underwent treatment with iStent in combination with phacoemulsification and who underwent phacoemulsification alone needed secondary glaucoma surgery. None of RCTs reported findings related to quality of life. Authors' conclusions There is very low-quality evidence that treatment with iStent may result in higher proportions of participants who are drop-free or achieving better TOP control, in the short, medium, or long-term. Results from the 13 studies with results not yet available may clarify the benefits of treatment of people with iStent. Additionally, future MIGS studies should consider measuring quality of life and outcomes that reflect people's ability to perform vision-dependent activities.

Anterior 360 degrees Synechiolysis in a Case of Late Iridocorneal Adhesions after 25-G Vitrectomy: Surgical and Physiopathogenetic Aspects - Nuzzi, R; Monteu, F (CASE REPORTS IN OPHTHALMOLOGY, 2017)
We describe the case of an 86-year-old patient, pseudophakic in both eyes and with high myopia, who had previously had a 25-G vitrectomy with 20% C3F8 used as a tamponade due to a total retinal detachment with choroidal hemorrhages and macular hole. At the postoperative 4-month follow-up, we found 360 degrees iridocorneal synechiae with elevated intraocular pressure due to angle closure in all sectors, with an adherent retina and in the absence of choroidal hemorrhage/detachment and of corneal edema or endothelial damage. The patient was, therefore, hospitalized to receive 360 degrees anterior synechiolysis with a single opening to the corneal limbus, like in paracentesis, with topical anesthesia. We have tried to study the possible causes of this case history. However, it should be recognized that the development of iridocorneal synechiae and the rise of intraocular pressure can be a possible complication of air/C3F8 vitrectomy, which cannot be managed with medical therapy. It will be essential to monitor the situation and to hospitalize the patient for surgical synechiolysis to restore the normal anatomy and physiology and to correct the ocular hypertension. During the vitrectomy, we will have to introduce in advance an adequate amount of viscoelastic material in the anterior chamber and to perform a preventive surgical iridectomy, even if the iridocorneal angle is open in all sectors. (C) 2017 The Author(s) Published by S. Karger AG, Basel

Cluster-randomised trial of community-based screening for eye disease in adults in Nepal: the Village-Integrated Eye Worker Trial II (VIEW II) trial protocol - O'Brien, KS; Stevens, VM; Byanju, R; Kandel, RP; Bhandari, G; Bhandari, S; Melo, JS; Porco, TC; Lietman, TM; Keenan, JD; Grp Information View (BMJ OPEN, 2020)
Introduction The majority of blindness worldwide could be prevented or reversed with early diagnosis and treatment, yet identifying at-risk and prevalent cases of eye disease and linking them with care remain important obstacles to addressing this burden. Leading causes of blindness like glaucoma, diabetic retinopathy and age-related macular degeneration have detectable early asymptomatic phases and can cause irreversible vision loss. Mass screening for such diseases could reduce visual impairment at the population level. Methods and analysis This protocol describes a parallel-group cluster-randomised trial designed to determine whether community-based screening for glaucoma, diabetic retinopathy and age-related macular degeneration reduces population-level visual impairment in Nepal. A door-to-door population census is conducted in all study communities. All adults aged >= 60 years have visual acuity tested at the census visit, and those meeting referral criteria are referred to a local eye care facility for further diagnosis and management. Communities are subsequently randomised to a community-based screening programme or to no additional intervention. The intervention consists of a single round of screening including intraocular pressure and optical coherence tomography assessment of all adults >= 60 years old with enhanced linkage to care for participants meeting referral criteria. Four years after implementation of the intervention, masked outcome assessors conduct a repeat census to collect data on the primary outcome, visual acuity. Individuals with incident visual impairment receive a comprehensive ophthalmological examination to determine the cause of visual impairment. Outcomes are compared by treatment arm according to the originally assigned intervention. Ethics and dissemination The trial has received ethical approval from the University of California San Francisco Institutional Review Board, Nepal Netra Jyoti Sangh and the Nepal Health Research Council. Results of this trial will be disseminated through publication in peer-reviewed journals and presentation at local and international meetings.

Management of diabetic retinopathy by Australian optometrists - McCarty, CA; McKay, R; Keeffe, JE; Working Grp Evaluation NHMRC Retin (AUSTRALIAN AND NEW ZEALAND JOURNAL OF OPHTHALMOLOGY, 1999)
Purpose: To describe current practices related to the management of diabetic retinopathy by Australian optometrists. Setting and Methods: A two-page self-administered questionnaire was mailed to a random sample of 504 Australian optometrists. The survey included questions about the practice (such as size and location); current practice with regard to management of patients with diabetic retinopathy; barriers to use of dilating drops; and a number of patient, scenarios related to screening, follow-up and treatment of diabetic retinopathy, Results: Completed questionnaires were returned by 407 of the 473 eligible optometrists (86%). They had been practising optometry between 1 and 50 years (median 14). Of the 243 optometrists who provided details about the location of their practices, 145 (37%) had at least one of their practices in a rural area The estimated percentage of patients with diagnosed diabetes ranged from 0.5 to 40% (median = 5.0%). Three-hundred and twenty-two optometrists (79%) reported that they would often or almost always ask new patients over the age of 40 whether they have diabetes. The majority of optometrists (n = 387, 95%) would often or almost always ask their new patients with diabetes about their control of blood glucose levels and the majority of optometrists (n = 330, 81%) would often or almost always tell their patients with diabetes about the importance of strict glucose control in delaying retinopathy. The most common barrier to dilated ophthalmoscopy was patients not wanting to be dilated, with 38.1% of optometrists reporting this to be a moderate or major barrier. The next most common barrier was fear of precipitating angle closure glaucoma; 17.1% of optometrists reported this to be a moderate or major barrier. Conclusion: The National Health and Medical Research Council (NHMRC) guidelines for the management of diabetic retinopathy are timely in relation to the expressed desire of Australian optometrists to learn more about management of diabetic retinopathy. These data will be used prospectively to assess changes in management of patients with diabetic retinopathy as a result of the release of the NHMRC guidelines.

Self-tonometry with a Telemetric Intraocular Pressure Sensor in Patients With Glaucoma - Koutsonas, A; Walter, P; Plange, N (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2016)
Background: Accurate acquisition of intraocular pressure (IOP) data, particularly short-term and long-term fluctuations, plays an important role in the medical care of glaucoma patients. Non-invasive self-tonometry with a telemetric IOP sensor can provide important data on the individual IOP profile. Methods: Within the framework of a prospective, single-centre pilot clinical trial, a ring-shaped telemetric IOP sensor was inserted into the ciliary sulcus after implantation of the intracapsular lens during planned cataract surgery. In accordance with the protocol, at the 5-month visit, all patients received a reading unit for one-month self-tonometry assessment. All patients were asked to measure the IOP at least once daily, and, if possible, at many different times. The first IOP measurement of each day was evaluated (covering one measurement daily per patient on 20 different days within the assessment interval). Furthermore, IOP data were analysed according to the time of day, divided into early phase (5 am to 11 am), midday (11 am to 4 pm) and late phase (4 am to 11 pm) (patients with at least 10 measurements and max. 20 measurements were included). Descriptive statistics of the original ARGOS system values were calculated, with evaluation of the percentiles and presentation in box plots. Results: All patients successfully performed self-tonometry at home after receiving brief instructions. The first IOP measurement of each day covered a very wide interindividual range (between 3.1 mmHg in patient 5 and 21.7 mmHg in patient 4). Analysis of IOP values by time of day showed that patient 1 had significantly higher IOP values in the late day phase. For patient 5, the highest values were at midday. Patients 3 and 4 showed no significant fluctuations during the day. Conclusions: Self-tonometry encourages patients to be actively involved in the management of their own illness and allows non-invasive assessment of IOP at different times and during diverse activities. However, the analysis and interpretation of these new data require further study, especially in relation to Goldmann applanation tonometry.

Hormone therapy for ophthalmoprophylaxis - Wenderlein, JM; Hensinger, E (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2003)
Background: It has been demonstrated that HRT which was administered directly after the onset of the menopause had vascular-protective and neuroprotective effects. It has therefore hypothesised that eye function could benefit from such treatment. Material and methods: Visual acuity, intraocular pressure, patient's gynaecological and ophthalmological history, especially HRT were obtained from women visiting the gynaecological and ophthalmological ambulance. Measuring the visus and the intraocular pressure of women with HRT from the gynaecological ambulance was easily undertaken in the neighbouring ophthalmological department. Unfortunately, due to absence of compliance a control group without HRT could not be recruited. Of 514 women, 402 without having had hysterectomy and adnexectomy could be included in the study from which data were received about the menopausal age. Results: In the group of women with cataract HRT over 5 years was administered less often (two times) than in the group of women with glaucoma. Women mainly aged over 70 suffering from age-related conditions such as glaucoma and cataract almost never had HRT. Thus in the following only women aged up to 60 have been of interest. 7 of 10 women being in the menopause for over 10 years with a visus higher than 0.7 received HRT. Only 1 of 10 women had a visual acuity less than 0.4. There was also a correlation between receiving HRT and intraocular pressure. In the group aged up to 60 without taking HRT 19% had an intraocular pressure above 19. In women with HRT over 5 years this occurred in only 7 %. Conclusions: Initiating HRT in healthy women shortly after the onset of the menopause may have vascularprotective and neuroprotective effects for the eye. This is supported by the fact that HRT administered for more than 5 years to healthy women aged up to 60 years was associated with better visual acuity and normal intraocular pressure. This is further highlighted by ultrasound scan studies in the literature. Thus an ophthalmoprophylaxis could be expected, which has to be confirmed in prospective studies using suitable control groups.

Recombinant tissue plasminogen activator in cases with fibrin formation after cataract surgery: a prospective randomised multicentre study - Heiligenhaus, A; Steinmetz, B; Lapuente, R; Krallmann, P; Althaus, C; Steinkamp, WK; Dick, B (BRITISH JOURNAL OF OPHTHALMOLOGY, 1998)
Aims-This study investigated the effect of tissue plasminogen activator (tPA) in patients with severe intracameral fibrin after extracapsular cataract extraction or phacoemulsification with posterior chamber intraocular lens implantation. Methods-A randomised prospective multicentre study was carried out in 86 patients with intraocular fibrin formation 2-8 days after cataract surgery. While the first group (n=41) received only antiinflammatory drugs, a single anterior chamber injection of tPA (10 mu g) as an additional treatment to the standard was given in the second group (n=44). On days 1, 2, 14, and 90 after randomisation, the visual acuities, slit lamp findings, and intraocular pressures were documented in standardised protocols. Efficacy of treatment was judged by the rate of fibrinolysis (primary objective), the frequency of synechiae, and central capsular fibrosis (secondary objectives). Results-The incidence and quantity of intraocular fibrin were significantly lower in the patients treated with tPA than in the control group (p<0.05). The frequencies of synechiae were reduced by tPA injection. The capsule fibrosis noted after 3 months was significantly lower in the tPA group (p=0.027). No ocular side effects were noted after the tPA injections. Conclusions-Lysis of postcataract fibrin formation is accelerated and increased by a single intracameral injection of 10 mu g tPA in addition to standard antiinflammatory treatment. The findings suggest that the tPA injection reduces posterior capsule fibrosis, which still has to be addressed in larger study populations and with a long term follow up.

Pivotal trial of an autonomous AI-based diagnostic system for detection of diabetic retinopathy in primary care offices - Abramoff, MD; Lavin, PT; Birch, M; Shah, N; Folk, JC (NPJ DIGITAL MEDICINE, 2018)
Artificial Intelligence (AI) has long promised to increase healthcare affordability, quality and accessibility but FDA, until recently, had never authorized an autonomous AI diagnostic system. This pivotal trial of an AI system to detect diabetic retinopathy (DR) in people with diabetes enrolled 900 subjects, with no history of DR at primary care clinics, by comparing to Wisconsin Fundus Photograph Reading Center (FPRC) widefield stereoscopic photography and macular Optical Coherence Tomography (OCT), by FPRC certified photographers, and FPRC grading of Early Treatment Diabetic Retinopathy Study Severity Scale (ETDRS) and Diabetic Macular Edema (DME). More than mild DR (mtmDR) was defined as ETDRS level 35 or higher, and/or DME, in at least one eye. AI system operators underwent a standardized training protocol before study start. Median age was 59 years (range, 22-84 years); among participants, 47.5% of participants were male; 16.1% were Hispanic, 83.3% not Hispanic; 28.6% African American and 63.4% were not; 198 (23.8%) had mtmDR. The AI system exceeded all pre-specified superiority endpoints at sensitivity of 87.2% (95% CI, 81.8-91.2%) (> 85%), specificity of 90.7% (95% CI, 88.3-92.7%) (> 82.5%), and imageability rate of 96.1% (95% CI, 94.6-97.3%), demonstrating AI's ability to bring specialty-level diagnostics to primary care settings. Based on these results, FDA authorized the system for use by health care providers to detect more than mild DR and diabetic macular edema, making it, the first FDA authorized autonomous AI diagnostic system in any field of medicine, with the potential to help prevent vision loss in thousands of people with diabetes annually.

Indications and Visual Outcome of Penetrating Keratoplasty in Tertialy Eye Care Institute in Uttarakhand - Raj, A; Gupta, N; Dhasmana, R; Nagpal, RC; Bahadur, H; Maitreya, A (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2016)
Introduction: Corneal blindness forms significant proportion of visual blindness in developing countries and penetrating keratoplasty (PK) can restore vision for this. The prognosis of PK is dependent on the corneal diseases responsible for corneal blindness. Aim: To evaluate the indications and visual outcome of PK in tertiary eye care institute in Uttarakhand, Materials and Methods: Data was reviewed from the medical records of 145 PK done in Department of Ophthalmology, Himalayan Institute of Medical Sciences from January 2012 to October 2014. Analysis of data was done for evaluation of the indications and visual outcome by Paired student's t-test for hypothesis testing of grouped values of preoperative and last follow-up best corrected visual acuity in cases of optical and therapeutic grafts. A p-value <0.05 was considered statistically Results: In this study data of 145 eyes of 138 patients was reviewed. The most common indication for keratoplasty was corneal scarring including adherent leucoma 48 (33.10%). Therapeutic keratoplasty was done for 33 cases with maximum 30(20.68%) cases of infectious keratitis. One case of tectonic graft was included in therapeutic keratoplasty group for analysis. There was statistically significant difference (p=.0001) in best corrected visual acuity improvement from 1.39 logMAR +/- 0.022(SD) preoperatively to 0.367 logMAR +/- 0.44(SD) postoperatively and 1.4 logMAR +/-.000(SD) preoperatively to 0.16 logMAR +/- 0.57(SD) postoperatively for optical and therapeutic grafts respectively. Conclusion: Infective keratitis either active or healed was the major indication for keratoplasty. Poor prognosis indications were most common in this part of the country. The visual outcome following corneal transplantation was encouraging particularly in cases of optical keratoplasty.

Barriers between community screening for visual problems and treatments in a tertiary center - Ferreira, GD; Rezende, MA; Meneghim, RLFD; Schellini, SA (REVISTA DE SAUDE PUBLICA, 2018)
OBJECTIVE: To evaluate the effectiveness of mobile ophthalmic unit screenings and to investigate barriers between community care and resolution of the problem at a tertiary center. METHODS: This prospective study evaluated a convenience sample from 10 municipalities in Sao Paulo State, Brazil. Patients were assessed in the municipality by a mobile ophthalmic unit and underwent a complete ophthalmic consultation. Patients were referred as warranted to a tertiary hospital. RESULTS: The mobile ophthalmic unit screened 1,928 individuals and 714 (37%) were referred. The mean age of the referred patients was 57.12 (SD = 19.5) years with best corrected visual acuity of 0.37 (SD = 0.36) logMAR. Forty-seven (6.6%) patients were blind and 185 (26.5%) were visually impaired. Cataracts (44.7%) and pterygium (14.7%) accounted for most referrals. Of those referred, 67.1% presented to the tertiary center. The diagnosis by the mobile ophthalmic unit corresponded to the one by the tertiary center in 88.5% of the cases. There were a significantly higher number of blind and visually impaired persons among those who presented to the hospital. There was a significantly greater attendance among patients living in more distant municipalities from the reference center with a higher number of inhabitants and a greater number of ophthalmologists in the cities of origin (p < 0.05, all comparisons). Complete treatment was performed in 65.6% of patients, and loss to follow-up was the main cause of incomplete treatment in 50.7% of patients. A total of 313 cataract surgeries were performed, which reduced the number of blind patients from 20 to 2 and of visually impaired individuals from 87 to 2 (p < 0.001). CONCLUSIONS: Only 37% of the patients assessed by a mobile ophthalmic unit required referral to a tertiary hospital. Among the referred patients, 67.1% presented to the hospital, and complete resolution after treatment was approximately 65.5%. There was a significant improvement in visual acuity and a reduction in the prevalence of blindness and visual impairment postoperatively.

GPR158, an Orphan Member of G Protein-Coupled Receptor Family C: Glucocorticoid-Stimulated Expression and Novel Nuclear Role - Patel, N; Itakura, T; Gonzalez, JM; Schwartz, SG; Fini, ME (PLOS ONE, 2013)
Members of the large G protein-coupled receptor (GPCR) clan are implicated in many physiological and disease processes, making them important therapeutic drug targets. In the present study, we follow up on results of a pilot study suggesting a functional relationship between glucocorticoid (GC)-induced ocular hypertension and GPR158, one of three orphan members of the GPCR Family C. GC treatment increases levels of GPR158 mRNA and protein through transcriptional mechanisms, in cultured trabecular meshwork (TBM) cells derived from the eye's aqueous outflow pathway. Like treatment with GCs, transient overexpression of GPR158 stimulates cell proliferation, while siRNA knockdown of endogenous GPR158 has the opposite effect. Both endogenous and overexpressed GPR158 show an unusual subcellular localization pattern, being found almost entirely in the nucleus. However, when cells are treated with inhibitors of clathrin-mediated endocytosis, GPR158 is shifted to the plasma membrane. Mutation of a bipartite nuclear localization signal (NLS) in the 8th helix also shifts GPR158 out of the nucleus, but in this case the protein is found in vesicles localized in the cytoplasm. These results suggest that newly synthesized GPR158 first traffics to the plasma membrane, where it rapidly undergoes endocytosis and translocation to the nucleus. Significantly, mutation of the NLS abrogates GPR158-mediated enhancement of cell proliferation, indicating a functional requirement for nuclear localization. GPR158 overexpression upregulates levels of the cell cycle regulator cyclin D1, but mutation of the NLS reverses this. Overexpression of GPR158 enhances the barrier function of a TBM cell monolayer, which is associated with an increase in the levels of tight junction proteins ZO-1 and occludin, similar to reported studies on GC treatment. Regulated paracellular permeability controls aqueous outflow facility in vivo. Since GCs stimulate GPR158 expression, the result is consistent with a role for elevation of GPR158 expression in GC-induced ocular hypertension.

Infectious endophthalmitis in Boston keratoprosthesis: incidence and prevention - Behlau, I; Martin, KV; Martin, JN; Naumova, EN; Cadorette, JJ; Sforza, JT; Pineda, R; Dohlman, CH (ACTA OPHTHALMOLOGICA, 2014)
PurposeTo determine the cumulative worldwide incidence of infectious endophthalmitis and associated vision loss after Boston keratoprosthesis (B-KPro) Type I/II implantation and to propose both safe and inexpensive prophylactic antibiotic regimens. MethodsTwo retrospective methods were used to determine the incidence, visual outcomes and aetiologies of infectious endophthalmitis associated with the B-KPro divided per decade: (i) systematic review of the literature from 1990 through January 2013 and (ii) a surveillance survey sent to all surgeons who implanted B-KPros through 2010 with 1-year minimum follow-up. In addition, a single-Boston surgeon 20-year experience was examined. ResultsFrom 1990 through 2010, there were 4729 B-KPros implanted worldwide by 209 U.S. surgeons and 159 international surgeons. The endophthalmitis cumulative mean incidence declined from 12% during its first decade of use to about 3% during its second decade in the Unites States and about 5% internationally during the second decade. There remains a large incidence range both in the United States (1-12.5%) and internationally (up to 17%). Poor compliance with daily topical antibiotics is an important risk factor. While Gram-positive organisms remained dominant, fungal infections emerged during the second decade. ConclusionsDaily prophylactic topical antibiotics have dramatically reduced the endophthalmitis incidence. Although Gram-positive organisms are the most common aetiology, antimicrobials must be inclusive of Gram-negative organisms. Selection of prophylactic regimens should be tailored to local antibiotic susceptibility patterns, be cost-effective, and should not promote the emergence of antimicrobial resistance. An example of a broad-spectrum, low-cost prophylactic option for non-autoimmune patients includes trimethoprim/polymyxinB once daily.

Resource utilization and use of life-extending therapies and corticosteroids in prostate cancer patients with corticosteroid-sensitive comorbidities - Bui, CN; Wang, L; Baser, O (CURRENT MEDICAL RESEARCH AND OPINION, 2014)
Objectives: Corticosteroids (CSs) are used concomitantly with life-extending therapies (LETs) in patients with castration-resistant prostate cancer (CRPC). This study examined time to LETs, LETs and concomitant CS adherence, and monthly all-cause healthcare utilization and costs in patients with CPRC with and without CS-sensitive comorbidities in the Veterans Health Administration population. Methods: Patients had CRPC if records showed prostate cancer diagnosis, medical/surgical castration and >= 2 prostate-specific antigen increases through 1 June 2007-31 May 2012. CS-sensitive comorbidities were assessed 6 months prior to the index date. Adherence, defined as medication possession ratio (MPR) >= 0.8, among patients initiating LETs (cabazitaxel, docetaxel, or abiraterone acetate) before 30 November 2011, resource utilization and costs among patients with concomitant CS were assessed. Statistical analysis included descriptive, Cox proportional hazards, and logistic regression models. Results: Common CS-sensitive conditions among 12,128 patients with CRPC included hypertension (75.74%) and hyperlipidemia (54.69%). Those with glaucoma (hazard ratio [HR] = 0.67), ischemic heart disease (HR = 0.78), and peripheral vascular disease (PVD) (HR = 0.78) were less likely to be prescribed LETs (all p<0.01). Duration of LET was shorter among patients with CS-sensitive comorbidities (125.02 vs 133.08 days; p = 0.04) in the 6 month follow-up period. Among LET-treated patients with and without CS-sensitive comorbidities, less than half had MPR >= 0.8 (LET: 48.72% vs 54.05%; concomitant CS: 42.19% vs 40.54%, respectively). Cerebrovascular disease (odds ratio = 0.107; 95% confidence interval = 0.012 to 0.966) and PVD (odds ratio = 0.523; 95% confidence interval = 0.276 to 0.991) were associated with reduced CS adherence. Among patients with concomitant CS, those with CS-sensitive comorbidities had more inpatient stays than those without (20.45% vs 12.88%; p = 0.033), incurring higher monthly inpatient costs ($1157 vs $342; p<0.0001) and total costs ($5725 vs $4772; p = 0.036). Conclusion: CS-sensitive conditions influence initiation and duration of LETs, concomitant CS adherence, inpatient stays, and total costs. Future efforts should focus on specific strategies for treating prostate cancer patients with CS-sensitive comorbidities to ensure that they have appropriate access to LETs and to reduce costs and inpatient stays. Study limitations include the use of retrospective claims data and the relatively restricted subpopulation of older North American males.

Short-Term Effects of Overnight Orthokeratology on Corneal Epithelial Permeability and Biomechanical Properties - Yeh, TN; Green, HM; Zhou, YX; Pitts, J; Kitamata-Wong, B; Lee, S; Wang, SL; Lin, MC (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2013)
PURPOSE. To investigate the effects of 30 nights of overnight orthokeratology (OOK) on corneal epithelial permeability (P-dc) and corneal biomechanical properties. METHODS. BE Retainer and Paragon CRT lenses were used. Visits were scheduled approximately 4 hours after awakening at baseline and after 1, 5, 10, 14, and 30 days of treatment. Pdc was measured at baseline and at day 30, whereas corneal biomechanical properties and visual acuities (VAs) were measured at all visits. RESULTS. Thirty-nine neophytes and soft contact lens wearers completed the study. There was no difference in Pdc between baseline (In[Pdc] [95% confidence interval (CI)] = -2.65 [-2.80 to -2.50]) and day 30 (In[P-dc][CI] = -2.68 [-2.85 to -2.50]) (P = 0.88). Corneal hysteresis (CH) and corneal resistance factor (CRF) reduced significantly from baseline (CH [CI] = 10.89 [10.59-11.19] mm Hg and CRF [CI] = 10.35 [9.99-10.72] mm Hg) to day 30 (CH [CI] 10.59 [10.31-10.87] mm Hg and CRF [CI] = 9.58 [9.26-9.89] mm Hg) (P = 0.001 for CH and P < 0.001 for CRF). Posttreatment VA did not reach baseline targets, and the difference was worse with low-contrast letters. Asian individuals (n = 18) had significantly worse VA than non-Asian individuals (n = 21) under most conditions through day 5, and the difference extended through day 14 with low-contrast letters under mesopic conditions. The percentage of participants who achieved 20/20 uncorrected was 17% Asian and 40% non-Asian individuals after day 1 and reached 69% Asian and 83% non-Asian individuals at day 30. CONCLUSIONS. Thirty nights of OOK did not alter Pdc when measured 4 hours after awakening. OOK caused CH and CRF to decrease, but the changes were not clinically significant compared with diseased and postsurgical cases. Asian individuals, who had lower baseline CH in this study, responded slower to OOK based on early uncorrected VA and overrefraction measurements.

Relationships between laser flare photometry values and complications of uveitis - Gonzales, CA; Ladas, JG; Davis, JL; Feuer, WJ; Holland, GN (ARCHIVES OF OPHTHALMOLOGY, 2001)
Objective: To determine whether relationships exist between elevated laser flare photometry values and common abnormalities and complications associated with uveitis. Methods: We retrospectively studied all patients with uveitis on whom laser flare photometry measurements ("flare") were obtained (N = 111) at 2 academic medical centers. The first laser flare photometry values obtained for each patient were compared with the presence or absence of the following abnormalities or complications associated with uveitis: keratic precipitates, posterior synechiae, cataract, macular edema, optic disc edema, and glaucoma. In bilateral cases, the eye with the higher flare was used in primary analyses. Results: Flare was significantly higher in patients with posterior synechiae (P < .001) and in those with macular edema (P=.02) than in patients with uveitis who did not have these complications. Flare was significantly higher in patients with prior cataract surgery or cataract at the study visit than in those without cataracts (P=.001). There was no significant difference in flare between patients with and without keratic precipitates, optic disc edema, or glaucoma. No relationships were found between abnormalities or complications and the level of inflammatory cells or flare as determined by clinical assessment. We also identified an inverse relationship between flare and visual acuity that was not completely explained by the presence of complications in a stepwise regression model. Conclusions: Although causal relationships were not established, associations between flare and some complications of uveitis suggest that aqueous humor protein may be an important factor in the development of these problems. Consequently, laser flare photometry could play a role in predicting outcomes or monitoring therapy for patients with uveitis.

Health professionals' and service users' perspectives of shared care for monitoring wet age-related macular degeneration: a qualitative study alongside the ECHoES trial - Townsend, D; Reeves, BC; Taylor, J; Chakravarthy, U; O'Reilly, D; Hogg, RE; Mills, N (BMJ OPEN, 2015)
Objectives: To explore the views of eye health professionals and service users on shared community and hospital care for wet or neovascular age-related macular degeneration (nAMD). Method: Using maximum variation sampling, 5 focus groups and 10 interviews were conducted with 23 service users and 24 eye health professionals from across the UK (consisting of 8 optometrists, 6 ophthalmologists, 6 commissioners, 2 public health representatives and 2 clinical eye care advisors to local Clinical Commissioning Groups). Data were transcribed verbatim and analysed thematically using constant comparative techniques derived from grounded theory methodology. Results: The needs and preferences of those with nAMD appear to be at odds with the current service being provided. There was enthusiasm among health professionals and service users about the possibility of shared care for nAMD as it was felt to have the potential to relieve hospital eye service burden and represent a more patient-centred option, but there were a number of perceived barriers to implementation. Some service users and ophthalmologists voiced concerns about optometrist competency and the potential for delays with referrals to secondary care if stable nAMD became active again. The health professionals were divided as to whether shared care was financially more efficient than the current model of care. Specialist training for optometrists, under the supervision of ophthalmologists, was deemed to be the most effective method of training and was perceived to have the potential to improve the communication and trust that shared care would require. Conclusions: While shared care is perceived to represent a promising model of nAMD care, voiced concerns suggest that there would need to be greater collaboration between ophthalmology and optometry, in terms of interprofessional trust and communication.

Regression of lid-parallel conjunctival folds (LIPCOF) on topical treatment with liposic eye gel - A pilot study - Hoh, H; Schwanengel, M (KLINISCHE MONATSBLATTER FUR AUGENHEILKUNDE, 2006)
Introduction: The aim of this observation study was to determine whether regression of lid-parallel conjunctival folds (LIPCOF) can be induced by repeated and intensive treatment with a gel-forming tear substitute. Methods: In cooperation with the referring ophthalmologists, patients suffering from advanced dry eye condition were recruited. LIPCOF grades from 1 to 3 were included. Tear film break-up time (BUT) had to be less than 10sec and the Schirmer-I test less than 10mm. All patients recruited had been using watery tear substitutes. Examinations including visual acuity, slit lamp, fluorescein test, Schirmer-I test, BUT, LIPCOF were performed at baseline and after 2 weeks and 2 months. All examinations were done by the same physician at the Dietrich-Bonhoeffer Eye Hospital of Neubrandenburg. Exclusion criteria were severe eye diseases such as glaucoma, cataract, retinal detachment, history of intraocular or conjunctival surgery and disorders of the eye lids. Pretreatment with gels was not allowed. In the study, patients were treated with Liposic Eye Gel at least three times a day for a period of two months. Results: LIPCOFs regressed in 10 eyes of 5 patients (1 x male, 4 x female) from a mean grade of 2.58 at baseline to 2.29 after 2 months under Liposic treatment. This improvement is statistically significant (n = 10, p = 0.04). Schirmer-I test results had improved in the same time period from a mean of 6.4 mm at baseline to a mean of 8.1 mm after 2 months (n. s., n = 10, p = 0.73). BUT improved from a mean of 12.5 sec at baseline to a mean of 17.5 sec at the 2-month follow-up (n. s., n = 10, p = 0,085). In one patient the cornea was fluorescein-positive at baseline and stayed so throughout the follow-up. Liposic Gel was used by the patients between 3 to 8 times per day. Tolerance was excellent. Discussion: The study results show that the morphological signs of the dry-eye condition like LIPCOFs can be reversed by intensive treatment with Liposic Gel. The improvements in BUT and Schirmer-I test results confirm the adherence of the patients to the treatment schedule. Conclusion: This pilot study provides the statistical data necessary for designing a major treatment study to prove not only the reversibility of LIPCOF, but also the dependence of the possible improvement on the grade of LIPCOF stage on the age of the patient and on other criteria.

Changes in attitudes and practices of optometrists in their management of diabetic retinopathy after the release of NHMRC guidelines - Wright, SE; McKay, R; Taylor, KI; Keeffe, JE; McCarty, CA; Working Grp Evaluation NHMRC R (CLINICAL AND EXPERIMENTAL OPHTHALMOLOGY, 2001)
The purpose of this study was to document attitudes and practices of Australian optometrists in their management of diabetic retinopathy prior to the release of the National Health and Medical Research Council (NHMRC) Clinical Practice Guidelines for the Management of Diabetic Retinopathy and at two time points following their release. A self- administered questionnaire was mailed to a stratified random sample of 500 Australian optometrists at the three time points. The same sample was used for the first two surveys and a new random sample was drawn for the second follow-up survey. The response to the three questionnaires was 86%, 80% and 84%, respectively. More than 90% of optometrists reported receiving a copy of the guidelines and 82% reported receiving the supplementary Retinopathy Chart. Fifty-seven per cent reported having read the guidelines at least once in entirety and 65% reported that they refer to the Retinopathy Chart at least monthly in their clinical practice. There was a significant decrease in the number of optometrists who reported that patient unwillingness to be dilated and their fear of precipitating angle closure glaucoma were moderate or major barriers to performing dilated ophthalmoscopy. Concomitantly, the percentage of optometrists who reported that they often or always perform dilated ophthalmoscopy on new patients with diabetes increased significantly from 74.5% (95% confidence limit = 70.2, 78.8) to 81.5% (95% confidence limit = 77.5, 85.5). There have been some significant changes in the self-reported management practices of optometrists in relation to diabetic retinopathy since the release of the NHMRC guidelines and Retinopathy Chart.

Tacrolimus eye drops as monotherapy for vernal keratoconjunctivitis: a randomized controlled trial - Muller, EG; dos Santos, MS; Freitas, D; Gomes, JAP; Belfort, R (ARQUIVOS BRASILEIROS DE OFTALMOLOGIA, 2017)
Purpose: To assess the efficacy of monotherapy using tacrolimus eye drops versus sodium cromoglycate for the treatment of vernal keratoconjunctivitis (VKC). Methods: Randomized double-masked controlled trial comparing the efficacy of tacrolimus 0.03% eye drops t.i.d. (Group 1) with sodium cromoglycate 4% eye drops t.i.d. (Group 2) for the symptomatic control of VKC at days 0, 15, 30, 45, and 90 of follow-up. Visual acuity, intraocular pressure, and other complications were evaluated to assess safety and side effects. Results: In total, 16 patients were included, with 8 enrolled in each group. Two patients from Group 2 were excluded from the analysis at days 45 and 90 because of corticosteroid use. Most patients were male (81.8%) and presented with limbal VKC (56.3%). There were statistically significant differences in favor of tacrolimus in the following severity scores: itching at day 90 (p = 0.001); foreign body sensation at day 15 (p = 0.042); photophobia at day 30 (p = 0.041); keratitis at day 30 (p = 0.048); and limbal activity at days 15 (p = 0.011), 30 (p = 0.007), and 45 (p = 0.015). No relevant adverse effects were reported, except for a burning sensation with tacrolimus, though this did not compromise treatment compliance. Conclusion: Treatment with tacrolimus was superior to sodium cromoglycate when comparing severity scores for symptoms of itching, foreign body sensation, and photophobia, as well as for signs of limbal inflammatory activity and keratitis.

Improvement of Subjective Symptoms and Eye Complications When Changing From 2-Week Frequent Replacement to Daily Disposable Contact Lenses in a Subscriber Membership System - Ichijima, H; Karino, S; Sakata, H; Cavanagh, HD (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2016)
Purpose: Subjective symptoms and other eye complications were assessed and retrospectively compared in patients belonging to a proprietary membership system who switched from 2-week frequent replacement (2WFR) wear to daily disposable (DD) lens use. Methods: Questionnaire responses were completed by all patients for a 5-year interval between October 2008 and September 2013 from 83 wearers in three Japanese clinics (59 female and 24 male; average age: 33.4 +/- 10.9 years). Complications were recorded for each patient at times of reexamination. Results: Over the 5-year observation period, the 83 patients wore lenses for more than 26 months. The average duration of use of 2WFR lenses was 14.5 +/- 2.7 days/lens (n=83) and subsequently 1.03 +/- 0.12 days/lens (n=83) for DD lenses. Compliance with the duration of use was consistently good as monitored by requests for lens resupply in both wearing modalities. The subjective complaint of dryness tended to consistently show improvement by the change to DD wear: 18.1% vs. 30.1% (P=0.10, Fisher exact test). Among eye complications noted in each group, the occurrence of superficial punctate keratitis (SPK) was significantly decreased in DD wear: 9.6% vs. 26.5% (P=0.008, Fisher exact test). The main reasons given by patients for changing to DD wear were (1) "DD lens wear was more hygienic" (78.6%) and (2) "DD lens use is more convenient for travel/business trips" (64.3%). Comments after the switch in wear were (1) "easy and convenient" (95.7%) and (2) "I don't have to worry about expiration dates" on solutions (57.1%). Overall, 95.7% of wearers making the change answered as "satisfied" and "mostly satisfied." Conclusions: In the subscription membership program, which provided free lens replacement and/or reexamination, individual compliance with duration of wear in 2WFR wear cycles was good; however, these patients switching to DD wear tended to have improvement in their subjective complaints of dryness and objectively demonstrated a significant reduction of SPK at follow-up examinations.

Use of Health Care Claims Data to Study Patients with Ophthalmologic Conditions - Stein, JD; Lum, F; Lee, PP; Rich, WL; Coleman, AL (OPHTHALMOLOGY, 2014)
Objective: To describe what information is or is not included in health care claims data, provide an overview of the main advantages and limitations of performing analyses using health care claims data, and offer general guidance on how to report and interpret findings of ophthalmology-related claims data analyses. Design: Systematic review. Participants: Not applicable. Methods: A literature review and synthesis of methods for claims-based data analyses. Main Outcome Measures: Not applicable. Results: Some advantages of using claims data for analyses include large, diverse sample sizes, longitudinal follow-up, lack of selection bias, and potential for complex, multivariable modeling. The disadvantages include (a) the inherent limitations of claims data, such as incomplete, inaccurate, or missing data, or the lack of specific billing codes for some conditions; and (b) the inability, in some circumstances, to adequately evaluate the appropriateness of care. In general, reports of claims data analyses should include clear descriptions of the following methodological elements: the data source, the inclusion and exclusion criteria, the specific billing codes used, and the potential confounding factors incorporated in the multivariable models. Conclusions: The use of claims data for research is expected to increase with the enhanced availability of data from Medicare and other sources. The use of claims data to evaluate resource use and efficiency and to determine the basis for supplementary payment methods for physicians is anticipated. Thus, it will be increasingly important for eye care providers to use accurate and descriptive codes for billing. Adherence to general guidance on the reporting of claims data analyses, as outlined in this article, is important to enhance the credibility and applicability of findings. Guidance on optimal ways to conduct and report ophthalmology-related investigations using claims data will likely continue to evolve as health services researchers refine the metrics to analyze large administrative data sets. (C) 2014 by the American Academy of Ophthalmology.

Pediatric intraocular lens implantation - Surgical results and complications in more than 300 patients - Zwaan, J; Mullaney, PB; Awad, A; Al-Mesfer, S; Wheeler, DT (OPHTHALMOLOGY, 1998)
Objective: The study aimed to review pediatric intraocular lens (IOL) implantations performed in the authors' institution for the past 7 years. Study Design: The study design was a retrospective chart review. Participants: All children who underwent IOL placement between January 1, 1989, and January 31, 1996, at ages 2 to 16 years were studied. Follow-up was a minimum of 6 months up to 4 years with an average of 13 months. Intervention: Placement of a primary or secondary posterior chamber IOL was performed, Main Outcome Measures: Visual acuity and possible complications were tabulated, Results: Fifty-seven percent of the cataracts were caused by trauma, and 37% were infantile cataracts, Visual acuities of 20/40 or better were attained in 44% of eyes and visual acuities of 20/50 to 20/80 were attained in 27% of eyes. Visual acuities were better in children older than 4 years of age (P = 0.001). Compliance with amblyopia therapy improved vision (P = 0.004). Fibrinous membranes occurred in 41 eyes (13%), and posterior capsule opacification occurred in 120 eyes (39%). There were no significant differences in visual outcome and complications between primary and secondary implants (17%) or between capsular bag and sulcus fixation (27%). The first stable postoperative refraction was predicted accurately in most patients, based on the Sanders-Retzlaff-Kraff II (SRK II) formula and intraoperative corneal curvature and axial length determinations. The mean refraction differed from the goal by only +0.28 diopter and 84% were within +/-2 diopters. A few patients showed large overcorrections or undercorrections. On average, no myopic shift occurred. Conclusions: Short-term results of IOLs implanted in children older than 2 years of age were favorable. Visual acuities obtained were better than 20/80 in 71% despite a high prevalence (28%) of penetrating trauma. Major complications were rare.

Optometrist referrals to an emergency ophthalmology department: a retrospective review to identify current practise and development of shared care working strategies, in England - Mas-Tur, V; Jawaid, I; Poostchi, A; Verma, S (EYE, 2021)
Background Direct referrals from optometrists account for up to 10% eye casualty attendances. Despite this, there remains a paucity of literature on optometrist referrals to eye casualty. A better understanding of these referrals could be helpful in the development of shared care emergency pathways. Diagnostic agreement between optometrists and ophthalmologists for emergency referrals can be used to identify areas for development of shared care working strategies in emergency ophthalmology. Methods A retrospective evaluation of 1059 consecutive optometric emergency referrals to Moorfields Eye Hospital was conducted. Referrals were only included when a letter or documentation for the reason for referral was provided. Diagnostic information from the referring optometrist and casualty doctor was summarised for each patient by an investigator (VMT) and recorded on a single spreadsheet. These clinical summaries were compared by a second independent investigator (IJ) and marked as agreeing, disagreeing or uncertain. Each clinical summary was then mapped to a diagnostic category using key word searches which were manually re-checked against the original summaries. Information on the timing of the referral and the outcome at the emergency department visit was also collated. Inter-observer agreement for diagnostic categories was measured using kappa coefficients. Results Diagnostic agreement ranged between kappa 0.59 and 0.87. It was best for diagnoses within the red eye category (kappa 0.87). Compliance with College of Optometrists referral guidance ranged between 11 and 100%. More than half of referrals for elevated intra-ocular pressure were discharged at the eye casualty visit. Overall, 54% of patients were managed with advice alone, 39% required treatment following referral and 7% required onward referral from eye casualty. Conclusion The majority of patients referred by optometrists were managed with advice alone. A collaborative approach at the point referral could be helpful to improve referral efficiency.

Contact Lens Complications in an Urgent-Care Population: The University of California, Los Angeles, Contact Lens Study - Lee, SY; Kim, YH; Johnson, D; Mondino, BJ; Weissman, BA (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2012)
Objectives: This is a prospective study in an urgent-care ophthalmic setting to investigate contact lens (CL) complications and their association with extended wear (EW). Methods: Data on CL designs, care system(s), and ocular complications were collected over a 6-month period. Results: One thousand three hundred and sixty-nine patients presented to the Jules Stein Eye Institute urgent care with symptoms of eye problems. Of these, 56 were identified with diagnoses etiologically associated with CL wear, and 49 were studied. The five most common ocular diagnoses found in our study were in the following order: epithelial staining or abrasion/epithelial defect, conjunctival injection, papillae, corneal neovascularization, and presumed microbial keratitis (PMK). Fifteen of 49 patients were diagnosed with PMK. The mean number of complications was 3.43 per eye. Most of the patients (65%) reported some form of EW. Analysis of the patients with PMK showed an association with EW. There seemed to be no statistical difference in the number of complications per symptomatic eye with hydrogel and silicone hydrogel lenses although 13 of the15 patients with PMK were silicone hydrogel wearers. Conclusions: We studied various aspects of care and compliance in an urgent-care population and found that most of our urgent-care patients slept with CLs on their eyes. Symptomatic CL wear-related complications, and specifically MK, strongly correlate with EW with less relation to lens design, material, and wear modality. We therefore conclude that CL EW is a risk factor leading to urgent-care visits.

Self-reported Use of Eye Care Among Adult Chinese Americans: The Chinese American Eye Study - Jiang, XJ; Varma, R; Torres, M; Hsu, CY; McKean-Cowdin, R; Chinese Amer Eye Study Grp (AMERICAN JOURNAL OF OPHTHALMOLOGY, 2017)
PURPOSE: To identify the prevalence and determinants of self-reported eye care use among Chinese Americans. DESIGN: Population-based, cross-sectional study. PARTICIPANTS: A total of 4582 Chinese Americans 50 years and older residing in Monterey Park, California. METHODS: Multivariable logistic regression analyses based on Andersen's Behavioral Model of Health Services Use were conducted to identify predisposing, enabling, and need variables associated with self-reported eye care use. MAIN OUTCOME MEASURES: Prevalence of self reported use assessed as eye care visit in the past 12 months, dilated eye examination in the past 12 months, and ever having had a dilated examination, and odds ratios for factors associated with these measures. RESULTS: Overall, 36% of participants reported an eye care visit and 21% reported a dilated examination in the past 12 months. forty-eight percent reported ever having had a dilated eye examination. Older age, female sex, preference for English, more education, health and vision insurance, a usual place for health care, currently driving, a greater number of comorbidities, and lower vision-specific quality-of-life (NEI VFQ-25) scores were associated with higher odds of reporting use of eye care. CONCLUSIONS: Use of eye care among Chinese Americans was found to be as low as what is reported for African Americans and Hispanics, and lower than what is reported for whites. Multiple modifiable factors are associated with use of eye care among the rapidly growing Chinese American population. Culturally sensitive interventions targeting these factors should be a priority. Further research is needed to investigate how findings from this group of Chinese Americans reflect other Asian Americans that are different in language and ethnicity. (C)2017 Elsevier Inc. All rights reserved.

Outcomes of phacoemulsification and intraocular lens implantation in microphthalmos and nanophthalmos - Day, AC; MacLaren, RE; Bunce, C; Stevens, JD; Foster, PJ (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2013)
PURPOSE: To evaluate the outcomes of phacoemulsification and intraocular lens (100 implantation in microphthalmos and nanophthalmos. SETTING: Moorfields Eye Hospital, London, United Kingdom. DESIGN: Retrospective case series. METHODS: Eyes with an axial length (AL) less than 21.0 mm had elective phacoemulsification and IOL implantation. RESULTS: One hundred three eyes (63 patients) were enrolled. The median AL was 20.65 mm (interquartile range [IQR], 20.26 to 20.86) and the median follow-up, 6.3 months. Complications occurred in 16 cases (15.5%). Zonular dehiscence, severe uveitis, and aqueous misdirection accounted for the majority of complications. Complication rates were 6 (7.3%) of 82 cases with an AL from 20.0 to 21.00 mm and 10 (47.6%) of 21 cases with an AL less than 20.0 mm (P=.0001). Only AL (odds ratio [OR], 0.52 per mm; P <=.0005) and abnormal intraocular pressure (IOP) of 22 mm Hg or more or on topical IOP control (OR, 10.1; P=.001) were significant independent risk factors for complications. For the cohort after adjusting for abnormal IOP, an AL less than 20.5 mm was associated with a 4 times higher odds of any complication (P=.028), an AL less than 20.0 mm was associated with a 15 times higher odds of any complication (P <=.0005), and an AL less than 19.00 mm was associated with a 21 times higher odds of any complication (P <=.0005). CONCLUSIONS: Phacoemulsification and IOL implantation in microphthalmos/nanophthalmos was challenging but appears safer than previously reported. A shorter AL and abnormal IOP were significant risk factors for complications. Financial Disclosure: No author has a financial or proprietary interest in any material or method mentioned. J Cataract Refract Surg 2013; 39:87-96 (C) 2013 ASCRS and ESCRS

Addressing inequalities in eye health with subsidies and increased fees for General Ophthalmic Services in socio-economically deprived communities: a sensitivity analysis - Shickle, D; Todkill, D; Chisholm, C; Rughani, S; Griffin, M; Cassels-Brown, A; May, H; Slade, SV; Davey, CJ (PUBLIC HEALTH, 2015)
Objectives: Poor knowledge of eye health, concerns about the cost of spectacles, mistrust of optometrists and limited geographical access in socio-economically deprived areas are barriers to accessing regular eye examinations and result in low uptake and subsequent late presentation to ophthalmology clinics. Personal Medical Services (PMS) were introduced in the late 1990s to provide locally negotiated solutions to problems associated with inequalities in access to primary care. An equivalent approach to delivery of optometric services could address inequalities in the uptake of eye examinations. Study design: One-way and multiway sensitivity analyses. Methods: Variations in assumptions were included in the models for equipment and accommodation costs, uptake and length of appointments. The sensitivity analyses thresholds were cost-per-person tested below the GOS1 fee paid by the NHS and achieving break-even between income and expenditure, assuming no cross-subsidy from profits from sales of optical appliances. Results: Cost per test ranged from 24.01 pound to 64.80 pound and subsidy required varied from 14,490 pound to 108,046 pound. Unused capacity utilised for local enhanced service schemes such as glaucoma referral refinement reduced the subsidy needed. Conclusions: In order to support the financial viability of primary eye care in socio-economically deprived communities, income is required from additional subsidies or from sources other than eye examinations, such as ophthalmic or other optometric community services. This would require a significant shift of activity from secondary to primary care locations. The subsidy required could also be justified by the utility gain from earlier detection of preventable sight loss. (C) 2014 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved.

Why Non-contact Tonometry Tests Cannot Evaluate the Effects of Corneal Collagen Cross-linking - Ortilles, A; Rodriguez-Matas, JF; Ariza-Gracia, MA; Pascual, G; Calvo, B (JOURNAL OF REFRACTIVE SURGERY, 2017)
PURPOSE: To assess the feasibility of characterizing and following up the mechanical behavior of the corneal tissue after corneal cross-linking (CXL) by using a combined mechanical (in vivo indentation and in vitro uniaxial tensile tests) and morphological (immunohistochemistry) experimental protocol. METHODS: CXL (3 mW/cm(2); 370 nm) for 20 minutes (total dose 3.6 J/cm(2)) was performed on 12 New Zealand rabbits. The mechanical behavior of the cornea was characterized in small and large strain regimens using an in vivo indentation test with a laboratory device and an in vitro uniaxial tensile test, respectively. These tests and corneal immunohistochemistry were performed before (PreCXL) and on the 7th (PostCXL-7d) and 56th days (PostCXL-56d) after CXL. The intraocular pressure and corneal thickness were measured before each test. RESULTS: For the indentation tests, significant differences were found between PreCXL and PostCXL-7d and between PostCXL-7d and PostCXL-56d, but not between PreCXL and PostCXL-56d. On average, for the small strain regimen, PostCXL-7d corneas showed the most compliant behavior, with progressive recovery of the corneal stiffness over time. For the large strain regimen, significant differences in the maximum tangent modulus between PreCXL and PostCXL-7d and between PreCXL and PostCXL-56d were observed for the uniaxial tensile tests, with no significant differences between PostCXL-7d and PostCXL-56d. Immunohistochemistry showed a lack of cells in the anterior stroma at PostCXL-7d, but at PostCXL-56d the cell density and morphology were comparable to PreCXL. CONCLUSIONS: Indentation tests cannot characterize the changes in the corneal collagen scaffold caused by the CXL, but the uniaxial test can. However, indentation tests can assess the recovery of keratocyte density after CXL.

Aerosol beclomethasone dipropionate spray compared with theophylline as primary treatment for chronic mild-to-moderate asthma - Reed, CE; Offord, KP; Nelson, HS; Li, JT; Tinkelman, DG; Amer Acad Allergy Asthma Immunology Beclometha (JOURNAL OF ALLERGY AND CLINICAL IMMUNOLOGY, 1998)
Background: Inhaled corticosteroids and oral theophylline are effective treatments for moderate asthma. Objective: We sought to compare the benefits and adverse reactions of theophylline and aerosol beclomethasone spray. Methods: A multicenter, double-blind, double-placebo, randomized, controlled trial of 1-year duration was performed. Seven hundred forty-seven patients with asthma received either beclomethasone dipropionate aerosol spray (84 mu g four times per day) or sustained-release theophylline twice per day in doses adjusted for optimum control of the disease. The main outcome measures were daily diary of symptoms and peak flow rates (recorded on a mark-sense computer-readable form); supplemental bronchodilator use; doctor's office or hospital visits and absence from work or school; spirometry; methacholine testing; adverse experiences; and cortisol blood measurements. Results: Both treatment strategies reduced symptoms promptly and achieved low absenteeism from work or school and low rates of emergency treatment for asthma. Both maintained nearly normal pulmonary function. Beclomethasone was statistically significantly more effective in reducing symptoms, supplemental bronchodilator and systemic glucocorticoid doses, bronchial hyperresponsiveness, and eosinophilia. However, the magnitude of these differences was small. Theophylline caused more headache, nervousness, insomnia, and gastrointestinal distress, and more patients discontinued treatment because of side effects. Beclomethasone caused more oropharyngeal candidiases and hoarseness and reduced morning plasma cortisol levels before and after cosyntropin. It reduced the rate of growth in children, No new cataracts or glaucoma developed. Conclusion: Theophylline effectively controlled symptoms at lower than the customarily recommended blood level. The risk/benefit profiles of these agents suggest that inhaled corticosteroids may be the preferred agent for most adult patients and for some children.

Preventing sight loss in older people. A qualitative study exploring barriers to the uptake of regular sight tests of older people living in socially deprived communities in South Wales - Biddyr, S; Jones, A (PUBLIC HEALTH, 2015)
Objectives: This paper describes research findings that try to understand some of the reasons that prevent older people in deprived communities in South Wales from accessing NHS funded sight tests and leads to a discussion of suitable interventions that seek to improve access to primary eye care services and prevent avoidable sight loss. Study design: Data were collected from eight focus groups (n = 63) of mixed gender and ages (60-80+ years), of white origin living in deprived communities in South Wales. Individuals were recruited for the focus groups by extensively publicizing the project, with a range of health and older people's community services and groups such as sheltered housing complexes, stroke support groups and coffee morning groups. The study included people who attended optometry services and people not engaged with services. A purposive sampling technique summarizes the sampling approach taken, an approach which the team utilized to recruit 'information rich' cases, namely individuals, groups and organizations that provided the greatest insight into the research question. Methods: Focus groups were recorded and transcribed verbatim. Data underwent thematic content analysis and subsequent interpretations were corroborated by expert advisors and a project steering group. Results: Cost was perceived as a significant barrier to accessing sight tests, particularly in relation to purchasing glasses. Other barriers included the perceived pressure to buy glasses associated with visits to the optometrists; poor understanding of the purpose of a sight test in a health prevention context and acceptance of deteriorating sight loss due to the ageing process. Conclusion: Areas of improvement for the delivery of preventative eye health services to older people are identified, as are areas for reflection on the part of those who work within the eye health industry. (C) 2014 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved.

Scleral Contact Lenses as an Alternative to Tarsorrhaphy for the Long-Term Management of Combined Exposure and Neurotrophic Keratopathy - Weyns, M; Koppen, C; Tassignon, MJ (CORNEA, 2013)
Purpose: Most ophthalmologists are unaware of the therapeutic applications of gas-permeable scleral contact lenses for the prevention and treatment of ocular complications in patients with facial nerve palsy and concomitant neuroparalysis. Methods: The case reports refer to 3 patients who developed unilateral lagophthalmos and corneal anesthesia after an acoustic neuroma or intracranial tumor resection. Two patients explicitly requested a tarsorrhaphy to be opened because they were incapacitated by the limited visual acuity and visual field. Tarsorrhaphy was not an acceptable aesthetic solution for the third patient. Fluid-ventilated scleral lenses were fitted because they protect the cornea by creating a precorneal fluid reservoir while optimizing visual acuity. Results: The follow-up periods were 3, 17, and 18 years. Two patients wear the contact lenses full time, but the wearing time is limited to 10 hours per day for the third patient. All patients were instructed not to wear their lenses while sleeping. Two eyes required a corneal transplant, but lens wear could be resumed 4 to 6 weeks after transplantation. The learning curve for the insertion and removal of this large-diameter lens is the main obstacle for a patient, especially when there is loss of corneal sensation. Conclusion: Scleral lens wear is a valid long-term alternative to standard treatment options such as tarsorrhaphy for patients with corneal exposure and corneal anesthesia as a consequence of postsurgery facial nerve paralysis. Scleral contact lenses provide these patients with effective protection of the ocular surface in an aesthetically acceptable way while optimizing visual function.

Perioperative complications of intraocular lens exchange in patients with opacified Aqua-Sense lenses - Dagres, E; Khan, MA; Kyle, GM; Clark, D (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2004)
Purpose: To evaluate the perioperative complications of intraocular lens (IOL) exchange in 25 eyes of 22 patients with opacified Aqua-Sense(R) IOLs (Ophthalmic Innovations International). Setting: Department of Ophthalmology, University Hospital Aintree, Liverpool, United Kingdom. Methods: The study comprised 22 patients (25 eyes) who had previous phacoemulsification and implantation of Aqua-Sense single-piece hydrophilic acrylic IOLs in the capsular bag and developed severe late opacification of the IOL. All patients reported glare and deterioration in vision. The IOLs were explanted and replaced with new lenses. The perioperative complications were evaluated. The best corrected visual acuity (BCVA) before and after surgery was compared. Results: In 24 eyes, the opacification was complete, involving the optic, haptics, and substance of the IOLs. Uneventful IOL exchange and placement of a new IOL in the bag was achieved in 13 eyes (52%). Complications occurred in the remaining 12 eyes (48%). Ten eyes (40%) developed zonular dehiscence, 4 (16%) of which were managed with anterior chamber IOL implantation. One eye (4%) developed posterior capsule rupture and 1 eye (4%), posterior capsule rupture and zonular dehiscence. The cornea decompensated in 2 eyes (8%). One eye (4%) developed Pseudomonas keratitis. The mean BCVA (decimal scale) before and after IOL exchange was 0.57 +/- 0.24 and 0.60 +/- 0.28, respectively. There was no significant difference in visual acuity between before and after IOL exchange (P = .782, paired t test). Conclusions: Explantation of Aqua-Sense IOLs was challenging because of the tight adherence of the optic and haptics to the capsule. Long-term follow-up of patients with Aqua-Sense IOLs should be maintained.

The Effects of Nd: YAG Laser Capsulotomy on Visual Acuity, Macular Thickness, and Intraocular Pressure in Diabetic Patients - Turkoglu, EB; Celik, E; Aksoy, O; Alagoz, G (TURK OFTALMOLOJI DERGISI-TURKISH JOURNAL OF OPHTHALMOLOGY, 2015)
Objectives: To compare macular thickness, best-corrected visual acuity (BCVA), and intraocular pressure (IOP) changes after Nd: YAG laser capsulotomy for posterior capsule opacification (PCO) in diabetic and non-diabetic eyes. Materials and Methods: Thirty-six eyes of 25 diabetic patients and 40 eyes of 25 non-diabetic patients were included. All patients was treated with Nd: YAG laser capsulotomy. Macular thickness measured by optical coherence tomography (OCT), IOP, and BCVA were evaluated before and 1 week, 1 month, and 3 months after the procedure. Re sults: There was no difference between the two groups in age, gender, and applied laser technique. The time interval between cataract surgery and laser capsulotomy was shorter in the group of diabetic patients (p=0.009). In both groups, BCVA was significantly increased 1 week after laser capsulotomy (respectively, p=0.023, p=0.016). However, there was no statistically significant difference between the two groups. There was no significant difference in macular thickness before and after the procedure between the two groups (p>0.05). However, in group 1, cystoid macular edema was observed in 2 eyes during follow-up. Despite prophylactic treatment, IOP remained around 21-30 mmHg in 3 patients in group 1 and 4 patients in group 2 at first day and at the end of the 1st week. IOP was controlled except in one glaucoma patient. In the two groups, IOP values before and after laser capsulotomy were not statistically significantly different (p>0.05). At first day, + 2 cells in the anterior chamber were detected in 3 patients in group 1 and in 2 patients in group 2; at 1 week after routine topical steroid treatment, anterior chamber reaction was not observed. Conclusion: It is known that there is a breakdown in the blood-aqueous and inner blood-retinal barriers in diabetes, however, no difference was determined in visual improvement, macular thickness, and IOP when comparing diabetic to non-diabetic eyes. We observed that Nd: YAG laser capsulotomy is a safe and effective method for posterior capsular opacification in diabetic and non-diabetic patients.

Early changes in tear film protein profiles after femtosecond LASIK surgery - Nattinen, J; Makinen, P; Aapola, U; Orsila, L; Pietila, J; Uusitalo, H (CLINICAL PROTEOMICS, 2020)
Background Femtosecond laser-assisted in situ keratomileusis (LASIK) has proven to be an efficacious, predictable, and safe procedure for the correction of refractive errors. We examined the early tear protein changes of patients undergoing LASIK surgery in order to better understand the mechanisms and proteins related to laser corneal surgery and initial recovery. Methods Corneal flaps were created with Ziemer FEMTO LDV Z6 I femtosecond laser and stroma was ablated using Wavelight EX500 excimer laser. Tear samples were collected preoperatively as well as 1.5 h and 1 month after LASIK treatment using glass microcapillary tubes. Relative quantification of tear proteins was performed with sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS). Results SWATH-MS revealed that 158 proteins had altered expression levels 1.5 h after the operation. Two-thirds of these proteins, mostly connected to migration and inflammation response, returned to preoperative levels within the first postoperative month. The other proteins, which did not return to baseline levels, included proteins connected to for example epithelial barrier function. We also identified several proteins, which correlated with surgical variables, such as the amount of correction, flap thickness and flap diameter. Conclusions The present study showed that an uneventful femtosecond LASIK refractive surgery induced a significant immune cell migration and inflammation-associated changes in tear proteomics profile quickly after the operation, but the expression of most proteins recovered almost completely to the preoperative levels within the first month. The individual proteins identified in our study are potential targets for the follow-up and modification of LASIK-induced biochemical processes.

Comparing Adherence and Persistence Across 6 Chronic Medication Classes - Yeaw, J; Benner, JS; Walt, JG; Sian, S; Smith, DB (JOURNAL OF MANAGED CARE PHARMACY, 2009)
BACKGROUND: The National Quality Forum recently endorsed the proportion of days covered (PDC)-a measure of medication adherence-as an indicator of quality in drug therapy management. OBJECTIVE: To inform initial efforts to improve the quality of drug therapy management, we compared PDC and persistence among new users of 6 commonly used chronic medication categories. METHODS: A retrospective analysis of pharmacy claims in a database of more than 64 million members enrolled in 100 health plans assessed persistence and adherence to drug therapy in 6 chronic conditions. Patients were included in the analysis if they initiated a prescription drug of interest in any of 6 drug classes-prostaglandin analogs, statins, bisphosphonates, oral antidiabetics, angiotensin 11 receptor blockers (ARBs), and overactive bladder (DAB) medications-between January 1 and December 31, 2005. The first claim for a drug of interest during this period was considered a patient's index date. Patients were required to have a minimum of 12 months of continuous enrollment both preceding and following their index date. New users of a treatment were identified by excluding patients who filled a prescription for any drug in the same class during the previous 12 months and were followed fora minimum of 12 months. Nonpersistence was defined as discontinuation of the therapy class following an allowed gap between refills-30-, 60-, and 90-day refill gaps were used. Adherence was defined as a continuous measure of the proportion of days covered (PDC) during the 12-month post-index period. Logistic regression analyses predicted (a) nonpersistence during the 12-month post-index period and (b) adherence (PDC) of at least 80%, with drug class as the predictor variable of interest, controlling for demographic variables, insurance and plan type, history of hospitalization, Charlson comorbidity score, copayment for index medication, and number of medications at index. RESULTS: A total of 167,907 patients were identified across 6 cohorts. Using the 60-day gap, 6-month persistence rates were prostaglandin analogs 47%, statins 56%, bisphosphonates 56%, oral antidiabetics 66%, ARBs 63%, and DAB medications 28%. After the first 90 days of therapy, relative persistence was stable across cohorts, and rates declined consistently from 6 months post-index to study end. Logistic regression models showed that oral antidiabetic users had a 59%, 36%, 37%, and 79% decreased risk of nonpersistence in a 12-month follow-up period compared with patients taking prostaglandin analogs, statins, bisphosphonates, or DAB medications, respectively. Risk of nonpersistence decreased with increasing age. Mean (SD) 12-month adherence rates were: prostaglandin analogs 37% (26%), statins 61% (33%), bisphosphonates 60% (34%), oral antidiabetics 72% (32%), ARBs 66% (32%), and DAB medications 35% (32%). Logistic regression indicated that oral antidiabetic use was a significant predictor of adherence (PDC) of at least 80% compared with other therapy classes. Adjusted odds ratios for oral antidiabetics were 17.60 (95% confidence interval [CI] = 15.38-20.14) versus prostaglandin analogs, 2.06 (95% Cl = 1.99-2.12) versus statins, 1.92 (95% Cl = 1.83-2.02) versus bisphosphonates, 1.29 (95% Cl = 1.24-1.34) versus ARBs, and 5.77 (95% Cl = 5.38-6.19) versus DAB medications. CONCLUSION: This analysis of adherence (PDC) and persistence across a sample of 6 chronic therapies found variable but uniformly suboptimal medication use. Adherence to prostaglandin eye drops and DAB medications was lower than to cardiovascular, oral antidiabetic, and oral osteoporosis therapies. These findings provide useful baseline information for the development of initiatives to improve the quality of drug therapy management.

Management of traumatic hyphema - Walton, W; Von Hagen, S; Grigorian, R; Zarbin, M (SURVEY OF OPHTHALMOLOGY, 2002)
Hyphema (blood in the anterior chamber) can occur after blunt or lacerating trauma, after intraocular surgery, spontaneously (e.g., in conditions such as rubeosis iridis,juvenile xanthogranuloma, iris melanoma, myotonic dystrophy, keratouveitis (e.g., herpes zoster), leukemia, hemophilia, von Willebrand disease, and in association with the use of Substances that. alter platelet or thrombin function (e.g., ethanol, aspirin, warfarin). The purpose of this review is to consider the management of hyphemas that occur after closed globe trauma. Complications of traumatic hyphema include increased intraocular pressure, peripheral anterior synechiae, optic atrophy, corneal bloodstaining, secondary hemorrhage, and accommodative impairment. The reported incidence of secondary anterior chamber hemorrhage, that is, rebleeding, in the setting of traumatic hyphema ranges from 0% to 38%. The risk of secondary hemorrhage may be higher in African-Americans than in whites. Secondary hemorrhage is generally thought to convey a worse visual prognosis, although the outcome may depend more directly on the size of the hyphema and the severity of associated ocular injuries. Some issues involved in managing a patient with hyphema are: rise of various medications (e.g., cycloplegics, systemic or topical steroids, antifibrinolytic agents, analgesics, and antiglaucoma medications); the patient's activity level; use of a patch and shield; outpatient vs. inpatient management; and medical Vs. surgical management. Special considerations obtain in managing children, patients with hemoglobin S, and patients with hemophilia. It is important to identify and treat associated ocular injuries, which often accompany traumatic hyphema. We consider each of these management issues and refer to the pertinent literature in formulating the following recommendations. We advise routine use of topical cycloplegics and corticosteroids, systemic antifibrinolytic agents or corticosteroids, and a rigid shield. We recommend activity restriction (quiet ambulation) and interdiction of non-steroidal anti-inflammatory agents. If there is no concern regarding compliance (with medication use or activity restrictions), follow-up, or increased risk for complications (e.g., history of sickle cell disease, hemophilia), outpatient management can be offered. Indications for surgical intervention include the presence of corneal blood staining or dangerously increased intraocular pressure despite maximum tolerated medical therapy, among others. (C) 2002 by Elsevier Science Inc. All rights reserved.

Ophthalmology patients' interest in online access to clinic notes at three US clinics - Lee, BS; Oster, NV; Chen, GY; Ding, LL; Walker, JD; Elmore, JG (OPHTHALMIC AND PHYSIOLOGICAL OPTICS, 2017)
PurposeThis study aimed to understand patients' perceptions about potential benefits and harms of accessing their own ophthalmology clinic notes via an electronic patient portal as part of the OpenNotes initiative. MethodsThe authors conducted a cross-sectional, in-person survey of ophthalmology patients at three US eye clinics. The paper survey was self-administered or administered with assistance from study staff before or after patients' clinical visits. The authors used descriptive statistics to summarise patient characteristics and patient attitudes about accessing their ophthalmology notes online. Chi-square and t-tests were performed to assess differences in patient responses between clinic locations. ResultsFour hundred and fifty-one patients responded (response rate 65%). Most patients thought that accessing doctors' notes online was a good idea (95%), wanted to view their clinic notes online (94%), and agreed online access would increase their understanding of their eye problems (95%) and help them better remember their care plan (94%); 14% said online access would increase their worry; 43% had privacy concerns; and 96% indicated they would show or discuss their notes with at least one other person. Non-white patients were more likely than white patients to perceive online clinic notes as a useful tool, but they were also more likely to worry and to express greater privacy concerns. ConclusionsPatients at three US eye clinics were strongly in favour of online access to ophthalmology notes and were optimistic this access would improve their understanding and self-care. Ophthalmologists should consider offering online access to their notes to enhance doctor-patient communication and improve clinical outcomes.

Long-term Contact Lens Wear of Children and Teens - Walline, JJ; Lorenz, KO; Nichols, JJ (EYE & CONTACT LENS-SCIENCE AND CLINICAL PRACTICE, 2013)
Objective: To compare current symptoms, compliance, ocular health, and previous adverse events between current successful long-term contact lens wearers fit as children or as teenagers. Methods: People who had successfully worn soft contact lenses for at least 10 years completed an online survey about demographics, current wearing status, compliance, symptoms, and previous adverse events. A subset reported for a slit-lamp examination, autorefraction, autokeratometry, and specular microscopy. Statistical comparisons were made between those fit as children (12 years or younger) and those fit as teenagers (13 years or older). Results: Of the 175 subjects completing the online survey, 86 (49.2%) were fit as children and 89 (50.8%) fit as teenagers. Those fit as children wore their contact lenses for an average of 14.8 +/- 3.4 hours per day, compared with 14.7 +/- 3.6 hours per day for those fit as teenagers (P=0.74). Eighteen (20.9%) fit as children and 17 (19.1%) fit as teenagers reported ever having had a painful, red eye that required a doctor visit (P=0.76). Overall, there were no differences in ocular health between the groups. Those fit as children were more myopic than those fit as teenagers (-4.30 +/- 1.69 and -2.87 +/- 2.75, respectively; P=0.02). Conclusions: Successful contact lens wearers fit as children are no more likely to report previous contact lens-related adverse events, problems with compliance, decreased wearing time, or worse ocular health than those fit as teenagers, so practitioners should not use age as a primary determinant in fitting children in contact lenses.

Impact of rigid gas-permeable contact lens extended wear on corneal epithelial barrier function - Lin, MC; Graham, AD; Fusaro, RE; Polse, KA (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2002)
PURPOSE. To measure the effect of hypoxia and eye closure on, p epithelial permeability to fluorescein (P-dc) during rigid lens extended wear (EW). METHODS. Central corneal thickness (CT) and P-dc were measured in 42 subjects with an optical pachometer and automated scanning fluorophotometer, respectively. All subjects had been successfully wearing rigid gas-permeable (RGP) lenses on a 6-night EW regimen, and each individual was randomized to wear either medium- or high-oxygen-permeable (Dk) RGP lenses (two types of siloxane-fluorocarbon polymer lenses with Dk of 49 and 92). CT and P-dc measurements were performed at an afternoon visit (baseline) and were repeated in the morning after 8 hours of overnight wear, Subjects slept with a patch over the right eye. The patch was not removed until immediately before the morning measurement. RESULTS. The mean overnight swelling response for subjects in the medium-Dk group was greater than that in the high-Dk group. Results of a paired t-test indicate that the eye wearing the medium-Dk lens with a patch overnight had a significant increase in epithelial permeability. Results of mixed-effect models suggest that eye closure and lens-induced hypoxia are significant factors in altering P-dc. CONCLUSIONS. The results indicate that corneal epithelial permeability increases with hypoxic dose and that epithelial barrier function is impaired by overnight rigid lens wear.

Once-Daily Netarsudil/Latanoprost Fixed-Dose Combination for Elevated Intraocular Pressure in the Randomized Phase 3 MERCURY-2 Study - Walters, TR; Ahmed, IIK; Lewis, RA; Usner, DW; Lopez, J; Kopczynski, CC; Heah, T; MERCURY-2 Study Grp (OPHTHALMOLOGY GLAUCOMA, 2019)
Purpose: To compare the ocular hypotensive efficacy and safety of a once-daily (PM) fixed-dose combination (FDC) product containing netarsudil 0.02% and latanoprost 0.005% with monotherapy with netarsudil or latanoprost. Netarsudil is a Rho kinase inhibitor that lowers intraocular pressure (IOP) primarily by increasing trabecular (conventional) outflow. Latanoprost is the most frequently prescribed of the prostaglandin analogs, which lower IOP primarily by increasing uveoscleral outflow. Design: Three-month, double-masked, randomized (1:1:1), phase 3, superiority study. Participants: Patients had unmedicated IOP > 20 to <36 mmHg at 8:00 AM and met other standard criteria for open-angle glaucoma and ocular hypertension. Methods: Randomization to once-daily (PM) netarsudil/latanoprost FDC, netarsudil, or latanoprost for 3 months. Main Outcome Measures: Mean IOP at 8:00 AM, 10:00 AM, and 4:00 PM at week 2, week 6, and month 3 (intent-to-treat). Statistical superiority was concluded if the P value for the comparison of netarsudil/latanoprost FDC with each component was <0.05 and the difference in mean IOP (netarsudil/latanoprost FDC minus comparator) was <0 for all time points at all visits. Safety was recorded throughout the treatment period. Results: A total of 750 patients were enrolled, with 90.2%, 89.4%, and 94.4% completing 3 months of treatment with netarsudil/latanoprost FDC, netarsudil, and latanoprost, respectively. Least-squares mean treated IOP ranged from 15.3 to 16.5 mmHg for netarsudil/latanoprost FDC, 17.4 to 19.8 mmHg for netarsudil, and 17.1 to 18.1 mmHg for latanoprost. Netarsudil/latanoprost FDC met the criteria for superiority to each active component at all 9 time points (all P < 0.0001), lowering IOP by an additional 2.2 to 3.3 mmHg versus netarsudil and an additional 1.5 to 2.4 mmHg versus latanoprost. At month 3, the proportion of patients achieving mean diurnal IOP <= 15 mmHg was 42.1% for netarsudil/latanoprost FDC, 15.8% for netarsudil, and 18.3% for latanoprost. No treatment-related serious adverse event (AE) was observed. Treatment-related systemic AEs were minimal. The most frequent ocular AE was conjunctival hyperemia (netarsudil/latanoprost FDC, 54.5%; netarsudil, 42.7%; latanoprost, 22.3%), which was generally mild. Conclusions: Once-daily netarsudil/latanoprost FDC demonstrated IOP reductions that were statistically and clinically superior to its individual components at all 9 time points over 3 months, with tolerable ocular safety. This FDC offers a reduced treatment burden that may improve adherence and clinical outcomes. (C) 2019 by the American Academy of Ophthalmology.

CORNEAL ABRASION ASSOCIATED WITH CONTACT-LENS CORRECTION OF KERATOCONUS - A RETROSPECTIVE STUDY - WEISSMAN, B; CHUN, MW; BARNHART, LA (OPTOMETRY AND VISION SCIENCE, 1994)
Background. Corneal abrasion is a frequently encountered complication of contact lens wear, but we are not aware of any previous study of relative frequency comparing keratoconic to nonkeratoconic patients. Methods. We retrospectively studied the incidence of corneal abrasion during 2 months of contact lens practice. Results. 784 contact lens-related patient visits (494 total patients); patients were assessed by 3 optometrists and 13 abrasions (11 patients) were diagnosed. Only the total number of individual patients and the first abrasion for each patient were statistically considered; the overall frequency of abrasion was therefore 11/494 (2.3%)/2 months. The frequency of abrasion was 5/68 (7.4%)/2 months for keratoconic patients and 6/426 (1.4%)/2 months for nonkeratoconic patients and this difference was significant (chi2 test: p < 0.01). Among nonkeratoconic patients, the frequency of abrasion was 2/246 (0.8%)/2 months with hydrogel contact lens wear and 4/178 (2.2%)/2 months with rigid gas permeable (RGP) contact lens wear, but this difference did not achieve significance (chi2 test: p = 0.10). Identified risk factors included: Contact lens wear; a torn lens and chemical keratitis for hydrogel lens wearers; an adherent ''bound'' lens and keratoconus for rigid lens wearers. Conclusion. Keratoconus appears to be a statistically significant risk factor for corneal abrasion among contact lens wearers.

Mapping and modeling of physician collaboration network - Uddin, S; Hamra, J; Hossain, L (STATISTICS IN MEDICINE, 2013)
Effective provisioning of healthcare services during patient hospitalization requires collaboration involving a set of interdependent complex tasks, which needs to be carried out in a synergistic manner. Improved patients' outcome during and after hospitalization has been attributed to how effective different health services provisioning groups carry out their tasks in a coordinated manner. Previous studies have documented the underlying relationships between collaboration among physicians on the effective outcome in delivering health services for improved patient outcomes. However, there are very few systematic empirical studies with a focus on the effect of collaboration networks among healthcare professionals and patients' medical condition. On the basis of the fact that collaboration evolves among physicians when they visit a common hospitalized patient, in this study, we first propose an approach to map collaboration network among physicians from their visiting information to patients. We termed this network as physician collaboration network (PCN). Then, we use exponential random graph (ERG) models to explore the microlevel network structures of PCNs and their impact on hospitalization cost and hospital readmission rate. ERG models are probabilistic models that are presented by locally determined explanatory variables and can effectively identify structural properties of networks such as PCN. It simplifies a complex structure down to a combination of basic parameters such as 2-star, 3-star, and triangle. By applying our proposed mapping approach and ERG modeling technique to the electronic health insurance claims dataset of a very large Australian health insurance organization, we construct and model PCNs. We notice that the 2-star (subset of 3 nodes in which 1 node is connected to each of the other 2 nodes) parameter of ERG has significant impact on hospitalization cost. Further, we identify that triangle (subset of 3 nodes in which each node is connected to the rest 2 nodes), alternative k-star (subset of k nodes in which 1 node is connected to each of other k-1 nodes), and alternative k-2 path (subset of k nodes in which, between a specific pair of nodes, there exists k-2 paths of length 2) parameters of ERG have impact on the hospital readmission rate. Our findings can have implications for healthcare administrators or managers who could potentially improve the practice cultures in their organizations by following these outcomes. Copyright (c) 2013 John Wiley & Sons, Ltd.

Myopia control with novel central and peripheral plus contact lenses and extended depth of focus contact lenses: 2 year results from a randomised clinical trial - Sankaridurg, P; Bakaraju, RC; Naduvilath, T; Chen, X; Weng, R; Tilia, D; Xu, P; Li, WN; Conrad, F; Smith, EL; Ehrmann, K (OPHTHALMIC AND PHYSIOLOGICAL OPTICS, 2019)
Purpose We aimed to determine myopia control efficacy with novel contact lenses (CL) that (1) reduced both central and peripheral defocus, and (2) provided extended depth of focus with better global retinal image quality for points on, and anterior to, the retina and degraded for points posterior to the retina. Methods Children (n = 508, 8-13 years) with cycloplegic spherical equivalent (SE) -0.75 to -3.50D were enrolled in a prospective, double blind trial and randomised to one of five groups: (1) single vision, silicone hydrogel (SH) CL; (2) two groups wearing SH CL that imposed myopic defocus across peripheral and central retina (test CL I and II; +1.00D centrally and +2.50 and +1.50 for CL I and II at 3 mm semi-chord respectively); and (3) two groups wearing extended depth of focus (EDOF) hydrogel CL incorporating higher order aberrations to modulate retinal image quality (test CL III and IV; extended depth of focus of up to +1.75D and +2.50D respectively). Cycloplegic autorefraction and axial length (AL) measurements were conducted at six monthly intervals. Compliance to lens wear was assessed with a diary and collected at each visit. Additionally, subjective responses to various aspects of lens wear were assessed. The trial commenced in February 2014 and was terminated in January 2017 due to site closure. Myopia progression over time between groups was compared using linear mixed models and where needed post hoc analysis with Bonferroni corrections conducted. Results Myopia progressed with control CL -1.12 +/- 0.51D/0.58 +/- 0.27 mm for SE/AL at 24 months. In comparison, all test CL had reduced progression with SE/AL ranging from -0.78D to -0.87D/0.41-0.46 mm at 24 months (AL: p CL; SE p CL III and IV) and represented a reduction in axial length elongation of about 22% to 32% and reduction in spherical equivalent of 24% to 32%. With test CL, a greater slowing ranging from 26% to 43% was observed in compliant wearers (>= 6 days per week; Control CL: -0.64D/0.30 mm and -1.14D/0.58 mm vs test CL: -0.42D to -0.47D/0.12-0.18 mm and -0.70 to -0.81D/0.19-0.25 mm at 12 and 24 months respectively). Conclusions Contact lenses that either imposed myopic defocus at the retina or modulated retinal image quality resulted in a slower progression of myopia with greater efficacy seen in compliant wearers. Importantly, there was no difference in the myopia control provided by either of these strategies.

Once-daily nepafenac ophthalmic suspension 0.3% to prevent and treat ocular inflammation and pain after cataract surgery: Phase 3 study - Modi, SS; Lehmann, RP; Walters, TR; Fong, R; Christie, WC; Roel, L; Nethery, D; Sager, D; Tsorbatzoglou, A; Philipson, B; Traverso, CE; Reiser, H (JOURNAL OF CATARACT AND REFRACTIVE SURGERY, 2014)
PURPOSE: To evaluate once-daily nepafenac 0.3% to prevent and treat ocular pain and inflammation after cataract surgery. SETTING: Sixty-five centers in the United States and Europe. DESIGN: Randomized double-masked vehicle- and active-controlled phase 3 study. METHODS: Patients received nepafenac 0.3% once daily, nepafenac 0.1% 3 times daily, or their respective vehicles from day 1 to day 14 after cataract extraction. An additional drop of study drug was administered 30 to 120 minutes preoperatively. The primary endpoint was the percentage of patients with a cure for inflammation (score of 0 for both aqueous cells and flare) at day 14. RESULTS: Of randomized patients, 817 received nepafenac 0.3%, 819 received nepafenac 0.1%, and 200 and 206 received the respective vehicles. Significantly more nepafenac 0.3% patients had no inflammation (68.4% versus 34.0%) and were pain free (91.0% versus 49.7%) at day 14 than vehicle patients (both P<.0001). Nepafenac 0.3% was noninferior to nepafenac 0.1% for inflammation (95% confidence interval [Cl], -5.73% to 3.17%) and pain-free rates (95% Cl, -3.08% to 2.70%). At all postoperative visits, fewer treatment failures (P <=.0012) and more clinical successes (P <=.0264) were observed with nepafenac 0.3% versus vehicle. Nepafenac 0.3% was well tolerated and had a safety profile comparable to that of nepafenac 0.1%. CONCLUSIONS: Once-daily nepafenac 0.3% was noninferior to nepafenac 0.1% 3 times daily for prevention and treatment of ocular inflammation and pain following cataract surgery. The safety of nepafenac 0.3% was comparable to that of nepafenac 0.1%, with the added convenience of once-daily dosing. (C) 2013 ASCRS and ESCRS

STAGED REMOVAL OF ACOUSTIC TUMORS - TECHNIQUES AND LESSONS LEARNED FROM A SERIES OF 83 PATIENTS - COMEY, CH; JANNETTA, PJ; SHEPTAK, PE; JHO, HD; BURKHART, LE (NEUROSURGERY, 1995)
THE REMOVAL OF large acoustic tumors is associated with increased mortality and cranial nerve injury. One method for treating these difficult lesions is staged resection. Between 1972 and 1992, more than 600 acoustic tumors were resected at our institution. Of these, 83 were removed in stages. This represents the largest series of staged acoustic tumor resections reported to date. A review of available films and patient records was performed for all acoustic tumors resected in stages between 1972 and early 1993 to analyze demographic information, tumor size, operative technique, outcome, and complications. The information was collected on standardized data sheets and entered into a computer database. Virtually all tumors were large, with the average size being 4 cm in greatest diameter. The average patient age was 41 years, and there was a slight preponderance of female patients. Ten patients had neurofibromatosis Type 2. The suboccipital approach was used in most patients. Anatomic preservation of the VIIth cranial nerve was achieved in >72% of patients, with an average House-Brackmann score of Grade 3 at the longest follow-up (mean, 43 mo). Facial reanimation was performed in 19 of 23 patients with transected VIIth cranial nerves. Complications included cerebrospinal fluid fistulas in 11 patients, with 8 of 11 fistulas resolving after lumbar drainage. Six patients had meningitis (bacterial in three and aseptic in three). Two patients developed wound infections, and 10 patients developed exposure keratitis. There were two documented recurrences. There were no operative deaths. In most series, the incidence of cranial nerve deficits as well as morbidity and mortality is directly related to tumor size. Our operative strategy involved debulking the lateral aspect of large tumors during Stage I. Second stage removal is performed after the remaining turner is shown to decompress out of the pens on computed tomographic or magnetic resonance images. During the second procedure, the residual tumor is less vascular and no longer densely adherent to the brain stem. Although staged removal is not without risk, there seems to be no apparent increase in morbidity when these results are compared with the results of series from the literature. Although there remain no absolute indications for staged resection of acoustic tumors, we think that it may represent the safest option for these difficult lesions.

High Molecular Weight Hyaluronan Promotes Corneal Nerve Growth in Severe Dry Eyes - Van Setten, GB; Stachs, O; Dupas, B; Turhan, SA; Seitz, B; Reitsamer, H; Winter, K; Horwath-Winter, J; Guthoff, RF; Muller-Lierheim, WGK (JOURNAL OF CLINICAL MEDICINE, 2020)
The purpose of this study was to investigate the effect of high molecular weight hyaluronan (HMWHA) eye drops on subbasal corneal nerves in patients suffering from severe dry eye disease (DED) and to evaluate the damage of subbasal corneal nerves associated with severe DED. Designed as an international, multicenter study, 16 patients with symptoms of at least an Ocular Surface Disease Index (OSDI) score of 33, and corneal fluorescein staining (CFS) of at least Oxford grade 3, were included and randomized into two study arms. The control group continued to use their individual optimum artificial tears over the study period of eight weeks; in the verum group, the artificial tears were substituted by eye drops containing 0.15% HMWHA. At the baseline visit, and after eight weeks, the subbasal nerve plexus of 16 patients were assessed by confocal laser scanning microscopy (CSLM). The images were submitted to a masked reading center for evaluation. Results showed a significant increase of total nerve fiber lengths (CNFL) in the HMWHA group (p = 0.030) when compared to the control group, where the total subbasal CNFL did not significantly change from baseline to week 8. We concluded that in severe DED patients, HMWHA from topically applied eye drops could cross the epithelial barrier and reach the subbasal nerve plexus, where it exercised a trophic effect.

Survival analysis and visual outcome in a large series of corneal transplants in India - Dandona, L; Naduvilath, TJ; Janarthanan, M; Ragu, K; Rao, GN (BRITISH JOURNAL OF OPHTHALMOLOGY, 1997)
Aim/background-The public health significance of corneal transplantation in dealing with corneal blindness in the developing world would depend upon the survival rate of transplants. This study was done to analyse the survival rate of corneal transplants in a large series in India, and to evaluate the influence of various risk factors on transplant survival. Methods-The records of a series of 1725 cases of corneal transplants carried out during 1987-95 at a tertiary eye care institution in India were reviewed. The Kaplan-Meier method was used to determine 5 year survival rates of corneal transplants performed for the various categories of preoperative diagnosis. Multivariate Cox proportional hazards regression was used to assess how preoperative diagnosis, socioeconomic status, age, sex, vascularisation of host cornea, quality of donor cornea, and training status of surgeon influenced transplant survival. The effect of these variables on visual outcome was assessed using multiple logistic regression. Results-The survival rates at 1, 2, and 5 years for all corneal transplants performed for the first time in 1389 cases were 79.6% (95% confidence interval = 77.3-81.9%), 68.7% (65.7-71.7%) and 46.5% (41.7-51.3%). The 5 year survival rate was highest if the corneal transplant was done for keratoconus (95.1% (84.8-100%)) and lowest if carried out for previous transplant failure (21.2% (13.8-28.6%)). The relative risk of transplant failure was higher if the preoperative diagnosis was previous transplant failure (2.04 (1.62-2.55)), aphakic bullous keratopathy (1.78 (1.38-2.28)), corneal clouding due to miscellaneous causes including congenital conditions and glaucoma (1.63 (1.21-2.19)), or adherent leucoma (1.11 (0.81-1.51)) than for the other preoperative diagnoses. Patients with lower socioeconomic status had higher relative risk of transplant failure (1.28 (1.16-1.42)), as did patients <10 years of age (1.42 (1.23-1.64)). Higher relative risk of transplant failure was associated with vascularisation of the host cornea before transplantation (1.15 (1.04-1.27)), and with the use of fair quality donor cornea for transplantation compared with excellent, very good, or good quality donor cornea (1.26 (1.06-1.52)). Before corneal transplant 80.2% of the eyes were blind (visual acuity <3/60), whereas at last follow up 41.8% eyes were blind. The odds of having visual acuity >6/18 were higher if the transplant was done for keratoconus (9.99 (6.10-16.36)) or corneal dystrophies (1.77 (1.21-2.58)) than for the other preoperative diagnoses. Conclusion-Reasonable success with corneal transplantation is possible in the developing world if data from this part of the world regarding the different survival rates for the various preoperative diagnoses and the influence of risk factors on transplant survival and visual outcome are taken into account while determining priority for transplant cases in the present situation of limited availability of donor corneas.

Single- and Multiple-Dose Pharmacokinetic, Safety, and Tolerability Profiles of Olanzapine Long-Acting Injection: An Open-Label, Multicenter, Nonrandomized Study in Patients With Schizophrenia - Mitchell, M; Kothare, P; Bergstrom, R; Zhao, FY; Jen, KY; Walker, D; Johnson, J; McDonnell, D (CLINICAL THERAPEUTICS, 2013)
Background: This was the first study, to our knowledge, in patients with schizophrenia in which olanzapine long-acting injection (LAI) was used to attempt delivery of depot formulation in multiple therapeutic doses. Objective: This study assessed the safety profile, tolerability, and pharmacokinetic (PK) properties of olanzapine after single and multiple administrations of olanzapine LAI and evaluated maintenance of symptom control. Methods: This was an open-label, multicenter, non-randomized study of olanzapine LAI in patients with schizophrenia stabilized with oral olanzapine. Key inclusion criteria included well-tolerated and efficacious treatment with daily olanzapine. Patients were required to be receiving a stable oral dose for 4 weeks before study entry with no requirement for as-needed additional antipsychotic medication within 2 weeks before entry. Exclusion criteria included serious unstable illnesses, unresolved seizures, pregnancy or breast-feeding, hypothyroidism, hyperthyroidism, narrow-angle glaucoma, or serious suicidal risk. Initially, 34 patients received olanzapine LAI as a single injection of 50 to 450 mg, and as the study progressed, 247 patients received consecutive injections of 100 to 405 mg olanzapine LAI administered every 2, 3, or 4 weeks for 3 to 6 months. Spontaneously reported adverse events were recorded at each visit. Analyses of efficacy and safety profile parameters were performed on an intent-to-treat basis. All hypotheses were tested at a 2-sided significance leyel of P < 0.05. Results: Study participants had a mean age of 39 years and were primarily white men. The PK properties suggested prolonged release providing sustained olanzapine plasma concentrations and supporting a dosing interval <= 4 weeks. Olanzapine LAI doses of 150 or 300 mg every 2 weeks and 210 or 405 mg every 4 weeks provide mean steady-state olanzapine concentrations similar to those after oral administration of 5 to 20 mg/d. The mean baseline Brief Psychiatric Rating Scale score of 17.27 decreased by 2.68 points, and the mean baseline Clinical Global Impression Severity score of 3.39 decreased by 0.23 points, indicating that patients' psychiatric health was maintained or slightly improved. Significant mean weight gain (P < 0.001) and treatment-emergent changes in nonfasting glucose were observed. Incidence of weight gain >= 7% of baseline was observed in 17.8% of patients. The common adverse events were injection site pain, anxiety, sedation, insomnia, somnolence, and headache, and the safety profile for olanzapine LAI was comparable to that of oral olanzapine, except for injection site related adverse events. Conclusion: The safety profile and PK data from this study support continued clinical development of olanzapine LAI in controlled efficacy studies at doses <= 300 mg every 2 weeks or 405 mg every 4 weeks. (C) 2013 Elsevier HS Journals, Inc. All rights reserved.